1-Maintenance : Marqueurs - _Projet EDI Formation (2021)
Keywords: 1-Cinéma; 1-Histoire de l'art; 1-Jeux vidéo; 1-TV; 2-Analyses formalistes; 2-Approches sociologiques; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Humanités numériques; 2-Muséologie critique; 2-Méthodologie de recherche décoloniale; 2-Pédagogie décoloniale; 2-Recherche-création; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 2-Étude de la réception; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Afrique (corpus analysé); 3-Amérique centrale (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 3-Océanie (corpus analysé); 4-Afrique (lieu de production du savoir); 4-Amérique centrale (lieu de production du savoir); 4-Amérique du Nord (lieu de production du savoir); 4-Amérique du Sud (lieu de production du savoir); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 4-Océanie (lieu de production du savoir); 5-Auteur.rice LGBTQ+; 5-Auteur.rice PANDC; 5-Auteur.rice autochtone; 5-Auteur.rice noir.e; 5-Autrice; 5-Créateur.rice LGBTQ+; 5-Créateur.rice PANDC; 5-Créateur.rice autochtone; 5-Créateur.rice noir.e; 5-Créatrice; 5-Identités diasporiques; _Nettoyé; _À analyser; _À nettoyer; _À vérifier-Cinéma; _À vérifier-Histoire de l'art; _À vérifier-Jeu vidéo; _À vérifier-Télé

Locating Television : Zones of Consumption - Pertierra, Anna; Turner, Graeme (Routledge, Taylor & Francis Group, 2013)

Reflexivity, methodology and contexts in participatory digital media research: making games with Latin American youth in London - Paula, Bruno de (Learning, Media and Technology, 2021)
In this paper, I intend to explore the role played by reflexivity in grounding a more critical perspective when designing, implementing and analysing participatory digital media research. To carry out this methodological reflection, I will present and discuss a recently concluded research project on young people’s game-making in an after-school programme targeting Latin American migrants in London/UK. I will pay special attention to how my subjectivities influenced planning, data generation and analysis of this programme, and to how context, lived experiences, curricular decisions and interpersonal relationships shaped the kinds of knowledge produced through this research. Findings emerging from this experience included relevant dissonances between curricular design/decisions and the use of participatory approaches in game-making, and the limitations of traditional analytical categories within the Social Sciences field (e.g., gender and intersectionality) to understanding subjectivities expressed through game-making. This study offers relevant insights into the place of reflexivity in research on digital media production by young people by highlighting its complexity and by calling for more critical and less homogenising approaches to this type of research.
_eprint: https://doi.org/10.1080/17439884.2021.1901114
Keywords: 1-Jeux vidéo; 2-Genre et sexualité; 2-Recherche-création; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Europe (corpus analysé); 4-Europe (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Créateur.rice PANDC; 5-Créatrice; 5-Identités diasporiques; _Nettoyé

Korean Soap Operas, Telenovelas and Sci-fi Conspiracies: A Game-making Experience with Latin American Youth in London - Paula, Bruno de (Digital Culture and Education, 2021)
This paper explores a game-making programme for 14 Latin American migrants aged 13-18 in London/UK, carried out between October/2017-January/2018, where I investigated the relationships between game conventions, platforms and personal preferences in the curation of fluid identities through game production. Participants presented varying levels of affinity with games linked both to access issues and to other specific elements (e.g. perception of games in contemporary culture, gender). Questionnaires, observations, unstructured/semistructured interviews and gaming archives were employed to explore this participatory initiative and data was analysed through Multimodal Sociosemiotics. Findings remarked how shared understandings about digital games can find their way into platforms and act as “cultural-technical gatekeepers”, supporting or hindering the engagement with game-making of those often perceived as outsiders to gaming culture. This gatekeeping happens when there are “creative dissonances” between, for example, personal preferences and platforms aligned to normative/mainstream genres. These dissonances, however, can end up fostering subversive designs, contravening gaming conventions and potentially challenging traditional gaming boundaries. This insight is relevant for understanding “cultural-technical constraints” and subversive/non-mainstream game-making, especially in relation to innovation and appropriation of game-making resources/strategies by non-mainstream groups.
Number: 2
Keywords: 1-Jeux vidéo; 1-TV; 2-Recherche-création; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des industries culturelles; 3-Europe (corpus analysé); 4-Europe (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Créateur.rice PANDC; 5-Identités diasporiques; _Nettoyé

Exploring game grammars: a sociosemiotic account of young people’s game-making practices - Paula, Bruno de (Visual Communication, 2021)
This article investigates the relationship between young people’s game-making practices and meaning-making in videogames. By exploring two different games produced in a game-making club in London through a multimodal sociosemiotic approach, the author discusses how semiotic resources and modes were recruited by participants to realize different discourses. By employing concepts such as modality truth claims and grammar, he examines how these games help us reflect on the links between intertextuality, hegemonic gaming forms and sign-making through digital games. He also outlines how a broader approach to what has been recently defined as the ‘procedural’ mode by Hawreliak in Multimodal Semiotics and Rhetoric in Videogames (2018) can be relevant for promoting different and more democratic forms of meaning-making through videogames.
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Humanités numériques; 2-Recherche-création; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude de la réception; 3-Europe (corpus analysé); 4-Europe (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé

“Emergent Countries Play, Too!”: The Zeebo Console as a (Partial) Decolonial Project - Paula, Bruno de (Revista Contracampo, 2021)
The present paper discusses questions related to the histories of videogames, more specifically in how we approach videogames in Global South. By using Zeebo, a Brazilian console produced in the late 2000s as an epistemic tool, I discuss the limitations of universalist, mainstream-centric epistemological models for exploring videogames as cultural phenomena. By investigating Zeebo’s discourses about piracy and players in the Global South, I argue that this platform can be seen as a partial decolonial project, destabilising conventional historical narratives about South-North relationships in videogames, but refraining from challenging a mainstream, Global North oriented epistemology. This exploratory work, therefore, elaborates on how a decolonial project of history of videogames, one that is more epistemically just to Global South, could be sought.
Number: 2
Keywords: 1-Jeux vidéo; 2-Humanités numériques; 2-Méthodologie de recherche décoloniale; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des industries culturelles; 4-Europe (lieu de production du savoir); 5-Créatrice; _Nettoyé

Decolonizing Game Literacy - Robinson, Petra A.; Williams, Kamala V.; Stojanović, Maja; Paula, Bruno de (Global Citizenship for Adult Education: Advancing Critical Literacies for Equity and Social Justice, 2022)
In the last decades, digital games have moved from niche to mainstream. As more people play, talk about, and engage with these artifacts, they have become an important part of contemporary cultures, giving rise to game literacy—the set of skills needed to meaningfully engage with video games. While the potentials of game literacy have, to some extent, been already discussed in the literature, we have not adequately discussed the need for a game literacy that problematizes the sociocultural dimensions of gaming, including the hegemonic, exclusionary rationales implicitly disseminated through mainstream gaming. In this chapter, I outline a decolonial model for game literacy, remarking how the reflection about the gaming circuits of production and dissemination should be part of any initiative that aims at dealing with critical and creative competences towards gaming, and how these are crucial for any citizen in contemporary societies.
OCLC: 1288078892
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Méthodologie de recherche décoloniale; 2-Théories et épistémologie postcoloniales et décoloniales; 4-Europe (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé

L’amour et les théories de la communication - Morin, Céline (Questions de communication, 2014)
Thématique a priori universelle, l’amour prête aisément à des réflexions anhistoriques que la philosophie antique aurait déjà définitivement formulées. Pourtant, la variabilité historique de ses expressions et la querelle sans cesse renouvelée sur ses significations démontrent qu’elle est, elle aussi, traversée de divers conflits épistémologiques. Loin d’un idéal transcendant, les récents travaux envisagent l’amour comme une visée communicationnelle en même temps que décroît l’idéologie du sacrifice personnel et que se forge une démocratie relationnelle où chacun doit en théorie pouvoir se faire entendre. Les outils y sont ceux de l’expression personnelle et de la responsabilisation, de la délibération et du compromis pour que soit construite une sphère publique intime où communiquent couple et individualités.
Place: Nancy
Keywords: amour; communication; démocratie; genre; intimité; réflexivité

Du romantisme à la relation pure ? Les amours des héroïnes de séries américaines depuis 1950 - Morin, Céline (Le Temps des médias, 2012)
RésuméLes séries télévisées américaines ont dès les années 1950 problématisé les articulations entre modèles amoureux et vagues d’émancipation des femmes. Cet article, centré sur les amours des héroïnes, propose un découpage en trois temps de l’histoire de ces séries, qui tend à montrer que si le romantisme continue de sous-tendre les pratiques, il se trouve confronté à la dissymétrie qu’il provoque entre hommes et femmes et perd du terrain face à la « relation pure », nouvel idéal relationnel. Les femmes au foyer des années 1950 sont soumises à l’insatisfaction de leur condition et laissent transparaître les premiers échecs de l’amour romantique, alors que, deux décennies plus tard, au milieu des années 1990, les working girls célibataires, égéries de l’après-féminisme, constituent l’amour en une menace à leur indépendance et à leur épanouissement. Enfin la récente vague de quadragénaires, veuves ou divorcées, tente de dépasser la contradiction entre indépendance et amour, en pratiquant réellement la « relation pure ».
Place: Paris

Romantic Comedies: When Stalking Has a Happy Ending - Beck, Julie (The Atlantic, 2016)
Overly persistent pursuit is a staple of movie love stories, but a new study shows that it could normalize some troubling behaviors.
Section: Health

Transnational Korean Television: Cultural Storytelling and Digital Audiences - Ju, Hyejung (Lexington Books, 2020)
Transnational Korean Television: Cultural Storytelling and Digital Audience provides previously absent analyses of Korean TV dramas' transnational influences, peculiar production features, distribution, and consumption to enrich the contextual understanding of Korean TV's transcultural mobility. Even as academic discussions about the Korean Wave have heated up, Korean television studies from transnational viewpoints often lack in-depth analysis and overlook the recently extended flow of Korean television beyond Asia. This book illustrates the ecology of Korean television along with the Korean Wave for the past two decades in order to showcase Korean TV dramas' international mobility and its constant expansion with the different Western television and their audiences. Korean TV dramas' mobility in crossing borders has been seen in both transnational and transcultural flows, and the book opens up the potential to observe the constant flow of Korean television content in new places, peoples, manners, and platforms around the world. Scholars of media studies, communication, cultural studies, and Asian studies will find this book especially useful.
Keywords: 1-TV; 2-Approches sociologiques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude de la réception; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; 5-Identités diasporiques; Corée du Sud (corpus analysé); _Nettoyé; États-Unis (lieu de production du savoir)

Civil Society as the Fifth Estate: Civil Society, Media Reform and Democracy in Korea - Kwak, Ki-Sung (Television, Regulation and Civil Society in Asia, 2002)
Since the Korean War (1950-53), South Korea (hereafter Korea) has undergone a series of political changes. The move towards democratisation was largely spurred on by the demonstrations and riots occurring throughout the 1980s. In 1987 massive demonstrations forced the then President Chun DooHwan to call a new presidential election, and President-elect Rho Tae-Woo to implement more social reforms. The notion of civil society in Korea has been a relatively new concept until very recently, mainly because it has not achieved wide recognition from the public, media or the state. The development of a people’s movement advocating democracy could be said to be the foundation of ‘civil society’ in Korea.
Num Pages: 17
Keywords: 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Océanie (lieu de production du savoir); 5-Auteur.rice PANDC; Australie (lieu de production du savoir); Corée du Sud (corpus analysé); _Nettoyé

Sliding Back the Screens: Civil Society and the Erosion of Bureaucratic Control of Television in Japan - Hirano, Chalinee (Television, Regulation and Civil Society in Asia, 2002)
Japan in the 1990s differs vastly from what it had been two or three decades earlier. The Japanese state has undergone such a fundamental change that it has been described as a ‘regime shift’ (Pempel 1998). Although the longterm ruling conservative Liberal Democratic Party (LDP) has returned to power after its defeat in 1993, it no longer has an absolute majority in the Cabinet. Surrounded by numerous scandals and corruption charges, both the government and bureaucracy have undergone major reforms to increase transparency and reduce bureaucratic influence over the policy-making process. The Japanese Diet has, for example, passed the Information Disclosure Law to increase openness in the administration. Economic policies have also been transformed to cope with the malaise characterised by continuing problems of bad loans in the financial sector, rising unemployment and declining manufacturing productivity.
Num Pages: 9
Keywords: 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Océanie (lieu de production du savoir); 5-Autrice; Australie (lieu de production du savoir); Japon (corpus analysé); _Nettoyé

Television in the Formation of Civil Society: The Role of a Non- Controversial Public Space in Hong Kong - Lee, Paul S. N. (Television, Regulation and Civil Society in Asia, 2002)
Television first appeared in Hong Kong in 1957. It was a cable television service run by the Rediffusion Company which had operated a highly successful wired sound broadcasting service since 1949. Hong Kong was the first British colony to have television. But the Rediffusion television service was very expensive. Its monthly subscription fee was HK$55. In 1958, a technical worker’s monthly wages were HK$360 and an unskilled worker earned only HK$75 (Hong Kong Government 1959: 32). A year before the introduction of free-to-air television in 1967, Rediffusion television had only 67,000 subscribers (Hong Kong Government 1967: 206). Thus before 1967 television was an elite medium and its social impact was minimal.
Num Pages: 8
Keywords: 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; Hong Kong (corpus analysé); Hong Kong (lieu de production du savoir); _Nettoyé

Civil Society, Regulatory Space and Cultural Authority in China’s Television Industry - Keane, Michael (Television, Regulation and Civil Society in Asia, 2002)
The question of why civil society presents such appeal for commentators, scholars and journalists writing about developing nations is an important one. The most likely explanation is that a kind of global faith exists in civil society as the driving force of a new world order. This global transformation, exemplified by the collapse of the Soviet bloc, celebrates people’s freedom to participate in public discourse, and ultimately in processes of directly electing political representatives. In this sense the concepts of civil society and the public sphere come together to describe a global anti-authoritarian groundswell where the power of ideas is linked to global cultural development.
Num Pages: 5
Keywords: 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Océanie (lieu de production du savoir); Australie (lieu de production du savoir); Chine (corpus analysé); _Nettoyé

Out of Reach: Television, the Public Sphere and Civil Society in the Philippines - Santos, Josefina M. C. (Television, Regulation and Civil Society in Asia, 2002)
In the uprising of 16-20 January 2001, which ousted former Philippine President Joseph Estrada from power, two forces stood out as pivotal: television (specifically the coverage of the impeachment trial which was the centre of public attention) and civil society (which was instrumental in the uprising itself). In this chapter I argue that notwithstanding the central importance of television in this most recent national political change, the regulation of the sector and its long-term associations with crony capitalism have established barriers to civil society finding its voice on television.
Num Pages: 1
Keywords: 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; Philippines (corpus analysé); Philippines (lieu de production du savoir); _Nettoyé

Civic or Civil Contingencies?: Regulating Television and Society in Singapore - Birch, David; Phillips, Marianne (Television, Regulation and Civil Society in Asia, 2002)
Singapore has changed dramatically in the last forty years, moving in the 1960s and 1970s from domestic import substitution to low-cost exportoriented goods. Then in the 1980s developing a regional financial and business hub and now increasingly positioning itself as an exporter of capital and expertise (Courtenay 1995: 90). With exceptionally high economic growth rates most years, a GNP per capita of US$6,000 more than Australia and three times Australia’s annual average growth, Singapore has attracted a high percentage of foreign direct investment. Despite exhibiting similar advantages to Australia in terms of a well-educated workforce, competitive pricing, developed transport and telecommunications and citizens from culturally diverse business, family and personal networks throughout the region, Singapore’s media and resultant civil and civic development has not been as progressive and liberal as Australia’s and indeed has not kept pace. So it would appear that state existence, security and prosperity as desired ends for Singapore do not necessarily rely on an equal strengthening of the public sphere, or at least this is not evident to date.
Num Pages: 16
Keywords: 1-TV; 2-Approches sociologiques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Océanie (lieu de production du savoir); 5-Autrice; Australie (lieu de production du savoir); Singapour (corpus analysé); _Nettoyé

Civil Society in Charge?: Television and the Public Sphere in Indonesia after Reformasi - Kitley, Philip (Television, Regulation and Civil Society in Asia, 2002)
Television was introduced to Indonesia in 1962 as part of President Sukarno’s flurry of nationalistic ‘symbol wielding’ associated with the Fourth Asian Games (Feith 1963). Televisi Republik Indonesia’s (TVRI) legal status as a creature of the president was reinforced further in Presidential Decree #27, 1963, when it was absorbed after the Games into the ‘Spirit of Sukarno Foundation’, a highly personalised institution under the direct control of the President. TVRI was established as a Foundation in its own right on 20 October 1963, with the President as General Manager (Presidential Decree #215, 1963). Article 3 nominates TVRI as the sole organisation authorised to establish and develop television stations in Indonesia, a highly significant provision which made the commercial broadcasters established in the 1990s dependent on TVRI. TVRI’s status as an activity of the TVRI Foundation was not formally revoked until the enactment of Broadcasting Law #24, 1997, although in administrative practice it came under the control of the Department of Information in 1966.
Num Pages: 10
Keywords: 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Océanie (lieu de production du savoir); Australie (lieu de production du savoir); Indonésie (corpus analysé); _Nettoyé

Out in Front: Government Regulation of Television in Malaysia: Government Regulation - Kitley, Philip; Nain, Zaharom (Television, Regulation and Civil Society in Asia, 2002)
Modern Malaysia was established in 1963 following a drawn-out struggle against British interests which had occupied territory on Penang and Singapore and the Straits of Malacca in 1786, 1819 and 1824 respectively. In 1867 these outposts came under the control of the British Colonial Office and were governed as a Crown Colony. Although Britain did not directly colonise the Malay States, which remained legally autonomous, it imposed effective administrative control over Malaya and the Borneo territories from the late 1870s until the Japanese occupation in 1942.
Num Pages: 2
Keywords: 1-TV; 2-Approches sociologiques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Europe (lieu de production du savoir); 4-Océanie (lieu de production du savoir); 5-Auteur.rice PANDC; Australie (lieu de production du savoir); Malaisie (corpus analysé); Royaume-Uni (lieu de production du savoir); _Nettoyé

Television, Media Reform and Civil Society in ‘Amazing Thailand’ - Lewis, Glen (Television, Regulation and Civil Society in Asia, 2002)
The reform of media regulation can be read as part of the wider movement towards democratisation in Thailand in the 1990s. Real progress was made in media reform, yet as the traditional control of the Army has been reduced, the power of commercial media monopolies has grown. The main threat to further media liberalisation is now the growth of private monopolies. This was exemplified by the election of Thaksin Shinawatra in January 2001, as he is a media magnate on an international scale comparable with Italy’s Silvio Berlusconi. Both men have used their communications business as a path to political power. The first part of this chapter will summarise Thai ideas about civil society, television regulation and the political context of media reform, followed by an analysis of how civil society issues are represented on Thai TV. Broadly, there are urban news and current affairs programmes of an investigative nature, and then there are rural-oriented programmes featuring community participation, notably Lan Ban Lan Muang. Finally, the prospects for media regulation since Thaksin’s election will be considered. The progress towards media reform made in the second half of the 1990s has since stalled under Thaksin’s new government.
Num Pages: 19
Keywords: 1-TV; 2-Approches sociologiques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); Thaïlande (corpus analysé); _Nettoyé; États-Unis (lieu de production du savoir)

Changing Contexts, New Texts: ‘‘Inserting’’ TV into the Transforming Text of Post-1980 Bengali Cinema - Gooptu, Sharmistha (Television in India: Satellites, Politics and Cultural Change, 2008)
This chapter analyses a profound transformation of Bengali regional-languagecinema since the early 1980s, a transformation that fundamentally changedthe industry and one that can arguably be attributed at least partly to thecreation of a Bengali television-watching public in the same period. Itfocuses on a trend that emerged in mainstream Bengali cinema during the1980s and was sustained thereafter, and brought into prominence a newconfiguration of elements previously marginal to Bengali films. This trans-formation was to do with mainstream Bengali cinema’s increasing adaptation of what are commonly known as the ‘‘masala’’ or ‘‘formula’’ elementsof Bombay cinema such as racy dialogues, stereotypical villainous char-acters, stylized fights and song-and-dance sequences. This new genre, whichhas commonly been discredited as the Bengali film industry’s totally unim-aginative imitation of the popular Hindi-language cinema of Bombay,completely altered what had been the dominant aesthetic of Bengali cinematill about the mid-1970s. Until this point, Bengali cinema was marked by itsclose relationship with Bengali literature and a Bengali middle-class worldview, greater realism than Bombay cinema or other mainstream regionalcinemas, and naturalistic acting styles, and was radically transformed by agrowing adoption of the ‘‘formula’’ elements commonly identified withpopular Hindi cinema. Industry sources, however, indicate that this newtrend was successful in boosting the Bengali film industry, which had beenswamped by a severe economic crisis since the 1970s. The industry’s crisiswas caused by a host of factors: the most important of these was the Ben-gali middle-class audience’s shift to television as a result of an increasingly unsatisfactory film-going experience in this period. The creation of a Ben-gali television public in the early 1980s shifted audiences from the cinematheatres, thereby significantly reducing film revenues in Calcutta, until then the prime market for Bengali films.
Num Pages: 11
Keywords: 1-Cinéma; 1-TV; 2-Analyses formalistes; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; Inde (corpus analysé); Inde (lieu de production du savoir); _Nettoyé

Bowling with the Wind: A Television Producer’s View on Cricket and Satellite TV in Contemporary India - Hutton, Peter (Television in India: Satellites, Politics and Cultural Change, 2008)
Growing up in England, it never really occurred to me to wonder why Inever saw cricket from India on television. Indian cricket was always insight; we had Bishen Singh Bedi in his mysterious headgear wheeling in forNorthamptonshire, Srinivas Venkatraghavan wrapped in sweaters at Derby,Madan Lal playing in front of handfuls of old men in the Yorkshire leagues.Yet the Packer ‘circus’ largely left India alone, and in England the touringIndian side became an unglamorous pause between the glorious tours bythe West Indies and Australia. Little was I to guess that once I started working in television, India would become central to the world cricketeconomy and crucial to the technological improvements in the coverage ofthe game.
Num Pages: 10
Keywords: 1-TV; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Europe (lieu de production du savoir); Inde (corpus analysé); Royaume-Uni (lieu de production du savoir); _Nettoyé

Soaps, Serials and the CPI(M), Crickets Beat Them All: Cricket and Television in Contemporary India - Majumdar, Boria (Television in India: Satellites, Politics and Cultural Change, 2008)
The changing relationship between cricket and satellite television in thecontext of the Indian sub-continent has been a subject of considerablescholarly inquiry. That one nourishes the other is well known. However,what is relatively little known is the degree to which this interdependence hasgrown in recent times. So much so that cricket tournaments, or ratherdesignated TV tournaments, are being planned with alacrity by the Board ofControl for Cricket in India (BCCI). Television rights for these overseastournaments/matches spread over the next 4 years had initially generated $219.5 million for the BCCI.1 On the other hand, satellite channels too havestarted planning cricket programming around these tournaments, program-ming expected to generate millions in advertising revenue.2 While theorganization of such big-money events well encapsulates the symbiotic rela-tionship between cricket and satellite television within a burgeoning Indianeconomy, other local/regional dimensions of this relationship are often noless fascinating. Tele-visual hype generated on the occasion of a regionalcricket body election in July 2006 in West Bengal, especially by the multiple 24-hour Bengali news channels, drew attention to the local variant of thestory involving big-money television and even bigger-money sport. Thischapter, on the basis of two distinct case studies – the implications of the tri-nation 1-day series played in Malaysia in September 2006 involving Aus-tralia, West Indies and India, and Television coverage of the Cricket Asso-ciation of Bengal Elections in July 2006 – will comment on the complex andever-changing relationship between cricket and television in India. At thesame time it will attempt to question the rationale behind this growing interdependence and probe what this means for the Indian nation at large.
Num Pages: 16
Keywords: 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Océanie (lieu de production du savoir); 5-Auteur.rice PANDC; Australie (lieu de production du savoir); Inde (corpus analysé); _Nettoyé

‘Give Me a Vote, and I Will Give You a TV Set’: Television in Tamil Nadu Politics - Ranganathan, Maya (Television in India: Satellites, Politics and Cultural Change, 2008)
The role of television in democratic politics has been a subject of politicalcommunication studies at least since John F. Kennedy’s performance ontelevised debates supposedly turned around his electoral fortunes and wonhim the 1960 US presidential election. In India too, the potential of themedium in political communication has mostly been analysed in the contextof how television coverage of political leaders and parties, or the lack of it,affects voting behaviour. This chapter differs in its approach. In analysing television’s role in electoral politics in the southern Indian state of Tamil Nadu, it does not look at discourses prevalent on television. Instead, itunderscores how the medium itself has become a part of political discourse,particularly during elections. It points out how television acquired centre-stage as an electoral issue in the 2006 Tamil Nadu assembly elections, evengoing to the extent of dictating poll alliances. Tamil Nadu offers an inter-esting case study to understand the interface between television and Indianpolitics not only because Tamil films and state politics have been inex-tricably intertwined for decades, but also because the two notable political parties in the state have a stake in the private satellite television business.
Num Pages: 18
Keywords: 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Autrice; Inde (corpus analysé); Inde (lieu de production du savoir); _Nettoyé

Muslims on Television: News and Representation on Satellite Channels - Sengupta, Roshni (Television in India: Satellites, Politics and Cultural Change, 2008)
For any exposition of the television news medium to hold merit itbecomes imperative to glide into the past to recover its earliest antecedent –the newsreel. Newsreel presentation involved an intimate relationshipbetween its producers and events that print reporters had never faced: it wasentirely dependent on pictures that required the camera to be in positionbefore they unfolded (Montague, 1938: 49). Thus, the early producers ofnewsreels discovered that at times when there was a lack of any worthwhileor pictorial news it was possible to create it. It was also possible to ‘experiment’ with news. Newsreels in the United States, therefore, experi-mented with everything: news borrowed from newspapers, studies by collegeprofessors, animated diagrammatical representations of a volatile stockmarket, and so on. Since newsreels were exhibited before drama perfor-mances and film shows in theatres, a great degree of dramatisation andsensationalism was not deemed out of place. They too became part of theentertainment media.
Num Pages: 19
Keywords: 1-TV; 2-Approches sociologiques; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Europe (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; Inde (corpus analysé); Pologne (lieu de production du savoir); _Nettoyé

Politics Without Television: The Bahujan Samaj Party and the Dalit Counter-Public Sphere - Loynd, Maxine (Television in India: Satellites, Politics and Cultural Change, 2008)
The place of the media in an effective liberal democracy is generally seen assacrosanct. The media play an important role in the collection and dissemination of information and provide an avenue for keeping politiciansaccountable to their constituents.Mindful of the impact themedia can have onthe fortunes of a political party, and the careers of individuals within it, mostpoliticians in liberal democracies tend to tread carefully in terms of how theymanage their relationship with the media. Politicians hire public relations andmedia advisors, and seek media training in order to learn how to ‘use’ themedia to further their political aims. In the main, the approach of India’spolitical parties to media relations has become remarkably similar. However, an exception appears when we examine the relationship of theBahujan Samaj Party (BSP), and its leader Mayawati, with the media in bothits mainstream forms – print and television. Despite early attempts to engagewith the media, by the late 1990s the BSP was running election campaignswith a media strategy of almost complete disengagement. This has not led topoor electoral results for the party. In fact, the party has been in power in thenorth Indian state of Uttar Pradesh (UP) on a number of occasions: in 1995,1997 and 2002, either in coalition or as a minority government. Upon winning minority government in the 2002 election, a journalist declared that ‘Inan age of television and information technology, Mayawati is a politician whodefies all conventional standards and norms . . . [and] despises giving interviews . . . ’(Bhushan, 2002: 18). In May 2007 the BSP won the UP state election outright to take power as the first majority government that UP hasseen for 15 years. Again this election was won while largely ignoring main-stream newspapers and television, with Mayawati even taunting journalistsafter the win, ‘I know you were upset I did not meet you during the campaign but I noticed that you had already run ahead with your conclusions, so Ithought why disturb you?’ (Gopinath, 2007).
Num Pages: 25
Keywords: 1-TV; 2-Approches sociologiques; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Océanie (lieu de production du savoir); Australie (lieu de production du savoir); Inde (corpus analysé); _Nettoyé

India Talking: Politics, Democracy and News Television - Mehta, Nalin (Television in India: Satellites, Politics and Cultural Change, 2008)
After four decades of state monopoly over television Indian viewers gottheir first taste of private television in the early 1990s. By 1998, the first of India’s private 24-hour news channels was on the airwaves and by 2007more than 300 satellite channels were broadcasting into Indian homes. Ofthese, 106 broadcast news in 14 languages and as many as 54 of these were24-hour news channels in 11 languages.1 These are conservative figures thatdo not include many foreign and local cable networks that also broadcastnews.2 Even so, the numbers are a stark illustration of how the Indian statelost control over television broadcasting despite its best efforts to the con-trary. No other country in the world has such a concentration of private news channels as India. The creation of a television public has significantimplications for democracy and this essay focuses on what 24-hour newsmeans for India. It argues that the emergence of television news networkshas greatly enhanced and strengthened deliberative Indian democracy.Commercial mass media stands at the junction of politics and the economy,enabling the entry of citizens onto the stage of politics, while simultaneouslyseeking to appropriate that energy for its own commercial benefit (Rajago-pal, 1999: 133). This is a claim that needs to be differentiated from the usual journalistic self-image of the fourth estate acting as vigilant defenders ofdemocratic ideals. That notion should not be romanticised too muchbecause news production itself is a cultural process that cannot be separatedfrom its social environment. News producers always function under certaininstitutional constraints that are endemic to the news-gathering process.Leftist and liberal scholars of the media differ in their emphasis but allagree that news production is always circumscribed by institutional filters.3News is ‘more a pawn of shared suppositions than the purveyor of selfconscious messages’ (Schudson, 1995: 15). Yet, the media are important,and while it is difficult to draw direct causal linkages, there is no doubt thatthey initiate and create a new sphere of political action.
Num Pages: 30
Keywords: 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Identités diasporiques; Inde (corpus analysé); Singapour (lieu de production du savoir); _Nettoyé

The Mahatma didn’t like the movies and why it matters: Indian broadcasting policy, 1920s–1990s - Jeffrey, Robin (Television in India: Satellites, Politics and Cultural Change, 2008)
This chapter examines the ideological and structural foundations of Indianbroadcasting policy as it developed from the 1930s to the 1990s. The chapter argues that the failure of Indian governments to make the most of radioand television for economic and social development stemmed from threesources: (i) the restrictive policies inherited from a colonial state, (ii) thepuritanism of the Gandhian national movement, and (iii) the fear, madevivid by the 1947 partition, of inflaming social conflict. The policies andinstitutions established in the 1940s and 1950s shaped Indian broadcasting for the next 40 years and have been significantly subverted only since 1992as a result of the transformation effected by satellite television.
Num Pages: 19
Keywords: 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Méthodologie de recherche décoloniale; 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); Inde (corpus analysé); Singapour (lieu de production du savoir); _Nettoyé

Television in Post-Reform China: Serial Dramas, Confucian Leadership and the Global Television Market - Zhu, Ying (Routledge, 2008)
This book explores the political, economic, and cultural forces, locally and globally that have shaped the evolution of Chinese primetime television dramas, and the way that these dramas in turn have actively engaged in the major intellectual and policy debates concerning the path, steps, and speed of China’s economic and political modernization during the post-Deng Xiaoping era. It intertwines the evolution of Chinese television drama particularly with the ascendance of the Chinese New Left that favors a recentralization of state authority and an alternative path towards China’s modernization and China’s current administration’s call for building a "harmonious society." Two types of serial drama are highlighted in this regard, the politically provocative dynasty drama and the culturally ambiguous domestic drama. The book also provides cross-cultural comparisons that parallel the textual and institutional strategies of transnational Chinese language TV dramas with dramas from the three leading centers of transnational television production, the US, Brazil and Mexico in Latin America, and the Korean-led East Asia region. The comparison reveals creative connections while it also explores how the emergence of a Chinese cultural-linguistic market, together with other cultural-linguistic markets, complicates the power dynamics of global cultural flows.
Keywords: 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; Chine (corpus analysé); _Nettoyé; États-Unis (lieu de production du savoir)

Prime Time Soap Operas on Indian Television - Munshi, Shoma (Routledge India, 2020)
This book examines the phenomenon of prime time soap operas on Indian television. An anthropological insight into social issues and practices of contemporary India through the television, this volume analyzes the production of soaps within India’s cultural fabric. It deconstructs themes and issues surrounding the "everyday" and the "middle class" through the fiction of the "popular". In its second edition, this still remains the only book to examine prime time soap operas on Indian television. Without in any way changing the central arguments of the first edition, it adds an essential introductory chapter tracking the tectonic shifts in the Indian "mediascape" over the past decade – including how the explosion of regional language channels and an era of multiple screens have changed soap viewing forever. Meticulously researched and persuasively argued, the book traces how prime time soaps in India still grab the maximum eyeballs and remain the biggest earners for TV channels. The book will be of interest to students of anthropology and sociology, media and cultural studies, visual culture studies, gender and family studies, and also Asian studies in general. It is also an important resource for media producers, both in content production and television channels, as well as for the general reader.
Keywords: 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; Inde (corpus analysé); Koweït (lieu de production du savoir); _Nettoyé

Culture, Politics, and Television in Hong Kong - Ma, Eric Kit-wai (Routledge, 1999)
Ma looks at the ways in which the identity of Hong Kong citizens has changed in the 1990s especially since the handover to China in 1997. This is the first analysis which focuses on the role, in this process, of popular media in general and television in particular. The author specifically analyses at the relationship between television ideologies and cultural identities and explores the role of television in the process of identity formation and maintenance.
Keywords: 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; Hong Kong (corpus analysé); Hong Kong (lieu de production du savoir); _Nettoyé

Television Regulation and Media Policy in China - Chin, Yik-Chan (Routledge, 2016)
Since the late 1990s, there has been a crucial and substantial transformation in China’s television system involving institutional, structural and regulatory changes. Unravelling the implications of these changes is vital for understanding the politics of Chinese media policy-making and regulation, and thus a comprehensive study of this history has never been more essential. This book studies the transformation of the policy and regulation of the Chinese television sector within a national political and economic context from 1996 to the present day. Taking a historical and sociological approach, it engages in the theoretical debates over the nature of the transformation of media in the authoritarian Chinese state; the implications of the ruling party’s political legitimacy and China’s central-local conflicts upon television policy-making and market structure; and the nature of the media modernisation process in a developing country. Its case studies include broadcasting systems in Shanghai and Guangdong, which demonstrate that varied polices and development strategies have been adopted by television stations, reflecting different local circumstances and needs. Arguing that rather than being a homogenous entity, China has demonstrated substantial local diversity and complex interactions between local, national and global media, this book will be of interest to students and scholars of Chinese media, politics and policy, and international communications.
Keywords: 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; Chine (corpus analysé); Chine (lieu de production du savoir); _Nettoyé

Cultural Polysemy and Vernacular Cosmopolitanism in the Theme Songs of Hong Kong Television Dramas - Kai Khiun, Liew (Television Histories in Asia, 2015)
In 1980, Hong Kong’s commercial Television Broadcast Limited (TVB) television drama The Bund ( 上海滩 ) was popularly received in the city as well as in South-East Asia and the broader Chinese diaspora. Set in the cosmopolitan treaty port of Shanghai in the 1920s, The Bund revolves around the violent ascent of a coolie (Ray Lui) and a disillusioned student activist (Chow Yun-Fat) to become prominent mobsters. Not only were two sequels made within that year, but this historical gangster drama has been repeatedly resurrected in television dramas and fi lms, including Chow’s redux, The Last Tycoon ( 大上海 ), three decades later in 2012. From karaoke lounges to social media sites, theme songs of The Bund remain popular more than three decades after the dramas were screened . With music composed by Joseph Koo, lyrics by Wong Jim and sung by Frances Yip, the main and supplementary theme songs refl ected the intimate role of the Hong Kong-based contemporary Cantonese popular music, or Canto-pop, in cultivating a more memorable and enduring televisual culture. With the smooth synchronization of Koo’s classical music with the undulating pitch of Yip, the song articulates the unpredictable tribulations of the changing fortunes in the treaty-port of Shanghai in the interwar years. To a certain extent, it is also a narrative that reminds viewers in Hong Kong and beyond of similar socio-political and historical predicaments.
Num Pages: 18
Keywords: 1-TV; 2-Analyses formalistes; 2-Approches sociologiques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; Hong Kong (corpus analysé); Singapour (lieu de production du savoir); _Nettoyé

Shifts in Korean Television Music Programmes: Democratization, Transnationalization, Digitalization - Jung, Sun (Television Histories in Asia: Issues and Contexts, 2015)
Korea was the fifteenth country in the world to start television broadcasting when it first launched in Seoul in 1956. Since then, the structure, content and policies concerning Korean television have continuously transformed, due largely to changing contextual circumstances such as wide-ranging socio-political democratization and the rise of the neoliberal global economic system and digital technologies. Up until the 1980s, the oligopolistic structure of the two public broadcasting networks – Korean Broadcasting System (KBS) and Munhwa Broadcasting Corporation (MBC) – dominated the broadcasting market. However the landscape has dramatically changed since the early 1990s, with 11 newly launched commercial terrestrial broadcasting channels (including Seoul Broadcasting System (SBS) in December 1991) and 153 cable channels when the multichannel television era began (Jin 2005 : 1). A digital satellite television system called Skylife was launched in March 2002, and airs 176 channels at the time of writing. Such changes stem from the shift in the domestic political climate where liberalization and privatization were promoted in assertively practiced neoliberal reform movement in the early 1980s, as well as changes in the global cultural industry environments based largely on globalization and the development of digital technologies. This chapter explores democratization, transnationalization and digitalization, three active factors within Korean television broadcasting by analysing changes and shifts in popular music programmes.
Num Pages: 16
Keywords: 1-TV; 2-Approches sociologiques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude de la réception; 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Océanie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; Australie (lieu de production du savoir); Corée du Sud (corpus analysé); _Nettoyé

Taiyu Serial Dramas in Taiwan: A History of Problem-Making - Irene Yang, Fang-Chih (Television Histories in Asia, 2015)
The construction of a problem, be it a crisis or a moral panic, is an attempt of policing and control, for the maintenance of hegemony and authority (Hall et al. 1978 ). A problem emerges as a problem only when it is out of its proper place, just like dirt becomes dirt only when it is not properly placed in the earth. The elimination of dirt is necessary in maintaining the cleanliness of the social order (Douglas 2002 ). In other words, it is the need for a particular social arrangement that constitutes the existence of a problem. Taiyu, the lingua franca of the Taiwanese, became a problem of dialect (called Minnanyu) to be eliminated when the KMT colonial regime moved to Taiwan, building it as a Chinese nation and instituting Mandarin as the national language. Television is central to the building of the Chinese nation. Taiyu serial dramas were broadcast soon after the fi rst network was established in 1962, but have been constructed as the most problematic and debased genre since the early 1970s when the second TV station, CTV (1969), and the third, CTS (1971), were established and used serial drama to compete for profi t. Accusations directed at the poverty of its quality and the vulgarity of the audiences have characterized mainstream criticisms and constructions of Taiyu serial dramas as problems from the 1970s to the present. This chapter investigates not only the how and what but also the why of this problem-construction, as an attempt to understand the power mechanisms at work in struggling for hegemonic control. It charts two historical moments – the 1970s and from the 1990s to the present – when language has played a signifi cant role in the articulations of serial dramas as problems and explores the changing political, economic and cultural forces that situate them as problems worthy of discussion. I argue that the history of this problem-making demonstrates the centrality of Chinese culture in political domination through cultural means, with ethnic/class politics playing a central role in the maintenance of a hierarchical social order. In the 1970s, Chinese culture was used to create ethnic/class divisions within Taiwan while simultaneously creating the illusion of a symbolic whole under the name of the Republic of China. However, since the 1990s, and intensifying after the 2000s, with the entanglement of democratization and neoliberalization in Taiwan and the rise of China, the ethnic/class tension is not just complicated by confl icted national identifi cations and Chinese culturepromoted by both the KMT Party’s Republic of China and the People’s Republic of China, but also for unifi cation purposes. While democratization, which involved the search for Taiwanese identity, led to the rise of Taiyu-based Hsiangtu drama, the neoliberal defi nition of culture as economic resource, which consecrates Chinese culture through capital investment, facilitates this unifi cation process while creating further ethnic/class/national identity divisions within Taiwan. The result is a disparaging of Taiyu-based culture in general and, in particular, Taiyu serial drama as a problem to be reformed.
Num Pages: 18
Keywords: 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Méthodologie de recherche décoloniale; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; Taiwan (corpus analysé); Taiwan (lieu de production du savoir); _Nettoyé

The Television of Intervention: Mediating Patron–Client Ties in the Philippines - Corpus Ong, Jonathan (Television Histories in Asia: Issues and Contexts, 2015)
Similar to the other countries discussed in this volume, elite dominance over mass media has been a main characteristic of Filipino history. Foreign-educated Filipino intellectuals from wealthy families founded the early periodicals that demanded reform and/or independence from Spanish colonization in the late nineteenth century (Anderson 1983 ). Today, ‘old rich’ landowning families own and operate television networks, radio stations, and newspapers not only as part of prestigious and profi table media conglomerates, but also in connection with their interests in industries as varied as oil and agriculture to insurance, shipping, and mining.
Num Pages: 20
Keywords: 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Étude de la réception; 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; Philippines (corpus analysé); _Nettoyé; États-Unis (lieu de production du savoir)

Unpacking Multiculturalism and Islam in Malaysia: State–Corporate Television Celebrations of Bangsa Malaysia - Khattab, Umi (Television Histories in Asia: Issues and Contexts, 2015)
This chapter presents a critical analysis of media and change in postcolonial Malaysia, a South-East Asian nation of 29 million multicultural people, with a focus on the role of television in the nation’s transformation following independence from British rule in 1957. Despite having inherited the basic democratic institutions of the British political tradition, Malaysia continues to debate the transition from soft authoritarianism to democracy (Means 1996 : 103). Since 1957, Malaysia has been led by a single political party, the Barisan Nasional (BN). While the BN is a coalition of three major ethnic-based political groups, the United Malays National Organisation (UMNO), Malaysian Chinese Association (MCA) and the Malaysian Indian Congress (MIC), it is, in effect, a symbol of Malay-Muslim supremacy (Ketuanan Melayu). UMNO, the dominant group within the party, has, since its formation, aspired to uphold Malay culture as national culture and Islam as the offi cial religion for the country. From the fi rst general elections in 1959 until the 2008 general elections, the BN held two-thirds of the 222 seats in the Dewan Rakyat (House of Representatives). Malaysian media scholar Karthigesu ( 1987 , 1994 ) contends this was largely due to the role of public television, which was launched and promoted by government itself, broadcasting in its colonial service model. In fact, the arrival of state television in 1963 coincided with the formation of the Federation of Malaysia (Moten and Mokhtar 2013 ). In this chapter I argue that television has been pivotal in shaping and transforming the political and cultural landscape of Malaysia as the medium evolved from a strictly national to a loosely global and then fluidly trans-local orientation. While television fi rst enabled the BN to hold its two-thirds majority and build the nation premised on Malay supremacy policies, it subsequently played a part in weakening the BN’s grip over the multiethnic electorate as the UMNO Ketuanan Melayu ideology, layered deep beneath the powdered face of television, surfaced in the digital media era.
Num Pages: 17
Keywords: 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Méthodologie de recherche décoloniale; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Océanie (lieu de production du savoir); 5-Autrice; Australie (lieu de production du savoir); Malaisie (corpus analysé); _Nettoyé

Working Women and Romance on Japanese Television Dramas: Changes since Tokyo Love Story - Freedman, Alisa (Television Histories in Asia: Issues and Contexts, 2015)
Since their development in their current format in the early 1990s as a means to attract female viewers in their twenties, Japanese prime-time television dramas-known commonly as ‘ dorama ’ 1 —have featured working women. Even police procedurals, medical dramas, and serials based on ‘ shojo manga ’ (graphic novels for girls) depict women working outside the home. The dorama most watched by Japanese audiences older than age 25, and those that continue to attract global fans, present the daily lives of independent women working in Tokyo. The protagonists enact fantasies about female professionals while depicting real issues facing the larger generations they represent. Viewers may not want to be these characters, but they can see aspects of themselves in them.
Num Pages: 15
Keywords: 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; Japon (corpus analysé); _Nettoyé; États-Unis (lieu de production du savoir)

Dramatizing the Nation: Television, History and the Construction of Singaporean Identity - Tay, Jinna (Television Histories in Asia: Issues and Contexts, 2015)
Television dramas, both serials and series, have been a long-term recruiter of large-scale national audiences for television broadcasters as they are potentially able to speak to their audience in affective and imaginative ways (Chan 2011 ; Sun and Gorfi nkel 2014). Usually it is the locally produced drama that resonates most with a national audience, the familiarity of the setting and context often carrying signifi cant implications for social and sometimes political life (Blandford et al. 2011 , Chan 2011 ). These television texts can pick up on popular strands of discourses in the public sphere and succeed in establishing a form of dialogue with audiences; in the instances examined in this chapter, this dialogue is about the formation of national identities or citizenships. There is good reason, then, for broadcasters and governments to attempt to use television drama to educate and persuade, although Sugg and Power ( 2011 : 26-7), long-term drama producers at the BBC World Service Trust, warn that for dramas to succeed in this manner, they first have to be entertaining, otherwise they are unlikely to generate an audience in the fi rst place. Audiences are not easily fooled and can sniff out the difference between being entertained and being preached at in a didactic way. This chapter deals with a period in the history of Singapore where television historical drama played a signifi cant role in creating a national past upon which the promotion of a distinctive national identity might be based. In addition to a consideration of a selection of drama series themselves, the chapter draws upon interviews where viewers are encouraged to share their memories of these dramas, and the part they played in the construction of a Singaporean identity.
Num Pages: 20
Keywords: 1-TV; 2-Approches sociologiques; 2-Étude de la réception; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; Singapour (corpus analysé); Singapour (lieu de production du savoir); _Nettoyé

Battling Angels and Golden Orange Blossoms: Thai Television and/as the Popular Public Sphere - Farmer, Brett (Television Histories in Asia: Issues and Contexts, 2015)
On 19 September 2006, the fi rst indication many people in Thailand received that the country was undergoing another military coup d’ é tat, the eighteenth such putsch since 1932, was when the nation’s six free-to-air television networks suddenly suspended regular programming and, channel by channel, started to broadcast a generic mix of royal news and light entertainment (Connors and Hewison 2008). Final confi rmation came again via television later that evening in the form of an offi cial announcement, broadcast at regular intervals across all stations from a central feed, in which the armed commanders in chief behind the coup – the awkwardly titled ‘Administrative Reform Group under the Democratic System with the King as the Head of State’ – explained apologetically that they had temporarily taken control of the nation’s airwaves, as indeed of the nation, exhorting viewers to remain calm and reassuring them that normalcy would soon be restored, at which point broadcasting reverted to the same steady flow of innocuous entertainment programming. For all its exceptional gravity, the 2006 coup’s strategic blend of direct state interventionist control of broadcasting combined with a more indirect use of escapist entertainment as populist pacifi er is arguably a structural characteristic of Thai television history writ large.
Num Pages: 18
Keywords: 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Océanie (lieu de production du savoir); Australie (lieu de production du savoir); Thaïlande (corpus analysé); _Nettoyé

Watching Television in Bhutan - Avieson, Bunty (Television Histories in Asia: Issues and Contexts, 2015)
The kingdom of Bhutan drew the international spotlight in 1999 when it became the last nation on earth to introduce broadcast television. It was a deliberate and strategic move by a country that for centuries had chosen to isolate itself from the rest of the world, turning inward to nurture its own culture. The small Himalayan country, whose population in 2013 was estimated at just 733,000, 1 sits uneasily between two feisty behemoths – China and India – each with over a billion people and an ongoing history of border disputes. Bhutan has long been wary of being swamped, either politically or culturally, by these larger neighbours, as well as the world beyond (Penjore 2004 ).
Num Pages: 16
Keywords: 1-TV; 2-Histoire/Historiographie critique; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Océanie (lieu de production du savoir); 5-Autrice; Australie (lieu de production du savoir); Bhoutan (corpus analysé); _Nettoyé

Trust and Television in Globalizing India - McMillin, Divya (Television Histories in Asia: Issues and Contexts, 2015)
Writing a history of Indian television immediately begs the question, how do we want it read? Exhaustive chronological treatments anchor the field (Kumar 2000 ), ideological examinations reveal a Hindu-centric nation with serious consequences for religious and gender minorities (Rajagopal 1996 ; Mitra 1993 ; Van der Veer 1997 ), development analyses demonstrate the failures of a socialist state (F ü risch and Shrikhande 2007 ), and audience studies reveal complex negotiations among multiple identity positions (Mankekar 1999 ). These critical approaches to the study of television in India rightly expose power differentials that facilitate, through the centuries, the inequities of interwoven structures of imperialism, colonialism, casteism, and capitalist patriarchy. Most importantly, they highlight the chronic condition of distrust in postcolonial societies, making it highly challenging to legitimize profi table connections to global circuits as they modernize under the very conditions that once constrained them.
Num Pages: 20
Keywords: 1-TV; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; Inde (corpus analysé); _Nettoyé; États-Unis (lieu de production du savoir)

Television, Scale and Place-Identity in the PRC: Provincial, National and Global Influences from 1958 to 2013 - Sun, Wanning; Gorfinkel, Lauren (Television Histories in Asia: Issues and Contexts, 2015)
One may argue that Chinese television has already received more than its fair share of attention in the study of Chinese media. As compared with radio and cinema, which developed in the socialist era (1949-78), television has been seen as the dominant medium in the decades of marketization and economic reforms since the late 1970s (Zhu and Berry 2008 ). Television has been studied as a metonym for the ongoing tension and complicity between the Chinese state and the market (e.g., Zhao 1998 ; 2008a) and as a metaphor for the contradictions between a legacy of socialist rhetoric and ethos and a neoliberal market agenda. It is precisely these contradictions that make up what is often referred to as the ‘Chinese characteristics’ (Zhao 2008a; Sun and Zhao 2009 ) of China’s television culture.
Num Pages: 19
Keywords: 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Océanie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; Australie (lieu de production du savoir); Chine (corpus analysé); _Nettoyé

Continental Reality Television and the Expansion of South African Capital - Jacobs, Sean (The Politics of Reality Television: Global Perspectives, 2010)
This chapter wants to argue two things: the ﬁrst part suggests that reality television in Africa – speciﬁcally the series Big Brother Africa, which completed its third season in November 2008 – has had profound impacts for identity politics, gender politics, and the politics of class on the continent. In fact, these are the issues most commonly illuminated by reality television and I wrote about these in a previously published article. The second part of the chapter moves into less explored territory. In that previous article, I brieﬂy discussed how speciﬁcally Big Brother Africa can illuminate the workings of globalization in Africa and, in particular, South Africa’s hegemonic role in that process. Here, I expand on my earlier argument by exploring that hegemony in the context of the growing Chinese presence in Africa. All economic and political indicators suggest that China’s growing investment in mining and infrastructure and its political clout relative to South Africa mean that it is destined to assume a place of prominence on the continent. But here I want to argue that if we want to understand how globalization plays out in Africa, we need to look beyond China’s military and economic expansion. For me, Big Brother Africa can help us make sense of these dynamic processes. South Africa has consistently remained the highest-ranking country in Africain terms of its “global competitiveness” as measured by the World Economic Forum. South Africa dominates regional markets in Southern Africa as well as remaining competitive in the rest of the continent against business rivals from United States and Europe. As it was under Apartheid, there is a close symbiosis between the continental aspirations and interests of the postapartheid state and that of South African business. The advent of democracy in 1994 has opened up African markets for South African business on an unprecedented scale. The South African state is very active on the African continent and keen to develop a leading role for itself. In fact, successive United States governments have viewed South Africa as a continental leader. For example, former President George W. Bush referred to former South African President Thabo Mbeki as his “point man in Africa.”4The South African government underwrites and actively promotes SouthAfrican business’s continental schemes through its “Proudly South African” campaign coordinated through an International Marketing Council situated in the Oﬃce of (the country’s) President since 2002, which links state nationalism with consumption. Separately a statutory Industrial Development Corporation (established in 1940) underwrites the business expansion of South African capital.
Num Pages: 17
Keywords: 1-TV; 2-Approches sociologiques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Afrique (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; Afrique du Sud (corpus analysé); _Nettoyé; États-Unis (lieu de production du savoir)

Reality Television and the Making of Mobile Publics: The Case of Indian Idol - Punathambekar, Aswin (The Politics of Reality Television: Global Perspectives, 2010)
In the summer of 2007, media coverage of Indian Idol-3 focused attention on how people in the Northeast Indian state of Meghalaya cast aside decades-old separatist identities to mobilize support for Amit Paul, a ﬁnalist from the region. While some fans set up websites and blogs to generate interest and support from the rest of the country and abroad, others formed a fan club and facilitated eﬀorts by a range of groups and organizations to sponsor and manage PCOs (public call oﬃces) in diﬀerent parts of Meghalaya, distribute pre-paid mobile phone cards, and set up landline voting booths. Recognizing the ways in which these activities were beginning to transcend long-standing ethnic, religious, linguistic, and spatial boundaries, state legislators and other politicians soon joined the eﬀort to garner votes for Amit Paul, with the chief minister D. D. Lapang declaring Amit Paul to be Meghalaya’s “brand Ambassador for peace, communal harmony and excellence.”1 It seemed that this three-month-long campaign around a reality television program could set the stage for a remarkable refashioning of the socio-cultural and political terrain in Meghalaya. As one commentator remarked:When Meghalaya’s history is written, it could well be divided into two distinct phases – one before the third Indian Idol contest and one after it. A deep tribal-non-tribal divide, punctuated by killings, riots, and attempts at ethnic cleansing, would mark the ﬁrst phase. A return to harmony and to the cosmopolitan ethos of the past would signify the second. The agent of change: Amit Paul, the ﬁnalist of the musical talent hunt on a TV channel.
Num Pages: 21
Keywords: 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 3-Asie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; Inde (corpus analysé); _Nettoyé; États-Unis (lieu de production du savoir)

Globalizing Lifestyles? Makeover Television in Singapore - Lewis, Tania (The Politics of Reality Television: Global Perspectives, 2010)
The past decade has seen an explosion of lifestyle makeover television shows with audiences being urged to “renovate” everything from their homes, bodies, and children to their pets, a process that has seen the emergence of an army of lifestyle gurus on television advising us on what not to eat and what not to wear. While critical academic attention has largely focused on blockbuster reality television formats like Big Brother and Survivor, more recently a growing body of scholarship has started to focus on the “lifestyle turn” on television and the rise of the makeover format. To date much of the work on makeover television has focused on its role in the US and UK. However, in the past couple of years the lifestyle makeover show has become an increasingly global phenomenon with audiences around the world embracing everything from home renovation to plastic surgery makeover shows. This essay is concerned with examining the implications of the global dissemination of such modes of programming, associated as they are with ideologies of neoliberal individualism, self-surveillance and self-promotion, and with a strongly consumption-oriented aesthetic. It emerges out of a pilot study I have been conducting with Dr Fran Martin at the University of Melbourne as a preliminary step in a larger transnational comparative study of lifestyle programming in Asia in which we seek to examine the role of lifestyle television in both shaping and reﬂecting broader shifts in social and cultural identity accompanying the rise of consumer-based modes of modernity.
Num Pages: 15
Keywords: 1-TV; 2-Approches sociologiques; 2-Étude de la réception; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Océanie (lieu de production du savoir); Australie (lieu de production du savoir); Singapour (corpus analysé); _Nettoyé

Latin American Television: A Global View - Sinclair, John (Oxford University Press, 1998)
Latin American Television makes English speakers aware of the dimensions, operation, and significance of the globalization of television in the Spanish-speaking world. Second only in scale to the market for English-language programming, the Spanish-language market embraces not just most nations of South and Central America but also Spain, and even the United States–the sixth largest Spanish-speaking country in the world. This intercontinental space is connected physically by satellite communication, and culturally by a common language and heritage which binds it as both a `geolinguistic region' and an `imagined community' which certain media corporations, Latin American and North American, seek to exploit. A similar phenomenon with regard to Brazil and the Portuguese-speaking world is ... Source: Publisher
Keywords: 1-TV; 2-Approches sociologiques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 4-Océanie (lieu de production du savoir); Australie (lieu de production du savoir); _Nettoyé

Television in Transition in East Asia - Kwak, Ki-Sung (Routledge, 2018)
This book examines the development of television broadcasting in Japan, Hong Kong and South Korea. It explores the policy regimes guiding the development of television broadcasting as a powerful institution and the extent to which new forms of television have become part of each country’s contemporary media mix. It analyses the interests involved in key policy decisions, the institutional dynamics promoting or inhibiting new media markets, and the relative importance in the different countries of cable, satellite, digital broadcasting, and the use of the Internet for purposes associated with television broadcasting. The nature of television regimes in each of the three countries is very different, and the contrasting situations provide great insights into how television is developing, and how it could develop further, both in East Asia and worldwide.
Keywords: 1-TV; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Océanie (lieu de production du savoir); 5-Auteur.rice PANDC; Australie (lieu de production du savoir); Corée du Sud (corpus analysé); Hong Kong (corpus analysé); Japon (corpus analysé); _Nettoyé

Tears, Talk, and Play: A Window to Gender and Sexuality on Tamil Television - Vangal, Uma (Channeling Cultures: Television Studies from India, 2014)
Tamil television lends itself to some interesting initiatives in gender empowerment through its programming in 3 categories – fiction, reality, and talent shows. This chapter provides a glimpse into television programmes on leading Tamil channels over the last decade (2000–10) from a gender perspective. Focusing particularly on women and transgender characters/hosts, emotional and psychological quotients of the shows and their audiences, moments of dramatic intensity, the chapter demonstrates how the vernacular televisual representations were quite different from the stereotypical portrayals of the mainstream ‘national’ television, even though the programmes were produced, televised, and received within the broader patriarchal framework of Tamil cultural and political contexts. The chapter, as a whole, intends to look at the production, representation and identification of Tamil television soaps and reality shows as vehicle for spotlighting gender issues and alternative sexualities in the public domain.
Keywords: 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; Inde (corpus analysé); Inde (lieu de production du savoir); _Nettoyé

Sange ThakunBangla News Channels and Media-Citizenry - Gupta, Nilanjana (Channeling Cultures: Television Studies from India, 2014)
With special reference to the current scenario in West Bengal, this chapter argues that the rise and popularity of Bangla news channels like Star Ananda, 24 Ghanta, Kolkata TV, and Tara News have resulted in the emergence of a vernacular style of news broadcasting which is quite distinct from that of global or national news media. One major point in this chapter is how the vernacular news channels encourage particular forms of address — the emotional, the intimate and the melodramatic — and how close-ups and sound bites create particular kinds of telegenic political leaders who can use these formal characteristics to their advantage. This chapter explores the ways in which a distinctive kind of vernacular is reconfiguring the nature of political participation itself and hence the notion of citizenship and perhaps even the nature and functioning of the nation-state in India.
Keywords: 1-TV; 2-Approches sociologiques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; Inde (corpus analysé); Inde (lieu de production du savoir); _Nettoyé

The Saffron Hues of Gender and Agency on Indian Television - Chakrabarti, Santanu (Channeling Cultures: Television Studies from India, 2014)
This chapter explores the contradiction between two sets of responses to the so-called K-serials, earlier, largely condemnatory ones, and more recent, largely laudatory ones. The chapter aims to understand this contradiction and resolve it. It does so by showing how K-serials were a definitive break at that specific point in time from the ones that had immediately preceded them, especially in bringing to the fore the bahu (daughter-in-law) of Hindu urban extended families. It traces the complex place of gender in the discourse of the Hindu right and explores the strong debt that the K-serials owe to the ideological constructions of the woman and the family by Hindu nationalism. It argues therefore that the consequences of celebrating agency and empowerment in a right wing milieu-as some recent scholarship has done-ends up advocating for a limited and exclusionary form of female agency.
Keywords: 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Europe (lieu de production du savoir); 5-Auteur.rice PANDC; Inde (corpus analysé); Royaume-Uni (lieu de production du savoir); _Nettoyé

Big Brother, Bigg Boss: Reality Television as Global Form - Sen, Biswarup (Channeling Cultures: Television Studies from India, 2014)
This chapter looks at one well-known format in reality television– Big Brother (Bigg Boss in India) – in order to shed light on the complicated relationship between the forces of globalization, national and local cultural formations and the dictates of commercially driven entertainment. It analyses the essential features of format television to argue that the very mode of its constitution as an economic and aesthetic object inclines it towards the global. The chapter elucidates the reality behind global cultural formations by discussing the two main theoretical approaches to the question of global culture – cultural imperialism and cultural globalization. It also offers some speculations about how reality television embodies global form and thus functions as a sort of “Bigg Boss” that dictates contemporary modes of meaningful behaviour.
Keywords: 1-TV; 2-Analyses formalistes; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; Inde (corpus analysé); _Nettoyé; États-Unis (lieu de production du savoir)

NDTV 24x7 Remix: Mohammad Afzal Guru Frame by Frame - Hutnyk, John (Channeling Cultures: Television Studies from India, 2014)
This chapter looks, in particular, at issues surrounding the trial of Mohammad Afzal Guru in 2006–7, but also with reference to the terrible Mumbai attacks of November 2008. Whilst tragic in multiple ways, these events are also made spectacular, emotive, and divisive, according to interpretation by television. The framing of television news in India could be several, but is often not. Pantomime terrors, extravagant formatting, phone-in trial reports seem to be the order of the day. The station ident, newsreader-presenter and video confession all contest for screen attention in the trial of Mohamed Afzal, and the ground for this was prepared long ago. This short history of a 24 hour news channel ends with ‘The Big Fight’ - a staged and theatrical mode of ‘infotainment’ that sacrifices intelligent reporting for ideological fit.
Keywords: 1-TV; 2-Approches sociologiques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); Inde (corpus analysé); Vietnam (lieu de production du savoir); _Nettoyé

When Live News was Too Dangerous: The Early History of Satellite TV in India - Mehta, Nalin (Channeling Cultures: Television Studies from India, 2014)
A unique confluence of technological, political and economic factors in the 1990s drove the transformative process that led to the battering down of the government’s monopoly over television. By the end of the 1990s, the growing strength of Indian capitalism after the liberalization of the Indian economy and the forces of what Thomas Friedman has called ‘Globalisation 3.0’ allowed Indian entrepreneurs to level the playing field. The Indian state, having embarked on economic liberalization, was forced to adapt to satellite television as an agent of global capitalism it certainly did not give up control over television easily or voluntarily. Operating at the junction of public culture, capitalism and globalization, satellite news networks have had profound implications for the state, politics, democracy and identity formation. Despite all their shortcomings and sensationalism, the emergence of satellite television news networks has enhanced and strengthened deliberative Indian democracy.
Keywords: 1-TV; 2-Histoire/Historiographie critique; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; Inde (corpus analysé); Inde (lieu de production du savoir); _Nettoyé

Television News and an Indian Infotainment Sphere - Thussu, Daya Kishan (Channeling Cultures: Television Studies from India, 2014)
The exponential growth of television news in India – from one state controlled network until 1991 to more than 100 news channels in 2012 – has transformed broadcast journalism in the country. This proliferation of news networks has intensified competition for audience and advertising revenue, leading to excessive marketization of news, which increasingly veers toward infotainment. The chapter examines the challenges faced by Indian television news – focusing on economic and political dimensions of television news - and its implications for the world’s largest democracy.
Keywords: 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; Hong Kong (lieu de production du savoir); Inde (corpus analysé); _Nettoyé

From Clients to Consumers: The Missing Citizens among the Indian Television Audience - Sinha, Dipankar (Channeling Cultures: Television Studies from India, 2014)
Beneath many instances of ’sweeping’ change, both structural and representational, in the market-dominant, liberalized and privatized Indian televisual scenario there lies a hidden transcript of continuity insofar as the encoding of development issues, images and messages is concerned. In the periods of Doordarshan and later corporate channels, though with markedly different historical contexts, reference points, contents and styles — the encoding of ’development’ leaves little autonomy to the audiences. In a political slant indicating how the two televisual periods converge in contracting the space for public debate and civic engagement the essay seeks to make a departure from the dominant view which puts them in binary positions.
Keywords: 1-TV; 2-Approches sociologiques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; Inde (corpus analysé); Inde (lieu de production du savoir); _Nettoyé

Spaces of Television: Rethinking the Public/Private Divide in Postcolonial India - Kumar, Shanti (Channeling Cultures: Television Studies from India, 2014)
This chapter critically evaluates changing definitions of ‘public’ in Indian television in relation to discourses of globalization and media privatization. It examines the debate over the nationalist agenda of public broadcasting in India in relation to the demands for alternative models of broadcasting, and the rise of private commercial satellite channels since the 1990s. It also discusses how representations of traditionally private desires of sexuality and intimacy in soap operas, reality TV shows and music television are redefining the public in India. It outlines the ways in which private desire is made visible — and thus made public — through the convergence of the television screen, the cinematic screen, the computer screen, and the mobile screen. It argues that binaries of ‘public’ versus ‘private’ force us into either/or debates even though such category systems are always-already hybrid in postcolonial societies such as India.
Keywords: 1-TV; 2-Approches sociologiques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Identités diasporiques; Inde (corpus analysé); _Nettoyé; États-Unis (lieu de production du savoir)

Television, Narrative Identity, and Social Imaginaries: Hermeneutic Approach - Asthana, Sanjay (Channeling Cultures: Television Studies from India, 2014)
The chapter argues that Paul Ricouer’s hermeneutics offers a way forward in examining not only the ideological and narrative structures of television, but also particular modalities through which viewers appropriate and interpret televisual texts. To this end, the chapter shall sketch an analytic framework by bringing together Ricoeur’s hermeneutic philosophy, particularly his concepts of narrative identity and temporality, and the notion of social imaginaries developed by postcolonial theory in a productive dialogue. Ricoeur’s hermeneutics presents an understanding of the human subject in terms of an embodied subjectivity that takes us beyond singular conceptions of identity, whether in terms of the abstract Cartesian subject, or various other discourse-centred theorizations of subject. The chapter demonstrates that the notion of embodied subjectivity and social imaginaries enable a better grasp in examining the articulations of class, caste, gender, and religious identities on Indian television.
Keywords: 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude de la réception; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; Inde (corpus analysé); _Nettoyé; États-Unis (lieu de production du savoir)

Televisual Temporalities and the Affective Organization of Everyday Life - Mankekar, Purnima (Channeling Cultures: Television Studies from India, 2014)
This chapter sketches a theoretical framework for analyzing the role of television in the temporal and affective organization of everyday life. Rather than engage an empirical analysis of the “impact” of television, the chapter aims to raise conceptual questions about how satellite television participates in the creation of regimes of affect and temporality. Diverging from theories of transnational media that foreground the ubiquity of spatiality, it proposes that we examine how duree and histoire, historical consciousness and the everyday are co-constructed through the affectivity of television. The chapter begins by examining the work of television news in the production of crisis; it analyses how television enables the formation of historical consciousness; and it points to the ways in which television participates in the creation of a sense of the everyday. It thus outlines some of the ways that we can theorize the centrality of television to the production of temporalities of historicity, contemporaneity, and futurity.
Keywords: 1-TV; 2-Approches sociologiques; 3-Asie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; Inde (corpus analysé); _Nettoyé; États-Unis (lieu de production du savoir)

TV after Television Studies: Recasting Questions of Audiovisual Form - Roy, Abhijit (Channeling Cultures: Television Studies from India, 2014)
This chapter locates India, and broadly the post-colonial context, within the larger debates concerning television’s audiovisual form and mode of address. It tries to demonstrate that certain key traits in Indian popular performative traditions, representing an ‘alternative’ negotiation with modernity, are somewhat homologous with what western theorists have tried to specify (though in contradicting terms) as the features of televisual mode of address and ‘flow’. The chapter reads the specific imports of this correspondence in histories of Indian television with special reference to a somewhat novel way television has started imagining the nation after liberalization. The significance of the Indian popular film form as lending a major legacy to tele-viewership in India constitutes a major strand of argument.
Keywords: 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; Inde (corpus analysé); Inde (lieu de production du savoir); _Nettoyé

Reformatting the Format: Philippines in the Global Television Format Business - Santos, Joseﬁna M. C. (Television Across Asia: TV Industries, Programme Formats and Globalisation, 2003)
In the eyes of many observers the Philippine cultural icon that is synonymous with travel, as well as being the subject of numerous advertisements is the jeepney, a public-transport vehicle assembled in the style of the US military jeep but lengthened to accommodate from fourteen to twenty-two sitting passengers. What distinguishes the jeepney from run-of-the-mill public transport however is its artistic décor: a clutter and kaleidoscope of various artefacts from miniature steel horses dotting the hood, to massive, jazzy plastic or steel billboards announcing the name of the jeepney, to murals painted in ﬁesta colours at the sides, to a bizarre combination of items in the front windshield juxtaposing conﬂicting images of the Sto. Nino (the baby Jesus Christ) and stickers with sexually risqué messages.
Num Pages: 12
Keywords: 1-TV; 2-Analyses formalistes; 2-Approches sociologiques; 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; Philippines (corpus analysé); Philippines (lieu de production du savoir); _Nettoyé

Closing the Creativity Gap – Renting Intellectual Capital in the Name of Local Content: Indonesia in the Global Television Format Business - Kitley, Philip (Television Across Asia: TV Industries, Programme Formats and Globalisation, 2003)
From time to time certain television shows ‘stop the nation’. In 2002 the localized version of the Celador licensed format2 Who Wants To Be A Millionaire? glued over a third of Indonesian television households to their screens at 7pm on Saturday nights.3 Is it the vicarious thrill of winning undreamed-of riches in a country which has been the slowest to recover from the Asian economic crisis of 1997 that attracts the audience? Circuses without bread? Perhaps, but this phenomenon is probably not profoundly related to local matters. We need look no further than the thin, phosphor coated screen. Millionaire, as it is referred to in television circles in Jakarta, is entertaining television. As other chapters testify, it has wowed viewers in countries in very varied economic circumstances. Millionaire is just one of a number of quiz and game show formats screening across all channels in Indonesia and is representative of the core business of international format providers in Indonesia which has been growing steadily since 1994.
Num Pages: 19
Keywords: 1-TV; 2-Approches sociologiques; 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); Australie (lieu de production du savoir); Indonésie (corpus analysé); _Nettoyé

Copied from Without and Cloned from Within: India in the Global Television Format Business - Thomas, Amos Owen; Kumar, Keval J. (Television Across Asia: TV Industries, Programme Formats and Globalisation, 2003)
Television programme format adaptation is becoming an increasingly signiﬁcant phenomenon in India as it is in many other countries with an active domestic television industry. Some obvious successes stand out in recent years, such as Kaun Banega Crorepati, the licensed adaptation of Celador’s global format success Who Wants To Be A Millionaire?, and C.A.T.S., a licensed Hindi version of the US detective series Charlie’s Angels. However, sensitivity to local cultural nuances has been critical to their popular reception by Indian audiences. Yet despite a few high-proﬁle licensed adaptations or copycatting, there are far more instances of unlicensed adaptations or cloning, sometimes subtle, other times not.
Num Pages: 16
Keywords: 1-TV; 2-Analyses formalistes; 2-Histoire/Historiographie critique; 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Auteur.rice PANDC; Inde (corpus analysé); Inde (lieu de production du savoir); Suède (lieu de production du savoir); _Nettoyé

Let the Contests Begin! ‘Singapore Slings’ into Action: Singapore in the Global Television Format Business - Lim, Tania (Television Across Asia: TV Industries, Programme Formats and Globalisation, 2003)
Why is the hit Singapore edition of Who Wants To Be A Millionaire? must-see TV?1. Watch it so that you can hold the ‘hottest topic’ with your friends. 2. So you can be encouraged by the courage of some contestants who are bold enough to brave national TV when apparently they have not read enough. 3. So you can judge for yourself if you are bold (and knowledgeable) enough to brave national TV for your possible 1st million. 4. So you can call the number on screen and make your 1st million. 5. Finally, watch it to see for yourself that Singaporeans are not as well read and as globalized as we all think we are.
Num Pages: 17
Keywords: 1-TV; 2-Approches sociologiques; 2-Étude de la réception; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; Singapour (corpus analysé); Singapour (lieu de production du savoir); _Nettoyé

A Revolution in Television and a Great Leap Forward for Innovation?: China in the Global Television Format Business - Keane, Michael (Television Across Asia: TV Industries, Programme Formats and Globalisation, 2003)
Unlike smaller nation-states in this study the People’s Republic of China has never really countenanced a scarcity of domestic television content. Supply has been constant, indicating both the importance and the sheer size of the sector. The nationalized broadcast media has for several decades churned out cheaply produced ﬁlms, documentaries, dramas, and news programmes. During the last two decades of the twentieth century, however, audience demand for domestic content began to wane as more as more international programmes found their way into schedules, particularly in southern China. China’s accession to the World Trade Organization in December 2001 seemed to herald soul-searching among its media mandarins. What would happen? Would China be inundated by foreign content (the worst case scenario) or would China, as it has done over time, absorb and regulate foreign inﬂuences?
Num Pages: 17
Keywords: 1-TV; 2-Analyses formalistes; 2-Approches sociologiques; 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Océanie (lieu de production du savoir); Australie (lieu de production du savoir); Chine (corpus analysé); _Nettoyé

Coping, Cloning and Copying: Hong Kong in the Global Television Format Business - Fung, Anthony (Television Across Asia: TV Industries, Programme Formats and Globalisation, 2003)
Hong Kong is famous internationally as a ﬁnancial market, a shopping paradise, and Chinese ﬁlm production hub, but notoriously (and perhaps even attractively for some) Hong Kong is also a hotbed of piracy of computer software, DVDs, watches and toys.1 While many cultural products such as television dramas and movies are original and quite reputable in the region, media critics argue that the copycat phenomenon, which includes borrowing, inserting and modifying other cultural texts to augment local production, is common in the media and entertainment industries (Fung 1998). Whenever a new form, style, or popular culture trend emerges in Hong Kong, market forces soon kick in to replicate it. However, this kind of reproduction, as shown by the history of cultural production in Hong Kong, does not necessarily lead to a degradation of programme quality. Reproduction is not only a savvy strategy to reduce the ﬁnancial risks inherent to new products, but also aims at producing ‘improved’ versions which can reap more proﬁts for the industry.
Num Pages: 14
Keywords: 1-TV; 2-Analyses formalistes; 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; Hong Kong (corpus analysé); Hong Kong (lieu de production du savoir); _Nettoyé

Cloning, Adaptation, Import and Originality: Taiwan in the Global Television Format Business - Liu, Yu-Li; Chen, Yi-Hsiang (Television Across Asia: TV Industries, Programme Formats and Globalisation, 2003)
Taiwan residents enjoy one of the most abundant television diets in East Asia. Eighty per cent of households subscribe to cable television services, offering a buffet of more than eighty channels including niche and full service channels. Taiwan’s television industry, while relatively small in comparison with its competitors in East Asia, has established a reputation for creatively re-generating formats developed elsewhere.
Num Pages: 20
Keywords: 1-TV; 2-Analyses formalistes; 2-Approches sociologiques; 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; Taiwan (corpus analysé); Taiwan (lieu de production du savoir); _Nettoyé

A Local Mode of Programme Adaptation: South Korea in the Global Television Format Business - Lee, Dong-Hoo (Television Across Asia: TV Industries, Programme Formats and Globalisation, 2003)
Television has been called ‘a Western-originated project’ (Barker 1997: 5) and an institution of Western capitalist modernity. The global circulation of Western-centred, or more speciﬁcally, American-centred cultural products, contributes to the formation and dissemination of a global shared culture that reaches across the boundaries of nation-states. In the process American cultural products play a role in the formation of local television cultures.
Num Pages: 18
Keywords: 1-TV; 2-Approches sociologiques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; Corée du Sud (corpus analysé); Corée du Sud (lieu de production du savoir); _Nettoyé

Feeling Glocal: Japan in the Global Television Format Business - Iwabuchi, Koichi (Television Across Asia: TV Industries, Programme Formats and Globalisation, 2003)
In March 2001 a Japanese newspaper report entitled ‘Indians are addicted to a quiz show’ drew attention to a phenomenally popular television programme in India – a quiz show that attracts millions of viewers in which challengers strive to win prize money (Asahi Shinbun 2001). What was particularly eye-catching for the journalist was the proﬂigately decorated studio set located in Mumbai (Bombay) and the caring guidance of the MC, a ﬁlm star famous in India. The name of the show, as you might have already inferred, was Who Wants To Be A Millionaire?.
Num Pages: 15
Keywords: 1-TV; 2-Approches sociologiques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; Japon (corpus analysé); Japon (lieu de production du savoir); _Nettoyé

Asia: New Growth Areas - Keane, Michael (Television Across Asia: TV Industries, Programme Formats and Globalisation, 2003)
The previous chapter introduced in broad brushstrokes the issues at stake in this study, beginning with a critique of globalization and moving on to sketch in ﬁner detail national television systems, the role of local content, and the economic importance of formats. The chapter concluded with a brief overview of the vagaries of copyright law as it applies to formats. Here, we initiate a discussion of Asian television systems beginning with a much different perspective on the ramiﬁcations of cultural borrowing. In this context we note that the format business straddles the divide between creative endeavour and innovation on the one hand, and slavish imitation on the other. This polarization manifests in widespread misunderstanding of the goals of format producers and distributors, and the role that formats play in the shaping of television schedules. We need therefore to ﬂesh out the in-between issues. These are primarily concerned with the relationship between the format and its localization, television consumption within ‘cultural continents’, and changes in media systems. Taking this further we note the relationship between production and reception within Asia, the growth of television industries in the region and the relationship between formatting and new media distribution platforms that use interactive technologies allowing viewers to feedback responses. This exercise enables us to identify an alternative list of conceptual tools to those championed by political economy scholars.
Num Pages: 12
Keywords: 1-TV; 2-Analyses formalistes; 2-Approches sociologiques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Océanie (lieu de production du savoir); Australie (lieu de production du savoir); _Nettoyé

Gender, Ideology and Latin American Children's Animated Television - Gonzalez-Rodriguez, Milton Fernando (Children, Youth, and International Television, 2022)
Animation allows for the creation of mediatic spaces that strengthen prevailing ideologies of masculinity and femininity. Manhood seems to operate as a key point of reference in the creation of televised animation across Latin America, especially by elevating certain heroic cultural narratives. Through a review of 21 television series, produced between 2008 and 2018, this chapter examines the portrayals of femininity and masculinity in some of the most widely broadcast animated series from the region. As a norm, Latin American illustrators adhere to the tradition of depicting female figures as secondary characters, as leading characters with a certain degree of autonomy, or as subaltern, considerate, and supportive figures. By contrast, male figures are portrayed as strong, daring, independent, and primary characters, often destined to lead their families and communities, and save their weaker friends that are typically female characters.
Num Pages: 11
Keywords: 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 4-Europe (lieu de production du savoir); 5-Auteur.rice PANDC; Argentine (corpus analysé); Belgique (lieu de production du savoir); Brésil (corpus analysé); Chili (corpus analysé); Colombie (corpus analysé); Mexique (corpus analysé); Pérou (corpus analysé); _Nettoyé

From Quinceañera to Miss XV: Coming of Age in Mexican Screen Melodrama - Rios, Sofia (Children, Youth, and International Television, 2022)
This chapter historicises and contextualises the evolution, production, and development of key Mexican screen melodramas over fifty-two years to understand and mediate Mexico’s ambivalence around socioeconomic background, ranother. Perhaps if Televisa had allowed its various ace and religion, gender and worth, family and duty. The chapter demonstrates the importance of localised scholarly inquiry into Mexican audiovisual media that considers not only narrative discourses, content and textual analyses, but also industrial records and practices, marketing campaigns and press releases, archival research and interviews, multimedia synergy, and comparative analysis. For some time, research on Mexican melodrama has had a strong social focus, with several writings about audience engagement, but it is imperative to have more close readings of the texts themselves to understand their cultural context and industrial histories. This research exposes societal changes within Mexico by utilising one of its most omnipresent forms of popular culture and provides a deeper understanding of Mexico’s primary media productions through the use of genre and remake theory. The representations of young women yield a multitude of tensions and ambiguities placed upon Mexican women, which reveal volumes about wider sociocultural expectations.
Num Pages: 20
Keywords: 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Océanie (lieu de production du savoir); 5-Autrice; Australie (lieu de production du savoir); Mexique (corpus analysé); _Nettoyé

Representations of Childhood and “Modes of Address” in Palestinian and Pan-Arab Programs for Children - Awan, Feryal (Children, Youth, and International Television, 2022)
This chapter explores the ways in which the portrayal of children in Palestinian screen content compares with the positioning of children in leading pan-Arab children’s channels. Using critical discourse analysis, it compares the definition and representation of childhood in three Arabic language texts (two magazine shows and one animation), and examines the ways in which the texts construct narratives of childhood and whether they reproduce or challenge hegemonic definitions of childhood. The chapter analyses the language used to address the child audience and the ways in which adult–child relations are depicted. The chapter concludes that while there are some characteristics unique to Palestinian programming, the positioning of children and the “modes of address” are similar in all three programmes, and there are common assumptions and idealizations of childhood. However, there is some evidence that the Emirati animation analysed challenges dominant (adult-generated) definitions of childhood present in Arab societies by presenting childhood as a dynamic space of empowerment
Num Pages: 16
Keywords: 1-TV; 2-Approches sociologiques; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Europe (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; Pakistan (corpus analysé); Royaume-Uni (lieu de production du savoir); _Nettoyé

Mexican Genders, Mexican Genres: Cinema, Television, and Streaming Since 2010 - Smith, Paul Julian (Boydell & Brewer, 2021)
Gender and the contemporary audio-visual landscape of Mexico.
Keywords: 1-Cinéma; 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); Mexique (corpus analysé); _Nettoyé; États-Unis (lieu de production du savoir)

Mexican genders, Mexican genres: cinema, television, and streaming since 2010 - Smith, Paul Julian (Tamesis Books, 2021)

The Evolution of Black Women in Television: Mammies, Matriarchs and Mistresses - Cheers, Imani M. (Routledge, 2017)
This book seeks to interrogate the representation of Black women in television. Cheers explores how the increase of Black women in media ownership and creative executive roles (producers, showrunners, directors and writers) in the last 30 years affected the fundamental cultural shift in Black women’s representation on television, which in turn parallels the political, social, economic and cultural advancements of Black women in America from 1950 to 2016. She also examines Black women as a diverse television audience, discussing how they interact and respond to the constantly evolving television representation of their image and likeness, looking specifically at how social media is used as a tool of audience engagement.
Keywords: 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude de la réception; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; _Nettoyé; États-Unis (corpus analysé); États-Unis (lieu de production du savoir)

Television Drama in Spain and Latin America : Genre and Format Translation - Julian Smith, Paul (Institute of Modern Languages Research, 2020)
Television Drama in Spain and Latin America addresses two major topics within current cultural, media, and television studies: the question of fictional genres and that of transnational circulation. While much research has been carried out on both TV formats and remakes in the English-speaking world, almost nothing has been published on the huge and dynamic Spanish-speaking sector. This book discusses and analyses series since 2000 from Spain (in both Spanish and Catalan), Mexico, Venezuela, and (to a lesser extent) the US, employing both empirical research on production and distribution and textual analysis of content. The three genres examined are horror, biographical series, and sports-themed dramas; the three examples of format remakes are of a period mystery (Spain, Mexico), a romantic comedy (Venezuela, US), and a historical epic (Catalonia, Spain). Paul Julian Smith is Distinguished Professor at the Graduate Center, City University of New York. He was previously Professor of Spanish at the University of Cambridge. He is the author of twenty books and one hundred academic articles.
Accepted: 2022-06-02T04:31:38Z Journal Abbreviation: Genre and Format Translation
Keywords: 1-TV; 2-Analyses formalistes; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 3-Europe (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); Espagne (corpus analysé); Mexique (corpus analysé); Venezuela (corpus analysé); _Nettoyé; États-Unis (corpus analysé); États-Unis (lieu de production du savoir)

Television and Dating in Contemporary China: Identities, Love and Intimacy - Yang, Chao (Palgrave Macmillan Singapore, 2017)
"This book considers the changing nature of intimacy in contemporary China, providing a unique case study of romantic subjectivities in young people in the world's fastest growing economy. Since the implementation of reform in 1978, the economic and socio-cultural environment of modern China has experienced a dramatic transformation under the influence of urbanization and globalization, facilitating more individualized identity among Chinese youth. This book bridges the gap between an emergent emphasis on individualisation and the country's traditional norms and values. It focuses on young people's understandings of various forms of relationships such as cohabitation, extramarital relationships and multiple relationships, suggesting a challenge to traditional familial values and an increasingly diversified understanding of the concepts of love and romance. By examining the formation of relationships among 21st century Chinese youth, notably through the lens of popular Chinese TV dating programs, this book considers how dating and relationships mirror China's changing societal structure and examines social and cultural transformations in Chinese society."
Keywords: 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude de la réception; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; Chine (corpus analysé); Chine (lieu de production du savoir); _Nettoyé

Globalization and Television: A Study of the Indian Experience, 1990-2010 - Narayan, Sunetra Sen (Oxford University Press, 2013)
This study explores the globalization and liberalization that has occurred in Indian television over the two decades starting from 1990.
Keywords: 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; Inde (corpus analysé); Inde (lieu de production du savoir); _Nettoyé

Cultural Economy and Television in Jamaica and Ghana: #decolonization2point0 - Hickling Gordon, Deborah (Palgrave Pivot, 2020)
This book proposes contemporary decolonization as an approach to developing cultural economies in the Global South. This book represents the first critical examination and comparison of cultural and creative industries (CCI) and economy concepts in the Caribbean and Africa.
Keywords: 1-TV; 2-Approches sociologiques; 2-Méthodologie de recherche décoloniale; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude de la réception; 2-Étude des industries culturelles; 3-Afrique (corpus analysé); 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; Ghana (corpus analysé); Jamaïque (corpus analysé); Jamaïque (lieu de production du savoir); _Nettoyé

Transnational Latin American Television: Genres, Formats and Adaptations - Ribke, Nahuel (Routledge, 2020)
This book examines the process of transnationalization of Latin American television industries. Drawing upon six representative case studies spanning the subcontinent’s vast and diverse geo-political and cultural landscape, the book offers a unique exploration of the ongoing formation of interrelated cultural, technological, and political landscapes, from the mid-1980s to the present. The chapters analyse the international circulation of the genres and formats of entertainment television across the subcontinent to explore the main driving forces propelling the production and consumption of television contents in the region, and what we can learn about the cultural and social identities of Latin American audiences following the journey of genres, formats, and media personalities beyond their own national borders. Taking a contemporary interdisciplinary approach to the study of transnational television industries, this book will be of significant interest to scholars and students of television and film studies, communication studies, Latin American studies, global media studies, and media and cultural industries.
Keywords: 1-TV; 2-Analyses formalistes; 2-Approches sociologiques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude de la réception; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Sud (corpus analysé); 4-Asie (lieu de production du savoir); Israël (lieu de production du savoir); _Nettoyé

Bridal Anxieties: Politics of Gender, Neoconservatism and Daytime TV in Turkey - Sayan-Cengiz, Feyda (Female Agencies and Subjectivities in Film and Television, 2020)
This chapter analyzes the reflections of Turkey’s neoconservative and neoliberal politics of gender on daytime television. The focus is on Bridal House, a popular daytime TV show in Turkey which interpellates women as domestic subjects competing with other women to prove their domestic abilities, particularly the ability to navigate the etiquette of domestic consumption. Hierarchies are instigated among women through symbolic battles on “tasteful” consumption, and the marital household surfaces as a space of constant regulation where women strive to be ideal housewives. By analyzing Bridal House through a Bourdieusian framework, this chapter traces the representations of the “ideal female subject” along neoconservative and neoliberal lines, and demonstrates the ways in which symbolic violences are enacted on women in contemporary Turkey’s daytime TV culture.
Keywords: 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude des représentations; 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; Turquie (corpus analysé); Turquie (lieu de production du savoir); _Nettoyé

Television in Post-Reform Vietnam: Nation, Media, Market - Nguyen-Thu, Giang (Routledge, 2018)
This book explores Vietnamese popular television in the post-Reform era, that is, from 1986, focussing on the relationship between television and national imagination. It locates Vietnamese television in the experiences of everyday life and the prevailing network of power relations resulting from marketization and globalization, and, as such, moves beyond the clichéd assumption of Vietnamese media as a mere propagandist instrument of the party state. With examples from a wide range of television genres, the book demonstrates how Vietnamese television enables novel conditions of cultural oppression as well as political engagement in the name of the nation. In sharp contrast to the previous image of Vietnam as a war-torn land, post-Reform television conjures into being a new sense of national belonging based on an implicit rejection of the socialist past, hopes for peace and prosperity, and anxieties about a globalized future. This book highlights the richness of Vietnam’s current culture and identity, characterized, the book argues, by ‘fraternity without uniformity’.
Keywords: 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Océanie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; 5-Identités diasporiques; Australie (lieu de production du savoir); Vietnam (corpus analysé); _Nettoyé

Dilemmas in Zimbabwe's Public Broadcasting in the Era of Digitisation - Matsilele, Trust; Maunganidze, Golden; Ruhanya, Pedzisai (Television in Africa in the Digital Age, 2021)
This chapter makes an empirical contribution to challenges the developing economies, often referred to as the global south, face when it comes to digital migration. This challenge has citizens of what were previously regarded as ‘third world countries’ having to rely on predominantly state and to a limited extent, public broadcast media for current news and information. This contribution, in making a seminal contribution on digitisation in Zimbabwe, demonstrates the challenges the country faces as to allow citizens access to more diversity and not just plurality. Conceptually, digitisation is deﬁned as the conversion of analogue content and production processes into digital format (Manzuch 2009). Seabright and Weeds (2007, 1) observe that digitisation has to do with ‘replacing analogue signals with digital format economises on processing, storage and transmission capacity, reducing costs and expanding capabilities’. Seabright and Weeds (2007) submit that moving from analogue to a digital space brings changes in digital recording and production techniques, digital compression in transmission, proliferation in transmission platforms (terrestrial, cable, satellite and broadband); digital set-top boxes and encryption technologies; and digital personal video recorders. These interventions contribute to lowering of costs, improving of picture quality and improving speed in news gathering and dissemination (Koss et al. 2013). Other than the ﬁnancial and technical imperatives that come with digitisation, the transition comes with certain cultural and political implications (Gripsrud 2009).
Keywords: 1-TV; 2-Approches sociologiques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Afrique (corpus analysé); 4-Afrique (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; Afrique du Sud (lieu de production du savoir); Zimbabwe (corpus analysé); Zimbabwe (lieu de production du savoir); _Nettoyé

Digital Terrestrial Television Broadcasting (DTTB) in Botswana: Prospects and Challenges - Mosanako, Seamogano; Lesitaokana, William O. (Television in Africa in the digital age, 2021)
The year 2015 was set by the International Telecommunication Union (ITU) for most of its member states globally to switch from analogue to digital terrestrial broadcasting. Digital television broadcasting is generally implied as transmission of broadcast content signals in the form of binary data, speciﬁcally 0 s and 1 s. Digitisation of television merges broadcasting, computing and telecommunications to transform both the way television content is made and consumers interact with content (Chalaby and Segell 1999). Referring to digital content, Flew (2004) suggested that digitisation of media and communication content grows “informatisation” of society.
Keywords: 1-TV; 2-Approches sociologiques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude de la réception; 2-Étude des industries culturelles; 3-Afrique (corpus analysé); 4-Afrique (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; Botswana (corpus analysé); Botswana (lieu de production du savoir); _Nettoyé

Chinese State Capitalism and the Transition to Digital Television in Africa - Abikanlu, Femi (Television in Africa in the Digital Age, 2021)
The transition to digital television referred to as the Digital Switchover (DSO) process or Digital Migration is an agreement of member countries of the International Telecommunications Union (ITU) at the Geneva Conference in 2006. The agreement requires changes to national spectrum allocation and redeﬁnes national participation in the global digital television and mobile telephony market. While the decision of most African states to embark on the digital migration programme remains independent, the policies and approach to the implementation were inﬂuenced by two dominant economic orthodoxies, the neoliberal free market (Becchio and Leghissa 2016; Johnson 2011; Overbeek and Apeldoorn 2012; Peters 2011) which promotes a media environment mainly driven by market imperatives and the Chinese State capitalism (Bremmer 2008; Gu et al. 2016; Lyons 2007; Szamosszegi and Kyle 2011; Xing and Shaw 2013) which is the economic ideology that drives the interventions of the Chinese government in the region’s digital migration.
Keywords: 1-TV; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Afrique (corpus analysé); 3-Asie (corpus analysé); 4-Océanie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Identités diasporiques; Chine (corpus analysé); Nigéria (corpus analysé); Nouvelle-Zélande/Aotearoa (lieu de production du savoir); _Nettoyé

Analysing How Zimbabwe Broadcasting Corporation (ZBC TV) and Eswatini TV (ESTV) Are Adapting to the Digital Era - Lunga, Carolyne M.; Musvipwa, Rosemary (Television in Africa in the Digital Age, 2021)
The internet has impacted on how media organisations do journalism. Many media organisations both print and broadcast now have an online presence to reach out to fragmented audiences that have migrated to online platforms. Television stations have increasingly embraced the use of digital (online) media to gain better access to their audiences in terms of content distribution and audience engagement. The rise of social media platforms such as Facebook, Twitter, YouTube and Instagram have given journalists and media organisations the ability to reach their audiences immediately, with the added beneﬁt of audience responses which come almost immediately. The use of new digital media has created platforms for news stations to share digital clips of news items or excerpts of news programmes to keep the audiences informed or enticed by the highlights.
Keywords: 1-TV; 2-Approches sociologiques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Afrique (corpus analysé); 4-Afrique (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; Eswatini (corpus analysé); Eswatini (lieu de production du savoir); Royaume-Uni (lieu de production du savoir); Zimbabwe (corpus analysé); _Nettoyé

Digitization of Television in Kenya: Changing Trends in Content and Consumption - Murunga, Protus; Diang'a, Rachael (Television in Africa in the Digital Age, 2021)
The purpose of this chapter is to examine how the digitization of television has impacted the architecture of television content generation, dissemination consumption in Kenya. Its key motivation is to answer two main questions: How has the digitization shift in Kenya’s television impacted the trends in production, dissemination, reception and consumption of television content; what is the effect of digitization on viewer satisfaction; and how has this shift transformed the role of television medium in the country? The chapter, therefore, answers these questions focusing on the television channels under study, namely, Citizen TV, Kenya Broadcasting Corporation (KBC) and Nation TV (NTV).
Keywords: 1-TV; 2-Approches sociologiques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Afrique (corpus analysé); 4-Afrique (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; Kenya (corpus analysé); Kenya (lieu de production du savoir); _Nettoyé

Exodus, Access and Inequalities: The Impact of Digital Migration in the Least Developed Countries of Africa - Motsaathebe, Gilbert; Chiumbu, Sarah H. (Television in Africa in the Digital Age, 2021)
There has been a hype regarding the beneﬁts of digital migration, which refers to switchover from analogue to digital broadcasting. Commonly referred to as digital migration, the switchover emanates from a decision made at the International Telecommunications Union (ITU) in 2006 to release a valuable spectrum, which can be used for other services. Other beneﬁts of digital TV include good sound and picture quality and availability of more channels giving viewers more choice. It has also been said that digital broadcasting will save the broadcasting stations’ cost, as transmitting content via digital platforms is less costly than transmitting via the analogue platform (Muthomi 2012). This implies that media houses can capitalise on this migration as a competitive advantage. Countries across the world have been undergoing this necessary switchover from analogue to digital platforms, with varying degree of success. While the merits of digital television are clear, it is not clear how this digitisation will realistically help in bridging habitual inequalities in developing countries.
Keywords: 1-TV; 2-Approches sociologiques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Afrique (corpus analysé); 4-Afrique (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; Afrique du Sud (lieu de production du savoir); _Nettoyé

Persuasion Across Platforms: A Rhetorical Analysis of Televised and Digitised News Reports on Economic Matters - Nkoala, Sisanda (Television in Africa in the Digital Age, 2021)
Audiovisual news media are compelling texts to study when it comes to how mass media shapes an audience’s perspective of the world (White 1998). This is due to the pivotal role these forms of media play in creating an informed citizenry as mediums that transmit information from news creators and news sources to the public as a mass audience (McQuail 1987). Even more signiﬁcant than this is the function of audiovisual news media as constructors of reality and ideology because of their pervasiveness in society (McLuhan and Fiore 1967; Hughes 1942). The advent of digital media has been touted as a means of diluting the inﬂuence of traditional mass media formats, such as television, with digital news media being forecast to take audiences away from these traditional media platforms (Lotz 2014).
Keywords: 1-TV; 2-Approches sociologiques; 2-Étude des industries culturelles; 3-Afrique (corpus analysé); 4-Afrique (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; Afrique du Sud (corpus analysé); Afrique du Sud (lieu de production du savoir); _Nettoyé

"Strike Fear in the Heart of the White Men": Hate Language on Digital Television-The Case of ZBC Television Online News - Munoriyarwa, Allen; Karombo, Stanley (Television in Africa in the Digital Age, 2021)
This chapter explores the extent to which Zimbabwe’s single public service television station (as of 2019), ZBC, employed hate language on its online news broadcasts during the 2008 presidential rerun election. Anchored on discourse theory and utilising discourse analysis, this chapter explores hate discourses on Zimbabwe’s online television news during the 2008 election. It seeks to answer the question: To what extent did the Zimbabwe Broadcasting Corporation Television (ZBC TV) online news rhetoric constitute hate discourses?
Keywords: 1-TV; 2-Approches sociologiques; 2-Étude des industries culturelles; 3-Afrique (corpus analysé); 4-Afrique (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; Afrique du Sud (lieu de production du savoir); Zimbabwe (corpus analysé); _Nettoyé

Culturaly Refigured: Assimilating Oedipus Rex into the Yoruba Mythical Universe Through Television Adaptation Processes - Ige, Segun (Television in Africa in the Digital Age, 2021)
Colonisation bequeathed classical education, among others, to the African continent. The post-colonial utility, function and status of such a knowledge system have been questioned and resisted, and African knowledgebased institutions are making efforts to decolonise such systems. The decolonial project has also impacted popular culture in the sense that African identity and self-presentation are being interrogated using various methods. Adaptations and productions of classical myths are implicated in this discourse. Implicated adaptations serve as platforms for allegorical cross-cultural conversation on shared experiences of a people group, perhaps of an earlier generation with the assumption of partial or absolute continuities. Continuity discourse is problematic when two cultures are implicated, particularly, when one is a colonial culture and the other colonised. The unity of discourse is either afﬁrmed, violated or reconstituted.
Keywords: 1-TV; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Afrique (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; _Nettoyé; États-Unis (lieu de production du savoir)

Digital Disruption in South African Television News - Stos, Susan (Television in Africa in the Digital Age, 2021)
The term digital “disruption” conjures up negative connotations, with implications of disturbance, interference or interruption. Certainly, virtually every aspect of life has been affected by digitisation, but it has been pointed out that it is detrimental “only for those who chose to ignore it or try to ﬁght it” (“Digital Disruption: What Is It?” 2016, para 2). One case in point is the American company Kodak. Where it once dominated the ﬁlm and camera market for most of the twentieth century, the company recently ﬁled for bankruptcy. Kodak’s mistake was continually opposing the digitisation of the industry and failing to read the writing on the wall (“Digital Disruption: What Is It?” 2016). Digitisation is as much a reality of life in the newsroom as it is in the boardroom.
Keywords: 1-TV; 2-Approches sociologiques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Afrique (corpus analysé); 4-Afrique (lieu de production du savoir); 5-Auteur.rice noir.e; 5-Autrice; 5-Créateur.rice PANDC; Afrique du Sud (corpus analysé); Afrique du Sud (lieu de production du savoir); _Nettoyé

Understanding Netflix's Foray into Original Productions in South Africa: A "Jet Plane" and "Helicopter" View - Chambwera, Collen (Television in Africa in the Digital Age, 2021)
Until recently, the South African television industry was dominated by the South African Broadcasting Corporation (SABC), etv, and Multichoice. The SABC and etv are free to air while Multichoice provides a satellite subscription service through its DSTV bouquet. This status quo was broken with the emergence of subscription video on demand (SVOD). While Multichoice launched its SVOD service, Showmax, in 2015, greater disruption happened in January 2016 when the current most successful global company in SVOD, Netﬂix, simultaneously launched in 130 countries including South Africa. The coming of Netﬂix to South Africa was reportedly greeted by excitement as viewers embraced choice of access to premium television entertainment. Considering that prior to this development, Multichoice had had a near monopoly in provision of premium television content through its DSTV and Showmax, the reported excitement came as no surprise.
Keywords: 1-TV; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Afrique (corpus analysé); 4-Afrique (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; Afrique du Sud (corpus analysé); Afrique du Sud (lieu de production du savoir); _Nettoyé

Entertaining Africans: Creative Innovation in the (Internet) Television Space - Dovey, Lindiwe (Television in Africa in the Digital Age, 2021)
Despite great heterogeneity, the vast continent of Africa and the diverse people of its countries and diasporas have often been represented through the most reductive, essentialising, and denigrating paradigms— a process that Nigerian writer Chimamanda Adichie Ngozi has referred to as “the danger of a single story”. One of the most dangerous of these paradigms is the developmentalist one, which shoehorns Africa into a western, capitalist teleological framework that overlooks and denies Africa’s production of and participation in forms of leisure, pleasure and entertainment.
Keywords: 1-TV; 2-Analyses formalistes; 2-Approches sociologiques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude de la réception; 3-Afrique (corpus analysé); 3-Europe (corpus analysé); 4-Europe (lieu de production du savoir); 5-Autrice; 5-Identités diasporiques; Royaume-Uni (corpus analysé); Royaume-Uni (lieu de production du savoir); _Nettoyé

The Little Emperors’ New Toys: A Critical Inquiry into Children and Television in China - Zhao, Bin (Springer, 2013)
Drawing on original research I conducted in the late 1980s, the book argues for a critical approach to the study of children and television. It begins with critical reappraisals of previous empiricist and interpretative studies to set the ground for a different theoretical inquiry which links biography with history. The situated activity of children's television viewing therefore has to be related to the broader historical and cultural formations in post-Mao China. By way of a methodological pluralism of questionnaire survey, in-depth interviews and observation, the book provides the reader with a thorough critical analysis of the rise of the new commercial ethic in Chinese society in general, and in the sector of media and communications in particular, at the very historical turning point of the late 1980s. Soon after that, Deng Xiaoping made his significant tour to south China, reckoning a big step forward towards further liberalization and started to form a brave new world in China ever since.
Keywords: 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude de la réception; 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; Chine (corpus analysé); Chine (lieu de production du savoir); _Nettoyé

The Little Emperors’ New Toys

Pimpin' Ain't Easy: Selling Black Entertainment Television - Smith-Shomade, Beretta E. (Routledge, 2007)
Launched in 1980, cable network Black Entertainment Television (BET) has helped make blackness visible and profitable at levels never seen prior in the TV industry. In 2000, BET was sold by founder Robert L. Johnson, a former cable lobbyist, to media giant Viacom for 2.33 billion dollars. This book explores the legacy of BET: what the network has provided to the larger US television economy, and, more specifically, to its target African-American demographic. The book examines whether the company has fulfilled its stated goals and implied obligation to African-American communities. Has it changed the way African-Americans see themselves and the way others see them? Does the financial success of the network - secured in large part via the proliferation of images deemed offensive and problematic by many black communities - come at the expense of its African-American audience? This book fills a major gap in black television scholarship and should find a sizeable audience in both media studies and African-American studies.
Keywords: 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; _Nettoyé; États-Unis (corpus analysé); États-Unis (lieu de production du savoir)

Chinese Television and Soft Power Communication in Australia - Li, Mei (Anthem Press, 2019)
Chinese Television and Soft Power Communication in Australia discusses China’s soft power communication approach and investigates information handling between China and its targeted audiences in the eyes of key influencers – intermediate elites (public diplomacy policy elites in particular) in China and Australia. It explores CGTN (with staff from several professional cultures) and conducts a systemic test of how successful/unsuccessful China’s soft power message projection is in terms of congruence between projected and received frames as a pivotal factor of its power status. The analysis is based on a case study of frames in the messaging on Chinese international TV about China’s Belt and Road Initiative and in the minds of Australian public diplomacy policy elites. The question raised is whether and how Australia is listening.
Keywords: 1-TV; 2-Approches sociologiques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Asie (corpus analysé); 3-Océanie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Autrice; 5-Créateur.rice PANDC; Australie (corpus analysé); Chine (corpus analysé); Chine (lieu de production du savoir); _Nettoyé

Television in Bangladesh: News and Audiences - Roy, Ratan Kumar (Routledge India, 2020)
This book examines the role of 24/7 television news channels in Bangladesh. By using a multi-sited ethnography of television news media, it showcases the socio-political undercurrents of media practices and the everydayness of TV news in Bangladesh. It discusses a wide gamut of issues such as news making; localised public sphere; audience reaction and viewing culture; impact of rumours and fake news; socio-political conditions; protest mobilization; newsroom politics and perspectives from the ground. An important intervention in the subject, this book will be useful to scholars and researchers of media studies, journalism and mass communication, anthropology, cultural studies, political sociology, political science, sociology, South Asian studies, as well as television professionals, journalists, civil society activists, and those interested in the study of Bangladesh.
Keywords: 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude de la réception; 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; Bangladesh (corpus analysé); Inde (lieu de production du savoir); _Nettoyé

It's Been Beautiful: Soul! and Black Power Television - Wald, Gayle (Duke University Press, 2015)
Soul! was where Stevie Wonder and Earth, Wind & Fire got funky, where Toni Morrison read from her debut novel, where James Baldwin and Nikki Giovanni discussed gender and power, and where Amiri Baraka and Stokely Carmichael enjoyed a sympathetic forum for their radical politics. Broadcast on public television between 1968 and 1973, Soul!, helmed by pioneering producer and frequent host Ellis Haizlip, connected an array of black performers and public figures with a black viewing audience. In It's Been Beautiful, Gayle Wald tells the story of Soul!, casting this influential but overlooked program as a bold and innovative use of television to represent and critically explore black identity, culture, and feeling during a transitional period in the black freedom struggle.
Keywords: 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; _Nettoyé; États-Unis (corpus analysé); États-Unis (lieu de production du savoir)

Producing Domestic Abuse in Pakistani Television: Between Commerce, Ratings and Social Responsibility - Cheema, Munira (Television for Women, 2016)
Before the liberalisation of television in 2000, Pakistan had one terrestrial channel.The Pakistan Television Corporation (commonly known as PTV) had been the statebroadcaster since 1964 and thus PTV content reflected the policies of differentgovernments. Liberal governments relaxed control over gender on screen – womencould be seen without dupatta – while religiously inclined governments brought intheir own agendas with restrictions on appearance of women, such as the dupattapolicy (see, for example, Ali, 1986; Suleman, 1990; Kothari, 2005; Nasir, 2012).1 In2002, the Independent Media Corporation launched its channel Geo News fromPakistan, followed by other networks, marking the formal launch of the policy ofliberalisation of media on television. Presently, five media groups have control of thePakistani media industry, including electronic and print media. These are Inde-pendent Media Corporation, Pakistan Herald Publications, ARY Group, WaqtGroup and Lakson Group (see for example Proffitt and Rasul, 2013). The broad-casting industry in Pakistan follows an advertiser-driven model that is run through asystem of ratings. At the time of the fieldwork reported here (October-April 2011),Media Logic and Gallup were the two operators that determined the popular tastesof consumers through ratings.2
Num Pages: 20
Keywords: 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 5-Auteur.rice PANDC; 5-Autrice; Pakistan (corpus analysé); _Nettoyé

Brown Girls Who don’t Need Saving: Social Media and the Role of ‘Possessive Investment’ in The Mindy Project and The Good Wife - Moorti, Sujata (Television for Women, 2016)
This poignant assertionby acclaimed actor Viola Davis, star of the series How to GetAway with Murder (ABC, 2014-), during her Emmy acceptance speechwent viral and becamethe flashpoint for heated discussion about contemporary television’s representational practices. The statement draws attention to questions of taste, what is acknowledgedby the industry and audiences as quality television and the political economy of thecontemporary industry. This moment in television history, with its attendant socialmedia afterlife, captures the key elements I wish to explore in this chapter: represen-tations of women of colour, production practices and viewer responses. As Viola Davisnotes in the quote above, the contemporary US television landscape offers limited rolesfor people of colour. The few shows starring people of colour have become the focus ofintense social media exchanges. In this chapter, I will explore how televisual womenof colour have become a key site from which viewers assert a possessive investmentof racialised identity. By focusing on social media responses, I delineate the ways inwhich viewers invest symbolic and literal ownership over these representations.Through such a multifaceted examination, this essay aims to elaborate how women ofcolour are accommodated within the concept of television for women, a term inter-rogated in this volume. In addition, I illustrate the ideological instability of the term‘women of colour’ and the capaciousness of the concept ‘television for women’.
Num Pages: 20
Keywords: 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude de la réception; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; 5-Identités diasporiques; _Nettoyé; États-Unis (corpus analysé); États-Unis (lieu de production du savoir)

Shaded Lives: African-American Women and Television - Smith-Shomade, Beretta E. (Rutgers University Press, 2002)
Since its invention, television has been one of the biggest influences on American culture. Through this medium, multiple visions and disparate voices have attempted to stake a place in viewer consumption. Yet even as this programming supposedly reflects characteristics of the general American populace, television-generated images are manipulated and contradictory, predicated by the various economic, political, and cultural forces placed upon it. In Shaded Lives, Beretta Smith-Shomade sets out to dissect images of the African American woman in television from the 1980s. She calls their depiction "binaristic," or split. African American women, although an essential part of television programming today, are still presented as distorted and deviant. By closely examining the television texts of African-American women in comedy, music video, television news and talk shows (Oprah Winfrey is highlighted), Smith-Shomade shows how these voices are represented, what forces may be at work in influencing these images, and what alternate ways of viewing might be available. Smith-Shomade offers critical examples of where the sexist and racist legacy of this country collide with the cultural strength of Black women in visual and real-lived culture. As the nation's climate of heightened racial divisiveness continues to relegate the representation of Black women to depravity and display, her study is not only useful, it is critical.
Keywords: 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; _Nettoyé; États-Unis (corpus analysé); États-Unis (lieu de production du savoir)

Romance in Post-Socialist Chinese Television - Wen, Huike (Palgrave Macmillan, 2020)
"Surveying the latest Chinese TV shows centered on romantic relationships, this book joins the expanding body of literature on the ever-evolving structures of feelings while breaking new grounds in media studies. With its thorough investigation of a wide range of genres, narratives, and public discourses, the volume makes timely and significant contributions to the fields of media studies, China studies, and the cultural history of love and romance."–Hui Faye Xiao, University of Kansas, USA "What does romantic love mean for Chinese people today? How is love represented in popular Chinese television programs? Huike Wens fascinating and important book explores how romantic love promises young Chinese urbanites individual freedom, fulfillment, and purpose in life, yet also plays an ideological role in creating social cohesion and maintaining traditional patriarchal values in post-socialist China. An entertaining and thought-provoking insight into how love functions in contemporary Chinese society." –Hsu-Ming Teo, Macquarie University, Australia This book examines how representations of romantic love in Chinese television programs reflect the contradictions inherent to changing dominant values in post-socialist Chinese mainstream culture. These representations celebrate individual freedom, passion, and gender equality, and promise change based on individual diligence and talent, while simultaneously obstructing the fulfillment of these ideals. Huike Wen is an Associate Professor at Willamette University (Salem, Oregon). Her research focuses on the intersection of genders, emotions, media technology, and nations in transnational Chinese and East Asian media and culture.
Keywords: 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; Chine (corpus analysé); _Nettoyé; États-Unis (lieu de production du savoir)

Black, White, and in Color: Television and Black Civil Rights - Torres, Sasha (Princeton University Press, 2018)
This book examines the representation of blackness on television at the height of the southern civil rights movement and again in the aftermath of the Reagan-Bush years. In the process, it looks carefully at how television's ideological projects with respect to race have supported or conflicted with the industry's incentive to maximize profits or consolidate power. Sasha Torres examines the complex relations between the television industry and the civil rights movement as a knot of overlapping interests. She argues that television coverage of the civil rights movement during 1955-1965 encouraged viewers to identify with black protestors and against white police, including such infamous villains as Birmingham's Bull Connor and Selma's Jim Clark. Torres then argues that television of the 1990s encouraged viewers to identify with police against putatively criminal blacks, even in its dramatizations of police brutality. Torres's pioneering analysis makes distinctive contributions to its fields. It challenges television scholars to consider the historical centrality of race to the constitution of the medium's genres, visual conventions, and industrial structures. And it displaces the analytical focus on stereotypes that has hamstrung assessments of television's depiction of African Americans, concentrating instead on the ways in which African Americans and their political collectives have actively shaped that depiction to advance civil rights causes. This book also challenges African American studies to pay closer and better attention to television's ongoing role in the organization and disorganization of U.S. racial politics.
Keywords: 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Méthodologie de recherche décoloniale; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; _Nettoyé; États-Unis (corpus analysé); États-Unis (lieu de production du savoir)

Black in the British Frame: The Black Experience in British Film and Television - Bourne, Stephen (Bloomsbury Publishing Plc, 2005)
In this updated edition of his acclaimed and award-winning study, Stephen Bourne takes a personal look at the history of black people in popular British film and television. He documents, from original research and interviews, the experiences and representations which have been ignored in previous media books about people of African descent. There are chapters about Paul Robeson, Newton I. Aduaka, soap operas and much more - as well as several useful appendices and suggestions for further reading.
Keywords: 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Étude de la réception; 2-Étude des représentations; 3-Europe (corpus analysé); 4-Europe (lieu de production du savoir); Royaume-Uni (corpus analysé); Royaume-Uni (lieu de production du savoir); _Nettoyé

The Impact of Watching Violent Television Programs on Secondary School Children in Tanzania - Masiba, Watson Lupogo; Kyando, Newton M. (Wipf and Stock Publishers, 2016)
Violent television programs are highly preferred by children. They stimulate their emotions and increase curiosity about violence-related issues. This means that watching violent television programs has an impact upon their way of perceiving the world around them and acting in response to it. This study investigated the impacts of watching violent television programs on secondary school children in Tanzania. The specific objectives were: to examine children's accessibility to the TV, ascertain the types of violent TV programs and the time children spend watching them, determine the ways in which watching violent TV programs affects their academic performance, find out the impact of watching violent TV programs on their discipline, and examine the role of parents in addressing the impacts of watching violent TV programs upon their children. Results indicate that most secondary school children watch violent TV programs at home in the sitting rooms. They spend an average of three hours per day on weekdays, and seven-and-half hours on weekends, watching movies, music, drama, and informational programs that were identified as the most violent ones. Obviously, spending lots of time watching violent TV programs decreases children's academic performance and discipline. This book is important because it discusses the parents' role in discouraging and limiting children from watching violent TV programs, and choosing appropriate TV programs for them.
Keywords: 1-TV; 2-Approches sociologiques; 2-Étude de la réception; 3-Afrique (corpus analysé); 4-Afrique (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; Tanzanie (corpus analysé); Tanzanie (lieu de production du savoir); _Nettoyé

Television and the Modernization Ideal in 1980s China: Dazzling the Eyes - Wen, Huike (Lexington Books, 2013)
Television and the Modernization Ideal in 1980s China: Dazzling the Eyes explores Chinese television history in the pivotal decade of the 1980s and explains the intellectual reception of television in China during this time. While the Chinese media has often been a topic within studies of globalization and the global political economy, scholarly attention to the history of Chinese television requires a more extensive and critical view of the interaction between television and culture. Using theories of media technology, globalization, and gender studies supplemented by Chinese periodicals including Life Out of 8 Hours, Popular TV, Popular Cinema, Modern Family, and Chinese Advertising, as well as oral history interviews, this book re-examines how Western technology was introduced to and embedded into Chinese culture. Wen compares and analyzes television dramas produced in China and imported from other nations while examining the interaction between various ideologies of Chinese society and those of the international media. Moreover, she explores how the hybridity between Western television culture and Chinese traditions were represented in popular Chinese visual media, specifically the confusions and ambitions of modernization and the negotiation between tradition and modernity, nationalism and internationalism, in the intellectual reception of television in China.
Keywords: 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; Chine (corpus analysé); _Nettoyé; États-Unis (lieu de production du savoir)

Dramatized Societies: Quality Television in Spain and Mexico - Smith, Paul Julian (Liverpool University Press, 2016)
Over the last decade Spain and Mexico have both produced an extraordinary wealth of television drama. Drawing on both national practices of production and reception and international theories of textual analysis this book offers the first study of contemporary quality TV drama in two countries where television has displaced cinema as the creative medium that shapes the national narrative. As dramatized societies, Spain and Mexico are thus at once reflected and refracted by the new series on the small screen.
Keywords: 1-TV; 2-Approches sociologiques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Amérique du Nord (corpus analysé); 3-Europe (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); Espagne (corpus analysé); Mexique (corpus analysé); _Nettoyé; États-Unis (lieu de production du savoir)

Defining the Nation?: Lebanese Television and Political Elites (1990–2005) - Nötzold, Katharina (Frank & Timme, 2013)
Katharina Nötzold explores whether and how mass media can contribute to nation-building after civil war. Drawing on the example of Lebanon’s audiovisual media organisations, which are mostly privately owned by politicians, she demonstrates how political elites use television to transmit their visions of post-war society. Lebanon’s nation-building process from 1990 to 2005 was characterized by Syrian dominance over political life. From an extensive content analysis of Lebanese news and interviews with analysts, journalists and managers from all Lebanese TV stations, it emerges that political information on television focused more on divisive experiences than cohesive ones. This has underpinned continued sectarianism in Lebanon, in the media as in society at large, and has impeded nation-building. Biographische Informationen Katharina Nötzold is a political scientist and RCUK Research Fellow at the University of Westminster's Arab Media Centre, and she completed her PhD in Media and Communications at the University of Erfurt, Germany. She lived in Beirut and Amman and worked previously for the Center for International Peace Operations, Berlin. She is editor of Westminster Papers in Communication and Culture and author of articles on Arab media and media representations of migrants and Islam. Reihe Medien und politische Kommunikation – Naher Osten und islamische Welt - Band 19
Keywords: 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Europe (lieu de production du savoir); 5-Autrice; Allemagne (lieu de production du savoir); Liban (corpus analysé); _Nettoyé

Real Housewives or Real Lies? New Constructions of "Housewives" on The Real Housewives of Atlanta - Shorter, Shavonne R. (Black Women's Portrayals on Reality Television: The New Sapphire, 2016)
An old adage prescribed that “art imitates life.” If one believes this to be true, then it is plausible that entertainment is a source from which information about everyday life can be gleaned? Can U.S. television shows provide a looking glass into how Americans perform certain aspects of their lives? For a “real” look into how careers are performed, I have examined content from a reality television show which bears a title that implies something about the cast— the Bravo Network’s Real Housewives of Atlanta series. This show was chosen for two reasons. First, The Real Housewives of Atlanta is the most popular show among the “Housewives” franchise. Thus with each airing of the show, those who watch have the opportunity to learn more about the career aspirations, roles, and behaviors, of the cast members. Second, this is the only show within The Real Housewives franchise that features a primarily black cast. As such, the question emerges— can this show provide insight into the way black women construct their career roles? Another goal of this study is to determine how cast members construct notions of housewifery. Hence, throughout this chapter, readers will see that these women are not the typical “housewives,” rather they have reinvented what it means to be a housewife in the modern age.
Keywords: 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; _Nettoyé; États-Unis (corpus analysé); États-Unis (lieu de production du savoir)

The "Down Ass Bitch" in the Reality Television Show Love and Hip Hop: The Image of the Enduring Black Women and Her Unwavering Support of the Black Man - Alameen-Shavers, Antwanisha (Black Women's Portrayals on Reality Television: The New Sapphire, 2016)
Within Spoken Soul, better known as Ebonics, the term down can be used as an adjective to describe a person that willingly yields a tremendous amount of support to another person. The “Down Ass Bitch” (DAB) is a controlling image of the black woman that calls for her unwavering support of the black man, even when it is pernicious to her best interest. In fact, we can see this in the black community on many levels: (1) from black women faithfully waiting years for men to be released from prison; (2) hiding domestic abuse or rape at the hands of black men for the sake of protecting the race; or (3) sexually exploiting our bodies for the financial benefit of black men. However, what is most interesting about this particular stereotype of the black woman being “down” for her man is that this is not an expectation that is asked of the black man. It is this author’s contention that the “Down Ass Bitch” is obsequious to the powers of black men— though she is portrayed as being strong, aggressive, and assertive. Essentially, the “Down Ass Bitch,” a highly celebrated image in the black community, is the black version of the submissive white woman, the Eurocentric construction of the idealized womanhood. Various controlling images of black womanhood— such as the mammy, the jezebel, and the welfare queen— served as justifications for the oppression of black women and have been discussed significantly by scholars.
Keywords: 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; _Nettoyé; États-Unis (corpus analysé); États-Unis (lieu de production du savoir)

Dehumanized and Empowered? Black Women, Reality Television, and Love and Hip Hop Atlanta - Bennett, Patrick; Griffin, Rachel Alicia (Black Women's Portrayals on Reality Television: The New Sapphire, 2016)
In recent years, scripted television has been joined by a more “realistic” look into peoples’ lives— reality television. Reality television claims to give viewers an unmediated glimpse into how real people live. The “realness” of reality television invokes controversy by providing a voyeuristic and potentially exploitive look into people’s lives. As the genre has matured, shows that offer insight into communities that are systemically underrepresented have become common. Indicative of this trend are shows that depict the lives of African Americans and opportunistically exploit representations of black culture for drama, ratings, and profit. One network that has taken considerable advantage of this is VH1— first, with the success of Flavor of Love and its spinoffs, then more recently with shows such as Basketball Wives and Love and Hip Hop. In fact, the excessive amount of fighting among Black women on Basketball Wives led to a boycott of the show, which prompted creator Shaunie O’Neal to promise less violence in its next season. Akin to Basketball Wives , Love and Hip Hop Atlanta exemplifies the trend of exploiting black culture. As members of the black community, we find ourselves both intrigued and troubled by the implications of the show. Capturing the essence of our paradoxical interpretation of Love and Hip Hop Atlanta — as one of many reality television shows that simultaneously reproduces and challenges negative stereotypes about blackness— are contradictory headlines such as “The 21 Most Ratchet Women of Black Reality TV,” “How Reality TV has Changed our Daughters,” and “Wealthy Reality Stars Humanize Black Women.”
Keywords: 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; _Nettoyé; États-Unis (corpus analysé); États-Unis (lieu de production du savoir)

A Critical Analysis of Black Womahood in NBC's The Apprentice - Griffin Padget, Donyale R.; Allison, Donnetrice C. (Black Women's Portrayals on Reality Television: The New Sapphire, 2016)
Reality programs rose to prominence based on claims that the shows depicted “real life,” but in recent years many shows have come under fire for being anything but “reality.” Orbe (1998) suggests viewers are drawn to such programs based on the notion that they show “real people in everyday interactions,” and there is a certain level of “unpredictability that comes with reality.” However, what has become predictable and potentially problematic, over the past two decades, are the negative stereotypes associated with African American women on these programs. This skewing of reality is particularly significant when we consider the limited opportunities these shows provide viewers to witness the many facets of black womanhood. From the head-bobbing and finger-waving of Alicia Calaway on season two of the hit show Survivor to the on-and-off-air mudslinging between Kenya Moore and NeNe Leakes of Real Housewives of Atlanta fame, black women are portrayed as disloyal, bitchy, lazy, difficult to work with, and a threat to others.
Keywords: 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; _Nettoyé; États-Unis (corpus analysé); États-Unis (lieu de production du savoir)

The "Tyra Tyrade": Reinforcing the Sapphire Through Online Parody - Patton, Tracey Owens; Snyder-Yuly, Julie (Black Women's Portrayals on Reality Television: The New Sapphire, 2016)
Tyra Banks, supermodel and producer, is the creator of the reality show America’s Next Top Model ( ANTM ), which is now in its twenty-second cycle, and features contestants who present themselves to a panel of judges for modeling critique. ANTM has been nominated for twenty-nine awards, including the GLAAD Media Award and Image Award, and the show has received five awards in 2009 from the Teen Choice Award and the Director’s Guild of America Award. Further, ANTM is currently shown in over 120 countries. The winner of each cycle receives a featured spread in a magazine, a modeling contract with a prominent agency, and a $100,000 modeling contract from a cosmetics company. In 2005, however, there was an infamous episode— dubbed the “Tyra Tyrade,” —where Tyra Banks yelled at a contestant whom she had just eliminated from the show. This episode was parodied more than any other ANTM episode, with the penultimate parody shown on a 2007 episode of Family Guy (a primetime cartoon television show with millions of viewers each week), where Tyra turns into a lizard and eats the model. While this episode is now nine years old, parodies from as recently as 2014 continue to live on and, as we argue, perpetuate negative stereotypes of black womanhood, particularly as related to the Sapphire mediated stereotype— loud, bossy, angry black woman. From the various interpretations of the “Tyra Tyrade,” it is clear that those who created the parodies covertly and overtly ventured into maintaining white supremacist stereotypes of black womanhood— where one is supposed to be beautiful, a jezebel, or a mammy, but not a Sapphire. Continuing the marginalizing mediated tradition, in almost every parody, the Tyra character becomes the object of ridicule for being “excessively black” and outside the parameters of her hegemonically prescribed role, because she demonstrated negative emotions resulting in an assertion of her power as the expert.
Keywords: 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; _Nettoyé; États-Unis (corpus analysé); États-Unis (lieu de production du savoir)

Is She Strong or Just a B!@*#? Discussion of Black Women's Anger in the Reality Show Bad Girls Club - Goldman, Adria Y. (Black Women's Portrayals on Reality Television: The New Sapphire, 2016)
It is near impossible to have a discussion of black women in reality television without mentioning the infamous Angry Black Woman (ABW). In fact, some critiques have argued reality television is damaging for black women since many shows focus heavily on this character. 1 This stereotypical characterization of black women is long-standing, due largely to its constant inclusion in media messages. As noted in chapter one, audiences were first officially introduced to her in the 1920s as Sapphire Stevens from the Amos ‘n’ Andy Show ; and her character continued to resurface throughout the years, across several different genres. Despite the many time periods through which this image has traveled, the key characteristic of the Sapphire— her unexplainable anger and aggression— seem to resonate in many modern day images of black women.
Keywords: 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; _Nettoyé; États-Unis (corpus analysé); États-Unis (lieu de production du savoir)

Can't Have It All: An Analysis of Black Motherhood on Reality Television - Alford, Allison M.; Maxwell, Madeline M.; Jones, Ryessia D.; Morris, Angelica N. (Black Women's Portrayals on Reality Television: The New Sapphire, 2016)
In this chapter we analyze three reality TV (RTV) shows whose main characters do not fit the old movie stereotypes of dark-skinned maternal Mammies, bossy, brown Sapphires or light-skinned sexy Jezebels. Many RTV shows with black cast members are falling back on such stereotypical representations. In contrast, the female characters we analyze are smart and sophisticated, and they live in multi-racial environments. Hence, the primary mediarelated question we address concerns how one slice of black motherhood is represented. The social question we address concerns the extent to which the character presentations actually point to social progress, with diverse symbols and meaning making of real life, or are they as artificial and stereotypical— perhaps in new ways— as the old portrayals?
Keywords: 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; _Nettoyé; États-Unis (corpus analysé); États-Unis (lieu de production du savoir)

Are Black Women Loud? Neoliberal and Postfeminist Protagonists in OWN's Televisual Sphere - Briceño, Mia E.; Estwick, Evene (Black Women's Portrayals on Reality Television: The New Sapphire, 2016)
Jones’ comments reflect a general consensus among TV critics and viewers that: 1) the black women who command the most attention on reality television tend to portray stereotypical, Sapphire-like characters; 2) as audiences consume such portrayals, there is a consistent line of argument from producers that insists “pitting [black women] against each other” is expected or “what the people want;” and 3) black female reality TV stars are willing to indulge the Sapphire fantasy if it means they will be able to further a personal and/or professional agenda. These are important themes to interrogate, especially given the history of mass mediated representations of black Americans, as well as the present-day “evolution” of black characters and other characters of color on unscripted and scripted American television. However, because attention is primarily focused on arguably “negative” portrayals, there has not been much critical analysis of “alternative” or more nuanced portrayals of black women in the televisual sphere. This chapter represents an attempt to fill in some of that blank space by focusing attention on an underexplored and relatively new consortium of reality television programming that features black women who are defined by their roles as mothers and entrepreneurs.
Keywords: 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; _Nettoyé; États-Unis (corpus analysé); États-Unis (lieu de production du savoir)

From 1990s Girl to Hip-Hop Wife: An Analysis of the Portrayal of Tiny as Black Mother in Reality Television - Jones, Ryessia D.; Jones, Johnny; Smith, Siobhan E. (Black Women's Portrayals on Reality Television: The New Sapphire, 2016)
Although African-American women are still underrepresented in narrative television, reality television appears to be a site where one can find many portrayals of them. As other scholars have explained, the representations of African American women in reality television are usually negative, generally presenting them as loud, angry, and without “class.” However, there has been little research on the complicated relationships of black motherhood, black wifehood, and their portrayals on reality television. One black mother who illustrates this tense interaction is Tameka “Tiny” Harris, nee Cottle, formerly of the 1990s girl group Xscape, and star of two reality television programs— BET’s Tiny & Toya , and VH1’s T.I. and Tiny: The Family Hustle . Though both programs prominently feature Cottle, BET’s program constructs Tiny as an emotionally strong and pragmatically capable business woman who maintains the emotional health and financial stability of her family while her relational partner/husband, rapper Tip “T.I.” Harris, is serving time in prison. However, upon T.I.’s return home, The Family Hustle presents Tiny as having little business savvy and as overly permissive with their blended family. This is a dangerous portrayal, given that reality TV purports to disseminate some version of “reality” to its viewers.
Keywords: 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; _Nettoyé; États-Unis (corpus analysé); États-Unis (lieu de production du savoir)

The God in Me: Faith, Reality TV, and Black Women - Egwu, Chetachi A. (Black Women's Portrayals on Reality Television: The New Sapphire, 2016)
The display of spirituality, faith and religion is not a new phenomenon among black women in the United States, nor is it new to the world of media. Africans came to the Americas with their own sense of spirituality and religion, and the awareness of a higher being became the mortar that bound the community together during the trials of enslavement and subsequent oppression. Not surprisingly, this legacy of worship continues to provide solace and strength, with black women at the helm.
Keywords: 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice noir.e; 5-Autrice; 5-Créateur.rice PANDC; 5-Identités diasporiques; _Nettoyé; États-Unis (corpus analysé); États-Unis (lieu de production du savoir)

High Tea, Church Hats, Pastor Wives, and Friendships: A Critical Race Feminism Analysis of Black Women in Preachers of L.A. - Whittington Cooper, Elizabeth (Black Women's Portrayals on Reality Television: The New Sapphire, 2016)
The premise of the show revolves around six preachers in the Los Angeles area. They each pastor churches ranging from 3,500– 4,000 members; however, one pastor’s church has nearly 20,000 members (season 1: episode 1). A multitude of cameras follow the stories of each of the pastors’ lives, their relationships with each other, as well as their wives relationships with one another. The show has five black male preachers and one white male preacher. In season 1, all of the pastors— except for two— are married; one of the unmarried pastors is engaged to the mother of his child, and the other has a long-standing relationship with a female friend who frequently appears on the show. As viewers watch the show, they are given a glimpse into the world of evangelical preachers. Although at first glance the show seems to only focus on the men, the women provide an interesting glimpse at what it means to be a preacher’s wife, fiancée, or female companion. There were a total of eight episodes that aired over the course of two months. This chapter explores how black women and their friendships are portrayed on Preachers of L.A. — including the one white woman on the show. It also examines their discourse between one another— using critical race feminism to analyze the roles of these women as first ladies (a term used to describe the wives of pastors), their relationship with one other, and the conversations they have surrounding sex, marriage, relationships, and friendships. The chapter focuses on the first season of the show, which began in the fall of 2013. The show was later renewed for a second season, which began airing late summer 2014. This critique attempts to bring awareness to black women in the church and the discourse that perpetuates the stereotypes of black women on television. It also aims to initiate further conversations on various stereotypes— regardless of context— that have the potential to bear negatively on black women.
Keywords: 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice noir.e; 5-Autrice; 5-Créateur.rice PANDC; _Nettoyé; États-Unis (corpus analysé); États-Unis (lieu de production du savoir)

Black Women's Portrayals on Reality Television: The New Sapphire - Allison, Donnetrice C.; Jones, Johnny; Alameen-Shavers, Antwanisha; Alford, Allison M.; Bennett, Patrick; Briceño, Mia E.; Egwu, Chetachi A.; Estwick, Evene; Goldman, Adria Y.; Griffin, Rachel Alicia (Lexington Books, 2016)

Making of Exile Culture: Iranian Television in Los Angeles - Naficy, Hamid (University of Minnesota Press, 1993)
Naficy explores the seemingly contradictory way in which immigrant media and cultural productions serve as the source both of resistance and opposition to the domination by host and home country's social values while simultaneously serving as vehicles for personal and cultural transformation and assimilation of those values.
Keywords: 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Créateur.rice PANDC; Iran (corpus analysé); _Nettoyé; États-Unis (lieu de production du savoir)

Representing Black Britain: Black and Asian Images on Television - Malik, Sarita (SAGE Publications, Limited, 2001)
'One of the most important books on race, representation and politics to come along in a decade' - Henry Giroux, Penn State University Representing Black Britain offers a critical history of Black and Asian representation on British television from the earliest days of broadcasting to the present day.
Keywords: 1-TV; 2-Approches sociologiques; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Europe (corpus analysé); 4-Europe (lieu de production du savoir); 5-Autrice; 5-Créateur.rice PANDC; Royaume-Uni (corpus analysé); Royaume-Uni (lieu de production du savoir); _Nettoyé

China Turned On: Television, Reform and Resistance - Lull, James (Taylor & Francis Group, 2013)
The years following the Cultural Revolution saw the arrival of television as part of China's effort to 'modernize' and open up to the West. Endorsed by the Deng Xiaoping regime as a 'bridge' between government and the people, television became at once the official mouthpiece of the Communist Party and the most popular form of entertainment for Chinese people living in the cities. But the authorities failed to realize the unmatched cultural power of television to inspire resistance to official ideologies, expectations, and lifestyles. The presence of television in the homes of the urban Chinese strikingly broadened the cultural and political awareness of its audience and provoked the people to imagine better ways of living as individuals, families, and as a nation. Originally published in 1991, set within the framework of China's political and economic environment in the modernization period, this insightful analysis is based on ethnographic data collected in China before and after the Tiananmen Square disaster. From interviews with leading Chinese television executives and nearly one hundred families in Beijing, Shanghai, Guangzhou, and Xian, the author outlays how Chinese television fosters opposition to the government through the work routines of media professionals, television imagery, and the role of critical, active audience members.
Keywords: 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude de la réception; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); Chine (corpus analysé); _Nettoyé; États-Unis (lieu de production du savoir)

Queering/Quaring Blackness in Noah’s Arc - Yep, Gust A.; Elia, John P. (Queer Popular Culture: Literature, Media, Film, and Television, 2007)
This chapter provides a description and critical analysis of Noah’s Arc , a Logo cable television series featuring a predominantly African American gay male cast. Queer theory and quare studies are used as theoretical tools to examine the conceptions of blackness in general, as well as representations of blackness in Noah’s Arc . Thereafter this chapter turns to an analysis of the representations in this series to illustrate how Noah’s Arc not only queers and quares notions of authentic blackness but also serves to expand various notions of blackness. Finally, this chapter provides a treatment of how whiteness and heteronormativity are implicated in this recent iteration of a racialized queer visibility in popular culture.
Keywords: 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé; États-Unis (corpus analysé); États-Unis (lieu de production du savoir)

Queer Popular Culture: Literature, Media, Film, and Television - Peele, T. (Palgrave Macmillan US, 2007)

The A to Z of African-American Television - Fearn-Banks, Kathleen (Scarecrow Press, 2009)
From Amos 'n' Andy to The Jeffersons to Family Matters to Chappelle's Show, this volume covers it all with entries on all different genres_animation, documentaries, sitcoms, sports, talk shows, and variety shows_and performers such as Muhammad Ali, Louis Armstrong, Bill Cosby, and Oprah Winfrey. Additionally, information can be found on general issues, ranging from African American audiences and stereotypes through the related networks and organizations. This book has hundreds of cross-referenced entries, from A to Z, in the dictionary and a list of acronyms with their corresponding definitions. The extensive chronology shows who did what and when and the introduction traces the often difficult circumstances African American performers faced compared to the more satisfactory present situation. Finally, the bibliography is useful to those readers who want to know more about specific topics or persons.
Keywords: 1-TV; 2-Histoire/Historiographie critique; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; _Nettoyé; États-Unis (corpus analysé); États-Unis (lieu de production du savoir)

Broadcasting Politics in Japan: NHK and Television News - Krauss, Ellis S. (Cornell University Press, 2018)
The aftermath of Japan's 1945 military defeat left its public institutions in a state of deep crisis; virtually every major source of state legitimacy was seriously damaged or wholly remade by the postwar occupation. Between 1960 and 1990, however, these institutions renewed their strength, taking on legitimacy that erased virtually all traces of their postwar instability.How did this transformation come about? This is the question Ellis S. Krauss ponders in Broadcasting Politics in Japan; his answer focuses on the role played by the Japanese mass media and in particular by Japan's national broadcaster, NHK. Since the 1960s, television has been a fixture of the Japanese household, and NHK's TV news has until very recently been the dominant, and most trusted, source of political information for the Japanese citizen. NHK's news style is distinctive among the broadcasting systems of industrialized countries; it emphasizes facts over interpretation and gives unusual priority to coverage of the national bureaucracy. Krauss argues that this approach is not simply a reflection of Japanese culture, but a result of the organization and processes of NHK and their relationship with the state. These factors had profound consequences for the state's postwar re-legitimization, while the commercial networks' recent challenge to NHK has helped engender the wave of cynicism currently faced by the state. Krauss guides the reader through the complex interactions among politics, media organizations, and Japanese journalism to demonstrate how NHK television news became a shaper of Japan's political world, rather than simply a lens through which to view it.
Keywords: 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); Japon (corpus analysé); _Nettoyé; États-Unis (lieu de production du savoir)

The Chinese Television Industry - Keane, Michael (A BFI Book published by Palgrave, 2015)
"Though the television industry in China is enormous, fewer people are watching television screens. In this groundbreaking study, Michael Keene shows how television content is changing, how the Chinese government is responding to the challenges presented by digital media, and how businesses are brokering alliances in both traditional and new media sectors. Keane outlines the process of making content in China, focusing on regulatory institutions, ownership, censorship, programmes and channels, copygright, formats and the role of media bases. Spanning a wide variety of genres, the book examines four models of content internationalisation: licensing of programmes, formats, co-productions and online media. Written in an accessible style by one of the world's leading experts on China's media, this book explores how streamed online content is impacting on the state's control of ideas and management of the traditional broadcasting sector. This is the authoritative text for scholars, students, businesses and policy makers wanting to understand how the rapid evolution of Chinese media aligns with the nation's soft power initiatives"–Back cover.
Keywords: 1-TV; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Océanie (lieu de production du savoir); Australie (lieu de production du savoir); Chine (corpus analysé); _Nettoyé

The Paramilitary Hero on Turkish Television: A Case Study on Valley of the Wolves - Çetin, Berfin Emre (Cambridge Scholars Publisher, 2015)
The Paramilitary Hero on Turkish Television: A Case Study on Valley of the Wolves explores the representation and reception of nationalism and masculinity in Turkey through an examination of the popular television serial, Valley of the Wolves which has been aired on Turkish television since 2003. This detailed examination of the show demonstrates a particular discourse of nationalism, namely the Turkish Islam synthesis embedded in a gender-specific regime in which the paramilitary hero is placed at the centre. The study draws on thirty-seven in-depth interviews with viewers of the programme from different social backgrounds. These viewers read the serial from various perspectives in the light of their gendered experiences, suggesting that the relationship between text and audience is not necessarily predetermined by the former, but is rather constructed through an interdiscursive process. The book also examines the pleasures of the “contesting” readers of Valley of the Wolves, drawing on the audience interviews, and argues that critical approaches to a particular media text do not present a barrier to audience pleasures.
Keywords: 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude de la réception; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; Turquie (corpus analysé); Turquie (lieu de production du savoir); _Nettoyé

Pretty Liar: Television, Language, and Gender in Wartime Lebanon - Khazaal, Natalie (Syracuse University Press, 2018)
"Pretty Liar" explores the rise of language and gender politics on Lebanese television to tell the untold story of the co-evolution of Lebanese television and its audiences and how the civil war of 1975-1991 affected that co-evolution. The shift in public interest in television has been widely acknowledged and interpreted within an institutional context as a victory of the neo-liberal entrepreneurship of a new, agile brand over the government inefficiency of Lebanon's national station, Télé Liban. Yet, the role of the Lebanese Civil War in reshaping national television and broadcasting in Arab media following the emergence of the Lebanese Broadcasting Company in 1985 has been unexplored. Based on empirical data and grounded in theory by Arab and global researchers, "Pretty Liar" offers textual analyses of five Lebanese fictional series, three major and several additional periodicals, and nine literary works, and provides context from unscripted interviews with television administrators, anchors, actors, and freelance contributors, print journalists, and audience members. Khazaal seeks to offer new insight into how entertainment television became a site for politics and political resistance, feminism, and the cradle for post-war Lebanon due to the shift in practices and standards of legitimacy. The history of television in Lebanon is not merely the history of technology and business, Khazaal argues, but rather the history of a people and their continuing quest for a responsive television even during times of civil unrest.
Keywords: 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude de la réception; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; Liban (corpus analysé); _Nettoyé; États-Unis (lieu de production du savoir)

Reimagining Brazilian Television: Luiz Fernando Carvalho's Contemporary Vision - Carter, Eli Lee (University of Pittsburgh Press, 2018)
The Brazilian television industry is one of the most productive and commercially successful in the world. At the forefront of this industry is TV Globo and its production of standardized telenovelas, which millions of Brazilians and viewers from over 130 countries watch nightly. Eli Lee Carter examines the field of television production by focusing on the work of one of Brazil's greatest living directors, Luiz Fernando Carvalho. Through an emphasis on Carvalho's thirty-plus year career working for TV Globo, his unique mode of production, and his development of a singular aesthetic as a reaction to the dominant telenovela genre, Carter sheds new light on Brazilian television's history, its current state, and where it is going–as new legislation and technology push it increasingly toward a post-network era.
Keywords: 1-TV; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Amérique du Sud (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); Brésil (corpus analysé); _Nettoyé; États-Unis (lieu de production du savoir)

Film and Television Culture in China - Zhifeng, Hu (Paths International, Limited, 2018)
Film and Television Culture in China gives a provocative analysis of film and television culture in China. The author first gives a panoramic picture of Chinese culture in which film and television was born and shaped. He then delineates the definition, composition, and basic relations in film and television culture. Also discussed are the two traditions in Chinese film and television culture–the worldly spirit and the poetic style. The two traditions are deeply rooted in Chinese Confucianism and Taoism, and have influenced Chinese film and television from the start. The author provides in-depth and original readings of the phenomena in Chinese film and television culture, such as: the reform films and the reflection films; the character and mission of television documentary; and a dialogue between the mainland and Taiwan. Film and Television Culture in China will be an essential guide to understand the film and television culture in China, from early screen to the present day.
Keywords: 1-Cinéma; 1-TV; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; Chine (corpus analysé); Chine (lieu de production du savoir); _Nettoyé

Arab Television Industries - Khalil, Joe; Kraidy, Marwan M. (BFI Publishing, 2009)
In recent years, Arab television has undergone a dramatic and profound transformation from terrestrial, government-owned, national channels to satellite, privately owned, transnational networks. The latter is the Arab television that matters today, economically, socially and politically. The resulting pan-Arab industry is vibrant, diverse, and fluid - very different, the authors of this major new study argue, from the prevailing view in the West, which focuses only on the al-Jazeera network. Based on a wealth of primary Arabic language sources, interviews with Arab television executives, and the authors' personal and professional experience with the industry, Arab Television Industries tells the story of that transformation, featuring compelling portraits of major players and institutions, and captures dominant trends in the industry. Readers learn how the transformation of Arab television came to be, the different kinds of channels, how programs are made and promoted, and how they are regulated. Throughout, the analysis focuses on the interaction of the television industry with Arab politics, business, societies and cultures.
Keywords: 1-TV; 2-Approches sociologiques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Créateur.rice PANDC; Qatar (lieu de production du savoir); _Nettoyé

Women, Television and Everyday Life in Korea: Journeys of Hope - Kim, Youna (Taylor & Francis Group, 2006)
Fusing audience research and ethnography, the book presents a compelling account of women's changing lives and identities in relation to the impact of the most popular media culture in everyday life: television. Within the historically-specific social conditions of Korean modernity, Youna Kim analyzes how Korean women of varying age and class group cope with the new environment of changing economical structure and social relations. The book argues that television is an important resource for women, stimulating them to research their own lives and identities. Youna Kim reveals Korean women as creative, energetic and critical audiences in their responses to evolving modernity and the impact of the West. Based on original empirical research, the book explores the hopes, aspirations, frustrations and dilemmas of Korean women as they try to cope with life beyond traditional grounds. Going beyond the traditional Anglo-American view of media and culture, this text will appeal to students and scholars of both Korean area studies and media and communications studies.
Keywords: 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude de la réception; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Europe (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; 5-Identités diasporiques; Corée du Sud (corpus analysé); France (lieu de production du savoir); _Nettoyé

Watching Si Doel: Television, Language and Identity in Contemporary Indonesia - Loven, Klarijn (BRILL, 2008)
While television in today's world increasingly displays a global character, national television systems are still firmly rooted in a specific locality. But in what ways does this locality actually shape the content and performance of national television? What is the significance of local cultures and local languages in these processes of mediation? And how do the local, the national, and the global intersect in discourses of and discourse on television? Taking a critical discourse analysis perspective, Watching Si Doel investigates these and related questions in the context of contemporary Indonesia. Starting from the nationwide popularity of the local television serial Si Doel Anak Sekolahan ("Educated Doel"), it examines the various ways in which the national government, Indonesian television producers, and local audiences shape, interpret, and struggle over the meaning of the phrase 'national television'. In doing so, the book explores what Indonesian television at the turn of the century sounds and looks like–and, significantly, ought to sound and look like–according to those who create and control television and those who watch and interpret it. While providing insight into the production, nature, and reception of television discourse in general, this book particularly seeks to clarify the relationship between television, language, and power in late New Order and post-Soeharto Indonesia.
Keywords: 1-TV; 2-Approches sociologiques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude de la réception; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Europe (lieu de production du savoir); 5-Autrice; Indonésie (corpus analysé); Pays-Bas (lieu de production du savoir); _Nettoyé

Global Media: The Television Revolution in Asia - White, James D. (Routledge, 2005)
This book is about the processes of globalization, demonstrated through a comparative study of three television case histories in Asia. Also illustrated are different approaches to providing television services in the world: public service (NHK in Japan), state (CCTV in China) and commercial (STAR TV, based in Hong Kong). Through its focus, Global Media addresses a considerable lacuna in the media studies literature, which tends to have a heavy Western bias. It provides an original addition to the literature on globalization, which is often abstract and anecdotal, in addition to making a major contribution to comparative research in Asia. Finally, it offers a thoughtful causal layered analysis, with a concluding argument in favor of public service television.
Keywords: 1-TV; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); Chine (corpus analysé); Hong Kong (corpus analysé); Japon (corpus analysé); _Nettoyé; États-Unis (lieu de production du savoir)

Telly-Guillotined: How Television Changed India - Shah, Amrita (SAGE Publications India Pvt, Ltd., 2019)
Fist-fights in television studios, dwindling media autonomy, sensationalism, fake news, religious hate, abusive trolls, political spin ... How did we get here? Three decades ago, before economic liberalization, came the expansion and privatization of Indian television. Technological innovation and easing of government controls offered the prospect of journalistic independence, artistic creativity and an empowered citizenry. This was rendered illusory by runaway growth and untrammelled commercialization. In that thwarted promise of the late 20th century lie the seeds of Indian democracy's current crisis. Telly-Guillotined: How Television Changed India tells the story of how technology was usurped, first by propagandists, then by the market. Going behind the scenes of the world′s greatest media explosion, this book describes the impact of consumerism on the newsroom, the shaping of a new cultural politics and the rise of a new politics of seduction. In a landscape of technological innovation, blurred boundaries and sensory overload, Amrita Shah paints a picture of the Fourth Estate′s challenging future.
Keywords: 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; Inde (corpus analysé); Inde (lieu de production du savoir); _Nettoyé

Visual Political Communication in Popular Chinese Television Series - Schneider, Florian; Dudbridge, Glen; Pieke, Frank N. (BRILL, 2012)
In Visual Political Communication in Popular Chinese Television Series, Florian Schneider analyses political discourses in Chinese TV dramas, the most popular entertainment format in China today.
Keywords: 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Europe (lieu de production du savoir); Chine (corpus analysé); Pays-Bas (lieu de production du savoir); Royaume-Uni (lieu de production du savoir); _Nettoyé

Muy buenas noches: Mexico, Television, and the Cold War - Gonzalez de Bustamante, Celeste (Nebraska Paperback, 2013)
By the end of the twentieth century, Mexican multimedia conglomerate Televisa stood as one of the most powerful media companies in the world. Most scholars have concluded that the company’s success was owed in large part to its executives who walked in lockstep with the government and the Partido Revolucionario Institucional (PRI), which ruled for seventy-one years. At the same time, government decisions regulating communications infrastructure aided the development of the television industry. In one of the first books to be published in English on Mexican television, Celeste González de Bustamante argues that despite the cozy relationship between media moguls and the PRI, these connections should not be viewed as static and without friction. Through an examination of early television news programs, this book reveals the tensions that existed between what the PRI and government officials wanted to be reported and what was actually reported and how. Further, despite the increasing influence of television on society, viewers did not always accept or agree with what they saw on the air. Television news programming played an integral role in creating a sense of lo mexicano (that which is Mexican) at a time of tremendous political, social, and cultural change. At its core the book grapples with questions about the limits of cultural hegemony at the height of the PRI and the cold war.
Keywords: 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; Mexique (corpus analysé); _Nettoyé; États-Unis (lieu de production du savoir)

Minority Television Trade as Cultural Journey: The Case of New Zealand’s Bro’Town - Havens, Timothy (Watching While Black, 2012)
Four animated, brown-skinned youth are lounging on a porch step in Auckland, New Zealand, when a fierce-looking social worker and police constable approach and insist on knowing where the father of two of the boys is. As the constable raises his nightstick, one of the boys fumbles in heavily accented Māori English, “He went to the pub four days ago and hasn’t been back.” The authorities quickly cart two of the boys off as wards of the state as another performs a Māori haka, or war chant, in mock warning to the police.
Keywords: 1-TV; 2-Approches sociologiques; 2-Épistémologies autochtones; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Océanie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); Nouvelle-Zélande/Aotearoa (corpus analysé); _Nettoyé; États-Unis (lieu de production du savoir)

South African Soapies: A “Rainbow Nation” Realized? - Burton, Nsenga K. (Watching While Black, 2012)
In the United States, daytime soap operas are often critiqued as escapist fantasies with narratives that provide leisure and pleasure for middle-class and stay-at-home mothers. The storylines typically involve forbidden sexual liaisons and business relationships, with physical and psychological behaviors that center on powerful families. One family unit usually represents “old money” while the other family represents “new money” or an upwardly mobile group with aspirations of power, status, and influence. The economic differences are usually the source of conflict between the families, around which all other social relationships develop. The temporal space expands and contracts to accommodate storylines, which
Keywords: 1-TV; 2-Approches sociologiques; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Afrique (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; Afrique du Sud (corpus analysé); _Nettoyé; États-Unis (lieu de production du savoir)

Resistance Televised: The TV da Gente Television Network and Brazilian Racial Politics - Gillam, Reighan Alexandra (Watching While Black, 2012)
As activists and political leaders in Brazil call for increasing rights, recognition, and redress to address the multiple forms of marginalization that Afro-Brazilians have endured, media has become an increasingly important sphere through which different constituencies mobilize to advance a project of racial equality. Among these groups enlisting available media resources was a group composed predominately of Afro-Brazilian media professionals who joined together to launch the TV da Gente (Our TV) television network, Brazil’s first television station with the mission to produce racially diverse programming directed toward a Black viewing audience.
Keywords: 1-TV; 2-Approches sociologiques; 2-Étude de la réception; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Sud (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; Brésil (corpus analysé); _Nettoyé; États-Unis (lieu de production du savoir)

Graphic Blackness/Anime Noir: Aaron McGruder’s the Boondocks and the Adult Swim - Whaley, Deborah Elizabeth (Watching While Black, 2012)
Aaron McGruder’s “The Return of the King” (2006) is one of many of the artist’s controversial episodes, yet it stands out because of the criticism it received among mainstream media outlets and civil rights leaders. It was the ninth episode to air from his series The Boondocks, which is an anime show that airs on the Cartoon Network’s Adult Swim cable channel. McGruder presents the following scenario in “The Return of the King”: What if Martin Luther King Jr. (MLK) did not die after his April 4, 1968, shooting and instead awoke after being in a coma for thirty-two years?
Keywords: 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; _Nettoyé; États-Unis (corpus analysé); États-Unis (lieu de production du savoir)

Nigger, Coon, Boy, Punk, Homo, Faggot, Black Man: Reconsidering Established Interpretations of Masculinity, Race, ans Sexuality Through Noah’s Arc - Cunningham, Mark D. (Watching While Black, 2012)
At best, our knowledge about the lives and experiences of Black gay men is limited to a series of stereotypes, snap judgments, and ridicule. In terms of television media product, this aforementioned knowledge has been packaged mostly within the framework of comedy: a red-leather-clad Eddie Murphy talking about the most effective ways to shield his ass from the gay male gaze in the 1983 HBO stand-up performance Delirious ; Damon Wayans and David Alan Grier’s effeminate film critics Blaine Edwards and Antoine Merriweather on the 1990s television variety show In Living Color ; fashionista panel members Miss J and Andre Leon Talley
Keywords: 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; _Nettoyé; États-Unis (corpus analysé); États-Unis (lieu de production du savoir)

Prioritized: The Hip Hop (Re)Construction of Black Womanhood in Girlfriends and the Game - Lewis, Nghana (Watching While Black, 2012)
Why is it important that a Black woman created, wrote for, and co-produced¹ two highly-regarded television situation comedies that engaged a variety of Black women’s health issues while at the same time these issues were being reduced, simplified, or altogether ignored in mainstream American hip hop? Mara Brock Akil tacitly responded to this question when asked why four episodes of the third season of Girlfriends (2000–2008), the situation comedy she created and co-produced for UPN, addressed the HIV/AIDS crisis among Black women in America. “I have things I want to say,” explained Brock Akil, “about bridging television’s gap between
Keywords: 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; _Nettoyé; États-Unis (corpus analysé); États-Unis (lieu de production du savoir)

Keepin’ It Reality Television - Gates, Racquel (Watching While Black, 2012)
On November 4, 2008, CNN anchor Anderson Cooper appeared on The Ellen DeGeneres Show via satellite. One of the more memorable moments of the interview came when Cooper expressed shock that DeGeneres was unfamiliar with the hit Bravo television show The Real Housewives of Atlanta. “You mean you don’t know about NeNe?” he demanded incredulously, referring to cast member NeNe Leakes—the most outspoken and self-proclaimed “realest” of the Housewives. Cooper’s segment, along with his admission that Leakes was his favorite of the cast, brought even more attention to the already widely debated show, the first of Bravo’s Housewives series
Keywords: 1-TV; 2-Approches sociologiques; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; _Nettoyé; États-Unis (corpus analysé); États-Unis (lieu de production du savoir)

Down in the Treme … Buck Jumping and Having Fun?: th Impact of Depictions of Post-Katrina New Orleans on Viewers’ Perceptions of the City - LeDuff, Kim M. (Watching While Black, 2012)
Five years after Hurricane Katrina devastated New Orleans, Louisiana, life remained not normal still for many residents of the city. And while mainstream news organizations remembered the fifth anniversary of the hurricane with extensive coverage, it was the work of filmmaker Spike Lee and television program creators David Simon and Eric Overmyer that perhaps created the greatest buzz about the fifth anniversary of Katrina in 2010. Spike Lee’s first documentary, When the Levees Broke , was released in 2006. It documented what happened in New Orleans through the voices of local residents, politicians, and experts during and immediately after the storm.
Keywords: 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Étude de la réception; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice noir.e; 5-Autrice; 5-Créateur.rice PANDC; _Nettoyé; États-Unis (corpus analysé); États-Unis (lieu de production du savoir)

Gimme a Break! and the Limits of the Modern Mammy - Fuller, Jennifer (Watching While Black, 2012)
Picture this: a comedy about an overweight Black woman who lives with and takes care of a white family. Joking all the way, she cooks, cleans, helps the father of the family, and comforts the children. Then at one point, we see the father holding his gun and pointing toward the door. The Black woman enters and jumps up and down, screaming, “Massa! Massa! Massa! Please don’t shoot!” It is easy to imagine these scenes in a 1930s film about the antebellum South. But they are actually from the first episode of a 1980s sitcom.
Keywords: 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; _Nettoyé; États-Unis (corpus analysé); États-Unis (lieu de production du savoir)

“Hey, Hey, Hey!”: Bill Cosby’s Fat Albert as Psychodynamic Postmodern Play - Russworm, TreaAndrea M. (Watching While Black, 2012)
Although the cartoon series Fat Albert and the Cosby Kids (CBS, 1972–1984) averaged only nine new episodes a year during its twelve-year run (compared to a more standard production cycle of twenty-five to sixty new episodes a year for other cartoons), the show remained a highly popular option for young viewers on late Saturday mornings. By the time of the series’ network premiere in 1972, the cartoon’s animated African American stars—Weird Harold, Dumb Donald, Fat Albert, Rudy, Mushmouth, Bucky, Russell, and Bill—were familiar and recognizable to American audiences as originating from Bill Cosby’s boyhood community of North
Keywords: 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; _Nettoyé; États-Unis (corpus analysé); États-Unis (lieu de production du savoir)

“Regular Television Put to Shame by Negro Production”: Picturing a Black World on Black Journal - Heitner, Devorah (Watching While Black, 2012)
In the first episode of Black Journal , before the opening credits, comedian Godfrey Cambridge appears dressed in overalls and a painter’s cap with a paint roller in hand and methodically paints the television frame. To the viewer, it appears that his or her television is being painted black from the inside—a potent visual symbol from the first national Black public affairs program. Initially, though, the symbol emphasizes a visual challenge to the absence of Black faces on television—a show that “looks” Black, because of the visibility of its Black hosts and reporters, but where whites still have significant
Keywords: 1-TV; 2-Approches sociologiques; 2-Méthodologie de recherche décoloniale; 2-Étude de la réception; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; _Nettoyé; États-Unis (corpus analysé); États-Unis (lieu de production du savoir)

Blacks in the Future: Braving the Frontier of the Web Series - Acham, Christine (Watching While Black, 2012)
Television’s synergy with the Web initially seemed inconceivable to network executives. With the rise of Internet use, newspaper and magazine articles announced the impending death of television. While that was clearly hyperbole, network executives, though often anonymously, expressed their fears that Web content would siphon off viewership and thus advertising dollars generated by television programming. Fears may have been quelled with the evidence of the success of television shows first made available streaming on network websites and then for paid download through digital servers such as iTunes.
Keywords: 1-TV; 2-Étude de la réception; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; _Nettoyé; États-Unis (corpus analysé); États-Unis (lieu de production du savoir)

A Black Cast Doesn’t Make a Black Show: City of Angels and the Plausible Deniability of Color-Blindness - Warner, Kristen J. (Watching While Black, 2012)
In a recent debate over the problematic characterization of Bonnie Bennett, the only Black female recurring character on the CW network series The Vampire Diaries (CW 2009), my challenger insisted that with all of the qualifiers I insisted she have, “maybe this is another hidden reason there are no minorities on television: everything becomes an issue and you just can’t win.” Indeed, the main qualifier I suggested that the series allow the character to possess—an innate sense of cultural difference—is difficult to grasp and maintain. However, I do not accept that just because race is difficult, it is
Keywords: 1-TV; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; _Nettoyé; États-Unis (corpus analysé); États-Unis (lieu de production du savoir)

Two Different Worlds: Television as a Producer’s Medium - Coleman, Robin R. Means; Cavalcante, Andre M. (Watching While Black, 2012)
Although discourses regarding 1980s representations of Blackness on television heavily focus on The Cosby Show, its NBC spin-off series, A Different World, depicting student life at a historically Black college, was equally groundbreaking and deserving of critical attention. Looking to transfer the appeal and audience share of The Cosby Show to A Different World, the spin-off show’s first season centered on the life of The Cosby Show’s star Denise Huxtable (Lisa Bonet) at Hillman College. A Different World’s story provides an illuminating case study of the role and power of television producers, highlighting their influence over a show’s narrative and
Keywords: 1-TV; 2-Approches sociologiques; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice; 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; _Nettoyé; États-Unis (corpus analysé)

The Importance of Roots - Pierson, Eric (Watching While Black, 2012)
In January 1977, I, along with over ninety million other Americans, watched at least one episode of the television miniseries Roots: The Saga of an American Family. Over the eight days of the broadcast, the audience grew, and debates regarding its impact filled media outlets. In the weeks and months after the show aired, the impact was measurable as many families sought out genealogists to research family histories and college campuses saw increased interest in African American Studies. Vernon Jordan, executive director of the National Urban League, commented, “ Roots was the single most spectacular educational experience in race relations in
Keywords: 1-TV; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Amérique du Nord (corpus analysé); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; _Nettoyé; États-Unis (corpus analysé); États-Unis (lieu de production du savoir)

Introduction: I See Black People - Smith-Shomade, Beretta E. (Watching While Black, 2012)
This project has been engaging my thoughts for nearly a decade. I was forced to actually address it while sitting in our temporary home in Ile-Ife, Nigeria, watching world satellite TV with virtually no Blacks on it. In Nigeria, I became acquainted with Paris-based Fashion TV, U.S.-based Style Network, and the Australian production McLeod’s Daughters. Outside of M-Net’s Africa Magic, a network dedicated to showing Nollywood productions primarily, television was anything but Black. This whitening of the televisual frame, even in Black Africa, made me begin to consider the dearth of knowledge circulating about Black television programming, even when abundance
Keywords: 1-TV; 2-Approches sociologiques; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice; 5-Auteur.rice noir.e; 5-Créateur.rice PANDC; _Nettoyé; États-Unis (corpus analysé); États-Unis (lieu de production du savoir)

Cinema and Television in Singapore: Resistance in One Dimension - Tan, Kenneth (BRILL, 2008)
Through close readings of contemporary made-in-Singapore films (by Jack Neo, Eric Khoo, and Royston Tan) and television programs (Singapore Idol, sitcoms, and dramas), this book analyzes the prospects of resistance in an advanced capitalist-industrial society with "global city" aspirations.
Keywords: 1-Cinéma; 1-TV; 2-Approches sociologiques; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Créateur.rice PANDC; Singapour (corpus analysé); Singapour (lieu de production du savoir); _Nettoyé

Gandhi Meets Primetime: Globalization and Nationalism in Indian Television - Kumar, Shanti (University of Illinois Press, 2005)
Shanti Kumar's Gandhi Meets Primetime examines how cultural imaginations of national identity have been transformed by the rapid growth of satellite and cable television in postcolonial India. To evaluate the growing influence of foreign and domestic satellite and cable channels since 1991, the book considers a wide range of materials including contemporary television programming, historical archives, legal documents, policy statements, academic writings and journalistic accounts. Kumar argues that India's hybrid national identity is manifested in the discourses found in this variety of empirical sources. He deconstructs representations of Mahatma Gandhi as the Father of the Nation on the state-sponsored network Doordarshan and those found on Rupert Murdoch's STAR TV network. The book closely analyzes print advertisements to trace the changing status of the television set as a cultural commodity in postcolonial India and examines publicity brochures, promotional materials and programming schedules of Indian-language networks to outline the role of vernacular media in the discourse of electronic capitalism. The empirical evidence is illuminated by theoretical analyses that combine diverse approaches such as cultural studies, poststructuralism and postcolonial criticism.
Keywords: 1-TV; 2-Approches sociologiques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; Inde (corpus analysé); _Nettoyé; États-Unis (lieu de production du savoir)

Politics After Television: Hindu Nationalism and the Reshaping of the Public in India - Rajagopal, Arvind (Cambridge University Press, 2001)
In January 1987, the Indian state-run television began broadcasting a Hindu epic in serial form, The Ramayana, to nationwide audiences, violating a decades-old taboo on religious partisanship. What resulted was the largest political campaign in post-independence times, around the symbol of Lord Ram, led by Hindu nationalists. The complexion of Indian politics was irrevocably changed thereafter. In this book, Arvind Rajagopal analyses this extraordinary series of events. While audiences may have thought they were harking back to an epic golden age, Hindu nationalist leaders were embracing the prospects of neoliberalism and globalisation. Television was the device that hinged these movements together, symbolising the new possibilities of politics, at once more inclusive and authoritarian. Simultaneously, this study examines how the larger historical context was woven into and changed the character of Hindu nationalism.
Keywords: 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; Inde (corpus analysé); _Nettoyé; États-Unis (lieu de production du savoir)

New Television, Globalisation, and the East Asian Cultural Imagination - Keane, Michael; Fung, Anthony Y. H.; Moran, Albert (Hong Kong University Press, 2007)
This volume is divided into three parts: 'Adaptation and Local Production in East Asia', 'Formats, Clones, and Generic Variations' and 'New Television'.
Keywords: 1-TV; 2-Analyses formalistes; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 4-Océanie (lieu de production du savoir); 5-Auteur.rice PANDC; Australie (lieu de production du savoir); Chine (corpus analysé); Corée du Sud (corpus analysé); Hong Kong (corpus analysé); Hong Kong (lieu de production du savoir); Japon (corpus analysé); Taiwan (corpus analysé); _Nettoyé

Manufacturing the Gang: Mexican American Youth Gangs on Local Television News - Tovares, Raul Damacio (Greenwood Publishing Group, Incorporated, 2002)
Coverage of Mexican-American youth gangs has been a staple of local television news in the United States for decades, and its form and content have come to embody many journalistic cliches: the rising tide of violence, the spread of drug addiction, the alienated minority youth. But as this bold new study argues, these stories contain gross exaggerations that lead to the reinforcement of stereotypes about Mexican-American young people and the Mexican-American community in general. Indeed, the police and community leaders greatly influence the content of this coverage by deciding what information to make available to the news media, while reporters select certain sources and ignore others, thus slanting the story even further. Source: Publisher
Keywords: 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé; États-Unis (lieu de production du savoir)

Maori Television: The First Ten Years - Smith, Jo (Auckland University Press, 2016)
Established in 2004, Maori Television has had a major impact on the New Zealand broadcasting landscape. But over the past year or so, the politics of Maori Television have been brought to the foreground of public consciousness, with other media outlets tracking Maori Television's search for a new CEO, allegations of editorial intervention and arguments over news reporting approaches to Te Kohanga Reo National Trust.Based on a Marsden Grant and three years of interviews with key stakeholders – staff, the Board, other media, politicians, funders and viewers – this is a deep account of Maori Television in its first ten years. Jo Smith argues that today's arguments must be understood within a broader context shaped by non-Maori interests. Can a Maori broadcaster follow both tikanga and the Broadcasting Standards Authority? Is it simply telling the news in Maori, or broadcasting the news with a Maori perspective? How can it support te reo Maori at the same time as appeal to all New Zealand? How does it function as the voice of its Maori stakeholders?Offering five frameworks to address the challenges of a Maori organisation working within a wider non-Maori context, this is a solidly researched examination of Maori Television's unique contribution to the media cultures of Aotearoa New Zealand.
Keywords: 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Méthodologie de recherche décoloniale; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 2-Étude des industries culturelles; 3-Océanie (corpus analysé); 4-Océanie (lieu de production du savoir); 5-Auteur.rice; Nouvelle-Zélande/Aotearoa (corpus analysé); Nouvelle-Zélande/Aotearoa (lieu de production du savoir); _Nettoyé

Television, Nation, and Culture in Indonesia - Kitley, Philip (Ohio University Press, 2014)
The culture of television in Indonesia began with its establishment in 1962 as a public broadcasting service. From that time, through the deregulation of television broadcasting in 1990 and the establishment of commercial channels, television can be understood, Philip Kitley argues, as a part of the New Order’s national culture project, designed to legitimate an idealized Indonesian national cultural identity. But Professor Kitley suggests that it also has become a site for the contestation of elements of the New Order’s cultural policies. Based on his studies, he further speculates on the increasingly significant role that television is destined to play as a site of cultural and political struggle.
Keywords: 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Océanie (lieu de production du savoir); 5-Auteur.rice PANDC; Australie (lieu de production du savoir); Indonésie (corpus analysé); _Nettoyé

Consuming Halal Turkish Television in Indonesia: A Closer Look at the Social Responses Towards Muhteşem Yüzyıl - Rakhmani, Inaya; Zakiah, Adinda (Television in Turkey: Local Production, Transnational Expansion and Political Aspirations, 2020)
This chapter unpacks the tension between secular, modern values and conservative, Islamic interpretations within the Indonesian middle class by taking the consumption of Turkish popular cultural products as a case. The chapter explicates the social responses towards the first Turkish television drama aired on terrestrial, private television in Indonesia: The Magnificent Century (Muhtesṃem Yüzyıl/Abad Kejayaan). This chapter understands the reproduction of secular and conservative Islamic values, while in contestation, as a response to broader global, market-capitalist developments. It finds that in response to audience criticism regarding the “un-Islamic” portrayal of the epoch in the drama—specifically the depiction of women as concubines—television stations enlisted the services of Muslim clerics to correct or justify the representation of historical facts. This reveals that market-driven self-censorship has opened up ways for Muslim clerics to influence television content. As such, the chapter argues that market-capitalist forces discursively use Islamic authority as a way to legitimise the halal consumption of Turkish drama among Indonesian Muslim audience at the expense of programme diversity.
Keywords: 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice; 5-Auteur.rice PANDC; Indonésie (corpus analysé); Indonésie (lieu de production du savoir); Turquie (corpus analysé); _Nettoyé

Turkish Drama Serials and Arab Audiences: Why Turkish Serials Are Successful in the Arab World - Berg, Miriam (Television in Turkey: Local Production, Transnational Expansion and Political Aspirations, 2020)
This chapter explores the social and cultural factors that have contributed to the success of Turkish programs in the Arab world. Following the cancelation of Turkish serials on the Arab world’s largest networks in Saudi Arabia and the United Arab Emirates, this chapter will explore how dedicated Arab fans are continuing to watch Turkish shows via alternative platforms after having seen them become such a large part of their daily lives and a permanent fixture on their screens in recent years. By using the Gulf State of Qatar as a departure point, it will examine why Turkish content resonates so closely with female Arab audiences, while also determining their viewing motivations and how Turkish serials have managed to fill a void among its viewers that Arab media has failed to satisfy. At the same time, this chapter will discuss why Turkish dramas have been widely perceived as a women’s genre despite being prime-time serials in Turkey.
Keywords: 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude de la réception; 2-Étude des représentations; 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice; Qatar (corpus analysé); Qatar (lieu de production du savoir); Turquie (corpus analysé); _Nettoyé

Mediatised Culturalisation Through Television: Second-Generation Alevi Kurds in London - Emre Cetin, Kumru Berfin (Television in Turkey: Local Production, Transnational Expansion and Political Aspirations, 2020)
Satellite television has not only provided migrant communities with stronger ties to their home countries but also enabled second-generation migrants in particular to know more about their country of origin beyond their family ties. The aim of this chapter is to explore the ways in which Turkish television contributes towards the making of the transnational identity of the “twice minority” group of Alevi Kurds through what I call mediatised culturalisation. Drawing on 17 in-depth interviews that I conducted with the second-generation members of the Alevi Kurdish community in London in 2016, I explore the role of Turkish television in contesting the boundaries of transnational social imaginaries of the second-generation viewers.
Keywords: 1-TV; 2-Approches sociologiques; 2-Étude de la réception; 2-Étude des représentations; 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Europe (lieu de production du savoir); 5-Auteur.rice; 5-Auteur.rice PANDC; Royaume-Uni (lieu de production du savoir); Turquie (corpus analysé); _Nettoyé

From TRT to Netflix: Implications of Convergence for Television Dramas in Turkey - Yanardağoğlu, Eylem; Turhallı, Neval (Television in Turkey: Local Production, Transnational Expansion and Political Aspirations, 2020)
Since the1980s, the television (TV) drama has proved to be one of the most dominant formats on Turkish TV channels and occupied major slots on primetime throughout the 1990s and 2000s. As Internet penetration grew, on-demand services transformed audiences’ expectations of TV series. Internet series first became a trend on YouTube in 2013, and Netflix began broadcasting in Turkey at the beginning of 2016. Its entry to the sector triggered video-on-demand suppliers like Blu TV and Puhu TV which are digital enterprises of Doğan and Doğusṃ Holdings. Blu TV announced their first original project in 2017, Masum (Innocent), which was a big-budget series that included famous actors. In the same year, Puhu TV released their first original, Fi (Phi). Finally, Netflix launched their first original production in Turkey, Hakan: The Protector, in 2018. This chapter focuses on the implications of convergence for the production and distribution of TV dramas and considers the changes in the sector as television broadcasting shifted to new media platforms in Turkey.
Keywords: 1-TV; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Auteur.rice; 5-Auteur.rice PANDC; Turquie (corpus analysé); Turquie (lieu de production du savoir); _Nettoyé

Mediatisation and Hyper-commodification of Sport in Post-1980 Turkey - Irak, Dağhan (Television in Turkey: Local Production, Transnational Expansion and Political Aspirations, 2020)
Sport has had a symbiotic relationship with television for decades, as it has always been one of the most marketable visual products for the medium. The new visual media technologies that have been introduced since the 1970s have altered this relationship greatly by incrementally commodifying sport at each step. One of the most crucial aspects of this relationship is globalisation, which initially depended on satellite television and took sport’s hyper-commodification to a whole new level. Turkey, which went through a massive transformation to a neoliberal rule following a bloody coup d’etat in 1980 that practically razed the whole social and political structure, has since become an important example of the roles of sport and television in an aggressively neoliberal setting. This chapter aims to explain why televised sport has had a remarkable role in the sociopolitical transformation of Turkey since the 1980 coup.
Keywords: 1-TV; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Europe (lieu de production du savoir); Royaume-Uni (lieu de production du savoir); Turquie (corpus analysé); _Nettoyé

Continuities and Changes in the Transnational Broadcasts of TRT - Karanfil, Gökçen (Television in Turkey: Local Production, Transnational Expansion and Political Aspirations, 2020)
This chapter traces the evolution of the Turkish Public Service Broadcaster with a focus on its transnationalization. Drawing parallels between the changing dynamics in politics, culture, and media in Turkey; contemporary cosmopolitan media cultures; and the continuities and changes in Turkish Radio and Television Corporation’s (henceforth TRT) identity as a public service broadcaster, I shed light on the ways in which TRT has been engaging in transnational broadcasts since the beginning of 1990s. For this I elaborate on the ways in which transnational broadcasting processes in Turkey have been influenced by media transnationalization around the world. I discuss two different incentives behind TRT’s transnational endeavors. First, I elaborate on TRT’s attempts at engaging with the Turkish diaspora around the world; later, I articulate how, in more recent years, TRT sets out to exert a Turkish cultural presence in the Middle East and North Africa (MENA) region. The chapter aims to draw a general portrait of the concept of transnational broadcasting in Turkey with a specific focus on the country’s public service broadcaster, TRT.
Keywords: 1-TV; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Auteur.rice PANDC; Turquie (corpus analysé); Turquie (lieu de production du savoir); _Nettoyé

Representing Female Detectives in Turkish Police Procedurals - Kesirli Unur, Ayşegül (Television in Turkey: Local Production, Transnational Expansion and Political Aspirations, 2020)
Police procedural has been historically perceived as a dominantly masculine genre for continually revolving around the investigations of male police officers. In accordance with the patriarchal norms that pervade Turkish society, local variations of the police procedural genre have conveniently appropriated this globally known convention and left little room for female detectives in their narratives. However, whenever they got a chance to be included in this male-dominated universe, female detectives have been frequently depicted as relatively independent women but also submitted to the traditional norms of womanhood in an ambivalent manner. This chapter examines this hesitant position of female police detectives in three contemporary Turkish police procedurals, Kanıt (The Evidence, 2010–2013), Cinayet (The Killing, 2014) and Sṃahsiyet (Personality, 2018), by building connections between the interest of police procedural genre in feminist debates in the global context and the influence of this interest on local variations.
Keywords: 1-TV; 2-Genre et sexualité; 2-Étude des représentations; 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Auteur.rice; Turquie (corpus analysé); Turquie (lieu de production du savoir); _Nettoyé

Women’s Fragile Trust: Safety, Familiarity, and Secrecy in the Marriage Show - Akınerdem, Feyza (Television in Turkey: Local Production, Transnational Expansion and Political Aspirations, 2020)
The marriage show was a popular reality show format that invited people to find their soulmate and marry on live television in Turkey. Based on ethnographic fieldwork which took place in the show’s studio between 2011 and 2012, this chapter explores female participants’ investment of their trust in the show. While being reluctant about finding a spouse on television, women take on registers of safety, familiarity, and secrecy to navigate the show as a safe venue. This endeavor also involved women’s safeguarding of themselves on their way to marriage. The fragility of trust in the show, therefore, indicates how women foresee risks and yet strive for securing happiness and safety in marriage in general. This affective tension, at a larger scale, is related to the increased sense of insecurity at a global scale, and the systematic failure of the family to provide the safe living environment it promises in the Turkish context.
Keywords: 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude des représentations; 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Auteur.rice; Turquie (corpus analysé); Turquie (lieu de production du savoir); _Nettoyé

Debating Women’s Issues on Turkish Television: Exploring the Role of Political Power in Women’s Talk - Özcan, Esra (Television in Turkey: Local Production, Transnational Expansion and Political Aspirations, 2020)
In this contribution, I provide an in-depth rhetorical and textual analysis of a television debate program broadcast in 2015 on the mainstream television news channel, Habertürk TV in Turkey. The debate brought together women committed to varying political projects, including Kemalism, Islamism, leftist movements, Kurdish women’s movements, and feminism. I find this debate program unique because it took place at a crucial moment in Turkey’s recent history, preceding increasing restrictions on the media that eventually cost more than half of the program participants’ jobs and positions. In my analysis, I focus on how the program’s moderator and the women participants define “women’s issues” in an increasingly authoritarian and conflictual political climate where women are divided with regard to supporting or opposing the Justice and Development Party’s (Adalet ve Kalkınma Partisi—AKP) political program. The results of my analysis show that “sisterhood” does not provide common ground for women in a politically polarized environment and women with more political power dominate the conservation.
Keywords: 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude des représentations; 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice; Turquie (corpus analysé); _Nettoyé; États-Unis (lieu de production du savoir)

Revisiting the Unplugged Margins: Rural Television Audiences and Mediatization - Türkoğlu, Nurçay (Television in Turkey: Local Production, Transnational Expansion and Political Aspirations, 2020)
This chapter examines the social transformation of the television audience of rural Turkey. Villages near a metropolitan area, which were subject to an administrative decision to be relocated, were the focus of my fieldwork 30 years ago. Several visits between 1987 and 2019 to the same location, which is inhabited by television viewers and non-viewers alike, yielded an insightful mapping of engagement with popular culture via television at the periphery in Turkey from a historical perspective. While rural inhabitants are busy with daily labor in the countryside and are not keen on watching television, they are nonetheless aware of and connected to new, nationwide cultural trends and social changes. By reflexively discussing these experiences in ethnographic fieldwork on television habits and reception in rural Turkey over a 30-year span, I avoid the traps of modern-traditional and urban-rural binaries, allowing for an exploration of the role of television in mediating social change in the rural context and thus an analysis of the various complex layers and processes of mediatization among rural audiences.
Keywords: 1-TV; 2-Approches sociologiques; 2-Étude de la réception; 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Auteur.rice; 5-Auteur.rice PANDC; Turquie (corpus analysé); Turquie (lieu de production du savoir); _Nettoyé

Televised Journalistic Documentaries of the 1990s: The Form, Content, and Historical Juncture - Çelik, Burçe (Television in Turkey: Local Production, Transnational Expansion and Political Aspirations, 2020)
The 1990s’ popular televised journalistic/history documentaries have played a vital role in the making of political television culture, society of political spectacle, and the production of popular history and memory in Turkey. Despite their importance, these documentaries did not attract enough scholarly attention. By focusing on arguably the most popular and impactful journalistic/history documentaries of Turkey’s history, developed by Mehmet Ali Birand in the 1990s, I will assess the role of television in teaching, telling, and writing the political history. In doing so, I will also contextualize the form and discourse of these documentary series within historical juncture of globalization and neoliberalization of television as well as the country’s political economy.
Keywords: 1-TV; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Europe (lieu de production du savoir); 5-Auteur.rice; 5-Auteur.rice PANDC; Royaume-Uni (lieu de production du savoir); Turquie (corpus analysé); _Nettoyé

The Regulation of Television Content in Turkey: From State Monopoly to Commercial Broadcasting and Beyond - Sümer, Burcu; Taş, Oğuzhan (Television in Turkey: Local Production, Transnational Expansion and Political Aspirations, 2020)
In contrast with radio broadcasting, which began in 1927, television started remarkably late in Turkey. When the country’s sole public service broadcaster, Turkish Radio and Television Corporation (TRT), was established in 1964 and all of the radio transmitters were transferred to the Corporation, even radio broadcasting was not successfully institutionalized to catch up with its Western counterparts. For a very young Republic like Turkey, radio was an integral part of the modernization and nation-building agenda of the early ruling elite and therefore it institutionalized as a part of the machinery of the state, under very strict state control. Much known indispensable merits of autonomy and independence attributed to the historical public service broadcasting model in Europe were hardly appreciated and supported in Turkey. Television broadcasting also had its share from this negative perception and had to face similar obstructions as radio from the beginning. This chapter traces the history of content regulation in television broadcasting by situating the political controversies at the center at different times from the 1960s until today. Unfortunately, as the saying goes, there is nothing new under the sun, not in Turkey.
Keywords: 1-TV; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Auteur.rice; 5-Auteur.rice PANDC; Turquie (corpus analysé); Turquie (lieu de production du savoir); _Nettoyé

Introduction: Turkey’s National Television in Transnational Context - Kaptan, Yeşim; Algan, Ece (Television in Turkey: Local Production, Transnational Expansion and Political Aspirations, 2020)
The Turkish television industry has undergone great transformation during the past three decades and enjoyed unprecedented success among national and transnational audiences alike. This chapter reconsiders the rise of Turkish television as a global player and an emerging national industry from a new theoretical perspective by situating Turkish television within the contemporary global developments of international television markets and within its own national history, economic, political, and cultural dynamics. By providing different examples of key turning points in its history, we offer a brief overview of TV production, distribution, and reception in Turkey since the beginning of the industry. We also illustrate how societal debates around television content, such as Turkish TV dramas (dizis), have ignited the question of representation and caused a struggle over official narratives, resulting in the entwining of the industry and production processes with politics. In our introductory chapter, we argue that with the increasing demand for content and the expansion of access to online TV platforms, emerging TV industries play an intricate and complex role in reshaping global television flows. Therefore, the case of the Turkish TV industry constitutes a significant example for understanding the current structural transformations in global television and sheds light on the interplay between national and transnational production, distribution, and reception processes.
Keywords: 1-TV; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice; Turquie (corpus analysé); _Nettoyé; États-Unis (lieu de production du savoir)

Media Power and Democratization in Brazil: TV Globo and the Dilemmas of Political Accountability - Porto, Mauro (Taylor & Francis, 2012)
This book analyzes the relationship between media power and democratization in transitional societies based on a case study about TV Globo, Brazil's largest media group.
OCLC: 1120933349
Keywords: 1-TV; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Amérique du Sud (corpus analysé); 4-Amérique du Sud (lieu de production du savoir); Brésil (corpus analysé); Brésil (lieu de production du savoir); _Nettoyé

Le soft power à l’épreuve de la réception. Le cas des fictions sérielles turques en Grèce - Larochelle, Dimitra Laurence (Réseaux, 2021)
La production de fictions sérielles turques est en constant développement. Ces fictions ont un très grand succès au niveau local (Tanriöver, 2011 ; Öztürkmen, 2018), avant d’être exportées au-delà des frontières turques depuis les années 2000, d’abord dans des pays sous l’influence culturelle de l’ancien Empire ottoman (à savoir les Balkans et le Moyen-Orient, puis au-delà (en Amérique latine, en Chine, au Pakistan, en Inde, au Bangladesh, etc.), faisant de la Turquie un leader mondial en matière de production et d’exportation. La Grèce est devenue un grand consommateur de fictions sérielles turques et les forts taux d’audience que ces dernières y réalisent ont conduit certains chercheurs à débattre du soft power turc. Plus précisément, en se basant sur les activités des fans des feuilletons en question (comme le tourisme en direction de la Turquie), certains ont soutenu que le visionnage des feuilletons turcs entraîne une amélioration des relations gréco-turques (Paris, 2013). En parallèle, de nombreux articles journalistiques, aussi bien en Grèce que dans d’autres pays, analysent le succès de ces feuilletons auprès du public grec comme une réussite diplomatique du gouvernement turc (Moore, 2013 ; Dimitrakopoulos, 2020).
Place: Paris
Keywords: 1-TV; 2-Approches sociologiques; 2-Étude de la réception; 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Europe (lieu de production du savoir); 5-Auteur.rice; France (lieu de production du savoir); Grèce (corpus analysé); Turquie (corpus analysé); _Nettoyé

South African Television Moves into the Global Age - Teer-Tomaselli, Ruth (The Routledge Companion to Global Television, 2019)
Television delivery throughout the world has changed rapidly over the past two decades. Within South Africa, much of this global narrative is repeated. The last 25 years saw a move from a single monopoly broadcaster within the ‘public service’ tradition (but later subsumed into the apartheid political agenda), to the present situation of a multi-company, multi-platform, increasingly digital delivery, calling into question even the very definition of ‘broadcasting’. ‘Global difference’ in South Africa plays out through a relatively late start but surprisingly short catch-up period, emphasizing a demographic/socio-economic specificity that has resulted in a highly skewed television market in which the uptake of high-end technology is less widespread than in other more ‘developed’ markets, and where the taste of local programming dominates even the technologically advanced sectors. The move toward a digital system, together with the introduction of competition, has provided challenges to the regulatory regime. The majority of the audience share, however, remains with local programming, regardless of its delivery.
Num Pages: 11
Keywords: 1-TV; 2-Approches sociologiques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 2-Étude des représentations; 3-Afrique (corpus analysé); 4-Afrique (lieu de production du savoir); 5-Auteur.rice; Afrique du Sud (corpus analysé); Afrique du Sud (lieu de production du savoir); _Nettoyé

Tactics of the Industry Against the Strategies of the Government: The Transnationalization of Turkey’s Television Industry - Algan, Ece (The Routledge Companion to Global Television, 2019)
Stuck between the political economy of the larger domestic television production industry and global market imperatives, I argue that Turkey’s TV industry executives and professionals had to develop and implement a number of tactics to achieve a locally based transnational cultural industry able to withstand both global and domestic pressures. In this chapter I identify three main tactics employed by Turkey’s TV industry executives and professionals to combat the socio-economic and political challenges they face: These tactics are: (1) carefully managing the content to skirt government restrictions; (2) adopting the government’s soft power discourse and public diplomacy aspirations by cooperating with government officials and businesses in their cultural promotion and nation-branding efforts; and (3) adapting to global TV trends by undertaking rigorous marketing and branding campaigns. A discussion of these tactics in the Turkish case can help us understand how culture industries in the developing world, which had to integrate into a neoliberal media environment after the 1980s due to market- and state-driven policies propelled mostly by US-based global media giants, negotiate being locally based transnational culture industries in the face of increasingly authoritarian and right-wing domestic political climates.
Num Pages: 13
Keywords: 1-TV; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice; Turquie (corpus analysé); _Nettoyé; États-Unis (lieu de production du savoir)

TV China: Control and Expansion - Zhu, Ying (The Routledge Companion to Global Television, 2019)
The chapter traces the evolution of Chinese television since 1958 from a state propaganda organ to a profit-generating media juggernaut, with China Central Television (CCTV) as the only network TV responding to both market principles and party directives. Commercialization and marketization played a major role in the rapid development of the Chinese television industry. In recent years China’s TV industry has witnessed the rise of private media companies and the rapid expansion of digital media and the proliferation of over the top (OTT) content. The chapter further provides an overview of China’s overall TV structures and teases out the relationship between CCTV and local stations. The most popular genre on Chinese TV is serial drama, which developed from predominantly single-episode anthology dramas in the 1980s to chiefly multi-episode serial dramas. Talk shows and reality TV became fashionable since the late 1990s.
Num Pages: 9
Keywords: 1-TV; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 4-Asie (lieu de production du savoir); 5-Auteur.rice; 5-Auteur.rice PANDC; Chine (corpus analysé); Hong Kong (lieu de production du savoir); _Nettoyé; États-Unis (lieu de production du savoir)

African Television in the Age of Globalization, Digitization, and Media Convergence - Eko, Lyombe (The Routledge Companion to Global Television, 2019)
African television is at the crossroads. This chapter surveys, describes, analyzes and explains the major changes that have taken place in the African television landscape since the 1990s. It focuses on three major developments that have marked the African television landscape: (1) liberalization of the television space to keep abreast of international developments, and the tension between entrenched governmental public broadcasting systems and newly licensed “independent” TV stations, (2) the process and impact of the analogue to digital TV switchover shepherded by the International Telecommunications Union, and (3) the diffusion of Chinese electronic technology, television, and film content on the African television market as part of the Asian giant’s “soft power” diplomacy and State capitalism. African television is constrained by political regimes that restrict freedom of expression, and regulatory agencies that preside over systems in which the law takes precedence over rights.
Num Pages: 15
Keywords: 1-TV; 2-Histoire/Historiographie critique; 2-Méthodologie de recherche décoloniale; 2-Étude des industries culturelles; 3-Afrique (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice noir.e; 5-Créateur.rice PANDC; _Nettoyé; États-Unis (lieu de production du savoir)

Structural Changes in the Ibero-American TV Market: Concentration and Convergence against Diversity? - Mastrini, Guillermo; Leiva, María Trinidad García (The Routledge Companion to Global Television, 2019)
This chapter examines the structural changes that can be identified in Ibero-American television in the first 15 years of the 21st century. Taking as a reference the main TV markets in the region (Mexico, Brazil, Argentina and Spain) and their peculiar historical developments, a brief introduction and overview describes their characteristics, potentials and limitations, underlining their strengths, weaknesses and challenges. The analysis, framed in the globalizing phase that cultural products and services are undergoing jointly with their increased digitization, suggests two fundamental drivers of change, summarized in the notions of concentration and convergence. To conclude, policies and recommendations for action are explored, with a view to promote and protect audiovisual diversity.
Num Pages: 10
Keywords: 1-TV; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Amérique du Sud (corpus analysé); 4-Amérique du Sud (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Auteur.rice; 5-Auteur.rice PANDC; Argentine (corpus analysé); Argentine (lieu de production du savoir); Brésil (corpus analysé); Espagne (corpus analysé); Espagne (lieu de production du savoir); Mexique (corpus analysé); _Nettoyé

Arab Television Industries: Enduring Players and Emerging Alternatives - Khalil, Joe F. (The Routledge Companion to Global Television, 2019)
This chapter provides an overview and analysis of emerging alternatives in the context of Arab television production, programming, and distribution. Media convergence and the access to digital technologies have accentuated the fragmentation of audiences, revenue streams, and forced alliances and competitions between previously discrete sectors of the media business. Yet, alternative practices are closely associated with changing political, economic, and cultural vectors in the Arab region and the increasing integration of its television industries in global media. The chapter argues that these alternatives constitute a set of continuities with the history of Arab television. Taken together, they also demonstrate some level of transformation in production practices, programming strategies, and distribution operations.
Num Pages: 10
Keywords: 1-TV; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; Qatar (lieu de production du savoir); _Nettoyé

Refashioning Chinese Television Through Digital Fun - Bai, Ruoyun (The Routledge Companion to Global Television, 2019)
This chapter discusses how Chinese television has been refashioned by the digital entertainment industry, and contends that new genres, identities, and representations have emerged in recognition of youths as the most valuable and desirable category of audience. It does so by way of three case studies. The first illustrates the symbiotic relationship between online literature and television drama production, and how the former contributes to the fantastical turn of Chinese television. The second seeks to understand the emergence of new cultural figures of “supreme heroine” and “sweet males” in the context of the rise of female fandom in contemporary Chinese popular culture. The third reveals how traditional television content, or in this case a political drama, may be recreated by online distributors and influencers so as to be aligned with the habits, attitudes, and preferences of the younger audiences. The chapter concludes that to understand contemporary Chinese television culture, the Internet and social media must become an integral component of inquiry because of their powerful remediating role in the public communication of any cultural text.
Num Pages: 12
Keywords: 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude de la réception; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice; 5-Auteur.rice PANDC; 5-Identités diasporiques; Canada (lieu de production du savoir); Chine (corpus analysé); _Nettoyé

Curating Life, Staging Art: Modernisms and the Art Practices of Television - Makhubu, Nomusa (The Routledge Companion to Global Television, 2019)
Television is predisposed to the perception that it is the opposite of art and politics and that it is a time-consuming means for “dumbing down,” placating, disempowering and benumbing the citizenry. Through a discussion of the place of art and that of television, I use, as a conceptual framework, the convergence of the white cube and the black box to interrogate dynamics of postcoloniality, vision and power and how this forged divergent modernisms. Television in Africa did not, as with postwar America, create a sense of collective communities of spectatorship that would be brought closer to art appreciation through television. Rather, television, as the political, social and cultural phenomenon of modernization in various African countries, seemed to corrupt what was regarded as “pristine” cultural practices. However, since it coincided with colonial independence and the emergence of postcolonial nations, it became intertwined with various modes and mediums through which new forms of social consciousness aimed at self-definition and self-representation could be disseminated. The convergence of the white cube spaces of art and the black box of television enables an engagement with the colonial spatio-temporal distanciation of Africa from the global stage.
Num Pages: 14
Keywords: 1-TV; 2-Approches sociologiques; 2-Méthodologie de recherche décoloniale; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Afrique (corpus analysé); 4-Afrique (lieu de production du savoir); 5-Auteur.rice; 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; Afrique du Sud (lieu de production du savoir); _Nettoyé

Transnational Screen Navigations: Priyanka Chopra’s Televisual Mobility in Hollywood - Singh, Pawan (The Routledge Companion to Global Television, 2019)
There was a time in Indian television when actors who had limited luck in the Hindi film industry would migrate to Indian television. By the 1990s, with the beginning of television’s transformation in India owing to economic liberalization, the converse was also occasionally true with former TV actors such as Shahrukh Khan and Vidya Balan becoming successful in Hindi cinema. The boundaries between Indian film and television were slowly becoming blurred toward the end of the twentieth century. Yet, the migration of stars from the big screen to the small was still considered a “failure” and the less common movement from television to film was deemed more successful. In the twenty-first century, however, television is no longer considered a consolation medium. The Hollywood television debut of the hugely successful Bollywood star Priyanka Chopra in a leading role on the TV show Quantico (USA, ABC, 2015–2018) and her subsequent numerous appearances on American television talk and award shows, including the Oscars, offer a prime example of television as a competitive medium for established stars. However, Chopra’s case is noteworthy for exemplifying not just star mobility between film and TV but also across national industries. Her move to American TV testifies to the increasing transnational viability of Bollywood stars in the twenty-first century. Importantly, the uptake of her rise on the American TV screen has been seen as part of the broader arrival of South Asian performers on American TV. But her success differs from Indian actors of American origin whose trajectory recapitulates the immigrant narrative of breaking free of stereotypical roles to play realistic, meaningful characters on the screen. Chopra’s representational currency and her “global” Indian English accent instantiate the logic of televisual mobility – her transnational screen navigations speak, not to a teleological moment of arrival on the American screen but her ability to make professional choices that enable her to represent Indians everywhere.
Num Pages: 14
Keywords: 1-TV; 2-Approches sociologiques; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 3-Asie (corpus analysé); 5-Auteur.rice PANDC; Inde (corpus analysé); _Nettoyé; États-Unis (corpus analysé)

Screening Right-Wing Populism in “New Turkey”: Neo-Ottomanism, Historical Dramas, and the Case of Payitaht Abdulhamid - Bulut, Ergin; İleri, Nurçin (The Routledge Companion to Global Television, 2019)
This chapter examines the intersection of popular culture and populism in Turkey by focusing on the TV show Payitaht Abdulhamid. Our motivation to analyze the recent TV series Payitaht Abdulhamid stems from our interest in the instrumental mobilization of popular culture for the Turkish government’s dual desire to both establish cultural hegemony and consolidate its populist style of government. Our analysis reveals that television, especially in the Global South, still plays a central role in governments’ desire to reconstruct history and establish cultural hegemony. This is particularly important as Turkey is going through a crisis of hegemony since the public is completely divided in its support for the government. Within the context of this hegemonic crisis, televised popular culture is vital, perhaps more than ever. Specifically, the show reduces a complicated history into easily understandable dichotomies and projects them on to contemporary politics in order to consolidate support for the government. Through televised popular culture, the government mobilizes history for purposes of cultural hegemony and populist politics flavored with nationalist, Islamist, and anti-Western motifs. Ultimately, the TV show presents yet another moment for understanding the mediated nature of 21st-century politics outside Western contexts.
Num Pages: 12
Keywords: 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Auteur.rice; 5-Créateur.rice PANDC; Turquie (corpus analysé); Turquie (lieu de production du savoir); _Nettoyé

Neoliberal Multiculturalism, Outsourced - Nadkarni, Asha (The Routledge Companion to Global Television, 2019)
This essay examines the 2010 NBC situation comedy Outsourced, with special attention to its representation of the racial politics surrounding business process outsourcing to India. Specifically, it discusses how Outsourced participates in what Jodi Melamed calls “neoliberal multiculturalism” to work through, symbolically and narratively, the realities and contradictions of globalized economies as they are experienced. By staging the dilemmas of outsourcing through the specter of the white male middle manager traveling to India to train Indian call center workers, Outsourced minimizes the affective labor necessarily performed by Indian call center workers and dramatizes outsourcing as a crisis of white U.S. masculinity alone. Moreover, it figures our white male protagonist as the global multicultural citizen to be emulated insofar as he models the appropriate attitude toward outsourcing and toward “other” cultures in general. Finally it suggests that the failure of the show has less to do with issues of cultural stereotyping and more to do with the failure of neoliberal multiculturalism to soothe anxieties around changing global economies.
Num Pages: 10
Keywords: 1-TV; 2-Approches sociologiques; 2-Méthodologie de recherche décoloniale; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice; 5-Créateur.rice PANDC; _Nettoyé; États-Unis (corpus analysé); États-Unis (lieu de production du savoir)

Venezuela : Fiction in the Dark - Alvarado, Morella; Torrealba, Luisa (Obitel 2020: Melodrama in Times of Streaming, 2020)
During 2019, various situations once again showed the deep crisis in the country. Audiovisual production continued, albeit with figures that account for a declining industry. Four productions were released: a first was made by the state channel (TVe), a second by a local independent producer (Oduver Cubillán and BGcreativos), the third was produced by the private channel (RCTV) and broadcast by the subscription channel IVC Networks, and the fourth was also produced by RCTV. While the first two productions did not exceed the 35-episode figure, the third and fourth had 73 episodes. On March 7, there was the biggest blackout in the country’s history. For more than a week, 95% of the territory was paralyzed by a lack of electricity. The action was classified by the government as an electric sabotage. The darkness that covered the country also subsumed serial fiction.
Keywords: 1-TV; 2-Approches sociologiques; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Sud (corpus analysé); 4-Amérique du Sud (lieu de production du savoir); 5-Auteur.rice; 5-Créateur.rice PANDC; Venezuela (corpus analysé); Venezuela (lieu de production du savoir); _Nettoyé

Uruguay: Ibero-American Fiction Loses Ground to Entertainment - Sánchez Vilela, Rosario; Gadea, Lucia (Obitel 2020: Melodrama in Times of Streaming, 2020)
A look at the screens of Uruguay’s open television in prime time will give the viewer a very reduced offer: after a television newscast that exceeds two hours long, there are only contest pro- grams, national or imported ones. It is possible that in the afternoon and at night the viewer finds a telenovela, almost always Turkish one. This is a very different panorama from the Uruguayan televi- sion history. Ibero-American fiction is in decline on open television, while its offer on VoD expands. In this chapter we will try to consider the various aspects of this landscape. Melodrama is on both options, open television and streaming, on a broad thematic spectrum, even in productions that are not usually classified as such. In the absence of national fiction in the period, at the end of the chapter we will study the melodrama in prison fiction, particularly in the case of El Marginal.
Keywords: 1-TV; 2-Approches sociologiques; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Sud (corpus analysé); 4-Amérique du Sud (lieu de production du savoir); 5-Auteur.rice; 5-Créateur.rice PANDC; Uruguay (corpus analysé); Uruguay (lieu de production du savoir); _Nettoyé

PORTUGAL: FTA and VoD: a generation gap - Burnay, Catarina Duff; Lopes, Perdo; de Sousa, Marta Neves; Félix, João; Carvalho, Ana Lúcia (Obitel 2020: Melodrama in Times of Streaming)

Peru: Social Issues and Comedy in Fiction - Cassano, Giuliana; Vásquez, Guillermo; Dettleff, James A. (Obitel 2020: Melodrama in Times of Streaming, 2020)
The country’s political crisis led to the confrontation between the Peruvian Congress and President Martín Vizcarra on irreconcil- able limits. After a second denial of confidence, Vizcarra made use of his constitutional prerogatives and dissolved Congress at the end of September 2019. The majority of the mass media step in line with the different positions of the Executive or the opposition, giv- ing much more attention to the political situation, thus modifying the TV programing. In this scenario, the Enfoca group – owner of Latina station – has continued looking for potential buyers, but without success yet. The conglomerate – with interest in financial, health and productive sectors – does not feel that the investment made in acquiring all the station’s shares seven years ago yielded the expected results. Meanwhile, Willax – a small locally held station acquired by the Wong group in 2015 with promises of a large investment – has become a stronghold of opposition to the government of Vizcarra and the largest broadcaster of Korean fictions. In February 2020, they an- nounced that a commercial partnership had been signed with South Korean company CJ ENM, a production company of several Korean dramas and the award-winning film Parasite, but without indicating what this company could mean for audiovisual production in Peru.
Keywords: 1-TV; 2-Approches sociologiques; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Sud (corpus analysé); 4-Amérique du Sud (lieu de production du savoir); 5-Autrice; Pérou (corpus analysé); Pérou (lieu de production du savoir); _Nettoyé

Mexico: The Melodrama on Netflix: Transformation or Evolution? - Orozco, Guillermo; Gómez, Gabriela; Franco, Darwin (Obitel 2020: Melodrama in Times of Streaming, 2020)
The high expectations of change caused by the victory of An- drés Manuel López Obrador for the presidency of Mexico have not been translated into any substantive modification in the Mexican media ecosystem or in the communication policies that have led the media-state relations in the country. However, what has been modi- fied/conditioned is the setting of the daily news agenda, since the new president has imposed a political-governmental communica- tion framework by holding morning press conferences, in which, with little opposition from the media, he sets the topics to be dis- cussed on a daily basis. It has created various problems with those media and/or journalists that have questioned the stances he has adopted, his plans and projects. The conflict escalated to such an extent that López Obrador has called his opponents “prensa fifí” (“snob press”), pointing out in a very clear way that these are ac- tors who only seek to defend the privileges lost during his govern- ment by conservative media, or, as he has called them: “la mafia del poder” (“the power mafia”).
Keywords: 1-TV; 2-Approches sociologiques; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; Mexique (corpus analysé); Mexique (lieu de production du savoir); _Nettoyé

Colombia: Melodrama Lives in Times of Streaming - Díaz, Fernando Aranguren; Bohórquez, Borys Bustamante; Riveros Solórzano, Hernán Javier (Obitel 2020: Melodrama in Times of Streaming, 2020)
The year 2019 in Colombia was characterized by the presence of a series of social and cultural phenomena of high impact on the population, such as the National Strike on November 21, when dif- ferent sectors expressed their disagreement with the country’s poli- cies and the reforms that were being proposed for the new year. This situation led to a leading presence of the news on the small screen and, at the same time, an interesting reflection of national identity, the needs of various Colombian social groups and the cul- tural matrices of the nation. In this hectic context and in accordance with a certain global climate of crisis in democratic and government systems, a highly interesting television phenomenon emerges: the highly successful reappearance of the programs that marked differ- ent generations of compatriots and that, as in the past, once again led families to discuss episodes and situations presented under the classical structure of melodrama.
Keywords: 1-TV; 2-Approches sociologiques; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Sud (corpus analysé); 4-Amérique du Sud (lieu de production du savoir); Colombie (corpus analysé); Colombie (lieu de production du savoir); _Nettoyé

Brazil: Time of Brazilian Streaming - Vassallo de Lopes, Maria Immacolata; Prezia Lemos, Ligia (Obitel 2020: Melodrama in Times of Streaming, 2020)
In 2019, the World Wide Web (www) celebrated its 30th anni- versary, However, the internet had not yet asserted itself as a right in the “network society” (Castells, 2009), and its balance points to the expansion of both opportunities and threats. Another fact that deserves to be highlighted in the year was the drop in the rating as a global phenomenon that challenges the television industry. It means change of habits and search for new business models. The integration of platforms and the generation of quality content appear as pillars of thetransformation of audiovisual worldwide. And the changes are manifested with a certain degree of diversity, according to the economic and cultural characteristics of each society, with disruptive processes.
Keywords: 1-TV; 2-Approches sociologiques; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Sud (corpus analysé); 4-Amérique du Sud (lieu de production du savoir); 5-Autrice; Brésil (corpus analysé); Brésil (lieu de production du savoir); _Nettoyé

Argentina: The Fall of Open TV Continues: Production Companies Bet on Platforms with Themes Regarding Marginality and Corruption - Aprea, Gustavo; Kirchheimer, Mónica S.; Rivero, Ezequiel A. (Obitel 2020: Melodrama in Times of Streaming, 2020)
Serial fiction released in Argentina in 2019 continues to fall. Only one telenovela had more than 200 chapters. To a lesser extent than the previous year, the supply of serialized fiction incorporated themes from the social agenda, especially feminist struggles and the visibility of sexual dissidence. The channels found in the co-produc- tion and in the production for platforms one of the ways in which fic- tion survives. Some of these programs are now on the open television screen. New fiction releases from Ibero-America are also falling.
Keywords: 1-TV; 2-Approches sociologiques; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Sud (corpus analysé); 4-Amérique du Sud (lieu de production du savoir); 5-Autrice; Argentine (corpus analysé); Argentine (lieu de production du savoir); _Nettoyé

Introduction: Ibero-American Fiction in the Midst of Political and Technological Changes: the Persistence of Melodrama as a Narrative Matrix - Aprea, Gustavo; Kirchheimer, Mónica S.; Rivero, Ezequiel A. (Obitel 2020: Melodrama in Times of Streaming, 2020)
This year, the Ibero-American Observatory of Television Fic- tion (Obitel) has dedicated special attention to the persistence of melodrama on screens in times of streaming and the proliferation of deprogrammed and multiscreen consumption. Obitel is made up of 12 countries that monitor the production and distribution of televi- sion fiction. For this yearbook, however, it was not possible to count on the participation of Ecuador, since it did not achieve the neces- sary conditions to work with the common methodology required. Chile, for its part, participated by providing data in order not to in- terrupt the historical series, but the analytical chapter corresponding to that country is not included either.
Keywords: 1-TV; 2-Étude des industries culturelles; 4-Amérique du Sud (lieu de production du savoir); 5-Autrice; Argentine (lieu de production du savoir); _Nettoyé

A Revolution in Television and a Great Leap Forward for Innovation?: China in the Global Television Format Business - Keane, Michael (Global Television Formats : Circulating Culture, Producing Identity, 2012)
Livre : For decades, television scholars have viewed global television through the lens of cultural imperialism, focusing primarily on programs produced in the US and UK markets and exported to foreign markets. This book explores how, thanks to recent technological innovation and globalization, television is now finally becoming truly global. Global Television Formats aims to revise the place of the global in television studies. The essays gathered here explore the diversity of global programming and approaches, and ask how to theorize contemporary
Keywords: 1-TV; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Océanie (lieu de production du savoir); Australie (lieu de production du savoir); Chine (corpus analysé); _Nettoyé

The Social and Political Dimensions of Global Television Formats: Reality Television in Lebanon and Saudi Arabia - Kraidy, Marwan (Global Television Formats: Understanding Television Across Borders, 2012)
When scholars and policy makers contemplate the Arab “media revolution,” they mostly think of Al-Jazeera and its news competitors. They are guided by the assumption that all-news satellite television networks are the predominant, even the single, shaper of the Arab public sphere, a perspective exacerbated by the September 11, 2001 attacks. Drawing on a larger work (Kraidy, 2009, forthcoming), this chapter presents an alternative view, emphasizing instead the combined impact of Arab entertainment television and small media such as mobile phones on Arab governance. It explores how entertainment television is an active contributor to shaping what Arab publics discuss and do in both the social and political realms. As local (in this case regional/pan-Arab, reaching two dozen Arabic-speaking countries) adaptations of global television formats, Arab reality television shows exhibit a combination of signs and practices from several worldviews. As such, this chapter will show how Arab reality shows are open to multiple processes of appropriation and redeployment. Though numerous scholars have for years studied the differentiated “reception” of television texts in various contexts, this chapter focuses speciﬁcally on television formats in a context of growing media convergence and protracted political instability and social upheaval. Speciﬁcally, it focuses on reality television’s social and political impact, which stems primarily from its activation of new communication processes between a variety of information and media technologies creating what I call “hypermedia space.” In the new Arab information order, reality television activates hypermedia space because it promotes participatory practices like voting, campaigning and alliance building, via mobile telephones and related devices.
Keywords: 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude de la réception; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; Arabie Saoudite (corpus analysé); Liban (corpus analysé); Qatar (lieu de production du savoir); _Nettoyé

Global Television Formats in Africa: Localizing Idol - Nkosi Ndlela, Martin (Global Television Formats: Understanding Television Across Borders, 2012)
During the last decade, popular television formats have been replicated across the globe for local or regional consumption as program imports, adaptations, clones or imitations, raising questions on the possible ramiﬁcations of such cultural inﬂows. For Africa the international program ﬂow and the inﬂuence of Western media content has been a contentious issue for decades, underlying the cultural imperialism thesis of the 1970s and 1980s, and the centre– periphery paradigms which conceptualized the series of dependency relationships. In African media research concepts like cultural colonialism, media imperialism, neocolonialism, Americanization, homogenization, have been used to denote the unequal ﬂow and inﬂuence of Western media products in Africa. Within the framework of media globalization some scholars have even propounded a scenario of the emergency of a global culture mediated by the dominant Western media. The central issues in African media discussions have mainly revolved around the ﬂow of ﬁnished media programs and their perceived detriment to local cultures and identities. What is missing in the African research literature is the attention to television formats, a phenomenon described by Keane et al. (2002) as a vehicle for localization, since what is imported is not the content itself, but a recipe for creating a local version. Global reality format shows thus create a new picture.
Keywords: 1-TV; 2-Approches sociologiques; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude de la réception; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Afrique (corpus analysé); 4-Europe (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; Afrique du Sud (corpus analysé); Ghana (corpus analysé); Nigéria (corpus analysé); Norvège (lieu de production du savoir); _Nettoyé

NZ Idol: Nation Building Through Format Adaptation - De Bruin, Joost (Global Television Formats: Understanding Television Across Borders, 2012)
Three seasons of NZ Idol , the New Zealand adaptation of the global Idols format, were aired on public broadcaster TVNZ’s channel TV2 in 2004, 2005 and 2006. The ﬁnal episode of the ﬁrst season was the most-watched television programme in New Zealand in 2004, with 1.4 million people, a third of the New Zealand population, tuning in (South Paciﬁc Pictures, 2004). In terms of ratings NZ Idol has been one of the most successful locally made television programmes of the last decade. At ﬁrst glance, NZ Idol has also been very successful in representing ethnic and cultural diversity. In the auditions phase of the show young New Zealanders of 16 years plus from a range of backgrounds are featured, and in the subsequent phases the audience gets to know a selection of them intimately. The winners of all three seasons (Ben Lummis in season 1, Rosita Vai in season 2, and Matt Sounoa in season 3) have Paciﬁc Island roots, and as a result three young “brown” people were crowned “New Zealand Idols.” This is remarkable, since according to a previous study by Misha Kavka (2004: 231) non-white people have largely been absent from New Zealand reality TV programmes. A closer look suggests, however, that featuring contestants from different cultural backgrounds in NZ Idol generally serves a particular nation building agenda that New Zealand is heavily involved in as a postcolonial society, in which ethnic minorities are subjected to representations that favour the interests of dominant cultural groups. The aim of this nation building agenda is to establish a new and distinct sense of national identity which will set New Zealand apart from Britain, the former colonial power, and other English-speaking nations.
Keywords: 1-TV; 2-Approches sociologiques; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude de la réception; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Océanie (corpus analysé); 4-Océanie (lieu de production du savoir); Aotearoa/Nouvelle-Zélande (corpus analysé); Aotearoa/Nouvelle-Zélande (lieu de production du savoir); _Nettoyé

Idol Worship: Ethnicity and Difference in Global Television - Sen, Biswarup (Global Television Formats: Understanding Television Across Borders, 2012)
The worldwide success of the Idol format may not require any explanation. We live under the ubiquitous sign of globalization; and hence it should come as no surprise that mass media— which together constitute an ecumenical vehicle of culture with an insatiable appetite for proﬁt— would generate forms (or formats) of art that travel with ease and are translatable into every context. The reception of these formats is, at one level, as unproblematic as its dissemination. To be global (and who isn’t?) is to be eagerly accepting of certain languages, technologies, discourses and styles. The craze surrounding competitive singing can then be explained as one more instance of borders proving permeable to the formulas of international popular culture. It is my argument that in order to understand the unique valence and signiﬁcance of global formats, we need to go beyond issues of production, distribution and reception, and focus instead on the phenomena that arise from their instantiation . This is so because implementing a format in a speciﬁc context has consequences that are neither written into the “program” nor purely derivable from local conditions. Let me provide an illustration. The call-in talk show has recently become a staple on Indian television. The format and content of these shows would be familiar to most Western viewers— a regular host, one or more “experts” discussing politics and culture, and a ﬁnal segment devoted to phone calls from the public.
Keywords: 1-TV; 2-Analyses formalistes; 2-Approches sociologiques; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Identités diasporiques; Asie du sud (corpus analysé); Inde (corpus analysé); _Nettoyé; États-Unis (corpus analysé); États-Unis (lieu de production du savoir)

Telenovelas in Brazil: From Traveling Scripts to a Genre and Proto-Format both National and Transnational - Straubhaar, Joseph (Global Television Formats: Understanding Television Across Borders, 2012)
In this chapter, we argue that there are several layers of genre, proto-format commercialization of program elements, and current commercially licensed formats. Some genre traditions, like melodrama, tend to be large, over-arching categories that already have a long history before television (Martín-Barbero 1993). Speciﬁc genres of television production, like the U.S. soap opera or the Latin American telenovela can develop within that larger tradition. Even more speciﬁc genres, like the Brazilian socially engaged or historical telenovelas, versus the romantic Mexican Cinderella story telenovela (Hernandez 2001), develop or emerge over time within those genre traditions. Television formats are now often distinguished as a parallel category which looks at forms of television that are packaged for licensing, transfer across cultures, and localized adaptation or implementation by regional, national or local networks. Speciﬁc formats are often imported and adopted. They can feed into genre development, grafted on to older traditions.
Keywords: 1-TV; 2-Analyses formalistes; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des industries culturelles; 3-Amérique du Sud (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); Brésil (corpus analysé); _Nettoyé; États-Unis (lieu de production du savoir)

‘Calling Out Around the World’: The Global Appeal of Reality Dance Formats - Heller, Dana (Global Television Formats: Understanding Television Across Borders, 2012)
In this chapter, I would like to consider how interactive reality television contributes to the negotiation between national particulars and transnational media ﬂows. Speciﬁcally, I want to look at the successful franchise So You Think You Can Dance , a dynamic global media ﬂashpoint and a remarkably adaptable format that serves as a site of pleasurable and contradictory engagement with the sense of national culture and community that television manufactures. But what makes the show of particular interest to me is that it allows audiences, in an increasing number of television markets around the world, to collectively determine their ideal national performers through a competition that requires mastery of a virtual international smorgasbord of popular dance forms and styles, the vast majority of which originate elsewhere, or from within the national, racial, and ethnic cultures of others. Second, in choosing to examine dance shows, I join with a growing number of scholars who have, over the past 15 years, argued for increased attention to dance as a primary site of knowledge production concerning bodies, identities, and representation.
Keywords: 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; Israël (corpus analysé); Proche-Orient (corpus analysé); Turquie (corpus analysé); _Nettoyé; États-Unis (corpus analysé); États-Unis (lieu de production du savoir)

More than Copycat Television: Format Adaptation as Performance - Navarro, Vinicius (Global Television Formats: Understanding Television Across Borders, 2012)
As a trend that captured the imagination of Brazilian audiences, the rapid proliferation of dance competitions on network television is meaningful not simply as a domestic phenomenon but also, and particularly, as an illustration of the mechanisms that enable the global popularity of formatted programs. While the shows were locally produced and relied on local talent, they were all based on formats that originated elsewhere, “imported ideas” that were recycled by Brazilian producers. References to foreign versions of the formats were also part of the discourses through which the domestic adaptations were described. As one show followed the other, they invited comparisons not only among themselves but also with their international counterparts. Yet, despite the association with foreign TV shows, the formats were easily incorporated to Brazil’s television culture, a feat that could surprise neither critics nor the industry.
Keywords: 1-TV; 2-Analyses formalistes; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 3-Amérique du Sud (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Identités diasporiques; Brésil (corpus analysé); _Nettoyé; États-Unis (lieu de production du savoir)

Interpreting Cubanness, Americanness, and the Sitcom: WPBT-PBS’s ¿Qué pasa U.S.A.? (1975–1980) - Rivero, Yeidy M. (Global Television Formats: Understanding Television Across Borders, 2012)
I was about 10 or 11 years old when I, together with my parents, religiously tuned in weekly to the situation comedy ¿Qué pasa U.S.A.? While I do not recall the speciﬁc year the show aired in Puerto Rico, I do remember that it was broadcast on WIPR-Channel 6, the island’s public television station. Watching one of my favorite sitcoms on what I then considered the boring channel was rather odd. However, I never thought it strange that the Peñas, ¿Qué pasa U.S.A.? ’s working-class three-generation Cuban/Cuban-American family, resided in Miami or that some of the characters communicated bilingually in English and Spanish. For me, ¿Qué pasa U.S.A.? was a show that resembled other locally produced situation comedies broadcast on commercial television, with the difference that the Peña family were Cuban immigrants who, instead of residing in Puerto Rico (like some of my childhood friends), lived in Miami (like many of my friends’ relatives). Probably as a result of the principal characters’ cultural references and their accents in Spanish, I decoded ¿Qué pasa U.S.A.? as a Cuban sitcom. Fast-forward to 2004. I was invited to write a 500-word encyclopedia entry on ¿Qué pasa U.S.A.? Without having any information on the show at hand, I immediately accepted. This was an opportunity to revisit a program I loved. After conducting the research I realized the uniqueness of ¿Qué pasa U.S.A.? Sponsored by the U.S. Ofﬁce of Education Emergency School Assistance Act– Television Program (ESAA-TV), ¿Qué pasa U.S.A.? —considered the ﬁrst bilingual situation comedy broadcast on U.S. television— addressed the culturalgenerational misunderstandings and the socio-cultural adjustments endured by the Peñas, a 1960 Cuban exile family.
Keywords: 1-TV; 2-Analyses formalistes; 2-Approches sociologiques; 2-Méthodologie de recherche décoloniale; 2-Étude de la réception; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; 5-Identités diasporiques; Cuba (corpus analysé); _Nettoyé; États-Unis (corpus analysé); États-Unis (lieu de production du savoir)

Introduction: American Game Studies - Jagoda, Patrick; Malkowski, Jennifer (American Literature, 2022)
In 2017, the American game designer Momo Pixel released the single-player, browser-based game Hair Nah. In this game, you play as Aeva, a Black woman taking trips to locations that include Osaka, Havana, and the Santa Monica Pier. As you move through levels on your journey—taking a taxi ride, traversing airport security, sitting on an airplane—you must slap away increasingly aggressive white hands that reach into the frame to touch your hair. Though Hair Nah taps into the genre of a casual button-mashing game, this interactive experience also explores the topic of microaggressions via unwanted hair touching. If you slap away enough hands on your travels, you reach a screen welcoming you to your destination with the message “YOU WIN!” but the caveat, “The game is over, but this experience isn’t. This is an issue that black women face daily. So a note to those who do it STOP THAT SHIT.”
Keywords: 1-Jeux vidéo; 2-Genre et sexualité; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice LGBTQ+; _Nettoyé

“My Whole Life I’ve Been on the Run”: Fugitivity as a Postracial Trope in Red Dead Redemption 2 - Marks, Katrina (American Literature, 2022)
This article discusses the popular video game Red Dead Redemption 2 (2018) by Rockstar Games, which follows Arthur Morgan, a white outlaw, during the decline of the “Wild West” in 1898 and 1899. Taking up conversations of fugitivity in critical ethnic studies, this article maintains that fugitivity operates as a rhetorical trope that stands in for racial identity where the logic of postracialism denies investments in race. Analyzing the narrative, spatial, and kinesthetic elements of the game, this article argues that Morgan, and by extension the player, is aligned with historically and geographically racialized others through a fugitive relationship to space. While Rockstar, as a video game studio, may not see itself explicitly intervening in a racialized and racializing political imaginary in its fictional worldbuilding, the kinesthetic, narrative, and cartographic strategies the studio employs respond to a set of cultural assumptions rooted in the rhetoric of postracialism. As such, Red Dead Redemption 2 serves as a multifaceted text through which to interrogate the dynamics of that rhetoric as it is mobilized in representations of fugitivity and identity.
Keywords: 1-Jeux vidéo; 2-Histoire/Historiographie critique; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; _Nettoyé

Reconsidering Lost Opportunities for Diverse Representation - Nguyen, Josef (American Literature, 2022)
This article considers the cultural politics of frustrated potential for diverse representation in games by examining developer comments on the 1995 digital game I Have No Mouth, and I Must Scream, adapted from Harlan Ellison’s 1967 science fiction story of the same name. While Ellison’s story featured a gay man named Benny among the protagonists, the game developers adapted Benny without his original sexual identity. In a 2012 Game Informer magazine article, however, the developers reflected on their version of Benny as a “lost opportunity” for exploring gay identity. Rooted in discussion of this frustrated potential for a gay in-game Benny, this article interrogates a logic of lost opportunity for diverse representation present in game-development discourse, which manifests in a longing for more diverse characters that could have been but never came to be. This logic suggests particular ways that developers might conceive of diverse representation as simply a design issue under neoliberal logics of economic opportunity, commercial risk, and fetishized innovation—without meaningful consideration of political significance. Opposing this instrumentalization of frustrated diverse representation, this article draws on queer game studies and speculative design and literature to explore the possible contours and implications of diverse characters that never were more seriously than such comments typically do. Doing so demands more than romanticized longings for lost opportunities for diverse representation that treat this longing as the end in itself.
Keywords: 1-Jeux vidéo; 2-Genre et sexualité; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé

Making Queer Asiatic Worlds: Performance and Racial Interaction in North American Visual Novels - Patterson, Christopher B. (American Literature, 2022)
This paper argues that video games expose the presumptions separating “Asian America” and “Asia” in the traditional senses of isolation, origination, and presumed distance. It does so by focusing on the most “Asiatic” genre of video games today, the North American visual novel, which offers a counterdiscourse to normative modes of play and attempts to offer utopic spaces to reflect upon the “real” genres of race and neo–Cold War geopolitics. Using theories of performance from Dorinne Kondo and others, the author shows how queer indie visual novels are primarily aspirational, in that they build queer, utopic, and seemingly anti-racist worlds through the Asiatic space of the visual novel form. In so doing, they also allow players to explore the Asiatic as a means of repairing the traumas and distances of American imperial cultures. The article analyzes four visual novels to make this argument: three by non-racially-identifying North American designers—Doki Doki Literature Club! (2017) by Dan Salvato, Analogue: A Hate Story (2012) by Christine Love, and Heaven Will Be Mine (2018) by Aevee Bee—and Butterfly Soup (2017), a game by the queer Asian/American designer Brianna Lei. If games make the boundaries of Asia and America irrelevant, visual novels explore this irrelevance through Asiatic irreverence.
Keywords: 1-Jeux vidéo; 2-Genre et sexualité; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Créateur.rice PANDC; _Nettoyé

The Mystery of the Missing AIDS Crisis: A Comparative Reading of Caper in the Castro and Murder on Main Street - Ruberg, Bo (American Literature, 2022)
This article addresses the seeming absence of the HIV/AIDS pandemic in video games from the 1980s and 1990s, the height of the US AIDS crisis. As Adrienne Shaw and Christopher Persaud have noted, stories about HIV/AIDS were pervasive across American popular media during this period, which also represented a boom in video game development. However, documentation remains of only a handful of early video games that mention HIV/AIDS. This article argues that, far from being absent from video game history, HIV/AIDS and the US AIDS crisis were actually influential in shaping a number of the design elements and narrative genres that have become important to contemporary video games. Scholars like Cait McKinney have demonstrated how people living with HIV/AIDS in America played a crucial part in the evolution of internet technologies that now form the backbone of video games. Through a comparative reading of two games by C. M. Ralph, Caper in the Castro (1989) and Murder on Main Street (1989), this article demonstrates how HIV/AIDS has also manifested in the content and form of video games, even (and perhaps especially) when it seems absent. Derritt Mason has explained how Caper in the Castro, widely celebrated as the first LGBTQ video game, contains clear echoes of the AIDS crisis. Yet, as this article demonstrates, HIV/AIDS remains a powerful presence even in Murder on Main Street, Ralph’s “straight version” of the game. Together, these games offer a microcosm through which to explore larger tensions between HIV/AIDS and video games, with the AIDS crisis representing a key element of what Cody Mejeur has termed the “present absence of queerness in video games.”
Keywords: 1-Jeux vidéo; 2-Genre et sexualité; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice LGBTQ+; _Nettoyé

L'Atelier de Courbet. Une énonciation du travail du peintre - Barbe, Noël (Le travail en représentations., 2005)
L'Atelier de Courbet a suscité de nombreuses interprétations qui s'ordonnent autour de quatre registres non-exclusifs : une expression sociale et politique, une approche stylistique, une théorisation de la position de l'artiste dans le monde, un autoportrait de Gustave Courbet. A côté de ces différents « jugements » qui opèrent par la recherche d'un ordre caché dans le tableau, il est ici approché de façon pragmatique comme ce qu'il déclare être : une tentative d'énonciation de son travail de peintre par Gustave Courbet. Si L'Atelier n'est pas un « vrai lieu », il s'agit bien pourtant de la figuration d'un système d'acteurs hétérogènes dont les interactions et les entre-définitions exprimées par la composition du tableau, font exister et tenir l'acte de peindre de Courbet. Si ce tableau n'est pas un cas isolé dans sa peinture qui se fait dans un rapport fondamental avec une réflexion sur l'acte de peindre, il prend cependant place dans une tentative de contournement des contraintes académiques pour s'imposer par la médiation de l'espace public.
Keywords: _Nettoyé

Du « dix-neuf » au « nineteen ». Une étude comparative des versions québécoise francophone et canadienne anglophone de la série télévisée 19-2 - Boisvert, Stéfany (Canadian Journal of Film Studies/Revue Canadienne d'études cinématographiques, 2016)
Cet article propose une étude comparative de la première saison de la série policière québécoise primée 19-2 (Ici Radio-Canada Télé, 2011-2015) et de son adaptation canadienne anglophone (Bravo, 2014-). L’étude des deux séries 19-2 permet d’investiguer, à travers un exemple récent, le processus d’adaptation télévisuelle au Canada. Les similitudes narratives et esthétiques entre les deux séries sont tout d’abord brièvement présentées: l’histoire et les arcs narratifs sont quasi identiques, la plupart des personnages conservent les mêmes noms, sans compter que les stratégies narratives marquantes de cette œuvres ont été pour la plupart reproduites dans la nouvelle version. Ces deux œuvres, appréhendées en tant que « performances » distinctes, sont ensuite analysées à travers le prisme du genre. L’analyse de quelques scènes clés et arcs narratifs permettra de démontrer que ces deux productions sont très différentes en ce qui concerne leur construction narrative de masculinités télévisées – particulièrement leur négociation différentielle de conceptions hégémoniques des identités – et leur représentation des rapports hommes-femmes.
Keywords: 1-TV; 2-Genre et sexualité; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; Canada (corpus analysé); Canada (lieu de production du savoir); _Nettoyé

Global Television Formats: Understanding Television Across Borders - Oren, Tasha; Shahaf, Sharon (Routledge, 2011)
Winner of the 2013 SCMS Best Edited Collection Award For decades, television scholars have viewed global television through the lens of cultural imperialism, focusing primarily on programs produced by US and UK markets and exported to foreign markets. Global Television Formats revolutionizes television studies by de-provincializing its approach to media globalization. It re-examines dominant approaches and their legacies of global/local and center/periphery, and offers new directions for understanding television’s contemporary incarnations. The chapters in this collection take up the format phenomena from around the globe, including the Middle East, Western and Eastern Europe, South and West Africa, South and East Asia, Australia and New Zealand, North America, South America, and the Caribbean. Contributors address both little known examples and massive global hits ranging from the Idol franchise around the world, to telenovelas, dance competitions, sports programming, reality TV, quiz shows, sitcoms and more. Looking to global television formats as vital for various cultural meanings, relationships, and structures, this collection shows how formats can further our understanding of television and the culture of globalization at large.

New Flows in Global TV - Moran, Albert (Intellect Books, 2009)
New Flows in Global TV provides a pioneering investigation into television distribution worldwide and the global trade in television program formats. Topics include explorations of how shows like Who Wants to Be a Millionaire? and Big Brother are reformatted for audiences in diverse markets such as Argentina, South Africa, the Middle East, and China; the international circulation of Dallas in the 1980s; and Australian and United Kingdom programming exports in the last decade. Moran argues that distribution is the crucial link in a chain that dictates the consumption and purchase of television content. Consequently, New Flows in Global TV will be a key text for scholars of global media, providing comprehensive insight into the cultural, social and economic exchanges underlying media programming.
Keywords: 1-TV; 2-Étude des industries culturelles; 3-Amérique centrale (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 3-Océanie (corpus analysé); 4-Océanie (lieu de production du savoir); Australie (lieu de production du savoir); _Nettoyé

Understanding the Global TV Format - Moran, Albert; Malbon, Justin (Intellect Books, 2006)
This volume presents a series of papers concerned with the interrelations between the postmodern and the present state of art and design education. Spanning a range of thematic concerns, the book reflects upon existing practice and articulates revolutionary prospects potentially viable through a shift in educative thinking.
Keywords: 1-TV; 2-Analyses formalistes; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Amérique du Nord (corpus analysé); 3-Europe (corpus analysé); 4-Océanie (lieu de production du savoir); Australie (lieu de production du savoir); _Nettoyé

McTV: Understanding the Global Popularity of Television Formats - Waisbord, Silvio (Television & New Media, 2004)
Globalization has intensified interconnectivity among television industries worldwide. Interconnectivity happens through structural and institutional linkages among television systems and industries worldwide, resulting in an increasingly integrated global business governed by similar practices and goals. The dynamics are reflected in the popularity of television formats. On the surface, global dissemination of formats may suggest not only the global integration of the economy of the industry but also the standardization of content. A dozen media companies are able to do business worldwide by selling the same idea, and audiences seem to be watching national variations of the same show. At a deeper level, however, formats attest to the fact that television still remains tied to local and national cultures. Bringing up examples of Latin American cases, this article argues that television is simultaneously global and national, shaped by the globalization of media economics and the pull of local and national cultures.
Keywords: 1-TV; 2-Approches sociologiques; 2-Étude de la réception; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 3-Europe (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Identités diasporiques; Argentine (corpus analysé); Brésil (corpus analysé); Mexique (corpus analysé); Royaume-Uni (corpus analysé); _Nettoyé; États-Unis (corpus analysé); États-Unis (lieu de production du savoir)

Planet TV: A Global Television Reader - Parks, Lisa; Kumar, Shanti (NYU Press, 2003)
From the 1967 live satellite program "Our World" to MTV music videos in Indonesia, from French television in Senegal to the global syndication of African American sitcoms, and from representations of terrorism on German television to the international Teletubbies phenomenon, TV lies at the nexus of globalization and transnational culture. Planet TV provides an overview of the rapidly changing landscape of global television, combining previously published essays by pioneers of the study of television with new work by cutting-edge television scholars who refine and extend intellectual debates in the field. Organized thematically, the volume explores such issues as cultural imperialism, nationalism, postcolonialism, transnationalism, ethnicity and cultural hybridity. These themes are illuminated by concrete examples and case studies derived from empirical work on global television industries, programs, and audiences in diverse social, historical, and cultural contexts. Developing a new critical framework for exploring the political, economic, sociological and technological dimensions of television cultures, and countering the assumption that global television is merely a result of the current dominance of the West in world affairs, Planet TV demonstrates that the global dimensions of television were imagined into existence very early on in its contentious history. Parks and Kumar have assembled the critical moments in television's past in order to understand its present and future. Contributors include Ien Ang, Arjun Appadurai, Jose B. Capino, Michael Curtin, Jo Ellen Fair, John Fiske, Faye Ginsburg, R. Harindranath, Timothy Havens, Edward S. Herman, Michele Hilmes, Olaf Hoerschelmann, Shanti Kumar, Moya Luckett, Robert McChesney, Divya C. McMillin, Nicholas Mirzoeff, David Morley, Hamid Naficy, Lisa Parks, James Schwoch, John Sinclair, R. Anderson Sutton, Serra Tinic, John Tomlinson, and Mimi White.
Keywords: 1-TV; 2-Approches sociologiques; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude de la réception; 2-Étude des industries culturelles; 2-Étude des représentations; 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; 5-Identités diasporiques; _Nettoyé

Television, Globalization and Cultural Identities - Barker, Chris (Open University Press, 1999)
* Are cultural identities socially constructed? * How are race, nation, sex and gender constructed and represented on television? * What is the impact of globalization on television and cultural identities? This introductory text examines issues of television and cultural identities in the context of globalization. It is a wide-ranging volume, exploring many of the central cultural issues in contemporary cultural studies, such as media, globalization, language, gender, ethnicity, cultural politics and identity - perhaps the topic of cultural studies over the past decade. At the core of the book are two critical arguments - that television is a proliferating resource for the construction of cultural identity, and that cultural identity is not a fixed essential 'thing' but a contingent social construction to which language is central. The book will be essential reading for undergraduate and postgraduate courses on television and cultural identities in the fields of cultural studies, communications, media studies and sociology, with a wider appeal to those with an interest in the television industry. Key concepts are introduced and explained for those new to cultural studies, whilst debates are extended and enriched for those already familiar with them. The text is well structured, links the vocabularies of media studies and cultural studies, and is supported by original case study material.
Keywords: 1-TV; 2-Approches sociologiques; 2-Étude de la réception; 4-Océanie (lieu de production du savoir); Australie (lieu de production du savoir); _Nettoyé

Copycat Television: Globalisation, Program Formats, and Cultural Identity - Moran, Albert (University of Luton Press, 1998)
"Addressing both the scope and the significance of television program format transferthe practice of using the basic idea of a program to produce a new version of that programthis book details this rapidly growing area of the international television distribution system. Also addressed is the remaking of a program by the television industry of another nation, highlighting issues of meaning and cultural identity of national audiences."
Keywords: 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude de la réception; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Europe (corpus analysé); 4-Océanie (lieu de production du savoir); Allemagne (corpus analysé); Australie (corpus analysé); Australie (lieu de production du savoir); Pays-Bas (corpus analysé); _Nettoyé

Global Television: An Introduction - Barker, Chris (Wiley-Blackwell, 1997)
This text provides readers with useful summaries and evaluations of key arguments relating to the development of television as an industry across the globe and its potential cultural impact. There is a continual insistence in the book on the need to connect issues of industry with those of culture.
Keywords: 1-TV; 2-Approches sociologiques; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude de la réception; 2-Étude des industries culturelles; 2-Étude des représentations; 4-Océanie (lieu de production du savoir); Australie (lieu de production du savoir); _Nettoyé

Channels of resistance: global television and local empowerment - Dowmunt, Tony (BFI Publishing in association with Channel Four Television, 1993)
Keywords: 1-TV; 2-Approches sociologiques; 2-Méthodologie de recherche décoloniale; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 3-Océanie (corpus analysé); 4-Europe (lieu de production du savoir); Angleterre (lieu de production du savoir); Australie (corpus analysé); Brésil (corpus analysé); Canada (corpus analysé)

Cross-Dressing and Transgender Representation in Swedish Cinema, 1908–2017 - Horak, Laura (European Journal of Scandinavian Studies, 2017)
Today’s explosion of Swedish films made by and about transgender people is sometimes considered in a vacuum. This article explores the long history of cross-gender performance in Swedish cinema and the relationship of these new films to older traditions. In this article, I will outline the contours of cross-gender performance in Swedish films from the 1908 to today, using some exemplary films to display the variety of styles, genres, and meanings that can be found: the short dance film Dances Through the Ages ( Skilda tiders danser , Walfrid Bergström, 1909); the swashbuckler Lasse-Maja (Gunnar Olsson, 1941); the romantic comedy Up With Little Märta ( Fram för Lilla Märta , Hasse Ekman, 1945); the dramatic art film The Magician ( Ansiktet , Ingmar Bergman, 1958); the recent romantic comedy Cockpit (Mårten Klingberg, 2012); and the trans art film Everything Falls Apart ( Nånting måste gå sönder , Ester Martin Bergsmark, 2016). I will show that the two main shifts in Swedish cinema’s representation of cross-gender performance occurred in the mid-1950s and in the 1990s, due to social changes and changes in the structure of the Swedish film industry. In Swedish cinema, as elsewhere, cross-dressing has never meant any one thing, so we must attend to the specific contexts of its expression in order to understand what it meant.
Keywords: 1-Cinéma; 2-Genre et sexualité; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Europe (corpus analysé); 5-Créateur.rice LGBTQ+; _Nettoyé

Undercurrents: Queer Culture and Postcolonial Hong Kong - Hok-Sze Leung, Helen (UBC Press, 2009)
Undercurrents engages the critical rubric of "queer" to examine Hong Kong's screen and media culture during the transitional and immediate postcolonial period. Helen Hok-Sze Leung draws on theoretical insights from a range of disciplines to reveal parallels between the crisis and uncertainty of the territory's postcolonial transition and the queer aspects of its cultural productions. Leung explores Hong Kong cultural productions – cinema, fiction, popular music and subcultural projects – and argues that while there is no overt consolidation of gay and lesbian identities in Hong Kong culture, undercurrents of diverse and complex expressions of gender and sexual variance are widely in evidence. Undercurrents uncovers a queer media culture that has been largely overloo... Source: Publisher
Keywords: 1-Cinéma; 2-Genre et sexualité; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); _Nettoyé

Revisitation: A Transgender Phenomenology of the Media Image - Keegan, Cáel M. (MedieKultur: Journal of Media and Communication Research, 2016)
How might certain moving images move us into transgender becoming? Th e recent proliferation of transgender images in the media of the Global North has been widely regarded as supporting transgender political and social equality.
Keywords: 1-Cinéma; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude des représentations; 4-Amérique du Nord (lieu de production du savoir); _Nettoyé

Crossdressing Cinema: An Analysis of Transgender Representation in Film - Miller, Jeremy Russell (2012)
Transgender representations generally distance the transgender characters from the audience as objects of ridicule, fear, and sympathy. This distancing is accomplished through the use of specific narrative conventions and visual codes. In this dissertation, I analyze representations of transgender individuals in popular film comedies, thrillers, and independent dramas. Through a textual analysis of 24 films, I argue that the narrative conventions and visual codes of the films work to prevent identification or connection between the transgender characters and the audience. The purpose of this distancing is to privilege the heteronormative identities of the characters over their transgender identities. This dissertation is grounded in a cultural studies approach to representation as constitutive and constraining and a positional approach to gender that views gender identity as a position taken in a specific social context. Contributions are made to the fields of communication, film studies, and gender studies through the methodological approach to textual analysis of categories of films over individual case studies and the idea that individuals can be positioned in identities they do not actively claim for themselves. This dissertation also makes a significant contribution to conceptions of the gaze through the development of three transgender gazes that focus on the ways the characters are visually constructed rather than the viewpoints taken by audience members. In the end, transgender representations work to support heteronormativity by constructing the transgender characters in specific ways to prevent audience members from developing deeper connections with them.
Accepted: 2012-10-19T15:30:33Z
Keywords: 1-Cinéma; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude des représentations; 4-Amérique du Nord (lieu de production du savoir); _Nettoyé

The Gendered Screen: Canadian Women Filmmakers - Austin-Smith, Brenda; Melnyk, George (Wilfrid Laurier University Press, 2010)
Discussions of established women filmmakers whose careers have produced major bodies of work, as well as newer filmmakers and new media artists.
OCLC: 729021166
Keywords: 1-Cinéma; 2-Genre et sexualité; 2-Étude des industries culturelles; 2-Étude des représentations; 5-Créatrice; _Nettoyé

Gendering the Nation Canadian Women's Cinema - Armatage, Kay; Banning, Kass; Longfellow, Brenda (University of Toronto Press, 2016)
Since Nell Shipman wrote and starred in Back to God's Country (1919), Canadian women have been making films. The accolades given to film-makers such as Patricia Rozema (I've Heard the Mermaids Singing, When Night is Falling), Alanis Obomsawin (My Name Is Kahenttiiosta, Walker), and Micheline Lanctot (Deux Actrices) at festivals throughout the world in recent years attest to the growing international recognition for films made by Canadian women. With Gendering the Nation the editors have produced a definitive collection of essays, both original and previously published, that address the impact and influence of a century of women's film-making in Canada. In dialogue with new paradigms for understanding the relationship of cinema with nation and gender, Gendering the Nation seeks to situate women's cinema through the complex optic of national culture. This collection of critical essays employs a variety of frameworks to analyse cinematic practices that range from narrative to documentary to the avant garde.
OCLC: 944178123
Keywords: 1-Cinéma; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude des représentations; 4-Amérique du Nord (lieu de production du savoir); 5-Créatrice; _Nettoyé

Alanis Obomsawin the Vision of a Native Filmmaker - Lewis, Randolph (University of Nebraska Press, 2006)
In more than twenty powerful films, Abenaki filmmaker Alanis Obomsawin has waged a brilliant battle against the ignorance and stereotypes that Native Americans have long endured in cinema and television.
OCLC: 1200868429
Keywords: 1-Cinéma; 2-Approches sociologiques; 2-Épistémologies autochtones; 2-Étude des représentations; 4-Amérique du Nord (lieu de production du savoir); 5-Créateur.rice autochtone; _Nettoyé

Decolonizing the Lens of Power: Indigenous Films in North America - Kerstin, Knopf (Rodopi, 2008)
Knopf samples a variety of Native American filmmaking genres, including documentary, short films, and full-length narrative films, providing a detailed synopsis and content analysis of several films. Since its genesis in the early 19005, film has been an effective colonizing tool, impacting Indigenous peoples around the globe.
Issue: 4 Pages: 611-614
Keywords: 1-Cinéma; 2-Approches sociologiques; 2-Méthodologie de recherche décoloniale; 2-Épistémologies autochtones; 2-Étude des représentations; 4-Amérique du Nord (lieu de production du savoir); 5-Créateur.rice autochtone; _Nettoyé

New Black Queer Cinema - Wallenberg, Louise (New Queer Cinema: A Critical Reader, 2004)
In 1989, three years before the New Queer Wave was even invented or discovered, two very different yet interconnected films were produced on either side of the Atlantic. Both soon became critically successful and both would win a number of prizes at different international film festivals and venues. In retrospect, these two films have come to constitute the very incitement to the Wave. British filmmaker Isaac Julien’s Looking for Langston premiered in early 1989 and American filmmaker Marlon Riggs’s Tongues Untied premiered later that same year, the latter including a still photo from the former so as to pay homage
Keywords: 1-Cinéma; 2-Genre et sexualité; 2-Étude des industries culturelles; 2-Étude des représentations; 4-Amérique du Nord (lieu de production du savoir); _Nettoyé

Migrating to the Movies: Cinema and Black Urban Modernity - Stewart, Jacqueline Najuma (University of California Press, 2005)
The rise of cinema as the predominant American entertainment around the turn of the last century coincided with the migration of hundreds of thousands of African Americans from the South to the urban "land of hope" in the North. This richly illustrated book, discussing many early films and illuminating black urban life in this period, is the first detailed look at the numerous early relationships between African Americans and cinema. It investigates African American migrations onto the screen, into the audience, and behind the camera, showing that African American urban populations and cinema shaped each other in powerful ways. Focusing on Black film culture in Chicago during the silent era, Migrating to the Movies begins with the earliest cinematic representations of African Americans and concludes with the silent films of Oscar Micheaux and other early "race films" made for Black audiences, discussing some of the extraordinary ways in which African Americans staked their claim in cinema's development as an art and a cultural institution.
Keywords: _Nettoyé

Our Stories Have Never Been Told: Preliminary Thoughts on Black Lesbian Cultural Production as Historiography in The Watermelon Woman - Richardson, Matt (Black Camera, 2011)
Cheryl Dunye's 1996 film The Watermelon Woman earned a place in cinematic history as the first feature-length narrative film written and directed by an out black lesbian about black lesbians. This article examines how the film provides an important opportunity to mark the burgeoning genre of black queer documentary as a historiographical medium. The documentary film is a tool that highlights underexplored issues in black experience and provides a cultural site for imagining new possibilities for black lesbian subjectivity and creating innovative approaches to representing sexuality in black filmmaking.
Keywords: 1-Cinéma; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude des industries culturelles; 2-Étude des représentations; 4-Amérique du Nord (lieu de production du savoir); 5-Créateur.rice LGBTQ+; 5-Créateur.rice noir.e; _Nettoyé

Pink Dollars: Gay and lesbian Film Festivals and the Economy of Visibility - Rhyne, Ragan (2007)
This dissertation is about gay and lesbian film festivals, the first of which was founded in San Francisco in 1977 and subsequently served as a model for their international proliferation over the next thirty years. While the films programmed in these festivals have received a great deal of attention from scholars and critics, the festival institution itself has received less consideration. This dissertation narrates the history of gay and lesbian film festivals through an economic lens, asking how fundraising practices have been deployed in the community building projects of festivals, how the administrative structures of festivals as nonprofit organizations have been leveraged by the state toward the management of new social movements, and how these nonprofits have participated in the identification and cultivation of populations as niche markets by the commercial sector. This historical schema will offer an alternative model for understanding queer image production, not through a textual analysis of those images, but through an examination of the material circumstances of their circulation and distribution. This dissertation is not simply about the ways that community organizations like film festivals have been strategically engaged by the state and the market in the management and exploitation of gays and lesbians, it argues that gays and lesbians themselves have articulated their politics, artistic practice, and discourse of community within (and against) the parameters defined by the demands of organizational sustainability. Furthermore, this dissertation will illustrate why taking economic activity seriously as a part of the material practices of queer image production answers crucial questions about the ways that sexuality operates as a category of governance. The history of gay and lesbian film festivals, and their regulation through the administrative structures of the nonprofit sector, is part of a much larger history of political struggle and the development of new social movements over the past three decades.
Keywords: 1-Cinéma; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Étude de la réception; 2-Étude des industries culturelles; 4-Amérique du Nord (lieu de production du savoir); _Nettoyé

New Queer Cinema and Lesbian Films - Pick, Anat (New Queer Cinema: A Critical Reader, 2004)
The immediate aim of this chapter is to provide a critical overview of the place of lesbian films within New Queer Cinema. The task is not an easy one in a field which is as contentious as it is broad. The main difficulty seems to be how best to approach a range of definitions, from ‘new’ to ‘queer’ to ‘lesbian’, since with every one of them, we risk biting off more than we can chew. As often happens with formal titles, so with the New Queer Cinema, its lifespan (‘officially’ 1992-2000) now seems to have been a great deal shorter
Keywords: 1-Cinéma; 2-Approches sociologiques; 2-Étude des industries culturelles; 2-Étude des représentations; 4-Europe (lieu de production du savoir); _Nettoyé

Struggles for Representation: African American Documentary Film and Video - Reid, Mark A. (American Literature, 2000)
Struggles for Representation examines over 300 non-fiction films by more than 150 African American film/videomakers and includes an extensive filmography, bibliography, and excerpts from interviews with film/videomakers. In eleven original essays, contributors explore the extraordinary scope of these aesthetic and social documents and chart a previously undiscovered territory: documentaries that examine the aesthetic, economic, historical, political, and social forces that shape the lives of black Americans, as seen from their perspectives.
Keywords: 1-Cinéma; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Étude des industries culturelles; 2-Étude des représentations; 4-Amérique du Nord (lieu de production du savoir); _Nettoyé

From a Real Place and Real People: Interview with Mississippi Damned Writer/Director Tina Mabry - Moore, Marlon Rachquel (Black Camera, 2011)
Marlon Rachquel Moore interviews emerging independent filmmaker Tina Mabry about her southern upbringing, racial and sexual consciousness, and the joys and turbulence of bringing her first feature-length film, Mississippi Damned, to the silver screen. Mississippi Damned is based on Mabry's family and set in her hometown of Tupelo, Mississippi.
Keywords: 1-Cinéma; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Créateur.rice noir.e; _Nettoyé

The Witch’s Flight: The Cinematic, the Black Femme, and the Image of Common Sense - Keeling, Kara (Duke University Press, 2007)
Kara Keeling contends that cinema and cinematic processes had a profound significance for twentieth-century anticapitalist Black Liberation movements based in the United States. Drawing on Gilles Deleuze’s notion of “the cinematic”—not just as a phenomenon confined to moving-image media such as film and television but as a set of processes involved in the production and reproduction of social reality itself —Keeling describes how the cinematic structures racism, homophobia, and misogyny, and, in the process, denies viewers access to certain images and ways of knowing. She theorizes the black femme as a figure who, even when not explicitly represented within hegemonic cinematic formulations of raced and gendered subjectivities, nonetheless haunts those representations, threatening to disrupt them by making alternative social arrangements visible.
Keywords: 1-Cinéma; 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Étude des représentations; 4-Amérique du Nord (lieu de production du savoir); _Nettoyé

Lesbian "Making-of" Documentaries and the Production of Lesbian Sex - Hankin, Kelly (The Velvet Light Trap, 2004)
The Velvet Light Trap 53 (2004) 26-39 On December 2, 2001, HBO began airing Project Greenlight, a twelve-part documentary series chronicling the production of a feature film by novice writer-director Pete Jones. With its spectacle of backroom dealings, unchecked egos, and human frailties, the television series capitalized on the contemporaneous success of like-minded "reality" programs such as Survivor and Temptation Island. Perhaps more closely, Project Greenlight also tapped into the current vogue for the "behind-the-scenes" and the "making-of" genres, represented by straight-to-video titles such as Star Trek-Deep Space Nine: Behind the Scenes (1993), Making of Jurassic Park (1995), and The Matrix Revisited (2001), television programs such as the Sundance Channel's Anatomy of a Scene, HBO's First Look, and MTV's Making the Video, and the proliferation of behind-the-scenes and making-of packaging on DVDs. A reflection of the growth of film-related ancillary products in the 1980s, the ever-expanding Hollywood ego, and the demands of a twenty-four-hour television cable market, the increased appearance of the making-of documentary format no doubt also reflects the renewed interest in amateur filmmaking promulgated by the age of desktop video. Perhaps as a manifestation of this interest, making-of documentaries have become increasingly more detailed in their coverage. Whereas the 1981 television special The Making of "Raiders of the Lost Ark" (Phillip Schuman) focuses mostly on the film's stunt work, special effects, location shoots, and set design, the recently released making-of documentary The Matrix Revisited focuses on script development, preproduction, production, postproduction, and exhibition, introducing viewers to costume designers, storyboard artists, and editors along the way. This attention to production detail can also be seen in Sundance's Anatomy of a Scene, which hones in on the construction, from music to costume to camera work, of a single scene. And certainly raising the bar on the level of detail included in the making-of genre is Project Greenlight, which is a "warts-and-all" look at film production, from squabbles over budgets to catering fiascos. Despite the making-of video's increased attention to the minutiae of filmmaking, one of the areas that remains outside the purview of most Hollywood making-of documentaries is the production of sex. Discussions about the cinematic logistics of creating a sex scene—how, when, and with what resources—are usually not featured in making-of documentaries. Of course, given our celebrity-driven culture, the question of sex vis-à-vis film production, particularly a Hollywood film production, is hardly absent from the publicity that surrounds a film. It is not uncommon to hear actresses or actors discussing what it was like to kiss another actor on the set. But these kinds of concerns are usually the province of entertainment magazines and television, not the province of ancillary related products such as the making-of video. While stories of roles requiring nudity or sex scenes abound on television shows such as Access Hollywood, Entertainment Tonight, and E! News Daily,these kinds of topics are less likely to appear in production-generated documentaries. Indeed, while the production of the provocative sex scene between Halle Berry and Billy Bob Thornton in Monster's Ball (Marc Forster, 2001) generated much discussion on television entertainment programs, talk shows, and newsmagazines, it was the film's prison execution sequence that was featured in the Sundance Channel's making-of special on the film. Given the lack of focus on sex scenes in most making-of documentaries, it is interesting to note that the two existing making-of documentaries for lesbian-made, lesbian-themed feature films—The Making of Bar Girls (1995) and Moments: The Making of Claire of the Moon (1992)—both heavily focus on the production of lesbian sex. Moreover, both lesbian making-of documentaries emphasize the cast's and the crew's sexual titillation over the creation of sexual sequences. In this essay I look at what this strategy reveals about the collective climate and concerns of lesbian feature filmmaking in the United States today.
Keywords: 1-Cinéma; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude des industries culturelles; 2-Étude des représentations; 4-Amérique du Nord (lieu de production du savoir); 5-Créateur.rice LGBTQ+; 5-Créateur.rice noir.e; _Nettoyé

Provincializing Hegemonic Histories of Media and Communication Studies: Toward a Genealogy of Epistemic Resistance in Africa - Willems, Wendy (Communication Theory, 2014)
In the late 1990s and 2000s, a number of calls were made by scholars to “internationalize” or “dewesternize” the field of media and communication studies. I argue that these approaches have indirectly silenced a much longer disciplinary history outside “the West” that has not only produced empirical knowledge but has also actively challenged Western epistemologies. This article seeks to reinscribe the epistemological and historical foundations of media and communication studies in Africa. By framing the research of African media and communication scholars within the changing nature of knowledge production, shifting power relations between African nations, and the evolving role of African universities, I demonstrate how academic knowledge production is frequently driven and constrained by particular dominant social, political, and economic interests.
_eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1111/comt.12043
Keywords: 1-Cinéma; 1-TV; 2-Méthodologie de recherche décoloniale; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Afrique (corpus analysé); 4-Europe (lieu de production du savoir); _Nettoyé

De-Westernization and Cosmopolitan Media Studies - Waisbord, Silvio (Internationalizing "International Communication", 2015)
The call for the “De-Westernization” (Curran & Park, 2000) of media studies hasattracted much attention in recent years. It is generally associated with the need to giveserious considerations to media systems outside the West. This paper critically reviewsthe meaning of “de-Westernization,” and argues that the main challenge is not simply to broaden the geographic scope by considering cases from the global South. The inclusionof non-Western cases could lead to the consolidation of “area studies”, a balkanizedresearch that may not contribute to a common set of questions and unifying theories.Instead, it is necessary to approach de-Westernization in order to promote cosmopolitanscholarship, an analytical approach that is open to the globalization of problems andacademic production. Rather than being constrained by geographical divisions, de-Westernization should help to expand analytical perspectives and brings theoretical andcomparative questions to the forefront of media studies.
Keywords: 1-Cinéma; 1-TV; 2-Approches sociologiques; 2-Théories et épistémologie postcoloniales et décoloniales; 4-Amérique du Nord (lieu de production du savoir); _Nettoyé

Examining Professional and Academic Culture in Chilean Journalism and Mass Communication Education - Mellado, Claudia (Journalism Studies, 2011)
This article discusses key findings from a survey of the professional patterns, scholarly productivity, and educational characteristics of Chilean Journalism and Mass Communication (JMC) educators, as well as documentary information about the schools where they work. The results reveal a weak academic culture that contrasts with a strong professional culture among the members of this community, but also the influence that both organizational and individual variables have on Chilean JMC educators' orientations. Specifically, the analyses indicated that the level of education, part-time/full-time commitment, and the type of university are the most influential factors in defining both the prevalence of a professional culture and the lack of research productivity. These findings support other international studies, indicating a global tendency across key variables that influence academic development in the field. Likewise, it shows how distant Chilean JCM educators are from the university-scholarly tradition.
_eprint: https://doi.org/10.1080/1461670X.2010.507373
Keywords: 2-Analyses formalistes; 2-Approches sociologiques; 2-Étude des industries culturelles; 3-Amérique du Sud (corpus analysé); 4-Europe (lieu de production du savoir); _Nettoyé

De- Westernizing Media Theory to Make Room for African Experience - Nyamnjoh, Francis B. (Popular Media, Democracy and Development in Africa, 2010)
How should one think about popular media in the African context? Should we attempt to understand and analyse the increasing proliferation of tabloids, reality television shows, pop music, websites and mobile communications through the analytical frameworks constructed by scholars in the Global North, or does Africa pose unique research questions? Is there a danger of either essentializing Africa by treating her as ‘different’, or by ignoring her specificity by approaching her media via Western theoretical constructs? The scholar wishing to understand the interface between popular media, development and democracy in contemporary African societies is faced with a complex double bind. Elsewhere (Nyamnjoh 2005: 2-3) I have argued that African worldviews and cultural values are doubly excluded from global media discourses, first by the ideology of hierarchies and boundedness of cultures, and second by cultural industries more interested in profits than the promotion of creative diversity and cultural plurality. Little attention is accorded to how Africans negotiate and navigate the various identity margins and cultural influences in their lives, in ways that are not easily reducible to simple options or straightforward choices. The consequence of rigid dichotomies or stubborn prescriptiveness based on externally induced expectations of social transformation is an idea of democracy hardly informed by popular articulations of personhood and agency in Africa, and media whose professional values and content are not in tune with the expectations of those they purport to serve. The predicament of media practitioners in such a situation, as well as those wishing to understand African media practice through media theory, is obvious: to be of real service to liberal democracy and its expectations of modernity, they must ignore alternative ideas of personhood and agency in the cultural communities within which such practices take place and of which such practitioners and, often, scholars form part. Attending to the interests of particular cultural groups as strategically essential entities risks contradicting the principles of liberal democracy and its emphasis on civic citizenship and the autonomous individual, which media practitioners in African societies are being held accountable to.
Num Pages: 13
Keywords: 1-Cinéma; 1-TV; 2-Approches sociologiques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Théories et épistémologie postcoloniales et décoloniales; 3-Afrique (corpus analysé); 4-Europe (lieu de production du savoir); 5-Auteur.rice noir.e; 5-Identités diasporiques; _Nettoyé

Transnational Communication as Deliberation, Ritual, and Strategy - Brüggemann, Michael; Wessler, Hartmut (Communication Theory, 2014)
Globalized communication flows transcend and transform national borders. Transnational media outlets targeting audiences around the globe, issues of global concern are subjected to border-crossing public debates, media events receive transnational attention, and public diplomacy efforts succeed—and fail—in characteristic patterns around the world. In response to these phenomena the article shows how the study of transnational communication can benefit from combining 3 theoretical perspectives that are rarely studied together: communication as deliberation, as ritual, and as strategy. Particularly in explaining the failures of transnational communication, explanatory potential often seems to lie just outside the limited vision of each of the 3 perspectives—and outside the scope of empirical analyses that are limited to Western contexts.
_eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1111/comt.12046
Keywords: 1-Cinéma; 2-Approches sociologiques; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 4-Europe (lieu de production du savoir); _Nettoyé

“Citizen Journalism” in the Syrian Uprising: Problematizing Western Narratives in a Local Context - Al-Ghazzi, Omar (Communication Theory, 2014)
This article analyzes the term ‘citizen journalism’ against the backdrop of the Arab uprisings in order to show how it overlooks the local context of digital media practices. The first part examines videos emanating from Syria to illustrate how they blur the lines between acts of witnessing, reporting, and lobbying, as well as between professional and amateur productions, and civic and violent intentions. The second part highlights the genealogies of citizenship and journalism in an Arab context and cautions against assumptions about their universality. The article argues that the oscillation of Western narratives between hopes about digital media's role in democratization in the Arab World and fears about their use in terrorism circumscribe the theorization of digital media practices.
_eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1111/comt.12047
Keywords: 1-Cinéma; 2-Approches sociologiques; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Europe (lieu de production du savoir); 5-Identités diasporiques; _Nettoyé

Petit guide sur le cinéma des femmes - Ouellet-Cummings, Catherine (Ciné-Bulles, 2011)
Thérèse Lamartine est bien connue des milieux féministes. Détentrice d’une maîtrise en études cinématographiques, elle a publié Elles, cinéastes... ad lib, en 1985, aux Éditions Remue-ménage, dans lequel elle présentait des réalisatrices de diverses origines, actives entre 1895 et 1981. En 2009, elle publiait Soudoyer Dieu, un roman scrutant la longue et inconsolable douleur d’un groupe de femmes après la tuerie de Polytechnique. Avec Le Féminin au cinéma, une petite plaquette consacrée aux films «de femmes» ou, comme elle le précise, aux films qui «sculptent un art du mieux-vivre la mixité dans nos sociétés ou [qui] débrident les stéréotypes et nous dérident à la fois», Lamartine ouvre les portes d’un monde cinématographique souvent méconnu et rend hommage à des femmes de cinéma, autant derrière que devant la caméra. En sortant ces femmes de l’ombre, elle met au jour un cinéma riche et original, mais méconnu.
Keywords: 1-Cinéma; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude des représentations; 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice; 5-Créatrice; _Nettoyé

"Just Because I'm a Lesbian Doesn't Mean I'm Evolved" The "Bad Queer" Women's Comedic Web Series - San Filippo, Maria (Velvet Light Trap, 2020)
The queer women's comedic web series that have flourished in the last decade, serving as launching pads for their creators, coincided with media-industry nichification's segmentation of a consumer population regarded by advertisers and content providers as one monolithic LGBTQ community. The series I examine-from The Slope, which premiered in 2010, to Strangers, released in 2017-voice their creators' and characters' marginalization from and even opposition to such an imagined community, through recourse to what I call a "bad queer" rhetorical practice, which uses ironic metacommentary to critique assimilationist values and tropes alongside queer identity policing. These series emerged, at least initially, as an alternative sphere of queer media production and a queer discursive mode that employs disidentification as a politicized strategy to challenge dominant LGBTQ scripts. Offering an irreverent alternative to mainstream and millennial LGBTQ cultural products, these "bad queer" web series express the plurality of the queer "community" and expose political contestations within its ranks, and in so doing serve as brand differentiation for a new generation of queer media producers.
Num Pages: 65-77 Place: Austin, United States
Keywords: 1-Cinéma; 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Créateur.rice LGBTQ+; 5-Créatrice; _Nettoyé

Uplift Cinema: The Emergence of African American Film and the Possibility of Black Modernity - Field, Allyson Nadia (Duke University Press, 2015)
Allyson Nadia Field recovers the forgotten body of African American filmmaking from the 1910s which she calls uplift cinema. These films were part of the racial uplift project, which emphasized education, respectability, and self-sufficiency, and weren't only responses to racist representations of African Americans in other films.
Keywords: 1-Cinéma; 2-Approches sociologiques; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Créateur.rice noir.e; _Nettoyé

Tracing the History of Trans and Gender Variant Filmmakers - Horak, Laura (Spectator: The University of Southern California Journal of Film & Television, 2017)
Most writing on transgender cinema focuses on representations of trans people, rather than works made by trans people. This article surveys the history of trans and gender variant people creating audiovisual media from the beginning of cinema through today. From the professional gender impersonators of the stage who crossed into film during the medium’s first decades to selfidentified transvestite and transsexual filmmakers, like Ed Wood and Christine Jorgensen of the mid-twentieth century, to the enormous upsurge in trans filmmaking of the 1990s, this article explores the rich and complex history of trans and gender variant filmmaking. It also considers the untraceable gender variant filmmakers who worked in film and television without their gender history becoming known and those who made home movies that have been lost to history.
Keywords: 1-Cinéma; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude des industries culturelles; 5-Créateur.rice LGBTQ+; _Nettoyé

"Rock-a-Bye, Baby!": Black Women Disrupting Gangs and Constructing Hip-Hop Gangsta Films - Smith-Shomade, Beretta E. (Cinema Journal, 2003)
This essay examines the cultural specificity of the gangster genre. In hip-hop gangsta films, the inclusion of black women as central to the gangster business not only transforms the gangster genre but, more important, adheres to black cultural norms. The films New Jack City, Sugar Hill, and Set It Off serve as case studies.
Keywords: 1-Cinéma; 2-Approches sociologiques; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); _Nettoyé

Why It Matters that Black Men and Queer Women Invented Digital Remix Culture - Kosnik, Abigail De (JCMS: Journal of Cinema & Media Studies, 2019)
The article offers information related to the incention of digital remix culture by black men and queer women. It mentions about technique of extracting segments from existing recordings and using them to form the musical tracks of hiphop songs; and nonqueer and nonfemale people have participated heavily in fan production, digital sampling and gave rise to culture that has proliferated and thrived on the internet primarily through the creative labor of minority musical and fiction artists.
Keywords: 1-Cinéma; 2-Genre et sexualité; 2-Étude des représentations; 5-Créateur.rice LGBTQ+; 5-Créateur.rice noir.e; _Nettoyé

Critical Distance - Critical Distance (Critical Distance)
Back in 2009, Critical Distance was founded to answer the question: “Where is all the good writing about games?” Our goal for the last 10 years has always been to facilitate dialogue. Through roundups, roundtables, podcasts, and critical compilations, we provide one place where all the most important discourse is collected together. We aim to build a foundation for ongoing conversations between developers, critics, educators and enthusiasts about critical issues in games culture. We are a compendium of the most incisive, thought-provoking, and remarkable discussion in and around games, keeping it archived for years to come. Our work has helped new writers to find their voice, educators to find resources to help their students develop critical thinking, and developers to become more reflective in their design practice.
Keywords: 1-Jeux vidéo; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des industries culturelles; 2-Étude des représentations; 5-Auteur.rice PANDC; _Nettoyé

DiGRA India - YouTube - DiGRA India (Youtube, 2020)
The Digital Games Research Association (popularly known as DiGRA) is “ the premiere international association for academics and professionals who research digital games and associated phenomena. It encourages high-quality research on games, and promotes collaboration and dissemination of work by its members” (DiGRA website). DiGRA was founded in 2003 and today, we are proud to inaugurate its Indian chapter almost two decades later. India’s ludic history is rich and ancient; the world’s longest epic The Mahabharata has as one of its crucial episodes, a dice-game match and the consensus among games historians is that Chess originated from chaturanga, the four-handed strategy game. Today, India is a major Cricketing nation and has a large presence in the Olympic games but it is also emerging as an important centre for digital gaming, particularly mobile gaming. Digital games have also emerged as platforms of cultural contentions, controversies, creativity and discussions around social issues. From a sole games researcher in 2001 to about a hundred odd in different parts of the country, research in digital games has grown significantly. Starting off as Games Studies India adda, this platform for discussing all issues relating to gaming cultures is now poised to take a new turn as DiGRA India. As there is no other platform that facilitates research on non-digital games as well on a regular basis, DiGRA India aims to provide a space for discussions on all kinds of games and game culture(s).
Keywords: 1-Jeux vidéo; 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; _Nettoyé

The Players' Realm: Studies on the Culture of Video Games and Gaming - Williams, James Patrick; Smith, Jonas Heide (McFarland, 2007)
"This study sketches some of the various trajectories of digital games in modern Western societies, looking at the growth and persistence of the moral panic that continues to accompany massive public interest in digital games. The book continues with a new phase of games research exemplified by systematic examination of specific aspects of digital games and gaming"–Provided by publisher.
OCLC: 700517982
Keywords: 1-Jeux vidéo; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des industries culturelles; 2-Étude des représentations; 5-Autrice; _Nettoyé

立命館学術成果リポジトリ - NetCommons (REPLAYING JAPAN, 2019)
CMS,Netcommons,Maple

Hyperculturality, Globalization and Cultural Representation in Japanese Survival Horror - Ramírez-Moreno, Carlos (Replaying Japan, 2019)
This article presents the ways in which Japanese survival horror employs video games as a tool for cultural representation. First, it analyses the main differences between American and Japanese horror, and how the historical relationships of competition/collaboration between both have led to a constant exchange of cultural references present in their games. This relationship of domination/submission traces back to the post-war period in which the United States began exercising control over Japan. It is as a result of this period that Japanese terror begins to take shape and take its first steps towards the current J-Horror. Second, it analyses the work of game designer Keiichiro Toyama, namely Silent Hill and Siren, as a well-known example of the construction of a cultural identity halfway between the devotion to the Other and the respect for tradition. Finally, the article addresses other examples of Japanese survival horror to analyse more deeply which stance Japanese industry takes in this era of cultural globalization, or hyperculturality, which is seriously transforming our conception of culture in digital media.
Keywords: 1-Jeux vidéo; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Europe (lieu de production du savoir); _Nettoyé

Per Aspera Ad Astra - Peterson, Jon (ROMchip, 2019)
Number: 1

Other Games, Other Histories - Byrd, Jodi A. (ROMchip, 2019)
What could a history of game studies be from the perspective of a queer Chickasaw feminist scholar? Should this be a disciplining manifesto, a polemical call to arms for radical transformation, a survey of the existing scholarship that has thus far framed games ludologically as fun, as sportsmanship, as design, or as epic struggles for political power where the player rather ominously wins or dies? I’m a bit of an interloper as a recent arrival from Indigenous studies to video-game studies, a field that represents both the end of history and the ahistoricity of pop-culturally–oriented archives that are presentist at best, and at worst, complicit with an industry derived from settler militaristic technologies and platforms and compelled by niche markets to innovate faster and faster to saturate more and more households at the structural level of occupation. And then there is the problem of what the history of game studies has been: Greco-Roman, European, cis white male, heterosexual, orientalist, algorithmic, and code driven with the techno-optimism of Silicon Valley alongside Jane McGonigal’s fundamental belief that games have and will save the world once they unite the collective brain power of all the gamers and bend them to a single task—and if not all that, then peak 1980s geekery with a hint of liberal multiculturalism thrown in, if Ernest Cline’s Ready Player One is anything to go by. It is as if the history of game studies has only ever been an imperial read-only memory to be mined, played, and spatialized within the conscriptions of conquistador archives already known and yet to be discovered.
Number: 1
Keywords: 1-Jeux vidéo; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; _Nettoyé

Video Game History and the Fact of Blackness - Russworm, TreaAndrea M. (ROMchip, 2019)
Video games studies, including many of our most inspired written accounts of video game history, is very white. Stories about US video game pioneers, from engineers and designers to early adopters and arcade patrons, tend to be mostly about the white men who created, consumed, and periodically saved the industry. Even now that game history is on the verge of becoming as queer and ostensibly nonconformist as some aspects of its games and culture are theorized to be, these new avenues of critical investigation speak most directly to a queer mainstream that has always been constructed as white. Although there is much to be inspired by in the proliferation of emergent video game histories that are more gender-inclusive, trans, or so-called diverse, with few exceptions these progressive accounts still tend to be White. White. White. Black designers, players, blerds, and technocrats have been excluded from the canon of old and new video game histories in much the same way Frantz Fanon theorized that blackness functions as a fact: an outwardly defined pejorative social inscription that justifies its alienation and exclusion.
Number: 1
Keywords: 1-Jeux vidéo; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; _Nettoyé

Is the Video Game a Cultural Vehicle? - Chen, Chi-Ying (Games and Culture, 2013)
Following the exportation of Japanese media products such as TV dramas, Japanese culture and products have swept across many Asian countries, especially Taiwan. Based on the historical background and unique characteristics of games, this study investigates the cultural effect of Japanese video games on players in Taiwan. This study also presents an analysis of the differences between TV and the video game as cultural vehicles. We used both quantitative and qualitative methods. Results indicate a relationship between game-playing behavior and the identification of Japanese culture. However, the relationship between video game playing and consumption was nonsignificant. This shows the power of video games in nation-building but not in nation-branding, in contrast with TV. This study presents a discussion of the findings to shed light on the cultural effects of video games.
Keywords: 1-Jeux vidéo; 2-Étude de la réception; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé; _À nettoyer; _À vérifier-Télé

From Separation to Integration: Identity Development of Korean Adult Players in Online Game World - Doh, Young Yim; Whang, Sang-Min Leo (Games and Culture, 2014)
This research examined the identity development of Korean adult players in the online game world. Q methodology was used to investigate the subjectivity of self-development in Mabinogi (Massive Multiplayer Online Role-Playing Game). Thirty-seven adult players sorted 57 behavior statements to reflect the changes in their behaviors from past to present. Three types of self-development were found: achievement-oriented development, control-oriented development, and relational development. The behavior patterns of these three types were compared to identify similarities and differences among them in terms of psychological meanings and values in the online game life. The results illustrate that the online game world can be defined as a new behavioral setting, made possible by digital technology, in which individuals are able to experience three different paths of identity development.
Keywords: 1-Jeux vidéo; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; _Nettoyé

Russian Overlords, Vodka, and Logoffski: Russian- and English- Language Discourse About Anti-Russian Xenophobia in the EVE Online Community - Goodfellow, Catherine (Games and Culture, 2015)
This article explores the attitudes of EVE Online players toward their Russian counterparts. Popular community opinion paints Russian players as aggressive, cliquish and hostile, and as cheats who exploit the game in order to make (real-world) money. The article also analyzes the ways in which Russian pilots challenge, subvert, and discuss these attitudes. Two key arguments are presented. First, that although perceptions of Russian EVE players are often negative, these discourses in EVE are complicated by the fact that aggression, organization, and tight player groups are prerequisites for success within the game. Second, the opinions and agency of Russian players are highlighted. By examining both Russian- and English-language discussions, we see that rather than being silent victims of discrimination, or economic migrants “ruining” the game for other players, Russian pilots inhabit a complex space in a community engaged in two-way dialogue about culture, ethnicity, and play practices in EVE.
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 3-Europe (corpus analysé); 4-Europe (lieu de production du savoir); 5-Autrice

Amateur Gold Farming in China: “Chinese Ingenuity,” Independence, and Critique - Liboriussen, Bjarke (Games and Culture, 2016)
Informed by a mix of theoretical sources and interviews with middle-class Chinese amateur gold farmers, this article argues that within China, the figure of the Chinese gold farmer might function as focus for reflection on Chineseness and China’s role in an increasingly interconnected world, rather than as a carrier of third-world stereotype as it tends to do in the West. The concept of shanzhai—often associated with sometimes comical, sometimes innovative Chinese copying of foreign consumer goods—is employed as a key analytical tool and helps highlight the themes of “Chinese ingenuity,” independence (from game operators and to some extent also parents), and critique (of games).
Keywords: 1-Jeux vidéo; 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); _Nettoyé

Sinological-orientalism in Western News Media: Caricatures of Games Culture and Business - Wirman, Hanna (Games and Culture, 2016)
From gold farmers and ‘100 million brain-damaged online gamers’ to the world’s biggest game company and more players than US citizens, China seems like the cabinet of curiosities for the whole world of digital gaming. This article focuses on news coverage around Chinese gaming and presents three phases of such journalism. China’s emerging games market was most prominently featured between 1999 and 2005, while 2006-2011 focused on extreme play behavior in China. Most recently, a discourse of vast business opportunities and stabilizing markets has been presented by Western news media. In total more than 853 news articles are explored in parallel to the theoretical concept of Sinological-orientalism. This article suggests significant historical changes in the ways in which knowledge of Chinese gaming has been produced in English language news media.
Keywords: 1-Jeux vidéo; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Autrice; _Nettoyé

Japanese Console Games Popularization in China: Governance, Copycats, and Gamers - Liao, Sara X. T. (Games and Culture, 2016)
This article attempts to explore the popularization of Japanese console games in China in the past two decades, which reveals the tripartite relationship of the nation-state, transnational cultural power, and local agents.1 This study focuses on the formation and development of the console game industry in a non-Western context, where the society has undergone dramatic transformations and has been largely influenced by the globalization process. Encountering social anti-gaming discourse and cultural protectionism, the importation and distribution of Japanese console games did not get support from the state. However, it found its way to the audience and gained popularity through piracy, the black market, and the local agents’ appropriation, becoming an integrated part of many Chinese early gamers’ lives. This article draws upon the intersection of cultural globalization with game studies, calling for an investigation into the complexity of the game industry through its sociohistorical, political, and cultural environment.
Keywords: 1-Jeux vidéo; 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; _Nettoyé

A Realm of Mere Representation? “Live” E-Sports Spectacles and the Crafting of China’s Digital Gaming Image - Szablewicz, Marcella (Games and Culture, 2016)
This article addresses the proliferation of images and appearances in the realm of e-sports culture in urban China. The author’s findings are based upon ethnographic research and participant observation of e-sports audience members, teams, and tournaments, including the 2010 E-sports Champion League tournament in Beijing, the 2012 and 2013 World Cyber Games Festivals in Kunshan, and a 2014 Starcraft II tournament in Shanghai. A comparison of these events leads the author to argue that live e-sports events in China are less about spectatorship than they are about creating a spectacle that presents a carefully crafted vision of Chinese politics, nationalism, and capitalist consumer culture. In these cases, the participants and audience members are not only commodities to be sold but also a means of masking contradictory and highly ambivalent discourses about China’s role in technological production, digital game culture, and the promotion of the discourse of Internet addiction.
Keywords: 1-Jeux vidéo; 2-Histoire/Historiographie critique; 3-Asie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; _Nettoyé

“Internet Gaming Disorder” in China: Biomedical Sickness or Sociological Badness? - Bax, Trent (Games and Culture, 2016)
“Internet addiction” in China and elsewhere is considered a serious social problem. In China, some psychiatrists have claimed 10% of all Internet users—60 million—are potentially “addicted” to the Internet. Following on the heels of the publication of the fifth edition of the Diagnostic and Statistical Manual of Mental Disorders (DSM-5), this qualitative-based research article critically investigates the new concept Internet gaming disorder, a category recently included in the DSM-5 as a condition “warranting more clinical research and experience before it might be considered for inclusion in the main book as a formal disorder.” This article takes up this challenge and responds in the following way: When we investigate the social existence of online gamers labeled Internet addicts in China, and then subject their social existence to the DSM’s own definition of a mental disorder, we discover not a clearly understood mental disorder called Internet gaming disorder but more so an issue of social deviance.
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); _Nettoyé

A Critical Cultural History of Online Games in China, 1995–2015 - Chew, Matthew M. (Games and Culture, 2016)
This study critically assesses the Chinese online games industry through problematizing the creativity of Chinese games. I find that between 1995 and 2001, Chinese online games were mostly developed by amateurs, noncommercial, and considerably creative. Between 2002 and 2005, industrial growth allowed some room for local creativity despite commercialization and dominance of imported games. Current scholarly, business, and media discourses unfairly ignore creativity in these first two periods and yet praise the Chinese game industry’s commercial success since the late 2000s. I challenge these discourses by illustrating that between 2006 and early 2009, a new, ethically dubious, and uniquely Chinese business model emerged, became domestically dominant, and quietly and profoundly impacted on global online game design. From mid-2009 to 2015, there is ongoing corporatization based on the dubious Chinese business model on the one hand, and a reemphasis on creativity motivated by browser and mobile game formats on the other.
Keywords: 1-Jeux vidéo; 2-Histoire/Historiographie critique; 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé

Professional Norms and Race in the North American Video Game Industry - Srauy, Sam (Games and Culture, 2019)
This article examines North American (i.e., Canada and the United States) video game developers’ understanding of race, how they construct narratives when they include characters of different races, and some of the pressures that may shape that process. Discourse analyses of semistructured interview texts found that video game developers operate under an internalized pressure to create game narratives that are quickly understandable and, thus, sellable. This pressure is normatively internalized in the profession as an attempt to hedge against market uncertainty. Video game developers, therefore, depend on social beliefs from the “real world” to inform how video game players might receive their games as well as narratives and themes from past texts such as the works of J. R. R. Tolkien. Therefore, this article argues that racism might be enabled because it is believed to be a hedge against market uncertainty.
Keywords: 1-Jeux vidéo; 2-Étude des industries culturelles; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé

Precarity and Why Indie Game Developers Can’t Save Us from Racism - Srauy, Sam (Television & New Media, 2019)
Exploring issues of labor and inequality at the intersection of AAA and indie sectors, this article interrogates the perception of the indie sector as key to mitigating the production of racializing or racist game content. As developers are central to the industry and the larger games culture, their views reveal how indies are imagined as a privileged site free from economic pressures where racism can be ameliorated. Based on interviews with developers, I argue that the project to redress representational inequities within games is shifted on to indie developers, intensifying their emotional and cultural labor. Indie game developers are imagined as the solution, yet this perspective underestimates the precariousness of independent game production. Economic precariousness may encourage indies to repeat certain patterns of racial representation.
Keywords: 1-Jeux vidéo; 2-Étude des industries culturelles; 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé

Realism in FIFA? How Social Realism Enabled Platformed Racism in a Video Game - Srauy, Sam; Cheney-Lippold, John (First Monday, 2019)
Platformed racism offers a unique lens through which to investigate technological structures that enable racism. Online video games, such as EA Sports’ FIFA series — which dominates the soccer video game market share through its touted realism — feature these structures. Like many platforms, FIFA enables representations of real bodies (i.e., professional soccer players). But, unlike many games, FIFA enables game players to directly affect the creation/modification of these representation in the form of player character cards. Analyzing a census of six years of player cards, this study found that platformed racism was enabled because the game’s realism invited racism when players tried to maintain that realism. The study concludes that the catalyst for racism to emerge in FIFA was the drive towards realism.
Keywords: 1-Jeux vidéo; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé

Games With a Continuum: Globalization, Regionalization, and the Nation-State in the Development of China’s Online Game Industry - Jiang, Qiaolei; Fung, Anthony Y.H. (Games and Culture, 2019)
As a case study, this article examines the development of China’s online game industry and how China responds to the forces of globalization. Based on in-depth interviews, ethnographic research, and the analysis of archive documents from the past few years, this study identifies China’s evolving strategy of neo-techno-nationalism. In the Chinese context, this national strategy manipulates technology to create a version of popular nationalism that is both acceptable to and easily censored by the authorities. Therefore, cultural industries that adopt this strategy stand a good chance of prevailing in the Chinese market. This success explains why the regional competitors of Chinese online games—Korean games—are more successful in China than most of their Western counterparts. By providing a snapshot of the current ecology of China’s online game industry, this article also discusses the influence of regional and global forces in a concrete context and argues that the development of China’s online game industry depends more on political factors than economic factors.
Keywords: 1-Jeux vidéo; 2-Histoire/Historiographie critique; 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; _Nettoyé

Balancing Gender Identity and Gamer Identity: Gender Issues Faced by Wang ‘BaiZe’ Xinyu at the 2017 Hearthstone Summer Championship - Schelfhout, Sam; Bowers, Matthew T.; Hao, Y. Andrew (Games and Culture, 2021)
This article examines a terrain in which gender inclusion remains a challenge: competitive esports. In the male-dominated sphere of esports, the underrepresentation of women and nonbinary people often leaves these marginalized groups invisible, with a significant lack of women and nonbinary people competing in top-tier tournaments. We highlight the experience of Wang ‘BaiZe’ Xinyu, a Chinese Hearthstone player who became the first woman to compete in a Hearthstone Championship Tour event in the game’s 3-year history. The narrative surrounding BaiZe’s participation largely focused on her gender and ignored the achievements that led her to qualify for the event. We argue that BaiZe’s entrance to the championship scene was received negatively by both competitors and spectators, reinforcing barriers that exclude women and nonbinary people from entering this male-dominated space. The discrimination faced by these esports competitors reinforces sexism inherent not only in Hearthstone but also in esports in general.
Keywords: 1-Jeux vidéo; 2-Genre et sexualité; 3-Asie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé

“I Can be Who I Am When I Play Tekken 7”: E-sports Women Participants from the Islamic Republic of Pakistan - Hussain, Umer; Yu, Bo; Cunningham, George B.; Bennett, Gregg (Games and Culture, 2021)
Extant research on e-sports has focused on the growth and value of the phenomenon, fandom, and participant experiences. However, there is a paucity of e-sports scholarship detailing women’s experiences from marginalized communities living in various conservative Muslim countries. This shortage of literature remains despite different radical Islamic groups’ consistent demand for banning several online video games and the Muslim youth’s resistance to these calls. This study aimed to understand the motives and lived experiences of Muslim women e-sports participants from Gilgit-Baltistan, Pakistan. The authors collected data via observations of online video games and in-depth interviews. The study participants revealed that they use e-sports as a vehicle for an oppositional agency and personal freedom from the patriarchal system. The findings also suggest that participants are facing systematic marginalization and grave intrusion of post-colonization. The study contributes to the limited scholarship concerning Indian subcontinent Muslim women’s e-sports participation.
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Genre et sexualité; 3-Afrique (corpus analysé); 3-Asie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé

Slave Revolt on Screen: the Haitian Revolution in Film and Video Games - Sepinwall, Alyssa Goldstein (University Press of Mississippi, 2021)
In Slave Revolt on Screen: The Haitian Revolution in Film and Video Games author Alyssa Goldstein Sepinwall analyzes how films and video games from around the world have depicted slave revolt, focusing on the Haitian Revolution (1791–1804). This event, the first successful revolution by enslaved people in modern history, sent shock waves throughout the Atlantic World. Regardless of its historical significance however, this revolution has become less well-known—and appears less often on screen—than most other revolutions; its story, involving enslaved Africans liberating themselves through violence, does not match the suffering-slaves-waiting-for-a-white-hero genre that pervades Hollywood treatments of Black history. Despite Hollywood’s near-silence on this event, some films on the Revolution do exist—from directors in Haiti, the US, France, and elsewhere. Slave Revolt on Screen offers the first-ever comprehensive analysis of Haitian Revolution cinema, including completed films and planned projects that were never made. In addition to studying cinema, this book also breaks ground in examining video games, a pop-culture form long neglected by historians. Sepinwall scrutinizes video game depictions of Haitian slave revolt that appear in games like the Assassin’s Creed series that have reached millions more players than comparable films. In analyzing films and games on the revolution, Slave Revolt on Screen calls attention to the ways that economic legacies of slavery and colonialism warp pop-culture portrayals of the past and leave audiences with distorted understandings.
Section: vi, 339 pages : illustrations ; 24 cm.
Keywords: 1-Jeux vidéo; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 3-Amérique centrale (corpus analysé); 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; _Nettoyé; _À nettoyer; _À vérifier-Cinéma

De la controverse autour des études postcoloniales à l’histoire intellectuelle de la décolonisation en France - Sibeud, Emmanuelle (Diogene, 2017)
En dépit des déclarations fracassantes sur le « tabou » qui pèserait en France sur l’histoire de la colonisation, celle-ci se porte bien. Les recherches se sont multipliées dans les vingt dernières années et elles sont à l’origine d’une production bien insérée dans les revues et en bonne place sur les tables des librairies. Au fil d’échanges nourris avec les réseaux anglophones, ces recherches se sont postcolonialisées de façon critique et participent de plain pied aux débats de la « nouvelle histoire impériale ». L’histoire de la colonisation est enseignée dans le secondaire et à l’université et là aussi la discordance est flagrante entre des débats publics qui dénoncent sempiternellement sa marginalisation, ou au contraire sa surreprésentation, et une diffusion active reposant notamment sur la traduction de travaux influents comme l’important programme de recherche formulé au cours des années 1990 par Frederick Cooper et Ann Stoler. Dès lors, comment relier ces trois éléments : le discret mais solide épanouissement académique de l’histoire de la colonisation depuis la fin des années 1990, la virulente controverse ouverte à partir de 2005 autour des études postcoloniales et un sens commun qui s’est approprié ce terme séduisant, mais qui peine à lui donner un contenu allant au-delà de la fausse évidence d’une distanciation mécaniquement produite par l’usure du temps ?
Bibliographie_available: 0 Cairndomain: www.cairn.info Cite Par_available: 0

Pour une autre histoire du cinéma français : blanchité et maghrébinité de la francité - Derfoufi, Mehdi (De l'autre côté, 2019)
Parution dans la revue Diogène d’un article co-écrit avec James Berclaz-Lewis. En dépit de la publication de travaux importants depuis les années 1990, le champ disciplinaire des études ciném…
Keywords: 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Afrique (corpus analysé); 3-Europe (corpus analysé); 4-Europe (lieu de production du savoir); _À vérifier-Cinéma

Décentrer l’histoire du jeu vidéo ? - Derfoufi, Mehdi (De l'autre côté, 2018)
Peut-on envisager une autre histoire du jeu vidéo ?
Keywords: 1-Jeux vidéo; 2-Méthodologie de recherche décoloniale; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 3-Asie (corpus analysé); 4-Europe (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Identités diasporiques; _Nettoyé

Paradoxale légitimation culturelle du jeu vidéo - Derfoufi, Mehdi (De l'autre côté, 2019)
Qualifié parfois de « dixième art », après que les jeux de rôles sur table (comme Donjons & Dragons) eurent commencé à céder du terrain dans les loisirs de la jeunesse à partir du mil…
Keywords: 1-Jeux vidéo; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 3-Asie (corpus analysé); 4-Europe (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Identités diasporiques; _Nettoyé

Sexe, Race et Gaming - Derfoufi, Mehdi (Revue du Crieur, 2019)
Aucune étude n’a jamais démontré que les formes médiatiques disposeraient d’un pouvoir direct de transformation des réalités sociales. Une approche critique un peu sérieuse préférera ainsi appréhender le jeu vidéo comme le site d’un ensemble de rapports de pouvoir opérant au sein de la culture dominante, traversé, à l’instar d’autres formes culturelles, par des contradictions, des résistances et des réappropriations – autrement dit par des circulations dans la production de sens, les formes et les affects, qui viennent renforcer, nuancer ou déstabiliser les normes de l’hégémonie culturelle. Depuis le début des années 2010 et en particulier la polémique du #GamerGate en 2014, la communauté vidéoludique ne peut plus ignorer le sexisme. Les féministes n’ont pourtant pas attendu si longtemps pour se manifester. Mais c’est peut-être l’année 2012 qui marqua un réel tournant, lorsque Anita Sarkeesian lança une campagne de crowdfunding pour une série de vidéos sur sa chaîne YouTube feministfrequency. Sa démarche déclencha une vague de cyberharcèlement qui alla des insultes aux menaces de mort et jusqu’à la publication de données personnelles. Ce modèle de violence sexiste s’est reproduit à de multiples reprises, notamment en France en 2013 à l’encontre de la créatrice de jeu et féministe Mar_Lard, attaquée pour sa critique argumentée du sexisme dans la culture geek. Elle revenait en particulier sur des propos plus que complaisants d’un journaliste à propos d’une séquence où le personnage de Lara Croft, héroïne du mythique je…
Bibliographie_available: 0 Cairndomain: www.cairn.info Cite Par_available: 0
Keywords: 1-Jeux vidéo; 2-Genre et sexualité; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 3-Europe (corpus analysé); 4-Europe (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Identités diasporiques; _Nettoyé

Young, Black (& Brown) and Don't Give a Fuck: Virtual Gangstas in the Era of State Violence - Leonard, David (Cultural Studies ↔ Critical Methodologies, 2009)
The popularity and visibility of video games within American popular culture is prompted debates within from a spectrum of institutions, ranging from the media and the academy to Main Street and the political sphere. Erasing the complexity, much of the discourse focuses instead on questions of violence and the impact of gaming culture on (White) American youth. While focusing on Grand Theft: San Andreas specifically, this essay explores the culture wars surrounding American video game culture, arguing that the moral panics directed at video games and the defenses/celebrations of virtual reality operate through dominant discourses and hegemonic ideologies of race. Erasing their racial content and textual support for state violence directed at communities of color, the dominant discourse concerning youth and video games rationalizes the fear and policing of Black and Brown communities.
Keywords: 1-Jeux vidéo; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); _Nettoyé

Racisme et jeu vidéo - Derfoufi, Mehdi (Éditions de la Maison des sciences de l'homme, 2021)
En 2007, le monde du jeu vidéo est secoué par une violente polémique au sujet du jeu vidéo Resident Evil 5. Ce dernier est accusé de faire commerce du racisme, en invitant à se glisser dans la peau d'un américain blanc body-buildé, missionné dans une région africaine anonyme, et tuant des dizaines d'hommes et de femmes noires présentées comme de dangereux zombies infectés du virus T. Depuis, la communauté des joueurs et joueuses de jeux vidéo interpelle régulièrement les créateurs et créatrices des jeux sur les questions du racisme et du sexisme.Dans son ouvrage, Mehdi Derfoufi analyse les rapports de force qui structurent l'industrie du jeu vidéo, dévoilant comment le racisme se niche parfois insidieusement au cœur de scénarios de jeux vidéo à succès. Il nous invite à nous questionner. Quels sont les pays qui pèsent sur les milliards d'euros du marché mondial du jeu vidéo ? Qui sont les game designers et auteurs des jeux ? Comment les représentations racistes sont-elles véhiculées à travers les personnageset les imaginaires vidéoludiques ? L'auteur nous dévoile avec brio les logiques racialisantes à l’œuvre au sein d’un marché économique très concurrentiel où des stéréotypes exotisants servent régulièrement à faire vendre un jeu. Il nous montre aussi comment la division internationale du travail et la hiérarchie économico-politique Nord/Sud pèse sur le marché du jeu vidéo et ralentit l’émergence de nouvelles représentations. Pourtant, de nombreux espoirs, notamment dans les pays du Sud participent au renouvellement de la culture geek : face aux violences racistes, la riposte s’organise.
Keywords: 1-Jeux vidéo; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Europe (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Identités diasporiques; _Nettoyé

The Iconography of Chicano Self-Determination: Race, Ethnicity, and Class - Goldman, Shifra M. (Art Journal, 1990)
In several cities in the Southwest and Midwest with sizable enclaves of Chicanos, there are to be found considerable numbers of images that have become leitmotifs of Chicano art. In their ubiquity, these motifs demonstrate that the Chicano phase of Mexican-American art (from 1965 to the 1980s) was nationally dispersed, shared certain common philosophies, and established a network that promoted a hitherto nonexistent cohesion. In other words, it was a movement, not just an individual assembly of Mexican-descent artists. In what follows, Chicano art is examined as statements of a conquered and oppressed people countering oppression and determining their own destiny, though not all the producers of these images necessarily saw their production in the political way they are framed below. Examples have been chosen specifically to show how, in response to exploitation, artists have taken an affirmative stance celebrating race, ethnicity, and class.
Keywords: 1-Histoire de l'art; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Créateur.rice PANDC; _Nettoyé

L’imbrication classe et sexe à l’œuvre : parcours identitaires et migratoires chez les personnes trans MtF latino-américaines - Gonzalez, Olga L. (Genre, Sexualité & Société, 2018)
Ce travail s’intéresse à la population trans MtF latino-américaine issue des secteurs populaires. Le travail a pour objectifs de (1) connaître les normes de genre du milieu d’origine de cette population (2) comprendre le lien du milieu d’origine avec leur parcours dans l’identité trans (3) examiner les parcours migratoires et comprendre leur très forte inscription dans la prostitution. L’enquête de terrain a été réalisée principalement en France et en Espagne. Concernant le cheminement identitaire, la recherche montre le poids de la formation sociale du milieu d’origine, et particulièrement le poids des normes relatives au genre dans les milieux populaires (hétéronormativité, homophobie, sanction des masculinités déviantes). Cette imbrication classe/sexe situe les personnes dans la position sociale marginale et stigmatisée de la prostitution. L’article apporte un éclairage sur cet environnement, où l’imaginaire festif côtoie l’ordinaire des violences. L’expérience migratoire, très valorisée dans le pays d’origine, est examinée. Le type de liens tissés avec la famille, et les difficultés liées à l’isolement linguistique et à la solitude sont abordés.
Keywords: 1-Cinéma; 1-Histoire de l'art; 1-Jeux vidéo; 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 3-Amérique du Sud (corpus analysé); 3-Europe (corpus analysé); 4-Europe (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Identités diasporiques; _Nettoyé

The Statue of a Doctor Who Experimented on Enslaved Women still Stands in Alabama. But now There’s also a Monument to His Victims. - Matchan, Linda (Washington Post, 2021)
Michelle Browder’s “The Mothers of Gynecology” remembers Black women who endured surgeries without anesthesia, or consent.
Keywords: 1-Histoire de l'art; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice; 5-Créateur.rice noir.e; _Nettoyé

Painting, Literature and Film in Colombian Feminine Culture, 1940-2005: Of Border Guards, Nomads and Women - Martin, Deborah (Cambridge University Press, 2013)
This book explores crucial moments in the emergence of feminine culture in Colombia hitherto unexamined in English-language criticism through an examination of the work of ground-breaking artist Débora Arango, best-selling novelist Laura Restrepo, and three generations of documentary filmmakers.
Keywords: 1-Cinéma; 1-Histoire de l'art; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 3-Amérique du Sud (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Créateur.rice PANDC; _Nettoyé

On How Queer Cinema Might Feel. - Quinlivan, Davina (Music, Sound, and the Moving Image, 2015)
Examines the soundscapes of Derek Jarman's film "Blue" (1993) and Isaac Julien's video installation 'True north' (2007), and the way they contribute to promoting embodied responses in the viewer. Draws on the writings of Luce Irigaray and Laura U. Marks to explore the relationship between haptic theory and queer spectatorship.
Num Pages: 63-77
Keywords: 1-Cinéma; 2-Genre et sexualité; 2-Étude de la réception; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); _Nettoyé

Paris is burning: Intersectionality in 90s Queer Cinema. - Brew, Tara (Film Matters, 2019)
The overlap of marginalised race and sexuality is highlighted in the 1990 documentary "Paris is burning" which depicts the life of New York's black and Latino drag queens. The author offers an analysis of the social circumstances that gave birth to this culture which originated in 1980s Harlem.
Num Pages: 7-18
Keywords: 1-Cinéma; 2-Genre et sexualité; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Identités diasporiques; _Nettoyé

Queer Cinema in the Twenty-first Century. - Hart, Kylo-Patrick R. (New Cinemas: Journal of Contemporary Film, 2012)
Introduction and seven articles looking at the range of present-day queer cinema to be found.
Num Pages: 97-207
Keywords: 1-Cinéma; 2-Approches sociologiques; 2-Genre et sexualité; 4-Amérique du Nord (lieu de production du savoir); _Nettoyé

New Queer Cinema 2.0?: Lesbian-focused Films and the Internet. - Beirne, Rebecca (Screen, 2014)
The Internet distribution of lesbian-focused films seen as an example of the ways in which independent producers and distributors are offering their films for sale on the web. Incl. a table comparing costs and number of films available across a range of legal and illegal sites.
Num Pages: 129-138
Keywords: 1-Cinéma; 2-Genre et sexualité; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); _Nettoyé

Queer Korean Cinema, National Others, and Making of Queer Space in Stateless Things - Kim, Ungsan (Journal of Japanese & Korean Cinema, 2017)
Analyses the narrative and formal elements of Kim Kyung-mook's "Stateless things" (2011) to argue how it critiques South Korea’s ethnocentrism and homophobic social structures by delineating a queer use of space. Gives recent examples of homoeroticism in commercial and independent South Korean cinema. Argues that Kim's film expand the definition of queer Korean cinema by deconstructing and reconstructing the heteronormative, progress-driven cityscape of Seoul.
Num Pages: 61-79
Keywords: 1-Cinéma; 2-Genre et sexualité; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 3-Asie (corpus analysé); 5-Identités diasporiques; _Nettoyé

We are here but are we Queer?: Lesbian Filmmaking versus Queer Cinema Conference, London, 12 March 1994 - Florence, Penny (Screen, 1994)
Num Pages: 297-300
Keywords: 1-Cinéma; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude des industries culturelles; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Créateur.rice LGBTQ+; _Nettoyé

The Queer Film Ecosystem: Symbolic Economy, Festivals, and Queer Cinema's Legs. - Damiens, Antoine (Studies in European Cinema, 2018)
Stresses the crucial importance of LGBT festivals in promoting examples of queer cinema throughout Europe and the USA.
Num Pages: 25-40
Keywords: 1-Cinéma; 2-Genre et sexualité; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Amérique du Nord (corpus analysé); 3-Europe (corpus analysé); 4-Europe (lieu de production du savoir); _Nettoyé

A Queer('s) Cinema. - Betancourt, Manuel (Film Quarterly, 2019)
Queer cinema, no matter how rebellious, is the child of straight cinema-its bastard child, perhaps, but its progeny no less. Queer cinema must push against decades of tradition to create itself anew. Borrowed genres and hand-me-down narratives have served their purpose. If the (curated though not novel) propositions and (recent though not unique) examples that follow point anywhere, it is to a still-to-be-imagined future where queer cinema can continue to expand while never ceding its right to be "nice" in order to serve those it portrays.
Num Pages: 15-17
Keywords: 1-Cinéma; 2-Genre et sexualité; 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice LGBTQ+; 5-Créateur.rice LGBTQ+; 5-Créateur.rice PANDC; _Nettoyé

The Desiring-Image: Gilles Deleuze and Contemporary Queer Cinema/Ethereal Queer: Television, Historicity, Desire - Betancourt, Manuel (Film Quarterly, 2013)
Betancourt reviews The Desiring-Image: Gilles Deleuze and Contemporary Queer Cinema by Nick Davis and Ethereal Queer Television, Historicity, Desire by Amy Villarejo.
Num Pages: 95 Place: Berkeley
Keywords: 1-Cinéma; 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude des industries culturelles; 4-Amérique du Nord (lieu de production du savoir); _Nettoyé

Review of Queer Film Culture: Queer Cinema & Queer Film Festivals International Conference. - Lindner, Katharina (Transnational Cinemas, 2015)
On the 'Queer Film Culture: Queer Cinema & Queer Film Festivals International Conference', held at the University of Hamburg, 14-15 October 2014, alongside the Hamburg International Queer Film Festival.
Num Pages: 97-103
Keywords: 1-Cinéma; 2-Genre et sexualité; 2-Étude des représentations; 3-Europe (corpus analysé); 4-Europe (lieu de production du savoir); _Nettoyé

Cinémas Et Médias Autochtones Dans Les Amériques: Récits, Communautés Et Souverainetés - Dudemaine, André; Marcoux, Gabrielle; St-Amand, Isabelle (Canadian Journal of Film Studies, 2020)
Le lieu de la rupture, ici, se voit déplacé : s'il faut rompre, en cinéma autochtone, ce n'est pas avec ses propres prédécesseurs, comme l'ont fait Jean-Luc Godard, François Truffaut et Agnes Varda. Des cinéastes tels Barnaby, Freeland et Grace peuvent ainsi s'appuyer sur le travail d'ouvreurs de sentiers tels le réalisateur māori Lee Tamahori (Once Were Warriors, en traduction française, Nous étions guerriers, 1994), le réalisateur cheyenne et arapaho Chris Eyre (Smoke Signals, 1998) , ainsi que des précurseurs incontournables tels Barclay, en Aotearoa, Nouvelle-Zélande, et la documentariste abénaquise Alanis Obomsawin, figure de proue du cinéma autochtone au Canada. Dans un récent document interne sur le cinéma autochtone en son sein, l'Office national du film (ONF), cet important producteur et diffuseur public d'œuvres audiovisuelles au Canada, explique que pour « comprendre la situation actuelle des cinéastes autochtones a l'ONF », il faut l'envisager a partir des « anciennes politiques gouvernementales visant explicitement a éliminer toute culture autochtone de la société canadienne ». Elle est également sous-tendue par le désir de proposer un storytelling, un art de raconter, issu des peuples autochtones, déterminé par ces derniers tant au niveau de la forme et du contenu cinématographique que dans le processus de production, de réalisation et de diffusion de ces œuvres.
Num Pages: 1-26 Place: North York
Keywords: 1-Cinéma; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 5-Auteur.rice autochtone; 5-Créateur.rice autochtone; _Nettoyé

Une histoire sans noms: les femmes et le concept d'auteur dans le cinéma des premiers temps. - Maule, Rosanna (Cinémas, 2005)
A discussion of authorship, relating to the feminist study of the role of women in early cinema.
Num Pages: 35-58
Keywords: 1-Cinéma; 2-Approches sociologiques; 2-Genre et sexualité; 5-Autrice; 5-Créatrice; _Nettoyé

Ciné-parcours dans l'Europe contemporaine : routes nécessaires, routes symboliques - Gandolfi, Paola (Cinémas : Revue d'études cinématographiques = Journal of Film Studies, 2010)
Cette vidéaste regarde - et nous fait regarder - la frontière comme un espace mental et matériel : les interviews, la voix over dont le texte apparaît à l'écran, les citations de textes, les images, les sons et le found footage sont combinés de façon à donner un aperçu saisissant et intime à la fois des conditions de vie des femmes (division du travail, prostitution, violence à l'égard des femmes dans les rues, etc.) propres aux régions frontalières, c'est-à-dire se définissant en fonction des contraintes liées à leur position limitrophe, mais offrant une certaine liberté aux gens qui y vivent du fait, justement, de cette position. Il est intéressant de voir comment le road movie permet de réaffirmer la place de l'automobile comme pur moyen de mobilité, mais en même temps comment il nous oblige à nous concentrer sur un autre type de mobilité, que Walter Moser (2008, p. 9) appelle la « médiamotion », soit : une forme de mobilité que nous procurent les médias mais qui, dans un certain sens, remplace ou redouble le déplacement physique en offrant aux êtres humains une expérience presque paradoxale : le contact à distance. On peut également voir dans le road movie contemporain un « road movie interculturel6», parce que la route y trace «un espace imaginaire particulièrement apte à figurer la complexité et les asymétries de l'interculturel » (Gin 2008, p. 41), mais également parce que : l'intetculturalité [...] du road movie résiderait en ce sens dans le mouvement que subit un principe ou une pulsion d'identification culturelle ne pouvant ni se réaliser ou s'assouvir - narrativement, visuellement - dans l'univocité d'un arrêt sur image, ni pour autant s'épuiser on the road Xp. 44). En fait, la mobilité transnationale se situant au centre de cette production filmique «accentuée» donne lieu à un ensemble de tentatives en constante évolution, où les identités culturelles en devenir peuvent être «constamment reformulées dans une perspective future, bien que conditionnées par des liens historiques et des devoirs avec le passé» (Grillo, Riccio et Salih 2000, p. 16), aussi bien que par les liens qu'entretiennent les migrants et les exilés avec leur identité et leur culture d'origine.
Num Pages: 23 Place: Montréal
Keywords: 1-Cinéma; 2-Étude des représentations; 3-Europe (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); _Nettoyé

The Carnival of Images : Brazilian Television Fiction - Mattelart, Michèle.; Mattelart, Armand. (Bergin & Garvey, 1990)
In creating and developing the new genre of the televised novela, a one-hour long dramatic serial, the Brazilian television industry grew, in less than 15 years, from an insignificant player in the international market to one of the largest, most influential in the world. In the first book in English to explore the phenomenon of the telenovela Michele and Armand Mattelart challenge accepted views of the world dominance of United States television and probe the socioeconomic impact of this new genre on a third world country. Using the telenovela and its impact on the medium world-wide, the authors document the important changes in the international circulation of television programs and in the way television is perceived theoretically as a subject of research. The book traces the development of the novela in a country that, in the early 1960s, did not have any nationwide media and later–from 1964 to the 1970s–was ruled by a military dictatorship. It further analyzes the formation of the genre and its mode of production, placing the novela's appearance and development in its cultural, institutional, and economic context. The authors look at the peculiar contradictory relation between the genre's creators and developers–generally left wing intellectuals–and the manipulations required to construct a television industry in a highly competitive marketplace. The book begins with a description of the economic, institutional, and cultural context which produced the genre. It explores the world of soap operas, the development of a national television industry, and the beginnings of an urban consumer society in Brazil. The authors include a valuable and detailed study of the mode of production of the telenovela, placing both the form and content of the genre in their specific economic and institutional context. The book goes on to examine the relationship between the genre and its wider social and cultural environment, explaining its immense popularity and the social function it fulfills. Finally, the authors link the study of Brazilian television to wider debates in media and cultural studies.
Keywords: 1-TV; 2-Approches sociologiques; 3-Amérique du Sud (corpus analysé); 4-Europe (lieu de production du savoir); 5-Auteur.rice; Brésil (corpus analysé); France (lieu de production du savoir); _Nettoyé

MELODRAMA IN TIMES OF STREAMING - Lopes, Maria Immacolata Vassallo de (MELODRAMA IN TIMES OF STREAMINGS)
This Obitel yearbook brings“Melodrama in times of streaming” as the topic of the year. It aims to identify, through the analysis of the characters, themes and narrative plots of melodrama that are circulating on VoD platforms, the particularities of

Television and narratives: cultural identities in globalization age - Vassallo-de-Lopes, Maria Immacolata (Comunicar, 2008)
This paper describes a current research integrated in an international and interdisciplinary project and developed in a global environment between two different tendencies: integration and desintegration. In this scenary, television narrative arises as an essential tool to create and consolidate new cultural identities in order to get a popular narrative on the concept of nation. El presente texto hace referencia a un estudio en curso1 que se enclava en un proyecto internacional de corte interdisciplinar y que se desarrolla en un escenario global caracterizado por la complejidad y la confrontación dialéctica existente entre las ambivalentes tendencias que se dan a favor de la integración o de la fragmentación. En este escenario, la narrativa televisiva surge como un instrumento determinante en la creación y consolidación de nuevas identidades culturales compartidas, configurándose como una narrativa popular sobre la nación.
Keywords: 1-TV; 2-Approches sociologiques

Observación de la ficción televisiva en ocho países iberoamericanos - Orozco Gómez, Guillermo; Vassallo de Lopes, María Immacolata (Comunicación y Sociedad, 2015)
En este texto se reportan comparativa e históricamente los resultados de la observación de la programación televisiva de ficción en ocho países iberoamericanos durante 2008. Se aprecian cambios significativos en la producción, en la transmisión y en la recepción de los diversificados formatos que presenta este género televisivo. La telenovela sigue siendo el formato más popular entre las audiencias, el que llena el prime timenacional y sirve, a la vez, de escaparate a una creciente naturalización de la publicidad y la política.

Quality in television fiction and audiences' transmedia interactions: Obitel 2011 - Orozco Gómez, Guillermo; Lopes, Maria Immacolata Vassallo de; Alvarado, Morella; Ibero-American Observatory of Television Fiction; Globo Universidade (Project) (2011)
OCLC: 934904289

Transnationalization of television fiction in Ibero-American countries: Obitel 2012 - Orozco Gómez, Guillermo; Lopes, Maria Immacolata Vassallo de; Alvarado, Morella; Ibero-American Observatory of Television Fiction; Globo Universidade (Project) (2012)
OCLC: 1055249499

Transmedia production strategies in television fiction: Obitel 2014 - Lopes, Maria Immacolata Vassallo de; Orozco Gomez, Guillermo; Alvarado, Morella; Ibero-American Observatory of Television Fiction; Globo Universidade (Project) (2014)
OCLC: 1055242231

Gender relations in television fiction: Obitel 2015 - Lopes, Maria Immacolata Vassallo de; Orozco Gomez, Guillermo; Alvarado, Morella; Ibero-American Observatory of Television Fiction; Globo Universidade (Project) (2015)
OCLC: 1055245896

Contemporary Greek Film Cultures from 1990 to the Present - Kazakopoulou, Tania; Fotiou, Mikela (Peter Lang Ltd, International Academic Publishers, 2017)
This collection of new writing on contemporary Greek cinema builds and expands on existing work in the field, providing a coherent analysis of films which, despite their international importance, have so far received limited critical attention. The volume maps key trends in Greek cinema since the 1990s within the wider context of production and consumption at both national and international levels. It offers a wide range of critical analyses of documentary and avant-garde filmmaking, art house and popular cinema, and the work of established and new directors as well as deliberations on teaching methodologies and marketing strategies. The book seeks to highlight the continuities, mutual influences and common contexts that inform, shape and inspire filmmaking in Greece today.
Issue: vol. 21
Keywords: 1-Cinéma; 2-Muséologie critique; 2-Étude des industries culturelles; 3-Europe (corpus analysé); 4-Europe (lieu de production du savoir); _Nettoyé

‘Shanghai is burning’: Extravaganza, Transgender Representation and Transnational Cinema - Bao, Hongwei (Global Media and China, 2018)
This article offers a critical analysis of Matthew Baren’s 2018 film Extravaganza, a documentary about drag scenes in Shanghai. By focusing on some drag performers represented in this film, in tandem with an examination of the social and industry contexts of the film, as well as my interviews with the filmmaker and performers, I problematise the gender identity of the performers and the national identity of the film. Drawing on Deleuze and Guattari’s notion of ‘becoming’ and Song Hwee Lim’s discussion of ‘trans’, I propose to think about certain modes of transnational production with the critical concept of ‘becoming trans’. ‘Becoming trans’ offers a productive way of conceptualising new modes of ‘minor’ transnational cinematic connections in a globalised world without having to resort to identity politics.
Keywords: 1-Cinéma; 2-Genre et sexualité; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Identités diasporiques; _Nettoyé

The Wonderful World of Queer Cinephilia - Ghosh, Shohini (BioScope: South Asian Screen Studies, 2010)
The silence around queerness is decisively broken. Much has happened in the last two decades. Today, there are queer groups, writers, activists, academics, filmmakers, and an increasing number of spaces where friendship, solidarity, and political engagement can be nurtured. Queer activism has been responsible for bringing a legal challenge to Section 377 (IPC) that criminalizes “sexual acts against the order of nature”.
Keywords: 1-Cinéma; 2-Genre et sexualité; 2-Étude des représentations; 3-Asie (corpus analysé); 5-Créateur.rice LGBTQ+; _Nettoyé

The View from here Conversations with Gay and Lesbian Filmmakers - Hays, Matthew (Arsenal Pulp Press,, 2007)
The history of gay and lesbian cinema is a storied one, and became that much larger with the recent success of Brokeback Mountain. But the history of gay and lesbian filmmakers is its own story. In The View From Here, queer directors and screenwriters speak passionately about the medium, in particular their personal experiences navi-gating the often cynical and cruel film industry. All of them offer fascinating anecdotes and ideas about cinema, and speak candidly about their attempts to combat studio apathy and demands of “the market” to create films that are entertaining, engaging, and truthful.
Pages: 1 vol. (383 p.) :
Keywords: 1-Cinéma; 2-Genre et sexualité; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des industries culturelles; 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice LGBTQ+; _Nettoyé

The Other in South Asian Religion, Literature and Film: Perspectives on Otherism and Otherness - Dimitrova, Diana (Routledge, 2013)
This book introduces the term "otherism" and looks at the discourse of otherism and the issue of otherness in South Asian religion, literature and film. It examines cultural questions related to the human condition of being the "other," of the process of "othering" and of the representation of "otherness" and its religious, cultural and ideological implications. The book applies the perspectives of ideological criticism, theories of hybridity, orientalism, nationalism, and gender and queer studies to gain new insights into the literature, film and culture of South Asia. It looks at the different ways of interpreting "otherness" today. The book goes on to analyze the ideological implications of the creation of "otherness" with regard to religious and cultural identity and the legitimation of power, as well as how the representation of "otherness" reflects the power structures of contemporary societies in South Asia. Offering a well-thought-out reflection on important cultural questions as well as a deep insight into the study of religion and "otherness" in South Asian literature and film, this book is a pioneering project that is of interest to scholars of South Asian Studies and South Asian religions, literatures and cultures.
Keywords: 1-Cinéma; 2-Approches sociologiques; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Europe (lieu de production du savoir); 5-Identités diasporiques; _Nettoyé

Straight Skin, Gay Masks and Pretending to Be Gay on Screen - Padva, Gilad (Routledge, 2020)
Straight Skin, Gay Masks and Pretending to Be Gay on Screen examines cinematic depictions of pretending-to-be-gay, assessing performances that not only reflect heteronormative and explicitly homophobic attitudes, but also offer depictions of gay selfhood with more nuanced multidirectional identifications. The case of straight protagonists pretending to be gay on screen is the ideal context in which to study unanticipated progressivity and dissidence in regard to cultural construction of human sexualities in the face of theatricalized epistemological collapse. Teasing apart the dynamics of depictions of both sexual stability and fluidity in cinematic images of men pretending to be gay offers new insights into such salient issues as sexual vulnerability and dynamics and long-term queer visibility in a politically complicated mass culture which is mostly produced in a heteronormative and even hostile cultural environment. Additionally, this book initially examines queer uses of sexuality masquerade in Alternate Gay World Cinema that allegorically features a world pretending to be gay, in which straights are harassed and persecuted, in order to expose the tragic consequences of sexual intolerance. Films and TV series examined as part of the analysis include The Gay Deceivers, Victor/Victoria, Happy Texas, William Friedkin’s Cruising and many other straight and gay screens. This is a fascinating and important study relevant to students and researchers in Film Studies, Media Studies, Gender Studies, Queer Studies, Sexuality Studies, Communication Studies and Cultural Studies.
Keywords: 1-Cinéma; 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); _Nettoyé

Coquie Hughes: Urban Lesbian Filmmaker Introduction to Yvonne Welbon’s Interview with Coquie Hughes - Brody, Jennifer Devere (Sisters in the Life: A History of Out African American Lesbian Media-Making, 2018)
Toni Morrison purportedly began her career as a novelist because she noticed a dearth of books about black women. As a result of this limitation, Morrison desired to write books “for people like [her], which is to say black people, curious people, demanding people—people who can’t be faked, people who don’t need to be patronized.”¹ Similarly the writer, director, and filmmaker Coquie Hughes (born Latasha Iva Hughes in Chicago in 1970) has produced narratives that feature an array of queer black women—“Girls Like Us” as she calls them in her web series—who are curious, demanding, flawed, and
Keywords: 1-Cinéma; 2-Genre et sexualité; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice LGBTQ+; 5-Créateur.rice noir.e; _Nettoyé

The Circuitous Route of Presenting Black Butch: The Travels of Dee Rees’s Pariah - Declue, Jennifer (Sisters in the Life: A History of Out African American Lesbian Media-Making, 2018)
At the 2012 Golden Globe awards, during her acceptance speech for the Best Actress award for her performance in The Iron Lady (Phyllida Lloyd, 2012), Meryl Streep gave a shout-out to Adepero Oduye for her role as Alike in Dee Rees’s feature film Pariah (2011). The sentiment behind this esteemed acknowledgment was that brilliant performances in important independent films were overlooked and deserved recognition. Streep would go on to win the Best Actress Oscar for a her portrayal of Britain’s first woman prime minister, the a ultraconservative Margaret Thatcher.
Keywords: 1-Cinéma; 2-Genre et sexualité; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Créateur.rice LGBTQ+; 5-Créateur.rice noir.e; _Nettoyé

Narrating Our History: Selections from a Dialogue among Queer Media Artists from the African Diaspora - Ferrera-Balanquet, Raúl; Harris, Thomas Allen; Frilot, Shari; Gilliam, Leah; Suggs, Dawn; Taylor, Jocelyn; Welbon, Yvonne; Juhasz, Alexandra (Sisters in the Life: A History of Out African American Lesbian Media-Making, 2018)
The first time I spoke in public about my work was during the Los Angeles Lesbian and Gay Festival in 1990. Cheryl Dunye was the only other woman of color on the panel. When I asked a question regarding funding, I naïvely stated that funding was not a prob lem for me considering the fact that my work at that time was of medium to low production quality. I had minimal access to a low-end production facility, and my piece was only five minutes long. I was alluding to the fact that it has been “easy” for me.
Keywords: 1-Cinéma; 2-Genre et sexualité; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 3-Afrique (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Créateur.rice LGBTQ+; 5-Créateur.rice noir.e; _Nettoyé

Creating the World Anew: Black Lesbian Legacies and Queer Film Futures - Gumbs, Alexis Pauline (Sisters in the Life: A History of Out African American Lesbian Media-Making, 2018)
Deeply grounded in the legacy of Black lesbian artists, writers, and filmmakers, current Black lesbian filmmakers are helping to build infrastructure for a transformed future using deeply interconnected methods to transform the whole world and (while we’re at it) the meaning of life. This chapter looks at two projects, the established and evolving Queer Women of Color Media Arts Project based in San Francisco and the emerging Queer Renaissance and Black Feminist Film School Project based in Durham, North Carolina, as examples of the robust future of Black lesbian filmmaking as a transformative community-building practice. The Queer Women of Color
Keywords: 1-Cinéma; 2-Genre et sexualité; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice LGBTQ+; 5-Créateur.rice noir.e; _Nettoyé

Narrating Our History: An Introduction - Harris, Thomas Allen (Sisters in the Life: A History of Out African American Lesbian Media-Making, 2018)
Around 1994 or 1995 I came across a call for articles for an anthology to be published by the XII Black International Cinema , documenting ten years of the festival and associated activities, 1986– 95. The request asked for articles and film lists from an international and intercultural group of scholars and filmmakers, and I thought this was an opportunity to document the exciting and pioneering work that was being done by a community of emerging Black lesbian and gay film-and video makers at the time.
Keywords: 1-Cinéma; 2-Approches sociologiques; 2-Genre et sexualité; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice LGBTQ+; 5-Créateur.rice noir.e; _Nettoyé

Identity and Performance in Yvonne Welbon’s Remembering Wei-Yi Fang, Remembering Myself: An Autobiography - Heitner, Devorah (Sisters in the Life: A History of Out African American Lesbian Media-Making, 2018)
In novel ways, and from a surprising location, Yvonne Welbon’s Remembering Wei-Yi Fang, Remembering Myself: An Autobiography (1995) explores some of the same dilemmas that earlier African American expatriate artists promulgated, using their time abroad as a win dow onto America, while relishing the nurturing possibilities of partial escape from American racism. Some of the most complex and insightful observations about America and American racism have been crafted by African American expatriate artists such as James Baldwin and Josephine Baker. These artists’ depictions of their encounters abroad complicate our understandings of American identity and American racism.
Keywords: 1-Cinéma; 2-Approches sociologiques; 2-Étude des industries culturelles; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Créateur.rice LGBTQ+; 5-Identités diasporiques; _Nettoyé

The Book of Ruins and Desire: Interactive Mechatronic Sculpture - Jennings, Pamela L. (Sisters in the Life: A History of Out African American Lesbian Media-Making, 2018)
The interactive book is a term heard frequently in reference to early experiments in multimedia production. But how to translate the concept of the book into a medium that has no paper, no pages, remains a challenge. Is not a book an object one holds in one’s hands—the cover affected over time by the acids and oils perspiring from the user’s skin, pages turned down and yellowed, torn or marked up? Research could show that the notion of the traditional book has been challenged throughout history. But this challenge has been accelerated with the growing accessibility of new computer
Keywords: 1-Cinéma; 2-Genre et sexualité; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Créateur.rice LGBTQ+; 5-Créateur.rice noir.e; _Nettoyé

Construction of Computation and Desire: Introduction to Yvonne Welbon’s Interview with Pamela L. Jennings - Keeling, Kara (Sisters in the Life: A History of Out African American Lesbian Media-Making, 2018)
Early in the following interview, Pamela Jennings explains to Yvonne Welbon that her work gradually expanded from an initial and abiding interest in street photography toward working with and through forms of computational media. Jennings equates her move toward what she describes as “computational-based creative expression” with her growing interest in multimedia throughout the early 1990s, and she uses the term multimedia as a way of marking her work in a variety of different media and her interest specifically in computational media because the formulation computational media was not available to her then. The compelling relationship Jennings narrates between her
Keywords: 1-Cinéma; 2-Genre et sexualité; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Créateur.rice LGBTQ+; 5-Créateur.rice noir.e; _Nettoyé

Producing Black Lesbian Media - Moore, Candace (Sisters in the Life: A History of Out African American Lesbian Media-Making, 2018)
In interviews the comedian Wanda Sykes describes being a successful black, openly gay woman in Hollywood as akin to being a unicorn. Clearly Sykes is majestic. Yet her joke hinges on a bitter truth: the mainstream media industry grants few women, not to mention lesbians of color, access to power. Despite shifts in the cultural imaginary around civil rights, Hollywood continues to maintain an embarrassing lack of diversity in its labor force, especially at decision-making levels. To battle this long-standing reputation, studios have developed diversity-hiring programs.
Keywords: 1-Cinéma; 2-Genre et sexualité; 2-Étude des industries culturelles; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Créateur.rice LGBTQ+; 5-Créateur.rice noir.e; _Nettoyé

A Cosmic Demonstration of Shari Frilot’s Curatorial Practice - Rastegar, Roya (Sisters in the Life: A History of Out African American Lesbian Media-Making, 2018)
Shari Frilot is a filmmaker and curator whose creative practice has been driven by sustained explorations of sexuality, technology, desire, cosmic and subatomic structures, mixed-raced identity, and chaos. She has often expressed her modus operandi in the following terms: “It’s impossible to see a cloud when you’re in the middle of it. You have to move outside of the cloud to really get a sense of it.” By continually shifting between the outside and inside of a given framework—whether institutional or personal—Frilot has developed keen modes of challenging conventional structures for understanding and engaging the moving image.
Keywords: 1-Cinéma; 2-Genre et sexualité; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Créateur.rice LGBTQ+; 5-Créateur.rice noir.e; _Nettoyé

Shine Louise Houston: An Interstice of Her Own Making - Stallings, L. H. (Sisters in the Life: A History of Out African American Lesbian Media-Making, 2018)
It is the twenty-first century, and there is a black lesbian director and producer making pornography! Porn, a genre of film and media that in the last quarter of the twentieth century many black feminist lesbians viewed as capable only of representing and manifesting violence, abuse, and shame. In this essay I examine one of the early works of the black lesbian filmmaker Shine Louise Houston, In Search of the Wild Kingdom (2007), to explore how and why we have arrived at what is a transition from Blues Legacies and Black Feminisms to Pink and White Productions, and from New
Keywords: 1-Cinéma; 2-Genre et sexualité; 2-Étude des industries culturelles; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Créateur.rice LGBTQ+; 5-Créateur.rice noir.e; _Nettoyé

Ruins and Desire: Interview with Pamela L. Jennings - WELBON, Yvonne (Sisters in the Life: A History of Out African American Lesbian Media-Making, 2018)
In the 1990s I lived in New York City. I moved to New York City shortly after graduating from Oberlin College, in Ohio. I lived there for almost a de cade, and during that time I was very actively engaged in continuing my pursuit of a career in photography. Photography was my first form of visual art going back to junior high school. I enrolled in the New York University International Center for Photography master’s program because I really wanted to understand what it was to be a photographer. At that time I was very interested in street photography.
Keywords: 1-Cinéma; 2-Genre et sexualité; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 5-Auteur.rice LGBTQ+; 5-Créateur.rice noir.e; _Nettoyé

Stepping Out on Faith: Interview with Coquie Hughes - Welbon, Yvonne (Sisters in the Life: A History of Out African American Lesbian Media-Making, 2018)
I grew up on the West Side of Chicago, where it was infested with gangs and drugs and violence. But I was always the type of person that wanted to be better than my environment, and I was also the type of person that didn’t want people to underestimate me because of where I came from. And so I made up in my mind, even as a young child, that I wanted to be somebody. I love making movies. I’ve wanted to be who I am ever since I saw Sidney Lumet’s movie The Wiz (1978).
Keywords: 1-Cinéma; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Créateur.rice LGBTQ+; 5-Créateur.rice noir.e; _Nettoyé

From Rage to Resignation: Reading Tina Mabry’s Mississippi Damned as a Post–Civil Rights Response to Nina Simone’s “Mississippi Goddam” - Moore, Marlon Rachquel (Sisters in the Life: A History of Out African American Lesbian Media-Making, 2018)
Much has been written about Nina Simone’s song “Mississippi Goddam” because it lyrically achieves the political consciousness of the embattled community whose experiences and energy it intends to speak to, through, and for. With its curse words, impatient tone, and energetic rhythm, it could never be mistaken for the traditional, Christian-inflected civil rights dirge. “Alabama’s got me so upset,” the chorus complains. “Tennessee made me lose my rest, and,” as if its atrocities need not be spelled out, “every body knows about Mississippi, goddam!” The song was banned from radio airplay but still became part of the civil rights sound
Keywords: 1-Cinéma; 2-Approches sociologiques; 2-Genre et sexualité; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice noir.e; 5-Créateur.rice LGBTQ+; _Nettoyé

Birth of a Notion: Toward Black, Gay, and Lesbian Imagery in Film and Video - Parkerson, Michelle (Sisters in the Life: A History of Out African American Lesbian Media-Making, 2018)
In mainstream media, gays and lesbians of color are either woefully present or predictably absent. The litany of black gay and lesbian characters in Hollywood films and network television reads like its own form of blackface. They range from the burly, black “bulldagger” as whore house madam in the 1933 film The Emperor Jones (starring Paul Robeson) to the predatory lesbian vamp in Spike Lee’s 1983 She’s Gotta Have It ; from Eddie Murphy’s ultracamp Miss Thing hairdresser on NBC’s Saturday Night Live to the snap! queen duo on Fox TV’s In Living Color. These relentless stereo types are part of
Keywords: 1-Cinéma; 2-Genre et sexualité; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); _Nettoyé

“Invite Me In!”: Angela Robinson at Hollywood’s Threshold - White, Patricia (Sisters in the Life: A History of Out African American Lesbian Media-Making, 2018)
In 2005 Angela Robinson released her spy spoof, D.E.B.S. (2004). Robinson first realized the project as the short film D.E.B.S. (2003) through a training program with POWER UP (Professional Organization of Women in Entertainment Reaching Up), the only 501(c)(3) nonprofit film production company and educational organization for women and the GLBTQ community. In 2005 she also became the second black woman and first black lesbian to direct a studio feature, the Disney film Herbie Fully Loaded starring Lindsay Lohan. This moment marked the beginning of the black lesbian media maker hyphenate as Angela Robinson moved to television and began working on The L Word as a writer, director, and eventually producer. Patricia White's essay in this section, "'Invite Me In!': Angela Robinson at the Hollywood Threshold," offers an in-depth exploration of her career trajectory.
Keywords: 1-Cinéma; 2-Genre et sexualité; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Créateur.rice LGBTQ+; 5-Créateur.rice noir.e; _Nettoyé

Stereotypy, Mammy, and Recovery in Cheryl Dunye’s The Watermelon Woman - Wimbley, Karin D. (Sisters in the Life: A History of Out African American Lesbian Media-Making, 2018)
The Mammy has been in our field of vision as a popular icon representing black womanhood for more than a century in literature, film, and television and in consumer and material culture.¹ Described as an asexual, rotund slave of older age whose sole responsibility is to take care of her master’s children, Mammy is a beloved character who represents all that is nurturing and maternal. She is dark-skinned and boisterous and thought to have mannish features such as large feet and hands. Mammy wears a large skirt, hiding her sex, and covers her nappy hair with a bandanna or handkerchief.
Keywords: 1-Cinéma; 2-Genre et sexualité; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Créateur.rice LGBTQ+; 5-Créateur.rice noir.e; _Nettoyé

Queering the Globe: A Conversation with Rosalind Galt and Karl Schoonover on Queer Cinema in the World - Longo, Regina (Film Quarterly, 2016)
Galt and Schoonover conceived and developed this book through a queer critical lens that invites questions and does not pretend to know—or desire to know—every possible outcome. Queer is neither adjective nor noun for Galt and Schoonover. Queer is a verb, and a transitive one at that. Queering the world and queering cinema studies are active processes in which Schoonover and Galt delight as theorists, historians, and consumers of media. To extend the travel metaphor a step further: they are intrepid, genial travel guides, and so much more.
Keywords: 1-Cinéma; 2-Approches sociologiques; 2-Genre et sexualité; 4-Amérique du Nord (lieu de production du savoir); _Nettoyé

Queer Times, Black Futures - Kara Keeling (New York University Press, 2019)
Finalist, 2019 Lambda Literary Award in LGBTQ StudiesA profound intellectual engagement with Afrofuturism and the philosophical questions of space and time Queer Times, Black Futures considers the promises and pitfalls of imagination, technology, futurity, and liberation as they have persisted in and through racial capitalism. Kara Keeling explores how the speculative fictions of cinema, music, and literature that center black existence provide scenarios wherein we might imagine alternative worlds, queer and otherwise. In doing so, Keeling offers a sustained meditation on contemporary investments in futurity, speculation, and technology, paying particular attention to their significance to queer and black freedom.Keeling reads selected works, such as Sun Ra's 1972 film Space is the Place and the 2005 film The Aggressives, to juxtapose the Afrofuturist tradition of speculative imagination with the similar “speculations” of corporate and financial institutions. In connecting a queer, cinematic reordering of time with the new possibilities technology offers, Keeling thinks with and through a vibrant conception of the imagination as a gateway to queer times and black futures, and the previously unimagined spaces that they can conjure.
Keywords: 1-Cinéma; 2-Genre et sexualité; 2-Méthodologie de recherche décoloniale; 2-Étude des industries culturelles; 3-Amérique du Nord (corpus analysé); 5-Identités diasporiques; _Nettoyé

ALT 36: Queer Theory in Film and Fiction: African Literature Today - Emenyonu, Ernest N.; Hawley, John C. (Boydell & Brewer, 2018)
"Debates on the future of the African continent and the role of gender identities in these visions are increasingly present in literary criticism forums as African writers become bolder in exploring the challenges they face and celebrating gender diversity in the writing of short stories, novels, poetry, plays and films. Controversies over the rights of Lesbian, Gay, Bisexual, Trans, Intersex, Queer (LGBTIQ) communities in Africa, as elsewhere, continue in the context of criminalization and/or intimidation of these groups. Residual colonial moralizing and contemporary western identity norms and politics vie with longstanding polyvalent indigenous sexual expression. In addition to traditional media, the new social media have gained importance, both as sources of information exchange and as sites of virtual construction of gender identities. As with many such contentious issues, the variety of responses to the "state of the question" is strikingly visible across the continent. In this issue of ALT, guest editor John Hawley has sampled the ongoing conversations, in both African writing and in the analysis of contemporary African cinema, to show how queer studies can break with old concepts and theories and point the way to new gender perspectives on literary and cinematic output. This volume also includes a non-themed section of Featured Articles and a Literary Supplement."–Publisher's description
Keywords: 1-Cinéma; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude des industries culturelles; 3-Afrique (corpus analysé); 4-Europe (lieu de production du savoir); 5-Auteur.rice noir.e; 5-Créateur.rice LGBTQ+; 5-Identités diasporiques; _Nettoyé

Impossible Presence: Toward a Queer Singapore Cinema, 1990s–2000s - Chan, Kenneth (Queer Singapore : Illiberal Citizenship and Mediated Cultures, 2012)
The writer frames his analysis of Kan Lume and Loo Zihan's feature length film Solos (2007) with a historical overview of the representation of queer sexualities in new Singaporean cinema. This approach also takes in the Penal Code Section 377A, arguing that not only do these repressive laws force queer sexualities to the margins of culture and society, but also that the State's censorship laws are a means by which it can reify ‘the Asian value system's supposed rejection of queerness’.
Keywords: 1-Cinéma; 2-Approches sociologiques; 2-Genre et sexualité; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); _Nettoyé

The Kids Are Not All Right: The Curious Case of Sapphic Censorship in City-State Singapore - Chen, Loretta (Queer Singapore : Illiberal Citizenship and Mediated Cultures, 2012)
The writer examines Singapore's Media Development Authority's censorship of representations of lesbianism in film, music video, television and theatre. She highlights the government surveillance and repression of portrayals of LGBT cultures and communities in Singapore by unpacking the ambiguities and contradictions underlying the censorship of these popular media forms. This reflects an institutional ‘inability to read lesbians’.
Keywords: 1-Cinéma; 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); _Nettoyé

Queer Cultural Movements and Local Counterpublics of Sexuality: a Case of Seoul Queer Films and Videos Festival - Kim, Jeongmin; Hong, Sunghee (Inter-Asia Cultural Studies, 2007)
This study is an attempt to examine the ways in which popular culture can restructure the relationship between sexuality and power, through the case of Seoul Queer Films and Videos Festival, a cultural arena of newly emerged queer discourses in Korean society. In the past 10 years, queer discourses in Korea have undergone a rapid change. With heterosexual normativity being challenged and ‘queer’ being consumed as a cultural code, Korean spectators come to engage with a queer film festival in multilateral and sometimes contradictory contexts. This study will try to pose a controversial question to the heterosexual society by reading the complex interactions between film festivals, films and spectators while paying attention to the experiences of the participants in the Seoul Queer Films and Videos Festival and pointing at the political implications of queer films now in 2006. Through this, I try to look for possibilities of a queer cultural movement which rejects being co‐opted by the heterosexual society, constructs new ideas of social powers in relation with sexuality, and seeks alternative visions for such change in relations.
_eprint: https://doi.org/10.1080/14649370701568086
Keywords: 1-Cinéma; 2-Genre et sexualité; 3-Asie (corpus analysé); _Nettoyé

Queer Cinema in the World - Padva, Gilad (Historical Journal of Film, Radio and Television, 2019)
Karl Schoonover and Rosalind Galt’s Queer Cinema in the World initially proposes a radical comparative vision of cinema’s queer globalism. It aims to explore how queer filmmaking intersects with international sexual cultures, geopolitics, and aesthetics to disrupt dominant modes of world making.
_eprint: https://doi.org/10.1080/01439685.2019.1600882
Keywords: 1-Cinéma; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 4-Amérique du Nord (lieu de production du savoir); _Nettoyé

Lesbian Cinema after Queer Theory - Bradbury-Rance, Clara (Edinburgh University Press, 2019)
The unprecedented increase in lesbian representation over the past two decades has, paradoxically, coincided with queer theory’s radical transformation of the study of sexuality. In Lesbian Cinema after Queer Theory, Clara Bradbury-Rance argues that this contradictory context has yielded new kinds of cinematic language through which to give desire visual form. By offering close readings of key contemporary films such as Blue Is the Warmest Colour, Water Lilies and Carol alongside a broader filmography encompassing over 300 other films released between 1927 and 2018, the book provokes new ways of understanding a changing field of representation. Bradbury-Rance resists charting a narrative of representational progress or shoring up the lesbian’s categorisation in the newly available terms of the visible. Instead, she argues for a feminist framework that can understand lesbianism’s queerness. Drawing on a provocative theoretical and visual corpus, Lesbian Cinema after Queer Theory reveals the conditions of lesbian legibility in the twenty-first century.
Keywords: 1-Cinéma; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude des représentations; 4-Europe (lieu de production du savoir); 5-Créateur.rice LGBTQ+; _Nettoyé

Hollywood at the Intersection of Race and Identity - Konzett, Delia Caparoso. (Rutgers University Press,, 2020)
Hollywood at the Intersection of Race and Identity explores the ways Hollywood represents race, gender, class, and nationality at the intersection of aesthetics and ideology and its productive tensions. This collection of essays asks to what degree can a close critical analysis of films, that is, reading them against their own ideological grain, reveal contradictions and tensions in Hollywood’s task of erecting normative cultural standards? How do some films perhaps knowingly undermine their inherent ideology by opening a field of conflicting and competing intersecting identities? The challenge set out in this volume is to revisit well-known films in search for a narrative not exclusively constituted by the Hollywood formula and to answer the questions: What lies beyond the frame? What elements contradict a film’s sustained illusion of a normative world? Where do films betray their own ideology and most importantly what intersectional spaces of identity do they reveal or conceal?
Pages: ix, 357 pages :
Keywords: 1-Cinéma; 2-Histoire/Historiographie critique; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); _Nettoyé

Embodied Female Experience Through the Lens of Imagination - Green, Sharon R. (Journal of Analytical Psychology, 2010)
In 1971, I made a film entitled Self Portrait of a Nude Model Turned Cinematographer in which I explore the objectifying ‘male’ gaze on my body in contrast to the subjective lived experience of my body. The film was a radical challenge to the gaze that objectifies woman – and thus imprisons her – which had hitherto dominated narrative cinema. Since the objectification of women has largely excluded us from the privileged phallogocentric discourses, in this paper I hope to bring into the psychoanalytic dialogue a woman's lived experience. I will approach this by exploring how remembering this film has become a personally transformative experience as I look back on it through the lens of postmodern and feminist discourses that have emerged since it was made. In addition, I will explore how this process of imaginatively looking back on an artistic creation to generate new discourses in the present is similar to the transformative process of analysis. Lastly, I will present a clinical example, where my embodied countertransference response to a patient's subjection to the objectifying male gaze opens space for a new discourse about her body to emerge.
_eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1111/j.1468-5922.2010.01847.x
Keywords: 1-Cinéma; 2-Genre et sexualité; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice; _Nettoyé

DV-made Tibet: Domestic Videos, Elite Films, and the Work of Pema Tseden - Barnett, Robert (DV-Made China: Digital Subjects and Social Transformations after Independent Film, 2015)
In the three decades after 1980, major changes took place in the ways in which culture in Tibet was produced, transmitted, and consumed.¹ These changes, however, were not evidence of the radical transformation often claimed as the result of digitization, but were brought about by earlier forms of technological development. In terms of music and radio, it was the arrival of cheap cassette players and recorders in Tibet in the late 1980s that allowed Tibetans to choose for the first time when to listen and, within the limits allowed by the market and the government, what to listen to (Dhondup
Keywords: 1-Cinéma; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); _Nettoyé

APPENDIX II: Tibetan Filmography/Videography - Barnett, Robert; Zhen, Zhang; Zito, Angela (DV-Made China: Digital Subjects and Social Transformations after Independent Film, 2015)
Keywords: 1-Cinéma; 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Identités diasporiques; _Nettoyé

APPENDIX I: Chinese and Non-Chinese Filmography/Videography - Cho, Ting-Wu; Zhen, Zhang; Zito, Angela (DV-Made China: Digital Subjects and Social Transformations after Independent Film, 2015)
Keywords: 1-Cinéma; 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Identités diasporiques; _Nettoyé

Chinese Independent Cinema in the Age of “Digital Distribution” - Gao, Dan (DV-Made China: Digital Subjects and Social Transformations after Independent Film, 2015)
My chapter looks at Chinese independent cinema as an institutionalizing enterprise. In other words, although many filmmakers keep emphasizing the individualistic quality of their agenda or the idiosyncrasy of their film works, independent films have developed things in common, such as certain thematics, addresses, formalistic styles, and modes of production. Their survival is also predicated more and more on shared infrastructures of film communities, distribution agents, and exhibition networks. Of course, this does not mean that the institution of Chinese independent cinema is settled and finalized; it isn’t like a breed of crops circled by impermeable ideological or physical fences.
Keywords: 1-Cinéma; 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Identités diasporiques; _Nettoyé

Filming Power and the Powerless: Zhao Liang’s Crime and Punishment (2007) and Petition (2009) - Li, Jie (DV-Made China: Digital Subjects and Social Transformations after Independent Film, 2015)
This article discusses two recent works by emerging documentary auteur Zhao Liang, Crime and Punishment(2007) and Petition(2009). These penetrating observations of state-society relations in contemporary China render visible those who are un(der)represented, critique the deception of mass media images, and show the various complex ways in which power is connected to surveillance and visibility. Thus the filmmaker, his camera, and the spectators are implicated in power relationships as we cast voyeuristic, panoptic, activist, empathetic, or critical gazes upon the representatives of state power and upon the disenfranchised.
Keywords: 1-Cinéma; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des représentations; 3-Asie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); _Nettoyé

Marking the Body: The Axiographics of the Visible Hidden Camera - Nornes, Abé Mark (DV-Made China: Digital Subjects and Social Transformations after Independent Film, 2015)
This chapter contemplates the ethical dimensions of the specific brand of observational cinema found in China. Because there is no popular understanding of independent documentary—and also because filmmakers almost invariably use amateur video cameras and shoot alone—many subjects are oblivious to the fact that their images are being captured for films being screened around the world. It is in this sense that, while their cameras are perfectly visible, they are also hidden. This enables directors to capture “life unawares,” as if people were being shot by a hidden camera. In this context, directors make the films they want, ignoring the ethical implications of shooting people without being upfront about their intentions or asking for consent. The chapter closely examines a set of films to explore the axiographics of the documentary, in other words how ethics is rendered in the time and space of the moving image.
Keywords: 1-Cinéma; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); _Nettoyé

Chinese Digital Shadows: Hybrid Forms, Bodily Archives, and Transnational Visions - Reynaud, Bérénice (DV-Made China: Digital Subjects and Social Transformations after Independent Film, 2015)
Taking Hao Jie’s Single Man as a case study, this chapter discusses the effect of globalization on independent DV production—a home-grown phenomenon born out of the availability of DV cameras and computer editing software and the spreading of the internet. Starting as a marginalized practice without access to the domestic market, and expressing a desire to saturate the visual field with obfuscated images and to create a counter-archive (a counter-memory of the Chinese people), it attracted international attention, which in turn allowed it to have access to alternative forms of financing as well as the input of foreign talent. The fluidity of digital modes of production also contributed to an eradication of the boundaries between documentary and fiction. Instead, the real divide lies between “the desire for cinema” and “the desire for documentation.”
Keywords: 1-Cinéma; 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); _Nettoyé

“To Whom Do Our Bodies Belong?”: Being Queer in Chinese DV Documentary - Robinson, Luke (DV-made China : digital subjects and social transformations after independent film, 2015)
In 1990s post-Reform China, a growing number of people armed with video cameras poured out upon the Chinese landscape to both observe and contribute to the social changes then underway. This digital turn has given us a 'DV China' that includes film and media communities across different social strata and disenfranchised groups. This study takes stock of these phenomena by surveying the social and cultural landscape of grassroots and alternative cinema practices.
Keywords: 1-Cinéma; 2-Étude de la réception; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Identités diasporiques; _Nettoyé

The Spectacular Crowd: Representing the Masses in DV Documentary - Shen, Shuang (DV-Made China: Digital Subjects and Social Transformations after Independent Film, 2015)
In their introduction to a collaborative study of crowds organized by the Stanford Humanities Lab in 2000, Jeffrey T. Schnapp and Matthew Tiews observe that while the first half of the twentieth century witnessed a rise of collective social action and various forms of mass assembly, the second half was a period of the decline of collective political formations and the replacement by virtual and media-based assemblies for physical crowds (Schnapp and Tiews 2006, xi). The postindustrial political economy in the West is “characterized by the coexistence of media aggregation and bodily disaggregation,” Schnapp and Tiews claim (xi).
Keywords: 1-Cinéma; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des représentations; 3-Asie (corpus analysé); _Nettoyé

The Cruelty of the Social: Xianchang, Intersubjectivity, and Interobjectivity - Sniadecki, J. P. (DV-Made China: Digital Subjects and Social Transformations after Independent Film, 2015)
At the closing awards ceremony for the 7th Annual DOChina Festival held in May 2010 in Songzhuang—a gentrified artists’ village at the far eastern edge of the Beijing municipality—young animator, poet, and filmmaker Xue Jianqiang was recognized with an honorable mention for his haunting documentary Martian Syndrome. The award came with 2000 RMB, a Panasonic DV camera (the jury’s official comments noted that Xue lacked his own camcorder and had to borrow one to make his film), and the chance to speak before a gathering of who’s who in Chinese independent documentary filmmaking.
Keywords: 1-Cinéma; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des représentations; 3-Asie (corpus analysé); 5-Identités diasporiques; _Nettoyé

DV and the Animateur Cinema in China - Voci, Paola (DV-Made China: Digital Subjects and Social Transformations after Independent Film, 2015)
Film scholarship on the movie-making, movie-viewing, and movie-circulating practices that have developed since the mid-1990s in China has appropriately emphasized the role played by the rise of digital video (DV) and its impact on independent and, in particular, documentary filmmaking. In this chapter, I want to explore one line of development in DV independent production that has received much less attention—what I call animateur cinema—which concerns short digital animations that are made by and/or circulated for online (or on-mobile) moviemakers/viewers. Fan-originated digital animation or egao animation can also be found online, but my focus is on animateur cinema
Keywords: 1-Cinéma; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des représentations; 3-Asie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); _Nettoyé

The Recalcitrance of Reality: Performances, Subjects, and Filmmakers in 24 City and Tape - Wang, Qi (DV-Made China: Digital Subjects and Social Transformations after Independent Film, 2015)
Since its beginning in the early 1990s, independent Chinese documentary has steadily built a reputation with its unflinching presentation of the underbelly of China’s economic boom and social sea changes. Individuals and groups whose experiences register the drastic costs of this process have become the most natural and common subject matter of independent documentaries. From the struggling artists who were among the first to quit state employment and go independent in Bumming in Beijing (Wu Wenguang 1990) to the art-aspiring young migrants from the rural area in The Other Bank (Jiang Yue 1995), from the homeless youngsters in Along the
Keywords: 1-Cinéma; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 5-Identités diasporiques; _Nettoyé

Toward a Digital Political Mimesis: Aesthetic of Affect and Activist Video - Zhen, Zhang (DV-Made China: Digital Subjects and Social Transformations after Independent Film, 2015)
In 1990s post-Reform China, a growing number of people armed with video cameras poured out upon the Chinese landscape to both observe and contribute to the social changes then underway. This digital turn has given us a 'DV China' that includes film and media communities across different social strata and disenfranchised groups. This study takes stock of these phenomena by surveying the social and cultural landscape of grassroots and alternative cinema practices
Keywords: 1-Cinéma; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); _Nettoyé

Crossing Cameras in China: Christian Aesthetics and Realized Fictions - Zito, Angela (DV-Made China: Digital Subjects and Social Transformations after Independent Film, 2015)
The films of director Gan Xiao’er are the first narrative features to take up Chinese Christians in their everyday concerns. This chapter discusses a pair of his films, one a fiction feature, the other a documentary made about taking that feature on the road and showing it in churches. It is about filmmaking practice—and especially documentary—as social occasion, as the concatenation between people of self-reflective moments of cultural creativity and critique. By social occasion, I mean that Gan has documented in the second film the moments of self-conscious “participation” in the fiction feature and in the documentary itself.
Keywords: 1-Cinéma; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); _Nettoyé

De-Westernizing Film Studies - Ba, Saer Maty; Higbee, Will (Routledge, 2012)
De-Westernizing Film Studies aims to consider what form a challenge to the enduring vision of film as a medium - and film studies as a discipline - modelled on ‘Western’ ideologies, theoretical and historical frameworks, critical perspectives as well as institutional and artistic practices, might take today. The book combines a range of scholarly writing with critical reflection from filmmakers, artists & industry professionals, comprising experience and knowledge from a wide range of geographical areas, film cultures and (trans-)national perspectives. In their own ways, the contributors to this volume problematize a binary mode of thinking that continues to promote an idea of ‘the West and the rest’ in relation to questions of production, distribution, reception and representation within an artistic medium (cinema) that, as part of contemporary moving image culture, is more globalized and diversified than at any time in its history. In so doing, De-Westernizing Film Studies complicates and/or re-thinks how local, national and regional film cultures ‘connect’ globally, seeking polycentric, multi-directional, non-essentialized alternatives to Eurocentric theoretical and historical perspectives found in film as both an artistic medium and an academic field of study. The book combines a series of chapters considering a range of responses to the idea of 'de-westernizing' film studies with a series of in-depth interviews with filmmakers, scholars and critics. Contributors: Nathan Abrams, John Akomfrah, Saër Maty Bâ, Mohammed Bakrim, Olivier Barlet, Yifen Beus, Farida Benlyazid, Kuljit Bhamra, William Brown, Campbell, Jonnie Clementi-Smith, Shahab Esfandiary, Coco Fusco, Patti Gaal-Holmes, Edward George, Will Higbee, Katharina Lindner, Daniel Lindvall, Teddy E. Mattera, Sheila Petty, Anna Piva, Deborah Shaw, Rod Stoneman, Kate E. Taylor-Jones
Keywords: 1-Cinéma; 2-Histoire/Historiographie critique; 2-Méthodologie de recherche décoloniale; 2-Théories et épistémologie postcoloniales et décoloniales; 4-Europe (lieu de production du savoir); 5-Identités diasporiques; _Nettoyé

Contemporary Jewish Reality in Germany and Its Reflection in Film - Dorchain, Claudia Simone; Wonnenberg, Felice Naomi (De Gruyter, 2012)
The notion of “self” and “other” and its representation in artwork and literature is an important theme in current cultural sciences as well as in our everyday life in contemporary Western societies. Moreover, the concept of “self” and “other” and its imaginary dichotomy is gaining more and more political impact in a world of resurfacing ideology-ridden conflicts. The essays deal with Jewish reality in contemporary Germany and its reflection in movies from the special point of view of cultural sciences, political sciences, and religious studies. This anthology presents challengingly new insights into topics rarely covered, such as youth culture or humor, and finally discusses the images of Jewish life as realities still to be constructed.
Publication Title: Contemporary Jewish Reality in Germany and Its Reflection in Film
Keywords: 1-Cinéma; 2-Histoire/Historiographie critique; 2-Étude des représentations; 3-Europe (corpus analysé); 4-Europe (lieu de production du savoir); 5-Auteur.rice; _Nettoyé

A Few of My Favourite Things: The Feiticeiro/a as Foundation for ‘Pervert’ Characterisation - Theo, LJ (Constructing Transgressive Sexuality in Screenwriting: The Feiticeiro/a as Character, 2017)
A non-foundationalist construct for the Feiticeiro/a character that assumes neither an essentialist nature nor a determinist set of activities is possible. This does not prescribe a ‘type’ of ‘pervert’ character, but instead delineates an epistemic framing for a Feiticeiro/a character. This chapter explores an etymologically based semiotic approach to character construction that accounts for a Derridean view that language is constituted by binary reciprocal delimitations and for a view of sex as a dereified expression of materialised instances of engagement by sexual subjects, in terms of which sexuality is rendered as an opened-outward and connected function. The chapter further deals with an approach based in an empathic engagement between audiences and Feiticeiro/a characters, which is apposite for audiences identifying with but not necessarily liking characters. The chapter closes the volume’s argument around how transgressive, sexually focused Feiticeiro/a characters might productively be constructed in terms other than of essences and determinist actions, but in terms of ‘meaning’ found in the points of connection between heterogeneous bodily surfaces.
Keywords: 1-Cinéma; 2-Approches sociologiques; 2-Genre et sexualité; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Identités diasporiques; _Nettoyé

Absenting Heteropatriarchal Discourses: The Invisible ‘Pervert’ - Theo, LJ (Constructing Transgressive Sexuality in Screenwriting: The Feiticeiro/a as Character, 2017)
Conservative discourses remain powerful in contemporary life. These demonise the notion of sexual transgressiveness without helping to give a clear, value neutral definition of what ‘transgressive’ is. Screenwriters attempting to write it into characters are therefore likely to rely on psychiatric epistemologies for sexual ‘perversion’ as framings for subjectivity. Unfortunately, Freudian epistemologies of ‘perversion’ render the psychical subject as invisible through built-in determining comparative reference to heteropatriarchal norms and through distinctions between ‘non-pathological’ and ‘pathological’ definitions. This chapter explores the Freudian constructs that entrench this, together with post-structuralist foundations that might revise the constitution and role of the individual subject (and therefore of filmic characters as facsimiles of real people) as he/she relates to the material world as a physical entity, and as he/she manipulates the discourses to which he/she is subject.
Keywords: 1-Cinéma; 2-Genre et sexualité; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); _Nettoyé

Anthropologically Present ‘Perverts’: Re-instating the Feitiço as the Feiticeiro/a - Theo, LJ (Constructing Transgressive Sexuality in Screenwriting: The Feiticeiro/a as Character, 2017)
A post-humanist lens is useful as a starting-point to remedy the absenting and invisibilising effects of sexological epistemologies for the purposes of conceiving a constitution of ‘pervert’ filmic characters, since certain strains of existential thinking have a meta-theoretical pliancy that is useful for reflecting the non-binary character of complex people beyond simple identity categories, across a range of types and styles of filmic products. If matched with a semiological approach such as that espoused by Barthes, it thereby becomes possible to manipulate signs in the form of character constructions to represent people as more than the sum of their parts and to contain deeper significations that are built into the fabric of their construction. This requires a deeper understanding of the semiotic notion of ‘semes’ as the foundation for character construction. To this end, this chapter explores how sexual ‘perversion’ as reflected in notion of the ‘feitiço’ might serve as a foundation for a new episteme for ‘perverse’ characters, as the Feiticeiro/a as ‘sorcerer/sorceress’.
Keywords: 1-Cinéma; 2-Approches sociologiques; 2-Genre et sexualité; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Identités diasporiques; _Nettoyé

Psychoanalytic Absence: Freudian Object-Focus and the Resultant ‘Pervert Sans-Corpus’ - Theo, LJ (Constructing Transgressive Sexuality in Screenwriting: The Feiticeiro/a as Character, 2017)
The notion of ‘perversity’ suggests inherent transgressiveness. However, a focus on practices does not help identify who filmic characters are in ways that might inform a paradigm for character identity suitable for translation into a visual medium. Failing to achieve this clarity, ‘perverts’ often end up as ‘ambulatory objects’ at once imagined and defined by what is not present. This chapter engages how this manifests in the nineteenth-century sexological discourses that reflected perverse prurience in terms of assumptions that all entities might be empirically identifiable in the same way that material phenomena can be perceived by means of the senses, which is especially visible in the various incarnations of Freudian constructs of ‘fetishism’ that refuse personal agency through reliance on a range of psychodynamic constructs.
Keywords: 1-Cinéma; 2-Approches sociologiques; 2-Genre et sexualité; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); _Nettoyé

Rephrasing Character Action for the Feiticeiro/a: External Coherence Through Transactional Relations - Theo, LJ (Constructing Transgressive Sexuality in Screenwriting: The Feiticeiro/a as Character, 2017)
If character actions are not to be seen in deterministic ways, then an alternative framing should be considered on which writers might base constructs of complexity of action. This is possible if action itself is seen as an expression of relationality rather than as activity-as-substance. Looking at people in this way enables the behaviour of Feiticeiro/a characters to be seen as activities that are more than the actions of combinations of sexed bodies in physical spaces. This chapter explores a construct for action on this basis as it becomes possible by acknowledging in a construct of ‘doing’ the phenomenological notions of ‘being’ as a Feiticeiro/a form constituted by a hybrid of ‘object-discourse-nature-society’ characterised by networks of confluence. The chapter explores the notion of the Feiticeiro/a character in terms of an internal coherency, taking account of interactions and activities (as exhibited through their material form), ‘naturalness’, linearity of course of action and embodied notions of meaning-creation.
Keywords: 1-Cinéma; 2-Genre et sexualité; 2-Recherche-création; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); _Nettoyé

Rephrasing the Feitiço: A New Episteme for Perverse Characters - Theo, LJ (Constructing Transgressive Sexuality in Screenwriting: The Feiticeiro/a as Character, 2017)
Interesting and challenging Hollywood-style films that centre on sexually transgressive characters are not easy to script. Many writers fail as a result of an over-valuation of image at the expense of psychologically complex and challenging subjectivity. A hook for exploring the nature of this phenomenon lies in the notion of ‘involving and disturbing’, with a focus on how films might represent it and how audiences might perceive it, and with attention paid to how characters might be constructed. The chapter expands on how this notion of audience engagement might engage with screenwriting as a design function, aimed to construct characters in visual terms yet through words rather than pictures. In addressing certain epistemic limitations to writing character complexity, an alternative epistemic framing for ‘perverse’ characters is considered in terms of characterological ‘is-ness’, philosophical constitution and behaviours and actions.
Keywords: 1-Cinéma; 2-Genre et sexualité; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); _Nettoyé

The Feiticeiro/a and the Categorical ‘Fetishist’: Sexuality Prescribed Through Psychiatric Classifications - Theo, LJ (Constructing Transgressive Sexuality in Screenwriting: The Feiticeiro/a as Character, 2017)
In seeking to find a solid paradigm for the Feiticeiro/a character, it is tempting to approach the established psychiatric categories. Unfortunately, many of these suggest that people are ineffably different from others and that people will behave according to type in a predictable, even inevitable way. This chapter explores the World Health Organization’s International Classification of Diseases (ICD), which merely re-inscribes essentialist and determinist tendencies by means of processes akin to the phenomenon of cross-linguistic influence and linguistic fixity. The chapter explores further how this is embedded in the category of ‘fetishism’, ‘fetishistic transvestism’ and ‘transvestic fetishism’, which contain certain problematic vestigial tails of Freudian categories that make the psychiatric definitions of ‘fetishism’ unsuitable as a foundation for the Feiticeiro/a character.
Keywords: 1-Cinéma; 2-Analyses formalistes; 2-Approches sociologiques; 2-Genre et sexualité; 4-Amérique du Nord (lieu de production du savoir); _Nettoyé

The Feiticeiro/a as a Materially Identifiable Character: Subjectively Conceived Filmic Participants - Theo, LJ (Constructing Transgressive Sexuality in Screenwriting: The Feiticeiro/a as Character, 2017)
If the Feiticeiro/a character is to be seen as a structure rather than a substance, the nature of such a structure requires elaboration. If this paradigm is to be internally coherent, a relation of intertwined co-existence between characters and audiences should be built into the framing in ways that provide functional epistemic signposts for mechanisms to translate characters’ intrinsic complexity to these audiences. This chapter approaches this by accounting both for the particularly visual nature of the filmic medium and for how screenplays are not a visual medium themselves and are put to different uses than other forms of narrative writing, therefore requiring distinctive attributes. An orientational notion of relationship between medium and audience is suggested as a foundation for the structure of Feiticeiro/a characters in terms of the philosophical distinction between ‘being’ and ‘appearance’, on the basis of which decisions might be made as to which elements of the character’s constitution should be made apparent and which should either remain invisible or intentionally be obfuscated.
Keywords: 1-Cinéma; 2-Genre et sexualité; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); _Nettoyé

The Internally Coherent Feiticeiro/a: A Structure not a Substance - Theo, LJ (Constructing Transgressive Sexuality in Screenwriting: The Feiticeiro/a as Character, 2017)
The categories for ‘perversion’ in the World Health Organization’s ICD fail to describe people and their practices, thereby obscuring the remarkable singularity of individuals and diversity of groups. Instead, they prescribe heteronormative sexual behaviour, which is unhelpful as a foundation for the Feiticeiro/a character. This chapter explores an alternative epistemic construct, as becomes available in the notion of a focalising character, which reflects a ‘semic’ construct that negates the notion of a ‘pervert’ character as a substance, but instead embraces the notion of a Feiticeiro/a character as a structure. The chapter further explores the philosophical nature of this structure as it relates to the thematic elements of a narrative whilst engaging in believable activities in a material world. The chapter then suggests an approach to structure based in a phenomenological notion of the replacement of ‘substance’ with ‘form’/‘structure’ as the foundation of meaning.
Keywords: 1-Cinéma; 2-Analyses formalistes; 2-Approches sociologiques; 2-Genre et sexualité; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); _Nettoyé

Towards an Episteme for the Feiticeiro/a: Realism in Character Construction - Theo, LJ (Constructing Transgressive Sexuality in Screenwriting: The Feiticeiro/a as Character, 2017)
An episteme for the Feiticeiro/a as a filmic character who is ‘perverse’ needs a form if it is to be useful to writers wanting to construct complex transgressive sexual characters. The beginnings of this framing are productively associated with the semiotic notion of ‘connotation’. This chapter explores what is meant by complexity in character construction and suggests a framing focused on character as an embodied being as a helpful starting-point for an episteme for characterological ‘perversion’. The chapter explores this as a non-foundationalist framing that transcends problematic Cartesian distinctions, concrete object materiality and woolly broad-stroke statements of a disembodied discursive constitution of social and personal experience.
Keywords: 1-Cinéma; 2-Analyses formalistes; 2-Approches sociologiques; 2-Genre et sexualité; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); _Nettoyé

Writing ‘Perverse’ Behaviour for the Feiticeiro/a: Revisioning the ICD Diagnostic Criteria - Theo, LJ (Constructing Transgressive Sexuality in Screenwriting: The Feiticeiro/a as Character, 2017)
If the Feiticeiro/a as a psychologically defined and complex character is to be seen as an embodied form/structure (not substance) that exists in dialectical relationships between self, other and discursive constructions of society, a clearer indication should be made about what kinds of behaviours or actions he/she should engage in. This chapter explores how psychiatric diagnostic criteria fail to provide assistance, despite professing to authoritatively mark stable, reliable and accurate epistemic boundaries to sexual activity. The chapter thereby addresses questions of the description of actions versus the demarcation of thoughts, objects, feelings and time as invisible and abstracted notions that are virtually the opposite of what is useful for an episteme for the Feiticeiro/a. It also approaches how the diagnostic criteria codify ‘perverse’ activity in determinist terms, thereby insidiously refusing an epistemic construct of action into which is built an acknowledgement of the behaviours of the Feiticeiro/a as a complex subjectivity.
Keywords: 1-Cinéma; 2-Analyses formalistes; 2-Approches sociologiques; 2-Genre et sexualité; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); _Nettoyé

Cinema's Queer Witness: Ira Sachs's Last Address and the Indifferent View - Rodness, Roshaya (CR: The New Centennial Review, 2019)
Roshaya Rodness is a senior doctoral candidate in the Department of English and Cultural Studies at McMaster University. Her dissertation addresses recent movements in queer theory with a special focus on cinema, poststructuralist ethics, and the nonhuman. She has published in Canadian Literature, Chiasma: A Site for Thought , and World Picture on topics that include contemporary film, indigenous authorship, postcontinental philosophy, and dream theories.
Keywords: 1-Cinéma; 2-Genre et sexualité; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Créateur.rice LGBTQ+; _Nettoyé

Queer Cinema in the World by Karl Schoonover and Rosalind Galt (review) - Llamas-Rodriguez, Juan (QED: A Journal in GLBTQ Worldmaking, 2018)
Karl Schoonover and Rosalind Galt attempt a formidable feat in Queer Cinema in the World: to take three charged yet indispensable concepts and theorize their interconnections. A tour-de-force analysis of the triangulation between “queer,” “cinema,” and “world”, this coauthored monograph largely succeeds in drawing out threads between crucial issues in cinema studies, queer theory, and global studies.
Keywords: 1-Cinéma; 2-Approches sociologiques; 2-Genre et sexualité; 4-Amérique du Nord (lieu de production du savoir); _Nettoyé

All About Almodóvar’s Men - Rey, Juan; Uceda Pérez, Francisco (Peter Lang Inc., International Academic Publishers, 2017)
Pedro Almodóvar is an internationally acclaimed Spanish director. The national and international fascination over Almodóvar's cinema lies in his ability to reflect the problems of contemporary society, his lucidity in combining the urban and the rural, his ability to express the frustrations of modern man, as well as his freshness and spontaneity. Although the vast majority of studies on this Spanish director have focused on women and the gay world, his films are crowded with many types and archetypes of heterosexual men. This groundbreaking edited volume studies the men in the cinema of Almodóvar from a broad yet comprehensive and complementary perspective. Each chapter of All About Almodóvar's Men methodically dissects these male characters—their misery and their greatness, their frustrations and their desires—offering a kaleidoscopic view of man that goes beyond the narrow framework in which many studies have locked the rich cinema of Almodóvar.
Issue: vol. 8
Keywords: 1-Cinéma; 2-Genre et sexualité; 2-Étude des représentations; 3-Europe (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Créateur.rice LGBTQ+; 5-Identités diasporiques; _Nettoyé

African American Cinema Through Black Lives Consciousness - Reid, Mark A. (Wayne State University Press,, 2019)
"African American Cinema through Black Lives Consciousness uses critical race theory to discuss American films that embrace contemporary issues of race, sexuality, class, and gender. Its linear history chronicles black-oriented narrative film from post-World War II through the presidential administration of Barack Obama. Editor Mark A. Reid has assembled a stellar list of contributors who approach their film analyses as an intersectional practice that combines queer theory, feminism/womanism, and class analytical strategies alongside conventional film history and theory. Taken together, the essays invigorate a "Black Lives Consciousness," which speaks to the value of black bodies that might be traumatized and those bodies that are coming into being-ness through intersectional theoretical analysis and everyday activism. The volume includes essays such as Gerald R. Butters's, "Blaxploitation Film," which charts the genre and its uses of violence, sex, and misogyny to provoke a realization of other philosophical and sociopolitical themes that concern intersectional praxis. Dan Flory's "African-American Film Noir" explains the intertextual-fictional and socio-ecological-dynamics of black action films. Melba J. Boyd's essay, "'Who's that Nigga on that Nag?': Django Unchained and the Return of the Blaxploitation Hero," argues that the film provides cultural and historical insight, "signifies" on blackface stereotypes, and chastises Hollywood cinema's misrepresentation of slavery. African American Cinema through Black Lives Consciousness embraces varied social experiences within a cinematic Black Lives Consciousness intersectionality. The interdisciplinary quality of the anthology makes it approachable to students and scholars of fields ranging from film to culture to African American studies alike."
Pages: x, 310 pages :
Keywords: 1-Cinéma; 2-Approches sociologiques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); _Nettoyé

Documenting What? Auto-Theory and Migratory Aesthetics - Bal, Mieke (A Companion to Contemporary Documentary Film, 2015)
As a method of learning more about contemporary culture than written documentation in libraries can provide, some 10 years ago I began to make documentary films. These films and what they showed me became, afterwards, secondary objects of analysis. Learning from and theorizing what I learned by reconsidering my own films yielded insights brought forth by the people “in” them. This became an ongoing, spiraling form of analysis-theory dialectic, and since my own films are the subject of my examination, I call it auto-theory. The best example is my video installation Nothing Is Missing (2006–2010). Here, 17 mothers of migrants, all living in different countries, explain in their own language what happened to their lives when one or more of their children decided to leave. These videos document a relationship, but not the one between maker and subject. The maker, here, is rather a facilitator, and the relationship that is documented, the one between the mother and someone close to her that has been modified by the migration of a child, is transformed in the process. The videos document this transformation itself, in the performance of it. This performative transformation is the subject of my article – it is what is being documented in the films.
Section: 6 _eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1002/9781118884584.ch6
Keywords: 1-Cinéma; 2-Étude des représentations; 4-Amérique du Nord (lieu de production du savoir); 5-Identités diasporiques; _Nettoyé

Reading Realness - Oishi, Eve (A Companion to Contemporary Documentary Film, 2015)
This essay performs a critical comparison of two documentary films about queer and trans people of color, Jennie Livingston's Paris is Burning (1991) and Wu Tsang's Wildness (2012) and examines how the two films negotiate of the politics of representing reality and “realness.” The comparison illuminates two entwined problematics: the ways in which the challenges faced by each film are emblematic of the larger historical context in which they were made, specifically notions of queer community and its subjects; and the ways in which the negotiation of these challenges occurs in relation to a broader field of ethical and formal questions relating to documentary itself.
Section: 12 _eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1002/9781118884584.ch12
Keywords: 1-Cinéma; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude des représentations; 5-Auteur.rice noir.e; 5-Créateur.rice LGBTQ+; _Nettoyé

Documentary Practice and Transnational Feminist Theory - White, Patricia (A Companion to Contemporary Documentary Film, 2015)
This paper looks at five documentaries on activism around ending the practice of female genital cutting (FGC) in Africa. All were made by or in partnership with UK and US producers and are distributed by the New York-based non-profit media arts organization Women Make Movies. By tracing changing political and representational strategies in feminist documentaries on the issue and the varying terms on which the films engage their subjects and address their viewers, the chapter aims to put the specificity of independent documentary formats, practices, and institutions in dialogue with feminist theoretical critiques of the wider discourse on women's human rights. The chapter looks at Kaplan and Grewal's critique of the neo-colonialism of Alice Walker and Pratibha Parmar's Warrior Marks, the observational strategies of Kim Longinotto's The Day I Will Never Forget, the diasporic dimensions of Mrs. Goundo's Daughter and Sarabah, and the visual rhetoric of human rights models in Equality Now's Africa Rising. The cultural field of documentary constitutes a public sphere in which activist and theoretical debate, contested reception, and continually renewed cultural production articulate the productively shifting terms of transnational feminism.
Section: 10 _eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1002/9781118884584.ch10
Keywords: 1-Cinéma; 2-Approches sociologiques; 2-Étude des industries culturelles; 3-Afrique (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Identités diasporiques; _Nettoyé

Open World Empire: Race, Erotics, and the Global Rise of Video Games - Patterson, Christopher B (New York University Press, 2021)
Seeking ways to understand video games beyond their imperial logics, Patterson turns to erotics to re-invigorate the potential passions and pleasures of play.
OCLC: 1237769915
Keywords: 1-Jeux vidéo; 2-Genre et sexualité; 2-Méthodologie de recherche décoloniale; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des industries culturelles; 2-Étude des représentations; 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé

The Race Card: from Gaming Technologies to Model Minorities - Fickle, Tara (New York University Press, 2020)
This book uncovers popular games' key role in the cultural construction of modern racial fictions. It argues that gaming provides the lens, language, and logic - in short, the authority - behind racial boundary making, reinforcing and at times subverting beliefs about where people racially and spatially belong. It focuses specifically on the experience of Asian Americans and the longer history of ludo-Orientalism, wherein play, the creation of games, and the use of game theory shape how East-West relations are imagined and reinforce notions of foreignness and perceptions of racial difference.
OCLC: 1155499741
Keywords: 1-Jeux vidéo; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude de la réception; 2-Étude des industries culturelles; 2-Étude des représentations; 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; _Nettoyé

White Out: the Continuing Significance of Racism. - Doane, Ashley W; Bonilla-Silva, Eduardo (Taylor and Francis, 2013)
What does it mean to be white? This remains the question at large in the continued effort to examine how white racial identity is constructed and how systems of white privilege operate in everyday life. White Out brings together the original work of leading scholars across the disciplines of sociology, philosophy, history, and anthropology to give readers an important and cutting-edge study of ""whiteness""
Keywords: 1-Cinéma; 1-Histoire de l'art; 1-Jeux vidéo; 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé

COLONIALITÉ ESTHÉTIQUE ET ART CONTEMPORAIN

Prácticas co-creativas. Decolonizar la naturaleza - Yeregui, Mariela (Artelogie. Recherche sur les arts, le patrimoine et la littérature de l'Amérique latine, 2017)
El diálogo arte-tecnología en América Latina pone en foco litigios recurrentes: ¿tecnologías sustentadas por los discursos legitimantes de la modernidad o paradigmas diferentes y periféricos en la asunción e ideación de tecnologías en el contexto del arte? ¿Qué sucede con las prácticas que incorporan elementos biológicos, habitualmente uniformizadas bajo la categoría de “bioarte”? Las prácticas artísticas tecnológicas en Argentina en los últimos diez años alumbran zonas de pensamiento y praxis que ameritan ser revisadas: el diálogo arte/naturaleza desde perspectivas no-antropocéntricas, la configuración de discursos en los que subyacen representaciones, miradas y prácticas que se apartan de cánones normalizados y, por último, operaciones disruptivas en lo que respecta a los algo usuales criterios de funcionalidad, utilitarismo y efectismo tecnológico.
Keywords: 1-Histoire de l'art; 2-Humanités numériques; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Sud (corpus analysé); 4-Amérique du Sud (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé

Discours sur le colonialisme ; suivi de Discours sur la négritude - Césaire, Aimé (2015)
Comme naguère Jean-Jacques Rousseau dénonçait le scandale d'une société fondée sur l'inégalité, avec la même clarté, et un bonheur d'écriture que seule peut inspirer la passion du juste, Aimé Césaire prend ses distance par rapport au monde occidental et le juge. Ce discours est un acte d'accusation et de libération. Sont assignés quelques ténors de la civilisation blanche et de son idéologie mystifiante, l'Humanisme formel et froid. En pleine lumière sont exposées d'horribles réalités : la barbarie du colonisateur et le malheur du colonisé, le fait même de la colonisation qui n'est qu'une machine exploiteuse d'hommes et déshumanisante, une machine à détruire des civilisations qui étaient belles, dignes et fraternelles. C'est la première fois qu'avec cette force est proclamée, face à l'Occident, la valeur des cultures nègres. Mais la violence de la pureté du cri sont à la mesure d'une grande exigence, ce texte chaud, à chaque instant, témoigne du souci des hommes, d'une authentique universalité humaine. Il s'inscrit dans la lignée de ces textes majeurs qui ne cessent de réveiller en chacun de nous la générosité de la lucidité révolutionnaires. Le Discours sur le colonialisme est suivi du Discours sur la Négritude, qu'Aimé Césaire a prononcé à l'Université Internationale de Floride (Miami), en 1987.
Keywords: 1-Cinéma; 1-Histoire de l'art; 1-Jeux vidéo; 1-TV; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Afrique (corpus analysé); 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; _Nettoyé

La (dé)mythification de l’artiste colombien MIGUEL ÁNGEL ROJAS ET JOSÉ ALEJANDRO RESTREPO - de la Cruz Lichet, Virginia (Revue Proteus, 2019)
Depuis quelques décennies, certains artistes colombiens cherchent à repenser ce que peut être aujourd’hui l’identité colombienne, et plus concrètement celle de l’artiste. Au-delà du stéréotype de ce qu’est le « Colombien » vu de l’extérieur, au-delà d’une histoire coloniale – et toutes ses problématiques – commune aux pays d’Amérique latine, ainsi que d’une histoire récente plus particulière connue pour son extrême violence, nous pouvons affirmer que l’identité colombienne est le résultat d’identités multiples, diverses et variées. Par ailleurs, il existe un dénominateur commun qui peut la définir car elle s’est construite durant ces deux derniers siècles à partir d’un concept : celui de « l’hybridité ».
Keywords: 1-Histoire de l'art; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Sud (corpus analysé); 4-Europe (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Créateur.rice PANDC; _Nettoyé

Kent Monkman : entre ré/appropriation et « Painting Back ». - Pancaldi, Valentina (Artelogie. Recherche sur les arts, le patrimoine et la littérature de l'Amérique latine, 2018)
À la suite d’une série d’évènements historiques de grande relevance sociopolitique, les années 1990 ont connu une montée d'initiatives menées par les artistes autochtones nord-américains visant à une récupération et une divulgation de leur l’héritage culturel, et, de ce fait, à une revendication de leur visibilité dans le panorama international. De cette résurgence, l’artiste multimédial autochtone canadien, Kent Monkman, constitue l’une des voix plus actives et plus emblématiques. En créant un dialogue épistémologique entre les études postcoloniales et l’art autochtone, cet article interrogera l’œuvre de Kent Monkman au prisme d’une notion dont sera proposée une définition, à savoir le « Painting Back ».
Keywords: 1-Histoire de l'art; 2-Analyses formalistes; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice; 5-Créateur.rice autochtone; _Nettoyé

Décoloniser la photographie documentaire : le collectif Rawiya en Palestine - Razek, Sherena (AWARE : Archives of Women Artists, Research and Exhibitions, 2019)
Keywords: 1-Histoire de l'art; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Asie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Créateur.rice PANDC; _Nettoyé

Réécrire les mémoires et dénoncer l’histoire : l’art postcolonial - Meisel, Nina (AWARE : Archives of Women Artists, Research and Exhibitions, 2020)
Keywords: 1-Histoire de l'art; 2-Genre et sexualité; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Afrique (corpus analysé); 3-Asie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Créateur.rice PANDC; _Nettoyé

Artistes afro-brésiliennes, d’un siècle à l’autre - Giunta, Andrea (AWARE : Archives of Women Artists, Research and Exhibitions, 2021)
Keywords: 1-Histoire de l'art; 2-Genre et sexualité; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Sud (corpus analysé); 4-Amérique du Sud (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Créateur.rice noir.e; _Nettoyé

Postcolonial/Décolonial: La preuve par l'art - Toussaint, Évelyne (Presses universitaires du Midi, 2021)
"Les liens entre l'art contemporain et les questions de colonialité, postcolonialité, et décolonialité sont anciens et multiples. Des artistes occidentaux et non-occidentaux, depuis plusieurs décennies déjà, s'en sont emparés pour produire des œuvres qui témoignent de leurs engagements politiques, sociétaux et esthétiques. Des concepts que les études postcoloniales ont approfondies ou inventées – agency (agentivité), mimicry (mimétisme/simulacre), ou essentialisme stratégique –, en autant d'outils utiles à démêler la complexité des relations coloniales et, au-delà, de toutes les relations de domination, sont ainsi revisités par les artistes. D'autre part, des auteurs, relevant de ces champs d'études qui conservent aujourd'hui toute leur actualité politique et leur pertinence théorique, disent à leur tour l'intérêt qu'ils portent à la création contemporaine. Associant vingt historiens de l'art et chercheurs en littérature, philosophie, droit ou psychanalyse, Postcolonial/Décolonial. La preuve par l'art présente des travaux portant sur des démarches artistiques (Betye Saar, Fred Wilson, Sarkis, Lidwien van de Ven, Voluspa Jarpa, des artistes du collectif Mira au Mexique, Iris Kensmil, Jean Renoir, et bien d'autres), mais aussi sur des propositions institutionnelles (notamment initiées par le Centro de Arte y Comunicación de Buenos Aires, la Biennale de Venise ou le Van Abbemuseum d'Eindhoven), associées en de nouveaux réseaux de solidarités. Une place particulière est réservée aux singularités artistiques, théoriques et juridiques en Amérique latine, lieu d'émergence des théories décoloniales. Sous un angle historiographique et épistémologique, on trouvera ici des analyses des fondements historiques, théoriques et idéologiques du postcolonial dont les théorisations, loin de la saturation conceptuelle dont certains veulent les accuser, concernent particulièrement l'histoire de l'art. "
Keywords: 1-Histoire de l'art; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 3-Europe (corpus analysé); 4-Amérique du Sud (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Créateur.rice PANDC; _Nettoyé

Réactualiser l’archive, réécrire l’histoire: Des pratiques artistiques décoloniales - De Souza, Fabiana (Revue Asylon(s), 2018)
Réfléchissant comme l’a fait Fanon, à partir de « la condition ontologique-existentielle racialisée du sujet colonisé », cet article se propose d’analyser des pratiques artistiques contemporaines qui cherchent à réactualiser le statut de l’archive. En faisant appel à la pensée décoloniale latino-américaine, nous allons voir comment des artistes affectés par des processus de « sélection et de répression » - enracinés dans les expériences subjectives et culturelles des populations regroupées sous le terme Sud global - ont ré-apprivoisé les archives, donnant lieu à des pratiques artistiques décoloniales ou pratiques artistiques de « ré-invention » de soi.
Keywords: 1-Histoire de l'art; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Sud (corpus analysé); 4-Europe (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé

Numéro spécial : Kin constellations languages waters futures - Eshraghi, Leuli; Moulton, Kimberly (Artlink, 2020)
In this edition, we consider Ancestral materiality, intellectual traditions and expressions spanning the great oceans, skies and lands connecting the kin and Country of First Peoples from around the world. We see the artistic, economic and cultural paradigms as a reflection on life and death, on black holes and shining stars illuminated as constellations in the night skies from the times of our Ancestors and traced in the footprints made on the lands we travel.
Keywords: 1-Histoire de l'art; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Océanie (corpus analysé); 4-Océanie (lieu de production du savoir); 5-Auteur.rice; 5-Auteur.rice LGBTQ+; 5-Auteur.rice autochtone; 5-Créateur.rice LGBTQ+; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Sovereign Words: Indigenous Art, Curation and Criticism - García-Antón, Katya (Office for Contemporary Art Norway ;, 2018)
Artists and cultural practitioners from Indigenous communities around the world are increasingly in the international spotlight. As museums and curators race to consider the planetary reach of their art collections and exhibitions, this publication draws upon the challenges faced today by cultural workers, Indigenous and non-Indigenous, to engage meaningfully and ethically with the histories, presents and futures of Indigenous cultural practices and world-views. Sixteen Indigenous voices convene to consider some of the most burning questions surrounding this field. How will novel methodologies of word/voice-crafting be constituted to empower the Indigenous discourses of the future? Is it sufficient to expand the Modernist art-historical canon through the politics of inclusion? Is this expansion a new form of colonisation, or does it foster the cosmopolitan thought that Indigenous communities have always inhabited? To whom does the much talked-of 'Indigenous Turn' belong? Does it represent a hegemonic project of introspection and revision in the face of today's ecocidal, genocidal and existential crises?"–Page 4 de la couverture. Autres auteurs/titres:edited by Katya García-Antón ; contributors, Daniel Browning, Kabita Chakma, Megan Cope, Santosh Kumar Das, Hannah Donnelly, Léuli Māzyār Luna'i Eshrāghi, David Garneau, Biung Ismahasan, Kimberley Moulton, Máret Ánne Sara, Venkat Raman Singh Shyam, Irene Snarby, Ánde Somby, Megan Tamati-Quennell, Prashanta Tripura, Sontosh Bikash Tripura.
Section: 287 pages : illustrations (principalement en couleur) ; 24 cm.
Keywords: 1-Histoire de l'art; 2-Approches sociologiques; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Afrique (corpus analysé); 3-Amérique centrale (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 3-Océanie (corpus analysé); 4-Afrique (lieu de production du savoir); 4-Amérique centrale (lieu de production du savoir); 4-Amérique du Nord (lieu de production du savoir); 4-Amérique du Sud (lieu de production du savoir); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 4-Océanie (lieu de production du savoir); 5-Auteur.rice; 5-Auteur.rice autochtone; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Sámi Art and Aesthetics: Contemporary Perspectives - Aamold, Svein (Aarhus University Press, 2017)
During the last five decades we have witnessed an increase in activity among artists identifying themselves as Sami, the only recognised indigenous people of Scandinavia. At the same time, art and duodji (traditional Sami art and craft) have been organized and institutionalized, not least by the Sami artists themselves.
OCLC: 1000570833
Keywords: 1-Histoire de l'art; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Europe (corpus analysé); 4-Europe (lieu de production du savoir); 5-Auteur.rice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

The Sámi Art Museum: There Is No - Or Is There? - Hanna Horsberg Hansen (Nordlit: Tidsskrift i litteratur og kultur, 2020)
This article aims to answer two questions. The first is: What is a Sámi art museum? The second question considers whether there is no Sámi art museum, as assumed by the Nordnorsk kunstmuseum (NNKM) as the title of a museum performance and exhibition in 2017. To answer the first question, it is necessary to tell the long story of the Sámi cultural-historical museum in Karasjok, Samiid Vuorká-Dávvirat (SVD). This museum was inaugurated in 1972 as an act of resistance against the increasing assimilation politics towards the Sámi population in the post-war period. The building that was erected became a cultural and political centre, and a living cultural institution that housed the increasing Sámi ethno-political movement and its energy. Furthermore, as I will argue, the activity that took place at the site became a part of Sámi cultural heritage. The museum has also collected art since 1972 - a collection that today comprises 1400 artworks. Since the 1980s, various plans have been made for a Sámi art museum in a separate building, somehow connected to SVD, however, none of these plans have yet been realised. The article discusses the different reasons for this, and points to the connotations embedded in the SVD building as a cultural and political centre as one of the contributing factors. To answer the question of whether there is no Sámi art museum, a critical reading of the Nordnorsk kunstmuseum’s 2017 museum performance There Is No is necessary. My answer to the question is that NNKM, unfortunately, fell into several traps in their attempt to focus on the fact that there is no physical building. One such trap, that is very common in Western museums displaying indigenous art, is their use of traditional art-historical models as interpretive lenses when displaying indigenous art. A different concept of what an art museum could be today, as a place where things happen, where we could meet counter narratives, or Sámi art and culture could be presented as being part of the present as well as the past and future, would have been closer to a Sámi art museum. I offer this conclusion both through the deeper understanding of Sámi cultural and ethno-political movements as offered in the story of SVD, and through my reading of the theories of the indigenous American scholar John Paul Rangel. While there may indeed be no physical building claiming to be a Sámi art museum, it does in fact exist through the Sámi concept of árbevierru.
Keywords: 1-Histoire de l'art; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Europe (corpus analysé); 4-Europe (lieu de production du savoir); 5-Auteur.rice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Performing Resistance/Negotiating Sovereignty: Indigenous Women's Perofrmance Art in Canada - Taunton, Carla Jane (Queen's University, 2011)
Performing Resistance/ Negotiating Sovereignty: Indigenous Women’s Performance Art In Canada investigates the contemporary production of Indigenous performance and video art in Canada in terms of cultural continuance, survivance and resistance. Drawing on critical Indigenous methodology, which foregrounds the necessity of privileging multiple Indigenous systems of knowledge, it explores these themes through the lenses of storytelling, decolonization, activism, and agency. With specific reference to performances by Rebecca Belmore, Lori Blondeau, Cheryl L'Hirondelle, Skeena Reece and Dana Claxton, as well as others, it argues that Indigenous performance art should be understood in terms of i) its enduring relationship to activism and resistance ii) its ongoing use as a tool for interventions in colonially entrenched spaces, and iii) its longstanding role in maintaining self-determination and cultural sovereignty.
Accepted: 2011-09-30T21:33:54Z
Keywords: 1-Histoire de l'art; 2-Genre et sexualité; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Embodying Sovereignty: Indigenous Women’s Performance Art in Canada - Taunton, Carla (Narratives Unfolding: National Art Histories in an Unfinished World, 2017)
Homi Bhabha’s pivotal 1994 book,The Location of Culture, begins with an epigraph from Heidegger’s “Building Dwelling Thinking”: “A boundary is not that at which something stops but, as the Greeks recognized, the boundary is that from whichsomething begins its presencing.” Cultural engagement, whether antagonistic or affiliative in nature, is produced performatively – not as a reflection of something that is given or set in stone, but as an ongoing process of negotiation.
Section: xviii, 437 pages : illustrations (principalement en couleur) ; 24 cm.
Keywords: 1-Histoire de l'art; 2-Genre et sexualité; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Re-Inventing Art Practices: Indigenous Women Artists Building Community through Art and Activism in Rural and Remote Manitoba - Nagam, Julie (University of Manitoba, 2006)
his thesis documents and explores community-based and socially engaged art by Indigenous women artists. Their artwork is impacting and strengthening communities in Manitoba. The Thesis explores the use of dialogical aesthetics in performance and socially-engaged art by Indigenous women artists in rural and remote areas of Manitoba, and relates these aesthetics to the concept of activism through their art and relationship to their community. The aim of this research and this paper is to document, support and expose the work of a small pocket of Indigenous women artists in Manitoba who are acting as activists or social change agents based on their artwork. I have arrived at this conclusion first by their personal testimonies, second, by their art being socially conscious and lastly, by their art practices entrenched in the framework of dialogical aesthetics, community-based and site-specific ideologies.
Keywords: 1-Histoire de l'art; 2-Approches sociologiques; 2-Genre et sexualité; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice; 5-Auteur.rice autochtone; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

(Re)Mapping the Colonized Body: The Creative Interventions of Rebecca Belmore in the Cityscape. - Nagam, Julie (American Indian Culture and Research Journal, 2011)
The cityscape holds the memories of indigenous bones and bodies that resurrect a deep sense of place that exists in the landscape of the city of Toronto. This deep sense of place is part of a connection to the land and stories of place. In this article, the author bridges the creative work of Anishinaabe artist Rebecca Belmore with the living histories of the indigenous bodies and bones that are buried beneath the ground of the city of Toronto and the city of Vancouver. She argues that Belmore's artwork is part of the living archive that performs cultural memory and employs telling as part of an embodied experience and a political act. Belmore's performance work creates, records, and stores indigenous stories of place. This article uses the ideas of cultural theorists Katherine McKittrick, Mishuana Goeman, and Matthew Sparke. Each of these people brings a different element to theories of the body and space. This article also uses feminist geographers Alison Blunt and Gillian Rose's work in women's colonial geographies to unpack the affects of the map in colonial spaces and the colonial gaze. (Contains 4 figures and 50 notes.)
Keywords: 1-Histoire de l'art; 2-Genre et sexualité; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice; 5-Auteur.rice autochtone; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Indigenous Research Methodologies in Sámi and Global Contexts - Virtanen, Pirjo Kristiina; Keskitalo, Pigga; Olsen, Torjer (Brill | Sense, 2021)
This book addresses the conceptualization and practice of Indigenous research methodologies especially in Sámi and North European academic contexts. It examines the meaning of Sámi research and research methodologies, practical levels of doing Indigenous research today in different contexts, as well as global debates in Indigenous research. The contributors present place-specific and relational Sámi research approaches as well as reciprocal methodological choices in Indigenous research in North-South relationships. This edited volume is a result of a research collaboration in four countries where Sámi people live. By taking the readers to diverse local discussions, the collection emphasizes communal responsibility and care as a key in doing Indigenous research. Contributors are: Rauni Äärelä-Vihriälä, Hanna Guttorm, Lea Kantonen, Pigga Keskitalo, Britt Kramvig, Petter Morottaja, Eljas Niskanen, Torjer Olsen, Marja-Liisa Olthuis, Hanna Outakoski, Attila Paksi, Jelena Porsanger, Aili Pyhälä, Rauna Rahko-Ravantti, Torkel Rasmussen, Ilona Rauhala, Erika Katjaana Sarivaara, Irja Seurujärvi-Kari, Trond Trosterud and Pirjo Kristiina Virtanen"– Provided by publisher
Keywords: _Nettoyé

Indigenous Research Methodologies - Chilisa, Bagele (SAGE, 2020)
Author Bagele Chilisa updates her groundbreaking textbook to give a new generation of scholars a crucial foundation in indigenous methods, methodologies, and epistemologies. Addressing the increasing emphasis in the classroom and in the field to sensitize researchers and students to diverse perspectives - especially those of women, minority groups, former colonized societies, indigenous people, historically oppressed communities, and people with disabilities, the second edition of Indigenous Research Methodologies situates research in a larger, historical, cultural, and global context to make visible the specific methodologies that are commensurate with thetransformative paradigm of social science research"
Section: xxiv, 368 pages : illustrations ; 24 cm.
Keywords: 1-Cinéma; 1-Histoire de l'art; 1-Jeux vidéo; 1-TV; 2-Genre et sexualité; 2-Méthodologie de recherche décoloniale; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Afrique (corpus analysé); 4-Afrique (lieu de production du savoir); 5-Auteur.rice; 5-Auteur.rice noir.e; _Nettoyé

Becoming our future: global indigenous curatorial practice - Nagam, Julie; Tamati-Quennell, Megan; Lane, Carly (ARP Books, 2020)
"This book investigates international Indigenous methodologies in art curatorial practice from the geographic spaces of Canada, Aotearoa (New Zealand) and Australia. From a perspective of Indigenous peoples important place within society, this collection explores how Indigenous art and culture operate within and from a structural framework that is unique and is positioned outside of the non-Indigenous cultural milieu. Through a selection of contributions, Becoming Our Future articulates this perspective, defines Indigenous curatorial practice and celebrates Indigenous sovereignty within the three countries. It begins to explore the connections and historical moments that draw Indigenous curatorial practices together and the differences that set them apart. This knowledge is grounded in continuous international exchanges and draws on the breadth of work within the field. With contributions by Nigel Borell, Nici Cumpston, Freja Carmicheal, Karl Chitham, Franchesca Cubillo, Léuli Eshraghi, Reuben Friend, Jarita Greyeyes, Heather Igloliorte, Jaimie Isaac, Carly Lane, Michelle LaVallee, Cathy Mattes, Bruce McLean, Kimberley Moulton, Lisa Myers, Julie Nagam, Wanda Nanibush, Jolene Rickard, Megan Tamati-Quennell, and Daina Warren."– Provided by publisher.
Section: 240 pages : illustrations (chiefly color) ; 26 cm
Keywords: 1-Histoire de l'art; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 3-Océanie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 4-Océanie (lieu de production du savoir); 5-Auteur.rice; 5-Auteur.rice autochtone; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Knowledge Positions in Aotearoa and Turtle Island Art Museums - Eshraghi, Leuli; Ash-Milby, Kathleen; Nuku, Maia; Borell, Nigel (Artlink, 2020)
Art, performance, and spoken or now written text, all belong to the same register of cultural practice in the First Nations I am familiar with or belong to: ceremony. This ceremonial register takes place in a set of spaces created to enact cultural responsibilities to place, people and balance. Galleries and museums, as sites of cultural production and presentation, have the potential to nurture new ceremonies and new working methods.
Keywords: 1-Histoire de l'art; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 3-Océanie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 4-Océanie (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Indigenous Cinema in Expansion: Challenges and Promises of an Intercultural Relationship - Frey, Aline; Brito, Thaís (Canadian Journal of Film Studies, 2020)
Les auteures dressent le portrait tant des défis actuels que des possibilités qui naissent des relations interculturelles se tissant entre commissaires et cinéastes autochtones et non-autochtones dans le cadre du plus grand festival du film autochtone du Brésil, Cine Kurumin. Ce festival annuel, fondé en 2011, se déroule dans des villages ruraux autochtones, de même que dans des métropoles brésiliennes, attirant ainsi des auditoires variés. Le festival est ouvert aux cinéastes autochtones et non-autochtones qui produisent du matériel audiovisuel portant sur des sujets autochtones de partout dans le monde. Divers processus créatifs y sont encouragés grâce à l’organisation d’ateliers de scénarisation, et des partenariats établis avec des chaînes de télévision permettent une plus large diffusion des films sélectionnés. Alors que les productions audiovisuelles autochtones se développent, leurs contenus se diversifient ; elles englobent en effet de plus en plus de thèmes et de styles, de formats et de perspectives variées. En s’appuyant sur un cadre théorique postcolonial et décolonial, les auteures proposent de nouvelles perspectives sur un cinéma en pleine expansion ; les réalisateurs autochtones et leurs films circulent de plus en plus au sein de festivals non thématiques, reçoivent des prix et font rayonner leurs propres voix et points de vue auprès de publics variés, ce qui crée de nombreuses possibilités d’interactions et de dialogues interculturels. En outre, la mise sur pied de Cine Kurumin témoigne du pouvoir des productions audiovisuelles autochtones de générer des relations interculturelles entre cinéastes, commissaires et public.
Keywords: 1-Cinéma; 2-Approches sociologiques; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Sud (corpus analysé); 4-Amérique du Sud (lieu de production du savoir); 5-Auteur.rice; 5-Créateur.rice PANDC; 5-Créateur.rice autochtone; _Nettoyé

Inuit Visual and Sensate Sovereignty in Alethea Arnaquq-Baril’s Angry Inuk - Burelle, Julie (Canadian Journal of Film Studies, 2020)
L’auteure soutient que le documentaire de 2016 d’Alethea Arnaquq-Baril, Angry Inuk (Inuk en colère), crée, grâce au cinéma, des espaces de « souveraineté visuelle » centrés sur l’« agentivité sensorielle » inuite (Raheja, 2010 ; Robinson, 2016). La réalisatrice propose un recadrage, selon un point de vue inuit, de la rhétorique dominante entourant la chasse aux phoques, pratique décriée violemment par des groupes de défense des droits des animaux. Plus qu’une simple réfutation de ces discours sudistes, ce film met de l’avant les connaissances inuites en lien avec le territoire et la gestion des ressources et remet en question les argumentaires libératoires soutenus par ces organismes, dont les raisonnements reconduisent des dynamiques coloniales plutôt que de les ébranler. Comme l’évoque son titre, le documentaire riposte à l’ire des protestataires anti-chasse aux phoques (dont la voix s’impose souvent au détriment des voix inuites, généralement tues), en créant un espace d’expression pour la colère inuite, présentée à la fois comme carburant et comme point de départ légitime et valide de la lutte contre les organismes en question. De façon centrale, le film met en scène des récits de chasse aux phoques s’appuyant sur une « agentivité sensorielle » inuite qui, aux yeux de Dylan Robinson, se manifeste sous la forme de « modes d’expression qui, à la fois, affirment une force culturelle et exercent une puissance affective auprès des personnes présentes ». Arnaquq-Baril propose ainsi des représentations de rires partagés, d’un froid ressenti, de sons joyeux de consommation communautaire de diverses parties du phoque, de même que des photos tirées de la campagne Twitter menée autour du mot-clic #sealfie ; cette campagne médiatique, ancrée dans une célébration humoristique et fière de la chasse inuite aux phoques, se veut en ce sens un contre-point au discours affectif simpliste et méprisant des organismes anti-chasse. En s’articulant autour de la résilience complexe propre aux Inuits, Inuk en colère incarne en soi une forme de souveraineté inuite, s’imposant au sein des récits qui participent à la sensibilisation du public quant aux enjeux entourant cette chasse. En outre, le film invite l’auditoire à réfléchir aux avenirs autochtones et à envisager de quelles manières l’activisme pour la défense des droits des animaux peut être décolonisé afin qu’il ne mène pas à la reconduction de dynamiques violentes d’extractivisme et de colonisation.
Keywords: 1-Cinéma; 1-Histoire de l'art; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Haerenga Wairua: Spirit(ual) Journeys in Twenty-First-Century Māori Cinema - Walker-Morrison, Deborah (Canadian Journal of Film Studies, 2020)
Haerenga Wairua / Spiritual Journeys explore le cinéma maori en tant que 4e cinéma, dans son articulation de la spiritualité maorie comme un ensemble de croyances et de pratiques vivantes et d’une grande pertinence pour ce XXIe siècle. Après une brève description des termes et croyances clés, l’auteure analyse deux longs-métrages de fiction récents, The Strength of Water (Armagan Ballantyne, scr Briar Grace-Smith, NZ & Allemagne 2009) et The Pā Boys (Himiona Grace, NZ, 2014) comme emblématiques des pratiques cinématographiques autochtones, en ce qu’ils mettent fortement en avant différents niveaux et expériences de transformation spirituelle, via divers voyages au propre comme au figuré : voyages réels, voyages psychologiques ET expériences après la mort, donc voyages spirituels. Positionnant ces films dans le contexte des traditions spirituelles de narration littéraire et cinématographique, l’auteure explore les diverses techniques filmiques et cinématographiques mises en œuvre pour rendre l’expérience spirituelle, via le son et l’image, en mettant en évidence les liens avec la Terre, l’Eau et l’environnement naturel en tant qu’éléments spirituels et souvent surnaturels. Alors que ces derniers sont généralement interprétés par les critiques et chercheurs allochtones comme étant de l’ordre du fantastique, dans le discours établi du réalisme magique, l’auteure avance plutôt que les représentations autochtones ne peuvent être ni expliquées ni contenues de manière adéquate par ce terme, et propose à sa place celui de « réalisme spirituel autochtone ». L’auteure conclut en soulignant la pertinence de voix autochtones comme celles-là, qui expriment une spiritualité enracinée dans l’interdépendance de tous êtres et de toutes choses : force de guérison dans notre planète meurtrie.
Keywords: 1-Cinéma; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Océanie (corpus analysé); 4-Océanie (lieu de production du savoir); 5-Auteur.rice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Dans toute son exubérance : Affirmation de soi et autoreprésentation chez Caroline Monnet - Marcoux, Gabrielle (Canadian Journal of Film Studies, 2020)
In this interview, multidisciplinary artist Caroline Monnet discusses how acts of critical self-representation open up new spaces for territorial, linguistic, and identity negotiations and affirmations for Indigenous creators. In this sense, Monnet expresses her desire to put forward exuberant, strong, and diverse representations of Indigenous women in order to counter pervasive rhetorical dynamics of victimhood conveyed by mass media and cinema. As she presents some of the visual and discursive techniques she develops through her films, installations, and photographic works, Monnet reflects on the constructive dialogues – as well as the moments of incommunicability – that emerge and fade within various spaces and contexts of creation and reception. She considers that her individual and collective creative projects fall within a pivotal period of self-determination for Indigenous artists; she thus provides a critical overview of current discourses of (re)concililation.
Keywords: 1-Cinéma; 1-Histoire de l'art; 2-Genre et sexualité; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Les archives à l’épreuve du temps : les recadrements temporels des courts métrages de la série Souvenir - Huberman, Isabella (Canadian Journal of Film Studies, 2020)
This article examines how “colonial time” is called into question in two short films of the National Film Board of Canada’s series Souvenir, from 2015. The question of time lies at the heart of this series, for which the NFB commissioned contemporary Indigenous filmmakers to take up their archives of visual material on Indigenous peoples. The colonial temporal framework is at work in the vast archives of ethnographic and documentary film and photography on Indigenous peoples dating back to the early twentieth century, in which Indigenous people are often represented as part of “vanishing” cultures. Thus, in this article, I underscore the temporal interruptions that occur when ethnographic visual material of Indigenous peoples is put into the hands of contemporary Indigenous artists. I focus first on what it means to repurpose dehumanizing colonial archives and ask whether visual sovereignty is in fact possible within the archives. By analyzing the reappropriation of archival footage in the short films Mobilize by Caroline Monnet and Etlinisigu’niet (Bleed Down) by Jeff Barnaby, I elucidate how the filmmakers break with modes of colonial time through what I propose to call “reframings” that offer alternative ways of conceiving of time. By rehabilitating ethnographic images, these filmmakers refuse to project the material into the distant past and complicate the readability of Indigenous images in the archives, revealing how the reappropriation of old images can be just as powerful as the production of new ones.
Keywords: 1-Cinéma; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Le cinéma autochtone au Québec: de la représentation à la ré-appropriation - Bertrand, Karine (Contemporary French Civilization, 2019)
Cet article se penche sur les relations et collaborations récentes entre les cinéastes autochtones et québécois. Une brève exploration des représentations autochtones antérieures et du contexte contemporain de co-réalisation Québec/Autochtonie nous permet d’esquisser un portrait plus nuancé des nouvelles configurations transnationales du paysage cinématographique québécois. De même, les notions d’autochtonisation du médium, de souveraineté visuelle et de survivance nous aideront à mieux cerner les œuvres de fiction réalisées par des cinéastes autochtones, qui contribuent à l’enrichissement d’un cinéma qui propose de nouvelles façons d’habiter les territoires québécois/autochtones.
Keywords: 1-Cinéma; 2-Genre et sexualité; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Le collectif Arnait Video Productions et le cinéma engagé des femmes inuits: Guérison communautaire et mémoire culturelle - Bertrand, Karine (Canadian Review of Comparative Literature / Revue Canadienne de Littérature Comparée, 2017)
Marie-Hélène Cousineau, qui regroupe des femmes inuits de la communauté d’Igloolik, utilise la vidéo pour démontrer l’importance de la femme inuit dans le développement et la cohésion de l’unité sociale et familiale de l’Arctique (passé, présent et futur). Soulignant la spécificité culturelle des femmes d’Igloolik, ainsi que la portée universelle de questions reliées par exemple à la maternité, au pouvoir et au potentiel des femmes qui sont considérées comme des agents de changement sociétal participant à la transmission et au renouvellement de la connaissance traditionnelle, les cinéastes d’Arnait ont participé à des projets novateurs (telle que l’initiative Live from the Toundra) où les outils technologiques (Internet, blogues, capsules vidéos, radio, satellite) ont servis à établir des ponts entre les di érentes communautés du Nord."
OCLC: 7014735516
Keywords: 1-Cinéma; 2-Genre et sexualité; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

L’œuvre documentaire d’Alanis Obomsawin et la voix des femmes autochtones. - Bertrand, Karine (De l'exclusion à la solidarité: regards intersectionnels sur les médias, 2020)
Résumé livre : "L’intersectionnalité, telle qu’élaborée par les féministes noires dans les années 1980, permet de réfléchir aux rapports de pouvoir dans leur complexe enchevêtrement. Au-delà d’un certain effet de mode, cette éthique est plus que jamais nécessaire pour comprendre le monde, à l’aube d’une décennie marquée par un virus ayant partout exacerbé la violence et les inégalités, et mis en évidence les systèmes de privilèges. Et qu’arrive-t-il lorsque l’on porte ce regard attentif sur les médias ? Les textes rassemblés dans cet ouvrage explorent avec aplomb les questions de l’inclusion et de l’exclusion médiatiques. Que décoder du traitement média réservé au port du hijab dans le sport, aux agressions sexuelles à l’endroit des femmes noires et autochtones, ou encore, de la place de la sourditude et des transidentités dans l’espace public? Un recueil qui amène son lot de réponses éclairantes et douloureuses, une rareté dans le paysage des études culturelles et médiatiques francophones."–Page 4 de la couverture
OCLC: 1136615376
Keywords: 1-Cinéma; 2-Genre et sexualité; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Remembering Vancouver's Disappeared Women: Settler Colonialism and the Difficulty of Inheritance - Dean, Amber (University of Toronto Press, 2015)
"Between the late 1970s and the early 2000s, at least sixty-five women, many of them members of Indigenous communities, were found murdered or reported missing from Vancouver's Downtown Eastside. In a work driven by the urgency of this ongoing crisis, which extends across the country, Amber Dean offers a timely, critical analysis of the public representations, memorials, and activist strategies that brought the story of Vancouver's disappeared women to the attention of a wider public. Remembering Vancouver's Disappeared Women traces "what lives on" from the violent loss of so many women from the same neighborhood. Dean interrogates representations that aim to humanize the murdered or missing women, asking how these might inadvertently feed into the presumed dehumanization of sex work, Indigeneity, and living in the Downtown Eastside of Vancouver. Taking inspiration from Indigenous women's research, activism, and art, she challenges readers to reckon with our collective implication in the ongoing violence of settler colonialism and to accept responsibility for addressing its countless injustices
Section: xxviii, 188 pages : illustrations ; 24 cm
Keywords: 1-Histoire de l'art; 2-Genre et sexualité; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Keetsahnak: Our Missing and Murdered Indigenous Sisters - Anderson, Kim; Belcourt, Christi; Campbell, Maria (The University of Alberta Press, 2018)
In Keetsahnak / Our Murdered and Missing Indigenous Sisters, the tension between personal, political, and public action is brought home starkly as the contributors look at the roots of violence and how it diminishes life for all. Together, they create a model for anti-violence work from an Indigenous perspective. They acknowledge the destruction wrought by colonial violence, and also look at controversial topics such as lateral violence, challenges in working with "tradition," and problematic notions involved in "helping." Through stories of resilience, resistance, and activism, the editors give voice to powerful personal testimony and allow for the creation of knowledge.
Keywords: _Nettoyé

Auto-histoires et représentations communautaires dans le cinéma des femmes autochtones - Bertrand, Karine (Canadian Journal of Film Studies, 2020)
In the last decade or so, cinema has revealed itself to be an ideal medium for the transfer and/or remediation of the spoken word as well as stories coming from oral tradition and Indigenous culture. Indeed, cinema is a place of expression which favours cyclical creativity and contributes to the decolonization of stereotyped images propagated by external voices that do not understand the subtleties of languages (real and symbolic) that are anchored in indigenous peoples’ cultural memory. By exploring indigenous cinema as practised by women of diverse nations, this piece demonstrates how cinema can induce the compression and dilation of time, to bring to the audience the fluidity of a story that has been reconfigured according to a new time and carried by spoken words that have chosen to either emancipate themselves from the image or to materialize themselves in it. Furthermore, this article illustrates how a new generation of Indigenous women use cinema to retrace and/or rewrite their personal narrative with the help of autobiographical or collective stories that travel back in time to fill in the blanks left by a fragile memory and to express their will to make peace with a difficult colonial past. Finally, the writings of Lee Maracle (I Am Woman, 1988) and Natasha Kanapé Fontaine (Manifeste Assi, 2014) are being brought forth to show how films such as Suckerfish (Lisa Jackson, 2004) Bithos (Elle-Máijá Tailfeathers, 2015) and Four Faces of the Moon (Amanda Strong, 2016) contribute to the individual and community healing of Indigenous peoples of Canada, through an aesthetic of reconciliation. The exploration of these works, therefore allows us to shed light on and better understand the roles/internal mechanisms of visual autobiographies in the larger context of reconciliation with individual and collective stories/memories.
Keywords: 1-Cinéma; 2-Genre et sexualité; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice; 5-Auteur.rice autochtone; 5-Créateur.rice PANDC; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Numéro spécial : Continuities Between Eras: Indigenous Art Histories Continuité entre les époques : histoires des arts autochtones - Igloliorte, Heather; Taunton, Carla (2017)
Keywords: _Nettoyé

Indigenous Sovereignty and Settler Amnesia: Robert Houle's "Premises for Self Rule" - Ernst, Stacy A. (RACAR: revue d'art canadienne / Canadian Art Review, 2017)
Le modernisme en art est souvent considéré comme un développement spécifiquement occidental. Robert Houle, l'artiste, écrivain et commissaire d'exposition d'origine Saulteaux, a cependant toujours soutenu que sa propre pratique est moderniste et qu'elle suit une filiation esthétique autochtone. Cet article s'intéresse particulièrement à une œuvre produite par Houle en 1994, Premises for Self Rule, dans laquelle l'artiste a juxtaposé des textes de législation coloniale à des panneaux peints en monochrome et des cartes postales trouvées en archives. Il propose qu'à travers cette stratégie de rapprochement, l'artiste fusionne la tradition de la peinture de parflèche à l'esthétique moderniste, remettant ainsi en lumière la négociation interculturelle, l'amnésie coloniale, ainsi que les écarts qui séparent les épistémologies et traditions artistiques des peuples autochtones et allochtones
Keywords: 1-Histoire de l'art; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice; 5-Créateur.rice autochtone; _Nettoyé

Hearts of our People: Native Women Artists - Ahlberg Yohe, Jill; Greeves, Teri (University of Washington Press, 2019)
"Women have long been the creative force behind Native American art, yet their individual contributions have been largely unrecognized, instead treated as anonymous representations of entire cultures. 'Hearts of Our People: Native Women Artists' explores the artistic achievements of Native women and establishes their rightful place in the art world. This lavishly illustrated book, a companion to the landmark exhibition, includes works of art from antiquity to the present, made in a variety of media from textiles and beadwork to video and digital arts. It showcases more than 115 artists from the United States and Canada, spanning over one thousand years, to reveal the ingenuity and innovation fthat have always been foundational to the art of Native women."–Page 4 de la couverture.
OCLC: 1153882782
Keywords: 1-Histoire de l'art; 2-Genre et sexualité; 2-Muséologie critique; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; 5-Créateur.rice LGBTQ+; 5-Créateur.rice autochtone; _Nettoyé

From Great-Grandmothers to Great-Granddaughters: "Moving Life" in Baby Carriers and Birchbark Baskets - Kahsenni:io Nahwegahbow, Alexandra (RACAR: revue d'art canadienne / Canadian Art Review, 2017)
Les porte-bébés et les paniers d'écorce autochtones sont, en tant que réceptacles, conçus pour porter et tenir. Outre cette fonction, ils sont aussi détenteurs d'histoires, de mémoire, et de liens familiaux. Créés individuellement et ornementés avec soin, ces objets constituent une sorte de portrait des femmes qui les ont produits, ainsi que des générations qui ont hérité des pratiques et des motifs servant à les fabriquer. En élargissant la définition de la notion de portrait de famille, cet article considère deux objets provenant de Bear Island, en Ontario. Le premier est un porte-bébé ayant appartenu à Madeline Katt Theriault, et le deuxième est un panier d'écorce vraisemblablement créé parson arrière-grand-mère Angele Katt. Par leur parenté, ces réceptacles englobent une histoire multigénérationnelle qui s'étend de l'arrière-grand-mère à son arrière-petite-fille
Keywords: 1-Histoire de l'art; 2-Histoire/Historiographie critique; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice; 5-Auteur.rice autochtone; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Archival Predecessors and Indigenous Modernisms: Archives in Contemporary Curatorial Practice on the Northwest Coast - Kisin, Eugenia (RACAR: revue d'art canadienne / Canadian Art Review, 2017)
Les projets d'expositions archivistiques—et leur documentation—sont des lieux de production de connaissances en histoire de l'art, ainsi que des interventions politiques, qui placent les documents dans un autre contexte afin d'interroger les canons et les façons de voir des colonialistes-colons. À partir de ces relations discursives, visuelles et archivistiques, cet article examine deux rétrospectives solos des œuvres sculptées et peintes des artistes modernistes kwakwaka'wakws, Doug Cranmer ('Namgis) et Henry Speck (Tlawit'sis), présentées à Vancouver en 2012. En considérant comment les conservateurs ont fait appel aux archives familiales intimes et à des documents du domaine public, il traite de l'utilité des archives du modernisme pour activer des liens affectifs, ancestraux et familiaux au-delà des modes de compréhension canoniques et historiques des mouvements esthétiques et des contextes de production
Keywords: 1-Histoire de l'art; 2-Histoire/Historiographie critique; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; 5-Créateur.rice autochtone; _Nettoyé

Les arts wendats au service de la diplomatie et de la traite - de Stecher, Annette (Recherches amérindiennes au Québec, 2014)
Cet article porte sur les oeuvres artisanales des femmes wendates du xix ₑ siècle dans le contexte plus large des traditions des arts visuels wendats. En plus des objets commerciaux, l’auteure présente des objets faits pour être utilisés lors d’occasions cérémonielles et rituelles spéciales, et qui avaient aussi une valeur importante dans la communauté. Ces deux catégories d’artisanat dévoilent la façon dont les femmes wendates adaptaient leurs traditions artistiques aux sphères économiques et diplomatiques du monde colonial, et ce avec grand succès. Ces arts ont aidé la communauté à conserver une vision du monde amérindienne et ont préservé des traditions culturelles qui se sont perpétuées d’une génération à l’autre, tout en intégrant des innovations créatives. Ils démontrent aussi le rôle diplomatique important joué par les oeuvres présentées aux dignitaires eurocanadiens et européens dans un contexte cérémoniel, afin d’établir et de maintenir des relations politiques et économiques harmonieuses.
Keywords: 1-Histoire de l'art; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

The Art of Community - de Stecher, Annette (RACAR: revue d'art canadienne / Canadian Art Review, 2017)
La nation huronne-wendat de Wendake (Lorette, Québec) a maintenu sa culture et son identité pendant des siècles, souvent en dépit de, et en résistance contre les pressions occasionnées par la présence missionnaire et les politiques coloniales. Cette survivance est tributaire de savoirs, de valeurs et de coutumes transmis de génération en génération. Cet article explore l'art de la communauté wendat et ses éléments constitutifs : la fabrication d'objets, la tradition orale, l'engagement actif des membres de la collectivité dans les pratiques traditionnelles, ainsi que l'adaptation des pratiques ancestrales aux préoccupations actuelles. Il montre comment la production artistique wendat, dans sa force expressive, contribue à la continuité et cohésion sociale de la nation wendat.
Keywords: 1-Histoire de l'art; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

“Embodiment and Subjectivity”: Intersectional Black Feminist Curatorial Practices in Canada - Joachim, Joana (RACAR: revue d'art canadienne / Canadian Art Review, 2018)
Dans le contexte de l’héritage canadien de colonialisme et de profond racisme, les musées ont contribué à l’oppression des Noir.e.s, des communautés de couleur et des peuples autochtones en gardant le silence ou en supprimant certaines histoires sous prétexte d’« objectivité ». Cet article examine les pratiques commissariales de deux femmes noires canadiennes, Gaëtane Verna, directrice et conservatrice en chef de la galerie d’art contemporain The Power Plant, et Andrea Fatona, commissaire indépendante, afin de situer le commissariat critique à l’intérieur de perspectives afroféministes intersectionnelles. En conformité avec une base conceptuelle fondamentale de ce féminisme, je soutiens que ce qui rend l’acte commissarial « critique » est la reconnaissance non seulement de la position qu’une personne occupe dans la société, mais aussi de celles dont elle ne fait pas toujours l’expérience. En examinant les pratiques de ces deux femmes, je mets au jour une riche histoire de l’art et du commissariat des Noir.e.s au Canada.
Keywords: 1-Histoire de l'art; 2-Genre et sexualité; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice noir.e; 5-Autrice; 5-Créateur.rice noir.e; 5-Créatrice; _Nettoyé

Shelley Niro. Scotiabank Award. - Rice, Ryan; Nanibush, Wanda (Steidl Verlag, 2018)
Shelley Niro is widely known for her ability to explode myths, transgress boundaries and embody the ethos of her matriarchal culture in a wide variety of mediums including photography, installation, film and painting. Niro creates photographic series that emphasize the medium?s inherent capacity for narrative and representation. She pushes the limits of photography by incorporating Mohawk imagery, re-appropriating traditional stories such as Skywoman and The Peacemaker, and by focusing on contemporary subjects with wit, irony and campy humor. Niro marries portraiture, performance art and satire by having her subjects and herself perform for the camera in ways that gently invite audiences to rethink their beliefs and preconceptions about indigenous peoples and themselves. With compassion and deep insight, Niro opens up the fault lines and desires of gender, sexuality and culture to create images of freedom from the status quo in representation. Photography was a medium that helped subjugate indigenous peoples, but in Niro?s revolutionary hands it empowers
Section: 228 pages
Keywords: 1-Histoire de l'art; 2-Genre et sexualité; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

George Littlechild: The Spirit Giggles Within - Littlechild, George (Heritage House Publishing Company Ltd, 2012)
George Littlechild: The Spirit Giggles Within is a stunning retrospective of a career that has spanned nearly four decades. Featuring more than 150 of the Plains Cree artist's mixed-media works, this sumptuous collection showcases the bold swaths of colour and subtle textures of Littlechild's work. Littlechild has never shied away from political or social themes. His paintings blaze with strong emotions ranging from anger to compassion, humour to spiritualism. Fully embracing his Plains Cree heritage, he combines traditional Cree elements like horses and transformative or iconic creatures with his own family and personal symbols in a unique approach. George Littlechild: The Spirit Giggles Within shows the evolution of an artist from his earliest works to the present day, including hints of future directions and themes. An insightful foreword by artist and curator Ryan Rice, a Mohawk from the Kahnawake First Nation in Quebec, and Littlechild's reflections on each piece build a broad understanding of Littlechild's work, his life and his views on the role of art within all cultures
Keywords: 1-Histoire de l'art; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Créateur.rice autochtone; _Nettoyé

Anthem: perspectives on home and native land - Rice, Ryan (Carleton University Art Gallery = Galerie d'art de l'Université Carleton, 2008)
Eight artists from across Canada create works identify varying forms of nationhood that either serve or detract from the concept of a national accord. Each artist explores the idea of ₃anthem₄ through a wide-angle lens, broadening the national discourse to include not only colonial histories, but also distinctive and multicultural liberties that take various forms: treaties, blood, languages, sexual orientation, faith, and oral traditions. The dynamic range of art works exhibited contribute to a more inclusive national narrative and expose and accept the diverse forms of nationalism that exist across the country.
Section: 61 pages : color illustrations ; 28 cm
Keywords: 1-Histoire de l'art; 2-Histoire/Historiographie critique; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Kwah í:ken tsi Iroquois - Rice, Ryan (Ottawa Art Gallery = Galerie d'art d'Ottawa, 2008)
Catalogue d'exposition avec des textes de Ryan Rice, Françoise Charron, Emily Falvey et Hilda Nicholae.
Section: 132 pages : illustrations (chiefly color) ; 26 cm
Keywords: 1-Histoire de l'art; 2-Histoire/Historiographie critique; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Hochelaga revisité = Hochelaga revisited - Rice, Ryan (MAI (Montréal, arts interculturels), 2009)
Catalogue d'exposition avec des textes de Ryan Rice; Jason Baerg; Lori Blondeau; Martin Loft; Cathy Mattes; Nadia Myre; Ariel Lightningchild Smith.
Section: 40 p. : ill. (certaines en coul.) ; 22 cm
Keywords: 1-Histoire de l'art; 2-Histoire/Historiographie critique; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Presence and Absence Redux: Indian Art in the 1990s - Rice, Ryan (RACAR: revue d'art canadienne / Canadian Art Review, 2017)
Les années 1990 sont une décennie cruciale pour l'avancement et le positionnement de l'art et de l'autonomie autochtones dans les récits dominants des états ayant subi la colonisation. Cet article reprend l'exposé des faits de cette période avec des détails fort nécessaires. Pensé comme une historiographie, il propose d'explorer chronologiquement comment les conservateurs et les artistes autochtones, et leurs alliés, ont répondu et réagi à des moments clés des mesures coloniales et les interventions qu'ellesontsuscitéesdu point de vue politique, artistique, muséologique et du commissariat d'expositions. À la lumière du 150e anniversaire de la Confédération canadienne, et quinze ans après la présentation de la communication originale au colloque, Mondialisation et postcolonialisme: Définitions de la culture visuelle v, du Musée d'art contemporain de Montréal, il reste urgent de faire une analyse critique des préoccupations contemporaines plus vastes, relatives à la mise en contexte et à la réconciliation de l'histoire de l'art autochtone sous-représentée.
Keywords: 1-Histoire de l'art; 2-Histoire/Historiographie critique; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Déni et ignorance de l'historicité autochtone dans l'histoire de l'art occidentale - Uzel, Jean-Philippe (RACAR: revue d'art canadienne / Canadian Art Review, 2017)
Western art history long refused to recognize the historicity of Indigenous art, seeing it instead as a "primitive" mode of human expression. While the dynamism of Indigenous creation since the 1960s has made such an assertion impossible, the institutional recognition given contemporary Indigenous art in the art world is paradoxically accompanied by a lack of critical and theoretical analysis. Today, there is a genuine ignorance concerning Indigenous conceptions of history-their "regime of historicity"-on the part of Western art historians. This is all the more surprising given the recent "temporal turn" taken by the discipline, which emphasizes the question of mixed temporalities without acknowledging it as an essential dimension of Indigenous art. This paper revisits Western art history's long-standing denial of the historicity of Indigenous art, and then considers its current disregard for the ways Indigenous art allows different forms of temporality to coexist. The underlying thesis of the essay is that today's disinterest is, in fact, a prolongation of yesterday's denial.
Keywords: 1-Histoire de l'art; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Land and Beaded Identity: Shaping Art Histories of Indigenous Women of the Flatland - Robertson, Carmen (RACAR: revue d'art canadienne / Canadian Art Review, 2017)
Le territoire constitue une force déterminante dans la création artistique. Les prairies austères, notamment, exigent des artistes actuels comme de ceux qui les ont précédés une adaptation constante, déterminée par l'accès aux ressources et la nécessité de mobilité. Cet article s'intéresse à l'impact du territoire sur la pratique du perlage telle qu'exercée par les femmes autochtones. Il met en relation des exemples de perlage traditionnel conservés dans les collections muséales de la Saskatchewan avec les œuvres de trois artistes contemporaines autochtones des plaines, soit Ruth Cuthand, Judy Anderson et Katherine Boyer. La comparaison vise à mieux comprendre le processus intergénérationnel de transmission des pratiques ancestrales et ainsi révéler comment s'exprime le territoire dans les objets et œuvres ornés de perles, qui contribuent à façonner le récit des plaines.
Keywords: 1-Histoire de l'art; 2-Genre et sexualité; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Holding Space: A Roundtable Conversation on Trauma and Teaching in the Museum - DeLos Santos, Jenevieve; Lee, Kathleen Pierce with Key Jo; Martínez, Gabriela; Reaves, Damon; Scruggs, Dalila (Art Journal Open, 2021)
Keywords: 1-Histoire de l'art; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Créateur.rice PANDC; _Nettoyé

Proposition avant-garde: a view from the South - Kapur, Geeta (Art journal / College Art Association of America., 2018)
Keywords: 1-Histoire de l'art; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Sud (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé

Haptic Encounters: Margarita Cabrera’s Space in Between - Szymanek, Angelique (Art Journal Open, 2020)
Keywords: 1-Histoire de l'art; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 5-Autrice; 5-Créateur.rice PANDC; _Nettoyé

Toward a Postcolonial Sociology: The View from Latin America - Bortoluci, José H; Jansen, Robert S (2013)
While sharing fundamental similarities with other colonial and post-colonial experiences, Latin America has a unique history of having been the proving ground for early Spanish and Portuguese imperial projects, of having experienced a relatively long duration of – but also historically early end to – these projects, and of negotiating a particular and complex trajectory of internal and external post-colonial relations. What can the study of this distinct colonial and post-colonial experience contribute to a broader program of postcolonial sociology? Conversely, what can a revitalized postcolonial sociology contribute to the study of Latin America? This article develops provisional answers to these questions by reviewing major currents in South and North American scholarship on the Latin American colonial and post-colonial experience. Some of this scholarship self-consciously identifies with broader movements in postcolonial studies; but much of it – both historical and contemporary – does not. By bringing together diverse strands of thought, this article sheds new light on what postcolonialism means in the Latin American context, while using the comparative leverage that this set of often overlooked cases provides to contribute to a new program of postcolonial sociology.
Keywords: 1-Cinéma; 1-Histoire de l'art; 1-Jeux vidéo; 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); _Nettoyé

Race-ing Art History: Critical Readings in Reace and Art History - Pinder, Kymberly N (Routledge, 2002)
This comprehensive anthology places issues of racial representation squarely on the canvas. Within these pages are representations of Nubians in ancient art, the great tradition of Westernmasters such as Manet and Picasso and contemporary work by lesser known artists.
OCLC: 804390860
Keywords: 1-Histoire de l'art; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 3-Afrique (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Europe (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; 5-Créateur.rice autochtone; 5-Créateur.rice noir.e; 5-Créatrice; _Nettoyé

Artistes femmes, queer et autochtones face à leur(s) image(s): pour une histoire intersectionnelle et décoloniale des arts contemporains autochtones aux Etats-Unis et au Canada (1969-2019) - Journée, Aurélie (École des hautes études en sciences sociales, 2020)
Fin des années 1960 aux Etats-Unis, les Indians of All Tribes impulsent un mouvement de contestations sociales qui a pour but la reconnaissance des droits inhérents aux peuples autochtones à la souveraineté et à l'auto-détermination. L'American Indian Movement et sa branche féminine Women of All Red Nations s'emparent de ces questions sociales, politiques et culturelles. Femmes et hommes entament de concert un processus d'émancipation dont l'accomplissement ne cesse d'être repoussé par les politiques assimilatrices successives du gouvernement états-unien. Au Canada aussi, des mobilisations collectives éclatent dans les années 1980 et 1990, et culminent avec les événements de Restigouche (1984) et la Crise d'Oka (1990). Ces évènements majeurs inspirent toute une jeune génération d'artistes autochtones et de femmes en particulier, formées notamment à l'Institute of American Indian Arts à Santa Fe (Nouveau-Mexique). De formations universitaires approfondies, elles développent des démarches artistiques transdisciplinaires à mi-chemin entre l'histoire de l'art et l'ethnographie. Elles mettent en évidence la porosité et la friabilité des frontières instaurées dans tous les secteurs par la société dominante contre les groupes considérés comme minoritaires. A cette fin, le photographique - par lequel nous désignons la pratique, la technique et l'image photographiques - devient un outil stratégique majeur de réappropriation et de réaffirmation de ce qu'elles sont et tendent à incarner. Ces artistes femmes interrogent grâce à ce médium les façons dont elles ont été représentées et se représentent elles-mêmes dans le cadre de démarches critiques des stéréotypes dont elles font l'objet depuis plusieurs siècles d'appropriation culturelle. Elles repensent par ce biais leurs identités, les rapports qu'elles entretiennent à leurs corps, à leurs sexualités et à leurs genres, à l'aune de leurs propres spiritualités. Grâce à leurs images artistiques et politiques, fruits de pratiques fondées sur une analogie entre la violation de leurs droits, l'exploitation de leurs terres et territoires, et les violences sexuelles dont elles font l'objet, elles continuent à prendre part aux mouvements de résistance actuels qui s'opposent aux projets extractivistes face auxquels elles s'affirment, une nouvelle fois, en première ligne. A partir d'un corpus iconographique de près de 400 œuvres réalisées entre 1969 et 2019, et d'entretiens individuels avec des artistes et des militantes femmes et queer autochtones des Etats-Unis et du Canada, cette thèse a pour objectif de montrer en quoi ces images - en particulier photographiques configurent des épistémologies nouvelles dans une perspective intersectionnelle, décoloniale et anticapitaliste, et s'inscrivent dans la continuité d'un processus de réaffirmation des droits inhérents des peuples autochtones, garantis par la Déclaration des Nations Unies sur les Droits des Peuples Autochtones (2007)
Pages: 1 online resource
Keywords: 1-Histoire de l'art; 2-Genre et sexualité; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Europe (lieu de production du savoir); 5-Auteur.rice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Decolonizing the Spirit in Education and Beyond: Resistance and Solidarity - Wane, Njoki Nathani; Todorova, Miglena S; Todd, Kimberly L (Palgrave Macmillan, 2021)
This multidisciplinary collection probes ways in which emerging and established scholars perceive and theorize decolonization and resistance in their own fields of work, from education to political and social studies, to psychology, medicine, and beyond
OCLC: 1233305994
Keywords: 1-Cinéma; 1-Histoire de l'art; 1-Jeux vidéo; 1-TV; 2-Pédagogie décoloniale; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Afrique (corpus analysé); 3-Amérique centrale (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 3-Océanie (corpus analysé); 5-Auteur.rice; 5-Auteur.rice PANDC; 5-Auteur.rice autochtone; 5-Auteur.rice noir.e; 5-Autrice; _Nettoyé

Decolonial Pedagogy: Examining Sites of Resistance, Resurgence, and Renewal - Wane, Njoki Nathani; Todd, Kimberly L (Palgrave Macmillan, 2018)
"Through innovative and critical research, this anthology inquires and challenges issues of race and positionality, empirical sciences, colonial education models, and indigenous knowledges. Chapter authors from diverse backgrounds present empirical explorations that examine how decolonial work and Indigenous knowledges disrupt, problematize, challenge, and transform ongoing colonial oppression and colonial paradigm. This book utilizes provocative and critical research that takes up issues of race, the shortfalls of empirical sciences, colonial education models, and the need for a resurgence in Indigenous knowledges to usher in a new public sphere. This book is a testament of hope that places decolonization at the heart of our human community." – Prové de l'editor.
OCLC: 1139473230
Keywords: 1-Histoire de l'art; 2-Méthodologie de recherche décoloniale; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Auteur.rice; 5-Auteur.rice noir.e; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Art of the Northwest Coast - Jonaitis, Aldona.. (University of Washington Press, 2006)
"Art of the Northwest Coast is a comprehensive survey of the Native arts of the Pacific Northwest Coast, spanning the region from Puget Sound to Alaska, and proceeding from prehistoric times to the present. Incorporating the region's social history with the observations of anthropologists, historians of art, and Native peoples, this rich, vibrant book reveals how a complex web of factors informed these groups' varied responses to the changes and challenges brought about by contact with Europeans."-
Section: 1 v. (XX-322 p.) : illustrations ; 25 cm
Keywords: 1-Histoire de l'art; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Unpacking Culture: Art and Commodity in Colonial and Postcolonial Worlds - Phillips, Ruth B.; Steiner, Christopher Burghard (University of California Press, 1999)
Tourist art production is a global phenomenon and is increasingly recognized as an important and authentic expression of indigenous visual traditions. These thoughtful, engaging essays provide a comparative perspective on the history, character, and impact of tourist art in colonized societies in three areas of the world: Africa, Oceania, and North America. Ranging broadly historically and geographically, Unpacking Culture is the first collection to bring together substantial case studies on this topic from around the world.
Keywords: 1-Histoire de l'art; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Afrique (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Océanie (corpus analysé); 4-Afrique (lieu de production du savoir); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice; 5-Créateur.rice PANDC; 5-Créateur.rice autochtone; 5-Créateur.rice noir.e; 5-Créatrice; _Nettoyé

Figurative Repatriation First Nations ‘Artist-Warriors’ Recover, Reclaim, and Return Cultural Property through Self-Definition - Kramer, Jennifer (Journal of Material Culture, 2004)
This article begins with an analysis of the problems of ‘physical repatriation’, as I review the case of the return of a First Nations mask to its community of origin. First Nations struggle to fit their concepts of ownership into western ones, where objects are viewed as alienable. As an alternative, the art of John Powell and Marianne Nicolson depicts a ‘figurative repatriation’ that does not rely on either the courts or museums to recognize legal or moral ownership. I argue that these contemporary artworks are social agents, which bring First Nations cultural objects home by staking out territory within museums. These ‘artist warriors’ forcibly recover (both literally and metaphorically) First Nations objects on display in foreign settings and reinscribe meaning at the level of the personal and the communal. They make objectified assertions of native identity that reclaim the right to self-definition. Moreover, these claims are made all the more powerful through their conscious location within an oppositional discourse framed by the Canadian western art world.
Keywords: 1-Histoire de l'art; 2-Histoire/Historiographie critique; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice; 5-Créateur.rice autochtone; _Nettoyé

Native Art of the Northwest Coast: A History of Changing Ideas - Townsend-Gault, Charlotte; Kramer, Jennifer (UBC Press, 2013)
This remarkable volume, many years in the making, records and scrutinizes definitions of Northwest Coast Native art and its boundaries. A work of critical historiography, it makes accessible for the first time in one place a broad selection of more than 250 years of writing on Northwest Coast "art." Organized thematically, its excerpted texts are from both published and unpublished sources, some not previously available in English. They cover such complex topics as the clash between oral and written knowledge, transcultural entanglement, the influence of surrealist thinking, and the long history of the deployment of Northwest Coast Native art for nationalist purposes. The selections are preceded by thought-provoking introductions that give historical context to the diverse intellectual traditions that have influenced, stimulated, and opposed each othe
Section: xxxvi, 1081 pages, 16 pages non numérotées en couleur : illustrations ; 26 cm
Keywords: 1-Histoire de l'art; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice; 5-Auteur.rice autochtone; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Unsettling Native Art Histories on the Northwest Coast - Bunn-Marcuse, Kathryn B.; Jonaitis, Aldona (Bill Holm Center for the Study of Northwest Native Art, Burke Museum, in association with University of Washington Press, 2020)
"This edited collection focuses on "unsettling" Northwest Coast art studies, bringing forward voices that uphold Indigenous priorities, engage with past and ongoing effects of settler colonialism, and advocate for practices for more accountable scholarship. Featuring authors with a variety of perspectives, backgrounds, and methodologies, Unsettling Art Histories offers new insights for the field of Northwest Coast art studies. Key themes include discussions of cultural heritage protections and long-standing defenses of natural resources and territory; re-centering women and the critical role they play in transmitting cultural knowledge across generations through materials, techniques, and creations; reflecting on the decolonization work being undertaken in museums; and examining how artworks function beyond previous scholarly framings as living documents carrying information critical to today's inquiries. Re-examining previous scholarship and questioning current institutional practices by prioritizing information gathered in Native communities, the essays in this volume exemplify various methods of "unsettling" and demonstrate how new methods of research have reshaped scholarship and museum practices."
Section: 334 pages : illustrations (chiefly color) ; 27 cm.
Keywords: 1-Histoire de l'art; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice; 5-Auteur.rice autochtone; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

À travers nos yeux : Santiago Reyes, la futurité Latinx et la performance contre-visuelle - González, Ezequiel N. (Crisol, 2020)
Esta investigación propone una lectura detallada de una obra de arte de performance creada por el artista ecuatoriano Santiago Reyes, “(REM) Romantic Eyes Movement”. Al examinar la representación de los ojos de Reyes, esta reflexión considera hasta qué punto su pieza puede proveer un espacio de resistencia contra-visual y de curación generacional. Por ende, la obra de Santiago Reyes se interpreta bajo la enmarcación teórica de la “futuridad Latinx” y desde una perspectiva decolonial, mostrando cómo la performance transnacional latinoamericana puede proporcionar un vasto corpus de estudio que reflexiona sobre el alcance y la potencial de la expresión corporal performática.
Keywords: 1-Histoire de l'art; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 3-Amérique du Sud (corpus analysé); 5-Créateur.rice PANDC; _Nettoyé

Killing the Indian Maiden: Images of Native American Women in Film - Marubbio, M. Elise (University Press of Kentucky, 2006)
Killing the Indian Maiden examines the fascinating and often disturbing portrayal of Native American women in film. M. Elise Marubbio examines the sacrificial role in which a young Native woman allies herself with a white male hero and dies as a result of that choice. In studying thirty-four Hollywood films from the silent period to the present, she draws upon theories of colonization, gender, race, and film studies to ground her analysis in broader historical and sociopolitical context and to help answer the question, "What does it mean to be an American?"
Keywords: 1-Cinéma; 2-Genre et sexualité; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice; _Nettoyé

Native Americans on Film: Conversations, Teaching, and Theory - Marubbio, M. Elise; Buffalohead, Eric L. (The University Press of Kentucky, 2012)
The film industry and mainstream popular culture are notorious for promoting stereotypical images of Native Americans: the noble and ignoble savage, the pronoun-challenged sidekick, the ruthless warrior, the female drudge, the princess, the sexualized maiden, the drunk, and others. Over the years, Indigenous filmmakers have both challenged these representations and moved past them, offering their own distinct forms of cinematic expression. Native Americans on Film draws inspiration from the Indigenous film movement, bringing filmmakers into an intertextual conversation with academic
Keywords: 1-Cinéma; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice; 5-Auteur.rice autochtone; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

La loi sur les Indiens revisitée = The Indian Act revisited - Sioui-Durand, Guy; Picard-Sioui, Louis-Karl (Musée huron-wendat, 2009)
Catalogue d'exposition
Section: 37 p. : ill. en coul. ; 28 cm
Keywords: 1-Histoire de l'art; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

L’autochtonie dans l’art actuel québécois. Une question partagée - Uzel, Jean-Philippe (Globe, 2014)
À l’heure où les artistes visuels autochtones (Premières Nations, Inuits et Métis) se détachent de la « politique de l’identité », les artistes allochtones (d’ascendance européenne) font de plus en plus souvent référence dans leurs oeuvres à des questions en lien avec l’autochtonie. Cet article examine certaines de ces questions en établissant trois dialogues entre le travail d’un artiste autochtone et d’un artiste allochtone vivant au Québec : l’exploitation industrielle des territoires autochtones dans le Nord du Québec, par l’Algonquine Nadia Myre et l’artiste d’origine suisse Thomas Kneubühler ; les nouvelles attitudes et comportements générés par la société d’hyperconsommation, par l’artiste laich-kwil-tach Sonny Assu et le collectif BGL ; les relations entre Autochtones et colons durant le régime colonial français, chez l’artiste innue Sonia Robertson et l’artiste montréalaise Cynthia Girard. Bien que l’autochtonie, à travers ces trois dialogues, apparaisse comme une question partagée par les artistes actuels autochtones et allochtones, à aucun moment il n’est possible d’établir une équivalence entre les uns et les autres. Alors que chez les artistes allochtones l’autochtonie est traitée comme un motif secondaire, passant parfois inaperçue aux yeux des critiques d’art, elle constitue toujours le thème central des artistes autochtones chez qui elle s’ancre dans le destin, souvent tragique, de leur communauté.
Keywords: 1-Histoire de l'art; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Créateur.rice autochtone; _Nettoyé

Femmes et violence de masse. - Myre, Nadia; Uzel, Jean-Philippe (Spirale, 2018)
"Si tous les groupes humains sont touchés par la violence à grande échelle, les femmes la subissent sous des formes spécifiques, comme en témoignent les assassinats systémiques des femmes et des filles autochtones en Amérique du Nord et en Amérique latine, ou encore les nombreux conflits armés (Syrie, Lybie, Birmanie, entre autres) dans lesquels le viol est érigé en arme de guerre. Les deux phénomènes peuvent d'ailleurs se recouper puisque l'un des tout premiers féminicides à avoir été qualifié et documenté comme tel en Amérique est celui ayant été perpétré contre les femmes mayas durant la guerre civile guatémaltèque au début des années 1980. Cependant, les femmes ne sont pas seulement les victimes de la violence de masse, puisqu'elles sont aussi les premières à témoigner et dénoncer pour faire barrage à cette violence. Ce numéro hors-série regroupe des articles et des projets visuels qui décrivent et analysent la violence de masse liée au genre. Il s'agit de réfléchir sur la manière de représenter cette violence et d'en témoigner, d'autant plus qu'elle est bien souvent rendue invisible et inaudible par le patriarcat, le colonialisme, les intérêts politiques en présence ou l'impéritie de l'État."
Section: 89 pages : illustrations en couleur ; 26 cm
Keywords: 1-Histoire de l'art; 2-Genre et sexualité; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Afrique (corpus analysé); 3-Amérique centrale (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 3-Asie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice; 5-Auteur.rice PANDC; 5-Autrice; 5-Créateur.rice PANDC; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Teresa Margolles: mundos - Margolles, Teresa; Uzel, Jean-Philippe; Garcia, Emeren; Zeppetelli, John; St-Gelais, Thérèse; Morales, Lourdes (Musée d'art contemporain de Montréal, 2017)
Violence and the dead are major thematics in the sociopolitical art of Teresa Margolles. Born in Culiacan, Mexico, Margolles unfalteringly exposes the social causes and consequences of the endemic violence that ravages her country: violent deaths from the drug trade, exclusions, feminicides, and social injustice. Many of her works consist of substances or objects that have been in close contact to violent crimes and dead bodies, such as water with which corpses have been cleaned, blood-soaked earth, or fabric drenched in body fluids. This monograph brings together works from the past decade, along with pieces that have never been shown before, including sculptural and photographic installations, performative interventions and videos. Spare, yet powerfully moving, Margolles's work reaches out and brings the viewer into the world of those whose lives have been made invisible.
Section: 118 pages : illustrations (some color) ; 25 cm
Keywords: 1-Histoire de l'art; 2-Genre et sexualité; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique centrale (corpus analysé); 4-Amérique centrale (lieu de production du savoir); 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; 5-Créateur.rice PANDC; 5-Créatrice; _Nettoyé

Walking With Our Sisters: une commémoration artistique pour le féminicide autochtone, en marche vers la décolonisation - Bruneau, Julie (Recherches féministes, 2017)
En réaction au féminicide autochtone au Canada et à l’inertie du gouvernement canadien, des groupes militants, des associations de familles et de proches des disparues ainsi que des groupes de femmes autochtones lancent régulièrement des actions commémoratives diverses. L’auteure a mené une enquête ethnographique lors de l’installation artistique commémorative Walking With Our Sisters présentée à Ottawa en 2015, projet réalisé par l’artiste métisse Christi Belcourt. Ainsi, l’auteure s’est interrogée sur la valorisation des femmes autochtones et leur prise de pouvoir au travers de ce processus. Elle remet en question la définition du féminisme occidental en prenant en considération les critiques formulées par les féministes autochtones
Keywords: 1-Histoire de l'art; 2-Genre et sexualité; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

L'art contemporain autochtone, point aveugle de la modernité - Uzel, Jean-Philippe (Monde et réseaux de l'art: diffusion, migration et cosmopolitisme en art contemporain, 2000)
Section: 307 pages ; 23 cm
Keywords: 1-Histoire de l'art; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Créateur.rice autochtone; _Nettoyé

La notion d’«autochtonie»: dans la littérature et les arts visuels contemporains - Uzel, Jean-Philippe (Captures, 2018)
Ce numéro, composé de contributions d’auteurs autochtones et allochtones, éclaire les débats actuels entourant la notion d’« autochtonie » dans le champ des arts visuels et de la littérature, tout en rendant compte de la nouvelle effervescence de la création autochtone contemporaine, tout particulièrement au Québec et au Canada. Chacun des textes se penche sur la question de savoir ce que signifie être un artiste autochtone aujourd’hui. Ils mettent tous en évidence que la création contemporaine contribue à l’énonciation de l’identité autochtone. This issue sheds light on current debates surrounding the notion of “Indigeneity” in literature and the visual arts, most particularly in Quebec and Canada. At the same time, the articles by Indigenous and Non-Indigenous authors account for the renewed effervescence of contemporary Indigenous creativity. Each of the texts reflect upon what it means to be an Indigenous artist today. They all bring to light the part played by contemporary Indigenous arts in the utterance of Indigenous identity.
OCLC: 8214656670
Keywords: 1-Histoire de l'art; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Créateur.rice autochtone; _Nettoyé

Pratiques professionnelles en arts visuels issues de l'autochtonie et de la diversité à Montréal - Uzel, Jean-Philippe; Conseil des arts de Montréal (2017)
Rapport commandé par le Conseil des arts de Montréal
OCLC: 1081308169
Keywords: 1-Histoire de l'art; 2-Approches sociologiques; 2-Étude des industries culturelles; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Créateur.rice PANDC; 5-Créateur.rice autochtone; 5-Créateur.rice noir.e; 5-Créatrice; 5-Identités diasporiques; _Nettoyé

La réponse à la Loi sur les Indiens dans les insoumissions performatives de Lawrence Paul Yuxweluptun, Teharihulen Michel Savard et Louis-Karl Picard-Sioui - Desrochers, Marianne (Université de Montréal, 2017)
Entre l’élaboration de la Loi sur les Indiens du Canada en 1876 et les débuts du mouvement Idle No More en 2012, plus d’un siècle de contestation et d’oppression hétéroclite s’est écoulé pour laisser place à une prise de parole vigoureuse portée par l’ensemble des Premières Nations. C’est dans cette perspective que ce mémoire s’intéresse aux pratiques performatives contemporaines élaborées par Lawrence Paul Yuxweluptun (Salish), Teharihulen Michel Savard (Wendat) et Louis-Karl Picard-Sioui (Wendat), dont les œuvres permettent de dresser un éventail varié des stratégies de résistance se consacrant à la libération du regard colonial. Les performances provocantes de ces trois artistes autochtones mettent en place une esthétique de la violence qui, considérée ici en tant qu’outil efficace de résilience et d’affirmation identitaire, déjoue l’autorité coercitive de la Loi sur les Indiens. Centrée sur une approche interdisciplinaire, cette recherche aborde au préalable l’historicité qui sous-tend la construction symbolique de l’indianité, laquelle fut par la suite démentie par les militant.e.s autochtones à travers une diversité de mouvements sociopolitiques contestataires au cours de la seconde moitié du XIXe siècle. Les œuvres performatives de Yuxweluptun, de Teharihulen et de Picard-Sioui font subséquemment l’objet d’une analyse détaillée en regard d’une réappropriation et d’une subversion des codes de la majorité, ce qui leur permet de défier les pouvoirs politiques, économiques, médiatiques et symboliques d’une société eurocentrique cautionnant encore à ce jour une vision figée de la réalité autochtone. Au-delà de la forme et du contenu, les œuvres performatives des artistes à l’étude réinterprètent les traditions immémoriales des Premières Nations tout en les actualisant, venant ainsi confirmer la persistance d’une spécificité culturelle et réfuter les volontés d’annihilation des puissances étatiques et coloniales.
Accepted: 2017-05-25T18:11:08Z
Keywords: 1-Histoire de l'art; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice; 5-Créateur.rice autochtone; _Nettoyé

La réappropriation comme acte politique à l'ère de la décolonisation: l'oeuvre de Nadia Myre - Darsigny-Trépanier, Maude (Université du Québec à Montréal, 2019)
Ce mémoire cherche à dresser l'historiographie de l'artiste anishnabé Nadia Myre. Il s'agit d'une analyse à la fois qualitative et quantitative de près de 200 textes récoltés au sujet de l'artiste du début de sa carrière (1995) jusqu'en 2016. En plus d'offrir une visualisation de l'accomplissement de celle-ci avec la création d'une feuille de calcul, le présent mémoire cherche aussi à analyser les différents propos des auteur.es au sujet de la pratique d'une artiste autochtone en territoire appelé Canada. Les œuvres les plus marquantes de l'artiste sont également analysées en profondeur.
Keywords: 1-Histoire de l'art; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude de la réception; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Oubliées ou disparues : Matérialiser absences et mémoires - Graff, Julie (ICOFOM Study Series, 2020)
L’exposition Öndia’tahterendih, oubliées ou disparues : Akonessen, Zitya, Marie et les autres, créée par la Boite Rouge Vif, une OBNL autochtone du Québec, et la commissaire wendate Sylvie Paré, présente 10 artistes rendant hommage aux femmes et aux filles autochtones touchées par le féminicide autochtone, tout en cherchant à mobiliser le public. Je souhaite dans le cadre de cet article explorer les stratégies mises en place au sein de l’exposition, telle qu’elle a été présentée au musée de la Civilisation du Québec en 2018. Je conclurai en explorant l’inscription de l’exposition dans le développement d’un commissariat engagé autochtone au Canada.
ISBN: 9782491997113 Number: 48-1
Keywords: 1-Histoire de l'art; 2-Approches sociologiques; 2-Genre et sexualité; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique centrale (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Ossements animaux dans l’art autochtone actuel Discours sur la mort, la résurgence et la guérison - Marcoux, Gabrielle (Recherches amérindiennes au Québec, 2015)
Les ossements animaux occupent des fonctions pratiques et rituelles extrêmement variées et complexes au sein des cultures ancestrales atikamekw et innue, que ce soit sur le plan spirituel, alimentaire, artistique ou autre. Encore aujourd’hui, en plus d’évoquer le trépas, les ossements font référence aux pratiques de communication avec les esprits animaux - comme la scapulomancie - et à la vision holistique du monde chez les peuples algonquiens. En intégrant des peaux et des fragments de squelettes animaux à leurs oeuvres portant sur des réalités contemporaines de pertes et de négociations intimes et collectives d’ordre culturel et territorial, les artistes Sonia Robertson et Eruoma Awashish parviennent à réactualiser le pouvoir de guérison et de résurgence traditionnellement associé aux ossements. Ainsi, la mise en scène d’os permet à ces créatrices de réécrire l’histoire de lieux chargés de sens et de réaffirmer l’importance actuelle de notions spirituelles, identitaires et culturelles autochtones ancestrales dans un contexte de réaffirmation collective et individuelle
Keywords: 1-Histoire de l'art; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Carl Beam: The Poetics of Being - Hill, Greg A. (National Gallery of Canada, 2010)
This major retrospective publication confirms Carl Beam (1943 - 2005) as one of North America's most important artists. Beam broke new ground throughout his career, notably as the first artist of Native Ancestry (Ojibwe) to have his work purchased by the National Gallery of Canada as Contemporary Art. Working in various mediums - photography, oil, acrylic, stone, cement, wood, ceramics and found objects - Beam's work continually explored the tensions between Western and Aboriginal relations. Featuring more than 50 of Beam's most remarkable works from his early career in the 1970s to the end of his production in the early 2000s, this richly illustrated monograph illuminates the artist's investigations into the metaphysical aspects of Western and Indigenous culture, while powerfully illustrating the wideranging physicality of his work. Source: Publisher
Section: 137 pages : illustrations (some color) ; 28 cm
Keywords: 1-Histoire de l'art; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Créateur.rice autochtone; _Nettoyé

Reservation X - McMaster, Gerald R. (Goose Lane, 1998)
Catalogue d'une exposition tenue à l'origine au "First People's Hall of the Canadian Museum of Civilization", prise en charge par Gerald McMaster. Publié avec le "Canadian Museum of Civilization
Keywords: 1-Histoire de l'art; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Aboriginal Territories in Cyberspace - Lewis, Jason E.; Fragnito, Skawennati T. (Cultural Survival Quarterly., 2005)
Indigenous peoples are making their own spaces online, using art as the backdrop for cross-cultural dialogue. Cyberspace—the websites, chat rooms, bulletin boards, virtual environments, and games that make up the internet—offers Aboriginal communities an unprecedented opportunity to assert control over how we represent ourselves to each other and to non-Aboriginals. This article introduces the concept of Aboriginally determined territories in cyberspace and discusses how these can be defined, maintained, and expanded. We will do this within the Canadian context, though much of the discussion is pertinent to Aboriginal communities in other parts of the world. We draw on lessons learned from creating and curating CyberPowWow, an Aboriginally determined online gallery, to propose Aboriginal Territories in Cyberspace, a series of initiatives to expand Aboriginal presence online. These include expanding CyberPowWow into an ongoing community of new media artists addressing Aboriginal issues; developing Skins, a project in which elders work with youth to explore tribal stories through the use of online virtual environments; and laying the foundations for Within Reservations, which will function as a blueprint for equipping Aboriginals for full participation in the ongoing revolution in networked information technologies.
Place: Cambridge, Mass. OCLC: 109435875
Keywords: 1-Histoire de l'art; 2-Humanités numériques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; _Nettoyé

Afterlives of Indigenous archives: essays in honor of The Occom Circle - Schweitzer, Ivy; Henry, Gordon (Dartmouth College Press, 2019)
"Afterlives of Indigenous Archives offers a compelling critique of Western archives and their use in the development of “digital humanities.” The essays collected here present the work of an international and interdisciplinary group of indigenous scholars; researchers in the field of indigenous studies and early American studies; and librarians, curators, activists, and storytellers. The contributors examine various digital projects and outline their relevance to the lives and interests of tribal people and communities, along with the transformative power that access to online materials affords. The authors aim to empower native people to re-envision the Western archive as a site of community-based practices for cultural preservation, one that can offer indigenous perspectives and new technological applications for the imaginative reconstruction of the tribal past, the repatriation of the tribal memories, and a powerful vision for an indigenous future."
OCLC: 1080555941
Keywords: 1-Histoire de l'art; 2-Histoire/Historiographie critique; 2-Humanités numériques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Indigenous Futurisms: Transcending Past/Present/Future - Herr, Chelsea; Well-Off-Man, Manuela; Fricke, Suzanne Newman (IAIA Museum of Contemporary Indian Arts, 2020)
Indigenous Futurisms: Transcending Past/Present/Future investigates a major trend in Contemporary Native Art–the rise of futuristic or science-fiction inspired Native American art. The essays and artworks present the future from a Native perspective and illustrate the use of Indigenous cosmology and science as part of tribal oral history and ways of life. Several of the artists use sci-fi related themes to emphasize the importance of Futurism in Native cultures, to pass on tribal oral history and to revive their Native language. However, Indigenous Futurism also offer a way to heal from the traumas of the past and present–the post-apocalyptic narratives depicted in some of the artworks are often reality for Indigenous communities worldwide.
OCLC: 1197536229
Keywords: 1-Histoire de l'art; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice; 5-Auteur.rice autochtone; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

You Want to Do What with Doda’s Stories? Building a Community for the Skins Workshops on Aboriginal Storytelling in Digital Media - Lewis, Jason E.; Fragnito, Skawennati (Community-Based Multiliteracies & Digital Media Projects : Questioning Assumptions and Exploring Realities, 2014)
Aboriginal Territories in Cyberspace (AbTeC) is a research network of artists, academics and technologists centrally concerned with Indigenous representation in, and production of, digital media (AbTeC, 2008). AbTeC investigates and identifies ways for Indigenous peoples to tell our stories via networked technologies, and in so doing, strengthen our communities while proactively participating in shaping cyberspace. We are based at Concordia University, in Montreal, Quebec.
Section: xvi, 258 pages ; 23 cm.
Keywords: 1-Histoire de l'art; 1-Jeux vidéo; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Aesthetics, Violence, and Indigeneity. - Rickard, Jolene (Public, 2016)
This essay considers the intersectionality between the field of art history focused on the subject category of Native American or Indigenous art and Indigenous Studies. Methodological gaps in the field of art history are discussed through the canonical genre of landscape art with a comparative reference to key exhibitions; Land Spirit Power: First Nations at the National Gallery of Canada, (1992), The West As America: Reinterpreting Images of the Frontier, 1820-1920, (1991), Submuloc Show/Columbus Wohs (1992), Our Land/Ourselves: Contemporary Native American Landscape (1991) and Picturing the Americas: Landscape Painting from Tierra del Fuego to the Artic (2015). The aestheticization of the colonization of the Americas as represented in the genre of landscape art is interrogated as a form of historical violence that needs to be decolonized within the field of art history.
OCLC: 1051992463
Keywords: 1-Histoire de l'art; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice; 5-Auteur.rice autochtone; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Partial Recall - Benally, Suzanne (New Press, 1992)
In Partial Recall, twelve Native American artists and writers look deep into the images that have shaped our ideas of "Indianness," and explore the complex relationship of photography to identity. For this volume, edited and introduced by Lucy Lippard, each contributor has chosen one or two photographs as the point of departure for their original poetic, historical, political, or autobiographical essays. With an additional portfolio of more than sixty photographs drawn from around the country, Partial Recall is a unique and valuable anthology.
OCLC: 26767689
Keywords: 1-Histoire de l'art; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice; 5-Auteur.rice autochtone; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Absorbing or Obscuring the Absence of a Critical Space in the Americas for Indigeneity: The Smithsonian's National Museum of the American Indian - Rickard, Jolene (Res: Anthropology and Aesthetics, 2007)
Keywords: 1-Histoire de l'art; 2-Approches sociologiques; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique centrale (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice; 5-Auteur.rice autochtone; _Nettoyé

Visualizing Sovereignty in the Time of Biometric Sensors - Rickard, Jolene (South Atlantic Quarterly, 2011)
Multiple expressions of sovereignty beyond a narrow legal interpretation are discussed through the artwork of contemporary Iroquois artists, G. Peter Jemison (Seneca), Alan Michelson (Mohawk), Samuel Thomas (Cayuga), and Marie Watt (Seneca). Michelson's installation at the Massena homeland security border checkpoint between the United States, Canada, and the Mohawk Nation, titled The Third Bank of the River, draws on the Guswentah or Two Row Wampum underscoring the problematic yet ongoing assertion of Haudenosaunee sovereignty. A link is made between the work of these artists and the 2008 Courtney Hunt film, Frozen River, based on the cultural and political understanding of the Two Row Wampum. The Guswentah is discussed as a demonstration of sovereignty and is historicized through Cayuga chief Deskaheh's call for the recognition of Haudenosaunee sovereignty at the League of Nations in Geneva, in 1923, John Mohawk's 1978 Basic Call to Consciousness, and more recently, Taiaiake Alfred's 1999 Peace, Power, Righteousness. These artists demonstrate the critical role they play in the ongoing formation of sovereignty as a visual or aesthetic issue in conjunction with its historic legal positioning.
OCLC: 6965319862
Keywords: 1-Histoire de l'art; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice; 5-Auteur.rice autochtone; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

La muséologie collaborative au Canada : le positionnement du Musée McCord à l’égard des communautés autochtones - Franco, Marie-Charlotte (Musées, mutations…, 2019)
Résumé livre : 4e de couv.: Les mutations qui se sont amorcées à partir de la fin de la Seconde Guerre mondiale et qui connaissent une accélération rapide avec les crises sociales, culturelles, économiques et environnementales contemporaines ont transformé le paysage muséal et les visions dont les musées se soutiennent et qu'ils entretiennent. La plupart des travaux produits au cours de ces années ont été portés par ces transformations et y contribuent : la recherche en muséologie s'est elle-même dissociée de la recherche dans les musées dans les années 1980. De plus, quelque chose s'est noué entre un tournant communicationnel dans les musées et un développement de la réflexion théorique et critique sur la communication. Dans une approche résolument pluridisciplinaire, cet ouvrage se propose d'analyser ces évolutions dans leurs dimensions institutionnelles, culturelles, communicationnelles, historiques, patrimoniales. Les perspectives réunies ici contribueront, sans aucun doute, à mettre au jour les mouvements de fond actuels, les tendances qui travaillent les institutions elles-mêmes, et le poids de ces changements dans la formulation des enjeux théoriques en muséologie.
Section: 324 pages ; 21 cm.
Keywords: 1-Histoire de l'art; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Le musée: un outil de développement identitaire et communautaire en contexte autochtone? : le cas du Musée des Abénakis à Odanak - Franco, Marie-Charlotte (Université du Québec à Montréal, 2012)
Section: 61, xii f. ; 28 cm.
Keywords: 1-Histoire de l'art; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Décoloniser l’imaginaire esthétique : Vers une écriture de nouveaux paradigmes caribéens - Kirchner-Blanchard, Catherine; Lefrançois, Frédéric (Revue d'Études Décoloniales, 2018)
Keywords: 1-Histoire de l'art; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique centrale (corpus analysé); 3-Amérique du Sud (corpus analysé); 5-Auteur.rice noir.e; 5-Créateur.rice PANDC; _Nettoyé

Épistémologies du Sud, pensées et féminismes décoloniaux latino-américains - Coenga-Oliveira, Danielle (Revue Possibles, 2019)
Keywords: 1-Cinéma; 1-Histoire de l'art; 1-Jeux vidéo; 1-TV; 2-Genre et sexualité; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique centrale (corpus analysé); 3-Amérique du Sud (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé

El color de la razón: racismo epistemológico y razón imperial - Castro-Gómez, Santiago; Eze, Emmanuel Chukwudi; Henry, Paget (Ediciones del Signo, 2014)
Keywords: 1-Cinéma; 1-Histoire de l'art; 1-Jeux vidéo; 1-TV; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Afrique (corpus analysé); 3-Amérique centrale (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 4-Afrique (lieu de production du savoir); 4-Amérique du Nord (lieu de production du savoir); 4-Amérique du Sud (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; _Nettoyé

Décolonisant l'argent à Porto Rico - Negrón-Muntaner, Frances (revue Periferias, 2019)
Keywords: 1-Histoire de l'art; 2-Approches sociologiques; 2-Recherche-création; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique centrale (corpus analysé); 4-Amérique centrale (lieu de production du savoir); 5-Auteur.rice; 5-Créateur.rice PANDC; 5-Identités diasporiques; _Nettoyé

WàCOLETIVO : Broderie, couture et crochet comme art contemporain dans l'espace public - WàCOLETIVO (revue Periferias, 2019)
Keywords: 1-Histoire de l'art; 2-Genre et sexualité; 2-Recherche-création; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Sud (corpus analysé); 4-Amérique du Sud (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Créateur.rice PANDC; _Nettoyé

Musee Migrant – MuMi - Clériga Morales, Deyanira; Valenzuela Arámburo, Pável; Ledón Pereyra, Aldo Jorge (revue Periferias, 2019)
Keywords: 1-Cinéma; 1-Histoire de l'art; 2-Histoire/Historiographie critique; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Sud (corpus analysé); 4-Amérique du Sud (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Créateur.rice PANDC; _Nettoyé

MuMi - Museo Migrante (Revista Periferias)
En la lucha es donde la gente se encuentra, Na luta é que a gente se encontra, porque a pesar de nuestras distancias físicas, del idioma, de las diferencias culturales, siempre están nuestras raíces históricas que nos dejan encontrarnos con gente que construye en medio de un mundo hostil. Este texto está realizado por miembros […]

L’art périphérique montre l’afro-diaspora en environnement digital - del Rei, Mariana (revue Periferias, 2021)
Keywords: 1-Histoire de l'art; 2-Humanités numériques; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Sud (corpus analysé); 4-Amérique du Sud (lieu de production du savoir); 5-Auteur.rice noir.e; 5-Créateur.rice noir.e; 5-Identités diasporiques; _Nettoyé

Pour un féminisme afro-latino-américain - Gonzalez, Leila (Revue d'Études Décoloniales, 2020)
Keywords: 1-Cinéma; 1-Histoire de l'art; 1-Jeux vidéo; 1-TV; 2-Genre et sexualité; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Sud (corpus analysé); 4-Amérique du Sud (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; _Nettoyé

Introduction de feminismos desde abya yala - Gargallo, Francesca (Revue d'Études Décoloniales, 2020)
Quand les conditions requises pour le dialogue ne sont pas réunies, il est difficile d’expliquer à une femme blanche : " écoute, nous ne voulons pas qu’on nous impose des de critères féministes hégémoniques " . Cela étant, je reconnais et j’apprécie tout ce que j’ai appris sur les différents courants féministes. Car grâce à eux, je me reconnais comme sujette épistémique et je peux me penser à partir du corps et de l’espace où je vis. Ou encore tisser des idées féministes. C’est ainsi que la construction consciente de mon identité féministe communautaire se renforce et en même temps, nous contribuons au mouvement féministe dans le monde. Par exemple, l’une des étapes que nous devons franchir passe par la langue : nommer dans nos propres langues, qui auront été libérées, les catégories et les concepts que nous élaborons pour analyser l’oppression subie par notre peuple dans l’histoire et notre libération en tant que femmes indigènes, autochtones, paysannes, rurales, ou villageoises. Francesca Gargallo est une écrivaine et féministe autonome italo-mexicaine. Licenciée en philosophie de la Sapienza de Rome et docteure en Études Latinoaméricaines de l’UNAM mexicaine, cette spécialiste de l’histoire des idées féministes, prenant acte de l’échec de l’utopie socialiste, propose de chercher des alternatives à partir d’un féminisme clairement antiraciste, qui fasse la critique de l’ eurocentrisme. Elle s’intéresse au concept de colonialisme interne de Pablo González Casanova, ou de Silvia Rivera Cusicanqui. Le livre dont nous traduisons deux extraits, Feminismos desde Abya Yala. Ideas y proposiciones de las mujeres de 607 pueblos en NuestraAmérica, a été publié en 2012 aux éditions Desde abajo.
Keywords: 1-Cinéma; 1-Histoire de l'art; 1-Jeux vidéo; 1-TV; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique centrale (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 4-Amérique du Sud (lieu de production du savoir); 5-Auteur.rice; _Nettoyé

L’hybris du point zero. Science, race et Lumières en Nouvelle-Grenade (1750-1816) - Castro-Gómez, Santiago (Revue d'Études Décoloniales, 2017)
Ce texte est la traduction de l’introduction au livre de Santiago Castro-Gómez, La hybris del punto cero: ciencia, raza e ilustración en Nueva Granada (1750-1816), Bogota: Ed. Pontificia Universidad Javeriana, 2005.
Keywords: 1-Cinéma; 1-Histoire de l'art; 1-Jeux vidéo; 1-TV; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Sud (corpus analysé); 4-Amérique du Sud (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé

L’hybris du point zero. Science, race et Lumières en Nouvelle-Grenade (1750-1816) - Rougier, Claude (Revue d'Études Décoloniales, 2017)
Ce texte est la traduction de l’introduction au livre de Santiago Castro-Gómez, La hybris del punto cero: ciencia, raza e ilustración en Nueva Granada (1750-1816), Bogota: Ed. Pontificia Univ…

Lumière sur le mouvement décolonial latino-américain - Bonvalot, Anne-Laure (Revue du crieur, 2020)
En France, depuis quelques années, le terme « décolonial » fait couler beaucoup d'encre. Employé d'abord dans les milieux militants antiracistes, il a fait plus récemment l'objet de manifestations scientifiques et de travaux académiques, ainsi que d'une réappropriation médiatique qui, en en dévoyant bien souvent le sens, jette sur lui une forme d'anathème, lui conférant une coloration largement polémique. Les théories et les mouvements décoloniaux restent ainsi fondamentalement mal compris, et leurs concepts fondateurs, comme la notion de colonialité, ne sont presque jamais rapportés à leur contexte d'origine ni aux penseurs et penseuses qui les ont forgés. L'histoire de la pensée et de la pratique décoloniales, malgré des travaux universitaires ou des revues dédiées de plus en plus nombreux, reste finalement mal aimée, parce que mal connue, du grand public. Pour dissiper les amalgames ordinaires qu'occasionne en France la réception souvent trop superficielle de ces courants, des universitaires et / ou militant·e·s tentent de diffuser la richesse conceptuelle et politique du mouvement. Leurs travaux soulignent la nécessité de faire connaître la voix d'intellectuel·le·s et d'activistes latino-américain·e·s en diffusant leurs textes en langue française, en les soumettant au débat ou en en proposant des approches critiques. On peut dire qu'un champ d'études décoloniales, encore jeune, mais pluriel et foisonnant, est en cours de consolidation. Retour aux origines Si les termes « décolonial » et « décolonialité » se chargent souvent dans les médias français de connotations hostiles, du fait notamment de la critique radicale de la modernité qu'ils induisent ou du soupçon de communautarisme qu'ils soulèvent, il importe de revenir à l'origine du mouvement décolonial, des théories et concepts qui le fondent, aux luttes, aux résistances concrètes et aux propositions de mondes qu'il recouvre. Pour tenter de mettre en lumière ses apports-philosophiques, mais aussi épistémologiques, politiques, ontologiques ou esthétiques-, un tour d'horizon s'impose des différent·e·s auteur·e·s et notions qui caractérisent le mouvement décolonial, au demeurant éminemment pluriel, d'Amérique latine.
Keywords: 1-Cinéma; 1-Histoire de l'art; 1-Jeux vidéo; 1-TV; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Sud (corpus analysé); 4-Europe (lieu de production du savoir); 5-Autrice

Le postcolonial en Amérique latine: débats contemporains - Gómez-Muller, Alfredo (2016)
"En Amérique latine comme ailleurs, la critique postcoloniale apparaît comme une condition pour le renouvellement des dialogues interculturels orientés vers la construction d'une modernité alternative, ou d'une vraie postmodernité, fondée sur une autre manière d'habiter la terre, moins dévastatrice pour la nature comme pour les humains. Reprenant d'une manière inédite la perspective ouverte au XXe siècle par des auteurs comme José Carlos Mariátegui, Alberto Flores Galindo, Pablo González Casanova ou René Zavaleta, les études postcoloniales latino-américaines contribuent à la critique d'un modèle culturel, social et politique fondé sur le clivage traditionnel entre la " civilisation " et la "barbarie". Articulée initialement par un versant de la modernité européenne qui trouvera au XVIIIe siècle une forme systématique dans l'anthropologie des Lumières (M. Duchet), cette dichotomie a été au départ la matrice idéologique de la domination coloniale européenne, et, plus tard, de celle des nouvelles élites " républicaines " attelées à la tâche de construire l'unité sociale et politique sur la base du modèle européen de l'État-nation. Au XIXe siècle et durant une bonne partie du XXe, l'unité de la "Nation" est imaginée de telle manière qu'elle implique l'exclusion de la différence culturelle dans l'espace public. Or, depuis les quatre dernières décennies, les nouvelles formes de la mobilisation indienne et la renaissance des identités afro-américaines participent à la crise des modèles identitaires établis et au surgissement, dans divers domaines du culturel et du politique, de manières inédites d'imaginer l'identité (subjective, sociale, culturelle, nationale) et d'assumer la diversité culturelle (inter-culturalité, multiculturalismes, indianisation) dans la sphère publique. Le présent ouvrage propose un aperçu des problématiques, recherches et discussions actuelles sur le postcolonial en Amérique latine, en prenant comme fil conducteur les processus de reconfiguration identitaire liés à l' " émergence indienne " et au renouveau actuel des identités afro-américaines."–Page 4 de la couverture.
Keywords: 1-Cinéma; 1-Histoire de l'art; 1-Jeux vidéo; 1-TV; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Sud (corpus analysé); 4-Europe (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé

La photographie comme affirmation. Aperçu d’un mouvement d’autoreprésentation - Guignard, Sophie (Inter, 2016)
Keywords: 1-Histoire de l'art; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Diversifying Sovereignty and the Reception of Indigenous Art - Rickard, Jolene (Art Journal, 2017)
Keywords: 1-Histoire de l'art; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 2-Étude de la réception; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; _Nettoyé

Indigenous Feature Film Production in Canada: A National and International Perspective - Goulet, Danis; Swanson, Kerry (ImagineNATIVE Film + Media Arts Festival, 2014)
The goal of this research is to examine Aboriginal feature film production in Canada, specifically within the genre of drama. This report documents the rise of Indigenous cinema worldwide and examines Canada's public funding landscape including funding allocations to Aboriginal feature film production from Canada's public funders of film over a five-year period from 2007 to 2012. This report also examines the barriers to feature film production for Aboriginal content creators in Canada, and suggests areas of opportunity that can be targeted in order to boost production in this sector. Aboriginal film production is a relatively young sector, with scarce research existing on the industry. To address this gap in the available information on the sector, the researchers expanded the scope of the study beyond public funding agencies in Canada to include data from public funding agencies in Australia and New Zealand. Aboriginal feature film production in Canada is situated within a global Indigenous cinema context. Australia and New Zealand, in particular, are two pillars of global Indigenous film that offer a realistic point from which to compare Canada's progress. As a result, data from Australia and New Zealand are included in the study, as well as one model in the United States.
Keywords: 1-Cinéma; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 2-Étude des industries culturelles; 3-Amérique du Nord (corpus analysé); 3-Océanie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Shapeshifters, Time Travellers and Storytellers - Hopkins, Candice; Swanson, Kerry (Royal Ontario Museum, 2008)
"Incorporating evocative objects from the Museum's collections, this thought-provoking exhibition presents eight contemporary Aboriginal artists whose works explore the ways in which past and present continue to merge and shape one another. This exhibition features eight striking installations, including more than 25 individual artworks by internationally renowned artists Suvinai Ahsoona, Faye HeavyShield, Cheryl L’Hirondelle, Isuma Productions (Zacharias Kunuk and Norman Cohn), Brian Jungen, Alan Michelson, Nadia Myre and Kent Monkman. Five of the eight works, which include video, sound, sculpture, drawings, painting and performance art, were created specifically for this exhibition. Co-organized by the Royal Ontario Museum’s Institute for Contemporary Culture and the imagineNATIVE Film + Media Arts Festival. Co-curated by Kerry Swanson and Candice Hopkins.
Section: 59 p. : ill. (chiefly col.), ports. ; 19 x 23 cm.
Keywords: _Nettoyé

Art for a New Understanding: Native Voices, 1950s to Now - Hopkins, Candice; Well-Off-Man, Manuela; Besaw, Mindy N.; Crystal Bridges Museum of American Art (University of Arkansas Press, 2018)
"Art for a New Understanding, an exhibition from Crystal Bridges Museum of American Art that opened in October 2018, seeks to radically expand and reposition the narrative of American art since 1950 by charting a history of the development of contemporary Indigenous art from the United States and Canada, beginning when artists moved from more regionally-based conversations and practices to national and international contemporary art contexts. This accompanying book documents and expands on the histories and themes of this exciting exhibition. This fully illustrated volume includes essays by art historians and historians and reflections by the artists included in the collection. Also included are key contemporary writings–from the 1950s onward–by artists, scholars, and critics, investigating the themes of transculturalism and pan-Indian identity, traditional practices conducted in radically new ways, displacement, forced migration, shadow histories, the role of personal mythologies as a means to reimagine the future, and much more. As both a survey of the development of Indigenous art from the 1950s to the present and a consideration of Native artists within contemporary art more broadly, Art for a New Understanding expands the definition of American art and sets the tone for future considerations of the subject. It is an essential publication for any institution or individual with an interest in contemporary Native American art, and an invaluable resource in ongoing scholarly considerations of the American contemporary art landscape at large."
Section: xiii, 205 pages : illustrations principalement en couleur, portraits ; 27 cm
Keywords: 1-Histoire de l'art; 2-Histoire/Historiographie critique; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Mapping Modernisms: Art, Indigeneity, Colonialism - Harney, Elizabeth; Phillips, Ruth B. (Ruth Bliss) (Duke University Press, 2018)
Mapping Modernisms" brings together scholars working around the world to address the modern arts produced by indigenous and colonized artists. Expanding the contours of modernity and its visual products, the contributors illustrate how these artists engaged with ideas of Primitivism through visual forms and philosophical ideas. Although often overlooked in the literature on global modernisms, artists, artworks, and art patrons moved within and across national and imperial borders, carrying, appropriating, or translating objects, images, and ideas. These itineraries made up the dense networks of modern life, contributing to the crafting of modern subjectivities and of local, transnationally-inflected modernisms. Addressing the silence on indigeneity in established narratives of modernism, the contributors decenter art history's traditional Western orientation and prompt a re-evaluation of canonical understandings of twentieth-century art history. 'Mapping Modernisms' is the first book in Modernist Exchanges, a multivolume project dedicated to rewriting the history of modernism and modernist art to include artists, theorists, art forms, and movements from around the world."
Section: xviii, 432 pages : illustrations (certaines en couleur) ; 23 cm.
Keywords: 1-Histoire de l'art; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; 5-Créateur.rice PANDC; 5-Créateur.rice autochtone; _Nettoyé

Sensible Objects: Colonialism, Museums, and Material Culture - Edwards, Elizabeth; Gosden, Chris; Phillips, Ruth B. (Routledge, Taylor & Francis Group, 2020)
Anthropologists of the senses have long argued that cultures differ in their sensory registers. This groundbreaking volume applies this idea to material culture and the social practices that endow objects with meanings in both colonial and postcolonial relationships. It challenges the privileged position of the sense of vision in the analysis of material culture. Contributors argue that vision can only be understood in relation to the other senses. In this they present another challenge to the assumed western five-sense model, and show how our understanding of material culture in both historical and contemporary contexts might be reconfigured if we consider the role of smell, taste, touch and sound, as well as sight, in making meanings about objects.
Keywords: 1-Histoire de l'art; 2-Approches sociologiques; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; 5-Créateur.rice PANDC; 5-Créateur.rice autochtone; _Nettoyé

Trading Identities: The Souvenir in Native North American Art from the Northeast, 1700-1900 - Phillips, Ruth B. (Ruth Bliss) (McGill-Queen's University Press, 1998)
Indians in northeastern North America produced a variety of art objects for sale to travelers and tourists during the 18th and 19th centuries. This art is of high quality and great aesthetic interest, but has been largely ignored by scholars. This study combines fieldwork, art historical analysis
Section: xvii, 334 pages : illustrations (certaines en couleur)
Keywords: 1-Histoire de l'art; 2-Approches sociologiques; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Museum Pieces: Toward the Indigenization of Canadian Museums - Phillips, Ruth B. (Ruth Bliss) (McGill-Queen's University Press, 2011)
Ruth Phillips argues that these practices are "indigenous" not only because they originate in Aboriginal activism but because they draw on a distinctively Canadian preference for compromise and tolerance for ambiguity. Phillips dissects seminal exhibitions of Indigenous art to show how changes in display, curatorial voice, and authority stem from broad social, economic, and political forces outside the museum and moves beyond Canadian institutions and practices to discuss historically interrelated developments and exhibitions in the United States, Britain, Australia, and elsewhere. Drawing on forty years of experience as an art historian, curator, exhibition critic, and museum director, she emphasizes the complex and situated nature of the problems that face museums, introducing new perspectives on controversial exhibitions and moments of contestation. A manifesto that calls on us to re-imagine the museum as a place to embrace global interconnectedness, Museum Pieces emphasizes the transformative power of museum controversy and analyses shifting ideas about art, authenticity, and power in the modern museum.
Section: xvi, 376 p., [16] p. de pl. : ill. (certaines en coul.).
Keywords: 1-Histoire de l'art; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Transforming Images: The Art of Silver Horn and His Successors - Berlo, Janet Catherine; Donnelley, Robert G; Green, Candace S (David and Alfred Smart Museum of Art, University of Chicago, 2001)
Silver Horn's art documents the changes in the lives of the Kiowa Indians, as well as changes in Kiowa art itself. The art presented here, shows the bridge he created between ancient Kiowa aesthetics and modern forms of expression that had an impact on younger Native American artists.
OCLC: 1101258728
Keywords: 1-Histoire de l'art; 2-Histoire/Historiographie critique; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; 5-Créateur.rice autochtone; _Nettoyé

The Early Years of Native American Art History: The Politics of Scholarship and Collecting - Berlo, Janet Catherine (University of Washington Press, 1992)
This collection of essays deals with the development of Native American art history as a discipline.
Keywords: 1-Histoire de l'art; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

The Land We Are: Artists & Writers Unsettle the Politics of Reconciliation - McCall, Sophie; L'Hirondelle Hill, Gabrielle (ARP Books, 2015)
The land we are' is a stunning collection of writing and art that interrogates the current era of reconciliation in Canada. Using visual, poetic, and theoretical language, the contributorsn approach reconciliation as a problematic narrative about Indigenous-settler relations, but also as a site where converseations about a just future must occur. The result of a four-year collaboration between artists and scholars engaged in resurgence and decolonization, 'The land we are' is a moving dialogue that blurs the boundaries between activism, research, and the arts
Section: viii, 225 pages : ment illustrations (principalement en couleur) ; 25 cm.
Keywords: 1-Histoire de l'art; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; _Nettoyé

Contemporary Indigenous Arts in the Classroom - Garneau, David; Nadeau, Stephanie; Dumais, Doug; Cross, Wahsontiio (Galerie d'art d'Ottawa = Ottawa Art Gallery, 2018)
Section: pages cm.
Keywords: 1-Histoire de l'art; 2-Pédagogie décoloniale; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; _Nettoyé

How Aborigines Invented the Idea of Contemporary Art: Writings on Aboriginal Contemporary Art - McLean, Ian (Institute of Modern Art, 2011)
Chronicles the global critical reception of Aboriginal art since the early 1980s and argues for a re-evaluation of Aboriginal art's critical intervention into contemporary art.
OCLC: 762144288
Keywords: 1-Histoire de l'art; 2-Approches sociologiques; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 2-Étude de la réception; 3-Océanie (corpus analysé); 4-Océanie (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Double Desire: Transculturation and Indigenous Contemporary Art - McLean, Ian (Cambridge Scholars Publishing, 2014)
ouble Desire challenges the tendency by critics to perpetuate an aesthetic apartheid between Indigenous and Western art. The double desire explored in this book is that of the divided but also amplified attractions that occur between cultural traditions in places where both indigenous and colonial legacies are strong. The result, it is argued, produces imaginative transcultural practices that resist the assimilation or acculturation of Indigenous perspectives into the dominant Western...
Section: xviii, 376 pages, 6 pages de planches : illustrations en partie en couleur ; 22 cm.
Keywords: 1-Histoire de l'art; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Afrique (corpus analysé); 3-Amérique centrale (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 3-Asie (corpus analysé); 3-Océanie (corpus analysé); 4-Océanie (lieu de production du savoir); 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

In the Shadow of the Sun: Perspectives on Contemporary Native Art - McMaster, Gerald (Canadian Museum of Civilization, 1993)
This volume makes available in English most of the essays written to accompany the Canadian Museum of Civilization's exhibition In the shadow of the sun. Not included from the original German publication are the exhibition catalogue section and the essays by Gisela Hoffmann, Bernadette Driscoll and Elizabeth McLuhan. However, Viviane Gray's article appears in this document for the first time. Complemented by images of contemporary Indian and Inuit art, the book provides an overview of the evolution of contemporary Canadian Native art. Regional styles as well as the styles of individual artists are discussed, and the various subjects, themes and techniques reflected in the works of art are examined
Section: XIII, 538 pages : illustrations ; 24 cm
Keywords: 1-Histoire de l'art; 2-Muséologie critique; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

On Aboriginal Representation in the Gallery - Jessup, Lynda; Bagg, Shannon (Canadian Museum of Civilization, 2002)
This book provides a glimpse of thirteenth-century life and death in a southern Ontario Iroquoian community. The renovation of a Toronto soccer field in 1997 resulted in the accidental discovery of an Iroquoian ossuary–a large pit containing the remains of at least 87 people. The pit was excavated and recorded, and the remains reburied in accordance with the wishes of the Six Nations Council of Oshweken. Scientific analyses of the bones resulted in a remarkably detailed demographic profile of the Moatfield people, along with indicators of their health and diet. The book reports these findings and includes a complete database of maps and profiles on an accompanying CD-ROM. Ronald F. Williamson is president of Archaeological Services Inc., Toronto. Susan Pfeiffer is professor of anthropology at the University of Toronto. Source: Publisher
Section: XXX-310 p. : illustrations ; 25 cm
Keywords: 1-Histoire de l'art; 2-Muséologie critique; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

D’Indigena à Sakahàn. Éléments de réflexion pour une affirmation autochtone dans l’art contemporain - Franco, Marie-Charlotte (Inter, 2016)
Keywords: 1-Histoire de l'art; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Àbadakone: feu continuel = continuous fire - Dickenson, Rachelle; Hill, Greg A.; Lalonde, Christine (Musée des beaux-arts du Canada, 2020)
Ce survol de l'art contemporain indigène, qui connut un succès retentissant dès son ouverture en novembre 2019, a été prolongé jusqu'au 4 octobre au Musée des beaux-arts du Canada. Àbadakone permet de découvrir des œuvres de plus de 70 artistes qui revendiquent leur appartenance à quelque 40 nations, ethnies et tribus de 16 pays, dont le Canada. Traitant des thèmes de la continuité, de l'activation et de l'interdépendance, Àbadakone explore la créativité, les préoccupations et la vitalité qui marquent l'art indigène de presque tous les continents. L'exposition est organisée par les conservateurs du Musée des beaux-arts du Canada Greg A. Hill, Christine Lalonde et Rachelle Dickenson, conseillés par les commissaires Candice Hopkins, Ariel Smith et Carla Taunton, ainsi que par une équipe d'experts du monde entier. .
Section: 271 pages : illustrations en couleur ; 25 cm
Keywords: 1-Histoire de l'art; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Afrique (corpus analysé); 3-Amérique centrale (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 3-Océanie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Dépister la colonialité à l’oeuvre. - Maire, Marc (Semin'ART, 2018)
Avertissement: le texte qui suit a pour objet de rassembler les prolégomènes du workshop à venir. Il n’est pas le fruit d’une recherche strictement personnelle et doit sa teneur en grande partie à une enquête consultative de divers travaux cités avec leurs auteurs en fin de divers travaux cités avec leurs auteurs en fin de billet.
Keywords: 1-Histoire de l'art; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Sud (corpus analysé); 4-Europe (lieu de production du savoir); _Nettoyé

Féminismes et artivisme dans les Amériques, XXe-XXIe siècles - Quiroz, Lissell (Presses universitaires de Rouen, 2021)
"Y la culpa no era mia, ni donde estaba, ni como vestia", chantaient des femmes aux yeux bandés dans différentes villes d'Amérique latine en novembre 2019. Cette performance, créée par le collectif féministe Las Tesis, a fait le tour du monde. Elle montre la force et la vitalité de l'artivisme dans les Amériques. Ce volume porte sur la diversité des théorisations et des mobilisations féministes du continent américain, très dynamiques historiquement et de plus en plus visibles depuis la fin du XXe siècle. Le féminisme des Amériques est pluriel et possède une généalogie propre. Les auteures s'attachent à décliner ses différentes formes : chicano, décolonial, lesbien, queer, entre autres. L'originalité des actions féministes de la région provient de la mobilisation politique de genres artistiques, qu'ils soient musicaux (rap, reggaeton), picturaux ou des arts visuels. Cet artivisme joue ainsi un rôle central dans les formes d'action du continent et ce volume présente leur diversité, leur richesse et leur force créatrice et politique."–Page 4 of cover.
Keywords: 1-Histoire de l'art; 2-Genre et sexualité; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Sud (corpus analysé); 4-Amérique du Sud (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé

La conscience de la Mestiza. Vers une nouvelle conscience - Anzaldúa, Gloria (Les cahiers du CEDREF. Centre d’enseignement, d’études et de recherches pour les études féministes, 2011)
Gloria Anzaldúa a délibérément écrit certains mots et certaines phrases en espagnol-chicano tout au long de cet article, choisissant pour des raisons politiques et esthétiques de produire un texte qui s’adresse à tout le monde mais peut être compris à des niveaux différents. Elle travaille ainsi aussi bien avec l’intelligibilité qu’avec la non-intelligibilité, liées au vécu et au positionnement social de chacun-e, au-delà de la langue elle-même. Pour tenter de respecter ce travail sur l’intelligibilité, nous avons procédé de la manière suivante. Dans certains cas, Anzaldúa a écrit une expression en espagno-chicano puis l’a traduite en anglais, nous avons alors procédé de la même manière. Dans les autres cas, nous avons laissé tel quel dans le corps du texte, ce qu’Anzaldúa a écrit en espagnol-chicano. Cependant, pour placer cette langue sur le même plan d’intelligibilité que l’anglais, pour le lectorat francophone, nous en proposons une traduction, en note. Enfin, nous avons ajouté un certain nombre de notes de contextualisation. Ainsi, les notes en lettres correspondent aux notes originales d’Anzaldúa, tandis que les notes en chiffres correspondent à la traduction de l’espagnol-chicano vers le français et enfin, les notes en i, ii, iii etc, correspondent aux notes des traductrices. Par ailleurs, deux termes sont particulièrement délicats à traduire : « raza » et « mestiza ». Au Mexique, le mot « raza » est polysémique. Au sens strict, il signifie « race », cependant son emploi actuel et courant n’implique aucune connotation raciale, mais plutôt populaire et affective (ma bande, mon quartier, ma famille élargie, les gens avec qui je m’identifie…), ce qui conduirait à le traduire plutôt par « peuple ». Nous avons donc choisi des traductions contextualisées, utilisant « race » pour la pensée de Vasconcelos (prise dans les courants racialistes internationaux des années vingt), et « peuple » pour la pensée d’Anzaldúa elle-même (qui l’utilise dans un sens actuel et populaire). L’ensemble de son œuvre montre amplement le caractère non-essentialiste de sa pensée, ce qui nous conforte dans ce choix. Enfin, le concept de « mestiza » (ou « mestizo ») possède au Mexique des connotations complexes et contradictoires. Il désigne une personne dominant-e par rapport à l’Indien-ne, mais aussi une personne dominé-e par rapport aux gens d’origine espagnole-européenne. Simultanément, il constitue l’archétype (positif) de la nouvelle « race » forgée dans l’ancienne colonie européenne transfigurée par l’indépendance puis la révolution. Pour Anzaldúa, le mot possède toutes ces connotations, mais signifie également la pluralité à l’intérieur de chaque être humain. Nous avons donc choisi de ne pas traduire le concept de « mestiza », qu’elle-même a décidé d’utiliser en espagnol, son article visant précisément à expliquer le sens nouveau qu’elle donne à la « nouvelle métisse ».
Keywords: 1-Cinéma; 1-Histoire de l'art; 1-Jeux vidéo; 1-TV; 2-Genre et sexualité; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Identités diasporiques; _Nettoyé

Épistémologies du Sud : lectures critiques du féminisme décolonial - Femenías, María Luisa (Les cahiers du CEDREF. Centre d’enseignement, d’études et de recherches pour les études féministes, 2019)
Publié en 2000, le livre de Boaventura de Sousa Santos — un sociologue émérite portugais — intitulé Critique de la raison indolente a eu un grand impact au Brésil comme dans le reste de l’Amérique Latine (De Sousa Santos, 2000/2003). Il y développait ce qu’il a appelé « les Épistémologies du Sud » global en opposition aux « Épistémologies du Nord », global également. De Sousa Santos entendait par « Épistémologies du Sud » les connaissances, théories et savoirs qui réfléchissent avec créativit...
Keywords: 1-Cinéma; 1-Histoire de l'art; 1-Jeux vidéo; 1-TV; 2-Genre et sexualité; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Sud (corpus analysé); 5-Autrice; _Nettoyé

Ensayos de crítica feminista en nuestra América - Mendoza, Breny (Editorial Herder, 2019)
El feminismo hegemónico latinoamericano entró en crisis en los años noventa por su creciente contubernio con el Estado liberal, así como por su práctica política carente de teoría. No supo cómo responder a los desaires de la izquierda masculinista y quedó intacto por los nuevos teóricos de la descolonialidad. Su acción y pensamiento no sólo se manifestaron profundamente colonizados por Occidente, sino que no encontraron una voz clara para entrar en diálogo con ciertas corrientes del feminimo latinoamericano que cuestionaron sus postulados de género, raza y heteronormatividad.
Keywords: 1-Cinéma; 1-Histoire de l'art; 1-Jeux vidéo; 1-TV; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique centrale (corpus analysé); 3-Amérique du Sud (corpus analysé); 4-Amérique du Sud (lieu de production du savoir); _Nettoyé

La question de la colonialité du genre - Mendoza, Breny (Les cahiers du CEDREF. Centre d’enseignement, d’études et de recherches pour les études féministes, 2019)
Au sein du tournant décolonial que la théorie féministe latino-américaine a commencé à prendre, un nouveau concept a émergé, qui pourrait constituer un changement de paradigme dans notre compréhension du genre. Il s'agit du concept colonialité du genre, forgé par la philosophe argentine Maria Lugones dans ses deux derniers articles : « Heterosexualism and the Colonial/ Modern Gender System » (2007) et, plus récemment, « Toward a Decolonial Feminism » (2010), article qui n'a pas encore été tra...
Keywords: 1-Cinéma; 1-Histoire de l'art; 1-Jeux vidéo; 1-TV; 2-Genre et sexualité; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Sud (corpus analysé); 4-Amérique du Sud (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé

Manuel Zapata Olivella, le muntu africain et la décolonisation des imaginaires et des épistémologies en Amérique Latine - Akassi, Clément Animan (Matraga - Revista do Programa de Pós-Graduação em Letras da UERJ, 2019)
Ce travail vise à montrer deux choses. La première, c’est de saisir toute l’importance du tournant postcolonial/afro-décolonial dans la construction d’une contre-épistémologie propre au sujet culturel colonisé africain. En d’autres termes, pour le sujet colonisé, cette contre-épistémologie sert à décoloniser les imaginaires, à partir d’un questionnement de la colonialité de l’épistémologie et du savoir donnés pour universels par l’occident. La deuxième chose, c’est que ̶ à quelques mois de la commémoration du centenaire de la naissance du prolixe et polygraphe auteur africain-colombien Manuel Zapata Olivella (1920-2004) ̶ cet article puisse le situer à sa juste place. Celle d’un sujet culturel colonisé africain des Amériques dont l’abondante production culturelle et la pensée, portées et révolutionnées par le concept de Muntu africain, participent de la décolonisation des imaginaires et de l’épistémologie
Keywords: 1-Cinéma; 1-Histoire de l'art; 1-Jeux vidéo; 1-TV; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 3-Afrique (corpus analysé); 3-Amérique du Sud (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 4-Amérique du Sud (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Créateur.rice PANDC; 5-Créateur.rice noir.e; _Nettoyé

Amérique du Nord: arts premiers - Berlo, Janet Catherine; Phillips, Ruth B. (Albin Michel, 2006)
Replaçant chaque oeuvre dans son contexte familial, social, géographique, économique et spirituel, cet album présente l'art des peuples premiers d'Amérique du Nord, des Inuits aux peuples des déserts du sud-ouest des Etats-Unis, des origines à la période contemporaine
Section: 263 p. : ill., cartes ; 24 cm.
Keywords: 1-Histoire de l'art; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Emergence from the Shadow: First Peoples' Photographic Perspectives - Thomas, Jeff (The Cultural Work of Photography in Canada, 2011)
Résumé livre : The Cultural Work of Photography in Canada is an in-depth study on the use of photographic imagery in Canada from the late nineteenth century to the present. This volume of fourteen essays provides a thought-provoking discussion of the role photography has played in representing Canadian identities. In essays that draw on a diversity of photographic forms, from the snapshot and advertising image to works of photographic art, contributors present a variety of critical approaches to photography studies, examining themes ranging from photography's part in the formation of the geographic imaginary to Aboriginal self-identity and notions of citizenship. The volume explores the work of photographs as tools of self and collective expression while rejecting any claim to a definitive, singular t... Source: Publisher
OCLC: 966299857
Keywords: _Nettoyé

Beat Nation: Art, Hip Hop and Aboriginal Culture - Ritter, Kathleen; Willard, Tania (Vancouver Art Gallery, 2012)
Catalgoue d'exposition
Section: 95 pages : illustrations en couleur
Keywords: 1-Histoire de l'art; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Pensée critique latino-américaine : de la philosophie de la libération au tournant décolonial - Hurtado López, Fátima (Cahiers des Amériques latines, 2009)
Cet article est une introduction à la pensée critique latino-américaine, de la philosophie de la libération au tournant décolonial proposé par le groupe de recherche pluridisciplinaire Modernité/Colonialité. Dans un premier temps sont présentées les principales contributions de la philosophie de la libération en tant que pensée critique latino-américaine. Est abordée ensuite la question de la pertinence actuelle des motivations et des inquiétudes initiales de la philosophie de la libération, ainsi que la pertinence de ses thèses et de ses principales catégories. Puis sont présentées les principales critiques adressées à ce courant de pensée en quarante ans d’existence. Enfin est introduit le tournant décolonial du groupe Modernité/Colonialité. L’accent est mis sur la notion de pluriversalité que proposent les penseurs critiques latino-américains présentés dans cet article.
Keywords: 1-Cinéma; 1-Histoire de l'art; 1-Jeux vidéo; 1-TV; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Sud (corpus analysé); 4-Europe (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé

Regards d'acier: portraits par des artistes autochtones. - Kunard, Andrea; Loft, Steve (Musée des beaux-arts du Canada, 2011)
Catalogue d'exposition avec plusieurs textes.
OCLC: 728495725
Keywords: 1-Histoire de l'art; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Manifest Manners: Narratives on Postindian Survivance - Vizenor, Gerald Robert (Univ. of Nebraska Press, 2010)
Combines post-modern theory with the comic wisdom of the tribal trickster to explore the effects of nostalgic simulations of "Indian-ness".
OCLC: 837681052
Keywords: 1-Cinéma; 1-Histoire de l'art; 1-Jeux vidéo; 1-TV; 2-Méthodologie de recherche décoloniale; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Indigena: Perspectives Autochtones Contemporaines - Martin, Lee-Ann; McMaster, Gerald (Musée canadien des civilisations, 1992)
Catlogue d'exposition avec plusieurs textes.
Section: 199 pages : illustrations (some color) ; 28 cm
Keywords: 1-Histoire de l'art; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Inclusive and Exclusive Perceptions of Difference. Native and Euro Based Concepts of Time, History, Change - Doxtator, Deborah (Decentring the Renaissance: Canada and Europe in Multidisciplinary Perspective 1500–1700, 2001)
In 1558, confronted by the differences in the ways Native peoples and Europeans perceived and structured their respective societies, Renais- sance travel writer Andre Thevet asserted that the indigenous popula- tions of North America, unlike Europeans, had neither religion, civility, nor books, and lived like 'beasts without reason' (Thevet [1558] 1878, 134-6). In 1603, writing of the Native groups he encountered, Samuel de Champlain remarked that since each person 'prayed in his heart just as he liked,' they in effect had 'no law among them and do not know what it is to worship God and pray to Him, living as they do like brute beasts' (Champlain 1922-36, 6: 52). In contrast, Native groups, although not always conciliatory, nonetheless sought out ways to incorporate Europeans into existing political and ideological structures, inviting Champlain, Jesuit missionaries, and others to come to live with them and to participate in their way of life (Dickason 1992, 103, 107).A funda- mental element of Rotinonhsyonni1 diplomacy was the political neces- sity to achieve integrations so that, at least ideologically, Europeans and Iroquoians could perceive themselves to be brothers, one and the same people (Jesuit Relations [1610-1791] 1896-1901 [hereafter JR] 27: 253- 61). When Jacques Cartier encountered the Montagnais-Naskapi in 1534, he remarked on their ease of manners in their coming 'freely on board our vessels as if they had been Frenchmen' (Cartier 1924, 76).
Pages: 33-47
Keywords: 1-Cinéma; 1-Histoire de l'art; 1-Jeux vidéo; 1-TV; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; _Nettoyé

Paix, pouvoir et droiture. Un manifeste autochtone - Alfred, Taiaiake (Éditions Hannenorak, 2014)
Paix, pouvoir et droiture : un manifeste autochtone, qui tire sa structure des chants rituels de la cérémonie de condoléances rotinohshonni, appelle toutes les Premières Nations à prêter attention aux messages des ancêtres afin de développer une philosophie visant à contrer l'assimilation. L'essai de Taiaiake Alfred est un véritable plaidoyer en faveur de droits et de l'autodétermination des peuples autochtones. Ce manifeste se veut avant-gardiste proposant des pistes de réflexion inédites ayant significativement participé à améliorer la compréhension des enjeux des Première Nations de l'Amérique du Nord.
Keywords: 1-Cinéma; 1-Histoire de l'art; 1-Jeux vidéo; 1-TV; 2-Méthodologie de recherche décoloniale; 2-Pédagogie décoloniale; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; _Nettoyé

Être un artiste contemporain et être autochtone: Quelques réflexions sur la polémique autour de Jimmie Durham - Uzel, Jean-Philippe (Captures, 2018)
Cet article revient sur la polémique qui a éclaté en juin 2017, lorsque des artistes, des intellectuels et des militants cherokees ont publié une lettre ouverte dénonçant comme frauduleuse l'identité cherokee de l'artiste Jimmie Durham, l'une des figures les plus reconnues de l'art contemporain autochtone. Loin de vouloir trancher un débat aux ramifications complexes, cet article entend plutôt restituer les termes de la querelle et examiner la façon dont cette controverse éclaire la notion d'« autochtonie
Keywords: 1-Histoire de l'art; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Créateur.rice autochtone; _Nettoyé

Perspectives photographiques sur l’autochtonie (1984-2011) - Guignard, Sophie (Captures, 2018)
Cet article s'intéresse aux diverses compréhensions de la notion d'autochtonie qui peuvent être mises au jour par l'étude du travail de photographes autochtones en Amérique du Nord. Pour cela, nous étudions deux brochures d'expositions collectives de photographes autochtones : Contemporary Native American Photography (1984), et Steeling the Gaze. Portraits by Aboriginal Artists (2011)
Keywords: 1-Histoire de l'art; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; 5-Créateur.rice autochtone; _Nettoyé

Installation ou sculpture?: Naufrage d’une œuvre de Carl Beam - Hardy, Dominic (Captures, 2018)
Ce texte, qui trace le parcours d’une œuvre de Carl Beam depuis sa présentation à Peterborough en 1989 jusqu’à son intégration à la collection permanente du Musée des beaux-arts du Canada en 2010, interroge le statut de la première itération d’un projet dont le passage hors du cadre local transforme cet évènement (exposition conçue pour un lieu et temps précis) en archive d’un présent, toujours national, détaché du territoire qui est une de ses conditions d’émergence.
Keywords: 1-Histoire de l'art; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Créateur.rice autochtone; _Nettoyé

Kanata… appropriation ou effacement ? - Nepton Hotte, Caroline (esse arts + opinions, 2019)
Keywords: 2-Approches sociologiques; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; _Nettoyé

L’appropriation culturelle et les peuples autochtones: entre protection du patrimoine et liberté de création. - Nepton-Hotte, Caroline; Jérôme, Laurent; Uzel, Jean-Philippe; Darsigny-Trépanier, Maude (GRIAAC, Groupe de recherche interdisciplinaire sur les affirmations autochtones contemporaines, 2019)
Le colloque « L’appropriation culturelle et les peuples autochtones : entre protection du patrimoine et liberté de création », organisé à l’UQAM en avril 2018, a suscité un dialogue fructueux à propos des multiples dimensions de l’appropriation culturelle. Réunissant des acteurs des milieux des arts et de la culture, du droit, de la politique, du tourisme et de la santé, ce colloque a permis de susciter des avenues de réflexion ainsi que différentes pistes d’action. Ce colloque, organisé par le Groupe de recherche interuniversitaire sur les affirmations autochtones contemporaines (GRIAAC-UQAM) en collaboration avec la Faculté des sciences humaines (FSH), la Société Recherches amérindiennes au Québec (SRAQ) et l’organisme Terres en vues, visait à réunir des experts et des praticiens des cultures et des sociétés autochtones (Premières Nations, Inuits et Métis), mais aussi des spécialistes des questions juridiques liées à la propriété intellectuelle, au droit d’auteur et aux droits collectifs, autour d’une question commune : comment respecter et protéger les traditions, les conceptions, les symboles, les savoirs, les patrimoines culturels matériels et immatériels autochtones, tout en continuant à favoriser la créativité et les échanges entre les cultures? À travers des présentations générales et des tables rondes réalisées sous forme d’ateliers, ce colloque visait non seulement à poser les termes de ces questions complexes, mais également à identifier des pistes concrètes d’actions pour que soient reconnues et respectées l’histoire, les lois et l’épanouissement tant des cultures autochtones que des autres cultures, et en particulier de la culture québécoise.
Section: 67 pages : illustrations (certaines en couleur) ; 28 cm
Keywords: 1-Cinéma; 1-Histoire de l'art; 1-Jeux vidéo; 1-TV; 2-Approches sociologiques; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Postcolonial Territorial Landmarks within Canada’s Multiculturalism: The Myth of Virility. - Pageot, Edith-Anne (Landscapes and Landmarks of Canada: Real, Imagined, (Re)Viewed, 2017)
Résumé livre : The image of the “land” is an ongoing trope in conceptions of Canada—from the national anthem and the flag to the symbols on coins—the land and nature remain linked to the Canadian sense of belonging and to the image of the nation abroad. Linguistic landscapes reflect the multi-faceted identities and cultural richness of the nations. Earlier portrayals of the land focused on unspoiled landscape, depicted in the paintings of the Group of Seven, for example. Contemporary notions of identity, belonging, and citizenship are established, contested, and legitimized within sites and institutions of public culture, heritage, and representation that reflect integration with the land, transforming landscape into landmarks. The Highway of Heroes originating at Canadian Forces Base Trenton in Ontario and Grosse Île and the Irish Memorial National Historic Site in Québec are examples of landmarks that transform landscape into a built environment that endeavours to respect the land while using it as a site to commemorate, celebrate, and promote Canadian identity. Similarly in literature and the arts, the creation of the built environment and the interaction among those who share it is a recurrent theme. This collection includes essays by Canadian and international scholars whose engagement with the theme stems from their disciplinary perspectives as well as from their personal and professional experience—rooted, at least partially, in their own sense of national identity and in their relationship to Canada.
Keywords: 1-Histoire de l'art; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; _Nettoyé

Présences, mémoires individuelles et plurielles comme dispositifs de construction dans le travail des créatrices autochtones - Pageot, Édith-Anne (Espace, 2018)
Keywords: 1-Histoire de l'art; 2-Genre et sexualité; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Figure de l’indiscipline. Domingo Cisneros, un parcours artistique atypique - Pageot, Edith-Anne (RACAR: revue d'art canadienne / Canadian Art Review, 2017)
Between 1974 et 1996, the Canadian artist of Mexican origin Domingo Cisneros was seen as a leading figure in contemporary art in Canada. He played a major role in the process of self-determination that First Nations artists undertook following the infamous 1969 White Paper, the Statement of the Government of Canada on Indian Policy. Cisneros was recognized both in the Native and Quebec francophone contemporary art worlds, and was internationally acclaimed within the conceptual and contextual art milieu gathered around the Polish artist Jan Swidzinski. His contribution has nevertheless been forgotten. Coinciding with his seventy-fifth birthday, this article aims to review, conceptually frame, and contextualize Cisneros’s role and impact on the Canadian art scene. It argues that his interdisciplinarity, or “indiscipline,” was instrumental in building connexions and bridges between heterogeneous values, cultural protocols, and epistemological principles.
Keywords: 1-Histoire de l'art; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; 5-Créateur.rice autochtone; _Nettoyé

L’art autochtone à l’aune du discours critique dans les revues spécialisées en arts visuels au Canada. Les cas de Sakah à n et de Beat Nation - Pageot, Edith-Anne (Muséologies, 2018)
This article offers a qualitative and quantitive analysis of the critical reception of two exhibitions, Sakahàn:International Indigenous Art (National Gallery of Canada, Ottawa 2013) and Beat Nation: Art, Hip-Hop and Aboriginial Culture (organised and circulated by the Vancouver Art Gallery, 2013-2014). The study treats articles which appeared between 2012 and 2015 in English and French visual-arts publications. The comparative analysis intends to highlight general trends, in order to identify challenges that contemporary Indigenous arts pose for art criticism. A review of the texts shows that all commentators, whether francophone or anglophone, indigenous or non-Indigenous, have welcomed these two exhibitions warmly. The discrepancy between the number of essays in French and those in English reflects the demographic weight of these two linguistic communities and the geographic distribution of First Nations in Canada. This will qualify, without denying, the hypothesis of Quebec's tardiness on the indigenous question. The authors largely recognize the necessity of initiating indigenization of the museum and emphasize the movement to internationalize contemporary indigenous art. Yet many commentators, particulary Indigenous people, dispute the efficacity of the concept of "strategic essentialism" put forward by the commissioners of the Sakahàn catalog. Despite both a real interest in these two major exhibitions and the quality of the commentary, in the end, for events of such a scale few texts have been published on the subject. The criteria for appreciation rooted in the institutional sociology of art endeavour to fully take into account the challenges posed by certain central aspects of the approach of several Indigenous creators, such as the intangible dimensions of their civic engagement, the dissolution of particular outside venues and the sisterhood of certain projects.
Keywords: 1-Histoire de l'art; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude de la réception; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; 5-Créateur.rice autochtone; _Nettoyé

Decolonize Me - Igloliorte, Heather; Loft, Steve; Croft, Brenda L. (Ottawa Art Gallery = Galerie d'art d'Ottawa, 2012)
Catalogue d'exposition avec des textes de Loft, Igloliorte et Croft. Galerie d'art d'Ottawa.
Section: 158 p. : ill. en coul. ; 24 cm.
Keywords: 1-Histoire de l'art; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 4-Océanie (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

‘‘When Keeping it Real Goes Wrong’’: Resident Evil 5, Racial Representation, and Gamers - Brock, André (Games and Culture, 2011)
Videogames’ ability to depict cultural iconographies and characters have occasionally led to accusations of insensitivity. This article examines gamers’ reactions to a developer’s use of Africans as enemies in a survival horror videogame, Resident Evil 5. Their reactions offer insight into how videogames represent Whiteness and White privilege within the social structure of ‘‘play.’’ Omi and Winant’s (1994) racial formation theory notes that race is formed through cultural representations of human bodies organized in social structures. Accordingly, depictions of race in electronic spaces rely upon media imagery and social interactions. Videogames construct exotic fantasy worlds and peoples as places for White male protagonists to conquer, explore, exploit, and solve. Like their precursors in science fiction, fantasy, and horror, videogame narratives, activities, and players often draw from Western values of White masculinity, White privilege as bounded by conceptions of ‘‘other,’’ and relationships organized by coercion and domination.
Keywords: 1-Jeux vidéo; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; _Nettoyé

SakKijâjuk: Art and Craft from Nunatsiavut - Igloliorte, Heather; Broomfield, Jenna Joyce; Chaulk, Aimee; Lalonde, Christine; Pottle, Barry (Goose Lane Editions, 2017)
Nunatsiavut, the Inuit region of Canada that achieved self-government in 2005, produces art that is distinct within the world of Canadian and circumpolar Inuit art. The world's most southerly population of Inuit, the coastal people of Nunatsiavut have always lived both above and below the tree line, and Inuit artists and craftspeople from "Nunatsiavut have had access to a diverse range of Arctic and Subarctic flora and fauna, from which they have produced a stunningly diverse range of work. Artists from the territory have traditionally used stone and woods for carving; fur, hide, and sealskin for wearable art; and saltwater seagrass for basketry, as well as wool, metal, cloth, beads, and paper. In recent decades, they have produced work in a variety of contemporary art media, including painting, drawing, printmaking, photography, video, and ceramics, while also working with traditional materials in new and unexpected ways. SakKijâjuk: Art and Craft from Nunatsiavut is the first major publication on the art of the Labrador Inuit. Designed to accompany a major touring exhibition organized by The Rooms Provincial Art Gallery of St. John's, the book will feature more than 80 reproductions of work by 45 different artists, profiles of the featured artists, and a major essay on the art of Nunatsiavut by Heather Igloliorte. SakKijâjuk - "to be visible" in the Nunatsiavut dialect of Inuktitut - provides an opportunity for readers, collectors, art historians, and art aficionados from the South and the North will come into intimate contact with the distinctive, innovative, and always breathtaking work of the contemporary Inuit artists and craftspeople of Nunatsiavut
Section: 188 pages : illustrations (principalement en couleur) ; 32 cm
Keywords: 1-Histoire de l'art; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Peau rouge, masques blancs: contre la politique coloniale de la reconnaissance - Coulthard, Glen Sean (Lux Editeur, 2018)
"Le paradigme hégélien de la reconnaissance, admirablement critiqué par Frantz Fanon dans l'œuvre phare à laquelle ce livre rend hommage, est aujourd'hui évoqué, sous sa forme libérale, dans les débats entourant l'autodétermination des peuples colonisés, notamment les peuples autochtones d'Amérique du Nord. Politologue et militant, membre de la Nation dénée du Nord-Ouest du Canada, l'auteur reprend ici la critique fanonienne et démontre en quoi cette reconnaissance ne fait que consolider la domination coloniale. Cet ouvrage de théorie politique engagée appelle à rebâtir et redéployer les pratiques culturelles des peuples colonisés sur la base de l'autoreconnaissance, seule voie vers une réelle décolonisation. Penseur marxiste, Coulthard sait que le marxisme ne peut s'appliquer tel quel à la lutte des Autochtones, mais il en souligne la contribution potentielle et signe ici un véritable traité de combat décolonial et anticapitaliste."
Section: 1 v. (359 p.) ; 19 cm
Keywords: 1-Cinéma; 1-Histoire de l'art; 1-Jeux vidéo; 1-TV; 2-Méthodologie de recherche décoloniale; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; _Nettoyé

Comprendre les arts autochtones au Canada aujourd'hui: un examen de las connaissance et de la documentation - Trépanier, France; Creighton-Kelly, Chris (Conseil des arts du Canada, 2013)
En 2009, le Conseil des arts du Canada a retenu les services de France Trépanier et Chris Creighton-Kelly pour mener l’étude fondée sur les sujets identifiés dans les consultations auprès de la communauté dans le cadre de son Initiative de recherche sur les arts autochtones (IRAA).
OCLC: 863594873
Keywords: _Nettoyé

Possessions: Indigenous Art / Colonial Culture - Thomas, Nicholas (Thames and Hudson, 1999)
Tribal art has greatly inspired much 20th-century Western art. But is this a cross-cultural discovery to be celebrated, or another example of Western colonial appropriation? This work, focusing on countries such as Australia and New Zealand, argues that both views are too simplistic
Section: 304 p. : illustrations ; 24 cm
Keywords: 1-Histoire de l'art; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Océanie (corpus analysé); 4-Océanie (lieu de production du savoir); 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Pour une autohistoire amerindienne: essai sur les fondements d'une morale sociale - Sioui, Georges E (Presses de l'Université Laval, 1999)
Sioui has produced a work not only of metahistory but of moral reflections. He contrasts Euroamerican ethnocentrism and feelings of racial superiority with the Amerindian belief in the "Great Circle of Life" and shows that human beings must establish intellectual and emotional connections with the entire living world if they hope to achieve abundance, quality, and peace for all. Sioui is proud to be a Huron and an Amerindian and is fully aware of the injustices that the aboriginal people of North America have suffered - and continue to suffer - at the hands of Euroamericans. He is convinced that the greatness of Amerindians does not lie only in the past but that Native peoples will play an even more important role in the future by providing ideas essential to creating aviable way of life for North America and the world. While this is a polemical work, Sioui never descends to recrimination or vituperative condemnation, even when that might seem justified. Instead, he has given us a polemic that is written at the level of philosophy.
OCLC: 1132447000
Keywords: 1-Cinéma; 1-Histoire de l'art; 1-Jeux vidéo; 1-TV; 2-Histoire/Historiographie critique; 2-Méthodologie de recherche décoloniale; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; _Nettoyé

Zacharie Vincent: une autohistoire artistique - Vigneault, Louise (Éditions Hannenorak, 2016)
"Qui était Zacharie Vincent, aussi connu, à l'époque, sous le nom de Tehariolin? Peu de gens le savent. Il s'agit pourtant d'une figure incontournable, considérée comme le premier peintre autochtone moderne. Le présent ouvrage, signé par l'historienne de l'art Louise Vigneault, lève donc le voile sur ce peintre et chef de guerre wendat, longtemps tombé dans l'oubli, qui a considérablement marqué le 19e siècle. Zacharie Vincent (1815-1886) a suscité la fascination, avec ses allures d'artiste bohème, sa dégaine de clochard mêlée à ses ornements d'apparat, la singularité de ses autoportraits. La légende entourant celui que l'on appelait le " dernier des Hurons " a attiré les regards sur la petite communauté de la Jeune-Lorette (aujourd'hui Wendake), pour ensuite révéler la fierté et la résilience du peuple wendat. Des peintres canadiens, tels Antoine Plamondon et Eugène Hamel, ont réalisé des portraits de Vincent, puis des photographes comme Louis-Prudent Vallée ont immortalisé son image. Zacharie Vincent : une autohistoire artistique nous plonge au cour de la vie et de l'ouvre d'un artiste énigmatique qui a laissé en héritage des témoignages essentiels sur sa nation, en équilibre entre la tradition et la modernité."– Quatrième de couverture
Section: 273 pages : illustrations (principalement en couleur) ; 26 cm
Keywords: 1-Histoire de l'art; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 2-Étude de la réception; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; 5-Créateur.rice autochtone; _Nettoyé

Manifeste pour l'avancement des arts, des artistes et des organisations artistiques autochtones au Québec. Tsi Non :We Tewèn :Teron - Là où est notre maison. État des lieux sur la situation des arts autochtones au Québec, Tiöhtià'ke/Montréal (Coeur des sciences de l'UQAM, 2017)
Keywords: 1-Histoire de l'art; 2-Approches sociologiques; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Créateur.rice autochtone; _Nettoyé

D'horizons et d'estuaires: entre mémoires et créations autochtones - Larivée, Camille; Eshrāghi, Léuli (Éditions Somme toute, 2020)
"D'horizons et d'estuaires. Entre mémoires et créations autochtones est une collection d'essais réunissant les voix de 16 artistes, commissaires, historien·ne·s de l'art et travailleur·se·s culturel·le·s autochtones, tant francophones qu'anglophones, œuvrant dans les territoires que l'on nomme Québec. Faisant suite à des expositions, des performances, des résidences d'artistes et des discussions mises en place lors du Projet Tiohtià:ke (2017-2019) du Collectif des commissaires autochtones, ces textes honorent les relations et les affinités qui sont au cœur de ces pratiques en arts visuels. Quelle place occupe actuellement les créations visuelles autochtones dans la société québécoise? Comment les créateur·trice·s imaginent-iels le futur de leurs expressions culturelles? Par la diversité des points de vue et les enjeux soulevés par ces écrits, ce livre pose des questions cruciales sur l'avenir des arts autochtones et ouvre la porte à des dialogues longtemps attendus au Québec qui, nous l'espérons, permettront de créer de réels changements positifs. Il est maintenant temps de plonger dans ces imaginaires collectifs éblouissants et de nager dans les eaux ondulantes de ces mémoires résilientes. Le texte est accompagné de 28 photographies d'œuvres d'artistes autochtones."– Fourni par l'éditeur
Section: 148 pages : illustrations en couleur ; 21 cm
Keywords: 1-Histoire de l'art; 2-Approches sociologiques; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Talking Back to the West: Contemporary First Nations Artists and Strategies of Counter-appropriation - Froschauer, Christina Marie (Concordia University, 2011)
Over a twenty-year period, renowned artists such as Edward Poitras, Robert Houle, Jim Logan, Kent Monkman, among others, appropriate renowned colonial landscape paintings and art historical canonical works, and then alter them to include First Nations narratives, as methods of critiquing the exclusionary nature of grand colonial narratives and their associated historical, art historical and, by extension, anthropological discourses. Using counter-appropriation as an artistic strategy, they critique: the West's disregard for First Nations histories in North America; Art History's past failures to classify their art objects as Fine Art; and contemporary cultural constructions of "Indianness" originating from colonial history and ideologies about the "Vanishing Race." With their works, the artists offer their viewers insight into First Nations histories and stories, thereby enriching the multiple narratives and pluralist discourses existent in North America.
OCLC: 896966575
Keywords: 1-Histoire de l'art; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; 5-Créateur.rice autochtone; _Nettoyé

Remix New Modernities in a Post-Indian World - Baker, Joe; McMaster, Gerald (Heard Museum/Natural Museum of American Indian, 2007)
Published in conjunction with the exhibition of the same name, on view at the Heard Museum in Phoenix, Arizona, from October 6, 2007, to April 27, 2008, and at the George Gustav Heye Center, National Museum of the American Indian, in New York, New York, from May 26 through September 30, 2008
OCLC: 845281405
Keywords: 1-Histoire de l'art; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Jouer à l'Indien est une chose, être un Amérindien en est une autre - Sioui Durand, Guy (Recherches amérindiennes au Québec, 2003)
Ainsi en fut-il de la restitution en août 1999 par le Royal Ontario Museum des ossements des quelque cinq cents ancêtres wendats, illégalement extirpés en 1947 de la fosse commune d'Ossosané par les anthropologues du Musée, ceux-ci ayant retracé le site du dernier grand festin collectif en Huronie en 1636 (alors décrit par le père Brébeuf), ce qui a donné lieu à la résurgence d'une nouvelle grande fête des Morts, célébrée de de manière privée par les quatre nations de la diaspora wendatte, sous les offices d'un chamane iroquois traditionnaliste parlant encore le huron ; - la réactivation de ces types de créations comme manifestation authentiquement artistique autochtone et surtout comme mécanismes culturels de transmission aux jeunes générations. Bien que l'habitation nomade de la tente, sous la forme de tipi, fût celle qui a été la plus diffusée médiatiquement (entendre le cinéma hollywoodien et les séries de télévision des cow-boys et des Indiens des années cinquante et soixante pour identifier ceux qu'on appelle, depuis l'erreur d'identification du continent par Christophe Colomb, les « Indiens »), sa stylisation par une découpe moderne se démarquait des nombreuses reproductions kitsch. La performance An Indian Act Shooting the Indian Act (1997) de l'artiste Lawrence Paul Xuweluptun, dont rendait compte une projection vidéo accompagnant son exposition « Coulour Zone », en avril 2000, au Centre Saydie Bronfman de Montréal, et l'installation multimédia Resig/Nation (1999) de l'artiste saulteux et métis Edward Poitras au Lieu, Centre en art actuel, à Québec à l'hiver 2000, étaient radicales
Keywords: 1-Histoire de l'art; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Créateur.rice autochtone; _Nettoyé

La voix du territoire: représentations territoriales plurielles dans l'œuvre d'Eruoma Awashish - Ruestchmann, Clara (Université de Montréal, 2019)
Le territoire (Nitaskinan), dans la pensée autochtone, est une notion centrale et pluridimensionnelle ; elle induit un territoire historique, géographique et politique revendiqué ainsi qu'un territoire cosmologique inscrit au cœur de rites et de croyances ancestrales. C'est l'articulation et l'harmonisation de ce territoire pluriforme que l'artiste atikamekw Eruoma Awahish entreprend de présenter dans son œuvre. Ce mémoire adresse la manière dont l'artiste représente le territoire, à la fois dans une volonté d'ancrage traditionnel et de réactualisation contemporaine dans une perspective diachronique. L'artiste déploie une esthétique franche et colorée, elle s'emploie à renverser les codes du colonialisme et développe des stratégies afin de contribuer aux revendications et à l'affirmation territoriale des Premières Nations. Par le biais d'une production artistique politisée, Eruoma Awashish applique un prisme décolonisateur ; elle réinvestit une histoire coloniale et offre aux symboles et aux narrations autochtones une place centrale et active. Ce mémoire met subséquemment l'emphase sur la capacité des nations autochtones à s'adapter, à s'auto-définir et à s'auto-représenter. Les artistes se font les témoins et les vecteurs d'une affirmation et d'une recherche de souveraineté qui, chez Awashish, est à la fois visuelle, culturelle et territoriale. Déployant une approche interdisciplinaire, à l'image de la production de l'artiste, ce mémoire prend pour appui les écrits de penseur.se.s autochtones afin de présenter la démarche et la production d'une artiste ancrée dans un contexte contemporain complexe soumis à de nombreuses revendications politiques, culturelles et territoriales. Si les œuvres d'Awashish transmettent et diffusent ces revendications, elles sont toutefois, avant tout, le reflet de croyances et d'une histoire territoriale atikamekw.
Keywords: 1-Histoire de l'art; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Du grenier à la forêt : le musée de l’immatériel - Paré, Sylvie (Recherches amérindiennes au Québec, 2003)
Keywords: 1-Histoire de l'art; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; _Nettoyé

Le jardin en ville, le cas des Jardins éphémères à Québec. Stratégie marchande et critique postcoloniale - Pageot, Édith-Anne (Globe, 2012)
Cet article se penche sur la portée philosophique du projet intitulé Jardins éphémères, un ensemble de onze jardins temporaires réalisés dans le cadre des activités visant à célébrer le 400ₑ anniversaire de la fondation de la ville de Québec au cours de l’été 2008. L’organisation, les intentions et les principaux thèmes sous-jacents aux différents projets sont présentés dans leur ensemble. Le jardin intitulé « Wampum 400 », créé par deux artistes autochtones, Domingo Cisneros et Sonia Robertson Piekuakamilnu, fait l’objet d’un commentaire plus long. L’analyse montre que le projet Jardins éphémères dans son ensemble incarnait les principaux enjeux actuels du jardin en ville. Certains aspects reconduisaient la vision idéelle du jardin, d’autres satisfaisaient la logique touristique de l’événement et d’autres, enfin, développaient une position critique qui concerne la réappropriation d’un espace à usage collectif et, du coup, interrogeaient les fondements épistémologiques et ontologiques du « jardin ».
Keywords: 1-Histoire de l'art; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique centrale (corpus analysé); 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; 5-Créateur.rice PANDC; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

L'art dans tous ses territoires au jardin des Premières-Nations: regards sur l'immatériel dans les œuvres du Concours d'œuvre murale éphémère - Lauzon Chiasson, Gabrielle (Université de Montréal, 2019)
De 2003 à 2017, le jardin des Premières-Nations du Jardin botanique de Montréal a été le lieu d'exposition de 12 œuvres d'artistes autochtones dans le cadre du Concours d'œuvre murale éphémère lancé par Sylvie Paré. Ce mémoire rassemble l'ensemble de cette exposition afin d'en relever le discours général et les liens que les œuvres entretiennent entre elles, avec le Jardin et avec les territoires
Keywords: 1-Histoire de l'art; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

La "monnaie des Sauvages": les colliers de wampum d'hier à aujourd'hui - Lainey, Jonathan C. (Septentrion, 2004)
« Tantôt présents ou documents figurés, tantôt considérés comme de la monnaie, les wampums sont des colliers de perles fabriquées de coquillages marins qui étaient utilisés par les Indiens du Nord-Est de l'Amérique et les Européens. Si des milliers de wampums sont cités dans les archives coloniales, peu d'entre eux sont parvenus jusqu'à nous et la tradition de leur échange a depuis longtemps cessé d'être pratiquée. Les wampums du Musée de la civilisation de Québec ont été acquis à la fin du XIXe siècle dans un contexte particulier où collectionneurs et numismates s'arrachaient les objets amérindiens et où ceux-ci, pour diverses raisons, acceptaient de s'en départir. Cette collection n'avait jamais été étudiée, ni par les historiens, ni par les ethnologues ou par les muséologues. Par un raisonnement critique, en avançant toujours avec prudence et sans jamais céder à la simplification, Jonathan C. Lainey soulève les difficultés et les problèmes reliés à leur étude et à leur interprétation. Il reconstitue méticuleusement les différentes étapes de la vie des objets, leur muséification et le sens qu'on peut leur donner aujourd'hui. Plus qu'une simple étude sur les wampums, cet ouvrage a le mérite de porter un regard sur certaines réalités historiques relatives à la culture matérielle d'un groupe amérindien de la région de Québec, les Hurons de Lorette. Ce sont le rapport à l'Autre, les processus d'appropriation et les transferts culturels qui sont abordés par l'étude de la transformation de l'usage des wampums, devenus aujourd'hui objets de musée. Reposant sur une ethnographie et une iconographie riches et détaillées, ce livre constitue une contribution importante aux études ethnohistoriques et aux études amérindiennes de l'Amérique du Nord-Est. »– Résumé de l'éditeur.
Section: xii, 283 pages : illustrations, portraits ; 23 cm
Keywords: 1-Histoire de l'art; 2-Histoire/Historiographie critique; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; _Nettoyé

La crise d'Oka en récits: territoire, cinéma et littérature - St-Amand, Isabelle (Presses de l'Université Laval, 2015)
La crise d'Oka marque un véritable moment de rupture dans lesrelatlons entre les premiers peuples et les colonies de peuplement. Dans les suites immédiates de l’échec de l’accord du lac Meech, ce long siège armé de 78 jours rend visible une présence autochtone que les sociétés québécoise et canadienne avaient imaginée évanouie. Àl’inverse, l’opposition à l’empiétement mis en œuvre à Kanehsatàke età Kahnawàke réactive une longue histolre de résistance au projet colonial d'appropriation des terres et d'effacement des peuples autochtones. Ce livre envisage la crise d'Oka, ou la résistance à Kanehsatàke, comme un espace de focalisatlon où se donne à voir larelation globale entre les peuples. Qu'est-ce que l'événement fait surgir, transforme et crée, dans la scénographie du siège, mais aussi dans les films documentaires et les récits littéraires, autochtones et allochtones? À l'heure où une nouvelle génération revient sur cette crise politique aux enjeux non résolus, ce livre ouvre un espace où entrent en relation et s'affrontent différents intérêts, connaissances et expressions relatifs à ce conflit territorial. Il engage une réflexion épistémologique essentielle à un processus de décolonisation aussi impératif qu'exigeant.
Section: xiv, 282 pages ; 23 cm.
Keywords: 1-Cinéma; 1-Histoire de l'art; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Nadia Myre, en[counter]s - Tougas, Colette; Couëlle, Marcia; Myre, Nadia (Éditions Art mûr, 2011)
Nadia Myre is a multidisciplinary artist whose work explores themes of language, culture, and memory, and who sources the culture of her Algonquin ancestors as a way of confronting contemporary realities. This monograph provides a comprehensive first look at this Montreal-based artist's remarkable career
Section: 93 pages : illustrations (principalement en couleur) ; 27 cm
Keywords: 1-Histoire de l'art; 2-Genre et sexualité; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Encounters on Contested Lands: Indigenous Performances of Sovereignty and Nationhood in Québec - Burelle, Julie (Northwestern University Press, 2019)
Encounters on Contested Lands analyzes films, plays, visual art, and protest marches by Indigenous artists in Québec, Canada, to explore the performance of cultural identity, sovereignty, and nationhood in Québec's independence movement
Section: xi, 215 pages : illustrations ; 23 cm.
Keywords: 1-Cinéma; 1-Histoire de l'art; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Sites of Aboriginal Difference: A Perspective on Installation Art in Canada - Collins, Curtis J (2002)
"This dissertation traces the presence of installation-based practices among artists of Aboriginal ancestry via selected exhibitions across Canada. It begins with a methodological perspective on Canadian art history, federal law, and human science, as a means of establishing a contextual backdrop for the art under consideration. The rise of an Indian empowerment movement during the twentieth century is then shown to take on an international voice which had cultural ramifications at the 1967 Canadian International and Universal Exhibition. Nascent signs of a multi-mediatic aesthetic are distinguished in selected works in Canadian Indian Art '74, as well as through Native-run visual arts programs. First Nations art history is charted via new Canadian art narratives starting in the early 1970s, followed by the development of spatial productions and hybrid discourses in New Work By a New Generation in 1982, and Stardusters in 1986. The final chapter opens with a history of installation art since the Second World War, as related to the pronounced presence of multi-mediactic works in Beyond History in 1989. Post-colonial and postmodern theories are deployed to conclusively situate both the artistic and political concerns featured throughout this study, and lead into the analysis of selected installations at Indigena: Contemporary Native Perspectives and Land, Spirit, Power: First Nations at the National Gallery of Canada. These 1992 shows in the national capital region ultimately confirm the maturation of a particular socio-political aesthetic that tested issues of Canadian identity, while signifying Aboriginal sites of difference."–
OCLC: 898194140
Keywords: 1-Histoire de l'art; 2-Histoire/Historiographie critique; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Créateur.rice autochtone; _Nettoyé

Entre-deux mondes: métissage, identité et histoire sur les traces de Sonia Robertson, Sylvie Paré et Rebecca Belmore, ou, Les parcours artistiques de trois femmes artistes autochtones, entre la mémoire et l'audace - Charce, Chloë (Université du Québec à Montréal, 2008)
Ce mémoire est globalement axé sur la légitimité de la notion d'identité dans les contextes postcolonial et postmoderne. Plus précisément, il porte sur le concept de métissage dans l'art actuel à l'heure de la mondialisation culturelle, lieu propice à un renouvellement de l'identité et de l'imaginaire pour les communautés des Premières Nations d'Amérique du Nord. Il est divisé en deux parties. Les deux premiers chapitres énoncent une perspective socio-ethnohistorique autour des notions d'identité et de métissage, alors que le troisième chapitre expose un point de vue analytique à partir d'un corpus d'oeuvres de trois femmes artistes autochtones du Québec et de l'Ontario s'exécutant sur la scène artistique contemporaine, soit Sonia Robertson, Sylvie Paré et Rebecca Belmore. Plus spécifiquement, le premier chapitre fait état des connaissances et des discours sur les définitions même d'identité et de métissage dans les contextes colonial / postcolonial et moderne / postmoderne. Par extension, je pose cette question concernant l'hybridité culturelle: s'agit-il d'un principe d'homogénéisation et d'essentialisation des cultures ou d'un facteur garant d'hétérogénéité, favorable au mélange et aux échanges interculturels ? Le deuxième chapitre, quant à lui, énonce les contextes de dépossession territoriale et d'exiguïté culturelle dans lesquels ont été contraints les peuples des Premières Nations depuis l'époque coloniale. Il fait aussi mention des métissages artistiques (post)postmodernes, qui contribuent à un renouveau de l'imaginaire amérindien. Dans un esprit à la fois de contestation face à l'image folklorisée de l'« Indien » et de transmission des valeurs traditionnelles, les artistes autochtones font place à la réappropriation culturelle. Enfin, le troisième chapitre souligne les parcours identitaires de Sonia Robertson (Ilnue), Sylvie Paré (métisse huronne-wendat) et Rebecca Belmore (Anishinabekwe). À titre de comparaison, j'analyse un corpus d'installations et de performances sous le thème de la mémoire et de l'identité en lien avec les concepts élaborés dans les chapitres précédents. Le choix d'examiner le travail de trois femmes artistes provenant de communautés différentes permet de rendre compte de réflexions personnelles de la part de femmes autochtones face à la culture dominante et par rapport à leur culture d'origine. Ce choix vise par ailleurs à circonscrire, au sein même de leur production, l'importance de la tradition en fonction de leur affirmation identitaire. Je souhaite ainsi étudier comment ces propositions se positionnent dans un contexte de déterritorialisation culturelle en fonction d'une réalité post(néo)colonialiste, corrélative d'un entre-deux mondes. Pour conclure, je reviens sur les questions d'identité, de mémoire et de territoire en soulignant l'importance idéologique du combat identitaire des communautés autochtones, qui vise la mise en échec des préjugés et des constructions mythiques persistantes entre le « Blanc » et l' « Indien ». Je mesure en ce sens l'impact que pourrait avoir la pensée universelle amérindienne sur nos sociétés hypermodernes en crise et en quête de valeurs.
OCLC: 757064976
Keywords: 1-Histoire de l'art; 2-Genre et sexualité; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Zacharie Vincent et ses héritiers - Vigneault, Louise (Inter, 2016)
OCLC: 6018624696
Keywords: 1-Histoire de l'art; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; 5-Créateur.rice autochtone; _Nettoyé

Pour en finir avec la spiritualité: l’esprit du corps dans les cosmologies autochtones du Québec - Laugrand, Frédéric (Les autochtones et le Québec : des premiers contacts au Plan Nord, 2013)
Depuis la « découverte de l’Amérique », les cosmologies amérindiennes et inuit n’ont cessé de nourrir l’imaginaire et les fantasmes de l’Occident. Les chroniqueurs missionnaires ont introduit un paradoxe qui persiste de nos jours, les Amérindiens et les Inuit étant souvent décrits comme des êtres religieux mais sans véritable religion (Désy, 1988 ; Gélinas et Teasdale, 2005). La notion de spiritualité est une manière commode de reproduire ce point de vue. D’une part, elle permet de regrouper ...
OCLC: 7316507793
Keywords: 1-Cinéma; 1-Histoire de l'art; 1-Jeux vidéo; 1-TV; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); _Nettoyé

Action-création: l’art de performance amérindien au Québec - Beaupré, Jonathan Lamy (Itinéraires, 2015)
Native artists of Quebec working in performance art set up actions that are similar to contemporary forms of rituals. These works have sometimes a poetic or “shamanic” character, are sometimes disturbing, especially through the critique of the clichés about First Nations, or mix those two components. They committed the body of the artist and the audience, while making the Native American cultural expression a both artistic and identity performance
Keywords: 1-Histoire de l'art; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Créateur.rice autochtone; _Nettoyé

Du stéréotype à la performance: les détournements des représentations conventionnelles des Premières Nations dans les pratiques performatives - Lamy Beaupré, Jonathan (Université du Québec à Montréal, 2012)
Cette thèse aborde des pratiques performatives contemporaines qui détournent les représentations conventionnelles des Premières Nations d'Amérique du Nord, pour dénoncer ou déjouer les clichés qui leur sont associés, pour exprimer ou évoquer l'amérindianité de manière critique et créative, et pour mettre en place une représentation personnelle et non conventionnelle du sujet amérindien. Les œuvres ici étudiées ont été réalisées dans les trente dernières années et sont issues principalement de l'art de performance (performance art) mais aussi des arts visuels et de la poésie, parfois combinés sous un mode interdisciplinaire. Ce corpus réunit, à la manière d'un commissariat d'exposition, des œuvres choisies parmi le travail de douze créateurs principalement (mais pas exclusivement) amérindiens : KC Adams, Lori Blondeau, Yves Boisvert, Jimmie Durham, Marvin Francis, Coco Fusco, Guillermo Gomez-Pena, Edgar Heap of Birds, Terrance Houle, James Luna, Kent Monkman et Josée Yvon. La diversité de leurs pratiques respectives permet de dresser un éventail varié des différentes possibilités de détournement des stéréotypes liés aux Premières Nations. La réflexion menée avec ces œuvres se situe dans un croisement entre les théories de la performance (performance studies), les études culturelles (cultural studies) et l'étude des Premières Nations (native studies). Elle est également nourrie par des travaux issus de la sémiologie, de l'histoire de l'art, des études littéraires et de l'anthropologie. Cette recherche interdisciplinaire aborde dans un premier temps (chapitre 1) la construction symbolique de l'amérindianité, qui se trouve élargie et défigée par les pratiques performatives abordées dans cette thèse. Trois œuvres de performance sont ensuite analysées de manière détaillée : The Artifact Piece (1987) de James Luna (chapitre 2), Two Undiscovered Amerindians (1992-1994) de Coco Fusco et Guillermo Gomez-Pena (chapitre 3) et Putting the Wild back to the West (2004-2010) de Lori Blondeau et Adrian Stimson (chapitre 4). Le chapitre 5 étudie quant à lui une sélection d'œuvres artistiques et littéraires, qui possèdent une forte dimension performative, parmi le travail des autres artistes et écrivains mentionnés plus tôt. L'analyse de ces pratiques performatives se montre particulièrement attentive à la tension entre stéréotype et subjectivité, de même qu'entre violence et ironie. Elle vise à démontrer qu'il est possible, en détournant les signes qui évoquent les Premières Nations de manière conventionnelle et reconnaissable, d'exprimer autrement l'amérindianité. Ces détournements affectent la perception des Premières Nations chez le spectateur et permettent de disconvenir des idées reçues à leur sujet. Ils mettent également en œuvre une amérindianité performative qui s'incarne par une attitude ironique, inscrivant l'expression identitaire et culturelle dans une dynamique qui remet en mouvement la représentation et la signification.
OCLC: 829061822
Keywords: _Nettoyé

Jeff Thomas. Droits de cité - Sabet, Aseman (Espace, 2014)
Keywords: 1-Histoire de l'art; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Monuments, Movements, and the Photography of Jeff Thomas. Discussion between Mikinaak Migwans (Curator of Indigenous Art, Art Museaum) and Maria Hupfield, with Syrus Marcus Ware - Thomas, Jeff
Interview vidéo et écrite.
Keywords: 1-Histoire de l'art; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Repenser le temps et l'espace, du wampum au selfie - Vigneault, Louise (RACAR: revue d'art canadienne / Canadian Art Review, 2017)
This article considers the way certain Indigenous artists are reviving conceptions of territory and history that are anchored in secular epistemologies and the construction of knowledge. Such conceptions provide a way for these artists to respond to colonial appropriation, reactivate interrupted dialogues, engender new forms of territorialization, and create places of commemoration and memory preservation. Similar to the historiographical deconstruction performed by thinkers and activists such as Vine Deloria Jr. and Taiaiake Alfred, these artists’ works offer a model of autonomy and environmental balance. While some are reviving mnemonic practices, such as the making of wampum, which traditionally preserve memories of alliances and conflicts, others have embraced Internet and selfie technologies as a means of creating new spaces for speech and recognition
Keywords: 1-Histoire de l'art; 2-Histoire/Historiographie critique; 2-Humanités numériques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Mises en récit 2.0 de l'activisme autochtone. The Indigenous Archival Photo Project et What Brings Us Here - Pinto Ferretti, Alexia (L'agir en condition hyperconnectée. Art et images à l'oeuvre., 2020)
La question de la mémoire en condition hyperconnectée s’articule également dans le potentiel des réseaux sociaux pour la mise en visibilité de différents mouvements activistes autochtones au Canada. À travers deux études de cas, le projet The Indigenous Archival Photo Project par l’écrivain Paul Seesequasis (Cri des plaines) et la page Instagram What Brings Us Here mettant en vedette les groupes d’activistes à Winnipeg The Bear Clan et Drag the Red, ce chapitre réfléchit à la manière dont les créateur.rice.s autochtones utilisent les réseaux sociaux comme des vecteurs d’agentivité narrative témoignant de différents enjeux touchant les communautés. Ces projets doivent être considérés comme des opérateurs de changements, car ils participent à la valorisation des voix autochtones et à l’instauration de divers réseaux de solidarité. Par différentes stratégies conversationnelles en ligne, ces projets renouent ainsi avec le communautarisme propre aux médiums de communication traditionnels autochtones où le dialogue est primordial.
Keywords: 1-Histoire de l'art; 2-Humanités numériques; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Rediscovered Self : Indigenous Identity and Cultural Justice. - Niezen, Ronald (McGill-Queen's University Press, 2014)
In a series of thematically linked essays, Ronald Niezen discusses the ways new rights standards and networks of activist collaboration facilitate indigenous claims about culture, adding coherence to their histories, institutions, and group qualities. Drawing on historical, legal, and ethnographic material on aboriginal communities in northern Canada, Niezen illustrates the ways indigenous peoples worldwide are identifying and acting upon new opportunities to further their rights and identities. He shows how - within the constraints of state and international legal systems, activist lobbying strategies, and public ideas and expectations - indigenous leaders are working to overcome the injuries of imposed change, political exclusion, and loss of identity. Taken together, the essays provide a critical understanding of the ways in which people are seeking cultural justice while rearticulating and, at times, re-dignifying the collective self. The Rediscovered Selfshows how, through the processes and aims of justice, distinct ways of life begin to be expressed through new media, formal procedures, and transnational collaborations.
Keywords: _Nettoyé

Digital Identity: The Construction of Virtual Selfhood in the Indigenous Peoples' Movement - Niezen, Ronald (Comparative Studies in Society and History, 2005)
Inventions have their greatest impact when they go beyond their possible practical applications and act upon the imagination. When Martin Behaim invented the first globe in 1490, a functionally useless object consisting mostly of terra incognita, he was widely ridiculed; but somehow the ideas that his globe represented stuck, and within a few decades the basic validity of his construction was confirmed by the voyages of Columbus, Cabot, Vasco de Gama, Magellan, and others. Today, with efforts to situate the rapid growth of information and communication technologies (ICTs), especially the Internet, in the context of globalization, there is a similar division between those who dismiss it as being of no importance and those who see in it a looming (for good or ill) global revolution. But, as with Behaim's globe, the imaginary possibilities of these innovations are important in determining how and to what extent human existence is to be transformed by them
Keywords: 1-Histoire de l'art; 2-Humanités numériques; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Créateur.rice autochtone; _Nettoyé

CyberPowWow: discours chronopolitiques autour des arts et muséographies numériques autochtones - L'Heureux, Isabelle (Université de Montréal, 2018)
Le collectif d'artistes Nation to Nation crée en 1996 CyberPowWow, une galerie d'art numérique autochtone en ligne. Entre 1997 et 2004, le projet voit quatre éditions se succéder et plus d'une vingtaine d'artistes y participer. CPW développe un modèle alternatif pour une production, une diffusion et une critique autodéterminée des arts numériques autochtones au Canada, ce qui lui confère une place importante dans la structuration de cette scène. Le présent mémoire vise à étudier la position de CPW - sa plateforme muséographique et ses œuvres - au sein d'un ensemble de discours chronopolitiques qui opèrent à l'intersection des arts, des technologies numériques et des identités autochtones
Keywords: 1-Histoire de l'art; 2-Approches sociologiques; 2-Humanités numériques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; 5-Créateur.rice autochtone; _Nettoyé

Indigenous Aestetics: Native Art, Media and Identity - Leuthold, Steven M.... (University of Texas Press, 1998)
What happens when a Native or indigenous person turns a video camera on his or her own culture? Are the resulting images different from what a Westernized filmmaker would create, and, if so, in what ways? This book discusses the core concepts of aesthetics and indigenous culture and examines the work of American Indian documentary filmmakers
Section: XIII-238 p. : illustrations ; 24 cm
Keywords: 1-Cinéma; 1-Histoire de l'art; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Technologies of Self-Fashioning : Virtual Ethnicities in New Media Art - Jim, Alice Ming Wai (Proceedings of the 21st International Symposium on Electronic Art, 2015)
This paper proposes a theoretical framework with which to dis- cuss the critical engagement of media art projects in Second Life with racialized self-representation, fashion and ethnic dress. Ex- amining Montreal-based Mohawk artist Skawennati’s machinima series, TimeTravellerTM (2008-13), a project of self- determination, survivance and Indigenous futurity, it argues the critically-aware act of ‘virtually self-fashioning’ racialized born- digital identities, or virtual ethnicities, disrupts ways in which today’s vast proliferation of self-technologies enabling the crea- tion, recreation and management of multiple selves, would other- wise remain complicit with neoliberal colour-blind racism
Keywords: 1-Histoire de l'art; 1-Jeux vidéo; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Sud (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Internet et le concept de religion chez les autochtones du Québec - Gélinas, Claude (Représentation, métissage et pouvoir: la dynamique coloniale des échanges entre Autochtones, Européens et Canadiens (XVIe-XXe siècle), 2012)
Résumé livre : Les échanges entre les Européens, leurs descendants en Amérique et les Autochtones depuis les premiers contacts jusqu’à nos jours constituent un thème de première importance dans les travaux menés depuis une quarantaine d’années en histoire des Amérindiens et en histoire coloniale. Ils sont cruciaux pour comprendre la situation contemporaine des nations amérindiennes, les relations entretenues avec les gouvernements, la question territoriale et la définition de l’identité. Pour rendre compte de la diversité des échanges entre Autochtones, Européens et Canadiens, et de leur importance dans l’histoire du Canada, les textes présentés dans cet ouvrage les abordent à partir des concepts de représentation, de métissage et de pouvoir. Les représentations qu’Amérindiens, Européens et Canadiens se sont forgées les uns des autres ont joué un rôle central dans leurs relations ; par exemple, la manière dont les Européens ont perçu, décrit ou imaginé les Autochtones a eu un poids déterminant sur les sociétés européennes et sur les politiques coloniales, influençant, en retour, les relations avec les Autochtones. Les images de l’Autre, en perpétuelle transformation, ont également eu une incidence sur la façon dont les Autochtones se sont auto-représentés, sur la façon dont ils ont adopté, transformé ces images pour se les approprier et, enfin, sur la façon dont ils les ont rejetées pour définir leur identité. Les représentations que les Autochtones ont forgées des Européens, moins bien connues malheureusement, ont également influencé l’évolution des rapports avec les colonisateurs. Utilisant différents supports : textes, images, récits oraux, sites internet et culture matérielle, les représentations résultent de processus complexes. Leur interprétation induit la question de leur élaboration et de leur transmission, celle de l’influence des idéologies et des catégories mentales de l’époque, mais aussi celle de la fonction et du pouvoir de ces représentations.
Section: xxi, 487 p. : ill. (certaines en coul.), cartes, portr. ; 23 cm
Keywords: 1-Histoire de l'art; 2-Humanités numériques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); _Nettoyé

Numéro spécial : Cinémas et médias autochtones dans les Amériques : récits, communautés et souverainetés - Dudemaine, André; Marcoux, Gabrielle; St-Amand, Isabelle (Canadian Journal of Film Studies, 2020)
Keywords: 1-Cinéma; 1-Histoire de l'art; 2-Genre et sexualité; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 3-Océanie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 4-Océanie (lieu de production du savoir); 5-Auteur.rice; 5-Auteur.rice autochtone; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Queering Decolonization – Two Spirit Resistance Across Borders From Turtle Island to Palestine (2019)
Avec Alex Wilson, Jeffrey McNeil, Teddy Syrette, May Ela and Ahmed Maswadeh.
Keywords: 1-Cinéma; 1-Histoire de l'art; 1-Jeux vidéo; 1-TV; 2-Genre et sexualité; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 3-Asie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Créateur.rice LGBTQ+; 5-Créateur.rice PANDC; 5-Créateur.rice autochtone; 5-Créatrice; 5-Identités diasporiques; _Nettoyé

Two-Spirit Resistance - Mcneil-Saymour, Jeffrey (Whose Land is it anyway? A Manual for Decolonization., 2017)
The publication of Whose Land Is It Anyway? A Manual for Decolonization is inspired by a 2016 speaking tour by Arthur Manuel, less than a year before his untimely passing in January 2017. The handbook provides a variety of Indigenous perspectives on the history of colonialism, current Indigenous activism and resistance, and outlines the path forward to reconciliation
Section: 79 pages : illustrations (some color) ; 29 cm
Keywords: 1-Cinéma; 1-Histoire de l'art; 1-Jeux vidéo; 2-Genre et sexualité; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice LGBTQ+; 5-Auteur.rice autochtone; _Nettoyé

Unsettled Landscapes - Dees, Janet; Hofmann, Irene; Hopkins, Candice; Sanromán, Lucia (SITE Santa Fe, 2014)
Published by SITE Santa Fe on occasion of the inaugural SITElines Biennial, 'Unsettled Landscapes'. Unsettled Landscapes was curated by Janet Dees, Irene Hofmann, Candice Hopkins, and Lucía Sanromán. The exhibition, featuring 47 artists from 14 countries, looks at the urgencies, political conditions and historical narratives that inform the work of contemporary artists across the Americas–from Nunavut to Tierra del Fuego. Through three themes–landscape, territory, and trade–this exhibition expresses the interconnections among representations of the land, movement across the land, and economies and resources derived from the land."–Résumé de l'éditeur
Section: 223 pages : illustrations (principalement en couleur) ; 24 cm.
Keywords: 1-Histoire de l'art; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 2-Étude des représentations; 3-Amérique centrale (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 4-Amérique centrale (lieu de production du savoir); 4-Amérique du Nord (lieu de production du savoir); 4-Amérique du Sud (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice autochtone; 5-Autrice; 5-Créateur.rice PANDC; 5-Créatrice; 5-Identités diasporiques; _Nettoyé

Interpellations: Three Essays on Kent Monkman - Thériault, Michèle (Galerie Leonard & Bina Ellen art gallery, 2012)
Trois essais de Richard W. Hill, Jonathan D Katz et Todd B Porterfield.
Section: 118 p. : ill. en coul. ; 25 cm.
Keywords: 1-Histoire de l'art; 2-Genre et sexualité; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Créateur.rice LGBTQ+; 5-Créateur.rice autochtone; _Nettoyé

La danse au berdache de Kent Monkman - Sioui Durand, Guy (Inter, 2009)
Keywords: 1-Histoire de l'art; 2-Genre et sexualité; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Créateur.rice LGBTQ+; 5-Créateur.rice autochtone; _Nettoyé

Éros et tabou: sexualité et genre chez les Amérindiens et les Inuit - Havard, Gilles; Laugrand, Frédéric (Septentrion, 2014)
Éros et tabou analyse les pratiques érotiques et les relations de genre au sein de diverses populations autochtones d'Amérique du Nord. Ces sociétés sont-elles plus ouvertes au principe de plaisir et aux pulsions sexuelles que les sociétés occidentales? L'ouvrage se penche particulièrement sur la tension existant parmi les Amérindiens et les Inuit entre, d'un côté, une sexualité d'apparence permissive qui peut acquérir un caractère public et décomplexé et, de l'autre, des pratiques strictement codifiées, souvent associées à des interdits. Le sexe apparaît donc comme un élément révélateur du social. Plusieurs thématiques sont examinées dans cette perspective, dont la différenciation des sexes et le travestissement, la contrainte et le consentement dans les unions et les mariages, la place du sexe dans la langue et la pensée symbolique, les relations sexuelles entre femmes autochtones et hommes d'origine européenne depuis le XVIe siècle ou encore la part jouée par les missionnaires dans la confrontation des Européens avec les moeurs autochtones. L'ouvrage est publié en hommage à Denys Delâge. Avec la collaboration de Marie-Pierre Bousquet, Denys Delâge, Raymond J. DeMallie, Louis-Jacques Dorais, Claude Gélinas, Anny Morissette, Murielle Nagy, Douglas R. Parks, Bernard Saladin d'Anglure et Olivier Servais.
Section: 500 pages : illustrations ; 23 cm
Keywords: 1-Cinéma; 1-Histoire de l'art; 1-Jeux vidéo; 1-TV; 2-Genre et sexualité; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; _Nettoyé

Indigenous and Decolonizing Studies in Education: Mapping the Long View - Tuhiwai Smith, Linda; Tuck, Eve; Yang, K. Wayne (Routledge, 2019)
Indigenous and decolonizing perspectives on education have long persisted alongside colonial models of education, yet too often have been subsumed within the fields of multiculturalism, critical race theory, and progressive education. Timely and compelling, Indigenous and Decolonizing Studies in Education features research, theory, and dynamic foundational readings for educators and educational researchers who are looking for possibilities beyond the limits of liberal democratic schooling. Featuring original chapters by authors at the forefront of theorizing, practice, research, and activism, this volume helps define and imagine the exciting interstices between Indigenous and decolonizing studies and education. Each chapter forwards Indigenous principles - such as Land as literacy and water as life - that are grounded in place-specific efforts of creating Indigenous universities and schools, community organizing and social movements, trans and Two Spirit practices, refusals of state policies, and land-based and water-based pedagogies.–publisher's description.
Keywords: 1-Cinéma; 1-Histoire de l'art; 1-Jeux vidéo; 1-TV; 2-Pédagogie décoloniale; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 3-Océanie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 4-Océanie (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; _Nettoyé

Feminismos disidentes en América Latina y el Caribe // Féminismes dissidents en Amérique latine et aux Caraïbes - Curiel, Ochy; Falquet, Jules; Masson, Sabine (Editions Antipodes, 2005)
La idea de elaborar un número sobre las luchas de las mujeres y las feministas en América Latina y el Caribe surgió de un encuentro entre Sabine Masson (Suiza), Jules Falquet (Francia) y Ochy Curiel (República Dominicana), cuyos caminos se cruzaron en el continente latinoamericano por razones personales y políticas. Debatimos y reflexionamos juntas sobre la cuestión de las barreras de "raza" y de clase que nos atraviesan a las feministas de diferentes partes del mundo, y que son en particular el reflejo de las relaciones de dominación entre el Sur y el Norte. Precisamente por estas barreras, las experiencias políticas y el trabajo de construcción colectiva de muchas feministas y mujeres, especialmente de América Latina y el Caribe, siguen siendo desconocidas para la mayoría de las feministas de otras latitudes, y de poco interés para las revistas académicas feministas de los países ricos. Oponerse a esta invisibilización y contribuir, aunque sea a nivel experimental y muy modesto, a la deconstrucción de estas barreras, fue nuestra principal motivación para organizar este número en una revista francófona como Nouvelles Questions Féministes. Sin embargo, el trabajo de coordinación presentó importantes contradicciones: primero, entre nosotros mismos. En primer lugar, tuvimos que reconocer e integrar las diferencias y similitudes de nuestras respectivas posiciones, para llegar a un consenso que nos permitiera desarrollar esta cuestión juntos. En segundo lugar, nos enfrentamos al riesgo de reproducir una vez más el saqueo de los conocimientos de las mujeres indias, afrodescendientes y mestizas latinoamericanas y caribeñas por parte de los "expertos del Norte". Los textos se traducirían al francés, lo que significaría que una ínfima minoría de mujeres latinoamericanas y caribeñas tendría acceso a ellos, mientras circulaban por Europa, enriqueciendo una vez más el conocimiento de las mujeres de los países ricos con el trabajo, las luchas, las historias y los escritos de las mujeres de los países pobres. Ante este problema, decidimos que la publicación de este número fuera acompañada de una versión en español, con el objetivo de hacer circular y compartir esta producción intelectual en América Latina y el Caribe L’idée de faire un numéro sur les luttes de femmes et les luttes féministes en Amérique latine et aux Caraïbes a surgi de la rencontre entre Sabine Masson (Suisse), Jules Falquet (France) et Ochy Curiel (République Dominicaine), dont les chemins se sont croisés sur le continent latino-américain pour des raisons personnelles autant que politiques. Nous avons débattu et réfléchi ensemble sur la question des barrières de « race » et de classe qui nous traversent, nous les féministes de différentes parties du monde, et qui sont notamment le reflet des rapports de domination entre le Sud et le Nord. Justement à cause de ces barrières, les expériences politiques et le travail de construction collective de beaucoup de féministes et de femmes, notamment latino-américaines et des Caraïbes, demeurent inconnus de la plupart des féministes d’autres latitudes, et intéressent peu les revues féministes académiques des pays riches. S’opposer à cette invisibilisation et contribuer, même si ce n’est qu’à un niveau expérimental et très modeste, à déconstruire ces barrières, a constitué notre principale motivation pour organiser ce numéro dans une revue francophone comme Nouvelles Questions Féministes . Néanmoins, le travail de coordination présentait d’importantes contradictions : d’abord, entre nous. Pour commencer, nous avons dû reconnaître et intégrer les différences et les similitudes de nos positions respectives, afin de parvenir à un consensus qui nous permette d’élaborer ce numéro ensemble. Ensuite, nous nous confrontions au risque de reproduire encore une fois le pillage des connaissances des femmes indiennes, afro-descendantes et métisses latino-américaines et des Caraïbes par les « expertes du Nord ». Les textes allaient être traduits en français, c’est-à-dire qu’une infime minorité de femmes latino-américaines et des Caraïbes pourrait y avoir accès, pendant qu’ils circuleraient en Europe, enrichissant une fois de plus le savoir des femmes des pays riches à partir du travail, des luttes, des histoires et des écrits des femmes des pays pauvres. Face à ce problème, nous avons décidé que la publication de ce numéro allait s’accompagner d’une version en espagnol, dans le but de faire circuler et de partager cette production intellectuelle en Amérique latine et aux Caraïbes
Link Catalogue Open WorldCat http://www.worldcat.org/oclc/728004883
Keywords: 1-Cinéma; 1-Histoire de l'art; 1-Jeux vidéo; 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique centrale (corpus analysé); 3-Amérique du Sud (corpus analysé); 4-Amérique centrale (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé

Crítica y descolonización: el sujeto colonial en la cultura latinoamericana - González-Stephan, Beatriz; Universidad Simón Bolívar (1992)
Keywords: 1-Cinéma; 1-Histoire de l'art; 1-Jeux vidéo; 1-TV; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Sud (corpus analysé); 4-Amérique du Sud (lieu de production du savoir); 5-Autrice; _Nettoyé

ETNICIDAD, INVESTIGACIÓN Y REPRESENTACIÓN EN LA EXPOSICIÓN VELORIOS Y SANTOS VIVOS. COMUNIDADES NEGRAS, AFROCOLOMBIANAS, RAIZALES Y PALENQUERAS - Figueroa, Cristina Lleras

Charla | Estética afro Identidad, saberes y resistencia - Banrepcultural (2019)
En esta charla conversaremos sobre las luchas históricas por la reivindicación de los derechos del pueblo afro que están detrás de su estética, específicamente en dos de sus expresiones femeninas: el turbante afro y el pelo natural, los cuales han servido como elementos de resistencia para la pervivencia de las prácticas y costumbres ancestrales. Como parte de la exposición temporal del Museo del Oro 'A bordo de un navío esclavista, La Marie-Séraphique' (que se presentó en Bogotá del 7 de octubre de 2018 al 7 de abril de 2019) hablamos en el museo sobre algunos peinados ancestrales, como la espina de pescado, las tropas, el hundidito, el ciempiés y la vicha, y sobre los usos, significados y modelos de los turbantes afro, como la cadena del esclavo, la autoridad, el kitambala, el enkeycha y el doek. El termino mata ‘e pelo surge de las expresiones propias de nuestras ancestras, que se referían al pelo afro cómo una gran mata (árbol), frondosa, incontrolable y rizada, que requería unos cuidados particulares por su condición crespa, abundante y diversa. El cuerpo de la mujer negra, raizal y palenquera ha estado históricamente ligado a las luchas por la reivindicación de los derechos del pueblo afro, siendo la mata ‘e pelo el elemento estético que más las ha transmitido. Entre las personas de ancestros africanos, la estética del pelo afro se remonta a un pasado cargado de lucha y resistencia, pues las trenzas fueron usadas para la elaboración de mapas que marcaban el camino a la libertad de los cimarrones. Las mujeres se reunían en el patio para peinar a las más pequeñas. Diseñaban en su cabeza un mapa lleno de caminitos y salidas de escape, en el que ubicaban los montes, ríos y árboles más altos. Así, al verlas, los hombres sabían cuáles rutas tomar. Su código, desconocido para los amos, les permitía a los esclavizados huir. El balance humano de la trata de cautivos africanos a través del Atlántico es dramático: con una inmensa brutalidad, desplazó a 13 millones de hombres, mujeres y niños entre la segunda mitad del siglo XVI y finales del siglo XIX. #ElMuseoDelOroTambiénEsAfro Producción Banco de la República Realización Santiago Martínez
Keywords: 1-Cinéma; 1-Histoire de l'art; 1-Jeux vidéo; 1-TV; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Muséologie critique; 2-Pédagogie décoloniale; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Sud (corpus analysé); 4-Amérique du Sud (lieu de production du savoir); 5-Auteur.rice noir.e; 5-Identités diasporiques; _Nettoyé

Vistazo Crítico 135: Nelson Fory Ferreira: la historia nuestra caballero. - Arcos-Palma, Ricardo (VISTAZOS CRÍTICOS: 20 años de crítica de la cultura y del arte, 2015)
Keywords: 1-Histoire de l'art; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Sud (corpus analysé); 4-Amérique du Sud (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Créateur.rice PANDC; 5-Créateur.rice noir.e; _Nettoyé

Presencia negra en Bogotá: Décadas 1940-1950-1960
La exposición Presencia negra en Bogotá hace parte de la investigación en Migraciones que desde la Universidad Nacional lideran Mercedes Angola y Maguemati Wabgou. Está presente en el Claustro de San Agustín, como un homenaje a los hacedores de grandes historias que se desconocen, personas cuyos aportes a la construcción de la sociedad colombiana y a la consolidación de la identidad nacional desde diversas perspectivas y disciplinas ha invisibilizado la historia colombiana. En compañía de sus protagonistas, acompáñenos en la formulación de nuevas preguntas de investigación en torno al aporte de la gente negra a Colombia y a países vecinos, pues no solo se ha producido migración interna sino, "fuga" hacia otros países. Invitados : Mercedes Angola, artista plástica e investigadora y Maguemati Wabgou, sociólogo e investigador.
Keywords: 1-Cinéma; 1-Histoire de l'art; 1-Jeux vidéo; 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Sud (corpus analysé); 4-Amérique du Sud (lieu de production du savoir); 5-Auteur.rice noir.e; 5-Identités diasporiques; _Nettoyé

¡Mandinga sea! África en Antioquia - Luz Adriana Maya Restrepo; Raúl Cristancho (Universidad de los Andes, 2015)
Compuesta por 355 obras de arte de naturaleza muy variada, la exposición en sala y ahora impresa busca visibilizar, dignificar, valorar y difundir los legados civilizatorios, reativos, culturales, económicos, sociales, políticos, tecnológicos, ambientales e históricos de los pueblos del África occidental y de sus descendientes en la construcción de Antioquia. Además, este catálogo pretende ubicar en las manos del público, y de los especialistas en museos y en estética, el de-bate sobre las encrucijadas que encierra la representación museal de las obras artísticas y de las culturas de los pueblos afroamericanos fraguados en el seno de las dinámicas esclavistas, imperiales y coloniales.
Keywords: 1-Histoire de l'art; 2-Histoire/Historiographie critique; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Afrique (corpus analysé); 3-Amérique du Sud (corpus analysé); 4-Amérique du Sud (lieu de production du savoir); 5-Autrice; 5-Créateur.rice noir.e; 5-Identités diasporiques; _Nettoyé

Critics and the Slippery Terrain of Latinx Art - Dávila, Arlene (Latin American and Latinx Visual Culture, 2019)
When E. Carmen Ramos organized Our America: The Latino Presence in American Art (2013) at the Smithsonian American Art Museum in Washington, DC, art holdings of Latinx artists at the institution were minimal and unbalanced. The museum lacked works by foundational figures; entire groups like Dominican Americans were missing, as were genres like abstract art; and with a collection dominated by colonial and folk art and work by Mexican Americans, it was impossible to produce any comprehensive exhibition of contemporary Latinx art, much less one that represented the diversity of artists and trends. Ramos was one of the few Latinx curators hired in the aftermath of the infamous 1994 “Willful Neglect” report documenting a historical pattern of discrimination at the Smithsonian Institute and calling for the hiring of Latinx curators to help direct the Smithsonian’s priorities in research, collections, and exhibitions.1 Twenty-five years later, this pattern of exclusion continues apace. In 2018, a study by UCLA’s Chicano Studies Research Center found that while the Smithsonian’s Latinx workforce grew from 2.5 percent to 10.1 percent, this growth falls short of representing the growth of the Latinx population, which since 1994 has doubled to 17.8 percent of the total population. In sum, the task of putting a dent in a mostly white canonical art history and collection was a daunting one, and whatever Ramos did would be a politically charged intervention. This would be the first major scholarly survey exhibition of Latinx art, a statement to insert it as central to US art history, and the first major show of its type in a major North American museum in decades.
Keywords: 1-Histoire de l'art; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Créateur.rice PANDC; _Nettoyé

Flora and Fauna Otherwise: Black and Brown Aesthetics of Relation in Firelei Báez and Wangechi Mutu - Alvarado, Leticia (Latin American and Latinx Visual Culture, 2019)
Pairing Dominican-born artist Firelei Báez with Kenyan-born artist Wangechi Mutu, this article meditates on relational black and brown aesthetic strategies by reading femme gestures performatively across individual works, as well as the exhibition spaces within which the artists draft practices of informed and resistant engagement. Working with both theories of brownness that emerge from Latinx studies as well as scholarship of the black radical tradition, the author follows a sense of shared aesthetic gestures in Báez and Mutu’s work toward an indictment of pervasive Global North racial epistemologies. Focusing on the performative gesture as the basis for relation, this article ultimately hones in on the chimeric figures—amalgamations of flora and fauna—that both artists deploy, arguing that these present a model for imagining an otherwise arrangement of the social.R Poniendo en diálogo a Firelei Báez, una artista nacida en República Dominicana, con Wangechi Mutu, que nació en Kenia, este artículo invita a una meditación sobre las estrategias estéticas relacionales negras y morenas mediante una lectura en clave performativa de gestos femeninos en obras individuales y en aquellos espacios de exposición en que las artistas elaboran prácticas de participación política informada y de resistencia. Trabajando tanto con las teorías de lo moreno (brownness) que emergen de los estudios Latinx como con el trabajo académico de la tradición radical negra, la autora rastrea gestos estéticos presentes tanto en el trabajo de Báez como en el de Mutu para denunciar las omnipresentes epistemologías raciales del norte global. Centrándose en el gesto performativo como la base de la relación, este artículo se enfoca en última instancia en las figuras quiméricas – amalgamaciones de flora y fauna – que ambas artistas despliegan en su trabajo para sostener que estas presentan un modelo para imaginar otra manera de organizar lo social.
Keywords: 1-Histoire de l'art; 2-Analyses formalistes; 2-Genre et sexualité; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Afrique (corpus analysé); 3-Amérique centrale (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Créateur.rice PANDC; _Nettoyé

Queer Latinidad: Identity Practices, Discursive Spaces - Rodriguez, Juana Maria (New York University Press, 2003)
According to the 2000 census, Latinos/as have become the largest ethnic minority group in the United States. Images of Latinos and Latinas in mainstream news and in popular culture suggest a Latin Explosion at center stage, yet the topic of queer identity in relation to Latino/a America remains under examined. Juana María Rodríguez attempts to rectify this dearth of scholarship in Queer Latinidad: Identity Practices, Discursive Spaces, by documenting the ways in which identities are transformed by encounters with language, the law, culture, and public policy. She identifies three key areas as the project’s case studies: activism, primarily HIV prevention; immigration law; and cyberspace. In each, Rodríguez theorizes the ways queer Latino/a identities are enabled or constrained, melding several theoretical and methodological approaches to argue that these sites are complex and dynamic social fields. As she moves the reader from one disciplinary location to the other, Rodríguez reveals the seams of her own academic engagement with queer latinidad. This deftly crafted work represents a dynamic and innovative approach to the study of identity formation and representation, making a vital contribution to a new reformulation of gender and sexuality studies.
Keywords: 1-Cinéma; 1-Histoire de l'art; 1-Jeux vidéo; 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Humanités numériques; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Identités diasporiques; _Nettoyé

Sexual Futures, Queer Gestures, and Other Latina Longings - Rodriguez, Juana Maria (New York University Press, 2014)
"Sexual Futures, Queer Gestures and Other Latina Longings proposes a theory of sexual politics that works in the interstices between radical queer desires and the urgency of transforming public policy, between utopian longings and everyday failures. Considering the ways in which bodily movement is assigned cultural meaning, Juana Maria Rodriguez takes the stereotypes of the hyperbolically gestural queer Latina femme body as a starting point from which to discuss how gestures and forms of embodiment inform sexual pleasures and practices in the social realm. Centered on the sexuality of racialized queer female subjects, the book's varied archive–which includes burlesque border crossings, daddy play, pornography, sodomy laws, and sovereignty claims–seeks to bring to the fore alternative sexual practices and machinations that exist outside the sightlines of mainstream cosmopolitan gay male culture. Situating articulations of sexual subjectivity between the interpretive poles of law and performance, Rodriguez argues that forms of agency continually mediate among these various structures of legibility–the rigid confines of the law and the imaginative possibilities of the performative. She reads the strategies of Puerto Rican activists working toward self-determination alongside sexual performances on stage, in commercial pornography, in multi-media installations, on the dance floor, and in the bedroom. Rodriguez examines not only how projections of racialized sex erupt onto various discursive mediums but also how the confluence of racial and gendered anxieties seeps into the gestures and utterances of sexual acts, kinship structures, and activist practices. Ultimately, Sexual Futures, Queer Gestures, and Other Latina Longings reveals–in lyrical style and explicit detail–how sex has been deployed in contemporary queer communities in order to radically reconceptualize sexual politics"–
Keywords: 1-Cinéma; 1-Histoire de l'art; 1-Jeux vidéo; 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 3-Amérique centrale (corpus analysé); 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé

Metamorphic and Sensuous Brown Bodies: Queer Latina/x Visual and Performance Cultures in San Francisco Strip Clubs, 1960s–1970s - Otálvaro-Hormillosa, Gigi (Latin American and Latinx Visual Culture, 2019)
In the 1960s, topless entertainment became legal in San Francisco, although cross-dressing continued to be criminalized. This article documents queer Latina/x visual and performance cultures of San Francisco’s strip club industry during this critical moment. It employs visual and performance analyses that draw from ethnographic interviews and archival research about three Latinas who performed as exotic dancers during this period, two of whom were out transsexuals: Roxanne Lorraine Alegria, Vicki Starr, and Lola Raquel. Engaging Marcia Ochoa’s notion of “spectacular femininities” and Juana María Rodríguez’s theory of “queer gesture,” the article maps out a queer Latina/x herstoriography about the early days of topless entertainment in San Francisco. It demonstrates how the transgressive practices of these Latina performers enrich genealogies of queer and Latina/x performance and visual cultures since the 1960s. It thus contributes to the expansion and intersection of the fields of performance studies, Latina/x studies, and feminist, gender, and sexuality studies. These fields and their intertwinings offer critical tools to resist the sexism, homophobia, racism, transphobia, and whorephobia that pervade every level of society, as well as the cultural amnesia to which San Francisco has been increasingly prone due to its incessant gentrification and growing technocracy since the early 2010s.RESUMEN Este artículo documenta las culturas visuales y de performance latinas/x queer de los clubes de striptease de San Francisco durante un momento crítico en la historia de la ciudad. En la década de 1960, los shows en topless se legalizaron en San Francisco, aunque el travestismo se continuó criminalizando. Otálvaro-Hormillosa emplea análisis visuales y de performance que se basan en entrevistas etnográficas e investigación de archivo sobre tres latinas que actuaron como bailarinas exóticas durante este período, dos de las cuales reconocían públicamente que eran transexuales: Roxanne Lorraine Alegria, Vicki Starr y Lola Raquel. En diálogo con la noción de “feminidades espectaculares” de Marcia Ochoa y la teoría de “gestos queer” de Juana María Rodríguez, Otálvaro-Hormillosa describe una historiografía latina/x queer propiamente femenina sobre los primeros días del entretenimiento en topless en San Francisco. El artículo demuestra cómo las prácticas transgresoras de estas intérpretes latinas enriquecen las genealogías de las culturas visuales y de performance queer y latinas/x desde los años sesenta. Al hacerlo, contribuye a la expansión e intersección de los campos de los estudios de performance, estudios latinas/x, y estudios feministas, de género y de sexualidad. Estos campos y sus entrecruzamientos pueden ofrecer herramientas críticas para resistir el sexismo, la homofobia, el racismo, la transfobia y la putafobia que permea todos los niveles de la sociedad, así como la amnesia cultural a la que San Francisco ha sido cada vez más propenso debido a su incesante gentrificación y creciente tecnocracia desde principios de los años 2010.RESUMO Este artigo documenta a cultura visual e de performance na indústria de clubes de strip-tease de São Francisco, durante um momento crítico da história da cidade. Nos anos 60, o entretenimento topless se tornou legal em São Francisco, embora a prática do cross-dressing continuasse criminalizada. Otálvaro-Hormillosa emprega análise visual e de performance baseadas em entrevistas etnográficas e pesquisas de arquivos sobre três latinas que se apresentaram como dançarinas exóticas durante esse período, duas das quais eram transexuais: Roxanne Lorraine Alegria, Vicki Starr e Lola Raquel. Engajando a noção de “feminilidades espetaculares” de Marcia Ochoa e a teoria do “gesto queer” de Juana María Rodríguez, Otálvaro-Hormillosa mapeia uma herstoriografia queer latina/x sobre os sobre os primórdios do entretenimento topless em São Francisco. O artigo demonstra como as práticas transgressivas dessas artistas latinas enriquecem as genealogias das culturas visual e de performance queer e latina/x desde os anos 1960. Deste modo, contribui para a expansão e intersecção dos campos de estudos da performance, estudos latinos e estudos feministas, de gênero e sexualidade. Esses campos e seus entrelaçamentos podem oferecer ferramentas críticas para resistir ao sexismo, homofobia, racismo, transfobia e putafobia que permeiam todos os níveis da sociedade, bem como a amnésia cultural para a qual San Francisco tem sido cada vez mais propensa devido à sua gentrificação incessante e crescente tecnocracia desde o início dos anos 2010.
Keywords: 1-Histoire de l'art; 2-Approches sociologiques; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice LGBTQ+; 5-Auteur.rice PANDC; 5-Créateur.rice LGBTQ+; 5-Créateur.rice PANDC; _Nettoyé

Postcolonial Modernism: Art and Decolonization in Twentieth-Century Nigeria - Okeke-Agulu, Chika (Duke University Press, 2015)
Written by one of the foremost scholars of African art and featuring more than 125 color images, Postcolonial Modernism chronicles the emergence of artistic modernism in Nigeria in the heady years surrounding political independence in 1960.
Keywords: 1-Histoire de l'art; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Afrique (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Créateur.rice noir.e; 5-Identités diasporiques; _Nettoyé

Visual Disobedience: The Geopolitics of Experimental Art in Central America, 1990-Present - Cornejo, Kency (N.D., 2014)
This dissertation centers on the relationship between art and politics in postwar Central America as materialized in the specific issues of racial and gendered violence that derive from the region's geopolitical location and history. It argues that the decade of the 1990s marks a moment of change in the region's cultural infrastructure, both institutionally and conceptually, in which artists seek a new visual language of experimental art practices to articulate and conceptualize a critical understanding of place, experience and knowledge. It posits that visual and conceptual manifestations of violence in Central American performance, conceptual art and installation extend beyond a critique of the state, and beyond the scope of political parties in perpetuating violent circumstances in these countries. It argues that instead artists use experimental practices in art to locate manifestations of racial violence in an historical system of domination and as a legacy of colonialism still witnessed, lived, and learned by multiple subjectivities in the region. In this postwar period artists move beyond the cold-war rhetoric of the previous decades and instead root the current social and political injustices in what Aníbal Quijano calls the `coloniality of power.' Through an engagement of decolonial methodologies, this dissertation challenges the label "political art" in Central America and offers what I call "visual disobedience" as a response to the coloniality of seeing. I posit that visual colonization is yet another aspect of the coloniality of power and indispensable to projects of decolonization. It offers an analysis of various works to show how visual disobedience responds specifically to racial and gender violence and the equally violent colonization of visuality in Mesoamerica. Such geopolitical critiques through art unmask themes specific to life and identity in contemporary Central America, from indigenous genocide, femicide, transnational gangs, to mass imprisonments and a new wave of social cleansing. I propose that Central American artists–beyond an anti-colonial stance–are engaging in visual disobedience so as to construct decolonial epistemologies in art, through art, and as art as decolonial gestures for healing.
Keywords: 1-Histoire de l'art; 2-Histoire/Historiographie critique; 2-Méthodologie de recherche décoloniale; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique centrale (corpus analysé); 4-Amérique centrale (lieu de production du savoir); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé

Decolonizing the Global Renaissance: A View from the Andes - Cohen-Aponte, Ananda (The Globalization of Renaissance Art: A Critical Review, 2017)
The development of Global Renaissance art history has had an undeniable impact on the field of colonial Latin American art. Some of the earliest manifestations of this disciplinary partnership can be found in exhibitions, monographs, articles, and edited volumes produced around the quincentennial of Christopher Columbus’s 1492 voyage. Exhibitions such as Circa 1492 at the National Gallery and a wave of scholarly publications addressed the cataclysmic impact of the European invasion and subsequent colonization of the Americas at an epistemological, linguistic, political, biological, and aesthetic level. The year 1992 precipitated an outpouring of critical reflection on the history of colonialism in the Western hemisphere and its enduring legacies both within Latin America and its diasporic communities.
LIVRE COMPLET : http://www.worldcat.org/oclc/1126363993
Keywords: 1-Histoire de l'art; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Sud (corpus analysé); 3-Europe (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; _Nettoyé

Equivocation, Translation, and Performative Interseccionality: Notes on Decolonial Feminist Practices and Ethics in Latin America - de Lima Costa, Claudia (ANGLO SAXONICA, 2013)
In this paper I offer a brief overview of the academic debates about post-colonial theories and the concept of coloniality, seeking to map out their Latin American translations, especially from the perspective of feminist theories in relation to the coloniality of gender. By emphasizing an intersectional approach to understand the gendered character of coloniality, decolonial feminists are seeking innovative ways of articulating new epistemologies or “saberes propios”. However, in these debates little attention has been given to the issue of the travels and translations of decolonial feminisms in Latin America. In focusing on the vexed issue of translation, I want to explore some of the challenges Latin American decolonial feminists are facing today.
PDF of the article included
Keywords: 1-Histoire de l'art; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 3-Amérique du Sud (corpus analysé); 4-Amérique du Sud (lieu de production du savoir); 5-Autrice; _Nettoyé

Memories of Underdevelopment: Art and the Decolonial Turn in Latin America, 1960-1985 - González, Julieta; Lerner, Sharon; Giunta, Andrea; Kanjo, Kathryn (Museum of Contemporary Art San Diego, 2018)
OCLC: 1056112657
Keywords: 1-Histoire de l'art; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Sud (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 4-Amérique du Sud (lieu de production du savoir); _Nettoyé

Essay on Decolonial Aesthetics in Latin America - Luciano, Paula (RELACult - Revista Latino-Americana de Estudos em Cultura e Sociedade, 2019)
This essay aims to trace an overview of the decolonial aesthetics through the analysis of artistic expressions that occurred in Latin American territory. This analysis will allow us to enhance the cultural and artistic practices within its plurality and the typical spatial archetypes within its temporal resignification. The necessity of creation and the search for new epistemological fields translate the historical movements of the Latin-American cultural mouvance and the juxtaposition of temporalities, practices and the confluence of knowledge. We can find a stage of resistance and socio-historical borders subverted, mainly in the context of artistic and cultural manifestations and its capacity of invention and relativization. This essay aims to bring a reflection on the construction of cultural spaces and the dismantling of a single hegemonic perspective to define the artistic practices. The analysis and the epistemological questioning of the Latin-American trans-historical movement delineates an overview of the history of artistic productions that came out of practices and every-day life inventions and the elaboration of temporary spaces of claim and contestation through exhibitions, performances, festivals, and so forth. The idea of subverting a geopolitical imaginary and a cartography of the world (even if initially in local dynamics) consists of a central focus of this work.
Keywords: 1-Histoire de l'art; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Sud (corpus analysé); 4-Amérique du Sud (lieu de production du savoir); 5-Autrice; _Nettoyé

An Aesthetic of Blackness: Strange and Oppositional - hooks, bell (Belonging: A Culture of Place, 2019)
There was no meaningful attempt to counter the black aesthetic with conceptual criteria for creating and evaluating art which would simultaneously acknowledge its ideological content even as it allowed for expansive notions of artistic freedom. To re-open the creative space that much of the black aesthetic movement closed down, it seems vital for those involved in contemporary black arts to engage in a revitalized discussion of aesthetics. In part, a radical aesthetic acknowledges that the people are constantly changing positions, locations, that their needs and concerns vary, that these diverse directions must correspond with shifts in critical thinking. Innovative African-American artists have rarely documented their process, their critical thinking on the subject of aesthetics. Certainly many of the revolutionary, visionary critical perspectives on music that were inherent to John Coltrane’s oppositional aesthetics and his cultural production will never be shared because they were not fully documented.
Keywords: 1-Histoire de l'art; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; _Nettoyé

Representations of Whiteness in the Black Imagination - hooks, bell (Belonging: A Culture of Place, 2019)
Searching the critical work of post-colonial critics, the author found much writing that bespeaks the continued fascination with the way white minds, particularly the colonial imperialist traveler, perceive blackness, and very little expressed interest in representations of whiteness in the black imagination. Some white people may even imagine there is no representation of whiteness in the black imagination, especially one that is based on concrete observation or mythic conjecture. Stereotypes black folks maintain about white folks are not the only representations of whiteness in the black imagination. Yet it is this representation of whiteness in the black imagination, first learned in the narrow confines of poor black rural community, that is sustained by the author travels to many different locations. Theorizing diverse journeying is crucial to the people understanding of any politics of location.
Keywords: 1-Cinéma; 1-Histoire de l'art; 1-Jeux vidéo; 1-TV; 2-Approches sociologiques; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 3-Amérique centrale (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; _Nettoyé

Discursos sobre "raza" y nación en Colombia, 1880-1930 - Bendezú, Mauro Vega (Universidad del Valle, Facultad de Humanidades, Departmento de Historia, 2013)
Discursos sobre “raza” y nación en Colombia, 1880-1930 constituye un aporte a la investigación sobre la formación de la nación en Colombia durante los siglos xix al xx. El libro es producto de la investigación de tesis de maestría del autor y se centra en mostrar cómo las elites del país concibieron y, en específico, aplicaron con la legislación y otros recursos políticos y culturales, formas de poder y hegemonía mediante las cuales establecieron su dominio a partir del control social, la higienización -“depuración racial o blanqueamiento de la raza”- y el señalamiento a los grupos que resistieron esas formas arbitrarias de poder desde arriba. La estructura del libro está dividida en una introducción, cuatro capítulos, las conclusiones, la bibliografía y una corta semblanza del autor. El primer capítulo es un análisis metodológico de la “alteridad”, a partir de la perspectiva poscolonial y decolonial; siguiendo a autores de renombre en ese campo, trata de demostrar – lamentablemente de modo uniforme– el carácter cruel y violento del proceso de europeización y de sus valores “irracionales” más recurrentes. Los capítulos del dos al cinco se dedican a sustentar la postura metodológica con un material de fuentes y de análisis sobre el racismo colombiano en los siglos xix y xx.
Keywords: 1-Cinéma; 1-Histoire de l'art; 1-Jeux vidéo; 1-TV; 2-Histoire/Historiographie critique; 2-Méthodologie de recherche décoloniale; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Sud (corpus analysé); 4-Amérique du Sud (lieu de production du savoir); _Nettoyé

Cuerpos in/a-propiados: carte-de-visite y las nuevas ciudadanias en la pardocracia venezolana postindependentista - González-Stephan, Beatriz (Memoria y Sociedad, 2013)
En medio del proceso de construcción de la República, durante el siglo xix, en Venezuela los sectores no blancos de la sociedad intentaron legitimarse a través de la fotografía en las carte-de-visite, con el objetivo de ratificar su posición en esta sociedad ‘café con leche’. El uso de esta tecnología, así como la aparición y aceptación de manuales de urbanidad, fueron parte de un proceso en el que estos sectores intentaron ‘modernizarse’, reflejando las tensiones sociales asociadas, por ejemplo, a la dicotomía campo-ciudad o a la necesidad de ‘blanquearse’ ante los ojos de los coterráneos. El objetivo de este trabajo, es estudiar la manera en que el retrato fotográfico y el manual de urbanidad actúan en una sociedad cuyas diferencias y distancias sociales y económicas han sufrido un gran trastorno luego del proceso independentista. During the process of the construction of the Republic, in the 19th Century, non-white sectors of Venezuelan society attempted to legitimise themselves through photographs in their cart-de-visite, with the object of ratifying their position in this ‘coffee and milk’ society. The use of such technology, as well as the introduction and acceptance of urbanity handbooks, were part of a process in which these sectors tried to ‘modernise’, reflecting related social tensions, for example, the urban-rural dichotomy or the need for ‘whitening’ themselves in the eyes of their fellow citizens. The purpose of this paper is to study the way in which photographic portraits and urbanity handbooks act in a society in which social and economic differences and distances have undergone a great upheaval since the independence process.
Keywords: 1-Histoire de l'art; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Étude des représentations; 3-Amérique du Sud (corpus analysé); 4-Amérique du Sud (lieu de production du savoir); 5-Autrice; _Nettoyé

Visionarias de la perspectiva de género en el arte contemporáneo del Caribe colombiano - Flórez, Alexa Cuesta (Memoria y Sociedad, 2017)
La perspectiva de género en el arte del Caribe colombiano se puede contextualizar con el movimiento feminista planetario. La comparación se establece en las creaciones de mujeres artistas de esta región, ya que subvierten, manifiestan y revelan con denotada libertad expresiva, no solamente sus inquietudes intimistas, sino toda una serie de cuestionamientos a las condiciones que culturalmente se le han impuesto a la mujer en el Caribe. Son dos generaciones diferentes; las primeras, analizadas en esta entrega, pueden ser catalogadas como pioneras de la perspectiva de género en el arte colombiano. Las segundas, consolidan problemáticas en apuestas individuales, de manera diaspórica y cada vez más comprometidas con el movimiento social de mujeres. En ambos casos lo hacen a través de las artes visuales, audiovisuales, performáticas e híbridas. Estamos ante artistas vanguardistas, de las artes visuales y performáticas en el Caribe colombiano; preferimos llamarlas, en ambos casos, visionarias. Gender perspective in the Colombian Caribbean art can be contextualized within the worldwide feminist movement. The comparison is established in the artwork of female artists from this region, as they subvert, demonstrate, and reveal with poignant expressive freedom, not only their intimate concerns, but a whole series of questions to the conditions that have been culturally imposed on women in the Caribbean. They come from two different generations. The first generation, analyzed in this installment, can be defined as the pioneers of gender perspective in Colombian art. The second generation consolidates issues through individual pledges in a diasporic way and increasingly committed to the social women’s movement. Both generations do this through performative, hybrid, visual and audiovisual art. These are avant-garde artists of the visual and performative art in the Colombian Caribbean. We prefer to call them, in both cases, visionaries.
Keywords: 1-Histoire de l'art; 2-Approches sociologiques; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 3-Amérique du Sud (corpus analysé); 4-Amérique du Sud (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Créateur.rice PANDC; _Nettoyé

Representaciones del espacio, el tiempo y las mujeres indígenas en fotografías, siglos XIX-XXI - Yujnovsky, Ines (Memoria y Sociedad, 2017)
Este trabajo se propone comprender la incidencia de las relaciones de poder que ciertas representaciones temporales acerca de grupos indígenas pueden ejercer en nuestra comprensión pasada y actual. Diversas imágenes reprodujeron ideas de indígenas que, aunque estuvieran vivos, mostraban una cultura asimilada a un pasado de amplias dimensiones. Por lo tanto, para comprender el proceso de invisibilización de la diversidad indígena en la cultura nacional, es relevante considerar los mecanismos de montaje discursivo —visuales y textuales—, vinculados con las nociones temporales de indios viviendo en un supuesto tiempo remoto. Atendiendo a ello, se analizan los procesos de montaje, desde la producción de las fotografías hasta la edición y presentación de imágenes, tanto en la prensa como en postales, publicaciones científicas y de divulgación, para ver cómo a veces pequeños cambios de encuadre, contraste, retoque o selección pueden incidir en la construcción de diversas historias, en la comprensión y en los sentidos construidos y en pugna.
Keywords: 1-Histoire de l'art; 2-Analyses formalistes; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 3-Amérique du Sud (corpus analysé); 4-Amérique du Sud (lieu de production du savoir); 5-Autrice; _Nettoyé

La temporalidad como política: nación, formas de pasado y perspectivas poscoloniales - Rufer, Mario (Memoria y Sociedad, 2010)
Este artículo discute el concepto de tiempo en la historia-disciplina como una noción política. A partir del análisis de las relaciones entre historia, nación y temporalidad, el autor intenta desentrañar por qué existe una distribución jerárquica de sujetos de la historia y sujetos de la cultura. Estudiando casos concretos de Sudáfrica y Argentina, intenta ver de qué manera esa distribución (incluso resignificada en la “nación multicultural”) impide ver ciertas continuidades en la reproducción de las asimetrías. El trabajo culmina analizando una noción poscolonial de historia como pérdida, como un regimen híbrido de historicidad. This article discusses the concept of time in History (the discipline) as a political notion. Starting with and analysis of the connivences between history, nation and temporality, the author tries to unravel why it operates a hierarchical distribution of “subjets of history” and “subjects of culture”. Dealing with specific cases of South Africa and Argentina, he tries to see how this distribution (even resignified in the “multicultural nation”) prevents to realize certain continuities in the reproduction of asymmetries. This piece of work ends analyzing a postcolonial notion of history as loss, meaning a hybrid regime of historicity.
Keywords: 1-Cinéma; 1-Histoire de l'art; 1-Jeux vidéo; 1-TV; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Afrique (corpus analysé); 3-Amérique du Sud (corpus analysé); 4-Amérique du Sud (lieu de production du savoir); _Nettoyé

Curar el pasado: teoría, curaduría y diálogo en una muestra de arte indígena contemporáneo del Gran Chaco Gualamba - Cantero, Emanuel (Memoria y Sociedad, 2018)
El siguiente artículo es una respuesta a la exposición de arte indígena contemporáneo Gran Chaco Gualamba. Arte, Cosmovisión, Soberanía (Chaco, Argentina; Julio de 2013). Sin desviarse de los propios objetivos de la muestra, problematiza la práctica curatorial como una forma de ver y mostrar a la producción artística de las poblaciones originarias como artefactos significantes íntimamente enlazados con sus formas de vida comunitaria -y no meramente obras de arte autónomas y asépticas de toda función social-. Contrastando las definiciones del equipo de curadoras, el corpus de obras expuestas y el discurso de pobladores originarios, se muestra que este intento por recuperar el nexo orgánico entre arte, cosmovisiones y vida en comunidad resulta trunco, dado que los propios pobladores originarios consideran esta vinculación como una circunstancia históricamente pretérita, previa a los procesos de colonización. Recuperando las luchas presentes de las comunidades, que a falta de ese pasado armonioso plantean su identidad como resistencia necesaria para un futuro distinto – mejor-. This work is a response to a contemporary indigenous art exhibition titled «Gran Chaco Gualamba - Arte, Cosmovisión, Soberanía» (Chaco, Argentina; July 2013). Consistent with the purposes of this exhibition, the article problematizes curatorial practice as a way to present the artistic production of the indigenous populations as significant artifacts intimately involved in the daily community life, and not merely as autonomous artistic objects with no social function. By contrasting the definitions provided by the curatorial team,the corpus of artworks exhibited and the native peoples’ speech, the article shows how the exhibit fails to recover the link between art, cosmovisions and community life because the native populations themselves consider these three spheres as an outdated historical circumstance, previous to the colonization processes. Finally, the current struggles of the communities are mapped which, in the absence of that harmonious past, pose their identity as a necessary resistance for a better future.
Keywords: 1-Histoire de l'art; 2-Histoire/Historiographie critique; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Sud (corpus analysé); 4-Amérique du Sud (lieu de production du savoir); 5-Créateur.rice autochtone; _Nettoyé

Imágenes de lo extraordinario. Memorias de un continente poblado por monstruos. - Gil, Slenka Leandra Botello; Camacho, Daianna Sierra (Cuadernos de Música, Artes Visuales y Artes Escénicas, 2021)
Este trabajo presenta los resultados de la investigación Imágenes de lo extraordinario: monstruos americanos del siglo XVI, proceso de creación artística desarrollado por los estudiantes del Semillero de Investigación en Artes Visuales (SINAV) del programa de Artes Visuales de la Universidad Nacional Abierta y a Distancia (UNAD) entre 2018 y 2019. Para analizar de manera crítica e histórica la construcción de identidades sobre lo latinoamericano, se tomó como marco de análisis la representación de lo monstruoso en los relatos y las imágenes construidas por los cronistas de Indias en el siglo XVI, los cuales marcaron procesos de marginalización cultural, construcción de subjetividades y dinámicas de poder, y presentaron al habitante americano como una otredad que estaba fuera de los límites de la cultura dominante occidental. Se presentan los postulados teóricos sobre lo monstruoso como marco para el análisis histórico y la creación de obra, con una metodología de trabajo colaborativo y en gran parte virtual. Posteriormente, se exponen algunos resultados de la investigación histórica que dan paso a detallar el proceso de creación de obra que culminó con la exposición de la instalación audiovisual Imágenes de lo extraordinario, así como con una amplia serie de ilustraciones contemporáneas sobre lo monstruoso y un producto digital en formato página web donde se presenta una cartografía de lo monstruoso en América Latina y se recogen las memorias de todo el proyecto. This work presents the results of the research Images of the Extraordinary: American Monsters of the 16th Century, artistic creation process developed by the students of the Research Seedbed in Visual Arts (SINAV, for its initials in Spanish) of the Visual Arts program of Universidad Nacional Abierta y a Distancia (UNAD) between 2018 and 2019. With the objective of analyzing, in a critical and historical way, the construction of identities on Latin American matters, the representation of the monstrous in the stories and images constructed by the chroniclers of the Indies in the 16th century was used as a framework of analysis. These chroniclers marked processes of cultural marginalization, construction of subjectivities and power dynamics, and presented the American inhabitant as an otherness that was outside the limits of the dominant Western culture. The theoretical postulates about the monstrous are presented as a framework for historical analysis and the creation of works, with a collaborative and largely virtual working methodology. Some results of the historical research are then presented, which gives way to detailing the process of creating work that culminated in the exhibition of the audiovisual installation Images of the Extraordinary, as well as a wide range of contemporary illustrations on the monstrous and a digital product in web page format where a cartography of the monstrous in Latin America is presented and the memories of the whole project are collected.
Keywords: 1-Histoire de l'art; 2-Histoire/Historiographie critique; 2-Méthodologie de recherche décoloniale; 2-Pédagogie décoloniale; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 3-Amérique centrale (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 4-Amérique du Sud (lieu de production du savoir); _Nettoyé

Memorias americoafricanas en el trabajo de artistas brasileñas contemporáneas - Sardelich, Maria Emilia; Cao, Marian López Fernandez (Cuadernos de Música, Artes Visuales y Artes Escénicas, 2021)
La memoria hace referencia a un conjunto de funciones psíquicas que permiten la actualización de imágenes de hechos pasados o que se representan como pasados. A diferencia de los estudios históricos, los de la memoria resaltan las subjetividades, amplían la discusión más allá del recuerdo y el olvido, y desplazan el debate hacia quien tiene el derecho a narrar su historia y aquellos que en ella se encuentran. Las inquietudes en torno a la memoria y sus lugares también se hacen visibles en el inquieto horizonte artístico, en el que pasados recientes y distantes se articulan en registros sobre diversas formas de traumas. Este artículo propone una reflexión sobre las relaciones entre arte y memoria a partir de la producción de dos artistas brasileñas contemporáneas: Rosana Paulino (São Paulo, 1968) y Aline Motta (Niterói, 1974). El análisis de esa producción se fundamenta en la interdisciplinaridad de los estudios de la memoria y destaca cómo la creación artística ofrece una posibilidad de resignificación individual y colectiva. Asimismo, conceptúa memorias americoafricanas como aquellas que emergen no solo en la memoria individual de las artistas presentadas en este artículo, sino también en la de muchas otras mujeres que se identifican con Americoáfrica como un sistema etnogeográfico de referencia. Son memorias americoafricanas porque se han gestado en la resistencia y creatividad contra la opresión, la humillación y la deshumanización, y que se insurgen contra la historia única proponiendo una revisión de la historiografía del país y del arte producido a partir de esos lugares. Memory refers to a set of psychic functions that allow the updating of images of past events or events that are represented as past. Unlike historical studies, memory studies highlight subjectivities, expand the discussion beyond memory and oblivion, and shift the debate towards who has the right to narrate their history and those who are in it. The concerns about memory and its places also become visible in the restless artistic horizon, in which recent and distant pasts are articulated in registers about various forms of trauma. This paper proposes a reflection on the relationship between art and memory based on the production of two contemporary Brazilian artists: Rosana Paulino (São Paulo, 1968) and Aline Motta (Niterói, 1974). The analysis of this production is based on the interdisciplinary nature of memory studies and highlights how artistic creation offers a possibility of individual and collective resignification. Likewise, it conceptualizes African-American memories as those that emerge not only in the individual memory of the artists presented in this article, but also in that of many other women who identify with Africa-America, as a reference ethnogeographic system. They are African-American memories because they have been born in resistance and creativity against oppression, humiliation and dehumanization, and because they insurrect against the unique history, proposing a review of the historiography of the country and the art produced out of those places.
Keywords: 1-Histoire de l'art; 2-Genre et sexualité; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 3-Amérique du Sud (corpus analysé); 4-Amérique du Sud (lieu de production du savoir); 5-Créateur.rice noir.e; _Nettoyé

Cuerpo, género y representación en el videoarte ecuatoriano (1998-2012) - Mantilla, Christian León (Cuadernos de Música, Artes Visuales y Artes Escénicas, 2016)
Este texto reflexiona sobre los discursos e imaginarios de género y sexualidad que se producen dentro del campo del videoarte realizado en Ecuador entre 1998 y 2013. Desde finales de los noventa, hay una presencia de videos que abordan temáticas de cuerpo, política, deseo, violencia, roles e identidad que posicionan nuevos temáticas, lugares de enunciación y sujetos través de las tecnologías de video. A través de un conjunto de obras emblemáticas, el texto analiza los discursos y las estrategias visuales con las cuales se construyen feminidades, masculinidades y diversidades sexuales en el contexto contemporáneo. Está producción plantea un relato alternativo frente a las tendencias dominantes dentro de la historia del arte ecuatoriano. Muestra las nuevas sensibilidades y sujetos que se afirman a través del uso de tecnologías de video. This paper reflects on the speeches and imaginary of gender and sexuality that occur within the field of video art made in Ecuador between 1998 and 2013. Since the late nineties, there is a presence of vid-eos that address issues of body politics, desire, vio-lence, roles and identity that position new themes, places and subjects of enunciation through video technologies. Through a set of emblematic works, the text analyzes the speeches and visual strategies which femininity, masculinity and sexual diversities are built in a contemporary context. This production presents an alternative story against the dominant trends in the history of Ecuadorian art. It shows the new sensibilities and subjects that are affirmed through the use of video technology.
Keywords: 1-Cinéma; 1-Histoire de l'art; 2-Approches sociologiques; 2-Genre et sexualité; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des représentations; 3-Amérique du Sud (corpus analysé); 4-Amérique du Sud (lieu de production du savoir); 5-Créateur.rice LGBTQ+; _Nettoyé

“Tu vida también es mi país”: sexualidades disonantes y fugas de género en Liliana Felipe y Jesusa Rodríguez - Muelle, Camila Esguerra; Martínez, Alejandra Quintana (Cuadernos de Música, Artes Visuales y Artes Escénicas, 2018)
Este artículo propone una reflexión sobre las prácticas vitales, artísticas y políticas de Liliana Felipe y Jesusa Rodríguez y sus experiencias de desobediencia frente a los regímenes de sexualidad y género articulados a regímenes de terror en México y Argentina. La metodología usada para llegar a la reflexión fue un análisis crítico multimodal del discurso hecho desde una perspectiva interseccional y descolonial que supone el análisis tanto de contextos como de los textos, subtextos y texturas que componen la obra y vida de estas artistas. Desde esta postura epistemológica, la obra performática y musical de Liliana y Jesusa es vista como un acervo de discursos multimodales. Nuestra reflexión muestra cómo la creación, la experiencia —entendida como lugar político— y las propuestas colectivas de Liliana y Jesusa se ponen en juego en un campo de lucha performativa donde sus discursos desobedientes proponen maneras de resistencia y fuga a los regímenes coloniales-modernos- capitalistas de género y sexualidad. Jesusa y Liliana proponen una obra multimodal y multimedial que fisura los límites de los géneros discursivos, los géneros musicales, el género gramatical y el sistema sexo género, lo cual amerita una mirada indisciplinada. Este artículo resulta ser un abordaje novedoso en la medida en que se acerca a la experiencia y a la obra de estas dos mujeres, no desde una visión disciplinar, sino a partir de una mirada transdisciplinaria, interseccional y descolonial que asume la producción artística como una apuesta política donde los límites entre lo personal y lo público se borran. This article seeks to do a reflection both on the vital, artistic and political practices of Liliana Felipe and Jesusa Rodríguez and on their experiences of disobedience to the regimes of sexuality and gender, which are articulated to regimes of terror in Mexico and Argentina. The methodology used in order to make this reflection was a Multimodal Critical Discourse Analysis from both an intersectional and decolonial perspective. This methodology implies the analysis of contexts, texts, subtexts and textures that make up the work and life of these artists. From this epistemological position, the performative and musical work of Liliana and Jesusa is seen as a collection of multimodal discourses. Creation, experience —understood as a political locus— and the collective proposals of Liliana and Jesusa are put into play in a field of performative struggle where their disobedient discourses propose ways of resistance to colonial-modern-capitalist regimes of gender and sexuality.Jesusa and Liliana propose a multimodal and multimedial work that fissures the limits of the discursive genres, the musical genres, the grammatical gender and the gender sex system, which deserves an undisciplined look. This article proposes an original approach insofar as it approaches the experience and work of these two women not from a disciplinary view, but from a transdisciplinary, intersectional and decolonial point of view, that assumes artistic production as a political commitment in where the boundaries between the personal and the public are erased.
Keywords: 1-Histoire de l'art; 2-Genre et sexualité; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Sud (corpus analysé); 4-Amérique du Sud (lieu de production du savoir); 5-Créateur.rice LGBTQ+; _Nettoyé

Procesos de invención decoloniales sobre visualidades indígenas. Hacia una reconfiguración de los imaginarios hegemónicos en el nordeste argentino - Reyero, Alejandra; Navas, Maia (Cuadernos de Música, Artes Visuales y Artes Escénicas, 2021)
El objetivo del artículo es discutir la potencialidad de prácticas artísticas contemporáneas que plantean ejercicios decoloniales al desestabilizar las matrices perceptivas eurocéntricas sobre grupos étnicos latinoamericanos. Desde la perspectiva de los estudios visuales, aborda la tentativa de demolición crítica de la cultura visual y los regímenes de visibilidad regidos por la lógica de la hipercomunicación y las tecnologías digitales. El punto de partida es el análisis del videoensayo Ashipegaxanacxanec iniciado en 2020 a partir de las acciones de control implementadas en la pandemia de covid-19. La producción se inscribe en las líneas de investigación del Núcleo de Estudios y Documentación de la Imagen (Nedim), Conicet-UNNE, con la finalidad de resignificar el acervo fotográfico del antropólogo alemán Lehmann Nitsche obtenido en el contexto de la masacre indígena en la Reducción de Napalpí, Chaco, en 1924. Metodológicamente, la propuesta explora la configuración experiencial de visualidades expandidas en la escena contemporánea, a partir de un anclaje en la dimensión especulativa en sintonía con un acercamiento contextual situado en las relaciones de convergencia entre pro- cedimientos, materiales, formatos, dispositivos e instancias disruptivas de prácticas y trayectorias estéticas. Ello supone la activación de procesos heurísticos y poéticos mediados por el ensayo y la escritura como montaje. Propuestas como el videoensayo analizado instauran la pregunta por el archivo y la memoria a través del montaje de temporalidades contradictorias. Su lugar de enunciación se posiciona como posibilidad de insurgencia estética que clausura tentativas de exotización hegemónica por parte de los dispositivos de control contemporáneos. The goal of this paper is to discuss the potentiality of contemporary artistic prac-tices that propose decolonial exercises by destabilizing the Eurocentric perceptual matrices on Latin American ethnic groups. From the perspective of visual studies, it addresses the attempt to critically demolish visual culture and the regimes of visibility governed by the logic of hypercommunication and digital technologies. The starting point is the analysis of the Ashipegaxanacxanec video essay started in 2020 based on the control actions implemented in the COVID-19 pandemic. The production is part of the research of the Image Studies and Documentation Center (Nedim), Conicet-UNNE, with the purpose of redefining the photographic collection of German anthropologist Lehmann Nitsche, obtained in the context of the indigenous massacre in the Napalpí reduction in Chaco, in 1924. Methodologi-cally, the proposal explores the experiential configuration of expanded visualities in the contemporary scene, based on an anchoring in the speculative dimension in tune with a contextual approach in the convergence relationships between proce-dures, materials, formats, devices and disruptive instances of practices and aes-thetic trajectories. This supposes the activation of heuristic and poetic processes mediated by essays and writing as montage. Proposals such as the analyzed video essay establish the question about the archive and memory through the montage of contradictory temporalities. Its place of enunciation is positioned as a possibili-ty of aesthetic insurgency that closes any attempts at hegemonic exoticization by contemporary control devices
Keywords: 1-Cinéma; 1-Histoire de l'art; 2-Analyses formalistes; 2-Histoire/Historiographie critique; 2-Humanités numériques; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Sud (corpus analysé); 4-Amérique du Sud (lieu de production du savoir); 5-Autrice; _Nettoyé

Shekuita o el mal trueno: documental performativo, conflictos ontológicos y descolonización de lo real - Rincón, Juan Carlos Valencia; Hoyos, Paula Andrea Restrepo (Cuadernos de Música, Artes Visuales y Artes Escénicas, 2021)
Este artículo analiza las implicaciones ontológicas y el carácter performativo del documental Shekuita o el mal trueno, lanzado en 2017 por un colectivo de producción audio- visual indígena wiwa en la Sierra Nevada de Santa Marta en Colombia. El documental explora las causas, dudas y consecuencias de un triste incidente ocurrido tres años antes: la caída de un rayo sobre una edificación ceremonial de los wiwas, que causó la muerte a casi una docena de líderes. A partir del contraste entre las explicaciones científicas de la tragedia y las que han investigado las autoridades espirituales de la comunidad desde sus ontologías relacionales, y basándonos en un trabajo de campo cuasietnográfico durante el proceso de filmación, buscamos dar cuenta de un caso específico de descolonización de lo real y de los esfuerzos de una comunidad indígena por la libre expresión y la representación autónoma. Encontramos que este documental abre puertas de forma artística a mundos otros, contados en clave insumisa desde una indigenidad que nos interpela. Concluimos que los wiwas performan un realidad que no necesariamente es la que vivieron, sino una que les permite estratégicamente alcanzar más fácilmente la realidad que quieren recuperar. El artículo intenta contribuir a la visibilización de otras ontologías distintas de la naturalista, a mostrar las autocríticas de esta y a manifestar cómo el audiovisual es un espacio propicio para descolonizar lo real. This paper analyzes the ontological implications and the performative nature of the documentary Shekuita o el mal trueno, released in 2017 by a Wiwa indigenous audiovisual production group in Sierra Nevada de Santa Marta, Colombia. The do-cumentary explores the causes, doubts and consequences of a sad incident that happened three years earlier: a lightning strike on a Wiwas ceremonial building, which killed nearly a dozen leaders. Based on the contrast between the scientific explanations of the tragedy and those that the spiritual authorities of the community have investigated according to their relational ontologies and based on a quasi-eth-nographic fieldwork during the filming process, we seek to account for a specific case of decolonization of reality and of the efforts of an indigenous community for free expression and autonomous representation. We find that this documentary opens doors to other worlds in an artistic way, told in an unsubmissive way by an indigenous community that challenges us. We conclude that the Wiwa perform a reality that is not necessarily the one they lived through, but one that strategically allows them to reach the reality they want to recover more easily. The paper at-tempts to contribute to the visibility of other ontologies other than the naturalistic one, to show self-criticism of it and to show how the audiovisual is a propitious space to decolonize reality.
Keywords: 1-Cinéma; 1-Histoire de l'art; 2-Recherche-création; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 2-Étude des représentations; 3-Amérique du Sud (corpus analysé); 4-Amérique du Sud (lieu de production du savoir); 5-Créateur.rice autochtone; _Nettoyé

The Limits of Feminism: Decolonizing Women's Liberation/Oppression Theory - Kuumba, Monica Bahati (Race, Sex & Class, 1994)
Keywords: 1-Cinéma; 1-Histoire de l'art; 1-Jeux vidéo; 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; _Nettoyé

Genealogías críticas de la colonialidad en América Latina, África, Oriente - Segato, [et al.], Rita Laura (Universidad Nacional de San Martín, 2016)
El espesor de este libro es propio de este tiempo. Cuerpos que se desplazan en masivas inmigraciones huyendo de todo tipo de violencias alcanzan a más de sesenta millones de personas, la mayor cifra de refugiados desde la segunda guerra mundial. El mundo experimenta una crisis humanitaria sobrecogedora ante la cual las potencias apelan a los mismos discursos que ya Aimé Césaire o Fanon condenaran. Dramatismo del exilio de este nomadismo a escala planetaria, al cual Stuart Hall calificaría como “amensia imperial”. Genealogías críticas de la colonialidad en América Latina, África, Oriente es un libro que deja al descubierto la piel del mundo contemporáneo. Un hecho cultural disruptivo que, anudado a una genealogía latinoamericana abierta a sí misma y hacia Otros Sures se interroga sobre los intrincados modos de narrar y silenciar los pasados coloniales.
Keywords: 1-Cinéma; 1-Histoire de l'art; 1-Jeux vidéo; 1-TV; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Afrique (corpus analysé); 3-Amérique centrale (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 3-Asie (corpus analysé); 4-Amérique du Sud (lieu de production du savoir); _Nettoyé

Coloniality of Power, Eurocentrism, and Latin America - Quijano, Anibal (Nepantla: Views from South, 2000)
What is termed globalization is the culmination of a process that began with the constitution of America and colonial/modern Eurocentered capitalism as a new global power. One of the fundamental axes of this model of power is the social classification of the world’s population around the idea of race, a mental construction that expresses the basic experience of colonial domination and pervades the more important dimensions of global power, including its specific rationality: Eurocentrism. The racial axis has a colonial origin and character, but it has proven to be more durable and stable than the colonialism in whose matrix it was established. Therefore, the model of power that is globally hegemonic today presupposes an element of coloniality. In what follows, my primary aim is to open up some of the theoretically necessary questions about the implications of coloniality of power regarding the history of Latin America.
Keywords: 1-Cinéma; 1-Histoire de l'art; 1-Jeux vidéo; 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Sud (corpus analysé); 3-Europe (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 4-Amérique du Sud (lieu de production du savoir); _Nettoyé

Interview with author, Dr. Laura Pérez - Ramirez, Abraham
Interview with author, Dr. Laura Pérez, Professor of Ethnic Studies at UC Berkeley on her most recent book, Eros Ideologies: Writings on Art, Sprituality, & the Decolonial.
Related with the book "Eros ideologies. Writings on art, spirituality, and the decolonial" of Laura Pérez
Keywords: 1-Histoire de l'art; 2-Approches sociologiques; 2-Genre et sexualité; 2-Méthodologie de recherche décoloniale; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 3-Amérique centrale (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Créateur.rice LGBTQ+; 5-Créateur.rice PANDC; _Nettoyé

Eros ideologies. Writings on art, spirituality, and the decolonial. - Perez, Laura E (Duke University Press, 2019)
In 'Eros Ideologies' Laura E. Perez explores the decolonial through Western and non-Western thought concerning personal and social well-being. Drawing upon Jungian, people-of-color, and spiritual psychology alongside non-Western spiritual philosophies of the interdependence of all life-forms, she writes of the decolonial as an ongoing project rooted in love as an ideology to frame respectful coexistence of social and cultural diversity. In readings of art that includes self-portraits by Frida Kahlo, Ana Mendieta, and Yreina D. Cervantez, the drawings and paintings of Chilean American artist Liliana Wilson, and Favianna Rodriguez's screen-printed images, Perez identifies art as one of the most valuable laboratories for creating, imagining, and experiencing new forms of decolonial thought. Such art expresses what Perez calls eros ideologies: understandings of social and natural reality that foreground the centrality of respect and care of self and others as the basis for a more democratic and responsible present and future. Employing a range of writing styles and voices-from the poetic to the scholarly-Perez shows how art can point to more just and loving ways of being.
Related with the Podcast "Interview with author, Dr. Laura Pérez"
Keywords: 1-Histoire de l'art; 2-Approches sociologiques; 2-Genre et sexualité; 2-Méthodologie de recherche décoloniale; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 3-Amérique centrale (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Créateur.rice LGBTQ+; 5-Créateur.rice PANDC; _Nettoyé

Revista N'oj Panel on Decolonizing Aesthetics - Latinx Research Center (2020)
The Latinx Research Center's Revista N'oj hosted a round table discussion on Decolonial Aesthetics titled, "Decolonizing Art & Praxis in the Time of Covid-19." The talk included Jesus Barraza, Dr. Guisela Latorre, Dr. Mauricio Barros de Castro, and Dr. Laura E. Pérez. The panel was moderated by Revista N'oj editor, Abraham Ramirez.
Revista N'oj : Issue No.2 (2020) Event was sponsored by the Latinx Research Center at the University of California, Berkeley
Keywords: 1-Histoire de l'art; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique centrale (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 4-Amérique du Sud (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Créateur.rice PANDC; _Nettoyé

Orientalismo, poscolonialidad y conocimientos de otro modo: bases, críticas, silencios y continuidades para una discusión político-cultural en el contexto latinoamericano - Estrada, Edwin Jader Suaza (Revista de Estudiantes de Ciencia Política, 2016)
La perspectiva de la modernidad/colonialidad provee un encuadre alternativo para los debates sobre la modernidad, la globalización y el desarrollo desde la periferia latinoamericana del sistema mundo moderno colonial. Las ideas que se exponen en el presente artículo, proporcionan un guía de lectura frente a los principales rasgos del entramado conceptual que rodea a este lugar de enunciación del conocimiento. La perspectiva modernidad/colonialidad aporta una reflexión sobre la cultura y diferentes planos de la realidad social y política, nutrida en debates académicos sustentados no desde una perspectiva intra-epistémica, como los discursos críticos europeos, sino desde la mirada de los receptores de los supuestos beneficios del mundo moderno. Se presenta así un contexto para interpretar Latinoamérica, entendida más como un espacio epistémico y de producción de conocimiento, que como una región objeto de conocimientos pre-establecidos.
Keywords: 1-Cinéma; 1-Histoire de l'art; 1-Jeux vidéo; 1-TV; 2-Histoire/Historiographie critique; 2-Méthodologie de recherche décoloniale; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 3-Amérique du Sud (corpus analysé); 4-Amérique du Sud (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé

Marta Rodríguez, descolonizando la representación documental latinoamericana - Moreno, Pedro Pablo Gómez (Estudios Artísticos, 2017)
En esta conversación entre la cineasta documental Marta Rodríguez y Pedro Pablo Gómez, antes que hacer un recorrido cronológico por el trabajo la artista, se abordan problemas tranversales que están presentes a lo largo de su obra: el cine documental como modo de representación; la construcción de una metodología del cine documental latinoamericano; el carácter decolonial de la obra de Rodríguez y su compromiso indeclinable durante más de cuatro décadas de acompañar las luchas de campesinos, indígenas y afrodescendientes, entre otros. Y es en este abordaje donde Marta Rodríguez, haciendo uso de una memoria extraordinaria, puede tejer un relato en el que se destaca la ética de la artista y su compromiso indeclinable de denuncia de las injusticias sociales, utilizando las tecnologías del cine, no para hablar por las víctimas, sino para hacer escuchar sus voces y mantener vivas sus imágenes; unas imágenes que interpelan el discurso colonial mediante el cual se ha tejido nuestro relato de nación. Dans cette conversation entre la cinéaste documentaire Marta Rodríguez et Pedro Pablo Gómez, avant d'entreprendre une tournée chronologique de l'œuvre de l'artiste, nous traitons les problèmes transversaux présents tout au long de son travail : le cinéma documentaire comme mode de représentation ; la construction d'une méthodologie du documentaire latino-américain; la nature décoloniale de l'œuvre de Rodríguez et son engagement pendant plus de quatre décennies pour accompagner les luttes des paysans, des indigènes et des Afro-descendants, entre autres. Et c'est dans cette approche que Marta Rodríguez, avec une mémoire extraordinaire, peut tisser une histoire qui souligne l'éthique de l'artiste et son engagement indécelable à dénoncer les injustices sociales, en utilisant les technologies du cinéma –pour ne pas parler en lieu des victimes, mais pour faire entendre leur voix et garder leurs images vivantes. Des images qui contestent le discours colonial par lequel notre récit de nation a été tissé.
Keywords: 1-Cinéma; 1-Histoire de l'art; 2-Histoire/Historiographie critique; 2-Méthodologie de recherche décoloniale; 2-Recherche-création; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 3-Amérique du Sud (corpus analysé); 4-Amérique du Sud (lieu de production du savoir); 5-Créatrice; _Nettoyé

“Estética(s) decolonial(es)1”: entrevista a Pedro Pablo Gómez - Vasquez, Angélica González; Zacarias, Gabriel Ferreira (Estudios Artísticos, 2016)
En esta conversación se indaga por la cuestión decolonial de la estética, sus puntos de origen históricos y geográficos, además de sus posibilidades en el contexto de reconfiguración actual del orden mundial. Desde esta perspectiva, se pretende aclarar en qué consiste la opción decolonial, respecto de otras opciones, sin olvidar cuestiones importantes del arte, la historia, el museo, la curaduría y sus implicaciones éticas, políticas y epistémicas. Cette conversation touche à la question de l’esthétique décoloniale, de ses points d’origine historiques et géographiques et de ses possibilités dans le contexte de la reconfiguration actuelle de l’ordre mondial. Dans cette perspective, l’objectif est de clarifier l’option décoloniale par rapport à d’autres options — sans oublier les questions importantes de l’art, de l’histoire, des musées, de la mission du curateur — et ses implications éthiques, politiques et épistémiques.
Texte en français : https://journals.openedition.org/marges/1207
Keywords: 1-Cinéma; 1-Histoire de l'art; 1-Jeux vidéo; 1-TV; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des industries culturelles; 4-Amérique du Sud (lieu de production du savoir); _Nettoyé

Orientalism - Said, Edward W (Penguin Books, 2019)
A groundbreaking critique of the West's historical, cultural, and political perceptions of the East that is—three decades after its first publication—one of the most important books written about our divided world. "Intellectual history on a high order ... and very exciting." —The New York Times In this wide-ranging, intellectually vigorous study, Said traces the origins of "orientalism" to the centuries-long period during which Europe dominated the Middle and Near East and, from its position of power, defined "the orient" simply as "other than" the occident. This entrenched view continues to dominate western ideas and, because it does not allow the East to represent itself, prevents true understanding. Source: Publisher
Keywords: 1-Cinéma; 1-Histoire de l'art; 1-Jeux vidéo; 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 3-Afrique (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Europe (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé

La relación: pauta epistémica de la decolonialidad del saber desde el pensamiento afroantillano Los contornos del concepto en el Tratado del Todo-Mundo de Édouard Glissant (1928-2011) - Juncosa, José Enrique (Estudios Artísticos, 2016)
El presente artículo rastrea y explora el sentido poético y las posibilidades epistémicas del término relación a partir de la obra Tratado del todo-mundo, de Édouard Glissant, asumida como aporte del pensamiento afroantillano al proyecto del giro decolonial de los estudios interculturales latinoamericanos. En un primer momento, se identifican los rasgos y contornos operatorios de la identidad relación a partir de las siguientes claves de lectura: imaginería, poética y retórica, espiritualidad y ética, política y epistémica. En el segundo momento, se identifican las conexiones e implicaciones más relevantes para el contexto andino. De la exploración, se desprende que el pensamiento afrocaribeño de Glissant, contribuye a generar posibilidades discursivas potentes para enriquecer identidades abiertas en su diferencia y prácticas epistémicas sin amurallamientos identitarios o ilusiones uniformizantes. Finalmente, el aporte de Glissant, ofrece espacios de búsquedas a los movimientos sociales andinos para enriquecer sus prácticas de identidad en tanto relación, más allá de los esencialismos y la pretensión de raíz única. Cet article retrace et explore le sens poétique et les possibilités épistémiques du terme relation dans le traité d’Édouard Glissant, Traité du Tout-Monde, en tant que contribution afro-antillaise au projet du virage décolonial dans les études interculturelles latino-américains. Premièrement, nous identifions les traits et les contours opératoires de l›identité relationnelle à partir de clés suivantes : imagerie, poétique et rhétorique, spiritualité et éthique, politique et épistémique. Les liens les plus pertinents et les implications pour le contexte andin sont alors identifiés. De cette exploration, il est clair que la pensée afro-antillaise de Glissant contribue à générer de puissantes possibilités discursives pour enrichir des identités ouvertes dans leurs différences et leurs pratiques épistémiques, sans de murs identitaires ni d’illusions normalisatrices. Enfin, la contribution de Glissant ouvre des espaces de recherche pour les mouvements sociaux andins afin d’enrichir leurs pratiques d’identité en tant que relation, au-delà des essentialismes et de la prétention d’une seule origine.
Keywords: 1-Cinéma; 1-Histoire de l'art; 1-Jeux vidéo; 1-TV; 2-Approches sociologiques; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique centrale (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 4-Amérique du Sud (lieu de production du savoir); 5-Créateur.rice PANDC; _Nettoyé

Imaginarios y estrategias decoloniales - Ferrera-Balanquet, Raúl Moarquech (Estudios Artísticos, 2018)
Enunciando el delinking de la matriz moderna/ colonial, este artículo imagina un territorio crítico teórico creativo partiendo de la aesthesis decolonial con el fin de dialogar con una serie de hacedores culturales que emplean estrategias creativas decoloniales en proyectos creativos. Un acercamiento a la exposición Haceres Decoloniales (2015) realizada en Bogotá, ofrece la oportunidad de conversar sobre el hacer creativo de Benvenuto Chavajay, Rosa Tisoy Tandoy y Marco Alonso Roa. Los efectos de la colonialidad sonora conllevan a dialogar con la artista maya k´iche Sandra Monterroso y el creador maya yucateco Isaac Carrillo Can. Discursamos sobre el proyecto Espejo Negro (2010) de Pedro Lasch y el mural Las Aguas Sagradas de La Llorona (2004) de la artista xicana Juana Alicia. Terminamos con una interpretación crítica sobre el proyecto Mariposa Memoria Ancestral (2013-2015), y el performance multidisciplinario Whip It Good (2013) de la artista danesa trinitobaguense Jeannette Ehlers. En reliant la déconnexion de la matrice moderne / coloniale, cet article imagine un territoire créatif- théorique-critique à partir de l’aesthésis décoloniale, afin de dialoguer avec une série d’acteurs culturels qui utilisent des stratégies décoloniales créatives dans des projets créatifs. Une approche de l’exposition Haceres Decoloniales (2015) tenue à Bogotá, offre l’occasion de parler du travail créatif de Benvenuto Chavajay, Rosa Tisoy Tandoy et Marco Alonso Roa. Les effets de la colonialité sonore impliquent un dialogue avec l’artiste maya k’iche Sandra Monterroso et le créateur maya yucatècque Isaac Carrillo Can. Nous parlons du projet Espejo Negro (2010) de Pedro Lasch et de la peinture murale Las Aguas Sagradas de La Llorona (2004) de l’artiste chicane Juana Alicia. Nous terminons avec une interprétation critique du projet Mariposa Memoria Ancestral (2013-2015) et la performance pluridisciplinaire Whip It Good (2013) de l’artiste danois né en Trinité-et-Tobago Jeannette Ehlers.
Keywords: 1-Histoire de l'art; 2-Approches sociologiques; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Afrique (corpus analysé); 3-Amérique du Sud (corpus analysé); 4-Amérique du Sud (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Créateur.rice PANDC; 5-Créateur.rice noir.e; _Nettoyé

Only Skin Deep: Changing Visions of the American Self - Fusco, Coco; Wallis, Brian (Abrams and International Center of Photography, 2003)
"By bringing together a provocative selection of essays and images, Only Skin Deep: Changing Visions of the American Self addresses the issues of nation, race, and selfhood and how they are depicted in ways that are challenging and informative, prompting readers to consider the impact of photography on our everyday lives." "If photographs are chiefly responsible for perpetuating myths of American identity, can a different reading of these representations break down distorting stereotypes? This is the central question posed by Only Skin Deep. The authors in this book forcefully argue that race and nation - and, indeed, photography itself - are fictions, cultural constructions that shape our social interactions. Even as symbols, these photographic depictions of ethnic difference and cultural superiority have very real consequences. This collection of works and essays addresses, for example, the lingering consequences of American colonial expansion; the conflict between public and private visualizations of individuals; the role of commercial imagery in shaping gender roles; the impact of fantasy in ethnic or ethnographic photography; and the uses of science to provide justification for politicized depictions of "race."" "Accompanying a major exhibition of the same name, Only Skin Deep offers a critical rereading of the archive of the history of photography. This applies to the works of famous photographers - such as Dorothea Lange, Walker Evans, Ansel Adams, and Edward Steichen - as well as lesser-known historical figures, including Charles Eisenmann, Frances Benjamin Johnston, Will Soule, and Toyo Miyatake. A substantial part of the book is devoted to contemporary artists and photographers who have moved beyond the multicultural approach to representations of "race" and have made an investigation of the semiotics of cultural identity a prevalent theme over the past decade. Among the recent photographers included are: Nancy Burson, Nikki S. Lee, Glenn Ligon, Paul Pfeiffer, Hulleah Tsinhnahjinnie, Cindy Sherman, Lorna Simpson, and Andres Serrano."–(BOOK JACKET)
Keywords: 1-Histoire de l'art; 2-Approches sociologiques; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Créateur.rice PANDC; 5-Créateur.rice noir.e; _Nettoyé

African American Art and Artists - Lewis, Samella (University of California Press, 2003)
Samella Lewis has brought African American Art and Artists fully up to date in this revised and expanded edition. The book now looks at the works and lives of artists from the eighteenth century to the present, including new work in traditional media as well as in installation art, mixed media, and digital/computer art. Generously and handsomely illustrated, the book continues to reveal the rich legacy of work by African American artists.
Keywords: 1-Histoire de l'art; 2-Analyses formalistes; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Créateur.rice PANDC; 5-Créateur.rice noir.e; _Nettoyé

Ain't I a Woman Black Women and Feminism - hooks, bell (Routledge, 2015)
This landmark work of history and theory challenges every accepted notion about the nature of black women’s lives. Ain’t I A Woman examines the impact of sexism on black women during slavery, the historic devaluation of black womanhood, black male sexism, racism within the recent women’s movement, and black women’s involvement with feminism. hooks refutes the antifeminist claim that black women are not victims of sexist oppression nor in need of an autonomous women’s movement. She pushes feminist dialogue to new limits by claiming that all progressive struggles are significant only when they take place within a broadly defined feminist movement which takes as its starting point that race, class, and sex are immutable facts of human existence. bell hooks’ insight as a black woman and a feminist extends the scope of feminist theory and practice for us all, and marks the emergence of a revitalized feminism in the 1980s.
Keywords: 1-Cinéma; 1-Histoire de l'art; 1-Jeux vidéo; 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; _Nettoyé

Black Looks: Race and Representation - hooks, bell (Routledge, 2015)
"In the critical essays collected in Black Looks, bell hooks interrogates old narratives and argues for alternative ways to look at blackness, black subjectivity, and whiteness. Her focus is on spectatorship–in particular, the way blackness and black people are experienced in literature, music, television, and especially film–and her aim is to create a radical intervention into the way we talk about race and representation. As she describes: 'The essays in Black Looks are meant to challenge and unsettle, to disrupt and subvert.' As students, scholars, activists, intellectuals, and any other readers who have engaged with the book since its original release in 1992 can attest, that's exactly what these pieces do"(Provided by publisher)
Keywords: 1-Cinéma; 1-Histoire de l'art; 1-Jeux vidéo; 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; _Nettoyé

L'Atlantique noir: modernité et double conscience - Gilroy, Paul (Éditions Amsterdam, 2010)
Qu'est-ce que l'identité noire ? Contre ceux qui en défendent une conception ethniciste ou nationaliste, ou qui cherchent avant tout à en préserver l'authenticité, Paul Gilroy montre comment cette identité complexe, nourrie d'une diversité irréductible, repose sur l'existence d'un espace transnational en constante transformation, qui n'est pas spécifiquement africain, américain, caribéen ou britannique, mais tout cela à la fois : l'Atlantique noir. L'objet de ce livre est de donner à voir l''existence de cet espace constitué dès le XVIIe siècle à travers l'histoire de la traite négrière, de retracer ce réseau serré de relations, d'échanges à multiples sens, d'idées, d'hommes et de productions culturelles. Au fil de pages peuplées par les figures les plus hétéroclites, de Spike Lee à Walter Benjamin en passant par les Jubilee Singers, Richard Wright, W. E. B. Du Bois, Jimi Hendrix, Wynton Marsalis et Hegel, l'espace et le temps singuliers de l'Atlantique noir prennent forme et consistance de façon saisissante. La musique, mode d'expression de prédilection d'une culture enracinée dans l'expérience des terreurs indicibles de l'esclavage, avec ses usages et ses allers-retours inattendus d'un bord à l'autre de l'Atlantique, joue ici un rôle de premier plan. Le retour sur l'esclavage et son caractère intrinsèquement moderne, opéré dans les oeuvres de nombreux écrivains noirs, ouvre par ailleurs à une relecture critique de la modernité, d'une portée universelle, au même titre que la critique des conceptions figées et réductrices de l'identité.
Keywords: 1-Cinéma; 1-Histoire de l'art; 1-Jeux vidéo; 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 3-Afrique (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Europe (corpus analysé); 4-Europe (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Identités diasporiques; _Nettoyé

Harlem Renaissance Art of Black America. - Driskell, David C; Lewis, David Levering; Willis, Deborah (ABRAMS, 1987)
In the 1920s, Harlem was the capital of Black America and home to an epochal African-American cultural flowering called the Harlem Renaissance. This book presents the work of the most important visual artists of the day, including Meta Warrick Fuller, Aaron Douglas and Palmer Hayden.
Keywords: 1-Histoire de l'art; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); _Nettoyé

Race and History: Selected Essays 1938-1988 - Franklin, John Hope (Louisiana State University Press, 1992)
John Hope Franklin, one of the US's foremost historians, collects twenty-seven of his most influential shorter writings. The essays are presented thematically and include pieces on southern history; significant but neglected historical figures; historiography; and the connection between historical problems and contemporary issues.
Keywords: 1-Cinéma; 1-Histoire de l'art; 1-Jeux vidéo; 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé

Black Art: Ancestral Legacy : The African Impulse in African-American Art. - Dallas Museum of Art (Dallas Museum of Art, 1990)
For the first time, a major exhibition examines the impact of African culture on black artists, both trained and self-taught, in a stunning range of 157 works which are variously bold, witty, historical, and mysterious. 49 biographical outlines; 320 illustrations, 170 in full color.
Keywords: 1-Histoire de l'art; 2-Approches sociologiques; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude de la réception; 3-Afrique (corpus analysé); 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Créateur.rice PANDC; 5-Créateur.rice noir.e; _Nettoyé

Collecting African American Art: the Museum of Fine Arts, Houston - Franklin, John Hope; Wardlaw, Alvia J (Museum of Fine Arts ; Yale University Press, 2009)
This important book showcases institutional and private efforts to collect, document, and preserve African American art in American's fourth largest city, Houston, Texas. Eminent historian John Hope Franklin's essay reveals his passionate commitment to collect African American art, while curator Alvia J. Wardlaw discusses works by Robert S. Duncanson, Henry Ossawa Tanner, Horace Pippen, and Bill Traylor as well as pieces by contemporary artists Kojo Griffin and Mequitta Ahuja. Quilts, pottery, and a desk made by an African American slave for his daughter contribute to the overview. The book also focuses on the collections of the "black intelligentsia," African Americans who taught at black colleges like Fisk University, where Aaron Douglas founded the art department. A number of the artists represented were collected privately before they were able to exhibit in mainstream museums.
Keywords: 1-Histoire de l'art; 2-Analyses formalistes; 2-Histoire/Historiographie critique; 2-Muséologie critique; 2-Méthodologie de recherche décoloniale; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Créateur.rice PANDC; _Nettoyé

Videojuegos y arte. Primeras manifestaciones de Game Art en Argentina - Jacobo, Mónica (Cuadernos del Centro de Estudios de Diseño y Comunicación Nº41, 2012)
A partir de indagaciones precedentes1 sobre cuestiones como la interactividad y la interfaz presentes en obras realizadas con tecnología digital, este texto realiza una exploración sobre los videojuegos como objetos populares interactivos y sus posibilidades artísticas, procurando contribuir a la construcción de la teoría y práctica en este campo emergente en el contexto local. La perspectiva que articula este trabajo, procura hacer visibles obras de arte producidas en Argentina plausibles de ser ubicadas bajo el campo denominado Game Art, el cual aglutina diferentes producciones en torno al videojuego, reflexionando sobre este como medio y objeto cultural. Esta área de tensiones y cruces vincula a las producciones tradicionales con las digitales, a la práctica denominada Fan Art 2 y al arte culto. Su formación comienza en los últimos años del siglo XX y primeros del Siglo XXI surgiendo esporádicamente en festivales de arte digital e Internet y posteriormente adquiriendo mayor visibilidad con exposiciones temáticas en museos y galerías.
Keywords: 1-Jeux vidéo; 2-Étude des industries culturelles; 3-Amérique du Sud (corpus analysé); 5-Autrice; _Nettoyé; _À analyser; _À nettoyer

The Interactive Past: Archaeology, Heritage & Video Games - Mol, Angenitus Arie Andries; Ariese-Vandemeulebroucke, Csilla E.; Boom, Krijn; Politopoulos, Aris (Sidestone Press., 2017)
Video games, even though they are one of the present's quintessential media and cultural forms, also have a surprising and many-sided relation with the past. From seminal series like Sid Meier's Civilization or Assassin's Creed to innovative indies like Never Alone and Herald, games have integrated heritages and histories as key components of their design, narrative, and play. This has allowed hundreds of millions of people to experience humanity's diverse heritage through the thrill of interactive and playful discovery, exploration, and (re-)creation. Just as video games have embraced the past, games themselves are also emerging as an exciting new field of inquiry in disciplines that study the past. Games and other interactive media are not only becoming more and more important as tools for knowledge dissemination and heritage communication, but they also provide a creative space for theoretical and methodological innovations. The Interactive Past brings together a diverse group of thinkers – including archaeologists, heritage scholars, game creators, conservators and more – who explore the interface of video games and the past in a series of unique and engaging writings. They address such topics as how thinking about and creating games can inform on archaeological method and theory, how to leverage games for the communication of powerful and positive narratives, how games can be studied archaeologically and the challenges they present in terms of conservation, and why the deaths of virtual Romans and the treatment of video game chickens matters. The book also includes a crowd-sourced chapter in the form of a question-chain-game, written by the Kickstarter backers whose donations made this book possible. Together, these exciting and enlightening examples provide a convincing case for how interactive play can power the experience of the past and vice versa. Source: Publisher
Section: 1 v. (235 p.) : illustrations en coul. ; 27 cm
Keywords: 1-Jeux vidéo; 2-Histoire/Historiographie critique; 2-Humanités numériques; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 2-Étude des représentations; 4-Amérique du Nord (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Autrice; _Nettoyé

Problématiques de l'imaginaire du Nord en littérature, cinéma et arts visuels - Bouchard, Joë; Chartier, Daniel; Nadeau, Amélie (Département d'études littéraires, UQÀM, 2004)
Conçu comme un discours et non comme un simple référent géographique, le Nord se déploie dans des formes littéraires et culturelles qui en déterminent les particularités. Pluriculturel, variable selon les époques, les lieux et les points de vue, le Nord ouvre des problématiques sur les liens entre le référent et la représentation, entre le discours et l'imaginaire. Qu'il soit scandinave, québécois, finlandais, inuit ou européen, qu'il se manifeste dans les récits, les films, les romans, la poésie, la photographie ou les arts visuels, qu'il soit le lieu d'une dénonciation post-coloniale ou d'un discours impérialiste, d'une recherche formelle ou de l'expression de la culture populaire, le discours du Nord et sur le Nord converge en des paradigmes et des problématiques qui lui sont propres. Dans ce recueil, issu des travaux du Laboratoire international d'étude multidisciplinaire comparée des représentations du Nord et initié par la tenue d'un colloque organisé en décembre 2003 par Joël Bouchard et Amélie Nadeau, le lecteur trouvera quelques pistes d'analyse pour saisir la complexité du système discursif du Nord, réparties en trois sections intitulées: «Formes et intertextualité», «Territoires», ainsi que «Iconographie, voyages, et cinéma».
Section: 171 p. : ill. ; $c 21 cm.
Keywords: 2-Épistémologies autochtones; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; _Nettoyé; _À analyser; _À nettoyer; _À vérifier-Cinéma; _À vérifier-Histoire de l'art; _À vérifier-Télé

Transformations and Remembrances in the Digital Game We Sing for Healing - LaPensee, Elizabeth A. (Transmotion, 2017)
Digital games, with their capacity for expression and facilitating experience through code, design, art, and audio, offer spaces for Indigenous creatives to contribute to Gerald Vizenor’s characterization of survivance as an active sense of Native presence. Indigenous digital games can be acts of survivance both in the ways they are created as well as the resulting designs. We Sing for Healing is an experiment in developing an Indigenous digital game during limited Internet access that resulted in a musical choose-your-own adventure text game with design, art, and code by Anishinaabe, Métis, and Irish game developer Elizabeth LaPensée alongside music by Peguis First Nation mix artist Exquisite Ghost. The non-linear gameplay expresses traditional storytelling patterns while enabling players to poetically travel in, through, and around traditional teachings. The design uses listening, choosing, and revisiting to reinforce what is best described as a non-linear loopular journey.
Number: 1
Keywords: 1-Jeux vidéo; 2-Humanités numériques; 2-Pédagogie décoloniale; 2-Recherche-création; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Honour water: Gameplay as a Pathway to Anishinaabeg Water Teachings - LaPensée, Elizabeth (Decolonization: Indigeneity, Education & Society, 2018)
Digital games can uniquely express Indigenous teachings by merging design, code, art, and sound. Inspired by Anishinaabe grandmothers leading ceremonial walks known as Nibi Walks, Honour Water (http://www.honourwater.com/) is a singing game that aims to bring awareness to threats to the waters and offer pathways to healing through song. The game was developed with game company Pinnguaq and welcomes people from all over to sing with good intentions for the waters. The hope is to pass on songs through gameplay that encourages comfort with singing and learning Anishinaabemowin. Songs were gifted by Sharon M. Day and the Oshkii Giizhik Singers. Sharon M. Day, who is Bois Forte Band of Ojibwe and one of the founders of the Indigenous Peoples Task Force, has been a leading voice using singing to revitalize the waters. The Oshkii Giizhik Singers, a community of Anishinaabekwe who gather at Fond du Lac reservation, contribute to the healing for singers, communities, and the waters. Water teachings are infused in art and writing by Anishinaabe and Métis game designer, artist, and writer Elizabeth LaPensée. From development to distribution, Honour Water draws on Indigenous ways of knowing to reinforce Anishinaabeg teachings with hope for healing the water.
Number: 1
Keywords: 1-Jeux vidéo; 2-Humanités numériques; 2-Pédagogie décoloniale; 2-Recherche-création; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

SPEAR: a Framework for Indigenous Cultural Games - LaPensee, Elizabeth (ANTARES: Letras e Humanidades, 2020)
Video games, which uniquely interweave design, code, art, and sound, can be an especially robust way to express Indigenous cultures. Such games should involve Indigenous people in meaningful roles throughout design and development from conceptualization to distribution with a focus on building capacity to encourage self-determination for Indigenous game developers. This call to action informs SPEAR (Sovereignty, Positionality, Equity, Advocacy, and Reciprocity), a framework for design and development informed by the Indigenous cultural game Thunderbird Strike.
Number: 28
Keywords: 1-Jeux vidéo; 2-Humanités numériques; 2-Recherche-création; 2-Épistémologies autochtones; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

“I see my ancestors”: Exploring Tribal College Student Experiences Playing When Rivers Were Trails - Emmons, Nichlas; LaPensee, Elizabeth (AlterNative: An International Journal of Indigenous Peoples, 2021)
The educational video game, When Rivers Were Trails, was launched in 2019. The purpose of the game is to teach players about Indigenous perspectives of history, US federal allotment policies affecting tribal nations, and some of the effects of these policies on Indigenous peoples. This article explores tribal college student experiences playing When Rivers Were Trails in hopes that it provides the basis for further research into how tribal college faculty may be able to teach the game within their own classrooms. Tribal colleges and universities were created by tribal nations to provide for the higher education needs of their citizens. Using phenomenological research methods, seven college students volunteered to participate in a brief study about their experiences playing the video game. Upon transcription and analysis of the interview data, three themes were developed that capture how these students define their experience with When Rivers Were Trails: feelings of representation, histories of land dispossession, and resilience of communities.
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Humanités numériques; 2-Pédagogie décoloniale; 2-Épistémologies autochtones; 2-Étude de la réception; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Towards Sovereign Games - LaPensée, Elizabeth A.; Laiti, Outi; Longboat, Maize (Games and Culture, 2021)
Video games can be dynamic sovereign spaces for Indigenous representation and expression when the self-determination of Indigenous people is supported. Where ga...
Publisher: SAGE PublicationsSage CA: Los Angeles, CA
Keywords: 1-Jeux vidéo; 2-Humanités numériques; 2-Pédagogie décoloniale; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; _Nettoyé

The Routledge Companion to Media and Race - Campbell, Christopher (Routledge, 2017)
"The Routledge Companion to Media and Race serves as a comprehensive guide for scholars, students, and media professionals who seek to understand the key debates about the impact of media messages on racial attitudes and understanding. Broad in scope and richly presented from a diversity of perspectives, the book is divided into three sections: first, it summarizes the theoretical approaches that scholars have adopted to analyze the complexities of media messages about race and ethnicity, from the notion of 'representation' to more recent concepts like Critical Race Theory. Second, the book reviews studies related to a variety of media, including film, television, print media, social media, music, and video games. Finally, contributors present a broad summary of media issues related to specific races and ethnicities and describe the relationship of the study of race to the study of gender and sexuality"–Provided by publisher.
Keywords: 1-Jeux vidéo; 2-Genre et sexualité; 2-Épistémologies autochtones; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; _Nettoyé; _À analyser; _À nettoyer; _À vérifier-Cinéma; _À vérifier-Histoire de l'art; _À vérifier-Télé

The Routledge Companion to Media Studies and Digital Humanities - Sayers, Jentery (Taylor and Francis, 2018)
"Although the fields of media studies and digital humanities are both well established, their overlaps have not been examined in depth. This comprehensive collection fills that gap, giving students, scholars, and media studies practitioners a cutting-edge guide to understanding the array of methodologies and projects operating at the intersection of digital humanities, computing, and culture. Topics covered include: networks; interfaces; media and culture at scale; procedures, programming, code; memory, digitization, and new media; and hacking, queering, and bending."–Provided by publisher
Keywords: 1-Jeux vidéo; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Humanités numériques; 2-Épistémologies autochtones; 2-Étude des industries culturelles; 2-Étude des représentations; 5-Auteur.rice autochtone; 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé; _À analyser; _À nettoyer; _À vérifier-Histoire de l'art; _À vérifier-Télé

Game Devs & Others: Tales from the Margins - DePass, Tanya (CRC Press, 2018)
Game Devs & Others: Tales from the Margins tell the true stories of life in the industry by people of color, LGBTQIA and other marginalized identities. This collection of essays give people a chance to tell their stories and to let others know what life on the other side of the screen is like when you’re not part of the supposed “majority”. Key Features This book is perfect for anyone interested in getting into the games industry who feels they have a marginalized identity For those who wish to better diversify their studio or workplace who may or may not have access to individuals that could or would share their stories about the industry Includes initiatives aimed at diversifying the industry that have a positive or negative impact on the ongoing discussions Coverage of ajor news items about diversity, conferences aimed at or having diversity at its core of content and mission are discussed Included essays are written with as little game dev specific jargon as possible, makeing it accessible to people outside the industry as well as those in the scene but that may not have all the insider lingo
Google-Books-ID: Gv5cDwAAQBAJ
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Genre et sexualité; 2-Méthodologie de recherche décoloniale; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice LGBTQ+; 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; 5-Créateur.rice LGBTQ+; 5-Créateur.rice PANDC; 5-Créateur.rice autochtone; 5-Créateur.rice noir.e; 5-Créatrice; 5-Identités diasporiques; _Nettoyé

Learning, Education & Games, Volume 3: 100 Games to Use in the Classroom & Beyond - Schrier, Karen (ETC Press, 2019)
Have you ever wanted to know which games to use in your classroom, library, or afterschool program, or even at home? Which games can help teach preschoolers, K-12, college students, or adults? What can you use for science, literature, or critical thinking skills? This book explores 100 different games and how educators have used the games to teach - what worked and didn't work and their tips and techniques. The list of 100 goes from A to Z Safari to Zoombinis, and includes popular games like Fortnite, Call of Duty: Modern Warfare, and Minecraft, as well as PC, mobile, VR, AR, card and board games.
Google-Books-ID: D_HCDwAAQBAJ
Keywords: 1-Jeux vidéo; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Humanités numériques; 2-Pédagogie décoloniale; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 2-Étude des représentations; 5-Auteur.rice autochtone; 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Digital Dispossessions: the Importance of Regional Specificity and Sovereign Spaces to Video Game Representations of Native American Cultural Heritage - Bird, Ashlee (Studia Neophilologica, 2021)
Indigenous peoples and their cultural heritages, their ways of knowing and living, are tied to land. As Mishuana Goeman states,“Land is foundational to people’s cultural practices, and if we define culture as meaning making rather than as differentiation and isolation in a multicultural neoliberal model, thanby thinking through land as a meaning-making process rather than a claimed object, the aspiration of Native people are apparent and clear,” (Goeman, 73).Goeman asserts here that land is not limited to physical space, and that land locates a group of people physically, culturally, spiritually, intellectually,etc. and provides them with both an internal and external locus of understanding for and within broader society. When digital representations of Indigenous peoples are completely removed from any meaningful connection to their land, anerasure of culture occurs. Moreover, the physical removal of Indigenous peoples from the virtual representations of their lands is another form of dispossession and the enactment of digital Manifest Destiny. This paperutilizes a decolonial Indigenous framework to analyze the dispossessions that take place within the digital realm of the video game, why they occur so frequently, and why they are so harmful.
_eprint: https://doi.org/10.1080/00393274.2021.1916995
Keywords: 1-Jeux vidéo; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; _Nettoyé

Examining the Intersection of Race and Gender in Video Game Advertising - Behm-Morawitz, Elizabeth (Journal of Marketing Communications, 2017)
Women and racial/ethnic minorities account for a growing percentage of video game players in the USA. The economic future of the video game industry may, in part, depend on the industry's ability to adapt marketing efforts to appeal to the growing female and racial/ethnic markets. Contrary to these efforts, however, is advertisers' reliance on stereotypes in advertisements to quickly establish a common understanding and wide appeal to a mass audience. This study investigates how race and gender intersect in the stereotypical character depictions used to market video games to consumers. A systematic content analysis was carried out of 383 US magazine advertisements of console, mobile, and PC video games. Stereotyping and intersectionality literatures were used as theoretical guides for this research. Findings reveal that the marketing of video games in the USA upholds some longstanding media stereotypes of minorities and women, including that of the White male hero, submissive sexualized female, Asian ninja, and deviant Black male. The potential social and economic implications of the video game industry's reliance on character stereotypes for the marketing of video games are discussed.
_eprint: https://doi.org/10.1080/13527266.2014.914562
Keywords: 1-Jeux vidéo; 2-Genre et sexualité; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; _Nettoyé

Video games and Indigenous education: Let’s bridge the ‘epistemology gap’ - Emery, Susannah; Habel, Chad (Ergo, 2017)
There are clear challenges posed by rural and remote education in Australia. These challenges are caused both by physical and material factors, but more importantly epistemological divisions that have created a separation between Indigenous and non-Indigenous worlds. Video games have the potential to bridge this epistemological gap by explicating the differences between different knowledge systems and engaging students in exploring these differences. Crucially, these projects need to be co-constructed to ensure that not only the representations of Indigenous people surpass some dubious traditions, but that different epistemologies are adequately framed. There is an urgent need for research-informed game-based learning projects to begin to address the ‘epistemology gap’ and the challenges faced by all Australians.
Number: 1
Keywords: 1-Jeux vidéo; 2-Humanités numériques; 2-Recherche-création; 2-Épistémologies autochtones; 2-Étude des représentations; 3-Océanie (corpus analysé); 4-Océanie (lieu de production du savoir); 5-Autrice; 5-Créatrice; _Nettoyé

Never Alone. A study of Articulations of Indigenous Religion in the Video Game - Lohne, Inger Lise Damli (UiT Norges arktiske universitet, 2020)
This thesis explores the many ways indigenous religion is articulated, performed and translated in the video game Never Alone - Kisima Inŋitchuŋa (2014). The video game was among the first of its kind – being made in a close collaboration with an indigenous group, and published by the first indigenous owned video game company in the U.S.A. At launch, Never Alone gathered attention from traditional media in both North America and in Europe, and the game reached a global audience. Never Alone tells a story based on Inupiat storytelling, and Cultural Ambassadors gives the player an insight into Inupiat culture and tradition. Never Alone balances on the edge between the conventions of the video game medium and its genres, and of indigenous tradition and religion. This thesis examines how vocabularies that can be related to ‘indigenous religion’ are used and translated in Never Alone, and how these vocabularies relate to a globalizing discourse on indigenous religion. This thesis also explores how the medium of video games facilitates new ways of reclaiming traditions and articulating indigenous religion.
Accepted: 2020-12-18T09:22:21Z
Keywords: 1-Jeux vidéo; 2-Épistémologies autochtones; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Europe (lieu de production du savoir); 5-Créateur.rice autochtone; _Nettoyé

Indigenous Representations and the Impacts of Video Games Media on Indigenous Identity - Lagace, Naithan (University of Manitoba, 2018)
This thesis analyzes and discusses the complexities of digital representations involving Indigenous peoples through video games. Connecting both Game Theory and Native Studies, I analyze how digital games incorporate identity, culture, and relationships in diverse and intellectual ways and provide new spaces for Indigenous agency and semiotics. Beginning with an analysis of several historical and negative representations of Indigenous peoples, I then compare those tropes to projects within today’s environment and mainstream video game companies, independent companies, and educational service providers. I assert that while some digital media representations of Indigenous cultures are stereotypical and problematic, others facilitate a sense of cultural continuance and survivance. Lastly, some video games display both stereotypical and cultural continuance within them.
Accepted: 2019-01-10T21:28:57Z
Keywords: 1-Jeux vidéo; 2-Histoire/Historiographie critique; 2-Épistémologies autochtones; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); _Nettoyé

“We All Stand Side by Side”: An Interview with Elizabeth LaPensée - Hearne, Joanna (Studies in American Indian Literatures, 2017)
Keywords: 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé; _À analyser; _À nettoyer; _À vérifier-Histoire de l'art

Coming to You from the Indigenous Future: Native Women, Speculative Film Shorts, and the Art of the Possible - Medak-Saltzman, Danika (Studies in American Indian Literatures, 2017)
Keywords: 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); _Nettoyé; _À analyser; _À nettoyer; _À vérifier-Cinéma; _À vérifier-Histoire de l'art; _À vérifier-Télé

Imagining Indigenous Digital Futures: An Afterword - Raheja, Michelle (Studies in American Indian Literatures, 2017)
In lieu of an abstract, here is a brief excerpt of the content: As I sit writing in my kitchen while the forces of the U.S. military state are brought to bear on thousands of Standing Rock water stewards and land protectors and their allies in Cannonball, North Dakota, I consider how this sail special issue on digital Indigenous studies not only represents a collection of essays about the critical work Indigenous women are performing in their various digital projects but also illustrates that these online “Indigenous territories” (Hearne), crafted on social media platforms such as Twitter and Facebook, save lives. Every single day since the protectors first gathered to oppose the proposed 1,170-mile Dakota Access pipeline (a project that would potentially contaminate the Missouri watershed and the Ogallala Aquifer and desecrate Dakota sacred sites), digital independent and social media have constantly covered the story. At least 1.3 million Facebook users checked in virtually at Oceti Sakowin and other Indigenous camps and communities to ensure that support presence is recognized, while the world monitors the presence of the military and police force gathering at the construction site to curb further violence. The Standing Rock gathering offers hope to networked Indigenous youth, a demographic between three and ten times as likely to commit suicide than the national average peer rate. The Nodapl action in the Indigenous imaginary is an invitation to stand at the front lines of a global movement to protect water and land resources for all living beings on this planet and to draw attention to and support those whose lives and ways of being are in peril through overt military action and consequential environmental destruction. It is also an occasion, in the words of Jolene Rickard, “to invest in the apparatus of the imagination” (Bernardin). One need only look at the online art, handwritten signs, and logos representing #nodapl, #standingrock, [End Page 172] #waterislife, and #rezpectourwater to see the ways in which Indigenous artists are creatively and powerfully envisioning this movement, most often immersed with work that features strong images of Native women and girls, the community backbone and life force. Or we need only view digital videos like computer animator and artist Joseph Erb’s black-and-red graphic history of Standing Rock, “Mni Wiconi / Water Is Life” (https://www.youtube.com/watch?v=kXoy5lzpjiM), and first-person game platforms like Elizabeth LaPensée’s Thunderbird Strike, which extend the conversations at Standing Rock to the struggles over Enbridge’s Alberta tar sands pipeline and fracking practices as players work to undo and prevent further environmental degradation. Following Idle No More’s digital and geospatial (re)articulation of Indigenous territories, we are now living and loving and hoping in this historic moment as new ways of relating to one another and living in deep connection with the land and all its forms of life are being physiologically, intellectually, and spiritually forged at the geospatial confluence of the Missouri and Cannonball Rivers. They are being forged as well through the confluences of digital rivers on our electronic devices and in our online conversations about the beauty and devastation of the events that are unfolding in Standing Rock. Susan Bernardin’s essay in this issue on Heid E. Erdrich’s “Pre-Occupied” considers the meaning of rivers to Native peoples and contends that images of waterways, particularly the Mississippi, are mobilized “to make visible the continuing claims of this and other imperiled riverine systems.” In her introduction, Joanna Hearne asks us, “How might such an intersection of digital and Indigenous specificities take place in a way that is ‘native to the device’; that is, how might Indigenous specificity be embedded in shared platforms that are therefore central to all of our digital lives?” The essays in this special issue respond to this question by theorizing digital media in fresh and innovative ways. Many of us teach digital humanities courses or classes with strong digital media content, but we lack the language for critically engaging this new field on its own terms as it intersects, extends, and radically reconceptualizes more familiar research areas such as cinema studies, Indigenous / Native American studies, communication, literature, art, and history.
Keywords: 1-Jeux vidéo; 2-Histoire/Historiographie critique; 2-Humanités numériques; 2-Épistémologies autochtones; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Thunderbird Strike: Survivance in/of an Indie Indigenous Game - LaPensée, Elizabeth (Video Game Art Reader 2.1, 2018)
Thunderbird Strike, a 2D side-scroller developed by Elizabeth LaPensée, allows a player fly from the Tar Sands to the Great Lakes as a thunderbird protecting Turtle Island with searing lightning against the snake that threatens to swallow the lands and waters whole. The game encouraged players to learn about the indigenous culture, reflect on water protection and alternative energy sources, and gain awareness of risks posed by oil pipeline construction for the conveyance of tar sands.Thunderbird Strike was developed through residencies including O k’inādās Residency, The Banff Musicians in Residence Program, and Territ-Aur(i)al Imprints Exchange thanks to the 2016 Artist Fellowship grant from the Arrowhead Regional Arts Council.
Keywords: 1-Jeux vidéo; 2-Humanités numériques; 2-Pédagogie décoloniale; 2-Recherche-création; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Critical Protocols in Indigenous Gamespace - Miner, Joshua D. (Games and Culture, 2022)
This article examines Indigenous video games that critique mainstream environmental politics at the level of mechanics. An analysis of video games’ influences on ecological values requires looking beyond the representational to the mechanical relationships between player and software. As a cultural–computational medium, video games are embedded with ethics of interaction that inflect this representational dimension by requiring that players generate the text as participant. With the recent visibility of Indigenous rights movements, developers have embedded Indigenous cultural protocols in the mechanical interactions (or technical protocols) of gameplay. In the context of critique, their integration produces “critical protocols,” configurations of gamic action that encourage players to evaluate their treatment of real-world environments. Critical protocols emerge between the technical and cultural, where scripts for interaction in algorithmic spaces intervene in affirmative game design and work as an analog beyond the game. Indigenous developers call for new ways of computing and critiquing settler digitality through play. These games aim toward representational as well as computational sovereignty.
Keywords: 1-Jeux vidéo; 2-Humanités numériques; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Créateur.rice autochtone; _Nettoyé

When Rivers Were Trails: Cultural Expression in an Indigenous Video Game - LaPensée, Elizabeth (International Journal of Heritage Studies, 2021)
When Rivers Were Trails is a 2D adventure game wherein The Oregon Trail meets Where the Water Tastes Like Wine through an Indigenous lens. The game depicts a myriad of cultures during the player’s journey from Minnesota to California amidst the impact of land allotment in the 1890s. Initiated by the Indian Land Tenure Foundation, the game was developed in collaboration with the Games for Entertainment and Learning Lab at Michigan State University thanks to support from the San Manuel Band of Mission Indians and the many Indigenous creatives who contributed design, art, music, and writing. Uniquely, When Rivers Were Trails is a sovereign game, meaning that it was directed and informed by Indigenous creatives who maintained the role of final decisions during development. Merging design research and close reading methods, this study sets out to describe the game’s design, development process in regards to the game writing, and the resulting themes which emerged as a result of engaging Indigenous writers in self-determined representations.
_eprint: https://doi.org/10.1080/13527258.2020.1746919
Keywords: 1-Jeux vidéo; 2-Histoire/Historiographie critique; 2-Humanités numériques; 2-Pédagogie décoloniale; 2-Épistémologies autochtones; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Le jeu vidéo comme vecteur d’expression du patrimoine culturel des Iñupiats d’Alaska - Hocine, Julien; Deslauriers, Patrick (Emulations - Revue de sciences sociales, 2019)
En 2014, une collaboration entre le studio Upper One Games et des conteurs et aînés iñupiats d’Alaska a mené au lancement du jeu vidéo Kisima Inŋitchuŋa (Never Alone). Ce jeu de plateforme invite à une immersion poétique dans un univers nordique guidée par une trame narrative inspirée d’une légende traditionnelle. Dans une perspective culturelle, les fonctions ludique et documentaire du jeu permettent d’acquérir des connaissances en lien avec les pratiques traditionnelles et la vision du monde des Iñupiats. Ainsi, l’étude exploratoire présentée dans cet article contribue à comprendre les caractéristiques du jeu (design, narration, mécaniques) et les stratégies relevant de sa conception. Les résultats invitent à reconsidérer des représentations dominantes du Grand Nord et soulignent en quoi le jeu vidéo se fait vecteur d’expression du patrimoine culturel, artistique et oral d’un peuple autochtone de l’Arctique.
Number: 30
Keywords: 1-Jeux vidéo; 2-Humanités numériques; 2-Pédagogie décoloniale; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); _Nettoyé

Indie and Dojin Games : a Multilayered Cross-Cultural Comparison - Fiadotau, Mikhail (Gamevironments, 2019)
The article provides a comparative account of two paradigms of independent videogame production: the Japanese dojin (doujin) games and the increasingly global indie games. Through a multilayered analysis, it expounds the conceptual metaphors associated with indie and d jin games, traces the two movements respective histories, situates them in wider media environments, and compares their characteristic traits.
Accepted: 2020-03-25T23:30:23Z
Keywords: 1-Jeux vidéo; 2-Histoire/Historiographie critique; 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Europe (lieu de production du savoir); _Nettoyé

Interview with Deyfou-lah Sani Bah-Traore on the Togolese Game Origin - the Rise of Dzitri - Kienzl, Lisa; Bah-Traore, Deyfou-lah Sani (Gamevironments, 2019)
In the Togelese game Origin - the Rise of Dzitri that was developed in Lome, the character Edoh takes you on a journey to historic places in the city to revive the spirit of Dzitri. Deyfou-lah Sani Bah-Traore, programmer and game developer, spoke with Lisa Kienzl about his and his Teammate s work on Origin - the Rise of Dzitri
Accepted: 2020-03-25T23:30:30Z
Keywords: 1-Jeux vidéo; 2-Histoire/Historiographie critique; 2-Étude des industries culturelles; 3-Afrique (corpus analysé); 4-Afrique (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Autrice; 5-Créateur.rice PANDC; 5-Créateur.rice noir.e; _Nettoyé

Interview with Mira Wardhaningsih from StoryTale Studios on the Indonesian Horror Game Pamali - Trattner, Kathrin; Wardhaningsih, Mira (Gamevironments, 2019)
An interview by Kathrin Trattner with Mira Wardhaningsih, Cultural Content Director from StoryTale Studios about the game Pamali
Accepted: 2020-03-25T23:30:30Z
Keywords: 1-Jeux vidéo; 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Autrice; 5-Créateur.rice PANDC; 5-Créatrice; _Nettoyé

Round Table Discussion on Nation(alism), Identity and Video Gaming with Megan Condis, Marijam Didzgalvyt , Georg Hobmeier and Souvik Mukherjee - Trattner, Kathrin; Condis, Megan; Didzgalvyt, Marijam; Hobmeier, Georg; Mukherjee, Souvik; Kienzl, Lisa (Gamevironments, 2019)
Questions of nation and identity not only concern multiple aspects of video games, their production, and their consumption, but also require further and manifold discussion from different perspectives. In an effort to bring together voices from different fields that engage with video games and gaming practices from various perspectives, this virtual round table discussion attempts to open up the conversation beyond the realms of academia. Kathrin Trattner and Lisa Kienzl talked to Megan Condis, Marijam Didzgalvyt , Georg Hobmeier and Souvik Mukherjee about how concepts such as nation(alism) and identity impact video game representations, the gaming industry, and online gaming cultures in numerous ways.
Accepted: 2020-03-25T23:30:29Z
Keywords: 1-Jeux vidéo; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des industries culturelles; 2-Étude des représentations; 4-Amérique du Nord (lieu de production du savoir); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; _Nettoyé

Glory to Trumpland! Critically Playing Border Games - Kagen, Melissa (Gamevironments, 2019)
This project examines the critical play of a variety of games about immigrant and refugee experience. These border games take place within fictional or actual borderlands and follow characters either in transit or trapped in detainment centers between nations. Spanning a range of genres, each deals differently with the major problem posed by their content - how to create a sensitive procedural rhetoric around migration. Drawing from Flanagan's conceptualization of critical play and Mukherjee's work on the ambivalence of postcolonial playing back, I explore the possibilities of critically playing border games and the extent to which each game's design (dis)allows for certain forms of play and protest. I focus on three paired case studies, Escape from Woomera (2003) and Smuggle Truck (2012); Papers, Please (2013) and Liberty Belle's Immigration Nation (2014); and Bury Me, My Love (2017) and The Waiting Game (2018). By considering both the design of these border games and the metagaming practices that have developed around them, I show how postcolonial misplay of fictional games draw more effective critical attention to injustice than the most well-intentioned and serious educational game
Accepted: 2020-03-25T23:30:29Z
Keywords: 1-Jeux vidéo; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 4-Europe (lieu de production du savoir); 5-Autrice; _Nettoyé

Interview With Ryan Sumo, Lead Artist/Business Developer At Squeaky Wheel Studio - Radde-Antweiler, Kerstin; Sumo, Ryan (Gamevironments, 2018)
Interview with Ryan Sumo, Lead Artist/Business Developer at Squeaky Wheel Studio
Accepted: 2020-03-25T23:30:10Z
Keywords: 1-Jeux vidéo; 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Autrice; 5-Créateur.rice PANDC; _Nettoyé

Interview With Ben Joseph P. Banta, Founder Of Ranida Games - Radde-Antweiler, Kerstin; Banta, Ben Joseph P. (Gamevironments, 2018)
Interview With Ben Joseph P. Banta, Founder Of Ranida Games
Accepted: 2020-03-25T23:30:10Z
Keywords: 1-Jeux vidéo; 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Autrice; 5-Créateur.rice PANDC; _Nettoyé

Interview With The Creator Of Boo! Dead Ka! Game - Radde-Antweiler, Kerstin; Prieto, Kurt (Gamevironments, 2018)
Interview with With Kurt Prieto, Games Designer Of Boo! Dead Ka! Game
Accepted: 2020-03-25T23:30:10Z
Keywords: 1-Jeux vidéo; 2-Humanités numériques; 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Autrice; 5-Créateur.rice PANDC; _Nettoyé

An Ethnoludography of the Game Design Industry in Kathmandu, Nepal - Grieve, Gregory P. (Gamevironments, 2018)
What counts as the field site when researching Nepali video game developers? Concentrating on the company Arcube Games and Animation, in the summer of 2017 I used the ethnoludographic method to research game development in the Kathmandu Valley. I recorded my findings in field notes, photographs, written documents and other material culture. My usual ethnographic method developed in two ways. First, I engaged in ludography, a humanistic qualitative method for interpreting gaming. Second, Nepal proved not to be an isolated location, but rather a vortex of global flows. I found that in the Kathmandu valley these flows are often focused on a fantasy of Shangri-La that poses Nepal as an underdeveloped traditional nation, full of picturesque poverty, and over-determined with religious culture, but blessed with beautiful Himalayan landscapes.
Accepted: 2020-03-25T23:30:09Z
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); _Nettoyé

Geemu On! A Preliminary Study Of Indie And Doujin Game Development In Japan - Helland, Christopher (Gamevironments, 2018)
This paper is a brief summary of a preliminary exploration of certain aspects of independent video game development in Japan. Initial interviews were conducted with researchers and indie game developers over a two-week period in Tokyo. Independent game developers from Kamakura were also interviewed as part of the research. Initial fieldwork was geared primarily toward doujin level game development and distribution. My key research question focused upon the religious and spiritual dimensions of doujin games. However, after conducting interviews it became clear that developers did not consider the Western frame or classification of religion and spirituality in their development but rather incorporated aspects of tradition, culture and values within their work.
Accepted: 2020-03-25T23:30:09Z
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); _Nettoyé

Interview with Zainuddeen Fahadh, Founder of Ogre Head Studio - Zeiler, Xenia; Zainuddeen, Fahadh (Gamevironments, 2018)
Interview with Zainuddeen Fahadh, Founder of Ogre Head Studio, Hyderabad, India
Accepted: 2020-03-25T23:30:09Z
Keywords: 1-Jeux vidéo; 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Autrice; 5-Créateur.rice PANDC; _Nettoyé

Interview with Avinash Kumar, Creative Director & Co-Founder, Quicksand Design Studio - Zeiler, Xenia; Kumar, Avinash (Gamevironments, 2018)
Interview with Avinash Kumar, Creative Director & Co-Founder, Quicksand Design Studio, India.
Accepted: 2020-03-25T23:30:09Z
Keywords: 1-Jeux vidéo; 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Autrice; 5-Créateur.rice PANDC; _Nettoyé

Interview with Avichal Singh, Founder and Game Designer of Nodding Heads Games - Zeiler, Xenia; Singh, Avichal (Gamevironments, 2018)
Interview with Avichal Singh, Founder and Game Designer of Nodding Heads Games, Pune, India.
Accepted: 2020-03-25T23:30:09Z
Keywords: 1-Jeux vidéo; 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Autrice; 5-Créateur.rice PANDC; _Nettoyé

Interview with Satyajit Chakraborty, Founder of Flying Robot Studios, Kolkata, India - Zeiler, Xenia; Chakraborty, Satyajit (Gamevironments, 2018)
Accepted: 2020-03-25T23:30:08Z
Keywords: 1-Jeux vidéo; 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Autrice; 5-Créateur.rice PANDC; _Nettoyé

Video Game Development In Asia: Voices From The Field - Grieve, Gregory P.; Radde-Antweiler, Kerstin; Zeiler, Xenia; Helland, Christopher (Gamevironments, 2018)
Introduction to the gamevironments Special Issue Video Game Development in Asia: Voices from the Field .
Accepted: 2020-03-25T23:30:09Z
Keywords: 1-Jeux vidéo; 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Autrice; _Nettoyé

You can Be Anyone; but there are Limits: a gendered Reading of Sexuality and Player Avatar Identification in Dragon Age: Inquisition - Hassan, Mohamed S. (Gamevironments, 2017)
Dragon Age: Inquisition s (2014) release opened a new world of character creation for the single-player RPG genre. Upon release, it allowed the player an extensive amount of customization. In addition to the typical variety of choices associated with hairstyle and color, face structure, tattoos, eye color, scarring, etc. the game also provides in-game unique sexuality quest lines that highlight the spectrum of sexual choices, race-defined features, different class options, and body-positive representations, which the player could project onto their avatar. However, in a game heralded as groundbreaking for representation, the creators fail to acknowledge the non-binary gender expressions of their players, instead, forcing the player to choose between the traditional male and female characters. This paper seeks to explore the different ways in which Dragon Age: Inquisition (DAI) purports to incorporate modern notions of representation in the sphere of gender and sexuality but fail to do so, instead, reinforcing traditional binary representations of gender and sexuality informed by racial and religious assumptions
Accepted: 2020-03-25T23:29:40Z
Keywords: 1-Jeux vidéo; 2-Genre et sexualité; 2-Étude des représentations; 4-Amérique du Nord (lieu de production du savoir); _Nettoyé; _À analyser

Video Game Development in Asia : a Research Project on Cultural Heritage and National Identity - Grieve, Gregory P.; Helland, Christopher; Radde-Antweiler, Kerstin; Zeiler, Xenia (Gamevironments, 2017)
A report of the 2017 collaborative research project Video Game Development in Asia. Cultural Heritage and National Identity.
Accepted: 2020-03-25T23:29:51Z
Keywords: 1-Jeux vidéo; 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Autrice; _Nettoyé

Global Conflicts, Episodic Framing and Attitude Change Towards the Israeli-Palestinian Conflict - Kampf, Ronit (Gamevironments, 2017)
This study compared the effects of episodic framing of the Checkpoint scenario and the Military Raid scenario in Global Conflicts (2010), a computerized simulation of the Israeli-Palestinian conflict, on developing impartial attitudes towards this conflict. The former presents a more human, individual and personal framing of the conflict than does the latter. Two hundred and ten Israeli-Jewish and Palestinian undergraduate students participated in the experiment. They filled in questionnaires measuring attitudes towards the Israeli-Palestinian conflict before and after playing the scenarios. Results suggested that participants playing the Checkpoint scenario became more impartial toward the Israeli-Palestinian conflict, unlike those playing the Military Raid scenario. The results show that computerized simulations of the Israeli-Palestinian conflict can be used for attitude change intervention, but the framing of the story in the game may be crucial in determining whether the players become impartial regarding the situation or not.
Accepted: 2020-03-25T23:29:51Z
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Humanités numériques; 2-Étude de la réception; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Autrice; _Nettoyé

Interview with Shailesh Prabhu, Indian Game Designer - Prabhu, Shailesh (Game Studies, 2016)
Interview with the Indian Game Designer Shailesh Prabhu about his game Sky Sutra.
Accepted: 2020-03-25T23:29:20Z
Keywords: 1-Jeux vidéo; 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Créateur.rice PANDC; _Nettoyé

The Indian Indie Game Development Scene - History and Cultural Heritage as Game Themes - Zeiler, Xenia (Gamevironments, 2016)
While the Indian indie game development scene is still relatively young, it has already lived through big changes. Like in many regions worldwide, indie game developers in India have to negotiate between practical issues, for example regarding market requirements and expectations, and committed ambitions, for example regarding creative aspirations in art design and game content. On the one hand and in order to persist in the ever extending industry, they need to acknowledge mainstream wants and practical demands from especially (though not exclusively) the Indian game market which at present is characterized by an overall dominance of mobile card and casino games. On the other hand, we see that especially Indian indie developers increasingly reflect on the role of Indian cultural heritage (including elements from history, architecture, music, etc.) for India produced games. This turn to own roots, to implement Indian cultural and historical heritage in games, is now visible in a number of games which have been recently Greenlit on Steam and are in the final production phases, such as Asura (2017 forthc.), Antariksha Sanchar (2017 forthc.), and others.
Accepted: 2020-03-25T23:29:32Z
Keywords: 1-Jeux vidéo; 2-Histoire/Historiographie critique; 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Europe (lieu de production du savoir); 5-Autrice; _Nettoyé

Videogames about Politics as States of Exception - Hao, Yu (Gamevironments, 2020)
This article looks at videogames about politics within the theoretical framework of Giorgio Agamben’s states of exception and argues that while videogames can reveal political issues by implementing rules into the gameplay, they simultaneously render the in-game rules and consequences inoperative in regard to real-world politics, which can be described as states of exception in Agamben’s sense. Agamben distinguishes between the fictitious and the real state of exception, and this distinction leads to his proposal of a politics of pure means in which he considers play as a means of profanation that renders what has been played with inoperative and free. Drawing on this discussion, the article looks at the parallel between the rules in videogames and the laws in states of exception and re-examines the concepts of game rules and play under the rubric of Agamben’s political philosophy. In so doing, it explores how playing with rules in videogames about politics can turn these games into states of exception to talk about and reflect on various political issues.
Accepted: 2020-12-29T10:13:26Z
Keywords: 1-Jeux vidéo; 2-Histoire/Historiographie critique; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 5-Auteur.rice PANDC; _Nettoyé

Imperialism and Fascism Intertwined. A Materialist Analysis of the Games Industry and Reactionary Gamers - Hammar, Emil Lundedal (Gamevironments, 2020)
This article paves way for a materialist analysis of the games industry as 21st century imperialism that is economically and culturally structured to cultivate anti-democratic norms that lead to fascist movements against those who question or seek to change the status quo. While much research has studied the politics of reactionary movements in gaming cultures, few have paid attention to the relation between the games industry as part of an imperialist economic system, the chauvinistic ideals symptomized in their cultural products, and the reactionist consumer audiences they attract and cultivate. As I argue, the economic structure of the industry as 21st century imperialism leads to perpetual anti-democratic crises that are maintained by reactionary forces that cultivate, attract, and form fascist grassroots organization. To conceptualize this dynamic, I invoke the labor aristocracy theory as suggested by Friedrich Engels and V.I. Lenin. This theory helps highlight the material basis from which consumers of digital games are bribed to become ideologically aligned with the chauvinism that the imperialist nature of the games industry is justified by. I also invoke W.E.B. Du Bois’ concept of a public and psychological wage to highlight the chauvinistic tendencies that the games industry cultivates via their products and marketing, in which the lack of democratic and equitable representation provides the reactionary consumers a sense of superiority. Together, these approaches account for the economic and cultural bases of both the games industry and its reactionary consumers. By anchoring my analysis in critical theories on imperialism and race, the article identifies the root causes of organized harassment and chauvinism in game cultures, as well as how the industry as 21st century imperialism benefits from and is protected by these forces of reaction.
Accepted: 2020-12-29T10:24:13Z
Keywords: 1-Jeux vidéo; 2-Genre et sexualité; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des industries culturelles; 4-Europe (lieu de production du savoir); _Nettoyé

Exploring the Difficulties African-American Middle School Girls Face Enacting Computational Algorithmic Thinking over three Years while Designing Games for Social Change - Thomas, Jakita O.; Rankin, Yolanda; Minor, Rachelle; Sun, Li (Computer Supported Cooperative Work, 2017)
Computational algorithmic thinking (CAT) is the ability to design, implement, and assess the implementation of algorithms to solve a range of problems. It involves identifying and understanding a problem, articulating an algorithm or set of algorithms in the form of a solution to the problem, implementing that solution in such a way that the solution solves the problem, and evaluating the solution based on some set of criteria. CAT is an important scaffolded on-ramp as students develop more advanced computational thinking capabilities and apply computational thinking to solve problems that are more constrained and require greater expertise. Supporting Computational Algorithmic Thinking (SCAT) is both a longitudinal between-subjects research project and a free enrichment program supporting and guiding African-American middle school girls over three years as they iteratively design a set of complex games for social change. This article explores Scholars' reflections about the difficulties they faced while using CAT capabilities as they engaged in collaborative game design for social change over those three years. We particularly focus on how these difficulties changed over the course of three years as well as new difficulties that emerged from year to year as Scholars become more expert game designers and computational algorithmic thinkers.
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Genre et sexualité; 2-Humanités numériques; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; _Nettoyé

Exploring Collaborative Talk Among African-American Middle-School Girls in the Context of Game Design for Social Change - Thomas, Jakita O.; Rankin, Yolanda; Saunders, Quimeka (Journal of Computing Sciences in Colleges, 2019)
Computer Science education research establishes collaboration among students as a key component in learning, particularly its role in pair programming. Furthermore, research shows that girls, an underrepresented population in computing, benefit from collaborative learning environments, contributing to their persistence in CS. However, too few studies examine the role and benefits of collaborative learning, especially collaborative talk, among African-American girls in the context of complex tasks like designing video games for social change. In this exploratory study, we engage 4 dyads of African-American middle school girls in the task of designing a video game for social change, recording the dyads' conversations with their respective partners over an eight-week summer game design experience during the second year of what has now become a six-year study. Qualitative analysis of dyadic collaborative discussion reveals how collaborative talk evolves over time in African-American middle-school girls.
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Genre et sexualité; 2-Humanités numériques; 2-Pédagogie décoloniale; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; _Nettoyé

Playing with Race: The Ethics of Racialized Representations in E-Games - Chan, Dean (Internaitonal Review of Information Ethics, 2005)
Questions about the meanings of racialized representations must be included as part of developing an ethical game design practice. This paper examines the various ways in which race and racial contexts are represented in a selected range of commercially available e-games, namely war, sports and action-adventure games. The analysis focuses on the use of racial slurs and the contingencies of historical re-representation in war games; the limited representation of black masculinity in sports games and the romanticization of ‘ghetto play’ in urban street games; and the pathologization and fetishization of race in ‘crime sim’ action-adventure games such as True Crime: Streets of LA. This paper argues for, firstly, a continuous critical engagement with these dominant representations in all their evolving forms; secondly, the necessary inclusion of reflexive precepts in e-games development contexts; and thirdly, the importance of advocating for more diverse and equitable racialized representations in commercial e-games.
Keywords: 1-Jeux vidéo; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Océanie (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé

Postcolonial Playgrounds: Games and postcolonial culture - Lammes, Sybille (Eludamos. Journal for Computer Game Culture, 2010)
Many games touch upon issues that are related to the postcolonial culture we live in. Be it in the shape of referring to how it has generated ethnic differences, subscribing to (post) capitalist values of winning and gaining, or by employing militarist strategies that have been partly shaped our colonial histories, cultural notions that are related to our colonial past are often resonant in games. However, one particular strand of strategy games takes the notions of colonialism as its most central focus. Games like Age Of Empires (AOE), Civilization and Rise of Nations, may differ greatly in certain ludological aspects, but all share a strong fascination with colonial history. Through employing colonial techniques of domination like exploring, trading, map-making and military manoeuvring, players create their personal colonial pasts and futures. Even though it is evident that such games share an explicit fascination with colonial history, it remains less clear in what way they may be called postcolonial. In this article I will shed light on why and how such games can be called postcolonial and should even be conceived as one of the most significant arenas to express the tensions and frictions that are part of the postcolonial culture we live in. As postcolonial playgrounds they offer the perfect means to play with and make sense of how colonial spatial practices have shaped contemporary culture. I will argue that the very character of digital games as well as the specific game mechanisms of historical strategy games makes them postcolonial playgrounds par excellence.
Number: 1
Keywords: 1-Jeux vidéo; 2-Histoire/Historiographie critique; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Europe (lieu de production du savoir); 5-Autrice; _Nettoyé

Digital Conquerors: Minecraft and the Apologetics of Neoliberalism - Dooghan, Daniel (Games and Culture, 2019)
The widespread popularity of sandbox games, and Minecraft in particular, may be a recent phenomenon, but their appeal may be much older. Rather than representing a wholly new development in gaming, these games may participate in a larger media ecology that flatters a neoliberal worldview. This research calls for greater attention to the coercive economic assumptions encoded in gamemechanics. Drawing on scholarship in ludology, postcolonial studies, and phenomenology, it suggests that sandbox games like Minecraft habituate players to myths of empire and capital that rationalize political and economic inequality. More than simply offering a blank slate for player creation, Minecraft rewards players for assuming their entitlement to the world’s resources and thus their superiority over other inhabitants of the game world.
Keywords: 1-Jeux vidéo; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); _Nettoyé

Playing at Colonization: Interpreting Imaginary Landscapes in the Video Game Tropico - Magnet, Shoshana (Journal of Communication Inquiry, 2006)
This article coins the term gamescape to offer a way of thinking about the implications of the way in which landscape in video games is actively constructed within a particular ideological framework. The author examines the spatial practices used to construct the gamescape in Tropico and their attendant dangers. The author concludes with a discussion of the theming of this gamescape, and the way in which the trope of tropicalization is used to stabilize Tropico as an “Othered” space.
Keywords: 1-Jeux vidéo; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 4-Amérique du Nord (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Autrice; _Nettoyé

On the Border: Pleasure of Exploration and Colonial Mastery in Civilization III Play the World - Lammes, Sybille (DiGRA '03 - Proceedings of the 2003 DiGRA International Conference: Level Up, 2003)
Games like Myst, Civilisation and Anno 1602 are centred around the virtual travelling of the gamer through unknown worlds. The voyage s/he undertakes often hinges on notions of colonialist exploration, turning the gamer into a traveller who surveys and masters unknown domains and learns to control techno-scientific principles along the way. Since such games are related to a mentality of colonialism, questions should be asked about how such games can be located in its discursive formation. This paper will shed light on these questions by analysing Civilization III and my experiences of playing this game.
Keywords: 1-Jeux vidéo; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 4-Europe (lieu de production du savoir); 5-Autrice; _Nettoyé

Lions & Jackals: the Politics of Far Cry 2 - Albor, Jorge (Well Played 2.0: Video Games, Value and Meaning, 2010)
Keywords: 1-Jeux vidéo; 2-Histoire/Historiographie critique; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); _Nettoyé

Cultural code: video games and Latin America - Penix-Tadsen, Phillip (The MIT Press, 2016)
How culture uses games and how games use culture: an examination of Latin America's gaming practices and the representation of the region's cultures in games. Video games are becoming an ever more ubiquitous element of daily life, played by millions on devices that range from smart phones to desktop computers. An examination of this phenomenon reveals that video games are increasingly being converted into cultural currency. For video game designers, culture is a resource that can be incorporated into games; for players, local gaming practices and specific social contexts can affect their playing experiences. In Cultural Code, Phillip Penix-Tadsen shows how culture uses games and how games use culture, looking at examples related to Latin America. Both static code and subjective play have been shown to contribute to the meaning of games; Penix-Tadsen introduces culture as a third level of creating meaning. Penix-Tadsen focuses first on how culture uses games, looking at the diverse practices of play in Latin America, the ideological and intellectual uses of games, and the creative and economic possibilities opened up by video games in Latin America—the evolution of regional game design and development. Examining how games use culture, Penix-Tadsen discusses in-game cultural representations of Latin America in a range of popular titles (pointing out, for example, appearances of Rio de Janeiro's Christ the Redeemer statue in games from Call of Duty to the tourism-promoting Brasil Quest). He analyzes this through semiotics, the signifying systems of video games and the specific signifiers of Latin American culture; space, how culture is incorporated into different types of game environments; and simulation, the ways that cultural meaning is conveyed procedurally and algorithmically through gameplay mechanics. Source: Publisher
Section: ix, 333 pages : illustrations ; 24 cm.
Keywords: 1-Jeux vidéo; 2-Analyses formalistes; 2-Approches sociologiques; 2-Étude de la réception; 2-Étude des représentations; 3-Amérique centrale (corpus analysé); 3-Amérique du Sud (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); _Nettoyé

Race, Colonial History and National Identity: Resident Evil 5 as a Japanese Game - Martin, Paul (Games and Culture, 2018)
Resident Evil 5is a zombie game made by Capcom, featuring a White Americanprotagonist and set in Africa. This article argues that approaching this as a Japanesegame reveals aspects of a Japanese racial and colonial social imaginary that are missedif this context of production is ignored. In terms of race, the game presents hybridracial subjectivities that can be related to Japanese perspectives of Blackness andWhiteness, where these terms are two poles of difference and identity throughwhich an essentialized Japanese identity is constructed in what Iwabuchi calls“strategic hybridism.” In terms of colonialism, the game echoes structures of Japa-nese colonialism through which Japanese colonialism is obliquely memorialized and a“normal” Japanese global subjectivity can be performed.
Keywords: 1-Jeux vidéo; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); _Nettoyé

Influence of Black Masculinity Game Exemplars on Social Judgments - Dill, Karen E.; Burgess, Melinda C. (Simulation and Gaming, 2013)
In this investigation, the authors ask how media exemplars of Black masculinity influence the views of and intentions toward other Black men. An experiment compared the effects of exposure to Black video game characters fitting the exemplar thug or street criminal (e.g., Carl Johnson from GRAND THEFT AUTO: SAN ANDREAS) versus exemplars of professional Black men (e.g., political leaders), on evaluations of an unknown and unrelated Black or White political candidate and on pro-Black attitudes. Results revealed significant interactions of exemplar type and candidate race on favorability and capability candidate ratings and on pro-Black attitudes. These data demonstrate the power of mass media exemplars of Black masculinity to prime meaningfully different outcomes in viewers. As the face of gaming evolves with advances in technology, so too should the characterization of race in games.
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Étude de la réception; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; _Nettoyé

Gaming: essays on algorithmic culture - Galloway, Alexander R. (University of Minnesota Press, 2006)
Considers the video game as a distinct cultural form that demands a unique interpretive framework. This book analyzes video games as something to be played rather than as texts to be read, and traces how the "algorithmic culture" created by video games intersects with theories of visuality, realism, allegory, and the avant-garde.
Section: 1 v. (XIII-143 p.) : illustrations ; 22 cm
Keywords: 1-Jeux vidéo; 2-Histoire/Historiographie critique; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des industries culturelles; 2-Étude des représentations; 4-Amérique du Nord (lieu de production du savoir); _Nettoyé

Mondes profanes: enseignement, fiction et histoire - Éthier, Marc-André 1969-; Lefrançois, David 1976-; Joly-Lavoie, Alexandre; Buysse, Alexandre. (Presses de l'Université Laval, 2018)
"Les bandes dessinées, chansons, films, jeux vidéos, musées, reconstitutions, romans, séries télévisées et voyages occupent de plus en plus de place dans la vie des élèves. Comment exploiter en classe ces biens, loisirs et services culturels d'histoire pour que les élèves posent de mieux en mieux certains actes mentaux que les historiennes et historiens doivent effectuer lorsqu'elles et ils adoptent leur pratique? Pour répondre à cette question, les auteures et auteurs de cet ouvrage explorent les usages scolaires possibles et souhaitables des produits qui ne sont pas associés à l'histoire savante et sur l'exploitation didactique de ce que la Loi québécoise sur les biens culturels désigne comme "?une oeuvre d'art, un bien historique, un monument ou un site historique ... une oeuvre cinématographique, audiovisuelle, photographique, radiophonique ou télévisuelle?". Les auteures et auteurs s'intéressent à des oeuvres qui ne sont pas créées pour l'école, mais qui peuvent néanmoins servir aux enseignantes et enseignants pour faire apprendre l'histoire aux élèves."–Résumé de l'éditeur.
Section: xvi, 515 pages ; 23 cm
Keywords: 1-Jeux vidéo; 2-Histoire/Historiographie critique; 2-Humanités numériques; 2-Méthodologie de recherche décoloniale; 2-Pédagogie décoloniale; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; _Nettoyé; _À analyser; _À nettoyer; _À vérifier-Cinéma; _À vérifier-Histoire de l'art; _À vérifier-Télé

The Meanings of Racist and Sexist Trash Talk for Men of Color: A Cultural Sociological Approach to Studying Gaming Culture - Ortiz, Stephanie M (New Media & Society, 2019)
Scholars have documented how people of color experience gaming culture as violent, yet it is unclear how this violence shapes conceptualizations of gaming culture. Undertaking a cultural sociological approach that foregrounds meaning-making, I demonstrate that trash talk is a useful site to explore how social actors construct and negotiate gaming culture. Analyzing data from 12 qualitative interviews with men of color, I argue that trash talk is a practice of boundary-making that reproduces racism and sexism. Respondent narratives about gaming culture vis-à-vis trash talk thus show how gaming culture is socially constructed in everyday interactions, and bound to cultural repertoires and structural conditions that exist outside of gaming. This study provides a potential avenue to explore the socially constructed and dynamic nature of gaming culture and gamer identity.
Keywords: 1-Jeux vidéo; 2-Genre et sexualité; 2-Étude de la réception; 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; _Nettoyé

Gender and Race in the Gaming World - Nakamura, Lisa (Society and the Internet : how networks of information and communication are changing our lives, 2019)
Age is not alone in shaping real and imagined differences in Internet use. Racial and gender-based stereotypes abound and need to be empirically challenged. This chapter explores the relationships between race, gender, sexuality, and digital cultures in one increasingly significant digital domain—gaming. With a review of previous scholarship on race, gender, and gaming, the author shows that we see few signs of a “post-racial” society being brought into being. In fact, gaming is a digital activity where racism and sexism are commonplace. The chapter thus leaves us with questions about why, when the Internet is a potentially powerful leveling tool in the quest for democracy and fairness, does it continue to be defined by egregious sexism and racism?
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Genre et sexualité; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des représentations; 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; _Nettoyé

The International Encyclopedia of Media Studies: Media History and the Foundations of Media Studies - Valdivia, Angharad N.; Nerone, John C.; Mayer, Vicki; Mazzarella, Sharon R.; Parameswaran, Radhika E.; Scharrer, Erica; Darling-Wolf, Fabienne; Gates, Kelly (Wiley-Blackwell, 2013)
Keywords: 1-Cinéma; 1-Jeux vidéo; 1-TV; 2-Analyses formalistes; 2-Approches sociologiques; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude de la réception; 2-Étude des industries culturelles; 2-Étude des représentations; 4-Amérique du Nord (lieu de production du savoir); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; _Nettoyé; _À analyser; _À nettoyer; _À vérifier-Cinéma; _À vérifier-Télé

Race and Media: Critical Approaches - Lopez, Lori Kido (New York University Press, 2020)
1. Racism and Mainstream Media / Lori Kido Lopez – 2. Image Analysis and Televisual Latinos / Mary Beltrán – 3. Visualizing Mixed Race and Genetics / Meshell Sturgis and Ralina L. Joseph – 4. Listening to Racial Injustice / Dolores Inés Casillas and Jennifer Lynn Stoever – 5. Branding Athlete Activism / Jason Kido Lopez – 6. The Burden of Representation in Asian American Television / Peter X. Feng – 7. Indigenous Video Games / Jacqueline Land – 8. Applying Latina/o Critical Communication Theory to Anti-Blackness / Mari Castañeda – 9. Asian American Independent Media / Jun Okada – 10. Remediating Trans Visuality / Amy Villarejo – 11. Intersectional Distribution / Aymar Jean Christian – 12. Podcasting Blackness / Sarah Florini – 13. Black Twitter as Semi-Enclave / Raven Maragh-Lloyd – 14. Arab Americans and Participatory Culture / Sulafa Zidani – 15. Diaspora and Digital Media / Lia Wolock – 16. Disrupting News Media / Meredith D. Clark – 17. Latinx Audiences as Mosaic / Jillian M. Báez – 18. Media Activism in the Red Power Movement / Miranda J. Brady – 19. Black Gamers' Resistance / Kishonna L. Gray – 20. Cosmopolitan Fan Activism / Susan Noh.
Keywords: 1-Jeux vidéo; 1-TV; 2-Genre et sexualité; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 2-Étude des représentations; 3-Amérique centrale (corpus analysé); 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; _Nettoyé; _À analyser; _À nettoyer; _À vérifier-Cinéma; _À vérifier-Télé

Representations of Africans in Popular Video Games in the U.S - Bayeck, Rebecca Y.; Asino, Tutaleni I.; Young, Patricia A. (Journal For Virtual Worlds Research, 2018)
Studies investigating the representation of Africans and other ethnicities are scarce in video game literature. Using a content analysis approach, this paper examines Africans’ representation in ten of the most popular games of 2014 in the United States based on industry market research reports. The findings show that Africans are underrepresented in video games explored in this study. The study also reveals that African characters in these games did not play leading roles in the storyline. Results are discussed as they pertain to Africans’ representation in video games, media effect, and media literature. This exploratory study broadens the discussion on representation in video games to other ethnicities and shows the need for studies on representation in contemporary video games that include understudied ethnicities.
Number: 2
Keywords: 1-Jeux vidéo; 2-Étude des représentations; 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; _Nettoyé

Exploring the Plurality of Black Women's Gameplay Experiences - Rankin, Yolanda A.; Han, Na-eun (Proceedings of the 2019 CHI Conference on Human Factors in Computing Systems, 2019)
Few gender-focused studies of video games explore the gameplay experiences of women of color, and those that do tend to only emphasize negative phenomena (i.e., racial or gender discrimination). In this paper, we conduct an exploratory case study attending to the motivations and gaming practices of Black college women. Questionnaire responses and focus group discussion illuminate the plurality of gameplay experiences for this specific population of Black college women. Sixty-five percent of this population enjoy the ubiquity of mobile games with casual and puzzle games being the most popular genres. However, academic responsibilities and competing recreational interests inhibit frequent gameplay. Consequently, this population of Black college women represent two types of casual gamers who report positive gameplay experiences, providing insights into creating a more inclusive gaming subculture.
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude de la réception; 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; _Nettoyé

The Privilege of Immersion: Racial and Ethnic Experiences, Perceptions, and Beliefs in Digital Gaming - Passmore, Cale J.; Birk, Max V.; Mandryk, Regan L. (Proceedings of the 2018 CHI Conference on Human Factors in Computing Systems, 2018)
People of color comprise a large proportion of the US player base, yet are systematically and grossly underrepresented in digital games. We constructed a survey to assess if players perceive this underrepresentation, how they experience these representations, and sample their beliefs about diversity and gaming. Mixed-methods analyses show significant differences between players of color and White players on perception of racial norms in gaming, effects on behavior, emotions, player satisfaction, engagement, and beliefs stemming from a lack of diversity. Players from all races-ethnicities overwhelmingly expressed a desire for greater diversity. We discuss reasons why our methodology shows higher dissatisfaction than previous research and discuss our findings in the context of industry's challenge to meet audience demands for greater racial diversity in games.
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Étude de la réception; 2-Étude des représentations; 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; _Nettoyé

Racial Diversity in Indie Games: Patterns, Challenges, and Opportunities - Passmore, Cale J.; Yates, Rowan; Birk, Max V.; Mandryk, Regan L. (Extended Abstracts Publication of the Annual Symposium on Computer-Human Interaction in Play, 2017)
Although gamers of color constitute a large part of the digital gaming player base in the US, they are systematically and enormously underrepresented by in-game characters in AAA titles. To extend these findings to indie games, we examine 80 titles and show that the pattern of lack of racial diversity holds. We discuss implications for the industry and players, and present challenges that must be addressed to increase diversity in racial representations of characters in games.
Keywords: 1-Jeux vidéo; 2-Histoire/Historiographie critique; 2-Étude des industries culturelles; 2-Étude des représentations; 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; _Nettoyé

Can the Subaltern Play and Speak or Just be Played With? - Leonard, David J. (Handbook of Research on Effective Electronic Gaming in Education, 2009)
This chapter examines and responds to the silencing, resistance to any intrusion of questions about race and racism, and overall erasure of race from the debates and broader discourse concerning video game culture. It not only provides insight into the nature and logics guiding claims of colorblindness, but also connects the ideologies and culture of denial to the broader racial discourse of post-civil rights America. Hoping to inspire debate and transformative knowledge sharing, this chapter additionally offers a textually-based racial analysis of Outlaw Volleyball as an example of the type of critical examination required to move beyond a culture that often reduces bodies and voices of people of color to objects of gaze, ridicule, and consumption while denying any sorts of criticism and questions regarding the racial meaning and texts evident within much of today’s gaming.
Google-Books-ID: Re8tGpC6_PsC
Keywords: 1-Jeux vidéo; 2-Genre et sexualité; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 4-Amérique du Nord (lieu de production du savoir); _Nettoyé

Handbook of Research on Effective Electronic Gaming in Education - Ferdig, Richard E. (Information Science Reference, 2009)
Games and gaming have always been an important part of society and culture. Within the last 35 years, due to numerous technology innovations, electronic games in many formats have not only become ubiquitous in everyday recreational life but have also permeated many professional fields and disciplines for multiple purposes including teaching and learning.The Handbook of Research on Effective Electronic Gaming in Education presents a framework for understanding games for educational purposes while providing a broader sense of current related research. Compiling over 50 groundbreaking research studies from leading international authorities in the field, this advanced and uniquely comprehensive reference is a must-have for academic and research libraries and for all those interested in expanding their theoretical and practical knowledge of the exciting field of electronic gaming.
Google-Books-ID: Re8tGpC6_PsC
Keywords: 1-Jeux vidéo; 2-Humanités numériques; 5-Auteur.rice PANDC; 5-Autrice; _Nettoyé

Gender and Racial Stereotypes in Popular Video Games - Mou, Yi; Peng, Wei (Handbook of Research on Effective Electronic Gaming in Education, 2009)
While the violent content of video games has caused wide concern among scholars, gender, and racial stereotypes in video games are still an understudied area. The purpose of this chapter is to provide a better understanding of the stereotypical phenomenon in video games. The book chapter first provides a comprehensive review of previous studies conducted upon gender-role and racial portrayals in video games. Then a small-scale content analysis on a sample of official trailers, introductory sequences and covers of 19 of the most popular video games is introduced. Finally, the implications of stereotype in video games and the possible social and psychological impacts on players, especially adolescent players, are discussed.
Google-Books-ID: Re8tGpC6_PsC
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude de la réception; 2-Étude des représentations; 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé

The Racialized Experiences of Video Games - Venegas, Mario (McNair Scholars Research Journal, 2013)
This research explores the ways different people experience the racial content of video games. Building on DeVane and Squire, this research speaks to content analyses literature that shows games as modern minstrelsies. Using Bonilla-Silva’s definition of Racial Ideology in conjunction with Winddance-Twine’s concept of Racial Literacy, I examined racial ideology and its role as an interpretative framework. I also used Bourdieu's notion of cultural capital to account for video game cultural knowledge. Data were collected through personal interviews where participants played the video game Grand Theft Auto: The Ballad of Gay Tony for 30-50 minutes. A sample of 31 participants covering variation in gender, gaming experience, and race answered questions assessing their racial ideology, then played the game introduction, and finally, answered questions assessing interpretations of game content. Racially aware people with little gaming experience echoed the content analysis minstrelsy findings while colorblind racist non-gamers believed the content accurately represented the world. However, deeper familiarity with gaming and other mass media opened up a new interstitial space for challenging the racial status quo. Racially aware gamers saw the franchises as lampooning the shallow stereotypes in mainstream society. More importantly, with a more sophisticated media context, many colorblind racist gamers also saw racial representations as intentionally offensive. Gamers herein create inventive, non-threatening, but meaningful ways to address racialization across a spectrum of racial literacies. As a result, content analyses need a richer understanding of the experiences of video games for consumers.
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Étude de la réception; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); _Nettoyé

Gender, Race, and Class in Media a Critical Reader - Dines, Gail.; Humez, Jean M. (SAGE Publications, 2015)
Incisive analyses of mass media - including such forms as talk shows, MTV, the Internet, soap operas, television sitcoms, dramatic series, pornography, and advertising-enable this provocative third edition of Gender, Race and Class in Media to engage students in critical mass media scholarship. Issues of power related to gender, race, and class are integrated into a wide range of articles examining the economic and cultural implications of mass media as institutions, including the political economy of media production, textual analysis, and media consumption. Throughout, Gender, Race and Class in Media examines the mass media as economic and cultural institutions that shape our social identities, especially in regard to gender, race, and class.
Section: 1 vol. (XIV-761 p.) : ill. ; 26 cm
Keywords: 1-Cinéma; 1-Jeux vidéo; 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des industries culturelles; 2-Étude des représentations; 4-Amérique du Nord (lieu de production du savoir); 4-Europe (lieu de production du savoir); 4-Océanie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; _Nettoyé; _À analyser; _À nettoyer; _À vérifier-Cinéma; _À vérifier-Télé

“Live in Your World, Play in Ours”: Race, Video Games, and Consuming the Other - Leonard, David J. (SIMILE: Studies In Media & Information Literacy Education, 2003)
As the nascent field of computer games research and games studies develops, one rich area of study will be a semiotic analysis of the tropes, conventions, and ideological sub-texts of various games. This article examines the centrality of race and gender in the narrative, character development, and ideologies of platform video games, paying particular attention to the deployment of stereotypes, the connection between pleasure, fantasy and race, and their link to instruments of power. Video games represent a powerful instrument of hegemony, eliciting ideological consent through a spectrum of white supremacist projects.
Keywords: 1-Jeux vidéo; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 4-Amérique du Nord (lieu de production du savoir); _Nettoyé

Don't Hate the Player, Hate the Game: The Racialization of Labor in World of Warcraft - Nakamura, Lisa (Critical Studies in Media Communication, 2009)
This article examines the racialization of informational labor in machinima about Chinese player workers in the massively multiplayer online role playing game World ofWarcraft. Such fan-produced video content extends the representational space of thegame and produces overtly racist narrative space to attach to a narrative that, whilecarefully avoiding explicit references to racism or racial conflict in our world, is premised upon a racial war in an imaginary world*the World of Azeroth. This profiling activityis part of a larger biometric turn initiated by digital culture’s informationalization of thebody and illustrates the problematics of informationalized capitalism. If late capitalism ischaracterized by the requirement for subjects to be possessive individuals, to make claims to citizenship based on ownership of property, then player workers are unnatural subjects in that they are unable to obtain avatarial self-possession. The painful paradox of this dynamic lies in the ways that it mirrors the dispossession of information workers in the Fourth Worlds engendered by ongoing processes of globalization. As long as Asian ‘‘farmers’’ are figured as unwanted guest workers within the culture of MMOs, user-produced extensions of MMO-space like machinima will most likely continue to depict Asian culture as threatening to the beauty and desirability of shared virtual space in the World of Warcraft.
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 3-Amérique du Nord (corpus analysé); 3-Asie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé

Looking for Leroy: Illegible Black Masculinities - Neal, Mark Anthony (New York University Press, 2013)
Mark Anthony Neal’s Looking for Leroy is an engaging and provocative analysis of the complex ways in which black masculinity has been read and misread through contemporary American popular culture. Neal argues that black men and boys are bound, in profound ways, to and by their legibility. The most “legible” black male bodies are often rendered as criminal, bodies in need of policing and containment. Ironically, Neal argues, this sort of legibility brings welcome relief to white America, providing easily identifiable images of black men in an era defined by shifts in racial, sexual, and gendered identities. Neal highlights the radical potential of rendering legible black male bodies—those bodies that are all too real for us—as illegible, while simultaneously rendering illegible black male bodies—those versions of black masculinity that we can’t believe are real—as legible. In examining figures such as hip-hop entrepreneur and artist Jay-Z, R&B Svengali R. Kelly, the late vocalist Luther Vandross, and characters from the hit HBO series The Wire, among others, Neal demonstrates how distinct representations of black masculinity can break the links in the public imagination that create antagonism toward black men. Looking for Leroy features close readings of contemporary black masculinity and popular culture, highlighting both the complexity and accessibility of black men and boys through visual and sonic cues within American culture, media, and public policy. By rendering legible the illegible, Neal maps the range of identifications and anxieties that have marked the performance and reception of post-Civil Rights era African American masculinity.
Google-Books-ID: sKRFmvIVcEIC
Keywords: 2-Étude des industries culturelles; 2-Étude des représentations; 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; _Nettoyé; _À analyser; _À nettoyer; _À vérifier-Cinéma; _À vérifier-Histoire de l'art; _À vérifier-Télé

Game over: Asian Americans and Video Game Representation - Phi, Thien-bao Thuc (Transformative Works and Cultures, 2009)
Even video games by Asian creators tend to depict primarily white characters or reference Asian stereotypes such as kung fu fighters or yakuza thugs. Games depicting the Vietnam war are particularly troubling for Asian players expected to identify with white characters. As the game industry continues to expand, its representation of Asians and Asian Americans must change.
Keywords: 1-Jeux vidéo; 2-Étude des industries culturelles; 2-Étude des représentations; 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé

Crash Override: How Gamergate (Nearly) Destroyed My Life, and How We Can Win the Fight Against Online Hate - Quinn, Zoë (PublicAffairs, 2017)
You've heard the stories about the dark side of the internet – hackers, #gamergate, anonymous mobs attacking an unlucky victim, and revenge porn – but they remain just that: stories. Surely these things would never happen to you. Zoe Quinn used to feel the same way. She is a video game developer whose ex-boyfriend published a crazed blog post cobbled together from private information, half-truths, and outright fictions, along with a rallying cry to the online hordes to go after her. They answered in the form of a so-called movement known as #gamergate–they hacked her accounts; stole nude photos of her; harassed her family, friends, and colleagues; and threatened to rape and murder her. But instead of shrinking into silence as the online mobs wanted her to, she raised her voice and spoke out against this vicious online culture and for making the internet a safer place for everyone. In the years since #gamergate, Quinn has helped thousands of people with her advocacy and online-abuse crisis resource Crash Override Network. From locking down victims' personal accounts to working with tech companies and lawmakers to inform policy, she has firsthand knowledge about every angle of online abuse, what powerful institutions are (and aren't) doing about it, and how we can protect our digital spaces and selves.Crash Override offers an up-close look inside the controversy, threats, and social and cultural battles that started in the far corners of the internet and have since permeated our online lives. Through her story – as target and as activist – Quinn provides a human look at the ways the internet impacts our lives and culture, along with practical advice for keeping yourself and others safe online.
Google-Books-ID: gpvUDQAAQBAJ
Keywords: 1-Jeux vidéo; 2-Genre et sexualité; 2-Étude des industries culturelles; 4-Europe (lieu de production du savoir); 5-Autrice; 5-Créatrice; _Nettoyé

Outside Oneself in World of Warcraft: Gamers' Perception of the Racial Self-other - Rowland, Thomas D.; Barton, Amanda C. (Transformative Works and Cultures, 2011)
The popularity of massively multiplayer online role-playing games (MMORPGs) has created a unique, heavily populated virtual reality wherein player characters are explicitly differentiated by the physical characteristics of their avatars. To investigate the way real-life race perceptions influence these adopted player-character identities, we invited MMO players to participate in an online survey. In this study, we are particularly interested in overlap, or deviation, between real-life racial perceptions and the perception of fictional fantastic races (elves, dwarves). On the basis of the data collected, we found that whether players consciously associate themselves with their avatars or consciously dissociate themselves from their avatars, real-life racial tendencies unconsciously manifest through players' choices of their avatars and in their interactions with other players within the game environment.
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Étude des représentations; 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; _Nettoyé

Learning Race and Ethnicity: Youth and Digital Media - Everett, Anna (The MIT Press, 2008)
An exploration of how issues of race and ethnicity play out in a digital media landscape that includes MySpace, post-9/11 politics, MMOGs, Internet music distribution, and the digital divide.
Section: 1 v. (IX-197 p.) : illustrations ; 27 cm
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude de la réception; 2-Étude des industries culturelles; 2-Étude des représentations; 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; _Nettoyé

Featuring Females: Feminist Analyses of Media - Cole, Ellen; Daniel, Jessica Henderson (American Psychological Association, 2005)
"Featuring Females analyzes the portrayals of women in a variety of outlets, including reality television shows, films, print and electronic news programming, magazines, video games, and commercial advertising. A highly esteemed group of scholars and researchers provides informed, original psychological study, and their thought-provoking findings address the ways in which aging, race/ethnicity, body image, gender roles, sexual orientation and relationships, and violence are treated in the media. Featuring Females is a diverse volume, exploring images and characterizations of women young and old and inspiring discussion of the effects that these representations have on girls, women, and society at large"–
OCLC: 57754311
Keywords: 1-Jeux vidéo; 2-Analyses formalistes; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude des industries culturelles; 2-Étude des représentations; 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; 5-Créateur.rice PANDC; 5-Créateur.rice noir.e; 5-Créatrice; _Nettoyé; _À analyser; _À vérifier-Cinéma; _À vérifier-Télé

Television and the Children of Ethnic Minorities - Comstock, George; Cobbey, Robin E. (Journal of Communication, 1979)
The issues that are raised by ethnic status are not exclusive to ethnicity but represent circumstances much wider in occurrence that appear more often among ethnic minorities.
Keywords: 1-TV; _Nettoyé; _À analyser; _À nettoyer; _À vérifier-Télé

The Virtual Census: Representations of Gender, Race and Age in Video Games - Williams, Dmitri; Martins, Nicole; Consalvo, Mia; Ivory, James (New Media & Society, 2009)
A large-scale content analysis of characters in video games was employed to answer questions about their representations of gender, race and age in comparison to the US population. The sample included 150 games from a year across nine platforms, with the results weighted according to game sales. This innovation enabled the results to be analyzed in proportion to the games that were actually played by the public, and thus allowed the first statements able to be generalized about the content of popular video games. The results show a systematic over-representation of males, white and adults and a systematic under-representation of females, Hispanics, Native Americans, children and the elderly. Overall, the results are similar to those found in television research. The implications for identity, cognitive models, cultivation and game research are discussed.
Keywords: 1-Jeux vidéo; 2-Genre et sexualité; 2-Étude des représentations; 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; _Nettoyé

Racial Logics, Franchising, and Video Game Genres: The Lord of the Rings - Young, Helen (Games and Culture, 2016)
This article explores the ways game adaptations engage with existing popular culture constructions of race within the framework of commercial franchises. Its focus is on games which are part of the so-called “Frodo Franchise” based on Peter Jackson’s Lord of the Rings and The Hobbit films. It considers the role played by licensing agreements, the conventions, and ludic elements of different game genres, the need for new characters and narratives to keep audiences engaged with an existing world, and the opportunity games offer for interactive exploration of a digital world, to illuminate both the challenges to and the opportunities for disrupting conventional representations of race and difference.
Keywords: 1-Cinéma; 1-Jeux vidéo; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 3-Europe (corpus analysé); 4-Océanie (lieu de production du savoir); 5-Autrice; _Nettoyé

Virtual Anti-racism: Pleasure, Catharsis, and Hope in Mafia III and Watch Dogs 2 - Leonard, David J. (Humanity & Society, 2020)
This essay examines the representation and consumption of Mafia III and Watch Dogs 2 as a site of catharsis, pleasure, and empowerment. Through not only its repre-sentation of white supremacy but its rendering of intervention and transformation as violence, Mafia III and Watch Dogs 2 offer a powerful inscription of gratification. In other words, offering both a space of oppositional gaze and a virtual reality invested in challenging gaze based in violence,Mafia IIIandWatch Dogs 2 reimagine the conventions of both video games and violence.
Keywords: 1-Jeux vidéo; 2-Histoire/Historiographie critique; 2-Humanités numériques; 2-Étude de la réception; 2-Étude des représentations; 4-Amérique du Nord (lieu de production du savoir); _Nettoyé

Not a Hater, Just Keepin' It Real The Importance of Race- and Gender-Based Game Studies - Leonard, David J. (Games and Culture, 2006)
Notwithstanding the presence of extreme racialized tropes within the world of videogames, public discourses continue to focus on questions of violence, denying the impor-tance of games in maintaining the hegemonic racial order. Efforts to exclude race (andintersections with gender, nation, and sexuality) from public discussions through its era-sure and the acceptance of larger discourses of colorblindness contribute to a problematicunderstanding of video games and their significant role in contemporary social, political,economic, and cultural organization. How can one truly understand fantasy, violence,gender roles, plot, narrative, game playability, virtual realities, and the like without ex-amining race, racism, and/or racial stratification—one cannot. This article challengesgame studies scholars to move beyond simply studying games to begin to offer insightand analysis into the importance of race and racialized tropes within virtual reality andthe larger implications of racist pedagogies of video games in the advancement of Whitesupremacy.
Keywords: 1-Jeux vidéo; 2-Genre et sexualité; 2-Méthodologie de recherche décoloniale; 2-Étude des industries culturelles; 2-Étude des représentations; 4-Amérique du Nord (lieu de production du savoir); _Nettoyé

Beyond Hate: White Power and Popular Culture - King, C. Richard; Leonard, David J. (Routledge, 2016)
Beyond Hate offers a critical ethnography of the virtual communities established and discursive networks activated through the online engagements of white separatists, white nationalists, and white supremacists with various popular cultural texts, including movies, music, television, sport, video games, and kitsch. Outlining the ways in which advocates of white power interpret popular cultural forms, and probing the emergent spaces of white power popular culture, it examines the paradoxical relationship that advocates of white supremacy have with popular culture, as they finding it to be an irresistible and repugnant reflection of social decay rooted in multiculturalism. Drawing on a range of new media sources, including websites, chat rooms, blogs and forums, this book explores the concerns expressed by advocates of white power, with regard to racial hierarchy and social order, the crisis of traditional American values, the perpetuation of liberal, feminist, elitist ideas, the degradation of the family and the fetishization of black men. What emerges is an understanding of the instruments of power in white supremacist discourses, in which a series of connections are drawn between popular culture, multiculturalism, sexual politics and state functions, all of which are seen to be working against white men. A richly illustrated study of the intersections of white power and popular culture in the contemporary U.S., and the use of use cyberspace by white supremacists as an imagined site of resistance, Beyond Hate will appeal to scholars of sociology and cultural studies with interests in race and ethnicity, popular culture and the discourses of the extreme right.
Keywords: 1-Jeux vidéo; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des représentations; 4-Amérique du Nord (lieu de production du savoir); _Nettoyé; _À nettoyer; _À vérifier-Cinéma; _À vérifier-Télé

Replaying Empire: Racialized Violence, Insecure Frontiers, and Displaced Terror in Contemporary Video Games - Leonard, David J.; King, C. Richard (Ethnicity and Race in a Changing World, 2009)
In the wake of 9/11, US popular culture has played an important role in the manufacture of consent and the mediation of contradictions. In particular, video games have aff orded the production of interactive, narrative spaces for the reassertion of race, nation, and gender. Through a close reading of two video games, Gun and Ghost Recon Advanced Warfighter 2, we unpack the insecurities of empire and how racialized violence, colonial categories, and territorial claims work to resecure Whiteness, masculinity, and Americanness. Special attention is given to the militarization of video games and rhetorical struggles over the meaning of race and culture amid the ‘War on Terror’.
Keywords: 1-Jeux vidéo; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); _Nettoyé

Playing to Win: Sports, Video Games, and the Culture of Play - Brookey, Robert Alan; Oates, Thomas Patrick (Indiana University Press, 2015)
In this era of big media franchises, sports branding has crossed platforms, so that the sport, its television broadcast, and its replication in an electronic game are packaged and promoted as part of the same fan experience. Editors Robert Alan Brookey and Thomas P. Oates trace this development back to the unexpected success of Atari's Pong in the 1970s, which provoked a flood of sport simulation games that have had an impact on every sector of the electronic game market. From golf to football, basketball to step aerobics, electronic sports games are as familiar in the American household as the televised sporting events they simulate. This book explores the points of convergence at which gaming and sports culture merge.
Keywords: 1-Jeux vidéo; 2-Genre et sexualité; 2-Étude des industries culturelles; 2-Étude des représentations; 4-Amérique du Nord (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Autrice; _Nettoyé

Computational Blackness: The Procedural Logics of Race, Game, and Cinema, or How Spike Lee's Livin' Da Dream Productively "Broke" a Popular Video Game - Russworm, TreaAndrea M. (Black Camera, 2018)
How have video games evolved to now create meaningful stories about race and sports? This essay examines how Spike Lee's film-within-a-game, Livin' Da Dream (2015), reproduces some existing procedural and racial logics that reflect the desire to constantly manage and contain the centrality of black athletic greatness in mainstream sports and video game culture. While Lee's long-form cinematic model for turning sports video games into narrative games has been emulated across the medium as a whole, fans and gamers continually discuss the film as an evidently "broken" part of the popular NBA 2K video game series. As I argue here, however, the film-within-a-game productively insists on a default blackness when it functions as what I call "procedural cinema" (a rules and process based narrative). Ultimately, in functioning procedurally, Lee's otherwise conservative melodramatic story serves as a particularly instructive example of how computational blackness may, in systematically subverting the rules of the game, signify disruptively both within and against the machine.
Keywords: 1-Cinéma; 1-Jeux vidéo; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; _Nettoyé; _À nettoyer; _À vérifier-Cinéma

Kill the Overseer!: the Gamification of Slave Resistance - Lauro, Sarah Juliet. (University of Minnesota Press, 2020)
Profiles and problematizes digital games that depict Atlantic slavery and "gamify" slave resistance. In videogames emphasizing plantation labor, the player may choose to commit small acts of resistance like tool-breaking or working slowly. Others dramatically stage the slave's choice to flee enslavement and journey northward, and some depict outright violent revolt against the master and his apparatus. This work questions whether the reduction of a historical enslaved person to a digital commodity in games such as Mission US, Assassin's Creed, and Freedom Cry ought to trouble us as a further commodification of slavery's victims, or whether these interactive experiences offer an empowering commemoration of the history of slave resistance.
Keywords: 1-Jeux vidéo; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; _Nettoyé

Zombie theory: a reader - Lauro, Sarah Juliet (University of Minnesota Press, 2017)
Zombies first shuffled across movie screens in 1932 in the low-budget Hollywood film White Zombie and were reimagined as undead flesh-eaters in George A. Romero's The Night of the Living Dead almost four decades later. Today, zombies are omnipresent in global popular culture, from video games and top-rated cable shows in the United States to comic books and other visual art forms to low-budget films from Cuba and the Philippines. The zombie's ability to embody a variety of cultural anxieties–ecological disaster, social and economic collapse, political extremism–has ensured its continued relevance and legibility, and has precipitated an unprecedented deluge of international scholarship. Zombie studies manifested across academic disciplines in the humanities but also beyond, spreading into sociology, economics, computer science, mathematics, and even epidemiology. Zombie Theory collects the best interdisciplinary zombie scholarship from around the world. Essays portray the zombie not as a singular cultural figure or myth but show how the undead represent larger issues: the belief in an afterlife, fears of contagion and technology, the effect of capitalism and commodification, racial exclusion and oppression, dehumanization. As presented here, zombies are not simple metaphors; rather, they emerge as a critical mode for theoretical work. With its diverse disciplinary and methodological approaches, Zombie Theory thinks through what the walking undead reveal about our relationships to the world and to each other.
Keywords: 2-Histoire/Historiographie critique; 2-Étude des représentations; 5-Autrice; _Nettoyé; _À analyser; _À nettoyer; _À vérifier-Cinéma

The Transatlantic Zombie: Slavery, Rebellion, and Living Death - Lauro, Sarah Juliet. (Rutgers University Press, 2015)
Our most modern monster and perhaps our most American, the zombie that is so prevalent in popular culture today has its roots in African soul capture mythologies. The Transatlantic Zombie provides a more complete history of the zombie than has ever been told, explaining how the myth's migration to the New World was facilitated by the transatlantic slave trade, and reveals the real-world import of storytelling, reminding us of the power of myths and mythmaking, and the high stakes of appropriation and homage. Beginning with an account of a probable ancestor of the zombie found in the Kongolese and Angolan regions of seventeenth-century Africa and ending with a description of the way, in contemporary culture, new media are used to facilitate zombie-themed events, Sarah Juliet Lauro plots the zombie's cultural significance through Caribbean literature, Haitian folklore, and American literature, film, and the visual arts. The zombie entered US consciousness through the American occupation of Haiti, the site of an eighteenth-century slave rebellion that became a war for independence, thus making the figuration of living death inseparable from its resonances with both slavery and rebellion. Lauro bridges African mythology and US mainstream culture by articulating the ethical complications of the zombie's invocation as a cultural conquest that was rebranded for the American cinema. As The Transatlantic Zombie shows, the zombie is not merely a bogeyman representing the ills of modern society, but a battleground over which a cultural war has been fought between the imperial urge to absorb exotic, threatening elements, and the originary, Afro-disaporic culture's preservation through a strategy of mythic combat
Keywords: 2-Histoire/Historiographie critique; 2-Étude des représentations; 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; _Nettoyé; _À analyser; _À nettoyer; _À vérifier-Cinéma

Landscapes of Empire in Metal Gear Solid V The Phantom Pain - Murray, Soraya (Critical Inquiry, 2018)
Keywords: 1-Jeux vidéo; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; _Nettoyé

On Video Games: the Visual Politics of Race, Gender and Space - Murray, Soraya (I.B. Tauris & Co. Ltd., 2018)
Today over half of all American households own a dedicated game console and gaming industry profits trump those of the film industry worldwide. In this book, Soraya Murray moves past the technical discussions of games and offers a fresh and incisive look at their cultural dimensions. She critically explores blockbusters likeThe Last of Us, Metal Gear Solid, Spec Ops: The Line, Tomb Raider and Assassin's Creed to show how they are deeply entangled with American ideological positions and contemporary political, cultural and economic conflicts.As quintessential forms of visual material in the twenty-first century, mainstream games both mirror and spur larger societal fears, hopes and dreams, and even address complex struggles for recognition. This book examines both their elaborately constructed characters and densely layered worlds, whose social and environmental landscapes reflect ideas about gender, race, globalisation and urban life. In this emerging field of study, Murray provides novel theoretical approaches to discussing games and playable media as culture. Demonstrating that games are at the frontline of power relations, she reimagines how we see them - and more importantly how we understand them.
Keywords: 1-Jeux vidéo; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; _Nettoyé

Gendered Play, Racialized Reality: Black Cyberfeminism, Inclusive Communities of Practice, and the Intersections of Learning, Socialization, and Resilience in Online Gaming - Richard, Gabriela T.; Gray, Kishonna L. (Frontiers, 2018)
In lieu of an abstract, here is a brief excerpt of the content: introduction While digital games hold promise for learning and socialization, emerging research and popular debates have critiqued inclusive access to these practices and literacies. This essay examines digital games for their potential to integrate diverse individuals and communities for learning and socialization, especially in online play and broadcasting of gameplay. For example, a level of cultural competency can be attained in well-developed games to overcome essentialist notions and assumptions about women and people of color. Using Black Cyberfeminism as a theoretical lens to make sense of players’ experiences, and Racialized Pedagogical Zones (RPZs) as an analytical frame to situate digital games’ entrenched ideologies of race and racism, we contend that games offer highly unproblematized depictions but have extreme potential for cultural competency. We further utilize Communities of Practice (CoP) as a frame for understanding and interrogating equitable access to community-supported collaborative learning and mastery within game culture, more broadly, and interest-driven guilds, clans, and affinity spaces, more specifically. In our extension of CoP, we integrate inclusive to highlight the resistive and resilient strategies employed by supportive communities for diverse women in addressing the systematic nature of oppression and power relations that undergird communities of practice, particularly in marked gendered spaces such as gaming. Marginalizing practices in game culture have become more widely publicized and understood in recent years, most notably because of high profile incidents of harassment. However, representations of women and racial or ethnic minorities by the gaming industry have also been problematic historically. For instance, since the 1980s video games have been critiqued for the hypersexualization of women and women are often the victims of misogynistic [End Page 112] vitriol, as the incidents around Gamergate have exposed. People of color are featured in largely stereotypical ways and are all but absent from the gaming industry. Queer gamers and gamers with dis/abilities are almost entirely absent and, when present, are not depicted fairly. This differential treatment appears to have a symbiotic relationship with the exclusion of marginalized players. As researchers have noted, Internet technologies and virtual communities operate in a manner that benefits privileged identities. These unequal power relations are accepted as legitimate and are embedded in the cultural practices of digital technology. Nevertheless, many gamers—most notably women—have resisted this perpetual state of inequity and the dominant narrative of power, control, and exclusion. Although some in gaming contend that these are not overt practices of exclusion, many players and scholars acknowledge the existence of symbolic exclusion, where those who are valued have the privilege to define legitimate practice and participation within gaming culture. The unequal power relations operating within the gaming community influence not only what gamers consume but also what they learn about themselves and others. Further, the racialized and gendered consumptive practices through gaming are often taken for granted. Commercial gaming culture is, with few exceptions, complicit in these exclusionary practices by continuing to design at a deficit, despite these increasingly apparent realities. But many gamers have begun to resist and challenge not only the imagery but also the practices that sustain white, masculine privilege within gaming and technology in general. While these practices have yet to reach a critical mass to disrupt the power structure operating within game culture as a whole, they exist counter to the mainstream and empower the marginalized operating within them. While the literature will provide an overview of these practices, our purpose is to privilege the resistance and resilience strategies of the marginalized to disrupt the traditional narrative while they empower themselves. We utilize Kimberlé Crenshaw’s framework of intersectionality to reflect on identity, recognizing that “the problem with identity politics is not that it fails to transcend difference, as some critics charge, but rather the opposite—that it frequently conflates or ignores intragroup differences.” We also want to caution that while we focus on players who have historically been the marginalized in gaming culture and game research, we recognize that men...
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Genre et sexualité; 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; _Nettoyé

Diffusion of Innovation Theory and Xbox Live: Examining Minority Gamers' Responses and Rate of Adoption to Changes in Xbox Live - Gray, Kishonna L. (Bulletin of Science, Technology & Society, 2012)
This article examines the response of minority gamers as they adopt new innovations in Xbox Live. Using diffusion of innovation theory, specific attention is given to gamers’ rate of adoption of the new Xbox Live environment, which was a recent update to the Xbox Live interface. By employing virtual ethnography, observations, and interviews reveal that gaming duration and gender are significant factors in identifying a gamer’s successful rate of adoption of the new innovation. Female participants reveal that Xbox Live intentionally targets males as the default gamer and enact changes based on their needs. The research concludes with a plea to Xbox Live to acknowledge minority gamers such as women to incorporate their needs within the decision-making process of new innovations.
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude de la réception; 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; _Nettoyé

Feminism in Play - Gray, Kishonna L.; Voorhees, Gerald; Vossen, Emma (Palgrave Macmillan, 2018)
Feminism in Play focuses on women as they are depicted in video games, as participants in games culture, and as contributors to the games industry. This volume showcases women's resistance to the norms of games culture, as well as women's play and creative practices both in and around the games industry. Contributors analyze the interconnections between games and the broader societal and structural issues impeding the successful inclusion of women in games and games culture. In offering this framework, this volume provides a platform to the silenced and marginalized, offering counter-narratives to the post-racial and post-gendered fantasies that so often obscure the violent context of production and consumption of games culture.
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Genre et sexualité; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude de la réception; 2-Étude des industries culturelles; 2-Étude des représentations; 4-Amérique du Nord (lieu de production du savoir); 4-Amérique du Sud (lieu de production du savoir); 4-Europe (lieu de production du savoir); 4-Océanie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; _Nettoyé

Race, Gender, and Deviance in Xbox Live: Theoretical Perspectives from the Virtual Margins - Gray, Kishonna L. (Anderson Pub., 2015)
Race, Gender, and Deviance in Xbox Live provides a much-needed theoretical framework for examining deviant behavior and deviant bodies within one of the largest virtual gaming communities—Xbox Live. Previous research on video games has focused mostly on violence and examining violent behavior resulting from consuming this medium. This limited scope has skewed criminologists' understanding of video games and video game culture. Xbox Live has proven to be more than just a gaming platform for users. It has evolved into a multimedia entertainment outlet for more than 20 million users. This book examines the nature of social interactions within Xbox Live, which are often riddled with deviant behavior, including but not limited to racism and sexism. The text situates video games within a hegemonic framework deploying whiteness and masculinity as the norm. The experiences of the marginalized bodies are situated within the framework of deviance as they fail to conform to the hegemonic norm and become victims of racism, sexism, and other types of harassment.
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Genre et sexualité; 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; _Nettoyé

Woke Gaming: Digital Challenges to Social Injustice - Gray, Kishonna L.; Leonard, David J. (University of Washington Press, 2018)
From #Gamergate to the daily experiences of marginalization among gamers, gaming is entangled with mainstream cultures of systematic exploitation and oppression. Whether visible in the persistent color line that shapes the production, dissemination, and legitimization of dominant stereotypes within the industry itself, or in the dehumanizing representations often found within game spaces, many video games perpetuate injustice and mirror the inequities and violence that permeate society as a whole. Drawing from the latest research and from popular games such as World of warcraft and Tomb raider, Woke gaming examines resistance to spaces of violence, discrimination, and microaggressions in gaming culture. The contributors of these essays identify strategies to detox gaming culture and orient players toward progressive ends, illustrating the power and potential of video games to become catalysts for social justice
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Genre et sexualité; 2-Méthodologie de recherche décoloniale; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des industries culturelles; 2-Étude des représentations; 4-Amérique du Nord (lieu de production du savoir); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 4-Océanie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; _Nettoyé

Do you Identify as a Gamer? Gender, Race, Sexuality, and Gamer Identity - Shaw, Adrienne (New Media & Society, 2012)
The demand for minority representation in video games often focuses on proving that members of marginalized groups are gamers. In turn, it is asserted that the gaming industry should focus on appealing to these players via targeted content. Being targeted as a gamer, however, does not a gamer make. Identity as a gamer intersects with other identities like gender, race, and sexuality. Negative connotations about gaming lead people to not identify as gamers, and even to not play video games. This article concludes, based on interview data, that those invested in diversity in video games must focus their attention on the construction of the medium, and not the construction of the audience as such. This shift in academic attention is necessary to develop arguments for representation in games that do not rely on marking groups as specific kinds of gaming markets via identifiers like gender, race, and sexuality.
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude des représentations; 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; _Nettoyé

A Call to Action for Video Game Studies in an Age of Reanimated White Supremacy - Russworm, Treaandrea M. (The Velvet Light Trap, 2018)
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Étude des représentations; 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; _Nettoyé

Power in the Visual: Examining Narratives of Controlling Black Bodies in Contemporary Gaming - Gray, Kishonna L. (The Velvet Light Trap, 2018)
Keywords: 1-Jeux vidéo; 2-Étude des représentations; 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; _Nettoyé

Are We There Yet? The Politics and Practice of Intersectional Game Studies - Shaw, Adrienne (The Velvet Light Trap, 2018)
Keywords: 1-Jeux vidéo; 2-Genre et sexualité; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; _Nettoyé

Lyrical Nationalism: Gender, Friendship, and Excess in 1970s Hindi Cinema - Jha, Priya (The Velvet Light Trap, 2003)
In this essay I examine one particular feature of the films, the song-and-dance sequences, as they draw attention to the fractious nature of the postcolonial nation while simultaneously attempting to construct a space for the articulation of a consolidated national identity.
Keywords: 1-Cinéma; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; 5-Identités diasporiques; _Nettoyé; _À analyser; _À nettoyer; _À vérifier-Cinéma

Japanese Culture Through Videogames - Hutchinson, Rachael (Routledge/Taylor & Francis Group, 2019)
"Examining a wide range of Japanese videogames, including arcade fighting games, PC-based strategy games and console JRPGs, this book assesses their cultural significance and shows how gameplay and context can be analyzed together to understand videogames as a dynamic mode of artistic expression. Well-known titles such as Final Fantasy, Metal Gear Solid, Street Fighter and Katamari Damacy are evaluated in detail, showing how ideology and critique are conveyed through game narrative and character design as well as user interface, cabinet art, and peripherals. This book also considers how Japan' has been packaged for domestic and overseas consumers, and how Japanese designers have used the medium to express ideas about home and nation, nuclear energy, war and historical memory, social breakdown and bioethics. Placing each title in its historical context, Hutchinson ultimately shows that videogames are a relatively recent but significant site where cultural identity is played out in modern Japan. Comparing Japanese videogames with their American counterparts, as well as other media forms, such as film, manga and anime, Japanese Culture Through Videogames will be useful to students and scholars of Japanese culture and society, as well as Game Studies, Media Studies and Japanese Studies more generally."– Provided by publisher.
Keywords: 1-Jeux vidéo; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Europe (lieu de production du savoir); 5-Autrice; _Nettoyé

History First-Hand: Memory, the Player and the Video Game Narrative in the Assassin's Creed Games - Menon, Lakshmi (Rupkatha Journal on Interdisciplinary Studies in Humanities, 2015)
This paper will look at the convergence of the interactive free flow of video games and the questioning and revisioning of historical continuity using the example of the Assassin's Creed series by Ubisoft. With a story that exists simultaneously in the modern day and the 15th century, the games allow the player to take control of characters and alter, or make possible, events recognisable as historical fact. It plays with both history and memory and history as memory, as the life of the primary player character is being relived through the genetic memories of one of his descendants. Being highly narrative-bound, the Assassin's Creed games use, via the medium of the screen, the rift between history and memory as a central element of narrative, theme, and game design, which this paper will explore. Furthermore, using theories of convergence this paper will examine how video games provide a new, interactive mode of storytelling that is rapidly becoming representative of our age.
Keywords: 1-Jeux vidéo; 2-Histoire/Historiographie critique; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; _Nettoyé

Digitalizing the Narratives: Structural Analysis of Far Cry 3 - Ali, Eeshan; Karati, Arijit (Rupkatha Journal on Interdisciplinary Studies in Humanities, 2015)
Every form has its own structure. Technically, though there is a difference between computer games and literature, but structurally both reflect same modes of the presentation which is carried out by certain codes. The present paper looks into the structural analysis of computer games with technical aspect as well as literature aspect with special reference to Far Cry 3, a first person action adventure computer game which received several awards and critically acclaimed for its graphics, story line, features etc. Besides this paper relocate Vladimir Propp’s theory of narrative function in Far Cry 3 and decode how the computer game with the help of certain binary opposition and codes have become one of the fundamental tools of getting entertained in the popular imagination.
Keywords: 1-Jeux vidéo; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 3-Amérique du Nord (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé

Games Studies India Adda Talk #9: Lakshmi Menon - Game Studies India Adda (Game Studies India Adda, 2021)
Unreal City: Expressions of Tokyo in Video Games Abstract: Games today, with advancements in graphic design and capability of the platforms on which they can be played, are almost akin to interactive films- in which the player not only consumes the movie-like storyline, but becomes an active participant in the narrative and its outcomes. Worldbuilding in video games has strong connections with the approaches contained in semiotics, as it is not with the images on the screen that players interact, but rather the world that is represented by the images. I intend to examine Tokyo as a virtually constructed game world in three separate texts – Atlus Studios’ Persona 5, Sega’s Yakuza series and Square Enix’s The World Ends with You. The fictionally created cityscapes of contemporary Japan have become ideal spaces for the video games to propagate, their construction in the texts can be seen a form of techno-orientalism that is simultaneously rooted in both Eastern and Western imagination. Each of these texts constructs its own version of Tokyo that, while being recognisable through the use of specific semiotic markers, is also sufficiently different enough to make it a virtual, unreal, space. However, what must be noted is that this space only exists in its entirety when it is interacted upon by the player. Using Lefebvre’s conceptualisation of social space into spatial practice, representations of space and representational space, this paper seeks to look at how the construction of the digital city is not merely a 3D representation thereof, but points where interactivity and narrative coincide. It is through the locus of these two elements that the player comprehends and navigates game narratives. My purpose will therefore be to look at the constructions of Tokyo within video games as data visualisations of spaces that become places through interactivity and comprehension of the player. About Laxmi: Lakshmi Menon is Assistant Professor of English at VTM NSS College, Trivandrum, and a PhD candidate at the Centre for English Studies, Jawaharlal Nehru University, where her thesis is a study of Harry Potter slash fanfiction and fan communities. She is currently researching Boys Love fan cultures in South Asia, while her wider research interests also include digital humanities, popular culture and queer literature.
Keywords: 1-Jeux vidéo; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; _Nettoyé

Game Studies India Adda Talk #8: Prabhash Tripathy - Game Studies India Adda (Game Studies India Adda, 2021)
What/Who is playing Cyborg: An investigation of the 'Gamer' as a figure - Prabhash Ranjan Tripathy The current talk is an exploration into the question as to whether the gamer figure that emerged in India in the 1990s can be thought of as a cyborg and if so, then what kind of cyborg is the gamer? Can one think of the gamer-cyborg as a posthuman liberatory figure or is the gamer-cyborg still all too human? The intent of the paper in asking these questions and problematizing the figure of the Gamer is to launch an investigation into the more pressing question that one encounter in the wake of the cyber/information-turn, that is, how does one contemplate, comprehend, and articulate the 'new' in the identities that are formed and acquired with the advent of what has been identified as the cyber/information turn in culture? Can the connection between biological and technological be the sole basis for considering figurations like the Gamer as something new? Can they be thought of as a new subjectivity, a new politics, a new relationship to power? Is this 'new' democratic, free of discrimination and based on an egalitarian principle or is the 'new' an optimization of old and existing structures and modes of oppression? Bio: Prabhash Ranjan Tripathy was born in Odisha, India. He completed his B.A. (Hons) English, M.A. in English literature and M.A. in Comparative Indian Literature from University of Delhi. He is currently a PhD scholar at the school of Arts and Aesthetics, Jawaharlal Nehru University. Has submitted his MPhil dissertation titled ‘Playing Cyborg: A study of the Gamer in the Videogame Parlours of Delhi and Mussoorie’, following which was a doctoral fellow at the International Research Centre “Interweaving Performance Cultures” and is currently working on his PhD dissertation titled ‘Between WorkStation and PlayStation: The Cultural Location of Videogames in India’. Interest areas include Superhero comic books, Anime, Video Games, Combat Sports, and Mythology. He is fascinated by felines and loves to trek, read, write, click and play.
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé

Games Studies India Adda Talk #7: Samya Brata Roy - Game Studies India Adda (Game Studies India Adda, 2021)
Hitman 2’s Mumbai mission, just like the film Extraction, looks at the oriental space in a similar ‘diseased’ yellow filter which is akin to the Mexico of Breaking Bad. Here, we have the perfect orientalist reduction of a culture. By digitising Mumbai and creating it into a gamic world, it produces a rather lazily translated and racialised appropriation of this particular South Asian space. The essential orientalist gaze thus reinforces the binary between the ‘I’ and the ‘other’: where the ‘I’ is the foreign Agent 47 and the ‘other’ are the yellow dwellers of Mumbai. The NPCs react to Agent 47 in awe as if a white man is a miracle of nature which they have never seen before. Not only that, but they also interact with themselves in a very essentialist way. The tea shops/kiosks are literally written as 'Chaye Dukan' (which is a direct translation for 'Tea Shop'). Not only does this point at a lack of research but also a lazy design. No matter how inferior a place is, no one names their establishment in a direct translation to their colonial/capitalist overlords. It becomes nothing but a city ‘lost in translation’. In this paper, I will read the Mumbai mission of Hitman 2 as a cultural artefact where the game scape becomes a techno-orientalist commodity. Like any other Literary text which fetishizes the ‘other’, Hitman 2 also becomes such a ‘digital/ludic’ text which manages to define the ‘Indian’ in its own myopic way. The discourse propagated thus reinforces the idea of ‘India’ or the ‘Orient’ as the literal plaything of the West. Thus, I will expand by elaborating on how the creators become a part of the greater orientalized theatricality by indulging in a form of ‘identity tourism’ (Nakamura ’96), where the autonomy of creating a cultural space takes the form of an essentialist fetish. About Samya : Samya Brata Roy (He/Him) is currently in the final semester of his M.A in English Literature from The English and Foreign Languages University in Hyderabad. Mainly his interests lie in and around the modalities of Digital Narratives, which he also tries to create at thepenarchist (wordpress.com). He is associated as a SIG facilitator with DHARTI (dhdharti.in), as a transcriber with The Canterbury Tales Project and as database contributor with Electronic Literature Knowledge Base | ELMCIP. He works in the field of Disability Studies by assisting in research. He is also passionate about teaching and inclusion and pursued it by teaching slum kids.
Keywords: 1-Jeux vidéo; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé

Games Studies India Adda #6: Zahra Rizvi - Game Studies India Adda (Game Studies India Adda, 2021)
Playing Dystopia: Searching for the Neganthropocene in Papers, Please and Orwell The way we play games and the way games play us is constantly changing. The physical shrinking of space can no longer be compensated by expansive gamescapes which otherwise provided a reprieve from diminishing access to space in 20th and 21st century childhood (Mayra, An Introduction to Game Studies). Gamescapes, increasingly, are becoming neo-explorations of “other people simulators” characterized by a suffocating hypernearing of the experience of the dystopia (Lucas Pope). Often ‘mundane’ mirrors of real-life situations, these dystopian games place the player in movement-limiting, choice-limiting challenging scenarios from where a fulfilling ending is more often than not impossible. I look at two of these dystopian games that offer covertly disruptive gameplay through alienating, often disembodied, simulation as a strategy for playing dystopia: Lucas Pope’s Papers, Please and Osmotic Studios’ Orwell. Closely engaging with issues of surveillance, digital governance, neurotechnology, illegal profiling, and ultimately, survival in a dystopia of technics, these games with their multiple endings caused by the smallest, seemingly most insignificant of differences in gameplay become crucial in their playing out of the possibilities of the neganthropocene.
Keywords: 1-Jeux vidéo; 2-Humanités numériques; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé

Games Studies India Adda #5: Souvik Mukherjee - Game Studies India Adda (Game Studies India Adda, 2021)
Speaking to the 'Missing' Player: Subaltern Poetics in Indian Videogames The degree of interactivity and agency of the player-character in videogames is often a moot question in Games Studies discourses (Atkins 2002 , Juul 2004, Salen and Zimmerman 2001). The assumption is that whether illusory or real, agency is an important element that drives the plot of digital games. To assume this, however, is to argue from a position of privilege and some videogames use their in-game mechanics to emphasise this. The assumption of a selfhood by the player while playing a digital game is the precondition to the experience of agency. Such a precondition is hardcoded into the gameplay on the basis of a default notion of empowerment and entitlement. What happens, however, in the case of the character that does not provide this sense of agency or for the game wherein such an experience of selfhood may not be possible? Using a well-worn but very relevant term from Postcolonial discourses, one could ask what happens where the game is about the Subaltern. Considering videogame studies from non-Western and South-South perspectives, such a default assumption of selfhood or agency may be challenged. Elsewhere (Mukherjee 2017), I have cited examples from the Cameroon, Indonesia and India that begin to address this challenge. Here, I wish to take two games from India as my texts for close-reading (or close-play) and show how a different poetics operates; indeed, my primary objective is to enquire into how the videogame as a narrative medium, which is by default apparently premised on agency, functions for the subaltern.
Keywords: 1-Jeux vidéo; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé

Games Studies India Adda Talk #4: Poonam Chowdhury - Game Studies India Adda (Game Studies India Adda, 2021)
Thatgamecompany’s 'Journey' (2012) is a videogame like no other. This serene atmospheric game came out at a time when fast-paced, aggressive, AAA games were (and still are) the norm. Soon after the game’s release in 2012, thatgamecompany’s courage and hard work started getting the appreciation it deserved. 'Journey' has won several ‘Game of the Year’ awards and received several other awards and nominations, including a ‘Best Score Soundtrack for Visual Media’ nomination for the 2013 Grammy Awards. For this Game Studies India Adda Talk, I will be discussing (read: gushing over) this game’s brilliant visual and auditory art, wordless storytelling techniques, and one-of-a-kind multiplayer experience. Please join me on this talk and let's take a ‘journey’ like no other. Pun intended. Thank you and I hope you all have a wonderful new year. 🙂 Here’s the game trailer: https://www.youtube.com/watch?v=Ie4iz...
Keywords: 1-Jeux vidéo; 2-Histoire/Historiographie critique; 2-Étude des industries culturelles; 3-Amérique du Nord (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; _Nettoyé

Games Studies India Adda Talk #3 The vanishing Curator - Game Studies India Adda (Game Studies India Adda, 2020)
Playing back to the Empire, in videogames, is rife with tensions. The imperialist sentiment inherent in reverse-colonist discourse featured in most strategy-based videogames like Europa Universalis IV, where the player could conquer Europe playing for the Marathas, has been noted by Souvik Mukherjee (2017) as playing into the colonial logic while futilely trying to challenge it. Studio Oleomingus, an Indian two-man game studio, is one of the few involved in a different experiment. Their mythical game Somewhere, chronicling a postmodernist search for identity and narrative in the forgotten city of Kayamgadh, has generated significant spin-offs into its universe. With attention to one such spin-off, I will focus critical attention on the issue of the postcolonial gaming of the Museum in A Museum of Dubious Splendors. I will examine the New Museological implications of A Museum of Dubious Splendors, keeping in mind Museologist Eilean Hooper-Greenhill’s assertion of museums embodying “the power to name, to represent common sense, to create official versions, to represent the social world, to represent the past” (Hooper-Greenhill 2001: 2). Oleomingus’ own description of A Museum, as an adaptation of edited, mangled, contested short stories by a fictional Urdu writer, Mir Umar Hassan, eschews the linear narrative production of the colonial museum for a game of meanings, where the player enters rooms according to his choice and constructs his/her own “quiet game about prosaic objects and spurious histories.” ("A Museum" 2018) The paper would take this into account and examine the reconceptualization of the museum space with respect to James Clifford’s sense of museums being “contact zones”: A Museum’s lack of any curator, with its curious blend of colonial and native tales and banal objects defamiliarised by “spurious histories” lends itself to questions of playing the Empire back according to a different episteme, through subaltern histories that the colonial museum space silenced. Paying close attention to the question of postcolonial spatiality in this game, I will analyze the historiographical implications of these identity-scatterings and recuperations at constant play in the structure of the game. Keywords: Museum Studies, Thing Theory, Game studies, Marginal identity, Postcolonial Studies
Keywords: 1-Jeux vidéo; 2-Humanités numériques; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé

GSI Adda Talk #2 Riko Banerjee What is it like to be a Gamer or pursue Game Studies in India? - Game Studies India Adda (Game Studies India Adda, 2020)
Video gaming is one of the most popular hobbies in the world, with the gaming industry grossing more revenue than the movie and the music industry combined. The estimated number of gamers across the whole world as of August 2020 is 2.7 billion, which is more than one-third of the world population. The benefits of gaming, as cited by numerous researchers, include a boost in confidence, improved cognitive abilities, stress relief, improved problem-solving skills, enhanced social skills among dyslexic kids, and among many others. Even though video gaming as a hobby and career is slowly getting recognition in India, majority of the population still scoff at the activity, shunning gamers and game researchers alike, citing out-of-context and sometimes even false media propaganda. The challenges faced by a typical gamer in India include lack of information, budget limitation, lack of support from parents and teachers when it comes to teenage gamers, and the overall lack of gaming as a mainstream culture among countrymen. As for someone who wants to pursue Game Studies, there is currently little to no provision for that due to the tightly knit education system in the country and the utter lack of educational institutes offering courses on game studies. We go on to further discuss all of the above challenges and experiences faced by a gamer or someone who wants to pursue game studies in India, in our detailed talk that is scheduled on November 21, 2020.
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Étude de la réception; 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé

First Person Encounters #5: Abhi, creator of Venba - Game Studies India Adda
Venba is a narrative cooking game, where you play as an Indian mom, who immigrates to Canada with her family in the 1980s. Players will cook various dishes and restore lost recipes, hold branching conversations and explore in this story about family, love, loss and more. More on Steam: https://store.steampowered.com/app/14.... Developer, Abhi, gives Game Studies India an exclusive preview talking about identity, nostalgia, memory and of course, food. In conversation with Poonam Chowdhury and Souvik Mukherjee.
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Étude des industries culturelles; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Créateur.rice PANDC; 5-Identités diasporiques; _Nettoyé

First-Person Encounters #4: Poornima Seetharaman - Game Studies India Adda (Game Studies India Adda, 2021)
First Person Encounters is a series of podcasts presented by Games Studies India, about our first experiences with Games while growing up in India. This our third podcast where we talk with Poornima Seetharaman. She is the first Indian to be inducted in the Women in Games (WIGJ) Hall of Fame and is also the lead game designer at Zynga. Hear as we talk about her foray in the world of gaming.
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Humanités numériques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; 5-Créateur.rice PANDC; 5-Créatrice; _Nettoyé

First-Person Encounters #3: Prof. Xenia Zeiler - Game Studies India Adda (Game Studies India Adda, 2021)
First Person Encounters is a series of podcasts presented by Games Studies India, about our first experiences with Games while growing up in India. This our third podcast where we interview Xenia Zeiler, an associate professor of South Asian studies at the University of Helsinki, Finland. Her research is situated at the intersection of digital media, religion, and culture, with a focus on India and the worldwide Indian community.
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; _Nettoyé

First-Person Encounters #2: Satyajit Chakaborty - Game Studies India Adda (Game Studies India Adda, 2021)
First Person Encounters is a series of podcasts presented by Games Studies India, about our first experiences with Games while growing up in India. This our second podcast where we interview Satyajit Chakraborty, a game developer, game designer and researcher. He also founded Flying Robots Studios in 2012 and has made various unique games. Here he talks about his first experiences with gaming in India.
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; 5-Créateur.rice PANDC; _Nettoyé

First Person Encounters #1: A Game Studies India Adda Podcast - Game Studies India Adda (2020)
The First Podcast in a series of podcasts presented by Games Studies India, about our first experiences with Games while growing up in India.
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Étude de la réception; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; _Nettoyé

Torture, Play, and the Black Experience - Trammell, Aaron (G|A|M|E Games as Art, Media, Entertainment, 2020)
This essay considers how the experience of Black folk descended from slaves in North America helps us to rethink a definition of play that has been largely informed by scholars and philosophers working within a White European tradition. This tradition of play, theorized most famously by Dutch Art Historian Johan Huizinga, French Sociologist Roger Caillois, Swiss Psychologist Jean Piaget, and New Zealander Brian Sutton-Smith reads play in a mostly positive sense and asserts that certain practices, namely torture, are taboo and thus cannot be play. I argue that this approach to play is short-sighted and linked to a troubling global discourse that renders the experiences of Black, Indigenous, and People of Color (BIPOC) invisible. In other words, by defining play only through its pleasurable connotations, the term holds an epistemic bias towards people with access to the conditions of leisure. Indeed, torture helps to paint a more complete picture where the most heinous potentials of play are addressed alongside the most pleasant, yet in so doing the trauma of slavery is remembered. In rethinking this phenomenology, I aim to detail the more insidious ways that play functions as a tool of subjugation. One that hurts as much as it heals and one that has been complicit in the systemic erasure of BIPOC people from the domain of leisure.
Keywords: 1-Jeux vidéo; 2-Histoire/Historiographie critique; 2-Méthodologie de recherche décoloniale; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 4-Europe (lieu de production du savoir); _Nettoyé

Games Studies India Adda #10: Aaron Trammell - Game Studies India Adda (Game Studies India Adda, 2021)
Repairing Play: Toward A Black Phenomenology of Play In this talk I offer the term "repairing play" or play that both repairs the damages wrought by colonialism, and is itself a form of reparations, in an effort to consider how we might advance an understanding of play that is inclusive of BIPOC people. I focus in on the Black American experience in order to better theorize a moment of repair, and consider how torture is memorialized in play through song. I also will draw on examples from Black artists and game designers in order to help show how their work in repairing play draws from the tradition of Black radical aesthetics. Bio: Aaron Trammell is an Assistant Professor of Informatics and Core Faculty in Visual Studies at UC Irvine. He writes about how BIPOC experience the games they play. Specifically, he is interested in how games and play further values of white privilege and hegemonic masculinity in geek culture. Aaron's work has been cited in Wired and featured on National Public Radio. It has been published in Game Studies, Games & Culture, New Media & Society, and G|A|M|E. He is the Editor-in-Chief of the journal Analog Game Studies and the Multimedia editor of the Sounding Out!
Keywords: 1-Jeux vidéo; 2-Histoire/Historiographie critique; 2-Méthodologie de recherche décoloniale; 2-Théories et épistémologie postcoloniales et décoloniales; 4-Europe (lieu de production du savoir); _Nettoyé

Japanese Video Games and Comics in Singapore: Issues in Popularization, Localization and their Implications - Ng Wai-ming, Benjamin (N.D., 1999)
OCLC: 882102421
Keywords: 1-Jeux vidéo; 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé

Play, History and Politics: Conceiving Futures Beyond Empire - Fordyce, Robbie (Games and Culture, 2021)
The worlds of games are important places for us to think about time, as demonstrated by historical game studies in evaluating the past, but there is a role for games to help us consider the future as well. Because games are, to some extent, systems, they facilitate a systems thinking approach that connects the material to the immaterial. Because games also tend to be action-based, they allow thinking through of acts as well as representations. Games allow us to think about a time and place that is different from the present and how it might operate as a system that we could live in. I argue that a post-autonomist method of game analysis requires an explicitly political interpretation that is focused on trying to imagine a political future through experiments in gaming.
Keywords: 1-Jeux vidéo; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Asie (corpus analysé); 4-Océanie (lieu de production du savoir); _Nettoyé

Games Studies India Adda Talk #11: Marcus Toftedahl - Game Studies India Adda (Game Studies India Adda, 2021)
Remember localization! Game localization from an indie development perspective Abstract: The game industry is today a global industry, where digital storefronts are used to distribute the digital product you are developing. This presents a number of challenges for a small scale game developer and localization is one. The talk will focus on game localization from an indie game development perspective. The research is based on data from field studies in Sweden, China and India and is a part of a PhD project conducted at the Division of Game Development at the University of Skövde, Sweden. Bio: Marcus Toftedahl is a game researcher, developer and lecturer at the University of Skövde, Sweden. His main competences lies within game production, game localization and game design, from a practical and research perspective. Marcus has worked at the University of Skövde since 2009 and has since then co-developed the world's first full concentration game writing education at university level and is teaching game design and game production.
Keywords: 1-Jeux vidéo; 2-Étude des industries culturelles; 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Europe (lieu de production du savoir); _Nettoyé

Games Studies India Talk #12: Geoffrey Fernandez - Game Studies India Adda (Game Studies India Adda, 2021)
Counter-Hegemonic Representations of Japanese Cultural Icons in Sekiro Abstract: Through fictional or non-fictional narratives, media representations of the past communicate specific interpretations, which lets users negotiate the past's prospective meanings. Additionally, these cultural constructions of the past are produced and disseminated in the present. Hence, the existing hegemonic power relations influence the depiction and recognition of cultural communities in the construction of the past. Therefore, the approach to framing cultures in pop-culture representations becomes a preponderating factor in how people perceive such cultures and periods. Sekiro: Shadows Die Twice, at first glance, can be considered as a game that follows the same vein of exploiting the western craze for the ninja archetype, as seen in its predecessors like the Onimusha and Tenchu series. However, it takes a bold stance against the persisting ‘self-Orientalist’ framework by reclaiming the ninja myth from marketized exoticization. Borrowing from Said’s theory of Orientalism, I would first like to analyze the existing self-Orientalism in depicting and marketing Japanese cultural icons. I would then like to highlight how this game is not an exoticized cultural artefact and further discuss the implications of such a portrayal in the contexts of representation and authenticity. I conclude that by undercutting innate stereotypes and using inherently Japanese characters, the game reappropriates the agency to depict Japanese cultural icons, from a non-Oriental, non-exoticized viewpoint. Thus, Sekiro: Shadows Die Twice becomes a stand-out in the video game industry in this respect. Bio: Geoffrey Fernandez is a PhD candidate at the Department of Humanities and Social Sciences at the Birla Institute of Technology and Science Pilani, Pilani campus. His doctoral research examines the use of culture, mythology, and folklore in video games.
Keywords: 1-Jeux vidéo; 2-Méthodologie de recherche décoloniale; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé

Politics of Production: Videogames 10 years after Games of Empire - Hammar, Emil L.; de Wildt, Lars; Mukherjee, Souvik; Pelletier, Caroline (Games and Culture, 2021)
2019 marked ten years since the publication of Nick Dyer-Witheford and Greig de Peuter’s Games of Empire, which has become a seminal book in videogame cultural criticism. Ten years later, there is still a pressing need for cultural and materialist criticism of the politics of production within game studies. In putting together this special issue, our hope is to identify new developments in the game industry and academia that are emblematic of 21st-century capitalism. Just as Games of Empire popularised critical political-economic perspectives ten years ago, we encourage others, as the authors in this issue did, to continue and maintain investigations into questions of ownership, privatized property, coercive class relations, military operations and radical struggle. Such analyses are necessary not only to trace but also to open up new directions in game culture and academia for decades to come.
Keywords: 1-Jeux vidéo; 2-Étude des industries culturelles; 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; _Nettoyé

Crab-Rangoons in Kyrat: (Re)Writing South-Asian History in Far Cry 4 - Mukherjee, Souvik (Games and Culture, 2021)
Recent research has started focusing on the representation of history in videogames. Such representation is almost always of mainstream history and usually presented from a Western perspective. Set in a fictitious Himalayan kingdom in South Asia, Ubisoft’s Far Cry 4 is arguably a crucial example of how history is represented using Western and even colonial frameworks and where the narratives that do not emerge from conventional written history are almost always rendered invisible. Using the frameworks of Subaltern Studies and “border-thinking,” this essay attempts to unpack issues of Orientalism and “colonial difference”; it then engages with postcolonial digital humanities and postcolonial game studies to comment on how history is represented in videogames and how the neglected gaps and silences in the game are important in constructing the historiography in videogames. In the process, the essay engages in a debate with current notions of videogame-historiography.
Keywords: 1-Jeux vidéo; 2-Histoire/Historiographie critique; 2-Méthodologie de recherche décoloniale; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé

Independent Videogames: Cultures, Networks, Techniques And Politics - Ruffino, Paolo (Routledge, 2021)
Independent Videogames investigates the social and cultural implications of contemporary forms of independent video game development. Through a series of case studies and theoretical investigations, it evaluates the significance of such a multi-faceted phenomenon within video game and digital cultures. A diverse team of scholars highlight the specificities of independence within the industry and the culture of digital gaming through case studies and theoretical questions. The chapters focus on labor, gender, distribution models and technologies of production to map the current state of research on independent game development. The authors also identify how the boundaries of independence are becoming opaque in the contemporary game industry – often at the cost of the claims of autonomy, freedom and emancipation that underlie the indie scene. The book ultimately imagines new and better narratives for a less exploitative and more inclusive videogame industry. Systematically mapping the current directions of a phenomenon that is becoming increasingly difficult to define and limit, this book will be a crucial resource for scholars and students of game studies, media history, media industries and independent gaming.
Keywords: 1-Jeux vidéo; 2-Analyses formalistes; 2-Approches sociologiques; 2-Genre et sexualité; 2-Humanités numériques; 2-Étude de la réception; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique centrale (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Europe (corpus analysé); 4-Amérique centrale (lieu de production du savoir); 4-Amérique du Nord (lieu de production du savoir); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Auteur.rice LGBTQ+; 5-Auteur.rice PANDC; 5-Autrice; 5-Créateur.rice LGBTQ+; 5-Créateur.rice PANDC; _Nettoyé

Interrogating Evil in Videogames about Violent Conflicts - Hammar, Emil Lundedal; Pötzsch, Holger (The Routledge International Handbook of Perpetrator Studies, 2020)
This contribution interrogates the figure of the perpetrator as it emerges in narrative videogames. First, we provide a brief outlook on some key characteristics of videogames, before we discuss how the specific affordances of this “new” medium offer unprecedented ways of approaching and dealing with perpetrators and perpetration. Finally, we offer concrete examples from three games to illustrate different possible configurations of the playerperpetrator nexus—Yager Development’s Spec Ops: The Line (2012), 11 Bit Studio’s This War of Mine (2015), and Hangar 13’s Mafia III (2016). In contrast to other media, games enable an active exploration of, and participation in, a variety of possible offenses. Rather than merely witnessing evil deeds, players are immersed in simulated environments that demand constant evaluations of complex settings and require decision-making under systemic limitations. This performative aspect of play makes games a unique medium for learning and teaching about the intricate logics and innate dynamics of perpetrations.
Keywords: 1-Jeux vidéo; 2-Histoire/Historiographie critique; 2-Humanités numériques; 2-Pédagogie décoloniale; 2-Étude des représentations; 4-Europe (lieu de production du savoir); _Nettoyé

The Routledge International Handbook of Perpetrator Studies - Knittel, Susanne C.; Goldberg, Zachary J. (Routledge, Taylor & Francis Group, 2020)
"The Routledge International Handbook of Perpetrator Studies provides the first comprehensive overview of this emerging interdisciplinary field in the humanities and social sciences. Featuring contributions by scholars from a wide variety of fields and disciplines, the Handbook charts the growth and development, foundations, key debates, core concerns, and frontiers of Perpetrator Studies. Focusing on genocide, terrorism, and other forms of political mass violence, this Handbook addresses questions of guilt and responsibility, definition, terminology, typology, motivations, group dynamics, memory, trauma, representation, and pedagogy. Offering a thematic and conceptual approach that facilitates a comparative analysis across historical, geographic, and disciplinary lines, the Handbook allows different disciplinary perspectives to confront one another. In so doing, this foundational volume presents contemporary perspectives on longstanding debates whilst also providing new contributions to the field. Written with an interdisciplinary readership in mind, the chapters provide an overview of existing work on a specific topic or issue, delineate current developments within the respective discipline or field, and make suggestions for further research. As such, the book will appeal to scholars across a range of disciplines, including history, sociology, anthropology, criminology, law, philosophy, memory studies, psychology, political science, literary studies, film studies, cultural studies, art history, and education"– Provided by publisher.
Keywords: 1-Histoire de l'art; 1-Jeux vidéo; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 4-Amérique du Nord (lieu de production du savoir); 4-Europe (lieu de production du savoir); 4-Océanie (lieu de production du savoir); 5-Autrice; _Nettoyé; _À analyser; _À nettoyer; _À vérifier-Cinéma; _À vérifier-Histoire de l'art

Ludotopia: Spaces, Places and Territories in Computer Games. - Aarseth, Espen; Günzel, Stephan (Transcipt Verlag, 2019)
Where do computer games "happen"? The articles collected in this pioneering volume explore the categories of "space", "place" and "territory" featuring in most general theories of space to lay the groundwork for the study of spatiality in games. Shifting the focus away from earlier debates on, e.g., the narrative nature of games, this collection proposes, instead, that thorough attention be given to the tension between experienced spaces and narrated places as well as to the mapping of both of these.
OCLC: 1119630732
Keywords: 1-Jeux vidéo; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 5-Auteur.rice PANDC; _Nettoyé

Manufacturing Consent in Video Games—The Hegemonic Memory Politics of Metal Gear Solid V: The Phantom Pain (2015) - Hammar, Emil Lundedal (Nordlit, 2019)
In this article I argue that the structural conditions of global capitalism and postcolonialism encourage game developers to rearticulate hegemonic memory politics and suppress subaltern identities. This claim is corroborated via an application of Edward Herman and Noam Chomsky’s propaganda model to the Japanese-developed video game Metal Gear Solid V: The Phantom Pain. This case study highlights that the hegemonic articulations of colonial histories are not exclusive to Western entertainment products where instead modes of production matter in the ‘manufacturing of mnemonic hegemony’. I also propose that the propaganda model, while instructive, can be improved further by acknowledging a technological filter and the role of the subaltern. Thus, the article furthers the understanding of the relation between production and form in contemporary technological phenomena like video games and how this relation motivates hegemonic articulations of the past in contemporary mass culture.
Keywords: 1-Jeux vidéo; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Europe (lieu de production du savoir)

War Games: Memory, Militarism and the Subject of Play - Hammond, Philip; Pötzsch, Holger (Bloomsbury Publishing USA, 2019)
Many of today's most commercially successful videogames, from Call of Duty to Company of Heroes, are war-themed titles that play out in what are framed as authentic real-world settings inspired by recent news headlines or drawn from history. While such games are marketed as authentic representations of war, they often provide a selective form of realism that eschews problematic, yet salient aspects of war. In addition, changes in the way Western states wage and frame actual wars makes contemporary conflicts increasingly resemble videogames when perceived from the vantage point of Western audiences.This interdisciplinary volume brings together scholars from games studies, media and cultural studies, politics and international relations, and related fields to examine the complex relationships between military-themed videogames and real-world conflict, and to consider how videogames might deal with history, memory, and conflict in alternative ways. It asks: What is the role of videogames in the formation and negotiation of cultural memory of past wars? How do game narratives and designs position the gaming subject in relation to history, war and militarism? And how far do critical, anti-war/peace games offer an alternative or challenge to mainstream commercial titles?
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude de la réception; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Autrice; _Nettoyé

Videogame Wastelands as (Non- )Places and 'Any-Space-Whatevers' - Mukherjee, Souvik (Ludotopia: Spaces, Places and Territories in Computer Games., 2019)
Where do computer games "happen"? The articles collected in this pioneering volume explore the categories of "space", "place" and "territory" featuring in most general theories of space to lay the groundwork for the study of spatiality in games. Shifting the focus away from earlier debates on, e.g., the narrative nature of games, this collection proposes, instead, that thorough attention be given to the tension between experienced spaces and narrated places as well as to the mapping of both of these.
OCLC: 1119630732
Keywords: 1-Jeux vidéo; 3-Amérique du Nord (corpus analysé); 3-Europe (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé

The Lure of Pokémon: Video Games and the Savage Mind - Nakazawa, Shin'ichi (Japan Publishing Industry Foundation for Culture, 2019)
From its humble beginnings as a video game launched in the mid-90s, Pokémon has become a global entertainment franchise, even reaching into the world via "augmented reality" with the mobile game Pokémon GO. In the work, Nakazawa Shinichi argues that the Pokémon worldview is the best contemporary example of Claude Lévi-Strauss's "savage mind" (la pensée sauvage), suggesting that computer games can often be viewed as attempts to reconnect the human unconscious with the true, hidden essence of nature.
Section: 1 v. (129 p.) : illustrations, couv. illustrations en coul. ; 22 cm
Keywords: 1-Jeux vidéo; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé

Video Games and the Global South - Penix-Tadsen, Phillip (ETC Press, 2019)
Redefines games and game culture from south to north, analyzing the social impact of video games, the growth of game development and the vitality of game cultures across Africa, the Middle East, Central and South America, the Indian subcontinent, Oceania and Asia.
OCLC: 1104212185
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Humanités numériques; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des industries culturelles; 3-Afrique (corpus analysé); 3-Amérique centrale (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Asie (corpus analysé); 4-Amérique centrale (lieu de production du savoir); 4-Amérique du Nord (lieu de production du savoir); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; _Nettoyé

Video Games Have Always Been Queer. - Ruberg, Bonnie (New York University Press, 2019)
While popular discussions about queerness in video games often focus on big-name, mainstream games that feature LGBTQ characters, like 'Mass Effect' or 'Dragon Age', Bonnie Ruberg pushes the concept of queerness in games beyond a matter of representation, exploring how video games can be played, interpreted, and designed queerly, whether or not they include overtly LGBTQ content. 'Video Games Have Always Been Queer' argues that the medium of video games itself can-and should-be read queerly. In the first book dedicated to bridging game studies and queer theory, Ruberg resists the common, reductive narrative that games are only now becoming more diverse. Revealing what reading D.A. Miller can bring to the popular 2007 video game 'Portal', or what Eve Sedgwick offers 'Pong', Ruberg models the ways game worlds offer players the opportunity to explore queer experience, affect, and desire. As players attempt to 'pass' in 'Octodad' or explore the pleasure of failure in 'Burnout: Revenge', Ruberg asserts that, even within a dominant gaming culture that has proved to be openly hostile to those perceived as different, queer people have always belonged in video games-because video games have, in fact, always been queer.
OCLC: 1099909377
Keywords: 1-Jeux vidéo; 2-Analyses formalistes; 2-Genre et sexualité; 2-Méthodologie de recherche décoloniale; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 3-Europe (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice LGBTQ+; _Nettoyé

Virtual History: How Videogames Portray the Past - Wainwright, A. Martin (Routledge, 2019)
Virtual History examines many of the most popular historical video games released over the last decade and explores their portrayal of history. The book looks at the motives and perspectives of game designers and marketers, as well as the societal expectations addressed, through contingency and determinism, economics, the environment, culture, ethnicity, gender, and violence. Approaching videogames as a compelling art form that can simultaneously inform and mislead, the book considers the historical accuracy of videogames, while also exploring how they depict the underlying processes of history and highlighting their strengths as tools for understanding history. The first survey of the historical content and approach of popular videogames designed with students in mind, it argues that games can depict history and engage players with it in a useful way, encouraging the reader to consider the games they play from a different perspective. Supported by examples and screenshots that contextualize the discussion, Virtual History is a useful resource for students of media and world history as well as those focusing on the portrayal of history through the medium of videogames.
Google-Books-ID: RZqfDwAAQBAJ
Keywords: 1-Jeux vidéo; 2-Histoire/Historiographie critique; 2-Humanités numériques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); _Nettoyé

Introduction to the Special Issue on Postcolonial Perspectives in Game Studies - Mukherjee, Souvik; Hammar, Emil Lundedal (Open Library of Humanities, 2018)
The treatment of colonialism in video games, barring a few notable exceptions, is marked by a Western and, specifically, late 19th-century imperialist bias. Simultaneously, in the past two decades of multifaceted research and the development of robust theoretical frameworks in the still fledgling discipline of game studies, postcolonial discourses, whether they comprise critiques of imperialism or neocolonialism, have not been prominently highlighted until very recently. A coherent effort to bring together the current research on postcolonialism in video games was also urgently required. Further, the past years has seen a rather persistent, albeit unexpected, emergence of a pro-colonial or pro-imperialist discourse in mainstream academia that even justifies the continuance of empire as an ameliorating influence on the people of the so-called developing countries, most of which had formerly been colonized by European powers.Thus, it is the aim of this issue to address this epistemic omission and counter such bias where it exists by also bridging video games research with larger discussions of postcolonialism in other humanities contexts and disciplines. The various articles in this special issue offer a range of perspectives from epistemological power to theory and praxis in critical academia, to contexts of production and practices of play, to close readings of postcolonial traces in video games. These varying approaches to the analysis of video games and their societal and historical contexts open up the debates further to a diverse set of topics ranging from board games to phone games or from mainstream high-budget console games to indie titles that question colonialism. As video games address issues relating to orientalism, subalternity, and hybridity as well as the current ambiguities in conceiving nationhood and the postcolony, the articles in this issue will also likely adumbrate further serious commentary that will develop both game studies research and current conceptions of the postcolonial.
Number: 2
Keywords: 1-Jeux vidéo; 2-Méthodologie de recherche décoloniale; 2-Théories et épistémologie postcoloniales et décoloniales; 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé

Counterfactual Communities: Strategy Games, Paratexts and the Player’s Experience of History - Apperley, Tom (Open Library of Humanities, 2018)
The genre of history strategy games is a crucial area of study because of what is at stake in the representation of controversial aspects of history in popular culture. Previous work has pointed to various affordances and constraints in the representation of history, based on the framing of the game interface, the alignment of goals with certain strategies and textual criticism of the contents of the games. In contrast, this article examines these games from the perspective of the player’s experience of play in relation to a wider gaming community. It is in these counterfactual communities that players negotiate their individual experience with their knowledge of the history that is presented in the games that they play, indicating that the relationship between digital games, players and history is highly contextual. The relevant practices of players of history strategy games are illustrated with examples from the official and unofficial communities of the Paradox Interactive games Europa Universalis II and Victoria: Empire Under the Sun. The shared paratexts demonstrate how positions are negotiated in relation to the ‘official’ version of history presented in the games. These negotiations are made tangible through the production and sharing of paratexts that remix the official history of the games to include other perspectives developed through counterfactual imaginations. These findings indicate the importance of including perspectives from gaming communities to support other forms of analysis in order to make rigorous observations about the impact of digital games on popular history.
Number: 1
Keywords: 1-Jeux vidéo; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude de la réception; 3-Amérique du Nord (corpus analysé); 3-Europe (corpus analysé); 4-Océanie (lieu de production du savoir); _Nettoyé

Settler Colonialism in the Digital Age: Clash of Clans, Territoriality, and the Erasure of the Native - Euteneuer, Jacob (Open Library of Humanities, 2018)
In the past ten years, two seemingly unconnected fields of study have risen to prominence. Patrick Wolfe’s 2006 theorization of settler colonialism called for the development of a distinct set of literature and analytical tools to analyze the relationship between indigenous peoples and occupying settlers. Meanwhile, Ian Bogost’s 2007 elaboration of the notion of procedural rhetoric provided a theoretical framework to approach the critical analysis of the ideology modeled by a game’s rules and design. While each of these theories have proliferated and prospered within their disciplines, this article seeks to bring the two fields together in order to establish a critical framework that can be used to highlight the presence of settler colonialism in popular mobile videogames, in particular Supercell’s 2012 mobile game Clash of Clans. Within this framework, the essay analyzes how the game engages in a system of play driven by its focus on improvement, progression, and expansion, which ends up operating under the same principles settler colonialism has used to justify the expansion of settler-states and the eradication of indigenous populations. Through an examination of the game’s economy, enemies, maps, and music, the essay connects the game’s systems of play to the embedded nature of settler colonialism in the videogame industry—particularly the mobile or casual scene—and contemporary life in settler-states. The ultimate goal is to explain how social meaning is derived from these types of games and what that means for both players and creators in terms of developing new, progressive opportunities for play.
Number: 1
Keywords: 1-Jeux vidéo; 2-Analyses formalistes; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 3-Europe (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); _Nettoyé

The Work of Postcolonial Game Studies in the Play of Culture - Murray, Soraya (Open Library of Humanities, 2018)
This article considers larger methodological questions of what political work is undertaken when scholars engage in postcolonial critiques of video games within academic intellectual frameworks. What is postcolonial game studies, and what is its purpose, within the context of larger issues of inclusion, representation, diversity, and the challenging of hegemonic power structures? After surveying some of the key literature in postcolonial game studies, the author provides critical frameworks for understanding the means by which these approaches have largely been excluded from video game studies, and their crucial function in operating against the grain of profit and innovation-driven discourses in games. This work is the extension of a larger discussion of inclusion, diversity, and tolerance discourse within the liberal academy, and particularly the functions of postcolonial, postmodern and other critical cultural scholarly interventions. In this article, the author argues for a postcolonial approach to game studies, but one that refuses to be reduced to an institutional cultural labor of due diligence, or according to Slavoj Žižek’s term, a ‘culturalization of politics’. Through the work of Stuart Hall and Sara Ahmed on intellectual diversity work within the context of large systems and academic institutions, this article asserts that the perception that critical theorizations (like postcolonial game studies) exert pressure on efficiency and innovation is greatly outweighed by the rich toolkits they bring to video games as maturing cultural forms.
Number: 1
Keywords: 1-Jeux vidéo; 2-Méthodologie de recherche décoloniale; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Théories et épistémologie postcoloniales et décoloniales; 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; _Nettoyé

Casual Empire: Video Games as Neocolonial Praxis - Harrer, Sabine (Open Library of Humanities, 2018)
As a media form entwined in the U.S. military-industrial complex, video games continue to celebrate imperialist imagery and Western-centric narratives of the great white explorer (Breger, 2008; Dyer-Witheford & de Peuter, 2009; Geyser & Tshalabala, 2011; Mukherjee, 2016). While much ink has been spilt on the detrimental effects of colonial imagery on those it objectifies and dehumanises, the question is why these games still get made, and what mechanisms are at work in the enjoyment of empire-themed play experiences. To explore this question, this article develops the concept of ‘casual empire’, suggesting that the wish to play games as a casual pastime expedites the incidental circulation of imperialist ideology. Three examples – Resident Evil V (2009), The Conquest: Colonization (2015) and Playing History: Slave Trade (2013) – are used to demonstrate the production and consumption of casual empire across multiple platforms, genres and player bases. Following a brief contextualisation of postcolonial (game) studies, this article addresses casual design, by which I understand game designers’ casual reproduction of inferential racism (Hall, 1995) for the sake of entertainment. I then look at casual play, and players’ attitudes to games as rational commodities continuing a history of commodity racism (McClintock, 1995). Finally, the article investigates the casual involvement of formalist game studies in the construction of imperial values. These three dimensions of the casual – design, play and academia – make up the three pillars of the casual empire that must be challenged to undermine video games’ neocolonialist praxis.
Number: 1
Keywords: 1-Jeux vidéo; 2-Analyses formalistes; 2-Histoire/Historiographie critique; 2-Méthodologie de recherche décoloniale; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Nord (corpus analysé); 3-Asie (corpus analysé); 4-Europe (lieu de production du savoir); 5-Autrice; _Nettoyé

Geralt of Poland: The Witcher 3 Between Epistemic Disobedience and Imperial Nostalgia - Majkowski, Tomasz Z. (Open Library of Humanities, 2018)
This article is a reading of The Witcher 3 in relation to postcolonial approaches to Polish culture. It departs from an analysis of an online debate on racial representation in the game as a possible act of epistemic disobedience, and moves on to a consideration of three narrative aspects of the game itself: its representation of political struggle, the ideological stance of the protagonist, and ethnic inspirations in worldbuilding. By referring those three issues to postcolonial analyses of Polish culture, as well as Walter D. Mignolo’s concept of decolonization through epistemic disobedience, this article aims to demonstrate paradoxical qualities of the game, which tries to simultaneously distance itself from the established, West-oriented ways of knowledge production and gain recognition as an artifact of modern Western pop culture. Moreover, it employs the tradition of Polish Romanticism to establish itself as a bridge between Slavdom and Western culture, and strengthen the colonial idea of Poland being the proper ruler over Slavs.
Number: 1
Keywords: 1-Jeux vidéo; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 3-Europe (corpus analysé); 4-Europe (lieu de production du savoir); _Nettoyé

Decolonising the Games Curriculum: Interventions in an Introductory Game Design Course - Geyser, Hanli (Open Library of Humanities, 2018)
Games face a crisis of diversity in both their content and in the industry itself. The inequalities that underlie these issues are heightened in the Global South. Addressing these issues will require a systemic decolonisation of games education in which future generations of industry professionals become critically engaged in their creative practice. Decolonisation requires the investigation and reconstruction of the ways knowledge is created and produced. To enable this, the curricula employed in teaching games requires close investigation and intervention. The difficulties of enabling access to knowledge when teaching games are exacerbated when seen in light of the need for decolonisation. Situated in a South African context, this article investigates the first-year core course ‘Key Concepts in Game Design’ offered at the University of the Witwatersrand in Johannesburg. It outlines the challenges games education faces in South Africa and takes stock of the state of the course and of the perceptions of students enrolled in it. It demonstrates that the course curriculum requires increased Africanisation and the establishment of common play practices. Finally, it highlights the importance of focusing on the development of critical game literacies as part of the decolonising project.
Number: 1
Keywords: 1-Jeux vidéo; 2-Pédagogie décoloniale; 2-Théories et épistémologie postcoloniales et décoloniales; 4-Afrique (lieu de production du savoir); 5-Autrice; _Nettoyé

Queerness in Play - Harper, Todd; Adams, Meghan Blythe; Taylor, Nicholas (Palgrave Macmillan, 2018)
"Queerness in Play examines the many ways queerness of all kinds - from queer as 'LGBT' to other, less well-covered aspects of the queer spectrum - intersects with games and the social contexts of play. The current unprecedented visibility of queer creators and content comes at a high tide of resistance to the inclusion of those outside a long-imagined cisgender, heterosexual, white male norm. By critically engaging the ways games - as a culture, an industry, and a medium - help reproduce limiting binary formations of gender and sexuality, Queerness in Play contributes to the growing body of scholarship promoting more inclusive understandings of identity, sexuality, and games."–Provided by publisher.
OCLC: 1057550232
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Méthodologie de recherche décoloniale; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; _Nettoyé

Facing Fanon: Examining Neocolonial Aspects in Grand Theft Auto V through the Prism of the Machinima Film Finding Fanon II - Krüger, Steffen (Open Library of Humanities, 2018)
In this article, I examine the Machinima film Finding Fanon II, by London-based artists Larry Achiampong and David Blandy, for what it can tell us about the relationship between video gaming and the postcolonial. Evoking Frantz Fanon, one of the most piercing voices of the decolonisation movement of the 1950s and 1960s, in the context of Grand Theft Auto (GTA), one of the most technologically advanced and, at the same time, scandalous video game series of the 21st century, Finding Fanon II amounts to a scathing critique of both the game series’ depiction of race and academic scholarship that has been defending the series on the grounds of its use of humour and irony. Shot in the in-game video editor of GTA V, Finding Fanon II lets this critique emerge from inside the game and as an effect of the artists’ engagement with it. By suspending the game’s mechanisms and programmed forms of interaction, the artwork brings their racialised logic to the fore, pointing towards the ways in which GTA V commodifies black men for the consumption of white players. This commodification has the effect of normalising and naturalising the precarious position of black people in Western society. What the artwork adds to this argument through its facilitation of a Fanonian perspective is a reminder that it is not only the gaming experience of white players that is framed in this way. Players with ethnic minority backgrounds might also accept the white gaze of the game as a given. Acts of self-commodification along the lines of a white Western rationality must thus be seen as a plausible new form of cultural imperialism promoted by the GTA series.
Number: 1
Keywords: 1-Jeux vidéo; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Europe (lieu de production du savoir); _Nettoyé

Hybridity, Reflexivity and Mapping: A Collaborative Ethnography of Postcolonial Gameplay - Lammes, Sybille; Smale, Stephanie de (Open Library of Humanities, 2018)
To date, game studies has largely undertheorized the co-production of postcolonial stories, exploration, and mapping in games. Furthermore, as has been noted before (Carr, 2006), the work that has been done on postcolonialism and play so far often leaves the player out of the equation, even sometimes as a theoretical construct. Yet player experience is crucial to understanding such games, as narratives are not only built on the ‘master’ level of game mechanics, but also through the personal stories players processually (Ash, 2009; Thrift, 2008) develop through their journey of touring and mapping, thereby developing spatial stories (De Certeau, 1984; Jenkins, 2004; Lammes, 2009) that may present us with conflicting spatio-temporal accounts. Through a comparative and collaborative auto-ethnographic analysis of Civilization VI (Sid Meier, 2016) – a turn-based strategy game – we want to push this discussion further and improve our theoretical understanding and analytical purchase of the triad relation between narrative and postcolonialism in games, thereby contributing to the field of postcolonial theory and game studies. Drawing on postcolonial geography, science and technology studies (STS), non-representational theory and game studies, we argue that games, through their playful, explorative and emergent qualities, are a powerful means of rethinking and reimagining colonial (hi)stories in this postcolonial era (Lammes, 2009, 2010) including issues of spatio-temporality, cartography and the hybrid relation between women and machines.
Number: 1
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Genre et sexualité; 2-Humanités numériques; 2-Méthodologie de recherche décoloniale; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Nord (corpus analysé); 4-Europe (lieu de production du savoir); 5-Autrice; _Nettoyé

Playing Subaltern: Video Games and Postcolonialism - Mukherjee, Souvik (Games and Culture, 2018)
The postcolonial has still remained on the margins of Game Studies, which has now incorporated at length, contemporary debates of race, gender, and other areas that challenge the canon. It is difficult to believe, however, that it has not defined the way in which video games are perceived; the effect, it can be argued, is subtle. For the millions of Indians playing games such as Empire: Total War or East India Company, their encounter with colonial history is direct and unavoidable, especially given the pervasiveness of postcolonial reactions in everything from academia to day-to-day conversation around them. The ways in which games construct conceptions of spatiality, political systems, ethics, and society are often deeply imbued with a notion of the colonial and therefore also with the questioning of colonialism. This article aims to examine the complexities that the postcolonial undertones in video games bring to the ways in which we read them.
Keywords: 1-Jeux vidéo; 2-Histoire/Historiographie critique; 2-Méthodologie de recherche décoloniale; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé

Video Games and Storytelling: Reading Games and Playing Books - Mukherjee, Souvik (Palgrave Macmillan, 2018)
The potential of video games as storytelling media and the deep involvement that players feel when they are part of the story needs to be analysed vis-a-vis other narrative media. This book underscores the importance of video games as narratives and offers a framework for analysing the many-ended stories that often redefine real and virtual lives.
OCLC: 1040048516
Keywords: 1-Jeux vidéo; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé

Who Made Your Phone? Compassion and the Voice of the Oppressed in Phone Story and Burn the Boards - Navarro-Remesal, Víctor; Zapata, Beatriz Pérez (Open Library of Humanities, 2018)
Burn the Boards (Causa Creations, 2015) portrays the life of an Indian worker who recycles electronic waste in a precarious environment. Phone Story (Molleindustria, 2011) simulates the journey and process of production and consumption of mobile phones, from Congo and China to Pakistan. Whereas Phone Story is described as ‘an educational game’ that addresses the player directly as a consumer, Burn the Boards is a resource management puzzle that creates compassion through role playing. These games bring to the fore a hidden reality of the everyday that is ingrained in historical relationships and power dynamics, drawing attention to what Michael Rothberg has recognized as ‘exploitation in an age of globalized neo-liberal capitalism’ (2014: iv). This article explores how these games denounce the smartphone industry by using that same technology. For this purpose, we refer to Game Studies theory on procedural rhetoric; values and ethics; and the role of the player, combined with questions of (neo)colonization, globalization, and neoliberalism drawn from Postcolonial Studies. Our analysis shows the complicity of users and their confrontation with the extreme vulnerability of others, emphasizing how the coloniality of power works in our global consumer society. Thus we study the power relationships described and established by these games, the affective reactions which they seek to trigger, and their potential to transform players from passive observers into ethical players and consumers.
Number: 1
Keywords: 1-Jeux vidéo; 2-Humanités numériques; 2-Pédagogie décoloniale; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des industries culturelles; 3-Europe (corpus analysé); 4-Europe (lieu de production du savoir); 5-Autrice; _Nettoyé

Virtual Worlds, Digital Dreams - Šisler, Vít (Digital Middle East: state and society in the information age, 2018)
Video games are inherently transnational by virtue of their industrial, textual and player practices. Until recently, the focus of research on the social and cultural aspects of video games has been on the traditional centers of the video game industry consumption, while the international flows of digital gaming remained largely underexplored. This chapter analyzes the cultural dynamics and technological processes influencing both video game development and the gaming culture in the Middle East. It conceptualizes Middle Eastern video games as imaginary spaces that entangle diverse and contradictory processes: global cultural flows, media policies of nation states, visions and engagements of private entrepreneurs, and migration and appropriation of Western game genres and rule systems. By mapping out dominant trends, the chapter offers the opportunity to think about processes and flows influencing the video game industry in the Middle East during the first fifteen years of its existence
Keywords: 1-Jeux vidéo; 2-Histoire/Historiographie critique; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 3-Europe (corpus analysé); 4-Europe (lieu de production du savoir); _Nettoyé

Digital Middle East: State and Society in the Information Age - Zayani, Mohamed (Oxford University Press, 2018)
In recent years, the Middle East’s information and communications landscape has changed dramatically. Increasingly, states, businesses, and citizens are capitalizing on the opportunities offered by new information technologies, the fast pace of digital transformations, and enhanced connectivity. These changes are far from turning Middle Eastern nations into network societies, but their impact is significant. The growing adoption of a wide variety of information technologies and new media platforms in everyday life has given rise to complex dynamics that beg for a better understanding. Digital Middle East sheds a critical light on continuing changes that are closely intertwined with the adoption of information and communication technologies in the MENA region. Drawing on case studies from throughout the Middle East, the contributors explore how these digital transformations are playing out in the social, cultural, political, and economic spheres, exposing the various disjunctions and discordances that have marked the advent of the digital Middle East.
Keywords: 1-Jeux vidéo; 3-Afrique (corpus analysé); 3-Asie (corpus analysé); 5-Auteur.rice PANDC; _Nettoyé

Video Game Modification in South Africa - Wrensch, Jesse J.; Koornhof, Pieter G.J. (South African Intellectual Property Law Journal, 2017)
This article explores the extent to which the practice of video game modification (commonly referred to as modding) is regulated under South African law. The relevant copyright laws (including impending changes to such laws) are explored, along with practical considerations such as the impact of end-user licence agreements. This is then compared to the position in the USA. The authors argue that modding is likely lawful under South Africa, and that steps should be taken to offer more clarity for modders in the future.
Keywords: 1-Jeux vidéo; 4-Afrique (lieu de production du savoir); _Nettoyé

Re-membering and Dismembering: Memory and the (Re)Creation of Identities in Videogames - Mukherjee, Souvik (Sessões do Imaginário, 2017)
The Prince of Persia in Prince of Persia: The Sands of Time (Ubisoft 2003) is ever reluctant to accept an ignominious end to his story, whether after a fall from atop a tower or after being killed by the sand demons. Every time he fails, the Prince exclaims ‘no no, that is not how it happened at all’. Like the videogame player controlling his avatar, the Prince wants the game sequence to be reloaded and replayed; only he appeals to an entity that the player often does not notice – memory. The Prince justifies the reload because he does not remember the events as they happen and he hankers for a return to a ‘true’ memory. There is an implicit problem here, however. We cannot ask the Prince what he remembers and during the game the player ends up remembering the ‘false’ memories, albeit often unconsciously. To progress further in the game, the player needs to have learned from his mistakes or, in other words, to have remembered the previous iterations of gameplay. According to the Prince’s memory, these failed instances of gameplay never happened; yet they happened in the gameplay and are remembered by players. Often, many players share the same experience and this exists as a shared memory. Players might also be drawing on collectively recorded memories – the written step by step guidelines in a walkthrough and the comments left by players on various gaming forums or wikis. What the player remembers is also often influential in determining the in-game identity of the player. Videogames themselves, such as Assassin’s Creed (Ubisoft 2008) and STALKER: Shadow of Chernobyl (GSC Gameworld 2007) have started self-reflexively exploring memory in their plots. Therefore, it will be useful to move the study of memory in videogames out of its relative obscurity and explore its multi-layered complexity.
Keywords: 1-Jeux vidéo; 2-Étude des représentations; 3-Europe (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé

Digital Saint-Domingue: Playing Haiti in Videogames - Lauro, Sarah Juliet (Archipelagos, 2017)
This article comes out of a longer project looking at digital commemorations of slave rebellion. In this excerpt from that work, the author considers the issues at stake in videogamic representations of colonial Saint Domingue and its denizens, particularly for their depiction of the prehistory of the Haitian Revolution. In two mainstream videogames, both part of the Assassin’s Creed franchise, the history of Saint Domingue, its legacy of slave resistance, and the Haitian Revolution are made into fodder for an interactive entertainment experience that intervenes in and reshapes history in a complex manner. There are several issues at stake, which the author focuses on exclusively in terms of the commodification of Saint Domingue. First, the games place the history of slave revolt into the hands of game players of diverse ancestry, allowing for a redistribution of ownership over narratives of emancipation and empowerment. Second, the games identify themselves as tampering with history, and their mélange of fictional characters and real personages seems to risk rewriting the history of Saint Domingue’s legacy of slave revolt and—by extension—of the Haitian Revolution itself. Given recent events in the United States, and increased attention to strategies of black resistance such as the Black Lives Matter movement, it seems all the more imperative that our depiction of slave revolts in popular culture be handled with care. And yet, the author finds a subversive maneuver visible in the games: the use of untranslated language, especially Haitian Kreyol, may work to preserve and limit the player’s mastery over these histories. This article provides a tour of this complex territory of digital Saint Domingue.
Keywords: 1-Jeux vidéo; 2-Humanités numériques; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; _Nettoyé

Gaming Representation: Race, Gender, and Sexuality in Video Games - Malkowski, Jennifer; Russworm, TreaAndrea M. (Indiana University Press, 2017)
Gaming Representation' offers a timely and interdisciplinary call for greater inclusivity in video games. The issue of equality transcends the current focus in the field of Game Studies on code, materiality, and platforms. Journalists and bloggers have begun to hold the digital game industry and culture accountable for the discrimination routinely endured by female gamers, queer gamers, and gamers of color. Video game developers are responding to these critiques, but scholarly discussion of representation in games has lagged behind. Contributors to this volume examine portrayals of race, gender, and sexuality in a range of games, from casuals like Diner Dash, to indies like Journey and The Binding of Isaac, to mainstream games from the Grand Theft Auto, BioShock, Spec Ops, The Last of Us, and Max Payne franchises. Arguing that representation and identity function as systems in games that share a stronger connection to code and platforms than it may first appear, 'Gaming Representation' pushes gaming scholarship to new levels of inquiry, theorizing, and imagination.
Google-Books-ID: qJwRvgAACAAJ
Keywords: 1-Jeux vidéo; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Humanités numériques; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Auteur.rice LGBTQ+; 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; 5-Créatrice; _Nettoyé

Videogames and Post-Colonialism: Empire Plays Back - Mukherjee, Souvik (Palgrave MacMillan, 2017)
This book focuses on the almost entirely neglected treatment of empire and colonialism in videogames. From its inception in the nineties, Game Studies has kept away from these issues despite the early popularity of videogame franchises such as Civilization and Age of Empire. This book examines the complex ways in which some videogames construct conceptions of spatiality, political systems, ethics and society that are often deeply imbued with colonialism. Moving beyond questions pertaining to European and American gaming cultures, this book addresses issues that relate to a global audience ? including, especially, the millions who play videogames in the formerly colonised countries, seeking to make a timely intervention by creating a larger awareness of global cultural issues in videogame research. Addressing a major gap in Game Studies research, this book will connect to discourses of post-colonial theory at large and thereby, provide another entry-point for this new medium of digital communication into larger Humanities discourses.
Section: ix, 121 pages : illustrations ; 22 cm.
Keywords: 1-Jeux vidéo; 2-Histoire/Historiographie critique; 2-Méthodologie de recherche décoloniale; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé

Migrating the Black Body: The African Diaspora and Visual Culture - Raiford, Leigh; Raphael-Hernandez, Heike (University of Washington Press, 2017)
Migrating the Black Body explores how visual media from painting to photography, from global independent cinema to Hollywood movies, from posters and broadsides to digital media, from public art to graphic novels has shaped diasporic imaginings of the individual and collective self. How is the travel of black bodies reflected in reciprocal black images? How is blackness forged and remade through diasporic visual encounters and reimagined through revisitations with the past? And how do visual technologies structure the way we see African subjects and subjectivity? This volume brings together an international group of scholars and artists who explore these questions in visual culture for the historical and contemporary African diaspora. Examining subjects as wide-ranging as the appearance of blackamoors in Russian and Swedish imperialist paintings, the appropriation of African and African American liberation images for Chinese Communist Party propaganda, and the role of YouTube videos in establishing connections between Ghana and its international diaspora, these essays investigate routes of migration, both voluntary and forced, stretching across space, place, and time.
Google-Books-ID: edBiDgAAQBAJ
Keywords: 2-Étude des représentations; 5-Auteur.rice PANDC; _Nettoyé; _À analyser; _À nettoyer; _À vérifier-Cinéma; _À vérifier-Histoire de l'art

Queer Game Studies - Ruberg, Bonnie; Shaw, Adrienne (University of Minnesota Press, 2017)
The in-depth, diverse, and accessible essays in Queer Game Studies use queerness to challenge the ideas that have dominated gaming discussions. This volume reveals the capacious albeit underappreciated communities that are making, playing, and studying queer games, demonstrating the centrality of LGBTQ issues to the gamer world and establishing an alternative lens for examining this increasingly important culture.
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Genre et sexualité; 2-Humanités numériques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude de la réception; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Auteur.rice LGBTQ+; 5-Autrice; 5-Créateur.rice LGBTQ+; 5-Créatrice; _Nettoyé

Methods for Studying Video Games and Religion - Šisler, Vít; Radde-Antweiler, Kerstin; Zeiler, Xenia (Taylor and Francis, 2017)
Game studies has been an understudied area within the emerging field of digital media and religion. Video games can reflect, reject, or reconfigure traditionally held religious ideas and often serve as sources for the production of religious practices and ideas. This collection of essays presents a broad range of influential methodological approaches that illuminate how and why video games shape the construction of religious beliefs and practices, and also situates such research within the wider discourse on how digital media intersect with the religious worlds of the 21st century. Each chapter discusses a particular method and its theoretical background, summarizes existing research, and provides a practical case study that demonstrates how the method specifically contributes to the wider study of video games and religion. Featuring contributions from leading and emerging scholars of religion and digital gaming, this book will be an invaluable resource for scholars in the areas of digital culture, new media, religious studies, and game studies across a wide range of disciplines.
Keywords: 1-Jeux vidéo; 2-Analyses formalistes; 2-Méthodologie de recherche décoloniale; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 4-Amérique du Nord (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Autrice; _Nettoyé

Video Games and Slavery - Mukherjee, Souvik (Transactions of the Digital Games Research Association, 2016)
What are the implications of freedom and agency when a player exercises agency to prevent another player or a non-player character fromacting freely? Such a scenario, taken to an extreme, would be that of slavery and in turn, would raise questions about the nature of freedom itself. Video games have recently begun to address questions of slavery in earnest although academic discussions on games have not yet caught up: the presence of slavers in Fallout 3, the portrayal of racism in Bioshock Infinite (Irrational Games 2014) and the direct depiction of the Caribbean slave trade in Assassin’s Creed: Freedom Cry (Ubisoft 2013) are extremely appropriate cases in point. This article compares the representation of slavery in video games to that of slave narratives in earlier media in order to examine how effectively digital games are able to convey the horrors of slavery as a human condition and what they can teach about the notion of human freedom and agency per se.
Number: 3
Keywords: 1-Jeux vidéo; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 3-Europe (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé

Envisioning Black Feminist Voodoo Aesthetics: African Spirituality in American Cinema - Martin, Kameelah L. (Lexington Books, 2016)
In the twenty-first century, American popular culture increasingly makes visible the performance of African spirituality by black women. Disney’s Princess and the Frog and Pirates of the Caribbean franchise are two notable examples. The reliance on the black priestess of African-derived religion as an archetype, however, has a much longer history steeped in the colonial othering of Haitian Vodou and American imperialist fantasies about so-called ‘black magic’. Within this cinematic study, Martin unravels how religious autonomy impacts the identity, function, and perception of Africana women in the American popular imagination. Martin interrogates seventy-five years of American film representations of black women engaged in conjure, hoodoo, obeah, or Voodoo to discern what happens when race, gender, and African spirituality collide. She develops the framework of Voodoo aesthetics, or the inscription of African cosmologies on the black female body, as the theoretical lens through which to scrutinize black female religious performance in film. Martin places the genre of film in conversation with black feminist/womanist criticism, offering an interdisciplinary approach to film analysis. Positioning the black priestess as another iteration of Patricia Hill Collins’ notion of controlling images, Martin theorizes whether film functions as a safe space for a racial and gendered embodiment in the performance of African diasporic religion. Approaching the close reading of eight signature films from a black female spectatorship, Martin works chronologically to express the trajectory of the black priestess as cinematic motif over the last century of filmmaking. Conceptually, Martin recalibrates the scholarship on black women and representation by distinctly centering black women as ritual specialists and Black Atlantic spirituality on the silver screen.
Google-Books-ID: VjfqDAAAQBAJ
Keywords: 1-Cinéma; 2-Genre et sexualité; _Nettoyé; _À analyser; _À nettoyer; _À vérifier-Cinéma

Towards Diversity: Interventions in Curriculum and Pedagogy of an Introductory Game Design Course - Hanli, Geyser (DiGRA/FDG '16 - Abstract Proceedings of the First International Joint Conference of DiGRA and FDG, 2016)
Transformation and the decolonization of the curriculum, modes of teaching, and classroomare key concerns in South African Higher Education. In game design education this need is exacerbatedby the slow pace of diversification in both academia and the industry.This paper presents a close analysis of interventions undertaken into an introductory game design course to address the difficultiesof diversification across racial, genderand economic divides. The results of the interventions are assessed, and recommendations for future adjustments to the course in aid curricular decolonization is are made.
Place: Dundee, Scotland
Keywords: 1-Jeux vidéo; 2-Genre et sexualité; 2-Pédagogie décoloniale; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Afrique (corpus analysé); 4-Afrique (lieu de production du savoir); 5-Autrice; _Nettoyé

The Current State of Muslim Representation in Video Games - Khan, Imad; Khalaf, Farah; Ismail, Rami; Ramzan, Romana (2016)
Muslim members of the video game industry discuss the current state of Muslim representation within video games. This includes current problems with the way Muslims are represented and potential solutions. Our panelists come from all sides of the industry. From AAA, to indie, the panelists all have a unique voice and angle they would like to bring to the discussion. All panelists have grown up Muslim in western countries and have had to deal with certain adversities and challenges. It's through that experience that the panelists want to bring a lively discussion, backed with personal accounts and sources, that is not only engaging, but educational.
Keywords: 1-Jeux vidéo; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 3-Europe (corpus analysé); 4-Europe (lieu de production du savoir); 4-Océanie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; _Nettoyé

Transnational Contexts of Culture, Gender, Class, and Colonialism in Play: Video Games in East Asia - Pulos, Alexis; Lee, S. Austin (Palgrave Macmillan, 2016)
This book examines the local, regional and transnational contexts of video games through a focused analysis on gaming communities, the ways game design regulates gender and class relations, and the impacts of colonization on game design. The critical interest in games as a cultural artifact is covered by a wide range of interdisciplinary work. To highlight the social impacts of games the first section of the book covers the systems built around high score game competitions, the development of independent game design communities, and the formation of fan communities and cosplay. The second section of the book offers a deeper analysis of game structures, gender and masculinity, and the economic constraints of empire that are built into game design. The final section offers a macro perspective on transnational and colonial discourses built into the cultural structures of East Asian game play
Keywords: 1-Jeux vidéo; 2-Genre et sexualité; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; _Nettoyé

Counter-Hegemonic Commemorative Play: Marginalized Pasts and the Politics of Memory in the Digital Game Assassin’s Creed: Freedom Cry - Hammar, Emil Lundedal (Rethinking History, 2015)
In this article, I argue that digital games hold the potential to influence processes of cultural memory related to past and contemporary forms of marginalization. By bringing cultural memory studies into dialogue with game studies, I account for the ways through which digital games and practices of play might influence historical discourses and memory politics pertaining to marginalized identities. In order to demonstrate this, I conduct an analysis of Assassin’s Creed: Freedom Cry, a digital game which includes representation of the eighteenth-century transatlantic slave trade and its racist systems. This analysis is then contrasted with statements by two critics, Evan Narcisse and Justin Clark, about how Freedom Cry highlights specific marginalized identities and represents the past through the game form. These statements, coupled with my game analysis, make the case for a concept that I term ‘counter-hegemonic commemorative play’. This makes visible a form of potentially cathartic power fantasy within a historical struggle, alongside emphasizing a form of designed recognition of marginalized identities within contemporary historical discourses and memory politics.
Number: 3
Keywords: 1-Jeux vidéo; 2-Histoire/Historiographie critique; 2-Humanités numériques; 2-Pédagogie décoloniale; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Europe (lieu de production du savoir); _Nettoyé

Playing with Being in Digital Asia: Gamic Orientalism and the Virtual Dōjō - Goto-Jones, Chris (Asiascape: Digital Asia, 2015)
Seeking to address the general question, ‘Where is Digital Asia?’, this paper explores the various ways in which the digital and virtual realm interacts with the problematic and contested category of Asia. Beginning with a discussion of the relationship between Asia and Digital Asia, as both cartographic and ideological sites, it moves on to connect Digital Asia with the discourse of techno-Orientalism. Using the example of the videogame as an instance of a digital location that can be visited and explored, this article suggests that the gamic quality of interactivity adds a new, experiential dimension to the ideological structure of (techno-)Orientalism, hence positing the utility of a new form of ‘Gamic Orientalism’. Focussing on the ‘digital dōjō’ as the site of Gamic Orientalism and Digital Asia par excellence, this paper concludes with a discussion of the ways in which gamers represent their engagement with this site in a manner that echoes the way martial artists talk about the significance of their art as self-cultivation. Illustrated with texts from the bushidō canon and interviews with gamers, this playful and experimental piece posits the possibility of ‘virtual bushidō’ as the ultimate expression of Gamic Orientalism, suggesting that Digital Asia is finally located in an ideologically conditioned mode of engagement with the digital medium rather than in any cartographically defined space.
Section: Asiascape: Digital Asia
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude de la réception; 4-Europe (lieu de production du savoir); _Nettoyé

Contemporary Sino-Japanese Relations on Screen: A History, 1989-2005 - Kirsch, Griseldis (Bloomsbury Publishing, 2015)
Japan and China look back on a history of friendship as well as friction, particularly in recent decades. As the People's Republic of China's economy began to grow in the 1990s, so did its political weight within Asia and its economical relevance for Japan. Covering the years from 1989 to 2005, this book looks at Sino-Japanese relations through film and television drama in the crucial time of China's ascent to an economic superpower in opposition to Japan's own ailing economy. It provides an overview of how Japan views China through its visual media, offers explanations as to how oppositions between the two countries came to exist, and how and why certain myths about China have been conveyed.Griseldis Kirsch argues that the influence of visual media within society cannot be underestimated, nor should their value be lessened by them being perceived as part of 'popular culture'. Drawing on examples from a crucial 16 years in the history of post-war Japan and China, she explores to what extent these media were influenced by the political discourse of their time. In doing so, she adds another layer to the on-going debate on Sino-Japanese relations, bringing together disciplines such as media studies, history and area studies and thus filling a gap in existing research.
Google-Books-ID: gdqxCAAAQBAJ
Keywords: 1-Cinéma; 2-Histoire/Historiographie critique; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 3-Asie (corpus analysé); 4-Europe (lieu de production du savoir); 5-Autrice; _Nettoyé; _À analyser; _À nettoyer; _À vérifier-Cinéma

The Playing Fields of Empire: Empire and Spatiality in Video Games - Mukherjee, Souvik (Journal of Gaming & Virtual Worlds, 2015)
As in historical accounts, empire in video games too is concerned with the acquisition of geographical space. Like the splash of red marking the stretch of the British Empire on Victorian world maps, video games that let one play at empire are also obsessed with stamping the imperialist authority of ‘your’ nation on their in-game maps. Video game empires too work on the necessary logic of spatial expansion connected with which is the necessity to remove the ‘fog’ which prevents the player’s ‘line of sight’ from accessing information about surrounding areas. The focus on cartography and surveying in British Raj India is a useful comparison. Although much scholarship exists around the representations of the spatiality of Empire in more traditional media, there is little that addresses the video game representations of Empire. This article is about the representation and experience of space in conceptions of Empire vis-à-vis in empire-building video games, as understood in terms of both cartography and the lived experience of space. It argues that although empire-building video games are largely framed within the western imperialist discourses, the very nature of gameplay itself challenges these set notions – in a way remediating the ambiguity and anxieties of the representations of empire and its spatial constructs in earlier media.
Keywords: 1-Jeux vidéo; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé

Les Jeux Video en Negroculture: Contribution a Une Anthropologie de La Solidarite Chez Les Jeunes du Cameroun - Otye Elom, Paul Ulrich (African Sociological Review / Revue Africaine de Sociologie, 2015)
En Afrique en général et au Cameroun en particulier, posséder une console de jeux vidéo n’est pas à la portée de tout le monde. Les jeunes puisque ce sont eux qui les affectionnent particulièrement, qui en possèdent une, font donc souvent appel à leurs pairs afin qu’ensemble, ils puissent s’amuser. L’espace où les jeunes jouent aux jeux vidéo devient de ce fait un espace où ces derniers s’affirment en tant que groupe à part entière. C’est un espace qui leur permet de se démarquer des adultes qui, le plus souvent dénigrent, voire méprisent cette activité ludique. Les jeunes y créent ainsi des « ethnométhodes » et développent une solidarité mécanique. Jouer aux jeux vidéo dans ce contexte n’est plus simplement une activité de loisir. L’espace de jeu devient un espace où se créent de nouvelles relations et où se raffermissent les anciennes. Mais également, un espace où se développent l ’esprit de compétition et corrélativement même des conflits. Celui avec qui on s’amuse aux jeux vidéo devient celui à qui on se confie, avec qui on partage ses joies et ses peines. La console de jeux n’ « appartient » plus à celui qui l ’a achetée, mais à tous ceux qui la jouent. Il n’est donc pas rare qu’elle s’exporte du domicile de son propriétaire pour le domicile d ’un autre adolescent. Il faut également préciser que le jeu vidéo reste en négroculture une activité essentiellement masculine ; l ’espace de jeu est donc le fief du garçon et les filles n’ont rien à y faire. Le jeu vidéo développe ainsi un certain machisme, une fierté d ’être homme plutôt que femme. Dans ce contexte, on peut noter une sorte de détribalisation. L’obédience ethnique de tout un chacun s’estompe pour laisser place à une société des jeunes tout court. Le jeu vidéo fait donc tomber les barrières raciales, tribales, ethniques. Et même si on peut y noter des effets pervers, ce qui est normal, puisque aucun système culturel n’est parfait, les jeux vidéo en contexte camerounais développent chez les adolescents le sentiment d ’appartenance à une même classe d ’âge.
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Genre et sexualité; 3-Afrique (corpus analysé); 4-Afrique (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé

Gaming at the Edge: Sexuality and Gender at the Margins of Gamer Culture - Shaw, Adrienne (University of Minnesota Press, 2015)
Video games have long been seen as the exclusive territory of young, heterosexual white males. In a media landscape dominated by such gamers, players who do not fit this mold, including women, people of color, and LGBT people, are often brutalized in forums and in public channels in online play. Discussion of representation of such groups in games has frequently been limited and cursory. In contrast, Gaming at the Edge builds on feminist, queer, and postcolonial theories of identity and draws on qualitative audience research methods to make sense of how representation comes to matter. In Gaming at the Edge, Adrienne Shaw argues that video game players experience race, gender, and sexuality concurrently. She asks: How do players identify with characters? How do they separate identification and interactivity? What is the role of fantasy in representation? What is the importance of understanding market logic? In addressing these questions Shaw reveals how representation comes to matter to participants and offers a perceptive consideration of the high stakes in politics of representation debates. Putting forth a framework for talking about representation, difference, and diversity in an era in which user-generated content, individualized media consumption, and the blurring of producer/consumer roles has lessened the utility of traditional models of media representation analysis, Shaw finds new insight on the edge of media consumption with the invisible, marginalized gamers who are surprising in both their numbers and their influence in mainstream gamer culture.
Keywords: 1-Jeux vidéo; 2-Analyses formalistes; 2-Approches sociologiques; 2-Genre et sexualité; 2-Méthodologie de recherche décoloniale; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude de la réception; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; _Nettoyé

Video Games Around the World - Wolf, Mark J. P. (MIT Press, 2015)
Video games have become a global industry, and their history spans dozens of national industries where foreign imports compete with domestic productions, legitimate industry contends with piracy, and national identity faces the global marketplace. This volume describes video game history and culture across every continent, with essays covering areas as disparate and far-flung as Argentina and Thailand, Hungary and Indonesia, Iran and Ireland.
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Étude des industries culturelles; 3-Afrique (corpus analysé); 3-Amérique centrale (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 3-Océanie (corpus analysé); 4-Afrique (lieu de production du savoir); 4-Amérique centrale (lieu de production du savoir); 4-Amérique du Nord (lieu de production du savoir); 4-Amérique du Sud (lieu de production du savoir); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 4-Océanie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; 5-Créateur.rice PANDC; _Nettoyé

Avatars of Whiteness: Racial Expression in Video Game Characters - Dietrich, David R. (Sociological Inquiry, 2013)
Video games are an enormous segment of popular media today, comparable to tele-vision and movies. Moreover, video games represent a new form of media distinguishedfrom previous forms due to the interactive element, where game players have the ability to change and influence the game world. This paper contributes to the study of race and popular media by examining how race is presented in role-playing video games throughthe feature of avatar creation. Capabilities for avatar creation are analyzed in over sixty massively multiplayer online role-playing games (MMORPGs) in service as of early2010 and twenty offline role-playing games (RPGs) published over the past 10 years.The analysis shows that the vast majority of games, both online and offline, do not allow for the creation of avatars with a non-white racial appearance. Forcing an Angloappearance on avatars that purport to represent the player has the potential to reinforce asense of normative whiteness as well as shape the social composition of online worldsinto all-white virtual spaces, contributing to the creation of a virtual“white habitus.”
Keywords: 1-Jeux vidéo; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); _Nettoyé

Gaming Globally: Production, Play, and Place - Huntemann, Nina B.; Aslinger, Ben (Palgrave Macmillan, 2013)
Video games are inherently transnational by virtue of their industrial, textual, and player practices. This collection includes essays from scholars from eight countries analyzing game cultures on macro- and micro-levels and investigates the growing transnational nature of digital play
Section: xi, 279 p. : ill. ; 23 cm.
Keywords: 1-Jeux vidéo; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 4-Amérique du Sud (lieu de production du savoir); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; 5-Créateur.rice PANDC; 5-Créatrice; _Nettoyé

Playing with the Past: Digital Games and the Simulation of History - Kapell, Matthew Wilhelm; Elliott, Andrew B. R. (Bloomsbury Publishing USA, 2013)
Game Studies is a rapidly growing area of contemporary scholarship, yet volumes in the area have tended to focus on more general issues. With Playing with the Past, game studies is taken to the next level by offering a specific and detailed analysis of one area of digital game play – the representation of history. The collection focuses on the ways in which gamers engage with, play with, recreate, subvert, reverse and direct the historical past, and what effect this has on the ways in which we go about constructing the present or imagining a future. What can World War Two strategy games teach us about the reality of this complex and multifaceted period? Do the possibilities of playing with the past change the way we understand history? If we embody a colonialist's perspective to conquer 'primitive' tribes in Colonization, does this privilege a distinct way of viewing history as benevolent intervention over imperialist expansion? The fusion of these two fields allows the editors to pose new questions about the ways in which gamers interact with their game worlds. Drawing these threads together, the collection concludes by asking whether digital games - which represent history or historical change - alter the way we, today, understand history itself.
Google-Books-ID: jXjHAgAAQBAJ
Keywords: 1-Jeux vidéo; 2-Analyses formalistes; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 4-Océanie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; _Nettoyé

A Pedestal, A Table, A Love Letter: Archaeologies of Gender in Videogame History - Nooney, Laine (Game Studies, 2013)
The history of videogames has largely been imagined as a patrilineal timeline. Women, when they emerge as participants in the game industry, are typically figured as outliers, exceptions, or early exemplars of “diversity” in the game industry. Yet the common practice of “adding women on” to game history in a gesture of inclusiveness fails to critically inquire into the ways gender is an infrastructure that profoundly affects who has access to what kinds of historical possibilities at a specific moment in time and space. This contribution aims to shift the relevant question from “Where are women in game history?” to “Why are they there in the way that they are?” To do so, the essay strategically deploys Sierra On-Line co-founder and lead designer Roberta Williams as an exceptional case study on the problem of gender in videogame history. Drawing from both media archaeology and feminist cultural studies, this contribution first outlines the function Roberta Williams serves as a gendered subject of game history. The remainder of the essay is organized as three short, non-chronological vignettes about specific objects and practices in the biography of Roberta Williams. Attention to the contextual specificity of Roberta Williams and her historical moment produces an alternative genealogy for gaming centered around relations of intimacy and labor in domestic space. Rather than producing a chronology, the method of this essay illustrates a historical critique by sketching a contour that unsettles the presumptive logic of what we must account for when we write about the objects and subjects of game history.
Number: 2
Keywords: 1-Jeux vidéo; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; 5-Créatrice; _Nettoyé

A Critical Interpretation of a New “Creative Industry” in Turkey: Game Studios and the Production of a Value Chain - Binark, Mutlu; Bayraktutan, Günseli (Computer Games and New Media Cultures: a Handbook of Digital Games Studies, 2012)
In this chapter, the creation of a value chain during the process of digital games development in Turkey is discussed using a critical political economy approach. This study claims to be the first of its kind that intends to examine the topography of the digital game industry in Turkey and gives a brief history and describes the present status of digital games production in Turkey. All the components of a value chain, namely, the industrial structure and development process, publishing and licensing, distribution and marketing structure, labor force, legal regulations, and governmental policies will be considered in that order to map out the present topography of the industry. The final part of the study will deal with possible solutions for further development in the industry. At this point, the study stresses the fact that all components of the value chain must be performed uninterrupted if the actors in Turkey’s digital game industry desire to position themselves as “producers” in global or local markets.
Keywords: 1-Jeux vidéo; 2-Histoire/Historiographie critique; 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; 5-Créateur.rice PANDC; _Nettoyé

Media Heterotopia and Transnational Filmmaking: Mapping Real and Virtual Worlds - Chung, Hye Jean (Cinema Journal, 2012)
Focusing on The Fall (Tarsem Singh, 2006), The World {}Zhangke S\a, 2004), and Avalon (Mamoru Oshii, 2001), this essay proposes a mode of heterotopic perception and analysis that recognizes the composited layers and material residues of giobally dispersed production sites and laboring bodies in mediated transnationa! spaces.
Keywords: 1-Cinéma; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 5-Auteur.rice PANDC; _Nettoyé; _À analyser; _À nettoyer; _À vérifier-Cinéma

Computer Games and New Media Cultures: a Handbook of Digital Games Studies - Fromme, Johannes; Unger, Alexander (Springer, 2012)
This handbook aims to reflect the relevance and value of studying digital games, now the subject of a growing number of studies, surveys, conferences and publications. As an overview of the current state of research into digital gaming, the 42 papers included in this handbook focus on the social and cultural relevance of gaming.
Keywords: 1-Jeux vidéo; 5-Auteur.rice PANDC; _Nettoyé

Race-based fantasy realm: Essentialism in the world of warcraft - Monson, Melissa J. (Games and Culture, 2012)
This article explores issues of racial essentialism and ethnicity in the massively multiplayer online role-playing game World of Warcraft (WoW). The fantasy world of Azeroth mirrors elements of real-world race-based societies where culture is thought to be immutably linked to race. The notion of biological essentialism is reinforced throughout the gamescape. Race plays a primary role in the social and political organization of Azeroth. Among other things, race determines alliances, language, intellect, temperament, occupation, strength, and technological aptitude. The cultural representation of the respective racial groups in WoW draws upon stereotypical imagery from real-world ethnic groups (e.g., American Indian, Irish/Scottish, Asian, African, etc.).
Number: 1
Keywords: 1-Jeux vidéo; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; _Nettoyé

Egoshooting in Chernobyl: Identity and Subject(s) in the S.T.A.L.K.E.R. Games - Mukherjee, Souvik (Computer Games and New Media Cultures: a Handbook of Digital Games Studies, 2012)
The issue of identity formation when playing an avatar in a video game has recently become perceived as both increasingly complex and contentious. Game critics argue both for and against the apparent seamlessness in the identity formation in video games. However, while the case against seamlessness builds up with respect to other gaming genres, first-person shooters (FPS) are often still singled out as best representing this first-person identification whereby players were supposed to be totally immersed in their avatars while they played the game. In the light of recent research, this chapter builds on earlier research to reveal further problems in assuming a seamless merging of identity even in the FPS. It argues that the very conception of subjectivity has always been problematized through the FPS, and that the genre itself self-consciously keeps pointing this out. As an example of the latter, the chapter focuses on the S.T.A.L.K.E.R. video games to show how FPS games prompt players to question their in-game identity(ies) because the playing subject, instead of being a fixed entity, is hard-wired into the process of exploration that constitutes gameplay.
Keywords: 1-Jeux vidéo; 2-Étude des représentations; 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé

Return to Darkness: Representations of Africa in Resident Evil 5 - Hanli, Geyser; Pippa, Tshabalala (DiGRA '11 - Proceedings of the 2011 DiGRA International Conference: Think Design Play, 2011)
Darkest Africa, the imagining of colonial fantasy, in many ways still lives on. Popular cultural representations of Africa often draw from the rich imagery of the un-charted, un-knowable ‘other’ that Africa represents, fraught with post-colonial tensions. When Capcom made the decision to set the latest instalment of its Resident Evil series in an imagined African country, it was merely looking for a new, unexplored setting, and they were therefore surprised at the controversy that surrounded its release. The 2009 game Resident Evil 5 was accused of racially stereotyping the black zombies and the white protagonist. These allegations have largely been put to rest, as this was never the intention of Capcom in developing the game or selecting the setting. However, the underlying questions remain: How is Africa represented in the game? How does the figure of the zombie resonate within that representation? And why does this matter?
Keywords: 1-Jeux vidéo; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Afrique (lieu de production du savoir); 5-Autrice; _Nettoyé

Beautiful Fighting Girl - Saitō, Tamaki; Azuma, Hiroki (University of Minnesota Press, 2011)
From Nausicaa to Sailor Moon, understanding girl heroines of manga and anime within otaku culture.
OCLC: 897044808
Keywords: 1-Cinéma; 1-Jeux vidéo; 1-TV; 2-Genre et sexualité; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé; _À analyser; _À nettoyer; _À vérifier-Cinéma

What's in a Game? Race, Gender, and LGB Representation in Video Games - Wilberg, Heather (Roosevelt University, 2011)
Though research examining violence in video games (VGs) and its potential real-world effects has been a target of academic attention, content analysis of demographical marginalization in VGs has not been as prolific. What little research there is reveals a pronounced absence and stereotyping of women and racial or ethnic minorities but ignores queer content altogether. This work explores video game demographics through quantitative analysis of the demographic composition and stereotyping of characters from 30 popular VG titles. Findings of this study support that of past analyses, evidencing that the representation of women and racial minorities is both rare and stereotyped. Queer characters are also shown to be sparse and stereotyped. While past research has largely treated race and gender separately, this study shows that multiply marginalized groups, including queers, are even more underrepresented and stereotyped. The sociocultural implications of these findings are discussed and suggestions are made for future analysis and marketing.
Keywords: 1-Jeux vidéo; 2-Analyses formalistes; 2-Genre et sexualité; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; _Nettoyé

‘Shall we kill the pixel soldier?’: Perceptions of Trauma and Morality in Combat Video Games - Mukherjee, Souvik; Pitchforn, Jenna (Journal of Gaming and Virtual Worlds, 2010)
The western media has been eager to construct an apparent link between the so-called moral desensitization of soldiers in the 2003 Iraq War and their expe-rience of video game combat. Commentators assert that ‘games have avoided engaging the real-life issues to which they are responding’ (Zacny 2008), includ-ing the issue of combat trauma. Contrary to such positions, many video games already simulate the trauma in their gameplay experience; this article explores this concept from Brown’s definition of trauma as ‘outside the range of human experience’ (1995: 101). This evokes recent work in games studies on in-game involvement and identity-formation and raises questions about the role of moral-ity in gameplay, especially in multi-player combat games like Counter-Strike, Call of Duty 4 and America’s Army. Working from these hitherto overlooked aspects of trauma in gameplay experiences, this article challenges the oversim-plified association of video games with the desensitization of US troops in recent conflicts.
Keywords: 1-Jeux vidéo; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Europe (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; _Nettoyé

Digital Diaspora: A Race for Cyberspace - Everett, Anna (SUNY Press, 2009)
Traces the rise of black participation in cyberspace.Deftly interweaving history, culture, and critical theory, Anna Everett traces the rise of black participation in cyberspace, particularly during the early years of the Internet. She challenges the problematic historical view of black people as quintessential information-age outsiders or poster children for the digital divide by uncovering their early technolust and repositioning them as eager technology adopters and consumers, and thus as coconstituent elements in the information technology revolution. She offers several case studies that include lessons learned from early adoption of the Internet by the Association of Nigerians Living Abroad and their Niajanet virtual community, the grassroots organizing efforts that led to the phenomenally successful Million Woman March, the migration of several historic black presses online, and an interventionist critique of race in contemporary video games. Ultimately, Digital Diaspora shows how African Americans and African diasporic peoples developed the necessary technomastery to ride in the front of the bus on the information superhighway.Anna Everett is Professor of Film and Media Studies at the University of California, Santa Barbara. Her books include Learning Race and Ethnicity: Youth and Digital Media; New Media: Theories and Practices of Digitextuality; and Returning the Gaze: A Genealogy of Black Film Criticism, 1909–1949.
Google-Books-ID: T3xhglJ1_bcC
Keywords: 1-Jeux vidéo; 2-Genre et sexualité; 2-Humanités numériques; 2-Étude des représentations; 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; _Nettoyé; _À analyser; _À nettoyer; _À vérifier-Cinéma; _À vérifier-Télé

Conference Proceedings of The Philosophy of Computer Games 2008 - Günzel, Stephan; Liebe, Michael; Mersch, Dieter (Potsdam University Press, 2009)
This first volume of the DIGAREC Series holds the proceedings of the conference The Philosophy of Computer Gamesʺ, held at the University of Potsdam from May 8-10, 2008. The contributions of the conference address three fields of computer game research that are philosophically relevant and, likewise, to which philosophical reflection is crucial. These are: ethics and politics, the action-space of games, and the magic circle. All three topics are interlinked and constitute the paradigmatic object of computer games: Whereas the first describes computer games on the outside, looking at the cultural effects of games as well as on moral practices acted out with them, the second describes computer games on the inside, i.e. how they are constituted as a medium. The latter finally discusses the way in which a border between these two realms, games and non-games, persists or is already transgressed in respect to a general performativity.
Google-Books-ID: SJ972ia4kZQC
Keywords: 1-Jeux vidéo; _Nettoyé

Blackless Fantasy: The Disappearance of Race in Massively Multiplayer Online Role-Playing Games - Higgin, Tanner (Games and Culture, 2009)
This article focuses on questioning and theorizing the visual and discursive disappearance of blackness from virtual fantasy worlds. Using EverQuest, EverQuest II, and World of Warcraft as illustrative of a timeline of character creation design trends, this article argues that the disappearance of blackness is a gradual erasure facilitated by multicultural design strategies and regressive racial logics. Contemporary fantasy massively multiplayer online role-playing games (MMORPGs) privilege whiteness and contextualize it as the default selection, rendering any alterations in coloration or racial selection exotic stylistic deviations. Given the Eurocentrism inherent in the fantasy genre and embraced by MMORPGs, in conjunction with commonsense conceptions of Blacks as hyper-masculine and ghettoized in the gamer imaginary, players and designers do not see blackness as appropriate for the discourse of heroic fantasy. As a result, reductive racial stereotypes and representations proliferate while productive and politically disruptive racial differences are ejected or neutralized through fantastical proxies.
Number: 1
Keywords: 1-Jeux vidéo; 2-Analyses formalistes; 2-Histoire/Historiographie critique; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); _Nettoyé

Gaming Cultures and Place in Asia-Pacific - Hjorth, Larissa; Chan, Dean (Routledge, 2009)
This collection explores the relationship between digital gaming and its cultural context by focusing on the burgeoning Asia-Pacific region. Encompassing key locations for global gaming production and consumption such as Japan, China, and South Korea, as well as increasingly significant sites including Australia and Singapore, the region provides divergent examples of the role of gaming as a socio-cultural phenomenon. Drawing from micro ethnographic studies of specific games and gaming locales to macro political economy analyses of techno-nationalisms and trans-cultural flows, this collection provides an interdisciplinary model for thinking through the politics of gaming production, representation, and consumption in the region.
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Genre et sexualité; 2-Humanités numériques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude de la réception; 3-Amérique du Nord (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; _Nettoyé

Différance at Play. Unfolding Identities Through Difference in Videogame Play - Mitsuishi, Yara (Conference Proceedings of The Philosophy of Computer Games 2008, 2009)
This paper approaches the debate over the notion of “magic circ-le” through an exploratory analysis of the unfolding of identities/differences in gameplay through Derrida’s différance. Initially, différance is related to the notion of play and identity/difference in Derrida’s perspective. Next, the notion of magic circle through Derrida’s play is analyzed, emphasizing the dynamics of diffé-rance to understand gameplay as process; questioning its boun-daries. Finally, the focus shifts toward the implications of the interplay of identities and differences during gameplay.
Google-Books-ID: SJ972ia4kZQC
Keywords: 1-Jeux vidéo; 2-Étude des représentations; 5-Autrice; _Nettoyé

Gameplay in the “Zone of Becoming”: Locating Action in the Computer Game - Mukherjee, Souvik (Conference Proceedings of The Philosophy of Computer Games 2008, 2009)
Extending Alexander Galloway’s analysis of the action-image in videogames, this essay explores the concept in relation to its source: the analysis of cinema by the French philosopher Gilles Deleuze. The applicability of the concept to videogames will, therefore, be considered through a comparison between the First Person Shooter S.T.A.L.K.E.R. and Andrey Tarkovsky’s film Stalker. This analysis will compellingly explore the nature of videogame-action, its relation to player-perceptions and its loca-tion within the machinic and ludic schema.
Google-Books-ID: SJ972ia4kZQC
Keywords: 1-Cinéma; 1-Jeux vidéo; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 4-Europe (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; _Nettoyé

Creative Industries Across Cultural Borders: The Case of Video Games in Asia - Tschang, Ted (Creative Economies, Creative Cities: Asian-European Perspectives, 2009)
This chapter examines the relationship between culture, economics and policy within the creative industries (which for the purposes of this paper, are assumed to be equivalent to the cultural industries), and their manifestation in Asia. Addressing any one of these three issues is a challenge in itself, but addressing all three of them together raises the complexity even further. Early writers on the “creative economy” have noted how it works differently from the traditional economy (Florida 2002; Howkins 2001).1 Culture is vitally important to understanding how creative industries develop, but the role of culture in shaping national competitive advantage is not that clear. The same can be said for policy, and a discussion of the triad can be quite convoluted. Having said that, all three levels are still very relevant to the proper description of a creative industry — as I will show in this chapter.This paper attempts to address this triad of issues primarily with a production-and-innovation-oriented view of industrial organisation, bringing in creativity, culture and policy where possible. I shall do this primarily through the lens of one sector in particular — the video games industry — in which Asia has been investing heavily lately, and in which Japan has been an early leader. I will also provide a limited focus on the animation sector for comparative purposes. I will first provide a summary of how creative production in video games occurs in the US, followed by an examination of how Asian patterns compare. In particular, I am interested in whether individual and industrial level creativity differs in Asia. Within Asia, more detailed cases of the Chinese online games industry and the Philippine animation industry will be discussed, but relevant observations are also drawn from general knowledge and a literature review of Japan, Korea and Singapore, as well as interviews which corroborate those observations.
Keywords: 1-Jeux vidéo; 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé

Video Games in Asia - Ng Wai-ming, Benjamin (The Video Game Explosion: a History from Pong to Playstation and Beyond, 2008)
Section: xxi, 380 pages : illustrations ; 26 cm
Keywords: 1-Jeux vidéo; 2-Histoire/Historiographie critique; 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé

Digital Arabs: Representation in Video Games - Šisler, Vít (European Journal of Cultural Studies, 2008)
This article presents the ways in which Muslims and Arabs are represented and represent themselves in video games. First, it analyses how various genres of European and American video games have constructed the Arab or Muslim Other. Within these games, it demonstrates how the diverse ethnic and religious identities of the Islamic world have been flattened out and reconstructed into a series of social typologies operating within a broader framework of terrorism and hostility. It then contrasts these broader trends in western digital representation with selected video games produced in the Arab world, whose authors have knowingly subverted and refashioned these stereotypes in two unique and quite different fashions. In conclusion, it considers the significance of western attempts to transcend simplified patterns of representation that have dominated the video game industry by offering what are known as 'serious' games.
Number: 2
Keywords: 1-Jeux vidéo; 2-Histoire/Historiographie critique; 2-Humanités numériques; 2-Pédagogie décoloniale; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 3-Europe (corpus analysé); 4-Europe (lieu de production du savoir); _Nettoyé

The Video Game Developpement Process - Tschang, Feichin Ted (The Video Game Explosion: a History from Pong to Playstation and Beyond, 2008)
Section: xxi, 380 pages : illustrations ; 26 cm
Keywords: 1-Jeux vidéo; 2-Étude des industries culturelles; 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé

The Video Game Explosion: a History from Pong to Playstation and Beyond - Wolf, Mark J. P. (Greenwood Press, 2008)
Video games have become a limitless and multifaceted medium through which major corporations and Hollywood visionaries alike are reaching broader global audiences and influencing cultural trends at a rate unmatched by any other media. This book traces the growth of a global phenomenon that has become an integral part of popular culture.
Section: xxi, 380 pages : illustrations ; 26 cm
Keywords: 1-Jeux vidéo; 2-Histoire/Historiographie critique; 2-Étude des industries culturelles; 5-Auteur.rice PANDC; _Nettoyé

ゲーム的リアリズムの誕生 ; Gēmu-teki riarizumu no tanjō - Azuma, Hiroki (Kōdansha, 2007)
Section: 1 vol. (339 p.) : ill. en n. et b. ; 18 cm.
Keywords: 1-Jeux vidéo; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé; _À analyser; _À nettoyer

The U.S. Video Game Industry: Analyzing Representation of Gender and Race - Dunlop, Janet C. (International Journal of Technology and Human Interaction, 2007)
Today’s media are vast in both form and influence; however, few cultural studies scholars ad-dress the video gaming industry’s role in domestic maintenance and global imposition of U.S. hegemonic ideologies. In this study, video games are analyzed by cover art, content, and origin of production. Whether it is earning more “powers” in games such as Star Wars, or earning points to purchase more powerful artillery in Grand Theft Auto, capitalist ideology is reinforced in a subtle, entertaining fashion. This study shows that oppressive hegemonic representations of gender and race are not only present, but permeate the majority of top-selling video games. Finally, the study traces the origins of best-selling games, to reveal a virtual U.S. monopoly in the content of this formative medium.
Number: 2
Keywords: 1-Jeux vidéo; 2-Genre et sexualité; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; _Nettoyé

Playing at Being Mobile: Gaming and Cute Culture in South Korea - Hjorth, Larissa (Fibreculture Journal, 2006)
This paper is based on ongoing research into the gendered use of mobile convergent media in the Asia-Pacific region. In particular, what role does the cute have and how does it correlate with types of consumption? As a region, the Asia-Pacific is marked by diverse penetration rates, subject to local cultural and socio-economic nuances. Two defining locations - Seoul (South Korea) and Tokyo (Japan) - are seen as both mobile centres and gaming centres which the world looks towards as examples of the future-in-the-present. Unlike Japan, which pioneered the keitai (mobile) IT revolution with devices such as i-mode, South Korea has become a centre for mobile DMB (Digital Multimedia Broadband) with the successful implementation of TV mobile phones (TU mobile) in 2005. One of the key features of mobile media technologies is the attempt by the industry to find the next killer application . One such application is the possibility of online multiplayer games accessed through mobile (broadband) telephonic devices such as MMO golf RPG Shot Online (a golf game for mobile phones). Amongst this frenzy of trend spotting and stargazing, Seoul as a mobile broadband and gaming centre provides a curious case study for the social and cultural intricacies informing the rise of gaming as an everyday practice for many Koreans.This article begins by outlining the game play and technoculture particular to South Korea and then explores the phenomenon of Kart Rider in South Korean gaming cultures - and its perception/ reception outside Korea - to sketch some of the issues at stake in playing it cute (particularly in the form of cute avatars), consuming Korea and the endurance of co-present communities. In particular, it contemplates the implications of current emerging online mobile gaming genres such as so-called female games such as the cute' Kart Rider in order to think about changing modes of game play and attendant social spaces.
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude de la réception; 3-Asie (corpus analysé); 4-Océanie (lieu de production du savoir); 5-Autrice; _Nettoyé

How East Asian films are Reshaping National Identities: Essays on the Cinemas of China, Japan, South Korea, and Hong Kong - Jackson, Andrew David; Gibb, Michael; White, Dave (Edwin Mellen Press, 2006)
This collection of essays explores the mosaic of East Asian cinema by focusing on issues of identity, history and trans-regional cultural flow withnin this dynamic region. The argument of the editors is firstly, cinematic cross-pollination within East Asian film has been a constant since 1945, and second, any discussion of the complex identity of East Asia and its national cinemas must consider regional historical issues. These arguments run counter to recent literature published in the field of East Asian cinema that claim responses to Western globalization and modernization are the shaping forces for Asian cultural identity.
OCLC: 86087667
Keywords: 1-Cinéma; 3-Asie (corpus analysé); _Nettoyé; _À analyser; _À nettoyer; _À vérifier-Cinéma

The potential of America's Army, the Video Game as Civilian-Military Public Sphere - Li, Zhan (Massachusetts Institute of Technology, 2003)
The US Army developed multiplayer online First Person Shooter video game, America's Army, was examined as the first instance of an entirely state-produced and directed enterprise leveraging video game popular culture. Specifically, this study is concerned with the potential of the America's Army gamespace as a US civilian-military public sphere of the Information Age, as assessed through Habermasian theories of democratic communication. Interview fieldwork was carried out in several America's Army game communities including those of real-life military personnel, Christian Evangelicals, and hackers. The political activities of these exceptional game communities are considered for the ways they escape and transcend current critical theories of Internet-based public spheres.
Accepted: 2007-10-22T19:02:27Z
Keywords: 1-Jeux vidéo; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé

Japanese Video Games in Singapore: History, Culture and Industry - Ng Wai-ming, Benjamin (Asian Journal of Social Science, 2001)
Globalization of Japanese popular culture is reshaping the global cultural landscape. Some forms of Japanese popular culture (such as video games animation and sushi) are well-received internationally, whereas others (such as pop music, films and TV dramas) are only popular in Asia. Of all forms of Japanese popular culture, video game is perhaps the most powerful due to its strong universal appeal. It has dominated the world market since the mid-1980s. This article uses Singapore as a case study to demonstrate the global popularization of Japanese video games. There has been a boom of Japanese popular culture in Singapore in the 1990s. In particular, Japanese video games, comics and animation have become an integral part of youth culture in Singapore (Ng, March 2000: 234-246; Ng, May 2000: 44-56; Ng, June 2000: 1-14). Video game is a neglected topic in cultural studies. Although there are some basic studies of Japanese video games in the Western world (Hayes & Disney, 1995; Herz, 1997; Kinder 1991; Monopolies, 1995; Sheff, 1993), its impact in Asia is largely unknown. This article is a preliminary study of the Japanese video game culture and industry in Singapore from historical and socio-cultural perspectives, focusing on consoles, games and players. Based on interviews, questionnaires and data from newspapers and magazines, this research aims at pro viding a general overview of the history and impact of Japanese video games in Singapore. All the data and analyses are basic and this is beyond the scope of this paper to discuss any particular issue or theory in details. This paper consists of four sections. The first three sections outline the development of home video game consoles, handheld electronic games and game arcades respectively. The concluding section pinpoints the characteristics of the video
Keywords: 1-Jeux vidéo; 2-Histoire/Historiographie critique; 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé

電脳遊戯の少年少女たち ; Dennō yūgi no shōnen shōjotachi - Nishimura, Kiyokazu (Kōdansha, 1999)
Section: 212 pages : illustrations ; 18 cm
Keywords: 1-Jeux vidéo; 2-Genre et sexualité; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé; _À analyser; _À nettoyer

Arts of engagement: taking aesthetic action in and beyond the Truth and Reconciliation Commission of Canada - Martin, Keith; Robinson, Dylan (Wilfrid Laurier University Press, 2016)
It's about the role that music, film, visual art, and Indigenous cultural practices play in and beyond Canada's Truth and Reconciliation Commission on Indian Residential Schools. The essays question the ways in which components of the reconciliation, such as apology and witnessing, have social and political effects for residential-schools survivors, intergenerational survivors, and settler publics."– Provided by publisher
Section: viii, 374 pages : illustrations ; 23 cm
Keywords: 1-Histoire de l'art; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

The Decolonial Turn in Media Studies in Africa and the Global South - Moyo, Last (Palgrave Macmillan, 2020)
This book develops a nuanced decolonial critique that calls for the decolonization of media and communication studies in Africa and the Global South. Last Moyo argues that the academic project in African Media Studies and other non-Western regions continues to be shaped by Western modernity’s histories of imperialism, colonialism, and the ideologies of Eurocentrism and neoliberalism. While Africa and the Global South dismantled the physical empire of colonialism after independence, the metaphysical empire of epistemic and academic colonialism is still intact and entrenched in the postcolonial university’s academic programmes like media and communication studies. To address these problems, Moyo argues for the development of a Southern theory that is not only premised on the decolonization imperative, but also informed by the cultures, geographies, and histories of the Global South. The author recasts media studies within a radical cultural and epistemic turn that locates future projects of theory building within a decolonial multiculturalism that is informed by trans-cultural and trans- epistemic dialogue between Southern and Northern epistemologies.
Keywords: 1-TV; 2-Approches sociologiques; 2-Méthodologie de recherche décoloniale; 2-Pédagogie décoloniale; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 3-Afrique (corpus analysé); 3-Amérique centrale (corpus analysé); 3-Amérique du Sud (corpus analysé); 3-Asie (corpus analysé); 4-Afrique (lieu de production du savoir); 5-Auteur.rice noir.e; _Nettoyé

The Decolonial Turn: Towards a Southern Theory in Media Studies - Moyo, Last (The Decolonial Turn in Media Studies in Africa and the Global South, 2020)
This chapter argues that media and communication studies lie at the centre of Euro-American modernity. There is no doubt that the interdiscipline is the bastion of the coloniality of knowledge and its decolonization is way overdue given the indispensability of communication in the political, cultural, and epistemic liberation in the Global South. As a field as well as a social process, ‘mass communication was instrumental in the twentieth century crusade of modernity where it remained a key element in the unfolding of the future’ (Hardt in Myths for the Masses: An Essay on Mass Communication. Blackwell, London, p. 3, 2004). Decoloniality arises as a necessary moral and epistemic project to develop a nuanced praxis of decolonization agenda in the interdiscipline. Decolonization must decentre Eurocentrism and imperial theories and deprovincialize the marginalized alternate epistemologies in media and communication studies. The aim of decolonial turn is not to reproduce a new Hegelian hierarchies or new knowledge power structures in the field, but to give birth to a truly multicultural critical media theory that emerges from intercultural and trans-epistemic dialogue between the geographic Northern and Southern epistemologies.

Telenovela, an Instrument for Democracy - Eskandari, Sina (Review of European Studies, 2017)
Telenovela shapes important and highly favorite section of the television productions. The T.V. series have moved out from their traditional structure with an entertaining aspect and have been divided into different types and scopes. Taking into consideration the time and the atmosphere of dissemination which the Telenovela programs hold in T.V. antenna, there is a need to conduct studies on sociology of Telenovela more than any other times in the past. This article is an attempt to review the two subject-matters of Telenovela and Narration and their connection with democracy through sociological sporadic studies. This will also present the significance of this genre in T.V. productions at local and international discourses. Observations, field researches and library study methods have been employed in this research.
Keywords: 1-TV; 2-Approches sociologiques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude de la réception; 3-Amérique du Sud (corpus analysé); 4-Europe (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Identités diasporiques; Colombie (corpus analysé); Espagne (lieu de production du savoir); _Nettoyé

A telenovela brasileira: do nacionalismo à exportação - Santos, Lidia (Caravelle. Cahiers du monde hispanique et luso-brésilien, 2000)
Rentable produit d'exportation diffusé dans 128 pays, le feuilleton télévisé brésilien fait partie du quotidien de la population depuis une trentaine d'années. Si une grande part de son succès repose sur l'exploitation de « la culture des sentiments », dans sa version la plus moderne, il sait aussi plonger au cœur de la réalité comme l'a démontré entre autres avec brio « Le roi du troupeau » (1986) qui mettait en scène le conflit entre les sans-terre et les grands propriétaires terriens.
Keywords: 1-TV; 2-Approches sociologiques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des représentations; 3-Amérique du Sud (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; 5-Identités diasporiques; Brésil (corpus analysé); _Nettoyé; États-Unis (lieu de production du savoir)

The Telenovela and Emancipation: A Study on Television and Social Change in Brazil - Vink, Nico. (Royal tropical Institute, 1988)
N.D.
Section: 287 p. : illustrations ; 24 cm
Keywords: 1-TV; 2-Approches sociologiques; 3-Amérique du Sud (corpus analysé); Brésil (corpus analysé); _Nettoyé

Arte contemporáneo, violencia y creación feminista. "Lo personal es político" y la transformación del arte contemporáneo - Collado, Ana Martínez (Dossiers feministes, 2014)
Este texto analiza la transcendencia de la revolución feminista que se inició en los años 60 a partir del lema «Lo personal es político» y su influencia en la transformación del arte contemporáneo. En este contexto el trabajo desarrollado por las prácticas artísticas y la crítica feminista en relación a la denuncia de la violencia contra la mujer ocupa una posición destacada. A lo largo de estas últimas décadas no sólo ha evidenciado la violencia como un hecho continuado y global hacia la mujer sino que, además, ha iniciado nuevas narraciones que dan respuesta a un drama considerado socialmente como un irremediable «trágico final».
Keywords: 1-Histoire de l'art; 2-Approches sociologiques; 2-Genre et sexualité; 4-Europe (lieu de production du savoir); 5-Autrice; 5-Créatrice; _Nettoyé

Género y postcolonialismo en la creación videográfica: mujeres que escriben con la cámara y seducen en la pantalla - López, Xesqui Castañer (Dossiers feministes, 2014)
Postcolonialismo y feminismo utilizan conceptos comunes para el análisis y de/construcción de las narrativas dominantes. En países donde la colonización ha hecho estragos, las mujeres ponen en valor su empoderamiento como protagonistas de su destino. En esta línea las mujeres han aportado sus propuestas feministas para una nueva visión de lo colonial/postcolonial. Este trabajo pretende hacer un chequeo por aquellos trabajos videográficos de mujeres que, después de haber sido colonizadas, han realizado una descolonización cultural, situando su creatividad en varios continentes.
Keywords: 2-Genre et sexualité; 2-Humanités numériques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 3-Afrique (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 4-Europe (lieu de production du savoir); 5-Autrice; 5-Créatrice; _À vérifier-Cinéma

Género, representación y nuevas tecnologías: mujeres y video en México - Pech, Cynthia (Revista mexicana de ciencias políticas y sociales, 2006)
En este artículo, se aborda la temática del video como tecnología de género. El video es el medio de creación artística que algunas mujeres están utilizando para crear lo que se puede llamar imá genes en femenino. Se hace un acercamiento al discurso feminista y los presupuestos teóricos que se han tomado para el análisis del discurso videográfico de las mujeres. Se presenta un breve análisis de los trabajos de las videastas Pola Weiss y Pilar Rodríguez.
Keywords: 1-Cinéma; 1-Histoire de l'art; 1-TV; 2-Genre et sexualité; 2-Humanités numériques; 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 4-Amérique du Sud (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Créatrice; _Nettoyé

Making Race : Modernism and Racial Art in America - Francis, Jacqueline (University of Washintong Press, 2012)
A history of a past phenomenon - racial art - which has ramifications for the present.
Keywords: 1-Histoire de l'art; 2-Approches sociologiques; 2-Théories et épistémologie postcoloniales et décoloniales; 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice noir.e; 5-Créateur.rice PANDC; 5-Créateur.rice noir.e; _Nettoyé

Multiculturalismo y crítica postcolonial: la diáspora artística latinoamericana (1990-2005) - Marín Hernández, Elizabeth (Universitat de Barcelona, 2005)
La presencia del arte contemporáneo latinoamericano en el mundo contemporáneo, es concebida y movilizada a través de la existencia de una diáspora que ha perdido toda clase de arraigo en sus lugares territoriales definitorios. Los lenguajes que éstas muestran tienden ha consolidar un gusto por la simultaneidad, por la complejidad, por lo marginal, por lo oculto, y por las relativizaciones de una realidad que se pregunta constantemente por el sentido de su ser. Las diásporas artísticas ubican sus propuestas en medio de una serie de posicionamientos, para tratar de narrar las historias y las situaciones, que comenzaron ha emerger, en el momento en el cual se establece una dominante epocal, observadora y tolerante de la diversidad de los márgenes. El arte de las diásporas parecía configurar un nuevo espacio de representación, digno de ser atrapado o explicado dentro de nuevas posiciones teóricas, que manifestarán el por qué de unas de estas expresiones, muchas veces imposibles de traducir ante la pérdida del sentido del monopolio cultural occidental en el campo de las artes. De allí que, se hallan confeccionado en el mundo contemporáneo tardocapitalista y posindustrial, posiciones teóricas que incluyentes y estudiosas de la alteridad, de las diferencias, de la otredad, de la subalternidad. Para partir de los enunciados fragmentarios y múltiples mostrados por las teorías multiculturalistas y por la Crítica Poscolonial. Un intento de dotar de sentido a una realidad global, que ha perdido las fronteras. En este sentido, el espectro teórico que estudia a la diversidad observa a las culturas, a sus contaminaciones y desplazamientos desde diversas perspectivas, las cuales han incido en el mundo del arte contemporáneo en la formulación de un Nuevo Internacionalismo incluyente de las representaciones de los otros. El arte latinoamericano en este contexto se encuentra convocado, invitado, para legitimar la puesta en escena de unas realidades que pretenden ser cercanas, y a su vez alejadas, por las tensiones producidas por las propuestas discursivas del multiculturalismo y del poscolonialismo, en sus lecturas sobre las culturas como opuestas y no como parte integrante de una metacultura global. Las diásporas se ubican a partir de la deconstrucción de los postulados mayores de estas nuevas tendencias teóricas, para evidenciar su localidad desde la particularidad de sus legados e historias. Espacio en el cual, los artistas pertenecientes a la diáspora contemporánea, han demostrado responder con presteza a la cantidad de situaciones presentadas en medio de una realidad interconectada desde tiempos anteriores, y que en la actualidad manifiesta la exacerbación de las relaciones con lo que se pretende diferente.
Keywords: 1-Histoire de l'art; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Sud (corpus analysé); 4-Europe (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Identités diasporiques; _Nettoyé

Fotografía Latinoamericana Contemporánea: crítica poscolonial y renovación de los lenguajes. El caso de Brasil. - Rigat, Leticia (Revista Crítica Cultural, 2018)
En el presente trabajo nos proponemos reflexionar sobre el surgimiento de la categoría Fotografía Latinoamericana hacia fines de la década del setenta. Una reflexión sobre las prácticas fotográficas que refleja un intento de descolonizar las definiciones y categorías sobre la fotografía realizada en América Latina.Desde aquel momento, se estableció un concepto que englobaba bajo una misma rúbrica la fotografía latinoamericana y la representación del Ser latinoamericano, su identidad y su historia compartida en las diferentes naciones de la región. Una definición que cambia en los años noventa donde puede observarse una renovación de los modos de representación que complejizan las miradas sobre el pasado colonial y la heterogeneidad de nuestras identidades.Tras el análisis general de la búsqueda de definir una práctica cultural desde una perspectiva poscolonial de la fotografía latinoamericana, buscaremos centrarnos en el caso de la fotografía brasileña en dicho período.
Keywords: 1-Histoire de l'art; 2-Humanités numériques; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Sud (corpus analysé); 4-Amérique du Sud (lieu de production du savoir); _Nettoyé

Decolonizing Art History - Grant, Catherine; Price, Dorothy (Art History, 2020)
When, in 2015, students at the University of Cape Town in South Africa demanded the removal of a statue of British colonial and diamond merchant Cecil Rhodes from their campus, they initiated what was to become a global call to ‘decolonize the university’. In the same year, students at University College London began to ask the question: why is my curriculum white? Other public sector cultural institutions soon joined the chorus in an overdue acknowledgement that unspoken colonial legacies had for too long upheld and promulgated white privilege. The role of public sculpture as a catalyst for political debate and change has a long tradition within art's histories. It serves to remind us of the centrality of the discipline in promoting and maintaining dominant cultural values; and yet it also enables us to interrogate them as historically located and subject to inevitable temporal mutation. Whilst postcolonial studies and critical race studies have been informing and challenging the shape of art history for several decades, new generations of students, scholars, critics, curators, collectors, artists and audiences are seeking radical re-evaluations of the academy and those cultural institutions who hold themselves up as standard-bearers of our collective cultural heritage. But, what, if anything, is specific about the current moment's demands to reassess how universities, museums, and galleries teach, research, collect and exhibit? How can art historians, curators, collectors, museum directors, artists and writers respond to the call to decolonize art history? How can we draw from the rich legacy of postcolonial, feminist, queer and Marxist perspectives within art history, and what are the new theoretical perspectives that are needed?
Keywords: 1-Histoire de l'art; 4-Europe (lieu de production du savoir); 5-Autrice; _Nettoyé

Indigeneity and Decolonial Seeing in Contemporary Art of Guatemala. - Cornejo, Kency (FUSE Magazine, 2013)
The magazine published its final issue in Winter 2013.
Keywords: 1-Histoire de l'art; 2-Approches sociologiques; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique centrale (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé

Coloniality at Large: Latin America and the Postcolonial Debate - Moraña, Mabel; Dussel, Enrique; Jáuregui, Carlos A. (Duke University Press, 2008)
Postcolonial theory has developed mainly in the U.S. academy, and it has focused chiefly on nineteenth-century and twentieth-century colonization and decolonization processes in Asia, Africa, the Middle East, and the Caribbean. Colonialism in Latin America originated centuries earlier, in the transoceanic adventures from which European modernity itself was born. Coloniality at Large brings together classic and new reflections on the theoretical implications of colonialism in Latin America. By pointing out its particular characteristics, the contributors highlight some of the philosophical and ideological blind spots of contemporary postcolonial theory as they offer a thorough analysis of that theory’s applicability to Latin America’s past and present. Written by internationally renowned scholars based in Latin America, the United States, and Europe, the essays reflect multiple disciplinary and ideological perspectives. Some are translated into English for the first time. The collection includes theoretical reflections, literary criticism, and historical and ethnographic case studies focused on Ecuador, Guatemala, Mexico, Brazil, the Andes, and the Caribbean. Contributors examine the relation of Marxist thought, dependency theory, and liberation theology to Latin Americans’ experience of and resistance to coloniality, and they emphasize the critique of Occidentalism and modernity as central to any understanding of the colonial project. Analyzing the many ways that Latin Americans have resisted imperialism and sought emancipation and sovereignty over several centuries, they delve into topics including violence, identity, otherness, memory, heterogeneity, and language. Contributors also explore Latin American intellectuals’ ambivalence about, or objections to, the “post” in postcolonial; to many, globalization and neoliberalism are the contemporary guises of colonialism in Latin America. Contributors : Arturo Arias, Gordon Brotherston, Santiago Castro-Gómez, Sara Castro-Klaren, Amaryll Chanady, Fernando Coronil, Román de la Campa, Enrique Dussel, Ramón Grosfoguel, Russell G. Hamilton, Peter Hulme, Carlos A. Jáuregui, Michael Löwy, Nelson Maldonado-Torres, José Antonio Mazzotti, Eduardo Mendieta, Walter D. Mignolo, Mario Roberto Morales, Mabel Moraña, Mary Louise Pratt, Aníbal Quijano, José Rabasa, Elzbieta Sklodowska, Catherine E. Walsh
Keywords: 1-Cinéma; 1-Histoire de l'art; 1-Jeux vidéo; 1-TV; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique centrale (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 4-Amérique du Sud (lieu de production du savoir); 4-Europe (lieu de production du savoir); _Nettoyé

Telenovelas and Transformation: Saving Brazil's Television Industry - Svartman, Rosane (Routledge, Taylor & Francis Group, 2021)
"This book investigates how telenovelas may be the key to the future of Brazilian television and how this content can survive in an interconnected media landscape. Recognised writer and scholar Rosane Svartman considers the particular characteristics of the telenovela format - number of episodes, melodrama influence, and influence of the audience on future writing - to explore how these can be preserved on multimedia platforms, and the challenges this change may present. Svartman further charts the transformations of the telenovela throughout its history and its major influences and unveils the main storytelling elements and writing processes. Chapters examine the business model of Brazilian corporate television within the current context of hypermedia and analyse how this relationship evolves as it is influenced by the new interactive tools and technologies that amplify the audience's power. Merging empirical practices and theory, this book will be of great interest to scholars and students of transmedia storytelling, television studies, and Latin American media, as well as professionals working in these areas"– Provided by publisher.
Keywords: 1-TV; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Amérique du Sud (corpus analysé); 4-Amérique du Sud (lieu de production du savoir); 5-Auteur.rice; 5-Auteur.rice PANDC; Brésil (corpus analysé); Brésil (lieu de production du savoir); _Nettoyé

Telenovelas in Pan-Latino context - Erlick, June Carolyn (Routledge, 2018)
Keywords: _À vérifier-Télé

Sobre la telenovela: historia y condiciones de producción de la telenovela peruana : análisis textual de tres telenovelas - Arias de Aramburú, Rosario. (Universidad de Lima, Facultad de Ciencias de la Comunicación, Facultad de Ciencias Humanas, 1993)
Section: 76 p. ; 24 cm.
Keywords: _À vérifier-Télé

Introduction: What Is Queer Production Studies/Why Is Queer Production Studies? - Martin Jr., Alfred L. (Journal of Film and Video, 2018)
An introduction is presented in which the editor discusses various reports within the issue on topics including where and how queerness is produced, the use of paratexts to expand and stop queer readings of films, and queers' non-reliance on mainstream media to produce queer stories.
Keywords: 1-Cinéma; 2-Approches sociologiques; 2-Genre et sexualité; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); _Nettoyé

Beyond Bollywood: the Cultural Politics of South Asian Diasporic Film. - Desai, Jigna (Taylor & Francis, 2004)
Beyond Bollywood is the first comprehensive look at the emergence, development, and significance of contemporary South Asian diasporic cinema. From a feminist and queer perspective, Jigna Desai explores the hybrid cinema of the 'Brown Atlantic' through a close look at films in English from and about South Asian diasporas in the United States, Canada, and Britain, including such popular films as My Beautiful Laundrette, Fire, Monsoon Wedding, and Bend it Like Beckham.
OCLC: 824549185
Keywords: 1-Cinéma; 2-Approches sociologiques; 2-Genre et sexualité; 3-Asie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Identités diasporiques; _Nettoyé

Queer Representations in Chinese-language Film and the Cultural Landscape - Chao, Shi-Yan (Amsterdam University Press, 2020)
This book provides a cultural history of queer representations in Chinese-language film and media, negotiated by locally produced knowledge, local cultural agency, and lived histories. Incorporating a wide range of materials in both English and Chinese, this interdisciplinary project investigates the processes through which Chinese tongzhi/queer imaginaries are articulated, focusing on four main themes: the Chinese familial system, Chinese opera, camp aesthetic, and documentary impulse. Chao's discursive analysis is rooted in and advances genealogical inquiries: a non-essentialist intervention into the "Chinese" idea of filial piety, a transcultural perspective on the contested genre of film melodrama, a historical investigation of the local articulations of mass camp and gay camp, and a transnational inquiry into the different formats of documentary. This book is a must for anyone exploring the cultural history of Chinese tongzhi/queer through the lens of transcultural media.
Keywords: 1-Cinéma; 2-Genre et sexualité; 2-Muséologie critique; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 3-Asie (corpus analysé); _Nettoyé

Queer/Palestinian Cinema: A Critical Conversation on Palestinian Queer and Women's Filmmaking - Jankovic, Colleen; Nadia, Awad (Camera Obscura: Feminism, Culture, and Media Studies, 2012)
While expanding critiques of pinkwashing have drawn increasing attention to how queer issues in Israel and the Occupied Palestinian Territories are perniciously mobilized by a network of lobby groups, Brand Israel initiatives, and international gay and lesbian organizations, these critiques often fail to consider how queer Palestinians mobilize and understand themselves. This article reports on an October 2011 panel and film screening at Yale University and the Hagop Kevorkian Center for Near Eastern Studies at New York University. “Queer/Palestinian: Critical Strategies in Palestinian Queer and Women's Filmmaking” uniquely focused on questions of queerness and Palestine through a program of eight new Palestinian visual productions. The program brought together Palestinian film scholars, filmmakers, visual artists, and curators for a discussion of queer and feminist artistic practice in relation to Palestinian strategies for resistance. Together, the “Queer/Palestinian” films suggest the urgency for Palestinian visual artists to persistently generate new means of expressing, embodying, and critiquing visions for Palestinian society. Films such as Victoria Moufawad-Paul's Nus Enssas/ صيصنصن (Canada, 2011) and Raafat Hattab's Hourieh (Palestine, 2011) explore issues ranging from queer diasporic solidarity politics and challenges to out/closeted binaries and to the creative reinscription of nakba narratives. Nadia Awad's Two Adaptations of the Same Novel (US, 2011), Suzy Salamy's 1982/2006 (US, 2006), and Moufawad-Paul's Rejoice, O My Heart / يبلق اي حرفا (Canada, 2011) suggest an irreverent queer strategy by undermining the narrative conventions and visual codes of mainstream news media and popular US and Egyptian cinema. Salamy's video, previously projected through mobile exhibition on city buildings, and Eli Rezik's online “web-movies” Living Alone without Me (Palestine, 2011) and Between Us Two (Palestine, 2011) compelled a panel discussion of alternative means of distribution and exhibition. Finally, Alaa AbuAsad's Masturbate bil beit (Palestine, 2011) rounded out the program with an explicitly erotic and unapologetically political version of the meeting of “queer” and “Palestinian.”
Keywords: 1-Cinéma; 2-Genre et sexualité; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des représentations; 3-Europe (corpus analysé); 5-Identités diasporiques; _Nettoyé

New Queer Sinophone Cinema: Local Histories, Transnational Connections - Pecic, Zoran 1981- (Palgrave Macmillan, 2016)
This book looks closely at some of the most significant films within the field of queer Sinophone cinema. Examining queerness in films produced in the PRC, Taiwan and Hong Kong, the book merges the Sinophone with the queer, theorising both concepts as local and global, homebound as well as diasporic.
Keywords: 1-Cinéma; 2-Genre et sexualité; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Identités diasporiques; _Nettoyé

Decolonial Aesthesis and the Museum An Interview with Rolando Vázquez Melken - We

Black Europe Body Politics: Towards an Afropean Decolonial Aesthetics - Lockward, Alanna (Social Text Online, 2013)
The conceptualization of decolonial aesthetics is fairly recent, however its points of departure — the epistemic shifts that have been challenging coloniality in the artistic and cultural practices of the Global South — are as old as the colonial system. The defiance of colonialism in Vodou dance and rituals, which in Haiti ultimately led to the first successful enslaved people’s revolution, is a splendid case in point.
Keywords: 1-Histoire de l'art; 2-Approches sociologiques; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Afrique (corpus analysé); 3-Europe (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé

Decolonial AestheSis at the 11th Havana Biennial - Ferrera Balanquet, Raul Moarquech; Rojas-Sotelo, Miguel (Social Text Online, 2013)
The written curatorial statement from the organizing committee of the 11th Havana Biennial arrived via email the same day that we were preparing a dossier for the Romanian magazine IDEA. As we put together a brief history of “Decolonial Aesthetics” meetings and some portions of the “Decolonial Manifesto,” we discussed the need to bring to the biennial some of the critical and creative processes emanating from the decolonial collective. Previous editions of the biennial were overcharged with doses of “postmodernity,” marginal notes on the “postcolonial” condition, and celebrations of the “altermodern” (with its postproduction and relational dimensions). These were present in the curatorial practices, as well as in several of the presentations at the Theoretical Forum during the 2006 and 2009 editions. As we kept reading through the Biennial‘s curatorial statement, its content promoted a heated discussion among us where the idea of presenting a panel on decolonial aestheSis at the Havana Biennial became seen as not only relevant, but also, and above all, necessary.
Keywords: 1-Histoire de l'art; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Sud (corpus analysé); 5-Auteur.rice PANDC; _Nettoyé

The Power of Self-Definition - baca, Kim (Native Peoples, 2016)

Art and Knowledge: Towards a Decolonial Perspective (transversal texts)

L’art sami . Une conversation entre Katya García-Antón, Charis Gullickson et Synnøve Persen, menée par Knut Ljøgodt - García-Antón, Katya; Gullickson, Charis; Ljøgodt, Knut; Persen, Synnøve (Perspective. Actualité en histoire de l’art, 2019)
Depuis quelques années, les artistes samis font l’objet d’une attention croissante, que ce soit en Scandinavie ou à l’échelle internationale, et ils ont porté l’art sami sur le devant de la scène artistique contemporaine. Nous pourrions ainsi citer la récente participation de certains d’entre eux à la documenta 14 (Cassel ; Athènes, 2017), ou des expositions comme Sámi Stories (New York ; Anchorage, 2014-2015), Let the River Flow (Oslo ; Stockholm, 2018-2019), ou encore l’actuelle Histories: ...

The “Law and Order” of Violence Against Native Women: A Native feminist Analysis of the Tribal Law and Order Act - Robertson, Kimberly (Decolonization: Indigeneity, Education & Society, 2016)
In this essay, I aim to engage the growing body of scholarship that employs Indigenous feminist theories to understand and mobilize against the sexual and gendered violence committed against Native peoples. To accomplish this, I construct a Native feminist analysis of the 2010 Tribal Law and Order Act. I posit that despite the overwhelmingly positive characterizations of the legislation as “historic” in its potential to address violence against Native women and reduce crime in Indian country, a Native feminist reading of the Tribal Law and Order Act illuminates the degree to which the Act emerges from, engages with, and advances settler colonial and heteropatriarchal logics that cause violence against Native women in the first place. I suggest that although the Act does contain measures that have the potential to alleviate the experience of violence in Native women’s lives, it also diminishes tribal sovereignty, perpetuates the ongoing encroachment of tribal jurisdiction, regulates the boundaries of Native identity, and limits our ability to envision and enact practices of decolonization.
Keywords: 1-Cinéma; 1-Histoire de l'art; 1-Jeux vidéo; 1-TV; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé

Decolonial Listening: Sonorous Bodies and the Urban unconscious in Mexico city - Hernández Catellanos, Donovan Adrian; Toro, Roddrigo (Radical Sounds of Latin America, 2020)

Control mapping: Peter Pitseolak and Zacharias Kunuk on reclaiming Inuit photographic images and imaging - Winfield, Norman David (Decolonization: Indigeneity, Education & Society, 2014)
Inuit have been participating in the development of photo-reproductive media since at least the 19th century, and indeed much earlier if we continue on Michelle Raheja’s suggestion that there is much more behind Nanook’s smile than Robert Flaherty would have us believe. This paper examines how photographer Peter Pitseolak (1902-1973) and filmmaker Zacharias Kunuk have employed photography and film in relation to Raheja’s notion of “visual sovereignty” as a process of infiltrating media of representational control, altering their principles to visualize Indigenous ownership of their images. For camera-based media, this pertains as much to conceptions of time, continuity and “presence,” as to the broader dynamics of creative retellings. This paper will attempt to address such media-ontological shifts – in Pitseolak’s altered position as photographer and the effect this had on his images and the “presence” of his subjects, and in Kunuk’s staging of oral histories and, through the nature of film as an experience of “cinematic time,” composing time in a way that speaks to Inuit worldviews and life patterns – as radical renegotiations of the mediating properties of photography and film. In that they displace the Western camera’s hegemonic framing and time-based structures, repositioning Inuit “presence” and relations to land within the fundamental conditions of photo-reproduction, this paper will address these works from a position of decolonial media aesthetics, considering the effects of their works as opening up not only for more holistic, community-grounded representation models, but for expanding these relations to land and time directly into the expanded sensory field of media technologies.
Keywords: 1-Cinéma; 1-Histoire de l'art; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Europe (lieu de production du savoir); 5-Créateur.rice autochtone; _Nettoyé

Animalité. L’oeil amérindien - Sioui Durand, Guy (Inter, 2013)
Keywords: 1-Histoire de l'art; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Créateur.rice autochtone; _Nettoyé

L'Oeil amérindien: regards sur l'animal - Dionne, Hélène (Éditions du Septentrion, 1991)
Cette publication a été réalisée à l'occasion de l'exposition "L'Oeil Amérindien, Regards sur l'Animal au Musée de la civilisation à Québec.
Section: 118, v pages : illustrations ; 22 cm
Keywords: 1-Histoire de l'art; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Exposer, diffuser, faire entendre sa voix: présence de l'art contemporain autochtone au Québec entre 1967 et 2013 - De Lacroix, Pricile (Université du Québec à Montréal, 2017)
Ce mémoire se penche sur la diffusion de l'art contemporain autochtone au Québec de 1967 à 2013. Grâce à un corpus constitué de 640 expositions comprenant au moins un artiste des Premières Nations, métis ou inuit s'étant tenues quelque part dans la province à l'intérieur de ces 46 années, il a été possible de dresser un portrait global raisonné de ce qui s'est fait – ou ne s'est pas fait – concrètement, au-delà des a priori maintes fois reconduits. Il démontre, par exemple, que la décennie 1990 n'a pas été si « désertique » qu'il n'y parait, mais que la période 2000-2013, malgré son apparente vigueur, cache plusieurs dynamiques à l'œuvre au Québec rendant la reconnaissance et l'intégration des artistes autochtones dans le grand réseau des arts contemporains encore difficile. Ce mémoire apporte un éclairage sur le rôle marquant joué par les réseaux parallèles dans la diffusion de l'art contemporain autochtone, celui, parfois novateur, joué par les musées d'histoire et d'ethnographie ainsi que par les musées au sein même des communautés autochtones, puis la fermeture bien visible des institutions d'art du Québec jusqu'au milieu des années 2000. Il met également en lumière la présence de solitudes existantes au Québec, c'est-à-dire celle qui opère une division entre les artistes autochtones francophones et anglophones, favorisant grandement ces derniers, ainsi qu'entre artistes autochtones versus allochtones, les deux se mélangeant encore difficilement au sein des expositions. Enfin, ce mémoire permet de constater qu'en quatre décennies, le nombre d'artistes autochtones pratiquant de manière professionnelle au Québec n'a cessé d'augmenter, que Montréal s'est inscrite de plus en plus comme une métropole pouvant attirer des artistes autochtones de calibre national et international, que certaines régions du Québec, comme le Saguenay et l'Abitibi, ont, contrairement à d'autres, fait preuve d'une ouverture certaine face à l'art autochtone, mais également qu'il y a eu – et qu'il y a peut-être encore – une corrélation entre événements festifs et expositions accrues d'art contemporain autochtone, ce qui a tendance à le garder dans le domaine du folklore au Québec, et nuire véritablement à la reconnaissance des artistes professionnels.
OCLC: 1005657445
Keywords: 1-Histoire de l'art; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Muséologie critique; 2-Étude de la réception; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Art contemporain autochtone: Une question d’auto-identification - De Lacroix, Pricile (Captures, 2018)
Cet article discute de la pertinence d’identifier les arts visuels autochtones comme tel, de maintenir une forme de distinction vis-à-vis des œuvres produites par les artistes autochtones. Il s’agit d’éclairer le débat en soutenant qu’il existe bel et bien certains éléments précis qui permettent encore de définir les arts autochtones. Est également abordé le fait que les artistes continuent d’employer la stratégie claire de l’auto-identification. Sous cet angle, cette catégorie des arts autochtones ne semble pas encore caduque
Keywords: 1-Histoire de l'art; 2; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; 5-Créateur.rice autochtone; _Nettoyé

Rituels, mort et renaissance. Une redécouverte de l’artiste huron-wendat Pierre Sioui - De Lacroix, Pricile (Frontières, 2018)
Le travail de l’artiste huron-wendat Pierre Sioui est assez méconnu au Québec. Prolifique dans les années 1980 et ayant exposé aux quatre coins du Canada ainsi qu’aux États-Unis, Sioui a ensuite totalement disparu du milieu des arts contemporains autochtones. Une relecture du travail de cet artiste permet de redécouvrir un créateur fascinant tout à fait inscrit dans les préoccupations esthétiques et politiques de sa décennie. Sioui semble surtout avoir employé sa démarche artistique au service d’une redécouverte de son identité et de ses racines. Il l’a fait par le biais de recherches à la fois théoriques, cosmologiques et esthétiques des valeurs et de la culture huronne, le conduisant vers une thématique entourant principalement le sens des rituels, la mort et le cycle de la vie. Tous ces vieillards dans ses oeuvres, ces cadavres, ces ossements et ces crânes, parlent de relations entre mort et renaissance, entre colonialisme puis réappropriation, et semblent être pour Sioui une véritable trame créatrice à renouveler sans cesse.
Keywords: 1-Histoire de l'art; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; 5-Créateur.rice autochtone; _Nettoyé

Initiative de recherche sur les arts autochtones: rapport des consultations - Trépanier, France; Conseil des arts du Canada (Conseil des arts du Canada, 2008)
Le présent document est un rapport sur la série de consultations tenues en 2007 avec des artistes, des administrateurs des arts, des aînés, des jeunes et d’autres membres de la communauté autochtone. Cette série de consultations a eu lieu dans le cadre de l’initiative de recherche sur les arts autochtones, mise sur pied dans le but de planifier et d’entreprendre les travaux de recherche nécessaires pour appuyer et orienter le plan d’action sur les arts autochtones du Conseil des arts du Canada.
OCLC: 319678657
Keywords: 1-Histoire de l'art; 2-Méthodologie de recherche décoloniale; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; 5-Créateur.rice autochtone; _Nettoyé

Native Studies Keywords - Teves, Stephanie N.; Smith, Andrea; Raheja, Michelle H. (The University of Arizona Press, 2015)
"Native Studies Keywords explores selected concepts in Native studies and the words commonly used to describe them, words whose meanings have been insufficiently examined. This edited volume focuses on the following eight concepts : sovereignty, land, indigeneity, nation, blood, tradition, colonialism, and indigenous knowledge. Each section includes three or four essays and provides definitions, meanings, and significance to the concept, lending a historical, social, and political context. Take sovereignty, for example. The word has served as the battle cry for social justice in Indian Country. But what is the meaning of sovereignty? Native peoples with diverse political beliefs all might say they support sovereignty-without understanding fully the meaning and implications packed in the word. The field of Native studies is filled with many such words whose meanings are presumed, rather than articulated or debated. Consequently, the foundational terms within Native studies always have multiple and conflicting meanings. These terms carry the colonial baggage that has accrued from centuries of contested words. Native Studies Keywords is a genealogical project that looks at the history of words that claim to have no history. It is the first book to examine the foundational concepts of Native American studies, offering multiple perspectives and opening a critical new conversation"–Résumé du site web de l'éditeur
Section: xi, 356 pages : illustrations ; 23 cm.
Keywords: 2-Méthodologie de recherche décoloniale; 2-Pédagogie décoloniale; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; _Nettoyé

Whose Land Is It Anyway?: A Manual for Decolonization - McFarlane, Peter; Schabus, Nicole (Fédération of Post-Secondary Education of BC, 2018)
Whose Land Is It Anyway? A Manual for Decolonization provides a variety of Indigenous perspectives on the history of colonialism, current Indigenous activism and resistance, and outlines the path forward to reconciliation. This audio version features renowned Indigenous writers Taiaiake Alfred, Glen Coulthard, Russell Diabo, Beverly Jacobs, Melina Laboucan-Massimo, Kanahus Manuel, Jeffrey McNeil-Seymour, Pamela Palmater, Shiri Pasternak, Nicole Schabus, Senator Murray Sinclair, and Sharon Venne. The late Arthur Manuel’s writings are read by his grandson, Mahekan Anderson.
OCLC: 1122613551
Keywords: 2-Histoire/Historiographie critique; 2-Méthodologie de recherche décoloniale; 2-Pédagogie décoloniale; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; _Nettoyé

Baliser le territoire: a stake in the ground : Manifestation d'art contemporain autochtone - Myre, Nadia (Les Éditions Art Mûr, 2012)
Catalogue d'exposition. Du 14 janvier au 25 février 2012 à Art Mûr (Montréal. Titre : Baliser le territoire : Manifestation d’art contemporain autochtone / A Stake in the Ground: Contemporary Native Art Manifestation. Commissaire : Nadia Myre Sonny Assu, Jason Baerg, Carl Beam, Rebecca Belmore, Kevin Lee Burton, Hannah Claus, Bonnie Devine, Raymond Dupuis, Edgar Heap of Birds, Vanessa Dion Fletcher, Nicholas Galanin, Greg Hill, Robert Houle, Maria Hupfield, Rita Letendre, Glenna Matoush, Alan Michelson, Nadia Myre, Marianne Nicolson, Michael Patten, Arthur Renwick, Sonia Robertson, Greg Staats, Tania Willard, Will Wils
Section: 30 pages : illustrations principalement en couleur ; 21 cm
Keywords: 1-Histoire de l'art; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Imagen, medios y telecolonialidad: hacia una crítica decolonial de los estudios visuales - León, Christian (AISTHESIS: Revista Chilena de Investigaciones Estéticas, 2012)
This paper discusses the visuality processes in Latin America since the called «decolonial turn» approach. It analyzes the structural relationship between visual practices and global power arising in the context of the modern world system. It seeks to study the relationship between visual technologies, discourses and practices and the analytics of the coloniality of power, knowledge and being. It addresses the different types of hierarchies produced through a visual dispositive in the context of the international division of technology labor, the racialization of the population, and the global economy of images.
Keywords: 1-Cinéma; 1-Histoire de l'art; 1-TV; 2-Humanités numériques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 3-Amérique du Sud (corpus analysé); 4-Amérique du Sud (lieu de production du savoir); _Nettoyé

Writing Art Histories From Below: A Decolonial Guanaca-Hood Perspective - Cornejo, Kency (Latin American and Latinx Visual Culture, 2019)
As a teenager during my first internship at the Los Angeles County Museum of Art, a diversity initiative for inner-city youth, the education curator enthusiastically asked, “Who here would like to be an art historian!?” Like all the other Black and Brown inner-city kids, I laughed inside. My response was not due to a lack of art appreciation; I grew up in a family of refugees who were all self-taught artists back home in El Salvador, who taught me to draw before I learned to read. Nor was my response rooted in apathy for creative expression, for I was involved in art and theater from my elementary through my high school years. Art was such a natural part of my life that the idea of studying it seemed wasteful to me. The truth was, the internship was one of two jobs I was working to financially help my family and pay for my first year of community college. Hidden even deeper, though, I believed the museum world was not my world. I was a guanaca (the appellative given to people from El Salvador) whose family fled war and remained invisible in mainstream US Latinx history and culture. I was also from the hood—in my case Compton, California, a city made notorious by gangsta rap and police brutality. I believed that people like me guarded the art on the museum walls, cleaned the floors and bathrooms for visitors, and served the food at the high-priced café. People who looked like me, who came from where I did, did not determine what art could be, nor could we afford to buy it. We certainly did not write the history of art, for if we had, we would see ourselves represented on the walls.
Keywords: 1-Histoire de l'art; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique centrale (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Identités diasporiques; _Nettoyé

Decolonizing the Camera: Photography in Racial Time - Sealy, Mark Anthony (Durham University, 2015)
This thesis argues that photography is tainted with ingrained racist ideologies that have been present since its earliest inception in 1839. It considers the act of photographing the Other as a site of Western violence, myth, fantasy and disavowal. It examines archival images through the prism of race, representation and human rights with the aim of extracting new meanings that bring the Other into focus. This is done by reading the images both against the politics of the time in which they were made and as contemporary objects at work in the political and cultural present. The thesis makes the case that photography is burdened with ideological fault-lines concerning race and rights. The fault-lines have been forged by cultural and colonial violence resulting in Western scopic regimes that have dominated and fixed the Other within an inescapable set of Western epistemologies that have been used to serve and enhance imperial perspectives on race. I argue that these perspectives are still active within the Western mindset manifest as benign acts of photographic empathy that work to ultimately bolster Western hegemonies and economies. This thesis is based on 25 years of experience as a researcher and curator of international photography exhibitions, direct research into archives in different continental settings, the presentation of papers in a variety of national and international contexts, and interviews withphotographers, curators and academics. My hypothesis is that the history of photography can only be complete if the voice of the subaltern is made critically present within it, so allowing us to engage with important political racial memory work that can help us re-read the past and reconfigure different meanings concerning history, race, rights and human recognition in the present. I argue that photography requires decolonising work to be carried out on its history. I propose that if we do not recognise the historical and political conjunctures of racial politics at work within photography and the effects on those that have been culturally erased, made invisible or less than human by such images, then we remain hemmed within established orthodoxies of colonial thought concerning the racialised body, the subaltern and the politics of human recognition.
Keywords: 1-Histoire de l'art; 2-Approches sociologiques; 2-Recherche-création; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Nord (corpus analysé); 3-Europe (corpus analysé); 4-Europe (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; _Nettoyé

Le ré-ensauvagement par l’art: Le vieil Indien, les pommes rouges et les Chasseurs-Chamanes-Guerriers - Sioui Durand, Guy (Captures, 2018)
L’article part de la notion wendat d’ohtehra’ pour développer une approche de l’art contemporain autochtone comme processus de « ré-ensauvagement » à l’œuvre, entre autres, chez les artistes Kent Monkman (Cri-Irlandais) et Caroline Monnet (Anishinaabe-Française). L’auteur, en s’appuyant sur les théoriciens Deborah Doxtator (Kanien’kehá:ka), Georges Emery Sioui (Wendat) et Taiaiake Alfred (Kanien’kehá:ka) propose également une analyse de l’autochtonie en Amérique du Nord comme un fait glocal d’Américité.
Keywords: 1-Histoire de l'art; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Sakahàn: art indigène international - Hill, Greg A.; Lalonde, Christine.; Hopkins, Candice (Musée des beaux-arts du Canada, 2013)
Sakahàn' celebrates a growing international commitment to the collection, study and exhibition of indigenous art. Featuring more than 75 artists from around the world, this remarkable project places indigenous art squarely at the centre of contemporary art produced today.
Section: 285 p. : ill. en coul. ; 25 cm.
Keywords: 1-Histoire de l'art; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Afrique (corpus analysé); 3-Amérique centrale (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 3-Océanie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; 5-Créateur.rice PANDC; 5-Créateur.rice autochtone; 5-Créateur.rice noir.e; 5-Créatrice; _Nettoyé

Danser sur le dos de notre tortue = Niimtoowaad mikinaag gijiying bakonaan: nouvelle émergence des Nishnaabeg - Simpson, Leanne (Varia/Groupe Nota bene, 2018)
On parle beaucoup au Québec, comme dans le reste du Canada, de réconciliation avec les Premières Nations. Mais pour qu'un rapprochement fécond puisse avoir lieu, qu'une nouvelle ère, égalitaire et respectueuse, s'ouvre, le cadre constitutionnel canadien ne peut à lui seul en définir les règles. Toute entente devra aussi tenir compte des traditions autochtones. C'est dans ce contexte que le livre de Leanne Simpson trouve toute sa pertinence. L'auteure s'y demande comment redonner force, consistance et valeur à un héritage politique, juridique et culturel mis à mal par le processus colonial. D'une façon aussi concrète que tonique et audacieuse, elle y explore la langue, les mythes, les coutumes et les expériences de sa culture ancestrale afin de recouvrer et révéler cette manière singulière et originale d'être au monde trop longtemps méprisée. Si l'entreprise est inspirante pour toute communauté issue des Premières Nations, elle l'est également pour quiconque s'intéresse aux contradictions de la modernité occidentale. – [Renaud-Bray]
Section: 216 pages ; 21 cm
Keywords: 2-Méthodologie de recherche décoloniale; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; _Nettoyé

Reservation Reelism: Redfacing, Visual Sovereignty, and Representations of Native Americans in Film. - Raheja, Michelle H. (University of Nebraska Press, 2011)
In this deeply engaging account, Michelle H. Raheja offers the first book-length study of the Indigenous actors, directors, and spectators who helped shape Hollywood's representation of Indigenous peoples. Since the era of silent films, Hollywood movies and visual culture generally have provided the primary representational field on which Indigenous images have been displayed to non-Native audiences. These films have been highly influential in shaping perceptions of Indigenous peoples as, for example, a dying race or as inherently unable or unwilling to adapt to change. However, films with Ind
Keywords: 1-Cinéma; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; _Nettoyé; _À vérifier-Cinéma

Indigenous Art: New Media and the Digital - Igloliorte, Heather; Nagam, Julie; Taunton, Carla (Public, 2016)
Indigenous Art New Media and the Digital convenes leading scholars, curators, and artists from the Indigenous territories in Canada, the United States of America, Australia, and Aotearoa (New Zealand). It brings forth urgent conversations about resistance to colonial modernism, and highlights the historic and ongoing use of technology by Indigenous communities and artists as vehicles of resilience and cultural continuity. This issue ignites productive dialogue around the definitions of new and digital media art and practice-based work within the framework of Indigenous art and theory
Section: 215 pages : illustrations (principalement en couleur) ; 24 cm.
Keywords: 1-Histoire de l'art; 2-Humanités numériques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 3-Océanie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 4-Océanie (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

‘Decolonising the Camera: Photography in Racial Time’: Mark Sealy’s decolonial perspective on photography - Campbell (Project Myopia, 2021)

Hacia una memoria decolonial: breves apuntes para indagar por el acontecimiento detrás del acontecimiento fotográfico - Schlenker, Alex (Revista de Investigación en el Campo del Arte, 2012)
El retrato ha sido, a lo largo de la historia de la fotografía, un ritual cuya gramática visual está siempre condicionada por una mirada determinada. Retratamos para recordar, para fijar un instante en el tiempo. Cuando recordamos lo fotografiado convocamos de nuevo ese instante, pero, además, convocamos una realidad, un orden social específico construido por determinados actores sociales. La fotografía ha representado y legitimado en muchos momentos un patrón de poder colonial que, a través de sus estructuras de dominación, ha elaborado rígidas jerarquías sociales y raciales que han circunscrito a indios, afros, mujeres y clases populares a lo que Frantz Fanon llama la zona del No-ser. ¿Es posible recordar, entonces, a partir de la fotografía, de manera crítica y sin reproducir en tal ejercicio la matriz colonial que hizo posible la toma de la imagen?
Keywords: 1-Histoire de l'art; 2-Approches sociologiques; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 3-Amérique du Sud (corpus analysé); 4-Amérique du Sud (lieu de production du savoir); _Nettoyé

Call it a Vision Quest : Machinima in a First Nations context - Lapensée, Elizabeth; Lewis, Jason E. (Understanding Machinima Essays on Filmmaking in Virtual Worlds, 2013)
Article sur les machinimas de l'artiste Skawennati (Kanien'kehá:ka) et du travail du laboratoire d'ABTEC (Aboriginal Territories on cyberspace) à l'Université Concordia.
Keywords: 1-Histoire de l'art; 2-Recherche-création; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé; _À vérifier-Jeu vidéo

Research is Ceremony: Indigenous Research Methods - Wilson, Shawn (Fernwood Pub., 2008)
Indigenous researchers are knowledge seekers who work to progress Indigenous ways of being, knowing and doing in a modern and constantly evolving context. This book describes a research paradigm shared by Indigenous scholars in Canada and Australia, and demonstrates how this paradigm can be put into practice. Relationships don’t just shape Indigenous reality, they are our reality. Indigenous researchers develop relationships with ideas in order to achieve enlightenment in the ceremony that is Indigenous research. Indigenous research is the ceremony of maintaining accountability to these relationships. For researchers to be accountable to all our relations, we must make careful choices in our selection of topics, methods of data collection, forms of analysis and finally in the way we present information
Section: 144 p. : ill. ; 23 cm
Keywords: 2-Méthodologie de recherche décoloniale; 3-Amérique du Nord (corpus analysé); 3-Océanie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; _Nettoyé

Decolonizing Methodologies: Research and Indigenous Peoples - Tuhiwai Smith, Linda (Zed books, 2012)
To the colonized, the term 'research' is conflated with European colonialism; the ways in which academic research has been implicated in the throes of imperialism remains a painful memory. This essential volume explores intersections of imperialism and research - specifically, the ways in which imperialism is embedded in disciplines of knowledge and tradition as 'regimes of truth.' Concepts such as 'discovery' and 'claiming' are discussed and an argument presented that the decolonization of research methods will help to reclaim control over indigenous ways of knowing and being. Now in its eagerly awaited third edition, this bestselling book includes a co-written introduction features contributions from indigenous scholars on the book's continued relevance to current research. It also features a chapter with twenty-five indigenous projects and a collection of poetry
Section: xv, 240 pages : illustrations ; 22 cm
Keywords: 1-Cinéma; 1-Histoire de l'art; 1-Jeux vidéo; 1-TV; 2-Méthodologie de recherche décoloniale; 2-Pédagogie décoloniale; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 3-Océanie (corpus analysé); 4-Océanie (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; _Nettoyé

Decolonization is not a Metaphor - Tuck, Eve; K. Wayne Yang (Journal Publishing Services, 2012)
Our goal in this article is to remind readers what is unsettling about decolonization. Decolonization brings about the repatriation of Indigenous land and life; it is not a metaphor for other things we want to do to improve our societies and schools. The easy adoption of decolonizing discourse by educational advocacy and scholarship, evidenced by the increasing number of calls to “decolonize our schools,” or use “decolonizing methods,” or, “decolonize student thinking”, turns decolonization into a metaphor. As important as their goals may be, social justice, critical methodologies, or approaches that decenter settler perspectives have objectives that may be incommensurable with decolonization. Because settler colonialism is built upon an entangled triad structure of settler-native-slave, the decolonial desires of white, non-white, immigrant, postcolonial, and oppressed people, can similarly be entangled in resettlement, reoccupation, and reinhabitation that actually further settler colonialism. The metaphorization of decolonization makes possible a set of evasions, or “settler moves to innocence”, that problematically attempt to reconcile settler guilt and complicity, and rescue settler futurity. In this article, we analyze multiple settler moves towards innocence in order to forward “an ethic of incommensurability” that recognizes what is distinct and what is sovereign for project(s) of decolonization in relation to human and civil rights based social justice projects. We also point to unsettling themes within transnational/Third World decolonizations, abolition, and critical space-place pedagogies, which challenge the coalescence of social justice endeavors, making room for more meaningful potential alliances
Keywords: 1-Cinéma; 1-Histoire de l'art; 1-Jeux vidéo; 1-TV; 2-Méthodologie de recherche décoloniale; 2-Pédagogie décoloniale; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; _Nettoyé

First Person Plural: Aboriginal Storytelling and the Ethics of Collaborative Authorship - McCall, Sophie (UBC Press, 2011)
Told-to narratives, or collaboratively produced texts by Aboriginal storytellers and (usually) non-Aboriginal writers, often confound traditional literary understandings of voice and authorship. In this innovative exploration, these unique narratives are not romanticized as unmediated translations of oral documents, nor are they dismissed as corruptions of original works. Rather, the approach emphasizes the interpenetration of authorship and collaboration. Discussing a wide range of told-to narratives, including ethnography, recorded (auto)biography, testimonial life narrative, documentary, myth, legend, and song, Sophie McCall explores the multifaceted implications of the choices that editors, translators, narrators, and filmmakers make as they channel these narratives into new forms. Focused on the 1990s, when debates over voice and representation were particularly explosive, this comprehensive study examines collaboratively produced texts in conjunction with key political events that have shaped the struggle for Aboriginal rights in Canada. Emphasizing the scope rather than the limits of the told-to narrative, McCall considers how Aboriginal voices have been represented in a range of forums such as public inquiries, commissioners’ reports, and land claims court cases. A captivating inquiry, First Person Plural offers a vital, interdisciplinary discussion of how told-to narratives contribute to larger debates about Indigenous voice and literary and political sovereignty. This innovative, interdisciplinary study will be of interest to students and scholars of Indigenous studies, textualized oral narrative, literary studies, and Canadian cultural studies
Section: ix, 254 p. ; 24 cm
Keywords: 2-Méthodologie de recherche décoloniale; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; _Nettoyé

Reclaiming Indigenous Voice and Vision - Battiste, Marie. (UBC Press, 2000)
This book seeks to clarify postcolonial Indigenous thought beginning at the new millennium. It represents the voices of the first generation of global Indigenous scholars and converges those voices, their analyses, and their dreams of a decolonized world.
Section: XXX-314 p. ; 24 cm
Keywords: 1-Cinéma; 1-Histoire de l'art; 1-Jeux vidéo; 1-TV; 2-Méthodologie de recherche décoloniale; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; _Nettoyé

Por uma pedagogia crioula : memória, identidade e resistência no quilombo de Conceição das Crioulas – PE - Nascimento, Márcia Jucilene do (Universidade de Brasília, 2017)
This dissertation aims to describe the specific schooling process developed in the quilombo of Conceição das Crioulas, in Salgueiro / PE. This process was a result of the socio-historical reconstruction movement of the quilombo’s history, which started in the 1980s. This process triggered several conflicts, and priority was given to the regaining of their territory and to the search for educational practices with decolonizing ideals. Based on the individual and collective memories of Conceição das Crioulas people, we have registered the historical accounts of the community’s resistance to the domination and oppression systems imposed to them since the arrival of the creole founders until today. The methodological trajectory was based on interviews, informal conversations and the analysis of a video-documentary, specifically recorded for this research. This path also allowed us to evaluate how we have perceived and done our school education over a period of twenty-two years, whose milestone is the inauguration, in 1995, of Professor José Mendes school, a local public school where grades 6th to 9th are taught. First, this paper addresses important elements for the beginning of this search. Next, it describes practices and specific actions of the education of Conceição das Crioulas. After that, it draws a comparative analysis about this and other pedagogical experiences, highlighting connections and significant distances between them. Finally, at the end of the last chapter, it conceptualizes this experience, which was named Crioula Pedagogy in the community.
Keywords: 2-Méthodologie de recherche décoloniale; 2-Pédagogie décoloniale; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Sud (corpus analysé); 4-Amérique du Sud (lieu de production du savoir); 5-Auteur.rice noir.e; _À analyser

Transference, Tradition, Technology: Native New Media Exploring Visual & Digital Culture - Townsend, Melanie A.; Hopkins, Candice (Walter Phillips Gallery Editions, 2005)
Transference, Tradition, Technology explores Canadian Aboriginal new media and references the work of artists within a political, cultural and aesthetic milieu. The book constructs a Native art history relating to these disciplines, one that is grounded in the philosophical and cosmological foundations of Aboriginal concepts of community and identity within the rigour of contemporary arts discourse. Approachable in nature but scholarly in content, this book is the first of its kind. A text book for students and teachers of Canadian Aboriginal history and visual and media art, and a source for writers, scholars and historians, Transference, Tradition, Technology is co-produced with the Art Gallery of Hamilton, Hamilton; and Indigenous Media Arts Group, Vancouver.
Keywords: 1-Cinéma; 1-Histoire de l'art; 2-Humanités numériques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Le territoire des ondes - Patrick, Boivin; Alland, Flammand (2006)
Documentaire du Wapikoni Mobile. Responsable de la radio de Wemotaci, le musicien atikamekw, Patrick Boivin, rencontre le sage Charles Coocoo. Un très beau film sur l'importance pour les autochtones de s'approprier les médias contemporains afin de faire entendre la voix de leur de peuple.
Keywords: _Nettoyé

Latin American Decolonial Thought, or Making the Subaltern Speak - Asher, Kiran (Geography Compass, 2013)
The Modernity/Coloniality/Decoloniality (MCD) research program is a collective project associated with Latin America. In addition to a critique of Eurocentric “colonial modernity,” the project highlights non-Eurocentric forms of knowing and being in the world. It also aims to foster alternative or decolonial thinking emerging from the lived colonial experiences of those situated “outside” Europe. This last is what MCD proponents claim differentiates it from postcolonial critiques of modernity with their emphasis on deconstruction. This review provides a brief but critical overview of the MCD project's parameters and claims. It makes a cautionary call to those tempted by “alternatives to modernity,” who might want to uncritically adopt alternative decolonial thinking. It concludes with a call for a closer and critical engagement with Latin American decolonial ideas and those they contest.
Keywords: 1-Cinéma; 1-Histoire de l'art; 1-Jeux vidéo; 1-TV; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Sud (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé

Feminist Geographies in Latin America: Epistemological Challenges and the Decoloniality of Knowledge - Silva, Joseli Maria; Ornat, Marcio Jose (Journal of Latin American Geography, 2020)
This paper analyzes the growth of gender studies in Latin America, despite facing resistance in the scientific field and from the advance of conservative policies on the continent. It also addresses the challenges that feminist research faces in colonized spaces. To develop our argument, we draw on the scholarship of feminist researchers in Brazil, Mexico, and Argentina, such as Veleda da Silva and Lan (2007), Silva and Vieira (2014), Silva, César and Pinto (2015), Colombara (2016), Lan (2016), Veleda da Silva (2016), Ibarra-García and Escamilla-Herrera (2016), Zaragocin-Carvajal, Moreano-Venegas, and Álvarez-Velasco (2018), and Silva and Ornat (2019). This paper also examines the difficulties that Latin American feminist geographies face in establishing their own foundations in a globalized world where the geopolitics of global knowledge of geography is increasingly structured by the epistemological centralization of the Anglophone northern hemisphere.
Keywords: 1-Cinéma; 1-Histoire de l'art; 1-Jeux vidéo; 1-TV; 2-Genre et sexualité; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Sud (corpus analysé); 4-Amérique du Sud (lieu de production du savoir); 5-Autrice; _Nettoyé

Re-Mapping Latin American Studies: Postcolonialism, Subaltern Studies, Postoccidentalism and Globalization Theory - Mendieta, Eduardo (Dispositio, 2005)
Keywords: 1-Cinéma; 1-Histoire de l'art; 1-Jeux vidéo; 1-TV; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Sud (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); _Nettoyé

The Postcolonial in Latin America and the Concept of Coloniality: A Historian’s Point of View - Salvatore, Ricardo D. (A Contracorriente: una revista de estudios latinoamericanos, 2010)
Discussion of Coloniality at Large: Latin America and the Postcolonial Debate (Durham, NC and London: Duke University Press, 2008) by Mabel Moraña, Enrique Dussel, and Carlos A. Jauregui (eds.).
Keywords: 1-Cinéma; 1-Histoire de l'art; 1-Jeux vidéo; 1-TV; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Sud (corpus analysé); 4-Amérique du Sud (lieu de production du savoir); _Nettoyé

Postcolonial Brazil - Weinstein, Barbara (The Oxford Handbook of Latin American History, 2010)
This article is a portal into the rapidly expanding historiography of modern Brazil. It highlights the major nodes of discussion and debate among historians of Brazil over the last two decades, and describes how these debates have been shaped by broader shifts in the historical profession. Two themes frame this survey of the new historiographical trends for postcolonial Brazil. One is the impact of the linguistic or cultural turn on that historiography. Slower to have an impact in the Brazilian historiography were the writings of the Subaltern Studies scholars and postcolonial theorists.
Keywords: 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Sud (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Autrice

Hacia una reapropiación de la geografía crítica en América Latina. - Zaragocin-Carvajal, Sofía; Moreano-Venegas, Melissa; Álvarez-Velasco, Soledad (Íconos. Revista de Ciencias Sociales, 2018)
This article attempts to review and synthesise the main debates in critical geography across both the Latin American and Anglo-Saxon traditions. By reviewing the main theoretical approaches including from political ecology, feminist geography, post-colonial and de-colonial approaches and the geography of motilities and migration, the aim of this article is to delineate a pan-Latin American approach to critical geography. We also consider why some approaches and topics have received greater or lesser attention in Latin American scholarship. Finally, we emphasize the importance of establishing a new transnational dialogue based on regionally situated critical research that questions and proposes new pathways in the production of knowledge from and about the region. We suggest this approach be nested in critical theory and committed to local political and territorial struggles.
Keywords: 1-Cinéma; 1-Histoire de l'art; 1-Jeux vidéo; 1-TV; 2-Genre et sexualité; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 4-Amérique du Sud (lieu de production du savoir); _Nettoyé

El giro decolonial: reflexiones para una diversidad epistémica más allá del capitalismo global - Castro-Gómez, Santiago; Grosfoguel, Ramón (Siglo del Hombre Editores, 2007)
Este libro reúne ensayos de doce teóricos latinoamericanos, quienes hacen una reflexión acerca de la diversidad epistémica en el mundo contemporáneo. Plantean que la decolonialidad en el siglo XXI tendrá que dirigirse a la heterarquía de las múltiples relaciones raciales, étnicas, sexuales, económicas y de género que quedaron intactas durante el siglo XX.
Keywords: 1-Cinéma; 1-Histoire de l'art; 1-Jeux vidéo; 1-TV; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Sud (corpus analysé); 3-Europe (corpus analysé); 4-Amérique du Sud (lieu de production du savoir); _Nettoyé

“Estrategia ARTNIVORA” Estéticas decoloniales, antropofagia y la construcción de una mirada crítica para las artes visuales en América Latina - López Jaramillo, David Andrés (Universidad Andina Simón Bolívar, 2016)
Este trabajo trata sobre artes visuales modernas y contemporáneas en América latina. Como ejes trasversales del texto se plantea: la decolonialidad y la antropofagia crítica. Parte desde la problematización de las estéticas decoloniales y la revisión histórica del arte latinoamericano del siglo XX, primero modernista luego posmoderno, desde una aproximación decolonial. Su intención es analizar si la opción decolonial es viable para artes visuales. Pretende analizar la propuesta de la decolonialidad, así como sus límites y sus principales riesgos. Además de establecer puentes con la ética posmoderna y la ética latinoamericana. En el capítulo dos trata como eje principal la antropofagia, tanto como movimiento artístico moderno, como propuesta de producción y aproximación crítica, cultural y artística. Mira a la antropofagia como proceso y como metodología posmoderna de resistencia. Bajo estos parámetros analiza la obra de tres artistas modernistas latinoamericanos: Joaquín Torres García, Tarsila do Amaral y Wilfredo Lam. Luego, y a partir de esta aproximación, en el capítulo tres se plantea el análisis crítico a una práctica artística: la muestra ARTNIVORA (2011) del colectivo femenino de arte La emancipada en Quito. Analiza en esta muestra, como el colectivo emplea la antropofagia crítica para buscar un argumento de emancipación de género. En esta muestra de arte actual, las estrategias de la apropiación y la cita contemporáneas son leídas como una práctica antropofágica. La intención es presentar un diferente punto de vista para la producción y la apreciación de las artes visuales y plásticas contemporáneas latinoamericanas, tanto obras de arte, como el trabajo creativo y los procesos de sus autores y autoras. El texto plantea la importancia del sentido de pertenencia con la localidad en la expresión de arte visual, si bien emplea un lenguaje cuyos códigos pueden ser leídos internacionalmente, su anclaje es su localidad y problemáticas insertas en un contexto local.
Keywords: 1-Histoire de l'art; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Sud (corpus analysé); 4-Amérique du Sud (lieu de production du savoir); _Nettoyé

Una lectura postpornográfica de Roberto Bolaño: escritura, feminismo y postcolonialismo - Rodríguez, Josué Hernández (Moderna språk, 2021)
The proliferation of critical and creative post-porn movements, which vindicate the representation of dissident sexualities under a new feminist, queer and transgender perspective, provide tools of analysis to rethink past literary and audiovisual pornographic productions, as well as to reformulate current ones. In this line of intermediate research, between cinema and literature, an approach to the work of Chilean writer Roberto Bolaño is proposed that will allow us to discern whether he can be considered a post-porn author related to the Golden Age of pornographic cinema in the 1970s and 1980s. Two of his stories and a novel will be studied: “Joanna Silvestri”, from which a gender reading will be made that problematizes the role of women within an eminently heteronormative industry, obsessed with representing male ejaculation; “Prefiguración de Lalo Cura”, analyzed under a postcolonial perspective of appropriation of subaltern bodies conceived as geographical territories, and Una novelita lumpen, in the field of porn pedagogy. The resulting findings make it possible to establish that Roberto Bolaño can indeed be considered a post-porn author by translating the narrative proposals of the Golden Age porn films into his own literary project, with a feminist and post-colonial critical intention.
Keywords: 2-Approches sociologiques; 2-Genre et sexualité; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 4-Amérique du Sud (lieu de production du savoir)

Imágenes decoloniales sobre la complejidad cultural - Lucero, Maria Elena (Revista SURES, 2015)
La producción visual de América Latina del siglo XX condensa una variable de emergentes artísticos diversosno solo por la complejidad histórica que caracteriza al continente sino por la pluralidad de comunidades nativas que conformaron su territorio geográfico. Así como la crítica cultural ha abonado fuertemente el terreno de las artes también han surgido otras vías de estudio enlazadas con dimensiones sociales, económicas y políticas. Cabe mencionar los aportes al ámbito de las producciones visualesde una perspectiva analítica que en el escenario latinoamericano se inscribe en el llamado ‘giro decolonial’. América Latina posee una tradición franqueada por luchas contra el colonialismo y el eurocentrismo. En la actualidad, la esfera artística contemporánea manifiesta sus posicionamientos colectivos frente a una sociedad globalizada. En este aspecto, las contribuciones de la inflexión decolonial permiten pensar otros sentidos inherentes a las formulaciones estéticas surgidas en estas regiones. Se analizarán las obras de Alfredo Jaar, Tania Bruguera y Milagros de la Torre.
Keywords: 1-Histoire de l'art; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Sud (corpus analysé); 4-Amérique du Sud (lieu de production du savoir); 5-Autrice; 5-Créateur.rice PANDC; _Nettoyé

Modernidad artística y giro decolonial - Rueda, María de los Ángeles De; Guzmán, Gerardo (Arte e Investigación Revista Científica de la Facultad de Bellas Artes, 2018)
Se trata de revisar las concepciones canónicas de la modernidad artística latinoamericana desde una perspectiva crítica y situada desde los estudios decoloniales y el hacer en las cátedras Historia de las Artes Visuales III e Historia de la Música III de la Facultad de Bellas Artes de la Universidad Nacional de La Plata. En ambas materias se trabajan contenidossobre las artes locales, nacionales y latinoamericanas/sudamericanas, en comparación conlos movimientos europeos de la modernidad y la contemporaneidad. Este proyecto revisa algunas líneas historiográficas recientes sobre la historia y la teoría de las artes locales ylatinoamericanas. Se revisarán, también, algunos casos de producciones artísticas.
Keywords: 1-Histoire de l'art; 2-Histoire/Historiographie critique; 2-Pédagogie décoloniale; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Sud (corpus analysé); 4-Amérique du Sud (lieu de production du savoir); _Nettoyé

El lugar del arte en la opción por una desobediencia epistémica decolonial // The place of art in the option for decolonial epistemic disobedience - Bolaños, Martin (Hermeneutic : Revista Digital de Arte, Crítia y Filosofía, 2020)
The visualization of the ways of doing what is sensible in a globalized society is one more form of discipline of sensitivity and its poetics. The border between a colonized sensibility and an insurgent sensibility becomes blurred as the international distribution of the sensible assigns specific ways capable of domesticating the sensibilities that overwhelm it. Those sensitivities not that cannot be captured neither as merchandise, nor as an archive, nor as heritage. The overflow and excess of these sensitivities that have not been caught in the networks of an international art market jeopardize, by their very existence, the categories that aesthetics, as a modern-colonial discipline has produced to conceptualize and codify the sensitivities (isolationism) neutralized their capacities to witness historically subjugated life experiences. In this sense, decolonial stasis retrace the traced path, and one of the ways of retracing is to disarticulate or at least resignify words such as "art", "artist", "work", "production", "aesthetic", or "Poetic", among others.
Keywords: 1-Histoire de l'art; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique centrale (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 4-Amérique du Sud (lieu de production du savoir); _Nettoyé

When Latin American Art Took a “Decolonial Turn” - Chilewich, Nika (Hyperallergic, 2018)
An exhibition at Mexico City's Museo Jumex argues that from 1960 and '85, artists across Latin America created a "decolonial" cultural history. However, the use of the term is largely unclear.
Keywords: 1-Histoire de l'art; 2-Muséologie critique; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Autrice

Corporeal Identities, Maternal Artivism: A New Decolonial Approach to the Study of Latin American Women Artists - Demori, Lara (Arts, 2019)
Stemming from Grosfoguel’s decolonial discourse, and particularly his enquiry on how to steer away from the alternative between Eurocentric universalism and third world fundamentalism in the production of knowledge, this article aims to respond to this query in relation to the field of the art produced by Latin American women artists in the past four decades. It does so by investigating the decolonial approach advanced by third world feminism (particularly scholar Chandra Talpade Mohanty) and by rescuing it from—what I reckon to be—a methodological impasse. It proposes to resolve such an issue by reclaiming transnational feminism as a way out from what I see as a fundamentalist and essentialist tactic. Following from a theoretically and methodological introduction, this essay analyzes the practice of Cuban-born artist Marta María Pérez Bravo, specifically looking at the photographic series Para Concebir (1985–1986); it proposes a decolonial reading of her work, which merges third world feminism’s nation-based approach with a transnational outlook, hence giving justice to the migration of goods, ideas, and people that Ella Shohat sees as deeply characterizing the contemporary cultural background. Finally, this article claims that Pérez Bravo’s oeuvre offers the visual articulation of a decolonial strategy, concurrently combining global with local concerns.
Keywords: 1-Histoire de l'art; 2-Genre et sexualité; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Sud (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; 5-Créatrice; _Nettoyé

Sensing Decolonial Aesthetics in Latin American Arts - Ramos, Juan G. (University Press of Florida, 2018)
Bringing Latin American popular art out of the margins and into the center of serious scholarship, this book rethinks the cultural canon and recovers previously undervalued cultural forms as art. Juan Ramos uses "decolonial aesthetics," a theory that frees the idea of art from Eurocentric forms of expression and philosophies of the beautiful, to examine the long decade of the 1960s in Latin America–a time of cultural production that has not been studied extensively from a decolonial perspective. Ramos looks at examples of "antipoetry," unconventional verse that challenges canonical poets and often addresses urgent social concerns. He analyzes the militant popular songs of nueva canción by musicians such as Mercedes Sosa and Violeta Parra. He discusses films that use visually shocking images and melodramatic effects to tell the stories of Latin American nations. He asserts that these different art forms should not be studied in isolation but rather brought together as a network of contributions to decolonial art. These art forms, he argues, appeal to an aesthetic that involves all the senses. Instead of being outdated byproducts of their historical moments, they continue to influence Latin American cultural production today.
Keywords: 1-Histoire de l'art; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Sud (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé

Beyond the Favela, the Rua and the Museum: Reading Hélio Oiticica and Artur Barrio from Decoloniality. Fluctuations and Paradoxes of a Latin-American Modernity - Lucero, María Helena (Southern Perspectives)
Keywords: 1-Histoire de l'art; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Sud (corpus analysé); 4-Amérique du Sud (lieu de production du savoir); 5-Autrice; _Nettoyé

Clearing a Path: New Ways of Seeing Traditional Indigenous Art - Robertson, Carmen.; Farrell Racette, Sherry (University of Regina, Canadian Plains Research Center, 2009)
Catalogue d'exposition. This exhibition includes art from artists who live in all parts of Saskatchewan, from Wood Mountain in the south to Turner Lake in the north. From youth to elder, the artists mentor others to ensure the ongoing vitality of traditional arts in the province
Section: 80 p. : ill. en coul. ; 21 cm.
Keywords: _Nettoyé

“I Want to Call Their Names in Resistance”: Writing Aboriginal Women into Canadian Art History. - Farrell Racette, Sherry (Rethinking Professionalism: Essays on Women and Art in Canada, 1850-1970, 2012)
As bell hooks points out in “Aesthetic Inheritances: History Worked by Hand,” writing an inclusive art history is no easy task. Until very recently, Aboriginal women have been written out of Canadian art history, or rather art history has been written around us. How do we write ourselves in? It falls far beyond simple insertion; the erasures are far too deep. Insertion presumes a simple forgetfulness, an oversight, a neglecting of the obvious. Insertion assumes a presence. It implies a shared mode of history, a common belonging to a collective archive, and an agreed-upon understanding of what it means to be an artist. Beyond the important considerations of race, gender, culture, and social class, our distinct legal status in Canada must be acknowledged. This was particularly true for women artists working between 1880 and 1970. For much of the time period under consideration, First Nations communities lived under a profoundly restrictive regime of colonial power. Relationships between First Nations people and the Canadian state have been defined by the Indian Act, a piece of legislation enacted in 1876 and surviving, through many amendments and revisions, until the present time.
Keywords: 1-Histoire de l'art; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Returning Fire, Pointing the Canon: Aboriginal Photography as Resistance - Farrell Racette, Sherry (The Cultural Work of Photography in Canada, 2011)
Résumé livre : The Cultural Work of Photography in Canada is an in-depth study on the use of photographic imagery in Canada from the late nineteenth century to the present. This volume of fourteen essays provides a thought-provoking discussion of the role photography has played in representing Canadian identities. In essays that draw on a diversity of photographic forms, from the snapshot and advertising image to works of photographic art, contributors present a variety of critical approaches to photography studies, examining themes ranging from photography's part in the formation of the geographic imaginary to Aboriginal self-identity and notions of citizenship. The volume explores the work of photographs as tools of self and collective expression while rejecting any claim to a definitive, singular t... Source: Publisher
Keywords: 1-Histoire de l'art; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; 5-Créateur.rice autochtone; _Nettoyé

‘Enclosing Some Snapshots’: James Patrick Brady, Photography, and Political Activism - Farrell Racette, Sherry (History of Photography, 2018)
James Brady was a mid twentieth-century Indigenous political organiser, trapper, prospector, writer, and intellectual. He was also a prolific photographer. This article considers the significance and aesthetics of Brady’s photographic archive through the lens of Indigenous visual sovereignty. Brady was Métis - one of Canada’s three recognised Indigenous peoples along with First Nations and Inuit. The Métis engaged in two conflicts with the Canadian state and negotiated the entry of a province into confederation. For a significant period of history, they lived outside Canadian infrastructures, whether the system of First Nations’ reserves created in the post-treaty era or Euro-Canadian settlements. Particularly vulnerable to land loss and displacement, the Métis were in desperate condition when Brady first began travelling with his camera. Brady’s photographs document the political rebirth of Métis people and the resilience and persistence of Métis communities in northern Alberta and Saskatchewan. They bear photographic witness to the lived experience of sovereignty rooted to place and continue to resonate with his subjects and their descendants
Keywords: 1-Histoire de l'art; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; 5-Créateur.rice autochtone; _Nettoyé

Sewing ourselves together: clothing, decorative arts and the expression of Metis and Half Breed identity. - Farrell Racette, Sherry. (University of Manitoba, 2009)
Keywords: 1-Histoire de l'art; _À vérifier-Histoire de l'art

Art in our Lives native Women Artists in Dialogue - Chavez Lamar, Cynthia; Farrell Racette, Sherry; Evans, Lara (School for Advanced Research Press, 2010)
The culmination of three seminars at SAR's Indian Arts Research Center (IARC) that brought together Native women artists to discuss the balancing of their art practice with the myriad roles, responsibilities, and commitments they have. The artworks were diverse in media and content and are featured in the plates section of this volume, along with the artist statements that accompanied the pieces in the exhibit. The chapters reflect some of the seminars emerging themes: gender, home/crossing, and art as healing/art as struggle
Section: 1 v. (x-142 p.) : ill. en coul. ; 26 cm
Keywords: 1-Histoire de l'art; 2-Approches sociologiques; 2-Genre et sexualité; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Close Encounters: The Next 500 Years - Farrell Racette, Sherry. (Plug In Editions., 2011)
Catalogue d'exposition publié à l'occasion de l'exposition tenue au Plug In Institute of Contemporary Art, Urban Shaman Contemporary Aboriginal Art, et Winnipeg Art Gallery, du 22 janvier au 8 mai 2011. Now is the moment to reconfigure our notions of time to reveal alternative ways of thinking and being for the future. In Close Encounters: The Next 500 Years Indigenous artists imagine the future within the context of present experiences and past histories. By radically reconsidering encounter narratives between native and non-native people, Indigenous prophecies, possible utopias and apocalypses, this exhibition proposes intriguing possibilities for the next 500 years. "We all in different measure have carved out the future," observes Hopi photographer and filmmaker, Victor Masayesva, in his book Husk of Time. "We are all clairvoyants, soothsayers, prophets, knowingly assuming our predictions. Close Encounters brings together over 30 Indigenous artists from across Canada, the United States, South America, Europe, Australia and New Zealand, including newly commissioned work from Rebecca Belmore, Faye HeavyShield, Kent Monkman, and Edward Poitras. Jimmie Durham's sculptural work A Pole to Mark the Centre of the World (at Winnipeg) will be an ongoing critique of widely held ideas surrounding space and location, while James Luna's poignant installation The Spirits of Virtue and Evil Await my Ascension, addresses issues of ritual and the passing of time. Close Encounters showcases artists and artworks that collectively invent provocative futures from a diversity of perspectives and practices. With its myriad histories, trajectories, tensions, collisions, and self-image(s), the city of Winnipeg offers an intriguing juxtaposition for these artistic mediations. Close Encounters: The Next 500 Years presents international Indigenous perspectives in a city that in many ways also epitomizes the future of Aboriginal people in Canada. Works in multiple venues throughout the city will serve as catalysts to invent different ways of thinking, acting, and being in the world of our shared future. At this pivotal moment in time, Close Encounters invites engagement with the speculative, the prophetic, and the unknown
Section: 1 volume (217 pages) : illustrations en coul. ; 26 cm.
Keywords: 1-Histoire de l'art; 2-Histoire/Historiographie critique; 2-Muséologie critique; 2-Épistémologies autochtones; 3-Amérique centrale (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Europe (corpus analysé); 3-Océanie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

About face: self-portraits by Native American, First Nations, and Inuit artists - Pearlstone, Zena; Ryan, Allan J. (Wheelwright Museum of the American Indian, 2006)
This catalogue accompanied a well-received exhibition organized by the Wheelwright Museum of the American Indian in 2006 featuring sixty-two self-portraits by indigenous artists from throughout the United States and Canada. The photographs and accompanying essays explore the artists' communal and cultural connections, and discuss the evolution of self-portraiture as a medium for empowerment and self-representation. Avec des textes des auteur.es allochtones et autochtones : Joanna Woods-Marsden, Joanna Roche, Janet Catherine Berlo et Lucy Lippard.
Section: xiii, 185 p. : ill. (certaines en coul.), ports. ; 31 cm
Keywords: _Nettoyé

The Trickster Shift: Humour and Irony in Contemporary Native Art - Ryan, Allan J. (University of British Columbia Press, 1999)
The influence of the "trickster" in contemporary Canadian native art is entwined with cultural sensibilities and expressed through ironic humour. Exploring the trickster's presence, this text allows the artists to offer their own ideas on the creative process and the nature of native humour.
Section: xv, 303 p. : ill. (certaines en coul.)
Keywords: 1-Histoire de l'art; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

La "chose indienne": cinéma et politiques de la représentation autochtone au Québec et au Canada - Cornellier, Bruno (Nota bene, 2015)
Comment se fait-il que le Canada puisse être représenté par des totems indiens à Walt Disney World ou par un inukshuk aux Jeux olympiques de Vancouver ? Il y a indéniablement « quelque chose » d’indien à propos du Canada. Pour survivre moralement et politiquement à son héritage colonial, l’État a besoin de se faire lui-même partiellement indien. Il lui faut ce je-ne-sais-quoi, cette « chose indienne », nommée sans l’être complètement, signalée sans jamais être définie. Cette indianité, bien qu’elle soit interpellée par la présence d’Autochtones, n’a plus besoin d’eux pour se manifester en tant que réalité. Historiquement, le cinéma constitue l’un des lieux privilégiés où se manifeste cette « chose indienne » prise dans les rets de l’imagination libérale et coloniale qui alimente les velléités de souveraineté du Québec et du Canada. Dans la mesure où une telle capture constitue l’un des principaux exercices politiques de l’État, le présent ouvrage avance une conception de la décolonisation qui ne relève plus de la révélation d’une réalité de l’Indien, cachée derrière sa représentation et ses distorsions filmiques, prête à resurgir au profit d’une « reconnaissance » par et dans l’État souverain. Il s’agit plutôt de comprendre le rapport colonial comme une lutte multipartite entre Canadiens, Québécois et Autochtones, avec pour enjeu de s’emparer du pouvoir exclusif de désigner et de représenter ce (et ceux) que cette « chose indienne » pourra (ou non) signifier et autoriser dans le voisinage colonial du souverain.
Section: 310 pages : illustrations ; 21 cm
Keywords: 1-Cinéma; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Créateur.rice autochtone; _Nettoyé; _À vérifier-Cinéma

Coded Territories: Tracing Indigenous Pathways in New Media Art - Loft, Steve; Swanson, Kerry (University of Calgary Press, 2014)
This collection of essays provides a historical and contemporary context for Indigenous new media arts practice in Canada. The writers are established artists, scholars, and curators who cover thematic concepts and underlying approaches to new media from a distinctly Indigenous perspective. Through discourse and narrative analysis, the writers discuss a number of topics ranging from how Indigenous worldviews inform unique approaches to new media arts practice to their own work and specific contemporary works. Contributors include: Archer Pechawis, Jackson 2Bears, Jason Edward Lewis, Steven Foster, Candice Hopkins, and Cheryl L'Hirondelle.
Section: xvii, 195 pages : illustrations en couleur ; 22 cm
Keywords: 1-Histoire de l'art; 2-Humanités numériques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; 5-Créateur.rice autochtone; _Nettoyé

Coded Territories: Tracing Indigenous Pathways in New Media Art. (University of Calgary Press., 2014)
OCLC: 1125476153

Indigenous Methodologies: Characteristics, Conversations, and Contexts - Kovach, Margaret (University of Toronto Press, 2009)
"An innovative and important contribution to Indigenous research approaches, this revised second edition provides a framework for conducting Indigenous methodologies, serving as an entry point to learn more broadly about Indigenous research."–
OCLC: 1223012487
Keywords: 2-Méthodologie de recherche décoloniale; 2-Pédagogie décoloniale; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; _Nettoyé

Indigenous Methodologies: Characteristics, Conversations, and Contexts . Margaret Kovach - Ferguson, T. J. (Journal of Anthropological Research, 2011)

Wampum as Hypertext: An American Indian Intellectual Tradition of Multimedia Theory and Practice - Haas, Angela M. (Studies in American Indian Literatures, 2007)

_Formation et questions (2021)

Images de nouveaux territoires : la décolonisation au cinéma - Protat, Zoé (Ciné-Bulles, 2011)
Keywords: _À analyser; _À nettoyer

Al Jazeera, production documentaire et « identité arabe » : Émergence et enjeux d’une industrie documentaire dans le monde arabe - Tabet, Michel (La circulation des productions culturelles : Cinémas, informations et séries télévisées dans les mondes arabes et musulmans, 2017)
Code: La circulation des productions culturelles : Cinémas, informations et séries télévisées dans les mondes arabes et musulmans
Keywords: 1-Cinéma; 1-TV; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 3-Afrique (corpus analysé); _À analyser